Bi-allelic ACBD6 variants lead to a neurodevelopmental syndrome with progressive and complex movement disorders. - Kaiyrzhanov, Rauan; Rad, Aboulfazl; Lin, Sheng-Jia; Bertoli-Avella, Aida; Kallemeijn, Wouter W; Godwin, Annie; Zaki, Maha S; Huang, Kevin; Lau, Tracy; Petree, Cassidy; Efthymiou, Stephanie; Karimiani, Ehsan Ghayoor; et al. (Brain, 2024)
The acyl-CoA-binding domain-containing protein 6 (ACBD6) is ubiquitously expressed, plays a role in the acylation of lipids and proteins and regulates the N-myristoylation of proteins via N-myristoyltransferase enzymes (NMTs). However, its precise function in cells is still unclear, as is the consequence of ACBD6 defects on human pathophysiology. Using exome sequencing and extensive international data sharing efforts, we identified 45 affected individuals from 28 unrelated families (consanguinity 93%) with bi-allelic pathogenic, predominantly loss-of-function (18/20) variants in ACBD6. We generated zebrafish and Xenopus tropicalis acbd6 knockouts by CRISPR/Cas9 and characterized the role of ACBD6 on protein N-myristoylation with myristic acid alkyne (YnMyr) chemical proteomics in the model organisms and human cells, with the latter also being subjected further to ACBD6 peroxisomal localization studies. The affected individuals (23 males and 22 females), aged 1-50 years, typically present with a complex and progressive disease involving moderate-to-severe global developmental delay/intellectual disability (100%) with significant expressive language impairment (98%), movement disorders (97%), facial dysmorphism (95%) and mild cerebellar ataxia (85%) associated with gait impairment (94%), limb spasticity/hypertonia (76%), oculomotor (71%) and behavioural abnormalities (65%), overweight (59%), microcephaly (39%) and epilepsy (33%). The most conspicuous and common movement disorder was dystonia (94%), frequently leading to early-onset progressive postural deformities (97%), limb dystonia (55%) and cervical dystonia (31%). A jerky tremor in the upper limbs (63%), a mild head tremor (59%), parkinsonism/hypokinesia developing with advancing age (32%) and simple motor and vocal tics were among other frequent movement disorders. Midline brain malformations including corpus callosum abnormalities (70%), hypoplasia/agenesis of the anterior commissure (66%), short midbrain and small inferior cerebellar vermis (38% each) as well as hypertrophy of the clava (24%) were common neuroimaging findings. Acbd6-deficient zebrafish and Xenopus models effectively recapitulated many clinical phenotypes reported in patients including movement disorders, progressive neuromotor impairment, seizures, microcephaly, craniofacial dysmorphism and midbrain defects accompanied by developmental delay with increased mortality over time. Unlike ACBD5, ACBD6 did not show a peroxisomal localization and ACBD6-deficiency was not associated with altered peroxisomal parameters in patient fibroblasts. Significant differences in YnMyr-labelling were observed for 68 co- and 18 post-translationally N-myristoylated proteins in patient-derived fibroblasts. N-myristoylation was similarly affected in acbd6-deficient zebrafish and X. tropicalis models, including Fus, Marcks and Chchd-related proteins implicated in neurological diseases. The present study provides evidence that bi-allelic pathogenic variants in ACBD6 lead to a distinct neurodevelopmental syndrome accompanied by complex and progressive cognitive and movement disorders.
Keywords: Adolescent; Adult; Animals; ATP-Binding Cassette Transporters; Child; Child, Preschool; Female; Humans; Infant; Intellectual Disability; Male; Microcephaly; Middle Aged; Movement Disorders; Nervous System Malformations; Neurodevelopmental Disorders; Tremor; Young Adult; Zebrafish

Germline Genetic Testing and Survival Outcomes Among Children With Rhabdomyosarcoma: A Report From the Children's Oncology Group. - Martin-Giacalone, Bailey A; Li, He; Scheurer, Michael E; Casey, Dana L; Dugan-Perez, Shannon; Marquez-Do, Deborah A; Donna M Muzny; Richard A Gibbs; Barkauskas, Donald A; Hall, David; Stewart, Douglas R; Schiffman, Joshua D; et al. (JAMA Netw Open, 2024)
IMPORTANCE: Determining the impact of germline cancer-predisposition variants (CPVs) on outcomes could inform novel approaches to testing and treating children with rhabdomyosarcoma. OBJECTIVE: To assess whether CPVs are associated with outcome among children with rhabdomyosarcoma. DESIGN, SETTING, AND PARTICIPANTS: In this cohort study, data were obtained for individuals, aged 0.01-23.23 years, newly diagnosed with rhabdomyosarcoma who were treated across 171 Children's Oncology Group sites from March 15, 1999, to December 8, 2017. Data analysis was performed from June 16, 2021, to May 15, 2023. EXPOSURE: The presence of a CPV in 24 rhabdomyosarcoma-associated cancer-predisposition genes (CPGs) or an expanded set of 63 autosomal-dominant CPGs. MAIN OUTCOMES AND MEASURES: Overall survival (OS) and event-free survival (EFS) were the main outcomes, using the Kaplan-Meier estimator to assess survival probabilities and the Cox proportional hazards regression model to adjust for clinical covariates. Analyses were stratified by tumor histology and the fusion status of PAX3 or PAX7 to the FOXO1 gene. RESULTS: In this study of 580 individuals with rhabdomyosarcoma, the median patient age was 5.9 years (range, 0.01-23.23 years), and the male-to-female ratio was 1.5 to 1 (351 [60.5%] male). For patients with CPVs in rhabdomyosarcoma-associated CPGs, EFS was 48.4% compared with 57.8% for patients without a CPV (P = .10), and OS was 53.7% compared with 65.3% for patients without a CPV (P = .06). After adjustment, patients with CPVs had significantly worse OS (adjusted hazard ratio [AHR], 2.49 [95% CI, 1.39-4.45]; P = .002), and the outcomes were not better among patients with embryonal histology (EFS: AHR, 2.25 [95% CI, 1.25-4.06]; P = .007]; OS: AHR, 2.83 [95% CI, 1.47-5.43]; P = .002]). These associations were not due to the development of a second malignant neoplasm, and importantly, patients with fusion-negative rhabdomyosarcoma who harbored a CPV had similarly inferior outcomes as patients with fusion-positive rhabdomyosarcoma without CPVs (EFS: AHR, 1.35 [95% CI, 0.71-2.59]; P = .37; OS: AHR, 1.71 [95% CI, 0.84-3.47]; P = .14). There were no significant differences in outcome by CPV status of the 63 CPG set. CONCLUSIONS AND RELEVANCE: This cohort study identified a group of patients with embryonal rhabdomyosarcoma who had a particularly poor outcome. Other important clinical findings included that individuals with TP53 had poor outcomes independent of second malignant neoplasms and that patients with fusion-negative rhabdomyosarcoma who harbored a CPV had outcomes comparable to patients with fusion-positive rhabdomyosarcoma. These findings suggest that germline CPV testing may aid in clinical prognosis and should be considered in prospective risk-based clinical trials.
Keywords: Child; Cohort Studies; Female; Genetic Testing; Germ Cells; Humans; Male; Neoplasms, Second Primary; Prospective Studies; Rhabdomyosarcoma

Somatic mutations of esophageal adenocarcinoma: a comparison between Black and White patients. - Lim, Hyeyeun; Marie-Claude Gingras; Zhao, Jing; Byun, Jinyoung; Castro, Patricia D; Tsavachidis, Spiridon; Jianhong Hu; Harshavardhan Doddapaneni; Yi Han; Donna M Muzny; Richard A Gibbs; Amos, Christopher I; et al. (Sci Rep, 2024)
Esophageal adenocarcinoma is the most common histological subtype of esophageal cancer in Western countries and shows poor prognosis with rapid growth. EAC is characterized by a strong male predominance and racial disparity. EAC is up to fivefold more common among Whites than Blacks, yet Black patients with EAC have poorer survival rates. The racial disparity remains largely unknown, and there is limited knowledge of mutations in EAC regarding racial disparities. We used whole-exome sequencing to show somatic mutation profiles derived from tumor samples from 18 EAC male patients. We identified three molecular subgroups based on the pre-defined esophageal cancer-specific mutational signatures. Group 1 is associated with age and NTHL1 deficiency-related signatures. Group 2 occurs primarily in Black patients and is associated with signatures related to DNA damage from oxidative stress and NTHL1 deficiency-related signatures. Group 3 is associated with defective homologous recombination-based DNA often caused by BRCA mutation in White patients. We observed significantly mutated race related genes (LCE2B in Black, SDR39U1 in White) were (q-value < 0.1). Our findings underscore the possibility of distinct molecular mutation patterns in EAC among different races. Further studies are needed to validate our findings, which could contribute to precision medicine in EAC.
Keywords: Adenocarcinoma; Black or African American; Esophageal Neoplasms; Exome Sequencing; Female; Humans; Male; Mutation; White

Variants in ZFX are associated with an X-linked neurodevelopmental disorder with recurrent facial gestalt. - Shepherdson, James L; Hutchison, Katie; Don, Dilan Wellalage; McGillivray, George; Choi, Tae-Ik; Allan, Carolyn A; Amor, David J; Banka, Siddharth; Basel, Donald G; Buch, Laura D; Carere, Deanna Alexis; Carroll, Renée; et al. (Am J Hum Genet, 2024)
Pathogenic variants in multiple genes on the X chromosome have been implicated in syndromic and non-syndromic intellectual disability disorders. ZFX on Xp22.11 encodes a transcription factor that has been linked to diverse processes including oncogenesis and development, but germline variants have not been characterized in association with disease. Here, we present clinical and molecular characterization of 18 individuals with germline ZFX variants. Exome or genome sequencing revealed 11 variants in 18 subjects (14 males and 4 females) from 16 unrelated families. Four missense variants were identified in 11 subjects, with seven truncation variants in the remaining individuals. Clinical findings included developmental delay/intellectual disability, behavioral abnormalities, hypotonia, and congenital anomalies. Overlapping and recurrent facial features were identified in all subjects, including thickening and medial broadening of eyebrows, variations in the shape of the face, external eye abnormalities, smooth and/or long philtrum, and ear abnormalities. Hyperparathyroidism was found in four families with missense variants, and enrichment of different tumor types was observed. In molecular studies, DNA-binding domain variants elicited differential expression of a small set of target genes relative to wild-type ZFX in cultured cells, suggesting a gain or loss of transcriptional activity. Additionally, a zebrafish model of ZFX loss displayed an altered behavioral phenotype, providing additional evidence for the functional significance of ZFX. Our clinical and experimental data support that variants in ZFX are associated with an X-linked intellectual disability syndrome characterized by a recurrent facial gestalt, neurocognitive and behavioral abnormalities, and an increased risk for congenital anomalies and hyperparathyroidism.
Keywords: Animals; Female; Humans; Hyperparathyroidism; Intellectual Disability; Male; Mutation, Missense; Neurodevelopmental Disorders; Phenotype; Transcription Factors; Zebrafish

Association of Mitochondrial DNA Copy Number With Brain MRI Markers and Cognitive Function: A Meta-analysis of Community-Based Cohorts. - Zhang, Yuankai; Liu, Xue; Wiggins, Kerri L; Kurniansyah, Nuzulul; Guo, Xiuqing; Rodrigue, Amanda L; Zhao, Wei; Yanek, Lisa R; Ratliff, Scott M; Pitsillides, Achilleas; Aguirre Patiño, Juan Sebastian; Sofer, Tamar; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: Previous studies suggest that lower mitochondrial DNA (mtDNA) copy number (CN) is associated with neurodegenerative diseases. However, whether mtDNA CN in whole blood is related to endophenotypes of Alzheimer disease (AD) and AD-related dementia (AD/ADRD) needs further investigation. We assessed the association of mtDNA CN with cognitive function and MRI measures in community-based samples of middle-aged to older adults. METHODS: We included dementia-free participants from 9 diverse community-based cohorts with whole-genome sequencing in the Trans-Omics for Precision Medicine (TOPMed) program. Circulating mtDNA CN was estimated as twice the ratio of the average coverage of mtDNA to nuclear DNA. Brain MRI markers included total brain, hippocampal, and white matter hyperintensity volumes. General cognitive function was derived from distinct cognitive domains. We performed cohort-specific association analyses of mtDNA CN with AD/ADRD endophenotypes assessed within ±5 years (i.e., cross-sectional analyses) or 5-20 years after blood draw (i.e., prospective analyses) adjusting for potential confounders. We further explored associations stratified by sex and age (<60 vs ≥60 years). Fixed-effects or sample size-weighted meta-analyses were performed to combine results. Finally, we performed mendelian randomization (MR) analyses to assess causality. RESULTS: We included up to 19,152 participants (mean age 59 years, 57% women). Higher mtDNA CN was cross-sectionally associated with better general cognitive function (β = 0.04; 95% CI 0.02-0.06) independent of age, sex, batch effects, race/ethnicity, time between blood draw and cognitive evaluation, cohort-specific variables, and education. Additional adjustment for blood cell counts or cardiometabolic traits led to slightly attenuated results. We observed similar significant associations with cognition in prospective analyses, although of reduced magnitude. We found no significant associations between mtDNA CN and brain MRI measures in meta-analyses. MR analyses did not reveal a causal relation between mtDNA CN in blood and cognition. DISCUSSION: Higher mtDNA CN in blood is associated with better current and future general cognitive function in large and diverse communities across the United States. Although MR analyses did not support a causal role, additional research is needed to assess causality. Circulating mtDNA CN could serve nevertheless as a biomarker of current and future cognitive function in the community.
Keywords: Aged; Alzheimer Disease; Brain; Cognition; Cross-Sectional Studies; DNA Copy Number Variations; DNA, Mitochondrial; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Prospective Studies

Association of Rare Protein-Truncating DNA Variants in APOB or PCSK9 With Low-density Lipoprotein Cholesterol Level and Risk of Coronary Heart Disease. - Dron, Jacqueline S; Patel, Aniruddh P; Zhang, Yiyi; Jurgens, Sean J; Maamari, Dimitri J; Wang, Minxian; Eric Boerwinkle; Morrison, Alanna C; de Vries, Paul S; Fornage, Myriam; Hou, Lifang; Lloyd-Jones, Donald M; et al. (JAMA Cardiol, 2023)
IMPORTANCE: Protein-truncating variants (PTVs) in apolipoprotein B (APOB) and proprotein convertase subtilisin/kexin type 9 (PCSK9) are associated with significantly lower low-density lipoprotein (LDL) cholesterol concentrations. The association of these PTVs with coronary heart disease (CHD) warrants further characterization in large, multiracial prospective cohort studies. OBJECTIVE: To evaluate the association of PTVs in APOB and PCSK9 with LDL cholesterol concentrations and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: This studied included participants from 5 National Heart, Lung, and Blood Institute (NHLBI) studies and the UK Biobank. NHLBI study participants aged 5 to 84 years were recruited between 1971 and 2002 across the US and underwent whole-genome sequencing. UK Biobank participants aged 40 to 69 years were recruited between 2006 and 2010 in the UK and underwent whole-exome sequencing. Data were analyzed from June 2021 to October 2022. EXPOSURES: PTVs in APOB and PCSK9. MAIN OUTCOMES AND MEASURES: Estimated untreated LDL cholesterol levels and CHD. RESULTS: Among 19 073 NHLBI participants (10 598 [55.6%] female; mean [SD] age, 52 [17] years), 139 (0.7%) carried an APOB or PCSK9 PTV, which was associated with 49 mg/dL (95% CI, 43-56) lower estimated untreated LDL cholesterol level. Over a median (IQR) follow-up of 21.5 (13.9-29.4) years, incident CHD was observed in 12 of 139 carriers (8.6%) vs 3029 of 18 934 noncarriers (16.0%), corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.28-0.89; P = .02). Among 190 464 UK Biobank participants (104 831 [55.0%] female; mean [SD] age, 57 [8] years), 662 (0.4%) carried a PTV, which was associated with 45 mg/dL (95% CI, 42-47) lower estimated untreated LDL cholesterol level. Estimated CHD risk by age 75 years was 3.7% (95% CI, 2.0-5.3) in carriers vs 7.0% (95% CI, 6.9-7.2) in noncarriers, corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.32-0.81; P = .004). CONCLUSIONS AND RELEVANCE: Among 209 537 individuals in this study, 0.4% carried an APOB or PCSK9 PTV that was associated with less exposure to LDL cholesterol and a 49% lower risk of CHD.
Keywords: Adult; Aged; Apolipoproteins B; Cholesterol, LDL; Coronary Disease; DNA; Female; Humans; Male; Middle Aged; Proprotein Convertase 9; Prospective Studies

Bi-allelic SNAPC4 variants dysregulate global alternative splicing and lead to neuroregression and progressive spastic paraparesis. - Frost, F Graeme; Morimoto, Marie; Sharma, Prashant; Ruaud, Lyse; Belnap, Newell; Calame, Daniel G; Uchiyama, Yuri; Matsumoto, Naomichi; Oud, Machteld M; Ferreira, Elise A; Narayanan, Vinodh; Rangasamy, Sampath; et al. (Am J Hum Genet, 2023)
The vast majority of human genes encode multiple isoforms through alternative splicing, and the temporal and spatial regulation of those isoforms is critical for organismal development and function. The spliceosome, which regulates and executes splicing reactions, is primarily composed of small nuclear ribonucleoproteins (snRNPs) that consist of small nuclear RNAs (snRNAs) and protein subunits. snRNA gene transcription is initiated by the snRNA-activating protein complex (SNAPc). Here, we report ten individuals, from eight families, with bi-allelic, deleterious SNAPC4 variants. SNAPC4 encoded one of the five SNAPc subunits that is critical for DNA binding. Most affected individuals presented with delayed motor development and developmental regression after the first year of life, followed by progressive spasticity that led to gait alterations, paraparesis, and oromotor dysfunction. Most individuals had cerebral, cerebellar, or basal ganglia volume loss by brain MRI. In the available cells from affected individuals, SNAPC4 abundance was decreased compared to unaffected controls, suggesting that the bi-allelic variants affect SNAPC4 accumulation. The depletion of SNAPC4 levels in HeLa cell lines via genomic editing led to decreased snRNA expression and global dysregulation of alternative splicing. Analysis of available fibroblasts from affected individuals showed decreased snRNA expression and global dysregulation of alternative splicing compared to unaffected cells. Altogether, these data suggest that these bi-allelic SNAPC4 variants result in loss of function and underlie the neuroregression and progressive spasticity in these affected individuals.
Keywords: Adolescent; Alleles; Alternative Splicing; Child; Child, Preschool; DNA-Binding Proteins; Female; HeLa Cells; Humans; Infant; Male; Paraparesis, Spastic; Pedigree; Protein Isoforms; Protein Structure, Secondary; RNA, Small Nuclear; RNA-Seq; Transcription Factors

The clinical and genetic spectrum of autosomal-recessive TOR1A-related disorders. - Saffari, Afshin; Lau, Tracy; Tajsharghi, Homa; Karimiani, Ehsan Ghayoor; Kariminejad, Ariana; Efthymiou, Stephanie; Zifarelli, Giovanni; Sultan, Tipu; Toosi, Mehran Beiraghi; Sedighzadeh, Sahar; Siu, Victoria Mok; Ortigoza-Escobar, Juan Darío; et al. (Brain, 2023)
In the field of rare diseases, progress in molecular diagnostics led to the recognition that variants linked to autosomal-dominant neurodegenerative diseases of later onset can, in the context of biallelic inheritance, cause devastating neurodevelopmental disorders and infantile or childhood-onset neurodegeneration. TOR1A-associated arthrogryposis multiplex congenita 5 (AMC5) is a rare neurodevelopmental disorder arising from biallelic variants in TOR1A, a gene that in the heterozygous state is associated with torsion dystonia-1 (DYT1 or DYT-TOR1A), an early-onset dystonia with reduced penetrance. While 15 individuals with AMC5-TOR1A have been reported (less than 10 in detail), a systematic investigation of the full disease-associated spectrum has not been conducted. Here, we assess the clinical, radiological and molecular characteristics of 57 individuals from 40 families with biallelic variants in TOR1A. Median age at last follow-up was 3 years (0-24 years). Most individuals presented with severe congenital flexion contractures (95%) and variable developmental delay (79%). Motor symptoms were reported in 79% and included lower limb spasticity and pyramidal signs, as well as gait disturbances. Facial dysmorphism was an integral part of the phenotype, with key features being a broad/full nasal tip, narrowing of the forehead and full cheeks. Analysis of disease-associated manifestations delineated a phenotypic spectrum ranging from normal cognition and mild gait disturbance to congenital arthrogryposis, global developmental delay, intellectual disability, absent speech and inability to walk. In a subset, the presentation was consistent with foetal akinesia deformation sequence with severe intrauterine abnormalities. Survival was 71%, with higher mortality in males. Death occurred at a median age of 1.2 months (1 week-9 years), due to respiratory failure, cardiac arrest or sepsis. Analysis of brain MRI studies identified non-specific neuroimaging features, including a hypoplastic corpus callosum (72%), foci of signal abnormality in the subcortical and periventricular white matter (55%), diffuse white matter volume loss (45%), mega cisterna magna (36%) and arachnoid cysts (27%). The molecular spectrum included 22 distinct variants, defining a mutational hotspot in the C-terminal domain of the Torsin-1A protein. Genotype-phenotype analysis revealed an association of missense variants in the 3-helix bundle domain to an attenuated phenotype, while missense variants near the Walker A/B motif as well as biallelic truncating variants were linked to early death. In summary, this systematic cross-sectional analysis of a large cohort of individuals with biallelic TOR1A variants across a wide age-range delineates the clinical and genetic spectrum of TOR1A-related autosomal-recessive disease and highlights potential predictors for disease severity and survival.
Keywords: Cross-Sectional Studies; Dystonia; Dystonic Disorders; Humans; Male; Molecular Chaperones; Mutation; Nervous System Malformations; Phenotype

Genome-wide coancestry reveals details of ancient and recent male-driven reticulation in baboons. - Sørensen, Erik F; R. Alan Harris; Zhang, Liye; Raveendran, Muthuswamy; Kuderna, Lukas F K; Walker, Jerilyn A; Storer, Jessica M; Kuhlwilm, Martin; Fontsere, Claudia; Seshadri, Lakshmi; Bergey, Christina M; Burrell, Andrew S; et al. (Science, 2023)
Baboons (genus ) are a morphologically and behaviorally diverse clade of catarrhine monkeys that have experienced hybridization between phenotypically and genetically distinct phylogenetic species. We used high-coverage whole-genome sequences from 225 wild baboons representing 19 geographic localities to investigate population genomics and interspecies gene flow. Our analyses provide an expanded picture of evolutionary reticulation among species and reveal patterns of population structure within and among species, including differential admixture among conspecific populations. We describe the first example of a baboon population with a genetic composition that is derived from three distinct lineages. The results reveal processes, both ancient and recent, that produced the observed mismatch between phylogenetic relationships based on matrilineal, patrilineal, and biparental inheritance. We also identified several candidate genes that may contribute to species-specific phenotypes.
Keywords: Animals; Biological Evolution; Gene Flow; Male; Papio; Phenotype; Phylogeny; Sex Characteristics; Species Specificity

Hemizygous variants in protein phosphatase 1 regulatory subunit 3F (PPP1R3F) are associated with a neurodevelopmental disorder characterized by developmental delay, intellectual disability and autistic features. - Liu, Zhigang; Xin, Baozhong; Smith, Iris N; Sency, Valerie; Szekely, Julia; Alkelai, Anna; Shuldiner, Alan; Efthymiou, Stephanie; Rajabi, Farrah; Coury, Stephanie; Brownstein, Catherine A; Rudnik-Schöneborn, Sabine; et al. (Hum Mol Genet, 2023)
Protein phosphatase 1 regulatory subunit 3F (PPP1R3F) is a member of the glycogen targeting subunits (GTSs), which belong to the large group of regulatory subunits of protein phosphatase 1 (PP1), a major eukaryotic serine/threonine protein phosphatase that regulates diverse cellular processes. Here, we describe the identification of hemizygous variants in PPP1R3F associated with a novel X-linked recessive neurodevelopmental disorder in 13 unrelated individuals. This disorder is characterized by developmental delay, mild intellectual disability, neurobehavioral issues such as autism spectrum disorder, seizures and other neurological findings including tone, gait and cerebellar abnormalities. PPP1R3F variants segregated with disease in affected hemizygous males that inherited the variants from their heterozygous carrier mothers. We show that PPP1R3F is predominantly expressed in brain astrocytes and localizes to the endoplasmic reticulum in cells. Glycogen content in PPP1R3F knockout astrocytoma cells appears to be more sensitive to fluxes in extracellular glucose levels than in wild-type cells, suggesting that PPP1R3F functions in maintaining steady brain glycogen levels under changing glucose conditions. We performed functional studies on nine of the identified variants and observed defects in PP1 binding, protein stability, subcellular localization and regulation of glycogen metabolism in most of them. Collectively, the genetic and molecular data indicate that deleterious variants in PPP1R3F are associated with a new X-linked disorder of glycogen metabolism, highlighting the critical role of GTSs in neurological development. This research expands our understanding of neurodevelopmental disorders and the role of PP1 in brain development and proper function.
Keywords: Autism Spectrum Disorder; Autistic Disorder; Glucose; Glycogen; Humans; Intellectual Disability; Male; Neurodevelopmental Disorders; Protein Phosphatase 1

Identification of USP9X as a leukemia susceptibility gene. - Sisoudiya, Saumya Dushyant; Mishra, Pamela; Li, He; Schraw, Jeremy M; Scheurer, Michael E; Salvi, Sejal; Harshavardhan Doddapaneni; Donna M Muzny; Mitchell, Danielle; Taylor, Olga; Aniko Sabo; Lupo, Philip J; et al. (Blood Adv, 2023)
We recently reported that children with multiple birth defects have a significantly higher risk of childhood cancer. We performed whole-genome sequencing on a cohort of probands from this study with birth defects and cancer and their parents. Structural variant analysis identified a novel 5 kb de novo heterozygous inframe deletion overlapping the catalytic domain of USP9X in a female proband with multiple birth defects, developmental delay, and B-cell acute lymphoblastic leukemia (B-ALL). Her phenotype was consistent with female-restricted X-linked syndromic intellectual developmental disorder-99 (MRXS99F). Genotype-phenotype analysis including previously reported female probands (n = 42) demonstrated that MRXS99F probands with B-ALL (n = 3) clustered with subjects with loss-of-function (LoF) USP9X variants and multiple anomalies. The cumulative incidence of B-ALL among these female probands (7.1%) was significantly higher than an age- and sex-matched cohort (0.003%) from the Surveillance, Epidemiology, and End Results database (P < .0001, log-rank test). There are no reports of LoF variants in males. Males with hypomorphic missense variants have neurodevelopmental disorders without birth defects or leukemia risk. In contrast, in sporadic B-ALL, somatic LoF USP9X mutations occur in both males and females, and expression levels are comparable in leukemia samples from both sexes (P = .54), with the highest expressors being female patients with extra copies of the X-chromosome. Overall, we describe USP9X as a novel female-specific leukemia predisposition gene associated with multiple congenital, neurodevelopmental anomalies, and B-ALL risk. In contrast, USP9X serves as a tumor suppressor in sporadic pediatric B-ALL in both sexes, with low expression associated with poorer survival in patients with high-risk B-ALL.
Keywords: Female; Humans; Intellectual Disability; Leukemia; Loss of Function Mutation; Male; Mutation, Missense; Phenotype; Ubiquitin Thiolesterase

Molecular basis of retinal remodeling in a zebrafish model of retinitis pigmentosa. - Santhanam, Abirami; Shihabeddin, Eyad; Wei, Haichao; Wu, Jiaqian; O'Brien, John (Cell Mol Life Sci, 2023)
A hallmark of inherited retinal degenerative diseases such as retinitis pigmentosa (RP) is progressive structural and functional remodeling of the remaining retinal cells as photoreceptors degenerate. Extensive remodeling of the retina stands as a barrier for the successful implementation of strategies to restore vision. To understand the molecular basis of remodeling, we performed analyses of single-cell transcriptome data from adult zebrafish retina of wild type AB strain (WT) and a P23H mutant rhodopsin transgenic model of RP with continuous degeneration and regeneration. Retinas from both female and male fish were pooled to generate each library, combining data from both sexes. We provide a benchmark atlas of retinal cell type transcriptomes in zebrafish and insight into how each retinal cell type is affected in the P23H model. Oxidative stress is found throughout the retina, with increases in reliance on oxidative metabolism and glycolysis in the affected rods as well as cones, bipolar cells, and retinal ganglion cells. There is also transcriptional evidence for widespread synaptic remodeling and enhancement of glutamatergic transmission in the inner retina. Notably, changes in circadian rhythm regulation are detected in cones, bipolar cells, and retinal pigmented epithelium. We also identify the transcriptomic signatures of retinal progenitor cells and newly formed rods essential for the regenerative process. This comprehensive transcriptomic analysis provides a molecular road map to understand how the retina remodels in the context of chronic retinal degeneration with ongoing regeneration.
Keywords: Animals; Disease Models, Animal; Female; Male; Retina; Retinal Degeneration; Retinal Rod Photoreceptor Cells; Retinitis Pigmentosa; Zebrafish

Multiscale analysis of pangenomes enables improved representation of genomic diversity for repetitive and clinically relevant genes. - Chin, Chen-Shan; Behera, Sairam; Khalak, Asif; Fritz J Sedlazeck; Sudmant, Peter H; Wagner, Justin; Zook, Justin M (Nat Methods, 2023)
Advancements in sequencing technologies and assembly methods enable the regular production of high-quality genome assemblies characterizing complex regions. However, challenges remain in efficiently interpreting variation at various scales, from smaller tandem repeats to megabase rearrangements, across many human genomes. We present a PanGenome Research Tool Kit (PGR-TK) enabling analyses of complex pangenome structural and haplotype variation at multiple scales. We apply the graph decomposition methods in PGR-TK to the class II major histocompatibility complex demonstrating the importance of the human pangenome for analyzing complicated regions. Moreover, we investigate the Y-chromosome genes, DAZ1/DAZ2/DAZ3/DAZ4, of which structural variants have been linked to male infertility, and X-chromosome genes OPN1LW and OPN1MW linked to eye disorders. We further showcase PGR-TK across 395 complex repetitive medically important genes. This highlights the power of PGR-TK to resolve complex variation in regions of the genome that were previously too complex to analyze.
Keywords: Genome, Human; Genomics; Humans; Major Histocompatibility Complex; Male

Novel LSS variants in alopecia and intellectual disability syndrome: New case report and clinical spectrum of LSS-related rare disease traits. - Elbendary, Hasnaa M; Marafi, Dana; Saad, Ahmed K; Elhossini, Rasha; Duan, Ruizhi; Rafat, Karima; Jhangiani, Shalini N; Richard A Gibbs; Pehlivan, Davut; Calame, Daniel G; Posey, Jennifer E; James R Lupski; et al. (Clin Genet, 2023)
Pathogenic biallelic variants in LSS are associated with three Mendelian rare disease traits including congenital cataract type 44, autosomal recessive hypotrichosis type 14, and alopecia-intellectual disability syndrome type 4 (APMR4). We performed trio research exome sequencing on a family with a four-year-old male with global developmental delay, epilepsy and striking alopecia, and identified novel compound heterozygous LSS splice site (c.14+2T>C) and missense (c.1357 G>A; p.V453L) variant alleles. Rare features associated with APMR4 such as cryptorchidism, micropenis, mild cortical brain atrophy and thin corpus callosum were detected. Previously unreported APMR4 findings including cerebellar involvement in the form of unsteady ataxic gait, small vermis with prominent folia, were noted. A review of all reported variants to date in 29 families with LSS-related phenotypes showed an emerging genotype-phenotype correlation. Our report potentially expands LSS-related phenotypic spectrum and highlights the importance of performing brain imaging in LSS-related conditions.
Keywords: Alopecia; Humans; Intellectual Disability; Male; Mutation; Phenotype; Rare Diseases; Syndrome

PLS3 missense variants affecting the actin-binding domains cause X-linked congenital diaphragmatic hernia and body-wall defects. - Petit, Florence; Longoni, Mauro; Wells, Julie; Maser, Richard S; Bogenschutz, Eric L; Dysart, Matthew J; Contreras, Hannah T M; Frénois, Frederic; Pober, Barbara R; Clark, Robin D; Giampietro, Philip F; Ropers, Hilger H; et al. (Am J Hum Genet, 2023)
Congenital diaphragmatic hernia (CDH) is a relatively common and genetically heterogeneous structural birth defect associated with high mortality and morbidity. We describe eight unrelated families with an X-linked condition characterized by diaphragm defects, variable anterior body-wall anomalies, and/or facial dysmorphism. Using linkage analysis and exome or genome sequencing, we found that missense variants in plastin 3 (PLS3), a gene encoding an actin bundling protein, co-segregate with disease in all families. Loss-of-function variants in PLS3 have been previously associated with X-linked osteoporosis (MIM: 300910), so we used in silico protein modeling and a mouse model to address these seemingly disparate clinical phenotypes. The missense variants in individuals with CDH are located within the actin-binding domains of the protein but are not predicted to affect protein structure, whereas the variants in individuals with osteoporosis are predicted to result in loss of function. A mouse knockin model of a variant identified in one of the CDH-affected families, c.1497G>C (p.Trp499Cys), shows partial perinatal lethality and recapitulates the key findings of the human phenotype, including diaphragm and abdominal-wall defects. Both the mouse model and one adult human male with a CDH-associated PLS3 variant were observed to have increased rather than decreased bone mineral density. Together, these clinical and functional data in humans and mice reveal that specific missense variants affecting the actin-binding domains of PLS3 might have a gain-of-function effect and cause a Mendelian congenital disorder.
Keywords: Actins; Adult; Animals; Hernias, Diaphragmatic, Congenital; Humans; Male; Mice; Mutation, Missense; Osteoporosis

SRSF1 haploinsufficiency is responsible for a syndromic developmental disorder associated with intellectual disability. - Bogaert, Elke; Garde, Aurore; Gautier, Thierry; Rooney, Kathleen; Duffourd, Yannis; LeBlanc, Pontus; van Reempts, Emma; Tran Mau-Them, Frederic; Wentzensen, Ingrid M; Au, Kit Sing; Richardson, Kate; Northrup, Hope; et al. (Am J Hum Genet, 2023)
SRSF1 (also known as ASF/SF2) is a non-small nuclear ribonucleoprotein (non-snRNP) that belongs to the arginine/serine (R/S) domain family. It recognizes and binds to mRNA, regulating both constitutive and alternative splicing. The complete loss of this proto-oncogene in mice is embryonically lethal. Through international data sharing, we identified 17 individuals (10 females and 7 males) with a neurodevelopmental disorder (NDD) with heterozygous germline SRSF1 variants, mostly de novo, including three frameshift variants, three nonsense variants, seven missense variants, and two microdeletions within region 17q22 encompassing SRSF1. Only in one family, the de novo origin could not be established. All individuals featured a recurrent phenotype including developmental delay and intellectual disability (DD/ID), hypotonia, neurobehavioral problems, with variable skeletal (66.7%) and cardiac (46%) anomalies. To investigate the functional consequences of SRSF1 variants, we performed in silico structural modeling, developed an in vivo splicing assay in Drosophila, and carried out episignature analysis in blood-derived DNA from affected individuals. We found that all loss-of-function and 5 out of 7 missense variants were pathogenic, leading to a loss of SRSF1 splicing activity in Drosophila, correlating with a detectable and specific DNA methylation episignature. In addition, our orthogonal in silico, in vivo, and epigenetics analyses enabled the separation of clearly pathogenic missense variants from those with uncertain significance. Overall, these results indicated that haploinsufficiency of SRSF1 is responsible for a syndromic NDD with ID due to a partial loss of SRSF1-mediated splicing activity.
Keywords: Child; Developmental Disabilities; Female; Haploinsufficiency; Humans; Intellectual Disability; Male; Mutation, Missense; Neurodevelopmental Disorders; Phenotype

Accurate profiling of forensic autosomal STRs using the Oxford Nanopore Technologies MinION device. - Hall, Courtney L; Kesharwani, Rupesh K; Phillips, Nicole R; Planz, John V; Fritz J Sedlazeck; Zascavage, Roxanne R (Forensic Sci Int Genet, 2022)
The high variability characteristic of short tandem repeat (STR) markers is harnessed for human identification in forensic genetic analyses. Despite the power and reliability of current typing techniques, sequence-level information both within and around STRs are masked in the length-based profiles generated. Forensic STR typing using next generation sequencing (NGS) has therefore gained attention as an alternative to traditional capillary electrophoresis (CE) approaches. In this proof-of-principle study, we evaluate the forensic applicability of the newest and smallest NGS platform available - the Oxford Nanopore Technologies (ONT) MinION device. Although nanopore sequencing on the handheld MinION offers numerous advantages, including low startup cost and on-site sample processing, the relatively high error rate and lack of forensic-specific analysis software has prevented accurate profiling across STR panels in previous studies. Here we present STRspy, a streamlined method capable of producing length- and sequence-based STR allele designations from noisy, error-prone third generation sequencing reads. To assess the capabilities of STRspy, seven reference samples (female: n = 2; male: n = 5) were amplified at 15 and 30 PCR cycles using the Promega PowerSeq 46GY System and sequenced on the ONT MinION device in triplicate. Basecalled reads were then processed with STRspy using a custom database containing alleles reported in the STRSeq BioProject NIST 1036 dataset. Resultant STR allele designations and flanking region single nucleotide polymorphism (SNP) calls were compared to the manufacturer-validated genotypes for each sample. STRspy generated robust and reliable genotypes across all autosomal STR loci amplified with 30 PCR cycles, achieving 100% concordance based on both length and sequence. Furthermore, we were able to identify flanking region SNPs in the 15-cycle dataset with > 90% accuracy. These results demonstrate that when analyzed with STRspy ONT reads can reveal additional variation in and around STR loci depending on read coverage. As the first and only third generation sequencing platform-specific method to successfully profile the entire panel of autosomal STRs amplified by a commercially available multiplex, STRspy significantly increases the feasibility of nanopore sequencing in forensic applications.
Keywords: DNA Fingerprinting; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Microsatellite Repeats; Nanopores; Reproducibility of Results; Sequence Analysis, DNA

Apolipoprotein E Polymorphism, Cardiac Remodeling, and Heart Failure in the ARIC Study. - Selvaraj, Senthil; Claggett, Brian; Johansen, Michelle C; Cunningham, Jonathan W; Gottesman, Rebecca F; Yu, Bing; Eric Boerwinkle; Mosley, Thomas H; Shah, Amil M; Solomon, Scott D (J Card Fail, 2022)
BACKGROUND: β-Amyloid has recently been discovered in the myocardium of patients with Alzheimer's disease (AD). Whether genetic variation in apolipoprotein E (APOE) ɛ4, a common variant associated with Alzheimer's disease, is associated with incident heart failure (HF), N-terminal pro-B-type natriuretic peptide (NT-proBNP), and cardiac structure and function is unknown. METHODS AND RESULTS: We studied 15,064 White and Black participants in the Atherosclerosis Risk in Communities, relating genotype status at visit 1 (1987-1989) to incident HF hospitalization using Cox regression. At visits 2, 4, and 5, we assessed NT-proBNP levels by genotype. At visits 3 and 5, we related Aβ peptides to incident HF. At visit 5 (2011-2013, n = 6251), we assessed the relationship of genotype with prevalent HF and echocardiographic parameters. The mean participant age was 54.7 ± 5.8 years, 45% were men, and 73% were White. At visit 5, there was no difference in prevalent HF by genotype. The APOE ε4 carriers did not have increased risk for HF hospitalization. The APOE ε4 genotype was not associated with cardiac structure and function or NT-proBNP levels. The Aβ peptides were not associated with incident HF after multivariable adjustment. CONCLUSIONS: A genetic predisposition to Alzheimer's disease through APOE ε4 is not associated with an increased prevalence of HF, HF hospitalization, myocardial remodeling, or biochemical evidence of HF.
Keywords: Alzheimer Disease; Apolipoprotein E4; Apolipoproteins E; Biomarkers; Female; Heart Failure; Humans; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Ventricular Remodeling

Association of Pathogenic Variants in Hereditary Cancer Genes With Multiple Diseases. - Zeng, Chenjie; Bastarache, Lisa A; Tao, Ran; Eric Venner; Hebbring, Scott; Andujar, Justin D; Bland, Sarah T; Crosslin, David R; Pratap, Siddharth; Cooley, Ayorinde; Pacheco, Jennifer A; Christensen, Kurt D; et al. (JAMA Oncol, 2022)
IMPORTANCE: Knowledge about the spectrum of diseases associated with hereditary cancer syndromes may improve disease diagnosis and management for patients and help to identify high-risk individuals. OBJECTIVE: To identify phenotypes associated with hereditary cancer genes through a phenome-wide association study. DESIGN, SETTING, AND PARTICIPANTS: This phenome-wide association study used health data from participants in 3 cohorts. The Electronic Medical Records and Genomics Sequencing (eMERGEseq) data set recruited predominantly healthy individuals from 10 US medical centers from July 16, 2016, through February 18, 2018, with a mean follow-up through electronic health records (EHRs) of 12.7 (7.4) years. The UK Biobank (UKB) cohort recruited participants from March 15, 2006, through August 1, 2010, with a mean (SD) follow-up of 12.4 (1.0) years. The Hereditary Cancer Registry (HCR) recruited patients undergoing clinical genetic testing at Vanderbilt University Medical Center from May 1, 2012, through December 31, 2019, with a mean (SD) follow-up through EHRs of 8.8 (6.5) years. EXPOSURES: Germline variants in 23 hereditary cancer genes. Pathogenic and likely pathogenic variants for each gene were aggregated for association analyses. MAIN OUTCOMES AND MEASURES: Phenotypes in the eMERGEseq and HCR cohorts were derived from the linked EHRs. Phenotypes in UKB were from multiple sources of health-related data. RESULTS: A total of 214 020 participants were identified, including 23 544 in eMERGEseq cohort (mean [SD] age, 47.8 [23.7] years; 12 611 women [53.6%]), 187 234 in the UKB cohort (mean [SD] age, 56.7 [8.1] years; 104 055 [55.6%] women), and 3242 in the HCR cohort (mean [SD] age, 52.5 [15.5] years; 2851 [87.9%] women). All 38 established gene-cancer associations were replicated, and 19 new associations were identified. These included the following 7 associations with neoplasms: CHEK2 with leukemia (odds ratio [OR], 3.81 [95% CI, 2.64-5.48]) and plasma cell neoplasms (OR, 3.12 [95% CI, 1.84-5.28]), ATM with gastric cancer (OR, 4.27 [95% CI, 2.35-7.44]) and pancreatic cancer (OR, 4.44 [95% CI, 2.66-7.40]), MUTYH (biallelic) with kidney cancer (OR, 32.28 [95% CI, 6.40-162.73]), MSH6 with bladder cancer (OR, 5.63 [95% CI, 2.75-11.49]), and APC with benign liver/intrahepatic bile duct tumors (OR, 52.01 [95% CI, 14.29-189.29]). The remaining 12 associations with nonneoplastic diseases included BRCA1/2 with ovarian cysts (OR, 3.15 [95% CI, 2.22-4.46] and 3.12 [95% CI, 2.36-4.12], respectively), MEN1 with acute pancreatitis (OR, 33.45 [95% CI, 9.25-121.02]), APC with gastritis and duodenitis (OR, 4.66 [95% CI, 2.61-8.33]), and PTEN with chronic gastritis (OR, 15.68 [95% CI, 6.01-40.92]). CONCLUSIONS AND RELEVANCE: The findings of this genetic association study analyzing the EHRs of 3 large cohorts suggest that these new phenotypes associated with hereditary cancer genes may facilitate early detection and better management of cancers. This study highlights the potential benefits of using EHR data in genomic medicine.
Keywords: Acute Disease; Female; Gastritis; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Male; Neoplastic Syndromes, Hereditary; Pancreatitis

Examining the Effects of Hibernation on Germline Mutation Rates in Grizzly Bears. - Wang, Richard J; Peña-Garcia, Yadira; Bibby, Madeleine G; Raveendran, Muthuswamy; R. Alan Harris; Jansen, Heiko T; Robbins, Charles T; Jeffrey Rogers; Kelley, Joanna L; Hahn, Matthew W (Genome Biol Evol, 2022)
A male mutation bias is observed across vertebrates, and, where data are available, this bias is accompanied by increased per-generation mutation rates with parental age. While continuing mitotic cell division in the male germline post puberty has been proposed as the major cellular mechanism underlying both patterns, little direct evidence for this role has been found. Understanding the evolution of the per-generation mutation rate among species requires that we identify the molecular mechanisms that change between species. Here, we study the per-generation mutation rate in an extended pedigree of the brown (grizzly) bear, Ursus arctos horribilis. Brown bears hibernate for one-third of the year, a period during which spermatogenesis slows or stops altogether. The reduction of spermatogenesis is predicted to lessen the male mutation bias and to lower the per-generation mutation rate in this species. However, using whole-genome sequencing, we find that both male bias and per-generation mutation rates are highly similar to that expected for a non-hibernating species. We also carry out a phylogenetic comparison of substitution rates along the lineage leading to brown bear and panda (a non-hibernating species) and find no slowing of the substitution rate in the hibernator. Our results contribute to accumulating evidence that suggests that male germline cell division is not the major determinant of mutation rates and mutation biases. The results also provide a quantitative basis for improved estimates of the timing of carnivore evolution.
Keywords: Animals; Germ Cells; Germ-Line Mutation; Hibernation; Male; Mutation Rate; Phylogeny; Ursidae

Genetic analyses of the electrocardiographic QT interval and its components identify additional loci and pathways. - Young, William J; Lahrouchi, Najim; Isaacs, Aaron; Duong, ThuyVy; Foco, Luisa; Ahmed, Farah; Brody, Jennifer A; Salman, Reem; Noordam, Raymond; Benjamins, Jan-Walter; Haessler, Jeffrey; Lyytikäinen, Leo-Pekka; et al. (Nat Commun, 2022)
The QT interval is an electrocardiographic measure representing the sum of ventricular depolarization and repolarization, estimated by QRS duration and JT interval, respectively. QT interval abnormalities are associated with potentially fatal ventricular arrhythmia. Using genome-wide multi-ancestry analyses (>250,000 individuals) we identify 177, 156 and 121 independent loci for QT, JT and QRS, respectively, including a male-specific X-chromosome locus. Using gene-based rare-variant methods, we identify associations with Mendelian disease genes. Enrichments are observed in established pathways for QT and JT, and previously unreported genes indicated in insulin-receptor signalling and cardiac energy metabolism. In contrast for QRS, connective tissue components and processes for cell growth and extracellular matrix interactions are significantly enriched. We demonstrate polygenic risk score associations with atrial fibrillation, conduction disease and sudden cardiac death. Prioritization of druggable genes highlight potential therapeutic targets for arrhythmia. Together, these results substantially advance our understanding of the genetic architecture of ventricular depolarization and repolarization.
Keywords: Arrhythmias, Cardiac; Death, Sudden, Cardiac; Electrocardiography; Genetic Testing; Humans; Male

Genetic errors of immunity distinguish pediatric nonmalignant lymphoproliferative disorders. - Forbes, Lisa R; Eckstein, Olive S; Gulati, Nitya; Peckham-Gregory, Erin C; Ozuah, Nmazuo W; Lubega, Joseph; El-Mallawany, Nader K; Agrusa, Jennifer E; Poli, M Cecilia; Vogel, Tiphanie P; Chaimowitz, Natalia S; Rider, Nicholas L; et al. (J Allergy Clin Immunol, 2022)
BACKGROUND: Pediatric nonmalignant lymphoproliferative disorders (PLPDs) are clinically and genetically heterogeneous. Long-standing immune dysregulation and lymphoproliferation in children may be life-threatening, and a paucity of data exists to guide evaluation and treatment of children with PLPD. OBJECTIVE: The primary objective of this study was to ascertain the spectrum of genomic immunologic defects in PLPD. Secondary objectives included characterization of clinical outcomes and associations between genetic diagnoses and those outcomes. METHODS: PLPD was defined by persistent lymphadenopathy, lymph organ involvement, or lymphocytic infiltration for more than 3 months, with or without chronic or significant Epstein-Barr virus (EBV) infection. Fifty-one subjects from 47 different families with PLPD were analyzed using whole exome sequencing. RESULTS: Whole exome sequencing identified likely genetic errors of immunity in 51% to 62% of families (53% to 65% of affected children). Presence of a genetic etiology was associated with younger age and hemophagocytic lymphohistiocytosis. Ten-year survival for the cohort was 72.4%, and patients with viable genetic diagnoses had a higher survival rate (82%) compared to children without a genetic explanation (48%, P = .03). Survival outcomes for individuals with EBV-associated disease and no genetic explanation were particularly worse than outcomes for subjects with EBV-associated disease and a genetic explanation (17% vs 90%; P = .002). Ascertainment of a molecular diagnosis provided targetable treatment options for up to 18 individuals and led to active management changes for 12 patients. CONCLUSIONS: PLPD defines children at high risk for mortality, and whole exome sequencing informs clinical risks and therapeutic opportunities for this diagnosis.
Keywords: Adolescent; Autoimmunity; Child; Child, Preschool; Exome Sequencing; Female; Genetic Association Studies; Genetic Testing; Herpesvirus 4, Human; Humans; Immunity; Infant; Lymphoproliferative Disorders; Male; Young Adult

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation. - Longchamps, R J; Yang, S Y; Castellani, C A; Shi, W; Lane, J; Grove, M L; Bartz, T M; Sarnowski, C; Liu, C; Burrows, K; Guyatt, A L; Gaunt, T R; et al. (Hum Genet, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes (p = 3.09 × 10) and the gene ontology (GO) terms for mtDNA metabolism (p = 1.43 × 10) and mtDNA replication (p = 1.2 × 10). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall (p = 0.044) and non-cancer mortality (p = 6.56 × 10).
Keywords: Aged; Cell Proliferation; DNA Copy Number Variations; DNA, Mitochondrial; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Megakaryocytes; Middle Aged; Mitochondria; Nucleotides; Phenotype; Platelet Activation; Polymorphism, Single Nucleotide

Kidney Risk Variants and Proteomics. - Chen, Teresa K; Surapaneni, Aditya L; Arking, Dan E; Ballantyne, Christie M; Eric Boerwinkle; Chen, Jingsha; Coresh, Josef; Köttgen, Anna; Susztak, Katalin; Tin, Adrienne; Yu, Bing; Grams, Morgan E (Clin J Am Soc Nephrol, 2022)
BACKGROUND AND OBJECTIVES: The risk variants (G1 and G2) are associated with kidney disease among Black adults, but the clinical presentation is heterogeneous. In mouse models and cell systems, increased gene expression of G1 and G2 confers cytotoxicity. How risk variants relate to the circulating proteome warrants further investigation. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Among 461 African American Study of Kidney Disease and Hypertension (AASK) participants (mean age: 54 years; 41% women; mean GFR: 46 ml/min per 1.73 m), we evaluated associations of risk variants with 6790 serum proteins (measured SOMAscan) using linear regression models. Covariates included age, sex, percentage of European ancestry, and protein principal components 1-5. Associated proteins were then evaluated as mediators of -associated risk for kidney failure. Findings were replicated among 875 Atherosclerosis Risk in Communities (ARIC) study Black participants (mean age: 75 years; 66% women; mean eGFR: 67 ml/min per 1.73 m). RESULTS: In the AASK study, having two (versus zero or one) risk alleles was associated with lower serum levels of APOL1 (=3.11E-13; =3.12E-06 [two aptamers]), APOL2 (1.45E-10), CLSTN2 (=2.66E-06), MMP-2 (=2.96E-06), SPOCK2 (=2.57E-05), and TIMP-2 (=2.98E-05) proteins. In the ARIC study, risk alleles were associated with APOL1 (=1.28E-11); MMP-2 (=0.004) and TIMP-2 (=0.007) were associated only in an additive model, and APOL2 was not available. high-risk status was associated with a 1.6-fold greater risk of kidney failure in the AASK study; none of the identified proteins mediated this association. APOL1 protein levels were not associated with kidney failure in either cohort. CONCLUSIONS: risk variants were strongly associated with lower circulating levels of APOL1 and other proteins, but none mediated the -associated risk for kidney failure. APOL1 protein level was also not associated with kidney failure.
Keywords: Animals; Apolipoprotein L1; Creatinine; Female; Genetic Predisposition to Disease; Genotype; Humans; Kidney; Male; Matrix Metalloproteinase 2; Mice; Proteoglycans; Proteomics; Renal Insufficiency, Chronic; Risk Factors; Tissue Inhibitor of Metalloproteinase-2

Phenotypic and mutational spectrum of ROR2-related Robinow syndrome. - Lima, Ariadne R; Ferreira, Barbara M; Zhang, Chaofan; Jolly, Angad; Du, Haowei; White, Janson J; Dawood, Moez; Lins, Tulio C; Chiabai, Marcela A; van Beusekom, Ellen; Cordoba, Mara S; Caldas Rosa, Erica C C; et al. (Hum Mutat, 2022)
Robinow syndrome is characterized by a triad of craniofacial dysmorphisms, disproportionate-limb short stature, and genital hypoplasia. A significant degree of phenotypic variability seems to correlate with different genes/loci. Disturbances of the noncanonical WNT-pathway have been identified as the main cause of the syndrome. Biallelic variants in ROR2 cause an autosomal recessive form of the syndrome with distinctive skeletal findings. Twenty-two patients with a clinical diagnosis of autosomal recessive Robinow syndrome were screened for variants in ROR2 using multiple molecular approaches. We identified 25 putatively pathogenic ROR2 variants, 16 novel, including single nucleotide variants and exonic deletions. Detailed phenotypic analyses revealed that all subjects presented with a prominent forehead, hypertelorism, short nose, abnormality of the nasal tip, brachydactyly, mesomelic limb shortening, short stature, and genital hypoplasia in male patients. A total of 19 clinical features were present in more than 75% of the subjects, thus pointing to an overall uniformity of the phenotype. Disease-causing variants in ROR2, contribute to a clinically recognizable autosomal recessive trait phenotype with multiple skeletal defects. A comprehensive quantitative clinical evaluation of this cohort delineated the phenotypic spectrum of ROR2-related Robinow syndrome. The identification of exonic deletion variant alleles further supports the contention of a loss-of-function mechanism in the etiology of the syndrome.
Keywords: Craniofacial Abnormalities; Dwarfism; Genes, Recessive; Humans; Limb Deformities, Congenital; Male; Phenotype; Receptor Tyrosine Kinase-like Orphan Receptors; Urogenital Abnormalities

Sex-specific epigenetic development in the mouse hypothalamic arcuate nucleus pinpoints human genomic regions associated with body mass index. - MacKay, Harry; Gunasekara, Chathura J; Yam, Kit-Yi; Srisai, Dollada; Yalamanchili, Hari Krishna; Yumei Li; Rui Chen; Coarfa, Cristian; Waterland, Robert A (Sci Adv, 2022)
Recent genome-wide association studies corroborate classical research on developmental programming indicating that obesity is primarily a neurodevelopmental disease strongly influenced by nutrition during critical ontogenic windows. Epigenetic mechanisms regulate neurodevelopment; however, little is known about their role in establishing and maintaining the brain's energy balance circuitry. We generated neuron and glia methylomes and transcriptomes from male and female mouse hypothalamic arcuate nucleus, a key site for energy balance regulation, at time points spanning the closure of an established critical window for developmental programming of obesity risk. We find that postnatal epigenetic maturation is markedly cell type and sex specific and occurs in genomic regions enriched for heritability of body mass index in humans. Our results offer a potential explanation for both the limited ontogenic windows for and sex differences in sensitivity to developmental programming of obesity and provide a rich resource for epigenetic analyses of developmental programming of energy balance.
Keywords: Animals; Arcuate Nucleus of Hypothalamus; Body Mass Index; Epigenesis, Genetic; Epigenomics; Female; Genome-Wide Association Study; Humans; Hypothalamus; Male; Mice; Obesity

Single cell RNA sequencing of the adult Drosophila eye reveals distinct clusters and novel marker genes for all major cell types. - Yeung, Kelvin; Bollepogu Raja, Komal Kumar; Shim, Yoon-Kyung; Yumei Li; Rui Chen; Mardon, Graeme (Commun Biol, 2022)
The adult Drosophila eye is a powerful model system for phototransduction and neurodegeneration research. However, single cell resolution transcriptomic data are lacking for this tissue. We present single cell RNA-seq data on 1-day male and female, 3-day and 7-day old male adult eyes, covering early to mature adult eyes. All major cell types, including photoreceptors, cone and pigment cells in the adult eye were captured and identified. Our data sets identified novel cell type specific marker genes, some of which were validated in vivo. R7 and R8 photoreceptors form clusters that reflect their specific Rhodopsin expression and the specific Rhodopsin expression by each R7 and R8 cluster is the major determinant to their clustering. The transcriptomic data presented in this report will facilitate a deeper mechanistic understanding of the adult fly eye as a model system.
Keywords: Animals; Drosophila; Drosophila Proteins; Female; Male; Photoreceptor Cells, Invertebrate; Rhodopsin; Sequence Analysis, RNA

TCEAL1 loss-of-function results in an X-linked dominant neurodevelopmental syndrome and drives the neurological disease trait in Xq22.2 deletions. - Hijazi, Hadia; Reis, Linda M; Pehlivan, Davut; Bernstein, Jonathan A; Muriello, Michael; Syverson, Erin; Bonner, Devon; Estiar, Mehrdad A; Gan-Or, Ziv; Rouleau, Guy A; Lyulcheva, Ekaterina; Greenhalgh, Lynn; et al. (Am J Hum Genet, 2022)
An Xq22.2 region upstream of PLP1 has been proposed to underly a neurological disease trait when deleted in 46,XX females. Deletion mapping revealed that heterozygous deletions encompassing the smallest region of overlap (SRO) spanning six Xq22.2 genes (BEX3, RAB40A, TCEAL4, TCEAL3, TCEAL1, and MORF4L2) associate with an early-onset neurological disease trait (EONDT) consisting of hypotonia, intellectual disability, neurobehavioral abnormalities, and dysmorphic facial features. None of the genes within the SRO have been associated with monogenic disease in OMIM. Through local and international collaborations facilitated by GeneMatcher and Matchmaker Exchange, we have identified and herein report seven de novo variants involving TCEAL1 in seven unrelated families: three hemizygous truncating alleles; one hemizygous missense allele; one heterozygous TCEAL1 full gene deletion; one heterozygous contiguous deletion of TCEAL1, TCEAL3, and TCEAL4; and one heterozygous frameshift variant allele. Variants were identified through exome or genome sequencing with trio analysis or through chromosomal microarray. Comparison with previously reported Xq22 deletions encompassing TCEAL1 identified a more-defined syndrome consisting of hypotonia, abnormal gait, developmental delay/intellectual disability especially affecting expressive language, autistic-like behavior, and mildly dysmorphic facial features. Additional features include strabismus, refractive errors, variable nystagmus, gastroesophageal reflux, constipation, dysmotility, recurrent infections, seizures, and structural brain anomalies. An additional maternally inherited hemizygous missense allele of uncertain significance was identified in a male with hypertonia and spasticity without syndromic features. These data provide evidence that TCEAL1 loss of function causes a neurological rare disease trait involving significant neurological impairment with features overlapping the EONDT phenotype in females with the Xq22 deletion.
Keywords: Autistic Disorder; Female; Humans; Intellectual Disability; Male; Muscle Hypotonia; Phenotype; Syndrome; Transcription Factors

Use of medical exome sequencing for identification of underlying genetic defects in NICU: Experience in a cohort of 2303 neonates in China. - Yang, Lin; Wei, Zejun; Chen, Xiang; Hu, Liyuan; Peng, Xiaomin; Wang, Jin; Lu, Chunmei; Kong, Yanting; Dong, Xinran; Ni, Qi; Lu, Yulan; Wu, Bingbing; et al. (Clin Genet, 2022)
Emerging evidence demonstrates the clinical utility of genomic applications in newborn intensive care unit (NICU) patients with strong indications of Mendelian etiology. However, such applications' diagnostic yield and utility remain unclear for NICU cohorts with minimal phenotype selection. In this study, focused medical exome sequencing was used as a first-tier, singleton-focused diagnostic tool for 2303 unrelated sick neonates. Integrated analysis of single nucleotide variants (SNVs), small insertions and deletions (Indels), and large copy number variants (CNVs) was performed. The diagnostic rate in this NICU cohort is 12.3% (284/2303), with 190 probands with molecular diagnoses made from SNV/Indel analyses (66.9%), 93 patients with diagnostic aneuploidy/CNVs findings (32.8%), and 1 patient with both SNV and CNV (0.4%). In addition, 54 (2.3%) of patients had a reportable incidental finding. Multiple organ involvements, craniofacial abnormalities, and dermatologic abnormalities were the strongest positive predictors for a molecular diagnosis. Among the 190 cases with SNV/Indel defects, direct impacts on medical management were observed in 46.8% of patients after the results were reported. In this study, we demonstrate that focused medical exome sequencing is a powerful first-line diagnostic tool for NICU patients. Significant number of diagnosed NICU patients can benefit from more focused medical management and long-term care.
Keywords: Alleles; China; Chromosome Mapping; DNA Copy Number Variations; Exome Sequencing; Female; Genetic Association Studies; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Testing; Humans; INDEL Mutation; Intensive Care Units, Neonatal; Male; Polymorphism, Single Nucleotide; Whole Genome Sequencing

Absent B cells, agammaglobulinemia, and hypertrophic cardiomyopathy in folliculin-interacting protein 1 deficiency. - Saettini, Francesco; Poli, Cecilia; Vengoechea, Jaime; Bonanomi, Sonia; Orellana, Julio C; Fazio, Grazia; Rodriguez, Fred H; Noguera, Loreani P; Booth, Claire; Jarur-Chamy, Valentina; Shams, Marissa; Iascone, Maria; et al. (Blood, 2021)
Agammaglobulinemia is the most profound primary antibody deficiency that can occur due to an early termination of B-cell development. We here investigated 3 novel patients, including the first known adult, from unrelated families with agammaglobulinemia, recurrent infections, and hypertrophic cardiomyopathy (HCM). Two of them also presented with intermittent or severe chronic neutropenia. We identified homozygous or compound-heterozygous variants in the gene for folliculin interacting protein 1 (FNIP1), leading to loss of the FNIP1 protein. B-cell metabolism, including mitochondrial numbers and activity and phosphatidylinositol 3-kinase/AKT pathway, was impaired. These defects recapitulated the Fnip1-/- animal model. Moreover, we identified either uniparental disomy or copy-number variants (CNVs) in 2 patients, expanding the variant spectrum of this novel inborn error of immunity. The results indicate that FNIP1 deficiency can be caused by complex genetic mechanisms and support the clinical utility of exome sequencing and CNV analysis in patients with broad phenotypes, including agammaglobulinemia and HCM. FNIP1 deficiency is a novel inborn error of immunity characterized by early and severe B-cell development defect, agammaglobulinemia, variable neutropenia, and HCM. Our findings elucidate a functional and relevant role of FNIP1 in B-cell development and metabolism and potentially neutrophil activity.
Keywords: Adult; Agammaglobulinemia; Animals; B-Lymphocytes; Cardiomyopathy, Hypertrophic; Carrier Proteins; Child; Child, Preschool; Chromosomes, Human, Pair 5; Codon, Nonsense; Consanguinity; Crohn Disease; Developmental Disabilities; Disease Models, Animal; Disease Susceptibility; DNA Copy Number Variations; Female; Heart Defects, Congenital; Humans; Immunologic Deficiency Syndromes; Infections; Loss of Function Mutation; Lymphopenia; Male; Mice; Neutropenia; Pedigree; Uniparental Disomy; Whole Exome Sequencing

Alternative genomic diagnoses for individuals with a clinical diagnosis of Dubowitz syndrome. - Dyment, David A; O'Donnell-Luria, Anne; Agrawal, Pankaj B; Coban Akdemir, Zeynep; Aleck, Kyrieckos A; Antaki, Danny; Al Sharhan, Hind; Au, Ping-Yee B; Aydin, Hatip; Beggs, Alan H; Bilguvar, Kaya; Eric Boerwinkle; et al. (Am J Med Genet A, 2021)
Dubowitz syndrome (DubS) is considered a recognizable syndrome characterized by a distinctive facial appearance and deficits in growth and development. There have been over 200 individuals reported with Dubowitz or a "Dubowitz-like" condition, although no single gene has been implicated as responsible for its cause. We have performed exome (ES) or genome sequencing (GS) for 31 individuals clinically diagnosed with DubS. After genome-wide sequencing, rare variant filtering and computational and Mendelian genomic analyses, a presumptive molecular diagnosis was made in 13/27 (48%) families. The molecular diagnoses included biallelic variants in SKIV2L, SLC35C1, BRCA1, NSUN2; de novo variants in ARID1B, ARID1A, CREBBP, POGZ, TAF1, HDAC8, and copy-number variation at1p36.11(ARID1A), 8q22.2(VPS13B), Xp22, and Xq13(HDAC8). Variants of unknown significance in known disease genes, and also in genes of uncertain significance, were observed in 7/27 (26%) additional families. Only one gene, HDAC8, could explain the phenotype in more than one family (N = 2). All but two of the genomic diagnoses were for genes discovered, or for conditions recognized, since the introduction of next-generation sequencing. Overall, the DubS-like clinical phenotype is associated with extensive locus heterogeneity and the molecular diagnoses made are for emerging clinical conditions sharing characteristic features that overlap the DubS phenotype.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Eczema; Exome; Exome Sequencing; Facies; Female; Genetic Predisposition to Disease; Genome, Human; Genomics; Growth Disorders; Histone Deacetylases; Humans; Infant; Intellectual Disability; Male; Microcephaly; Phenotype; Repressor Proteins

Association Between Midlife Obesity and Kidney Function Trajectories: The Atherosclerosis Risk in Communities (ARIC) Study. - Yu, Zhi; Grams, Morgan E; Ndumele, Chiadi E; Wagenknecht, Lynne; Eric Boerwinkle; North, Kari E; Rebholz, Casey M; Giovannucci, Edward L; Coresh, Josef (Am J Kidney Dis, 2021)
RATIONALE & OBJECTIVE: Obesity has been related to risk for chronic kidney disease. However, the associations of different measures of midlife obesity with long-term kidney function trajectories and whether they differ by sex and race are unknown. STUDY DESIGN: Observational study. SETTING & PARTICIPANTS: 13,496 participants from the Atherosclerosis Risk in Communities (ARIC) Study. PREDICTORS: Midlife obesity status as measured by body mass index (BMI), waist-to-hip ratio, and predicted percent fat at baseline. OUTCOMES: Estimated glomerular filtration rate (eGFR) calculated using serum creatinine level measured at 5 study visits, and incident kidney failure with replacement therapy (KFRT). ANALYTICAL APPROACH: Mixed models with random intercepts and random slopes for eGFR. Cox proportional hazards models for KFRT. RESULTS: Baseline mean age was 54 years, median eGFR was 103mL/min/1.73m, and median BMI was 27kg/m. Over 30 years of follow-up, midlife obesity measures were associated with eGFR decline in White and Black women but not consistently in men. Adjusted for age, center, smoking, and coronary heart disease, the differences in eGFR slope per 1-SD higher BMI, waist-to-hip ratio, and predicted percent fat were 0.09 (95% CI, -0.18 to 0.36), -0.25 (95% CI, -0.50 to 0.01), and-0.14 (95% CI, -0.41 to 0.13) mL/min/1.73m per decade for White men; -0.91 (95% CI, -1.15 to-0.67), -0.82 (95% CI, -1.06 to-0.58), and-1.02 (95% CI, -1.26 to-0.78) mL/min/1.73m per decade for White women; -0.70 (95% CI, -1.54 to 0.14), -1.60 (95% CI, -2.42 to-0.78), and-1.24 (95% CI, -2.08 to-0.40) mL/min/1.73m per decade for Black men; and-1.24 (95% CI, -2.08 to-0.40), -1.50 (95% CI, -2.05 to-0.95), and-1.43 (95% CI, -2.00 to-0.86) mL/min/1.73m per decade for Black women. Obesity indicators were independently associated with risk for KFRT for all sex-race groups except White men. LIMITATIONS: Loss to follow-up during 3 decades of follow-up with 5 eGFR assessments. CONCLUSIONS: Obesity status is a risk factor for future decline in kidney function and development of KFRT in Black and White women, with less consistent associations among men.
Keywords: Black or African American; Body Mass Index; Creatinine; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Longitudinal Studies; Male; Middle Aged; Obesity; Proportional Hazards Models; Renal Replacement Therapy; Sex Factors; Waist-Hip Ratio; White People

Chromosome Xq23 is associated with lower atherogenic lipid concentrations and favorable cardiometabolic indices. - Natarajan, Pradeep; Pampana, Akhil; Graham, Sarah E; Ruotsalainen, Sanni E; Perry, James A; de Vries, Paul S; Broome, Jai G; Pirruccello, James P; Honigberg, Michael C; Aragam, Krishna; Wolford, Brooke; Brody, Jennifer A; et al. (Nat Commun, 2021)
Autosomal genetic analyses of blood lipids have yielded key insights for coronary heart disease (CHD). However, X chromosome genetic variation is understudied for blood lipids in large sample sizes. We now analyze genetic and blood lipid data in a high-coverage whole X chromosome sequencing study of 65,322 multi-ancestry participants and perform replication among 456,893 European participants. Common alleles on chromosome Xq23 are strongly associated with reduced total cholesterol, LDL cholesterol, and triglycerides (min P = 8.5 × 10), with similar effects for males and females. Chromosome Xq23 lipid-lowering alleles are associated with reduced odds for CHD among 42,545 cases and 591,247 controls (P = 1.7 × 10), and reduced odds for diabetes mellitus type 2 among 54,095 cases and 573,885 controls (P = 1.4 × 10). Although we observe an association with increased BMI, waist-to-hip ratio adjusted for BMI is reduced, bioimpedance analyses indicate increased gluteofemoral fat, and abdominal MRI analyses indicate reduced visceral adiposity. Co-localization analyses strongly correlate increased CHRDL1 gene expression, particularly in adipose tissue, with reduced concentrations of blood lipids.
Keywords: Cardiometabolic Risk Factors; Chromosomes, Human, X; Eye Proteins; Female; Gene Expression Regulation; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genotype; Humans; Lipids; Male; Middle Aged; Nerve Tissue Proteins; Phenomics; Polymorphism, Single Nucleotide; Subcutaneous Tissue; Whole Genome Sequencing

Clinical characterization of individuals with the distal 1q21.1 microdeletion. - Edwards, Stacey D; Schulze, Katharina V; Rosenfeld, Jill A; Westerfield, Lauren E; Gerard, Amanda; Bo Yuan; Grigorenko, Elena L; Posey, Jennifer E; Bi, Weimin; Liu, Pengfei (Am J Med Genet A, 2021)
Distal 1q21.1 microdeletions have shown highly variable clinical expressivity and incomplete penetrance, with affected individuals manifesting a broad spectrum of nonspecific features. The goals of this study were to better describe the phenotypic spectrum of patients with distal 1q21.1 microdeletions and to compare the clinical features among affected individuals. We performed a retrospective chart review of 47 individuals with distal 1q21.1 microdeletions tested at a large clinical genetic testing laboratory, with most patients being clinically evaluated in the same children's hospital. Health information such as growth charts, results of imaging studies, developmental history, and progress notes were collected. Statistical analysis was performed using Fisher's exact test to compare clinical features among study subjects. Common features in our cohort include microcephaly (51.2%), seizures (29.8%), developmental delay (74.5%), failure to thrive (FTT) (68.1%), dysmorphic features (63.8%), and a variety of congenital anomalies such as cardiac abnormalities (23.4%) and genitourinary abnormalities (19.1%). Compared to prior literature, we found that seizures, brain anomalies, and FTT were more prevalent among our study cohort. Females were more likely than males to have microcephaly (p = 0.0199) and cardiac abnormalities (p = 0.0018). Based on existing genome-wide clinical testing results, at least a quarter of the cohort had additional genetic findings that may impact the phenotype of the individual. Our study represents the largest cohort of distal 1q21.1 microdeletion carriers available in the literature thus far, and it further illustrates the wide spectrum of clinical manifestations among symptomatic individuals. These results may allow for improved genetic counseling and management of affected individuals. Future studies may help to elucidate the underlying molecular mechanisms impacting the phenotypic variability observed with this microdeletion.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Child; Child, Preschool; Chromosome Deletion; Chromosomes, Human, Pair 1; Developmental Disabilities; DNA Copy Number Variations; Failure to Thrive; Female; Genetic Counseling; Genetic Testing; Heart Defects, Congenital; Humans; Infant; Intellectual Disability; Male; Megalencephaly; Microcephaly; Pedigree; Seizures; Young Adult

Clinical, neuroimaging, and molecular spectrum of TECPR2-associated hereditary sensory and autonomic neuropathy with intellectual disability. - Neuser, Sonja; Brechmann, Barbara; Heimer, Gali; Brösse, Ines; Schubert, Susanna; O'Grady, Lauren; Zech, Michael; Srivastava, Siddharth; Sweetser, David A; Dincer, Yasemin; Mall, Volker; Winkelmann, Juliane; et al. (Hum Mutat, 2021)
Bi-allelic TECPR2 variants have been associated with a complex syndrome with features of both a neurodevelopmental and neurodegenerative disorder. Here, we provide a comprehensive clinical description and variant interpretation framework for this genetic locus. Through international collaboration, we identified 17 individuals from 15 families with bi-allelic TECPR2-variants. We systemically reviewed clinical and molecular data from this cohort and 11 cases previously reported. Phenotypes were standardized using Human Phenotype Ontology terms. A cross-sectional analysis revealed global developmental delay/intellectual disability, muscular hypotonia, ataxia, hyporeflexia, respiratory infections, and central/nocturnal hypopnea as core manifestations. A review of brain magnetic resonance imaging scans demonstrated a thin corpus callosum in 52%. We evaluated 17 distinct variants. Missense variants in TECPR2 are predominantly located in the N- and C-terminal regions containing β-propeller repeats. Despite constituting nearly half of disease-associated TECPR2 variants, classifying missense variants as (likely) pathogenic according to ACMG criteria remains challenging. We estimate a pathogenic variant carrier frequency of 1/1221 in the general and 1/155 in the Jewish Ashkenazi populations. Based on clinical, neuroimaging, and genetic data, we provide recommendations for variant reporting, clinical assessment, and surveillance/treatment of individuals with TECPR2-associated disorder. This sets the stage for future prospective natural history studies.
Keywords: Adolescent; Carrier Proteins; Child; Child, Preschool; Cohort Studies; Cross-Sectional Studies; Family; Female; Hereditary Sensory and Autonomic Neuropathies; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Models, Molecular; Mutation, Missense; Nerve Tissue Proteins; Neuroimaging; Pedigree; Phenotype; Protein Conformation

Clinical presentation and evolution of Xia-Gibbs syndrome due to p.Gly375ArgfsTer3 variant in a patient from DR Congo (Central Africa). - Mubungu, Gerrye; Makay, Prince; Boujemla, Bouchra; Yanda, Stephane; Posey, Jennifer E; James R Lupski; Bours, Vincent; Lukusa, Prosper; Devriendt, Koenraad; Lumaka, Aimé (Am J Med Genet A, 2021)
Xia-Gibbs syndrome (XGS) is a very rare genetic condition. The clinical spectrum is very broad and variable. The phenotype and evolution in a Congolese boy with XGS have been reported. At 6 years he had speech delay, drooling, marked hyperactivity, attention deficit, aggressive behavior, and intellectual disability. Dysmorphological evaluation revealed strabismus, mild unilateral ptosis, uplifted ear lobes, flat philtrum, thin upper lip vermillion, high arched palate, and flat feet. Patient-only whole exome sequencing identified a known pathogenic frameshift variant in the AHDC1 gene [NM_001029882.3(AHDC1):c.1122dupC;(p.Gly375ArgfsTer3)]. The clinical follow-up revealed the deterioration of his fine motor skills and significant cerebellar phenotype including tremor, pes cavus, and gait instability at the age of 12 years. This patient was compared with three previously reported patients with the same variant but did not identify a consistent pattern in the evolution of symptoms with age.
Keywords: Abnormalities, Multiple; Agenesis of Corpus Callosum; Attention Deficit Disorder with Hyperactivity; Child; Democratic Republic of the Congo; Developmental Disabilities; DNA-Binding Proteins; Exome Sequencing; Face; Frameshift Mutation; Humans; Intellectual Disability; Language Development Disorders; Male; Mitral Valve Insufficiency; Palate; Syndrome; Talipes Cavus

Common variants in Alzheimer's disease and risk stratification by polygenic risk scores. - de Rojas, Itziar; Moreno-Grau, Sonia; Tesi, Niccolo; Grenier-Boley, Benjamin; Andrade, Victor; Jansen, Iris E; Pedersen, Nancy L; Stringa, Najada; Zettergren, Anna; Hernández, Isabel; Montrreal, Laura; Antúnez, Carmen; et al. (Nat Commun, 2021)
Genetic discoveries of Alzheimer's disease are the drivers of our understanding, and together with polygenetic risk stratification can contribute towards planning of feasible and efficient preventive and curative clinical trials. We first perform a large genetic association study by merging all available case-control datasets and by-proxy study results (discovery n = 409,435 and validation size n = 58,190). Here, we add six variants associated with Alzheimer's disease risk (near APP, CHRNE, PRKD3/NDUFAF7, PLCG2 and two exonic variants in the SHARPIN gene). Assessment of the polygenic risk score and stratifying by APOE reveal a 4 to 5.5 years difference in median age at onset of Alzheimer's disease patients in APOE ɛ4 carriers. Because of this study, the underlying mechanisms of APP can be studied to refine the amyloid cascade and the polygenic risk score provides a tool to select individuals at high risk of Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Protein Precursor; Apolipoproteins E; Case-Control Studies; Cohort Studies; Datasets as Topic; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Humans; Male; Middle Aged; Multifactorial Inheritance; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors

COPB2 loss of function causes a coatopathy with osteoporosis and developmental delay. - Marom, Ronit; Burrage, Lindsay C; Venditti, Rossella; Clément, Aurélie; Blanco-Sánchez, Bernardo; Jain, Mahim; Scott, Daryl A; Rosenfeld, Jill A; Sutton, V Reid; Shinawi, Marwan; Mirzaa, Ghayda; DeVile, Catherine; et al. (Am J Hum Genet, 2021)
Coatomer complexes function in the sorting and trafficking of proteins between subcellular organelles. Pathogenic variants in coatomer subunits or associated factors have been reported in multi-systemic disorders, i.e., coatopathies, that can affect the skeletal and central nervous systems. We have identified loss-of-function variants in COPB2, a component of the coatomer complex I (COPI), in individuals presenting with osteoporosis, fractures, and developmental delay of variable severity. Electron microscopy of COPB2-deficient subjects' fibroblasts showed dilated endoplasmic reticulum (ER) with granular material, prominent rough ER, and vacuoles, consistent with an intracellular trafficking defect. We studied the effect of COPB2 deficiency on collagen trafficking because of the critical role of collagen secretion in bone biology. COPB2 siRNA-treated fibroblasts showed delayed collagen secretion with retention of type I collagen in the ER and Golgi and altered distribution of Golgi markers. copb2-null zebrafish embryos showed retention of type II collagen, disorganization of the ER and Golgi, and early larval lethality. Copb2 mice exhibited low bone mass, and consistent with the findings in human cells and zebrafish, studies in Copb2 mouse fibroblasts suggest ER stress and a Golgi defect. Interestingly, ascorbic acid treatment partially rescued the zebrafish developmental phenotype and the cellular phenotype in Copb2 mouse fibroblasts. This work identifies a form of coatopathy due to COPB2 haploinsufficiency, explores a potential therapeutic approach for this disorder, and highlights the role of the COPI complex as a regulator of skeletal homeostasis.
Keywords: Animals; Ascorbic Acid; Bone and Bones; Brain; Child; Child, Preschool; Coat Protein Complex I; Coatomer Protein; Collagen Type I; Developmental Disabilities; Embryo, Nonmammalian; Endoplasmic Reticulum; Female; Fibroblasts; Gene Expression Regulation, Developmental; Golgi Apparatus; Haploinsufficiency; Humans; Intellectual Disability; Male; Mice; Osteoporosis; RNA, Small Interfering; Severity of Illness Index; Zebrafish

Deep clinicopathological phenotyping identifies a previously unrecognized pathogenic EMD splice variant. - Calame, Daniel G; Fatih, Jawid M; Herman, Isabella; Coban-Akdemir, Zeynep; Du, Haowei; Mitani, Tadahiro; Jhangiani, Shalini N; Marafi, Dana; Richard A Gibbs; Posey, Jennifer E; Mehta, Vidya P; Mohila, Carrie A; et al. (Ann Clin Transl Neurol, 2021)
Exome sequencing (ES) has revolutionized rare disease management, yet only ~25%-30% of patients receive a molecular diagnosis. A limiting factor is the quality of available phenotypic data. Here, we describe how deep clinicopathological phenotyping yielded a molecular diagnosis for a 19-year-old proband with muscular dystrophy and negative clinical ES. Deep phenotypic analysis identified two critical data points: (1) the absence of emerin protein in muscle biopsy and (2) clinical features consistent with Emery-Dreifuss muscular dystrophy. Sequencing data analysis uncovered an ultra-rare, intronic variant in EMD, the gene encoding emerin. The variant, NM_000117.3: c.188-6A > G, is predicted to impact splicing by in silico tools. This case thus illustrates how better integration of clinicopathologic data into ES analysis can enhance diagnostic yield with implications for clinical practice.
Keywords: Adult; Exome Sequencing; Humans; Male; Membrane Proteins; Muscle, Skeletal; Muscular Dystrophy, Emery-Dreifuss; Nuclear Proteins; Young Adult

Deforming Polyarthritis in a North Indian Family-Clinical Expansion of STING-Associated Vasculopathy with Onset in Infancy (SAVI). - Anjani, Gummadi; Jindal, Ankur Kumar; Prithvi, Ashwini; Kaur, Anit; Rawat, Amit; Sharma, Madhubala; Bo Yuan; Chinn, Ivan K; Singh, Surjit (J Clin Immunol, 2021)
Keywords: Anti-Inflammatory Agents; Arthritis; Biomarkers; Child; Child, Preschool; Diagnosis, Differential; Family; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Immunosuppressive Agents; India; Joints; Male; Membrane Proteins; Phenotype; Tomography, X-Ray Computed; Treatment Outcome

Delineating the molecular and phenotypic spectrum of the SETD1B-related syndrome. - Weerts, Marjolein J A; Lanko, Kristina; Guzmán-Vega, Francisco J; Jackson, Adam; Ramakrishnan, Reshmi; Cardona-Londoño, Kelly J; Peña-Guerra, Karla A; van Bever, Yolande; van Paassen, Barbara W; Kievit, Anneke; van Slegtenhorst, Marjon; Allen, Nicholas M; et al. (Genet Med, 2021)
PURPOSE: Pathogenic variants in SETD1B have been associated with a syndromic neurodevelopmental disorder including intellectual disability, language delay, and seizures. To date, clinical features have been described for 11 patients with (likely) pathogenic SETD1B sequence variants. This study aims to further delineate the spectrum of the SETD1B-related syndrome based on characterizing an expanded patient cohort. METHODS: We perform an in-depth clinical characterization of a cohort of 36 unpublished individuals with SETD1B sequence variants, describing their molecular and phenotypic spectrum. Selected variants were functionally tested using in vitro and genome-wide methylation assays. RESULTS: Our data present evidence for a loss-of-function mechanism of SETD1B variants, resulting in a core clinical phenotype of global developmental delay, language delay including regression, intellectual disability, autism and other behavioral issues, and variable epilepsy phenotypes. Developmental delay appeared to precede seizure onset, suggesting SETD1B dysfunction impacts physiological neurodevelopment even in the absence of epileptic activity. Males are significantly overrepresented and more severely affected, and we speculate that sex-linked traits could affect susceptibility to penetrance and the clinical spectrum of SETD1B variants. CONCLUSION: Insights from this extensive cohort will facilitate the counseling regarding the molecular and phenotypic landscape of newly diagnosed patients with the SETD1B-related syndrome.
Keywords: Epilepsy; Histone-Lysine N-Methyltransferase; Humans; Intellectual Disability; Male; Neurodevelopmental Disorders; Phenotype; Seizures

Diagnostic yield and clinical impact of exome sequencing in early-onset scoliosis (EOS). - Zhao, Sen; Zhang, Yuanqiang; Chen, Weisheng; Li, Weiyu; Wang, Shengru; Wang, Lianlei; Zhao, Yanxue; Lin, Mao; Ye, Yongyu; Lin, Jiachen; Zheng, Yu; Liu, Jiaqi; et al. (J Med Genet, 2021)
BACKGROUND: Early-onset scoliosis (EOS), defined by an onset age of scoliosis less than 10 years, conveys significant health risk to affected children. Identification of the molecular aetiology underlying patients with EOS could provide valuable information for both clinical management and prenatal screening. METHODS: In this study, we consecutively recruited a cohort of 447 Chinese patients with operative EOS. We performed exome sequencing (ES) screening on these individuals and their available family members (totaling 670 subjects). Another cohort of 13 patients with idiopathic early-onset scoliosis (IEOS) from the USA who underwent ES was also recruited. RESULTS: After ES data processing and variant interpretation, we detected molecular diagnostic variants in 92 out of 447 (20.6%) Chinese patients with EOS, including 8 patients with molecular confirmation of their clinical diagnosis and 84 patients with molecular diagnoses of previously unrecognised diseases underlying scoliosis. One out of 13 patients with IEOS from the US cohort was molecularly diagnosed. The age at presentation, the number of organ systems involved and the Cobb angle were the three top features predictive of a molecular diagnosis. CONCLUSION: ES enabled the molecular diagnosis/classification of patients with EOS. Specific clinical features/feature pairs are able to indicate the likelihood of gaining a molecular diagnosis through ES.
Keywords: Adolescent; Adult; Age of Onset; Child, Preschool; China; Cohort Studies; Exome; Exome Sequencing; Female; Genetic Predisposition to Disease; Humans; Male; Retrospective Studies; Scoliosis

Durable Response to Larotrectinib in a Child With Histologic Diagnosis of Recurrent Disseminated Ependymoma Discovered to Harbor an Fusion: The Impact of Integrated Genomic Profiling. - Mangum, Ross; Reuther, Jacquelyn; Bertrand, Kelsey C; Chandramohan, Raghu; Kukreja, Marcia K; Paulino, Arnold C; Donna M Muzny; Jianhong Hu; Richard A Gibbs; Curry, Daniel J; Malbari, Fatema; Chintagumpala, Murali M; et al. (JCO Precis Oncol, 2021)
Keywords: Brain Neoplasms; Child; Ependymoma; Gene Expression Profiling; Humans; Male; Membrane Glycoproteins; Neoplasm Recurrence, Local; Pyrazoles; Pyrimidines; Receptor, trkB

Epigenome-wide association study of mitochondrial genome copy number. - Wang, Penglong; Castellani, Christina A; Yao, Jie; Huan, Tianxiao; Bielak, Lawrence F; Zhao, Wei; Haessler, Jeffrey; Joehanes, Roby; Sun, Xianbang; Guo, Xiuqing; Longchamps, Ryan J; Manson, JoAnn E; et al. (Hum Mol Genet, 2021)
We conducted cohort- and race-specific epigenome-wide association analyses of mitochondrial deoxyribonucleic acid (mtDNA) copy number (mtDNA CN) measured in whole blood from participants of African and European origins in five cohorts (n = 6182, mean age = 57-67 years, 65% women). In the meta-analysis of all the participants, we discovered 21 mtDNA CN-associated DNA methylation sites (CpG) (P < 1 × 10-7), with a 0.7-3.0 standard deviation increase (3 CpGs) or decrease (18 CpGs) in mtDNA CN corresponding to a 1% increase in DNA methylation. Several significant CpGs have been reported to be associated with at least two risk factors (e.g. chronological age or smoking) for cardiovascular disease (CVD). Five genes [PR/SET domain 16, nuclear receptor subfamily 1 group H member 3 (NR1H3), DNA repair protein, DNA polymerase kappa and decaprenyl-diphosphate synthase subunit 2], which harbor nine significant CpGs, are known to be involved in mitochondrial biosynthesis and functions. For example, NR1H3 encodes a transcription factor that is differentially expressed during an adipose tissue transition. The methylation level of cg09548275 in NR1H3 was negatively associated with mtDNA CN (effect size = -1.71, P = 4 × 10-8) and was positively associated with the NR1H3 expression level (effect size = 0.43, P = 0.0003), which indicates that the methylation level in NR1H3 may underlie the relationship between mtDNA CN, the NR1H3 transcription factor and energy expenditure. In summary, the study results suggest that mtDNA CN variation in whole blood is associated with DNA methylation levels in genes that are involved in a wide range of mitochondrial activities. These findings will help reveal molecular mechanisms between mtDNA CN and CVD.
Keywords: Aged; DNA Copy Number Variations; DNA Methylation; DNA, Mitochondrial; Epigenome; Female; Genome, Mitochondrial; Humans; Male; Middle Aged

The Exceptional Responders Initiative: Feasibility of a National Cancer Institute Pilot Study. - Conley, Barbara A; Staudt, Lou; Takebe, Naoko; David A Wheeler; Wang, Linghua; Cardenas, Maria F; Korchina, Viktoriya; Zenklusen, Jean Claude; McShane, Lisa M; Tricoli, James V; Williams, Paul M; Lubensky, Irina; et al. (J Natl Cancer Inst, 2021)
BACKGROUND: Tumor molecular profiling from patients experiencing exceptional responses to systemic therapy may provide insights into cancer biology and improve treatment tailoring. This pilot study evaluates the feasibility of identifying exceptional responders retrospectively, obtaining pre-exceptional response treatment tumor tissues, and analyzing them with state-of-the-art molecular analysis tools to identify potential molecular explanations for responses. METHODS: Exceptional response was defined as partial (PR) or complete (CR) response to a systemic treatment with population PR or CR rate less than 10% or an unusually long response (eg, duration >3 times published median). Cases proposed by patients' clinicians were reviewed by clinical and translational experts. Tumor and normal tissue (if possible) were profiled with whole exome sequencing and, if possible, targeted deep sequencing, RNA sequencing, methylation arrays, and immunohistochemistry. Potential germline mutations were tracked for relevance to disease. RESULTS: Cases reflected a variety of tumors and standard and investigational treatments. Of 520 cases, 476 (91.5%) were accepted for further review, and 222 of 476 (46.6%) proposed cases met requirements as exceptional responders. Clinical data were obtained from 168 of 222 cases (75.7%). Tumor was provided from 130 of 168 cases (77.4%). Of 117 of the 130 (90.0%) cases with sufficient nucleic acids, 109 (93.2%) were successfully analyzed; 6 patients had potentially actionable germline mutations. CONCLUSION: Exceptional responses occur with standard and investigational treatment. Retrospective identification of exceptional responders, accessioning, and sequencing of pretreatment archived tissue is feasible. Data from molecular analyses of tumors, particularly when combining results from patients who received similar treatments, may elucidate molecular bases for exceptional responses.
Keywords: Adult; Aged; Aged, 80 and over; Exome Sequencing; Feasibility Studies; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Mutation; National Cancer Institute (U.S.); Neoplasms; Pilot Projects; Precision Medicine; Retrospective Studies; Sequence Analysis, RNA; Transcriptome; United States

Exome sequencing in children with clinically suspected maturity-onset diabetes of the young. - Tosur, Mustafa; Soler-Alfonso, Claudia; Chan, Katie M; Khayat, Michael M; Jhangiani, Shalini N; Meng, Qingchang; Refaey, Ahmad; Donna M Muzny; Richard A Gibbs; David R Murdock; Posey, Jennifer E; Balasubramanyam, Ashok; et al. (Pediatr Diabetes, 2021)
OBJECTIVE: Commercial gene panels identify pathogenic variants in as low as 27% of patients suspected to have MODY, suggesting the role of yet unidentified pathogenic variants. We sought to identify novel gene variants associated with MODY. RESEARCH DESIGN AND METHODS: We recruited 10 children with a clinical suspicion of MODY but non-diagnostic commercial MODY gene panels. We performed exome sequencing (ES) in them and their parents. RESULTS: Mean age at diabetes diagnosis was 10 (± 3.8) years. Six were females; 4 were non-Hispanic white, 5 Hispanic, and 1 Asian. Our variant prioritization analysis identified a pathogenic, de novo variant in INS (c.94G > A, p.Gly32Ser), confirmed by Sanger sequencing, in a proband who was previously diagnosed with "autoantibody-negative type 1 diabetes (T1D)" at 3 y/o. This rare variant, absent in the general population (gnomAD database), has been reported previously in neonatal diabetes. We also identified a frameshift deletion (c.2650delC, p.Gln884AsnfsTer57) in RFX6 in a child with a previous diagnosis of "autoantibody-negative T1D" at 12 y/o. The variant was inherited from the mother, who was diagnosed with "thin type 2 diabetes" at 25 y/o. Heterozygous protein-truncating variants in RFX6 gene have been recently reported in individuals with MODY. CONCLUSIONS: We diagnosed two patients with MODY using ES in children initially classified as "T1D". One has a likely pathogenic novel gene variant not previously associated with MODY. We demonstrate the clinical utility of ES in patients with clinical suspicion of MODY.
Keywords: Adolescent; Autoantibodies; Child; Diabetes Mellitus, Type 1; Diabetes Mellitus, Type 2; Diagnosis, Differential; Exome Sequencing; Female; Frameshift Mutation; Genetic Variation; Humans; Islets of Langerhans; Male; Mutation, Missense; Pedigree

Exome sequencing reveals genetic architecture in patients with isolated or syndromic short stature. - Fan, Xin; Zhao, Sen; Yu, Chenxi; Wu, Di; Yan, Zihui; Fan, Lijun; Song, Yanning; Wang, Yi; Li, Chuan; Ming, Yue; Gui, Baoheng; Niu, Yuchen; et al. (J Genet Genomics, 2021)
Short stature is among the most common endocrinological disease phenotypes of childhood and may occur as an isolated finding or in conjunction with other clinical manifestations. Although the diagnostic utility of clinical genetic testing in short stature has been implicated, the genetic architecture and the utility of genomic studies such as exome sequencing (ES) in a sizable cohort of patients with short stature have not been investigated systematically. In this study, we recruited 561 individuals with short stature from two centers in China during a 4-year period. We performed ES for all patients and available parents. All patients were retrospectively divided into two groups: an isolated short stature group (group I, n = 257) and an apparently syndromic short stature group (group II, n = 304). Causal variants were identified in 135 of 561 (24.1%) patients. In group I, 29 of 257 (11.3%) of the patients were solved by variants in 24 genes. In group II, 106 of 304 (34.9%) patients were solved by variants in 57 genes. Genes involved in fundamental cellular process played an important role in the genetic architecture of syndromic short stature. Distinct genetic architectures and pathophysiological processes underlie isolated and syndromic short stature.
Keywords: Adolescent; Alleles; Child; Child, Preschool; China; Disease Management; DNA Copy Number Variations; Dwarfism; Exome; Exome Sequencing; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Testing; Genotype; Humans; Male; Mutation; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Syndrome

Exome sequencing reveals predominantly de novo variants in disorders with intellectual disability (ID) in the founder population of Finland. - Järvelä, Irma; Määttä, Tuomo; Acharya, Anushree; Leppälä, Juha; Jhangiani, Shalini N; Arvio, Maria; Siren, Auli; Kankuri-Tammilehto, Minna; Kokkonen, Hannaleena; Palomäki, Maarit; Varilo, Teppo; Fang, Mary; et al. (Hum Genet, 2021)
The genetics of autosomal recessive intellectual disability (ARID) has mainly been studied in consanguineous families, however, founder populations may also be of interest to study intellectual disability (ID) and the contribution of ARID. Here, we used a genotype-driven approach to study the genetic landscape of ID in the founder population of Finland. A total of 39 families with syndromic and non-syndromic ID were analyzed using exome sequencing, which revealed a variant in a known ID gene in 27 families. Notably, 75% of these variants in known ID genes were de novo or suspected de novo (64% autosomal dominant; 11% X-linked) and 25% were inherited (14% autosomal recessive; 7% X-linked; and 4% autosomal dominant). A dual molecular diagnosis was suggested in two families (5%). Via additional analysis and molecular testing, we identified three cases with an abnormal molecular karyotype, including chr21q22.12q22.2 uniparental disomy with a mosaic interstitial 2.7 Mb deletion covering DYRK1A and KCNJ6. Overall, a pathogenic or likely pathogenic variant was identified in 64% (25/39) of the families. Last, we report an alternate inheritance model for 3 known ID genes (UBA7, DDX47, DHX58) and discuss potential candidate genes for ID, including SYPL1 and ERGIC3 with homozygous founder variants and de novo variants in POLR2F and DNAH3. In summary, similar to other European populations, de novo variants were the most common variants underlying ID in the studied Finnish population, with limited contribution of ARID to ID etiology, though mainly driven by founder and potential founder variation in the latter case.
Keywords: Exome; Exome Sequencing; Family; Female; Finland; Genes, Recessive; Genetic Predisposition to Disease; Genotype; Homozygote; Humans; Intellectual Disability; Male; Pedigree

Functional interpretation of ATAD3A variants in neuro-mitochondrial phenotypes. - Yap, Zheng Yie; Park, Yo Han; Wortmann, Saskia B; Gunning, Adam C; Ezer, Shlomit; Lee, Sukyeong; Duraine, Lita; Wilichowski, Ekkehard; Wilson, Kate; Mayr, Johannes A; Wagner, Matias; Li, Hong; et al. (Genome Med, 2021)
BACKGROUND: ATPase family AAA-domain containing protein 3A (ATAD3A) is a nuclear-encoded mitochondrial membrane-anchored protein involved in diverse processes including mitochondrial dynamics, mitochondrial DNA organization, and cholesterol metabolism. Biallelic deletions (null), recessive missense variants (hypomorph), and heterozygous missense variants or duplications (antimorph) in ATAD3A lead to neurological syndromes in humans. METHODS: To expand the mutational spectrum of ATAD3A variants and to provide functional interpretation of missense alleles in trans to deletion alleles, we performed exome sequencing for identification of single nucleotide variants (SNVs) and copy number variants (CNVs) in ATAD3A in individuals with neurological and mitochondrial phenotypes. A Drosophila Atad3a Gal4 knockin-null allele was generated using CRISPR-Cas9 genome editing technology to aid the interpretation of variants. RESULTS: We report 13 individuals from 8 unrelated families with biallelic ATAD3A variants. The variants included four missense variants inherited in trans to loss-of-function alleles (p.(Leu77Val), p.(Phe50Leu), p.(Arg170Trp), p.(Gly236Val)), a homozygous missense variant p.(Arg327Pro), and a heterozygous non-frameshift indel p.(Lys568del). Affected individuals exhibited findings previously associated with ATAD3A pathogenic variation, including developmental delay, hypotonia, congenital cataracts, hypertrophic cardiomyopathy, and cerebellar atrophy. Drosophila studies indicated that Phe50Leu, Gly236Val, Arg327Pro, and Lys568del are severe loss-of-function alleles leading to early developmental lethality. Further, we showed that Phe50Leu, Gly236Val, and Arg327Pro cause neurogenesis defects. On the contrary, Leu77Val and Arg170Trp are partial loss-of-function alleles that cause progressive locomotion defects and whose expression leads to an increase in autophagy and mitophagy in adult muscles. CONCLUSION: Our findings expand the allelic spectrum of ATAD3A variants and exemplify the use of a functional assay in Drosophila to aid variant interpretation.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Animals; ATPases Associated with Diverse Cellular Activities; Autophagy; Computer Simulation; Drosophila; Female; Genetic Variation; Humans; Infant; Infant, Newborn; Locomotion; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Mitophagy; Mutation, Missense; Neurogenesis; Neurons; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Young Adult

Genetic susceptibility, obesity and lifetime risk of type 2 diabetes: The ARIC study and Rotterdam Study. - Ligthart, Symen; Hasbani, Natalie R; Ahmadizar, Fariba; van Herpt, Thijs T W; Leening, Maarten J G; Uitterlinden, André G; Sijbrands, Eric J G; Morrison, Alanna C; Eric Boerwinkle; Pankow, James S; Selvin, Elizabeth; Ikram, M Arfan; et al. (Diabet Med, 2021)
AIMS: Both lifestyle factors and genetic background contribute to the development of type 2 diabetes. Estimation of the lifetime risk of diabetes based on genetic information has not been presented, and the extent to which a normal body weight can offset a high lifetime genetic risk is unknown. METHODS: We used data from 15,671 diabetes-free participants of European ancestry aged 45 years and older from the prospective population-based ARIC study and Rotterdam Study (RS). We quantified the remaining lifetime risk of diabetes stratified by genetic risk and quantified the effect of normal weight in terms of relative and lifetime risks in low, intermediate and high genetic risk. RESULTS: At age 45 years, the lifetime risk of type 2 diabetes in ARIC in the low, intermediate and high genetic risk category was 33.2%, 41.3% and 47.2%, and in RS 22.8%, 30.6% and 35.5% respectively. The absolute lifetime risk for individuals with normal weight compared to individuals with obesity was 24% lower in ARIC and 8.6% lower in RS in the low genetic risk group, 36.3% lower in ARIC and 31.3% lower in RS in the intermediate genetic risk group, and 25.0% lower in ARIC and 29.4% lower in RS in the high genetic risk group. CONCLUSIONS: Genetic variants for type 2 diabetes have value in estimating the lifetime risk of type 2 diabetes. Normal weight mitigates partly the deleterious effect of high genetic risk.
Keywords: Aged; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Life Style; Male; Middle Aged; Multifactorial Inheritance; Obesity; Risk; White People

Genome-wide meta-analysis of muscle weakness identifies 15 susceptibility loci in older men and women. - Jones, Garan; Trajanoska, Katerina; Santanasto, Adam J; Stringa, Najada; Kuo, Chia-Ling; Atkins, Janice L; Lewis, Joshua R; Duong, ThuyVy; Hong, Shengjun; Biggs, Mary L; Luan, Jian'an; Sarnowski, Chloe; et al. (Nat Commun, 2021)
Low muscle strength is an important heritable indicator of poor health linked to morbidity and mortality in older people. In a genome-wide association study meta-analysis of 256,523 Europeans aged 60 years and over from 22 cohorts we identify 15 loci associated with muscle weakness (European Working Group on Sarcopenia in Older People definition: n = 48,596 cases, 18.9% of total), including 12 loci not implicated in previous analyses of continuous measures of grip strength. Loci include genes reportedly involved in autoimmune disease (HLA-DQA1 p = 4 × 10), arthritis (GDF5 p = 4 × 10), cell cycle control and cancer protection, regulation of transcription, and others involved in the development and maintenance of the musculoskeletal system. Using Mendelian randomization we report possible overlapping causal pathways, including diabetes susceptibility, haematological parameters, and the immune system. We conclude that muscle weakness in older adults has distinct mechanisms from continuous strength, including several pathways considered to be hallmarks of ageing.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Studies; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Growth Differentiation Factor 5; HLA-DQ alpha-Chains; Humans; Male; Middle Aged; Muscle Strength; Muscle Weakness; Polymorphism, Single Nucleotide; Sarcopenia

Genomic analysis and preclinical xenograft model development identify potential therapeutic targets for MYOD1-mutant soft-tissue sarcoma of childhood. - Ting, Michelle A; Reuther, Jacquelyn; Chandramohan, Raghu; Voicu, Horatiu; Gandhi, Ilavarasi; Liu, Meng; Cortes-Santiago, Nahir; Foster, Jennifer H; Hicks, John; Nuchtern, Jed; Scollon, Sarah; Plon, Sharon E; et al. (J Pathol, 2021)
The myogenic differentiation 1 gene (MYOD1) p.L122R somatic mutation was first discovered in a subset of clinically aggressive embryonal rhabdomyosarcomas and has since been described in both pediatric and adult spindle cell/sclerosing rhabdomyosarcomas. Relatively little is known about the clinical, molecular, and histopathological features of these tumors in children. In order to further characterize the genomic and clinical features of pediatric MYOD1-mutant sarcomas, we evaluated a cohort of soft-tissue sarcoma patients treated at Texas Children's Hospital. Tumor DNA was subjected to next-generation panel sequencing and/or Sanger sequencing of the MYOD1 hotspot mutation. The MYOD1 p.L122R mutation was identified in six tumors, with a variant allele fraction greater than 0.8 in three cases, suggestive of loss of heterozygosity. One sclerosing rhabdomyosarcoma lacking the MYOD1 hotspot mutation was observed to have a MYOD1 copy number gain, also with evidence of loss of heterozygosity. Cancer gene panel sequencing revealed potentially targetable alterations in six of seven (86%) patients with MYOD1 alterations, including four patients with an alteration in the PI3K-AKT pathway: two hotspot PIK3CA mutations and deletions in PTEN and TSC2. On histopathologic review, MYOD1-altered tumors exhibited spindle and/or round cells and varying degrees of hyaline sclerosis. At last follow-up, six patients had died of disease and the seventh progressed early and was subsequently lost to follow-up. Both pre- and post-therapy patient-derived xenograft models were generated from one patient's tumor. These models were confirmed to harbor the MYOD1 and PIK3CA mutations seen in the primary tumor and were shown to be sensitive to PI3K/mTOR inhibition in vitro and in vivo. In conclusion, this study adds to recent reports describing the clinicopathologic and genomic features of MYOD1-altered soft-tissue sarcomas in children, including dismal prognosis and potential molecular targets for therapy. The novel preclinical models developed will facilitate further biological and preclinical study of this rare and aggressive tumor. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
Keywords: Adolescent; Animals; Antineoplastic Agents; Child; Female; Genomics; Humans; Imidazoles; Male; Mice; Mutation; MyoD Protein; Quinolines; Rhabdomyosarcoma; Soft Tissue Neoplasms; Xenograft Model Antitumor Assays; Young Adult

High prevalence of multilocus pathogenic variation in neurodevelopmental disorders in the Turkish population. - Mitani, Tadahiro; Isikay, Sedat; Gezdirici, Alper; Gulec, Elif Yilmaz; Punetha, Jaya; Fatih, Jawid M; Herman, Isabella; Akay, Gulsen; Du, Haowei; Calame, Daniel G; Ayaz, Akif; Tos, Tulay; et al. (Am J Hum Genet, 2021)
Neurodevelopmental disorders (NDDs) are clinically and genetically heterogenous; many such disorders are secondary to perturbation in brain development and/or function. The prevalence of NDDs is > 3%, resulting in significant sociocultural and economic challenges to society. With recent advances in family-based genomics, rare-variant analyses, and further exploration of the Clan Genomics hypothesis, there has been a logarithmic explosion in neurogenetic "disease-associated genes" molecular etiology and biology of NDDs; however, the majority of NDDs remain molecularly undiagnosed. We applied genome-wide screening technologies, including exome sequencing (ES) and whole-genome sequencing (WGS), to identify the molecular etiology of 234 newly enrolled subjects and 20 previously unsolved Turkish NDD families. In 176 of the 234 studied families (75.2%), a plausible and genetically parsimonious molecular etiology was identified. Out of 176 solved families, deleterious variants were identified in 218 distinct genes, further documenting the enormous genetic heterogeneity and diverse perturbations in human biology underlying NDDs. We propose 86 candidate disease-trait-associated genes for an NDD phenotype. Importantly, on the basis of objective and internally established variant prioritization criteria, we identified 51 families (51/176 = 28.9%) with multilocus pathogenic variation (MPV), mostly driven by runs of homozygosity (ROHs) - reflecting genomic segments/haplotypes that are identical-by-descent. Furthermore, with the use of additional bioinformatic tools and expansion of ES to additional family members, we established a molecular diagnosis in 5 out of 20 families (25%) who remained undiagnosed in our previously studied NDD cohort emanating from Turkey.
Keywords: Adolescent; Adult; Child; Child, Preschool; Cohort Studies; Exome Sequencing; Female; Genomics; Humans; Infant; Infant, Newborn; Male; Middle Aged; Mutation; Neurodevelopmental Disorders; Pedigree; Phenotype; Prevalence; Turkey; Young Adult

IFIH1 loss-of-function variants contribute to very early-onset inflammatory bowel disease. - Cananzi, Mara; Wohler, Elizabeth; Marzollo, Antonio; Colavito, Davide; You, Jing; Jing, Huie; Bresolin, Silvia; Gaio, Paola; Martin, Renan; Mescoli, Claudia; Bade, Sangeeta; Posey, Jennifer E; et al. (Hum Genet, 2021)
Genetic defects of innate immunity impairing intestinal bacterial sensing are linked to the development of Inflammatory Bowel Disease (IBD). Although much evidence supports a role of the intestinal virome in gut homeostasis, most studies focus on intestinal viral composition rather than on host intestinal viral sensitivity. To demonstrate the association between the development of Very Early Onset IBD (VEOIBD) and variants in the IFIH1 gene which encodes MDA5, a key cytosolic sensor for viral nucleic acids. Whole exome sequencing (WES) was performed in two independent cohorts of children with VEOIBD enrolled in Italy (n = 18) and USA (n = 24). Luciferase reporter assays were employed to assess MDA5 activity. An enrichment analysis was performed on IFIH1 comparing 42 VEOIBD probands with 1527 unrelated individuals without gastrointestinal or immunological issues. We identified rare, likely loss-of-function (LoF), IFIH1 variants in eight patients with VEOIBD from a combined cohort of 42 children. One subject, carrying a homozygous truncating variant resulting in complete LoF, experienced neonatal-onset, pan-gastrointestinal, IBD-like enteropathy plus multiple infectious episodes. The remaining seven subjects, affected by VEOIBD without immunodeficiency, were carriers of one LoF variant in IFIH1. Among these, two patients also carried a second hypomorphic variant, with partial function apparent when MDA5 was weakly stimulated. Furthermore, IFIH1 variants were significantly enriched in children with VEOIBD as compared to controls (p = 0.007). Complete and partial MDA5 deficiency is associated with VEOIBD with variable penetrance and expressivity, suggesting a role for impaired intestinal viral sensing in IBD pathogenesis.
Keywords: Child, Preschool; Female; Humans; Infant; Inflammatory Bowel Diseases; Interferon-Induced Helicase, IFIH1; Italy; Loss of Function Mutation; Male; Whole Genome Sequencing

Investigation of product-derived lymphoma following infusion of piggyBac-modified CD19 chimeric antigen receptor T cells. - Micklethwaite, Kenneth P; Gowrishankar, Kavitha; Gloss, Brian S; Li, Ziduo; Street, Janine A; Moezzi, Leili; Mach, Melanie A; Sutrave, Gaurav; Clancy, Leighton E; Bishop, David C; Louie, Raymond H Y; Cai, Curtis; et al. (Blood, 2021)
We performed a phase 1 clinical trial to evaluate outcomes in patients receiving donor-derived CD19-specific chimeric antigen receptor (CAR) T cells for B-cell malignancy that relapsed or persisted after matched related allogeneic hemopoietic stem cell transplant. To overcome the cost and transgene-capacity limitations of traditional viral vectors, CAR T cells were produced using the piggyBac transposon system of genetic modification. Following CAR T-cell infusion, 1 patient developed a gradually enlarging retroperitoneal tumor due to a CAR-expressing CD4+ T-cell lymphoma. Screening of other patients led to the detection, in an asymptomatic patient, of a second CAR T-cell tumor in thoracic para-aortic lymph nodes. Analysis of the first lymphoma showed a high transgene copy number, but no insertion into typical oncogenes. There were also structural changes such as altered genomic copy number and point mutations unrelated to the insertion sites. Transcriptome analysis showed transgene promoter-driven upregulation of transcription of surrounding regions despite insulator sequences surrounding the transgene. However, marked global changes in transcription predominantly correlated with gene copy number rather than insertion sites. In both patients, the CAR T-cell-derived lymphoma progressed and 1 patient died. We describe the first 2 cases of malignant lymphoma derived from CAR gene-modified T cells. Although CAR T cells have an enviable record of safety to date, our results emphasize the need for caution and regular follow-up of CAR T recipients, especially when novel methods of gene transfer are used to create genetically modified immune therapies. This trial was registered at www.anzctr.org.au as ACTRN12617001579381.
Keywords: Aged; DNA Transposable Elements; Gene Expression Regulation, Neoplastic; Gene Transfer Techniques; Humans; Immunotherapy, Adoptive; Leukemia, B-Cell; Lymphoma; Lymphoma, B-Cell; Male; Receptors, Antigen, T-Cell; T-Lymphocytes; Transcriptome; Transgenes

Loss of C2orf69 defines a fatal autoinflammatory syndrome in humans and zebrafish that evokes a glycogen-storage-associated mitochondriopathy. - Wong, Hui Hui; Seet, Sze Hwee; Maier, Michael; Gurel, Ayse; Traspas, Ricardo Moreno; Lee, Cheryl; Zhang, Shan; Talim, Beril; Loh, Abigail Y T; Chia, Crystal Y; Teoh, Tze Shin; Sng, Danielle; et al. (Am J Hum Genet, 2021)
Human C2orf69 is an evolutionarily conserved gene whose function is unknown. Here, we report eight unrelated families from which 20 children presented with a fatal syndrome consisting of severe autoinflammation and progredient leukoencephalopathy with recurrent seizures; 12 of these subjects, whose DNA was available, segregated homozygous loss-of-function C2orf69 variants. C2ORF69 bears homology to esterase enzymes, and orthologs can be found in most eukaryotic genomes, including that of unicellular phytoplankton. We found that endogenous C2ORF69 (1) is loosely bound to mitochondria, (2) affects mitochondrial membrane potential and oxidative respiration in cultured neurons, and (3) controls the levels of the glycogen branching enzyme 1 (GBE1) consistent with a glycogen-storage-associated mitochondriopathy. We show that CRISPR-Cas9-mediated inactivation of zebrafish C2orf69 results in lethality by 8 months of age due to spontaneous epileptic seizures, which is preceded by persistent brain inflammation. Collectively, our results delineate an autoinflammatory Mendelian disorder of C2orf69 deficiency that disrupts the development/homeostasis of the immune and central nervous systems.
Keywords: Animals; Biological Evolution; Cell Line; CRISPR-Cas Systems; Encephalitis; Female; Genes, Recessive; Glycogen; Humans; Inflammation; Male; Membrane Proteins; Mitochondrial Diseases; Pedigree; Seizures; Zebrafish

Mass-spectrometry-based proteomic correlates of grade and stage reveal pathways and kinases associated with aggressive human cancers. - Monsivais, Diana; Vasquez, Yasmin M; Chen, Fengju; Zhang, Yiqun; Chandrashekar, Darshan S; Faver, John C; Masand, Ramya P; Scheurer, Michael E; Varambally, Sooryanarayana; Matzuk, Martin M; Creighton, Chad J (Oncogene, 2021)
Proteomic signatures associated with clinical measures of more aggressive cancers could yield molecular clues as to disease drivers. Here, utilizing the Clinical Proteomic Tumor Analysis Consortium (CPTAC) mass-spectrometry-based proteomics datasets, we defined differentially expressed proteins and mRNAs associated with higher grade or higher stage, for each of seven cancer types (breast, colon, lung adenocarcinoma, clear cell renal, ovarian, uterine, and pediatric glioma), representing 794 patients. Widespread differential patterns of total proteins and phosphoproteins involved some common patterns shared between different cancer types. More proteins were associated with higher grade than higher stage. Most proteomic signatures predicted patient survival in independent transcriptomic datasets. The proteomic grade signatures, in particular, involved DNA copy number alterations. Pathways of interest were enriched within the grade-associated proteins across multiple cancer types, including pathways of altered metabolism, Warburg-like effects, and translation factors. Proteomic grade correlations identified protein kinases having functional impact in vitro in uterine endometrial cancer cells, including MAP3K2, MASTL, and TTK. The protein-level grade and stage associations for all proteins profiled-along with corresponding information on phosphorylation, pathways, mRNA expression, and copy alterations-represent a resource for identifying new potential targets. Proteomic analyses are often concordant with corresponding transcriptomic analyses, but with notable exceptions.
Keywords: Cell Cycle Proteins; Female; Gene Expression Regulation, Neoplastic; Humans; Male; MAP Kinase Kinase Kinase 2; Microtubule-Associated Proteins; Neoplasm Grading; Neoplasm Staging; Neoplasms; Phosphoproteins; Phosphotransferases; Protein Serine-Threonine Kinases; Protein-Tyrosine Kinases; Proteomics; Transcriptome

Molecular Features of Cancers Exhibiting Exceptional Responses to Treatment. - David A Wheeler; Takebe, Naoko; Hinoue, Toshinori; Hoadley, Katherine A; Cardenas, Maria F; Hamilton, Alina M; Laird, Peter W; Wang, Linghua; Johnson, Adrienne; Dewal, Ninad; Miller, Vincent; Piñeyro, David; et al. (Cancer Cell, 2021)
A small fraction of cancer patients with advanced disease survive significantly longer than patients with clinically comparable tumors. Molecular mechanisms for exceptional responses to therapy have been identified by genomic analysis of tumor biopsies from individual patients. Here, we analyzed tumor biopsies from an unbiased cohort of 111 exceptional responder patients using multiple platforms to profile genetic and epigenetic aberrations as well as the tumor microenvironment. Integrative analysis uncovered plausible mechanisms for the therapeutic response in nearly a quarter of the patients. The mechanisms were assigned to four broad categories-DNA damage response, intracellular signaling, immune engagement, and genetic alterations characteristic of favorable prognosis-with many tumors falling into multiple categories. These analyses revealed synthetic lethal relationships that may be exploited therapeutically and rare genetic lesions that favor therapeutic success, while also providing a wealth of testable hypotheses regarding oncogenic mechanisms that may influence the response to cancer therapy.
Keywords: Antineoplastic Agents; Biopsy; Epigenesis, Genetic; Female; Gene Regulatory Networks; Genetic Variation; Genomics; Humans; Male; Neoplasms; Prognosis; Survival Analysis; Treatment Outcome; Tumor Microenvironment

Neurodevelopmental disorder in an Egyptian family with a biallelic ALKBH8 variant. - Saad, Ahmed K; Marafi, Dana; Mitani, Tadahiro; Du, Haowei; Rafat, Karima; Fatih, Jawid M; Jhangiani, Shalini N; Coban-Akdemir, Zeynep; Richard A Gibbs; Pehlivan, Davut; Hunter, Jill V; Posey, Jennifer E; et al. (Am J Med Genet A, 2021)
Alkylated DNA repair protein AlkB homolog 8 (ALKBH8) is a member of the AlkB family of dioxygenases. ALKBH8 is a methyltransferase of the highly variable wobble nucleoside position in the anticodon loop of tRNA and thus plays a critical role in tRNA modification by preserving codon recognition and preventing errors in amino acid incorporation during translation. Moreover, its activity catalyzes uridine modifications that are proposed to be critical for accurate protein translation. Previously, two distinct homozygous truncating variants in the final exon of ALKBH8 were described in two unrelated large Saudi Arabian kindreds with intellectual developmental disorder and autosomal recessive 71 (MRT71) syndrome (MIM# 618504). Here, we report a third family-of Egyptian descent-harboring a novel homozygous frame-shift variant in the last exon of ALKBH8. Two affected siblings in this family exhibit global developmental delay and intellectual disability as shared characteristic features of MRT71 syndrome, and we further characterize their observed dysmorphic features and brain MRI findings. This description of a third family with a truncating ALKBH8 variant from a distinct population broadens the phenotypic and genotypic spectrum of MRT71 syndrome, affirms that perturbations in tRNA biogenesis can contribute to neurogenetic disease traits, and firmly establishes ALKBH8 as a novel neurodevelopmental disease gene.
Keywords: Adolescent; AlkB Homolog 8, tRNA Methyltransferase; Brain; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Humans; Infant; Magnetic Resonance Imaging; Male; Neurodevelopmental Disorders; Pedigree

NMIHBA results from hypomorphic PRUNE1 variants that lack short-chain exopolyphosphatase activity. - Nistala, Harikiran; Dronzek, John; Gonzaga-Jauregui, Claudia; Chim, Shek Man; Rajamani, Saathyaki; Nuwayhid, Samer; Delgado, Dennis; Burke, Elizabeth; Karaca, Ender; Franklin, Matthew C; Sarangapani, Prasad; Podgorski, Michael; et al. (Hum Mol Genet, 2021)
Neurodevelopmental disorder with microcephaly, hypotonia and variable brain anomalies (NMIHBA) is an autosomal recessive neurodevelopmental and neurodegenerative disorder characterized by global developmental delay and severe intellectual disability. Microcephaly, progressive cortical atrophy, cerebellar hypoplasia and delayed myelination are neurological hallmarks in affected individuals. NMIHBA is caused by biallelic variants in PRUNE1 encoding prune exopolyphosphatase 1. We provide in-depth clinical description of two affected siblings harboring compound heterozygous variant alleles, c.383G > A (p.Arg128Gln), c.520G > T (p.Gly174*) in PRUNE1. To gain insights into disease biology, we biochemically characterized missense variants within the conserved N-terminal aspartic acid-histidine-histidine (DHH) motif and provide evidence that they result in the destabilization of protein structure and/or loss of exopolyphosphatase activity. Genetic ablation of Prune1 results in midgestational lethality in mice, associated with perturbations to embryonic growth and vascular development. Our findings suggest that NMIHBA results from hypomorphic variant alleles in humans and underscore the potential key role of PRUNE1 exopolyphoshatase activity in neurodevelopment.
Keywords: Acid Anhydride Hydrolases; Alleles; Animals; Child, Preschool; Female; Humans; Infant; Intellectual Disability; Male; Mice; Microcephaly; Muscle Hypotonia; Mutation; Neurodevelopmental Disorders; Pedigree; Phenotype; Phosphoric Monoester Hydrolases

Noncoding mutation in contributes to inherited retinal degenerations. - Zou, Gang; Zhang, Tao; Cheng, Xuesen; Igelman, Austin D; Wang, Jun; Qian, Xinye; Fu, Shangyi; Wang, Keqing; Koenekoop, Robert K; Fishman, Gerald A; Yang, Paul; Yumei Li; et al. (Mol Vis, 2021)
PURPOSE: Despite the extensive use of next-generation sequencing (NGS) technology to identify disease-causing genomic variations, a major gap in our understanding of Mendelian diseases is the unidentified molecular lesion in a significant portion of patients. For inherited retinal degenerations (IRDs), although currently close to 300 disease-associated genes have been identified, the mutations in approximately one-third of patients remain unknown. With mounting evidence that noncoding mutations might contribute significantly to disease burden, we aimed to systematically investigate the contributions of noncoding regions in the genome to IRDs. METHODS: In this study, we focused on , which has been linked to various IRD phenotypes, including Leber congenital amaurosis (LCA), retinitis pigmentosa (RP), and macular dystrophy (MD). As several noncoding mutant alleles have been reported in and we observed that the mutation carrier frequency of is higher in patient cohorts with unsolved IRDs, we hypothesized that mutations in the noncoding regions of might be a significant contributor to pathogenicity. To test this hypothesis, we performed whole-genome sequencing (WGS) for 25 patients with unassigned IRD who carry a single mutation in . RESULTS: Three noncoding variants in , including a 2,890 bp deletion and two deep-intronic variants (c.2710+233G>A and c.1468-263G>C), were identified as putative second hits of in three patients with LCA. The mutant alleles were validated with direct sequencing or in vitro assays. CONCLUSIONS: The results highlight the significance of the contribution of noncoding pathogenic variants to unsolved IRD cases.
Keywords: Adult; Alleles; Child, Preschool; Cloning, Molecular; Cytoskeletal Proteins; Electroretinography; Female; Humans; Male; Mutation; Phenotype; Real-Time Polymerase Chain Reaction; Retina; Retinal Degeneration; RNA, Untranslated; Tomography, Optical Coherence; Transfection; Visual Acuity; Whole Genome Sequencing

Novel Anaplastic Thyroid Cancer PDXs and Cell Lines: Expanding Preclinical Models of Genetic Diversity. - Maniakas, Anastasios; Henderson, Ying C; Hei, Hu; Peng, Shaohua; Chen, Yunyun; Jiang, Yujie; Ji, Shuangxi; Cardenas, Maria; Chiu, Yulun; Bell, Diana; Williams, Michelle D; Hofmann, Marie-Claude; et al. (J Clin Endocrinol Metab, 2021)
CONTEXT: Anaplastic thyroid cancer (ATC) is a rare, aggressive, and deadly disease. Robust preclinical thyroid cancer models are needed to adequately develop and study novel therapeutic agents. Patient-derived xenograft (PDX) models may resemble patient tumors by recapitulating key genetic alterations and gene expression patterns, making them excellent preclinical models for drug response evaluation. OBJECTIVE: We developed distinct ATC PDX models concurrently with cell lines and characterized them in vitro and in vivo. METHODS: Fresh thyroid tumor from patients with a preoperative diagnosis of ATC was surgically collected and divided for concurrent cell line and PDX model development. Cell lines were created by generating single cells through enzymatic digestion. PDX models were developed following direct subcutaneous implantation of fresh tumor on the flank of immune compromised/athymic mice. RESULTS: Six ATC PDX models and 4 cell lines were developed with distinct genetic profiles. Mutational characterization showed one BRAF/TP53/CDKN2A, one BRAF/CDKN2A, one BRAF/TP53, one TP53 only, one TERT-promoter/HRAS, and one TERT-promoter/KRAS/TP53/NF2/NFE2L2 mutated phenotype. Hematoxylin-eosin staining comparing the PDX models to the original patient surgical specimens show remarkable resemblance, while immunohistochemistry stains for important biomarkers were in full concordance (cytokeratin, TTF-1, PAX8, BRAF). Short tandem repeats DNA fingerprinting analysis of all PDX models and cell lines showed strong concordance with the original tumor. PDX successful establishment rate was 32%. CONCLUSION: We have developed and characterized 6 novel ATC PDX models with 4 matching cell lines. Each PDX model harbors a distinct genetic profile, making them excellent tools for preclinical therapeutic trials.
Keywords: Aged; Animals; Apoptosis; Biomarkers, Tumor; Cell Proliferation; Disease Models, Animal; Female; Gene Expression Regulation, Neoplastic; Humans; Male; Mice; Middle Aged; Phenotype; Prognosis; Survival Rate; Thyroid Carcinoma, Anaplastic; Thyroid Neoplasms; Tumor Cells, Cultured; Xenograft Model Antitumor Assays

A novel homozygous SLC13A5 whole-gene deletion generated by Alu/Alu-mediated rearrangement in an Iraqi family with epileptic encephalopathy. - Duan, Ruizhi; Saadi, Nebal Waill; Grochowski, Christopher M; Bhadila, Ghalia; Faridoun, Afnan; Mitani, Tadahiro; Du, Haowei; Fatih, Jawid M; Jhangiani, Shalini N; Akdemir, Zeynep C; Richard A Gibbs; Pehlivan, Davut; et al. (Am J Med Genet A, 2021)
Biallelic loss-of-function (LoF) of SLC13A5 (solute carrier family 13, member 5) induced deficiency in sodium/citrate transporter (NaCT) causes autosomal recessive developmental epileptic encephalopathy 25 with hypoplastic amelogenesis imperfecta (DEE25; MIM #615905). Many pathogenic SLC13A5 single nucleotide variants (SNVs) and small indels have been described; however, no cases with copy number variants (CNVs) have been sufficiently investigated. We describe a consanguineous Iraqi family harboring an 88.5 kb homozygous deletion including SLC13A5 in Chr17p13.1. The three affected male siblings exhibit neonatal-onset epilepsy with fever-sensitivity, recurrent status epilepticus, global developmental delay/intellectual disability (GDD/ID), and other variable neurological findings as shared phenotypical features of DEE25. Two of the three affected subjects exhibit hypoplastic amelogenesis imperfecta (AI), while the proband shows no evidence of dental abnormalities or AI at 2 years of age with apparently unaffected primary dentition. Characterization of the genomic architecture at this locus revealed evidence for genomic instability generated by an Alu/Alu-mediated rearrangement; confirmed by break-point junction Sanger sequencing. This multiplex family from a distinct population elucidates the phenotypic consequence of complete LoF of SLC13A5 and illustrates the importance of read-depth-based CNV detection in comprehensive exome sequencing analysis to solve cases that otherwise remain molecularly unsolved.
Keywords: Alu Elements; Child, Preschool; Chromosomes, Human, Pair 17; DNA Copy Number Variations; Epilepsy, Generalized; Exome Sequencing; Female; Homozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Pedigree; Sequence Deletion; Symporters

Novel pathogenic genomic variants leading to autosomal dominant and recessive Robinow syndrome. - Zhang, Chaofan; Mazzeu, Juliana F; Eisfeldt, Jesper; Grochowski, Christopher M; White, Janson; Akdemir, Zeynep C; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; Lindstrand, Anna; James R Lupski; Sutton, V Reid; et al. (Am J Med Genet A, 2021)
Robinow syndrome (RS) is a genetically heterogeneous disorder characterized by skeletal dysplasia and a distinctive facial appearance. Previous studies have revealed locus heterogeneity with rare variants in DVL1, DVL3, FZD2, NXN, ROR2, and WNT5A underlying the etiology of RS. The aforementioned "Robinow-associated genes" and their gene products all play a role in the WNT/planar cell polarity signaling pathway. We performed gene-targeted Sanger sequencing, exome sequencing, genome sequencing, and array comparative genomic hybridization on four subjects with a clinical diagnosis of RS who had not had prior DNA testing. Individuals in our cohort were found to carry pathogenic or likely pathogenic variants in three RS related genes: DVL1, ROR2, and NXN. One subject was found to have a nonsense variant (c.817C > T [p.Gln273*]) in NXN in trans with an ~1 Mb telomeric deletion on chromosome 17p containing NXN, which supports our contention that biallelic NXN variant alleles are responsible for a novel autosomal recessive RS locus. These findings provide increased understanding of the role of WNT signaling in skeletal development and maintenance. These data further support the hypothesis that dysregulation of the noncanonical WNT pathway in humans gives rise to RS.
Keywords: Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; Craniofacial Abnormalities; Dishevelled Proteins; Dwarfism; Exome Sequencing; Female; Genes, Dominant; Genes, Recessive; Genetic Heterogeneity; Genetic Predisposition to Disease; Genomic Structural Variation; Humans; Limb Deformities, Congenital; Male; Oxidoreductases; Receptor Tyrosine Kinase-like Orphan Receptors; Urogenital Abnormalities; Whole Genome Sequencing; Wnt Signaling Pathway

Origins and Long-Term Patterns of Copy-Number Variation in Rhesus Macaques. - Thomas, Gregg W C; Wang, Richard J; Nguyen, Jelena; R. Alan Harris; Raveendran, Muthuswamy; Jeffrey Rogers; Hahn, Matthew W (Mol Biol Evol, 2021)
Mutations play a key role in the development of disease in an individual and the evolution of traits within species. Recent work in humans and other primates has clarified the origins and patterns of single-nucleotide variants, showing that most arise in the father's germline during spermatogenesis. It remains unknown whether larger mutations, such as deletions and duplications of hundreds or thousands of nucleotides, follow similar patterns. Such mutations lead to copy-number variation (CNV) within and between species, and can have profound effects by deleting or duplicating genes. Here, we analyze patterns of CNV mutations in 32 rhesus macaque individuals from 14 parent-offspring trios. We find the rate of CNV mutations per generation is low (less than one per genome) and we observe no correlation between parental age and the number of CNVs that are passed on to offspring. We also examine segregating CNVs within the rhesus macaque sample and compare them to a similar data set from humans, finding that both species have far more segregating deletions than duplications. We contrast this with long-term patterns of gene copy-number evolution between 17 mammals, where the proportion of deletions that become fixed along the macaque lineage is much smaller than the proportion of segregating deletions. These results suggest purifying selection acting on deletions, such that the majority of them are removed from the population over time. Rhesus macaques are an important biomedical model organism, so these results will aid in our understanding of this species and the disease models it supports.
Keywords: Animals; DNA Copy Number Variations; Female; Gene Duplication; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Male; Mutation; Selection, Genetic; Sequence Deletion; Whole Genome Sequencing

Pedigree reconstruction and distant pairwise relatedness estimation from genome sequence data: A demonstration in a population of rhesus macaques (Macaca mulatta). - Petty, Lauren E; Phillippi-Falkenstein, Kathrine; Kubisch, H Michael; Raveendran, Muthuswamy; R. Alan Harris; Vallender, Eric J; Huff, Chad D; Bohm, Rudolf P; Jeffrey Rogers; Below, Jennifer E (Mol Ecol Resour, 2021)
A primary challenge in the analysis of free-ranging animal populations is the accurate estimation of relatedness among individuals. Many aspects of population analysis rely on knowledge of relatedness patterns, including socioecology, demography, heritability and gene mapping analyses, wildlife conservation and the management of breeding colonies. Methods for determining relatedness using genome-wide data have improved our ability to determine kinship and reconstruct pedigrees in humans. However, methods for reconstructing complex pedigree structures and estimating distant relatedness (beyond third-degree) have not been widely applied to other species. We sequenced the genomes of 150 male rhesus macaques from the Tulane National Primate Research Center colony to estimate pairwise relatedness, reconstruct closely related pedigrees, estimate more distant relationships and augment colony records. Methods for determining relatedness developed for human genetic data were applied and evaluated in the analysis of nonhuman primates, including identity-by-descent-based methods for pedigree reconstruction and shared segment-based inference of more distant relatedness. We compared the genotype-based pedigrees and estimated relationships to available colony pedigree records and found high concordance (95.5% agreement) between expected and identified relationships for close relatives. In addition, we detected distant relationships not captured in colony records, including some as distant as twelfth-degree. Furthermore, while deep sequence coverage is preferable, we show that this approach can also provide valuable information when only low-coverage (5×) sequence data is available. Our findings demonstrate the value of these methods for determination of relatedness in various animal populations, with diverse applications to conservation biology, evolutionary and ecological research and biomedical studies.
Keywords: Animals; Breeding; Chromosome Mapping; Genetics, Population; Genome; Genotype; Macaca mulatta; Male; Pedigree; Polymorphism, Single Nucleotide

Primary Infection May Be an Underlying Factor Contributing to Lethal Hemorrhagic Disease Caused by Elephant Endotheliotropic Herpesvirus 3 in African Elephants (). - Pursell, Taylor; Spencer Clinton, Jennifer L; Tan, Jie; Peng, Rongsheng; Xiang Qin; Harshavardhan Doddapaneni; Menon, Vipin; Momin, Zeineen; Kottapalli, Kavya; Howard, Lauren; Latimer, Erin; Heaggans, Sarah; et al. (Microbiol Spectr, 2021)
Distinct but related species of elephant endotheliotropic herpesviruses (EEHVs) circulate within Asian and African elephant populations. Primary infection with EEHVs endemic among Asian elephants can cause clinical illness and lethal EEHV hemorrhagic disease (EEHV-HD). The degree to which this occurs among African elephants has not been fully established. Recent cases of EEHV-HD caused by the EEHV3 species in African elephants housed in North American zoos has heightened concern about the susceptibility of this elephant species to EEHV-HD. In this study, we utilize the luciferase immunoprecipitation system (LIPS) to generate a serological assay specific for EEHV3 in African elephants by detecting antibodies against the EEHV3 E34 protein. The results showed that the majority of tested elephants from four separate and genetically unrelated herds, including five elephants that survived clinical illness associated with EEHV3, were positive for prior infection with EEHV3. However, African elephants who succumbed to EEHV3-HD were seronegative for EEHV3 prior to lethal infection. This supports the hypothesis that fatal EEHV-HD caused by EEHV3 is associated with primary infection rather than reactivation of latent virus. Lastly, we observed that African elephants, like Asian elephants, acquire abundant anti-EEHV antibodies prenatally and that anti-EEHV3 specific antibodies were either never detected or declined to undetectable levels in those animals that died from lethal disease following EEHV3 infection. Prior to 2019, only five cases of clinical disease from EEHV infection among African elephants had been documented. Since 2019, there have been at least seven EEHV-HD cases in North American zoos, resulting in three fatalities, all associated with EEHV3. Evidence is accumulating to suggest that EEHV-associated clinical illness and death among Asian elephants is due to primary infection and may be associated with waning anti-EEHV antibody levels in young elephants. The development of the EEHV3 serological test described in this study enabled us to confirm that similar dynamics may be contributing to EEHV-HD in African elephants. The ability to screen for EEHV immune status in African elephant calves will have a major impact on managing captive African elephant herds and will provide new tools for investigating and understanding EEHV in wild populations.
Keywords: Animals; Animals, Zoo; Antibodies, Viral; Elephants; Female; Hemorrhagic Disorders; Herpesvirus 3, Equid; Male; Serologic Tests; Viral Zoonoses

Prostate adenocarcinoma and COVID-19: The possible impacts of TMPRSS2 expressions in susceptibility to SARS-CoV-2. - Cheng, Jingliang; Zhou, Ju; Fu, Shangyi; Fu, Jiewen; Zhou, Baixu; Chen, Hanchun; Fu, Junjiang; Wei, Chunli (J Cell Mol Med, 2021)
TMPRSS2 (OMIM: 602060) is a cellular protease involved in many physiological and pathological processes, and it facilitates entry of viruses such as SARS-CoV-2 into host cells. It is important to predict the prostate's susceptibility to SARS-CoV-2 infection in cancer patients and the disease outcome by assessing TMPRSS2 expression in cancer tissues. In this study, we conducted the expression profiles of the TMPRSS2 gene for COVID-19 in different normal tissues and PRAD (prostate adenocarcinoma) tumour tissues. TMPRSS2 is highly expressed in normal tissues including the small intestine, prostate, pancreas, salivary gland, colon, stomach, seminal vesicle and lung, and is increased in PRAD tissues, indicating that SARS-CoV-2 might attack not only the lungs and other normal organs, but also in PRAD cancer tissues. Hypomethylation of TMPRSS2 promoter may not be the mechanism for TMPRSS2 overexpression in PRAD tissues and PRAD pathogenesis. TMPRSS2 expresses eleven isoforms in PRAD tissues, with the TMPRSS2-001 isoform expressed highest and followed by TMPRSS2-201. Further isoform structures prediction showed that these two highly expressed isoforms have both SRCR_2 and Trypsin (Tryp_SPc) domains, which may be essential for TMPRSS2 functional roles for tumorigenesis and entry for SARS-CoV-2 in PRAD patients. Analyses of functional annotation and enrichment in TMPRSS2 showed that TMPRSS2 is mostly enriched in regulation of viral entry into host cells, protein processing and serine-type peptidase activity. TMPRSS2 is also associated with prostate gland cancer cell expression, different complex(es) formation, human influenza and carcinoma, pathways in prostate cancer, influenza A, and transcriptional misregulation in cancer. Altogether, even though high expression of TMPRSS2 may not be favourable for PRAD patient's survival, increased expression in these patients should play roles in susceptibility of the SARS-CoV-2 infection and clinical severity for COVID-19, highlighting the value of protective actions of PRAD cases by targeting or androgen-mediated therapeutic strategies in the COVID-19 pandemic.
Keywords: Adenocarcinoma; COVID-19; DNA Methylation; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Gene Ontology; Genetic Predisposition to Disease; Humans; Kaplan-Meier Estimate; Male; Promoter Regions, Genetic; Prostate; Prostatic Neoplasms; SARS-CoV-2; Serine Endopeptidases

Proteins Associated with Risk of Kidney Function Decline in the General Population. - Grams, Morgan E; Surapaneni, Aditya; Chen, Jingsha; Zhou, Linda; Yu, Zhi; Dutta, Diptavo; Welling, Paul A; Chatterjee, Nilanjan; Zhang, Jingning; Arking, Dan E; Chen, Teresa K; Rebholz, Casey M; et al. (J Am Soc Nephrol, 2021)
BACKGROUND: Proteomic profiling may allow identification of plasma proteins that associate with subsequent changesin kidney function, elucidating biologic processes underlying the development and progression of CKD. METHODS: We quantified the association between 4877 plasma proteins and a composite outcome of ESKD or decline in eGFR by ≥50% among 9406 participants in the Atherosclerosis Risk in Communities (ARIC) Study (visit 3; mean age, 60 years) who were followed for a median of 14.4 years. We performed separate analyses for these proteins in a subset of 4378 participants (visit 5), who were followed at a later time point, for a median of 4.4 years. For validation, we evaluated proteins with significant associations (false discovery rate <5%) in both time periods in 3249 participants in the Chronic Renal Insufficiency Cohort (CRIC) and 703 participants in the African American Study of Kidney Disease and Hypertension (AASK). We also compared the genetic determinants of protein levels with those from a meta-analysis genome-wide association study of eGFR. RESULTS: In models adjusted for multiple covariates, including baseline eGFR and albuminuria, we identified 13 distinct proteins that were significantly associated with the composite end point in both time periods, including TNF receptor superfamily members 1A and 1B, trefoil factor 3, and -trace protein. Of these proteins, 12 were also significantly associated in CRIC, and nine were significantly associated in AASK. Higher levels of each protein associated with higher risk of 50% eGFR decline or ESKD. We found genetic evidence for a causal role for one protein, lectin mannose-binding 2 protein (LMAN2). CONCLUSIONS: Large-scale proteomic analysis identified both known and novel proteomic risk factors for eGFR decline.
Keywords: Age Factors; Aged; Cohort Studies; Female; Glomerular Filtration Rate; Humans; Male; Middle Aged; Proteomics; Renal Insufficiency, Chronic; Risk Factors

RCL1 copy number variants are associated with a range of neuropsychiatric phenotypes. - Brownstein, Catherine A; Smith, Richard S; Rodan, Lance H; Gorman, Mark P; Hojlo, Margaret A; Garvey, Emily A; Li, Jianqiao; Cabral, Kristin; Bowen, Joshua J; Rao, Abhijit S; Genetti, Casie A; Carroll, Devon; et al. (Mol Psychiatry, 2021)
Mendelian and early-onset severe psychiatric phenotypes often involve genetic variants having a large effect, offering opportunities for genetic discoveries and early therapeutic interventions. Here, the index case is an 18-year-old boy, who at 14 years of age had a decline in cognitive functioning over the course of a year and subsequently presented with catatonia, auditory and visual hallucinations, paranoia, aggression, mood dysregulation, and disorganized thoughts. Exome sequencing revealed a stop-gain mutation in RCL1 (NM_005772.4:c.370 C > T, p.Gln124Ter), encoding an RNA 3'-terminal phosphate cyclase-like protein that is highly conserved across eukaryotic species. Subsequent investigations across two academic medical centers identified eleven additional cases of RCL1 copy number variations (CNVs) with varying neurodevelopmental or psychiatric phenotypes. These findings suggest that dosage variation of RCL1 contributes to a range of neurological and clinical phenotypes.
Keywords: Adolescent; DNA Copy Number Variations; Exome Sequencing; Humans; Male; Mutation; Phenotype

Risk of sudden cardiac death in EXOSC5-related disease. - Calame, Daniel G; Herman, Isabella; Fatih, Jawid M; Du, Haowei; Akay, Gulsen; Jhangiani, Shalini N; Coban-Akdemir, Zeynep; Milewicz, Dianna M; Richard A Gibbs; Posey, Jennifer E; Marafi, Dana; Hunter, Jill V; et al. (Am J Med Genet A, 2021)
The RNA exosome is a multi-subunit complex involved in the processing, degradation, and regulated turnover of RNA. Several subunits are linked to Mendelian disorders, including pontocerebellar hypoplasia (EXOSC3, MIM #614678; EXOSC8, MIM #616081: and EXOSC9, MIM #618065) and short stature, hearing loss, retinitis pigmentosa, and distinctive facies (EXOSC2, MIM #617763). More recently, EXOSC5 (MIM *606492) was found to underlie an autosomal recessive neurodevelopmental disorder characterized by developmental delay, hypotonia, cerebellar abnormalities, and dysmorphic facies. An unusual feature of EXOSC5-related disease is the occurrence of complete heart block requiring a pacemaker in a subset of affected individuals. Here, we provide a detailed clinical and molecular characterization of two siblings with microcephaly, developmental delay, cerebellar volume loss, hypomyelination, with cardiac conduction and rhythm abnormalities including sinus node dysfunction, intraventricular conduction delay, atrioventricular block, and ventricular tachycardia (VT) due to compound heterozygous variants in EXOSC5: (1) NM_020158.4:c.341C > T (p.Thr114Ile; pathogenic, previously reported) and (2) NM_020158.4:c.302C > A (p.Thr101Lys; novel variant). A review of the literature revealed an additional family with biallelic EXOSC5 variants and cardiac conduction abnormalities. These clinical and molecular data provide compelling evidence that cardiac conduction abnormalities and arrhythmias are part of the EXOSC5-related disease spectrum and argue for proactive screening due to potential risk of sudden cardiac death.
Keywords: Antigens, Neoplasm; Atrioventricular Block; Child; Death, Sudden, Cardiac; Echocardiography; Electrocardiography; Exosome Multienzyme Ribonuclease Complex; Facies; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Mutation; Pedigree; Phenotype; RNA-Binding Proteins; Sequence Analysis, DNA; Young Adult

Sequencing of a central nervous system tumor demonstrates cancer transmission in an organ transplant. - Marie-Claude Gingras; Aniko Sabo; Cardenas, Maria; Rana, Abbas; Dhingra, Sadhna; Meng, Qingchang; Jianhong Hu; Donna M Muzny; Harshavardhan Doddapaneni; Perez, Lesette; Korchina, Viktoriya; Nessner, Caitlin; et al. (Life Sci Alliance, 2021)
Four organ transplant recipients from an organ donor diagnosed with anaplastic pleomorphic xanthoastrocytoma developed fatal malignancies for which the origin could not be confirmed by standard methods. We identified the somatic mutational profiles of the neoplasms using next-generation sequencing technologies and tracked the relationship between the different samples. The data were consistent with the presence of an aggressive clonal entity in the donor and the subsequent proliferation of descendent tumors in each recipient. Deleterious mutations in , , , , and , and a chromosomal deletion spanning the genes, were shared between the recipients' lesions. In addition to demonstrating that DNA sequencing tracked a donor/recipient cancer transmission, this study established that the genetic profile of a donor tumor and its potential aggressive phenotype could have been determined before transplantation was considered. As the genetic correlates of tumor invasion and metastases become better known, adding genetic profiling by DNA sequencing to the data considered for transplant safety should be considered.
Keywords: Adolescent; Adult; Biomarkers, Tumor; Biopsy; Central Nervous System Neoplasms; DNA Mutational Analysis; Exome Sequencing; Female; Humans; INDEL Mutation; Male; Middle Aged; Mutation; Organ Transplantation; Prognosis; Sequence Analysis, DNA; Tissue Donors; Transplant Recipients; Transplants; Young Adult

Shotgun transcriptome, spatial omics, and isothermal profiling of SARS-CoV-2 infection reveals unique host responses, viral diversification, and drug interactions. - Butler, Daniel; Mozsary, Christopher; Meydan, Cem; Foox, Jonathan; Rosiene, Joel; Shaiber, Alon; Danko, David; Afshinnekoo, Ebrahim; MacKay, Matthew; Fritz J Sedlazeck; Ivanov, Nikolay A; Sierra, Maria; et al. (Nat Commun, 2021)
In less than nine months, the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) killed over a million people, including >25,000 in New York City (NYC) alone. The COVID-19 pandemic caused by SARS-CoV-2 highlights clinical needs to detect infection, track strain evolution, and identify biomarkers of disease course. To address these challenges, we designed a fast (30-minute) colorimetric test (LAMP) for SARS-CoV-2 infection from naso/oropharyngeal swabs and a large-scale shotgun metatranscriptomics platform (total-RNA-seq) for host, viral, and microbial profiling. We applied these methods to clinical specimens gathered from 669 patients in New York City during the first two months of the outbreak, yielding a broad molecular portrait of the emerging COVID-19 disease. We find significant enrichment of a NYC-distinctive clade of the virus (20C), as well as host responses in interferon, ACE, hematological, and olfaction pathways. In addition, we use 50,821 patient records to find that renin-angiotensin-aldosterone system inhibitors have a protective effect for severe COVID-19 outcomes, unlike similar drugs. Finally, spatial transcriptomic data from COVID-19 patient autopsy tissues reveal distinct ACE2 expression loci, with macrophage and neutrophil infiltration in the lungs. These findings can inform public health and may help develop and drive SARS-CoV-2 diagnostic, prevention, and treatment strategies.
Keywords: Adult; Aged; Angiotensin Receptor Antagonists; Angiotensin-Converting Enzyme Inhibitors; Antiviral Agents; COVID-19; COVID-19 Drug Treatment; COVID-19 Nucleic Acid Testing; Drug Interactions; Female; Gene Expression Profiling; Genome, Viral; HLA Antigens; Host Microbial Interactions; Humans; Male; Middle Aged; Molecular Diagnostic Techniques; New York City; Nucleic Acid Amplification Techniques; Pandemics; RNA-Seq; SARS-CoV-2

Single-Cell Transcriptomics Identifies a Unique Entity and Signature Markers of Transit-Amplifying Cells in Human Corneal Limbus. - Li, Jin-Miao; Kim, Sangbae; Zhang, Yun; Bian, Fang; Hu, Jiaoyue; Lu, Rong; Pflugfelder, Stephen C; Rui Chen; Li, De-Quan (Invest Ophthalmol Vis Sci, 2021)
PURPOSE: Differentiated from adult stem cells (ASCs), transit-amplifying cells (TACs) play an important role in tissue homeostasis, development, and regeneration. This study aimed to characterize the gene expression profile of a candidate TAC population in limbal basal epithelial cells using single-cell RNA sequencing (scRNA-seq). METHODS: Single cells isolated from the basal corneal limbus were subjected to scRNA-seq using the 10x Genomics platform. Cell types were clustered by graph-based visualization methods and unbiased computational analysis. BrdU proliferation assays, immunofluorescent staining, and real-time reverse transcription quantitative polymerase chain reaction were performed using multiple culture models of primary human limbal epithelial cells to characterize the TAC pool. RESULTS: Single-cell transcriptomics of 16,360 limbal basal cells revealed 12 cell clusters. A unique cluster (3.21% of total cells) was identified as a TAC entity, based on its less differentiated progenitor status and enriched exclusive proliferation marker genes, with 98.1% cells in S and G2/M phases. The cell cycle-dependent genes were revealed to be largely enriched by the TAC population. The top genes were characterized morphologically and functionally at protein and mRNA levels. The specific expression patterns of RRM2, TK1, CENPF, NUSAP1, UBE2C, and CDC20 were well correlated in a time- and cycle-dependent manner with proliferation stages in the cell growth and regeneration models. CONCLUSIONS: For the first time, to the best of our knowledge, we have identified a unique TAC entity and uncovered a group of cell cycle-dependent genes that serve as TAC signature markers. The findings provide insight into ASCs and TACs and lay the foundation for understanding corneal homeostasis and diseases.
Keywords: Cell Count; Cell Cycle; Cell Differentiation; Cell Proliferation; Cells, Cultured; Epithelium, Corneal; Eye Proteins; Female; Humans; Limbus Corneae; Male; RNA, Messenger; Transcriptome; Up-Regulation

Technical note: multi-alleles at the DYS385ab locus with high frequency in a Han Chinese population from southwestern China. - Fu, Jiewen; Fu, Shangyi; Yin, Shiqiang; Cheng, Jingliang; Liu, Xiaoyan; Jin, Zeming; He, Tao; Fu, Junjiang (Int J Legal Med, 2021)
Y-chromosome short tandem repeat (Y-STR) markers have been widely used in forensic applications and usually show monoallelic or diallelic genotypic patterns at certain double-copied loci. In this study, we have found 13 samples among 703 males with multi-alleles at the DYS385ab locus, including one with five mutant alleles, nine with four, and three with three. The frequency of abnormal DYS385ab genotypes was 1.85% (13/703), which is very high in the Han Chinese population. The percentage of samples with diallelic patterns at DYS385ab was higher than that of monoallelic patterns (80.23% vs. 17.92%). Additionally, the percentage of samples with tetra-allelic patterns at DYS385ab was higher than that of tri-allelic patterns (1.28% vs. 0.43%), suggesting that there are possibly two copies with duplicated events happening frequently on the Y chromosome. Interestingly, the peak height of allele 13 was two to three-folds higher than that of other alleles. The allele 18 peak height was also two-fold higher than others, which could potentially be explained by a duplication event mechanism. We also found that tri-allelic genotypes for alleles 13, 17, and 20, tetra-allelic genotypes for alleles 13, 14, 19, and 20, and tetra-allelic genotypes for alleles 12, 13, 19 and 21 were more common than others. Furthermore, all 13 samples had multi-alleles containing allele 13, implying a founder effect in this particular Chinese-specific ethnic group. Taken together, this study provides new information for this population and will be useful for paternal lineage identification, kinship analysis, and family relationship reconstruction using Y-STR forensic DNA analysis methods.
Keywords: Alleles; Asian People; China; Chromosomes, Human, Y; Gene Frequency; Genetic Loci; Genotype; Humans; Male; Microsatellite Repeats

Two novel bi-allelic KDELR2 missense variants cause osteogenesis imperfecta with neurodevelopmental features. - Efthymiou, Stephanie; Herman, Isabella; Rahman, Fatima; Anwar, Najwa; Maroofian, Reza; Yip, Janice; Mitani, Tadahiro; Calame, Daniel G; Hunter, Jill V; Sutton, V Reid; Yilmaz Gulec, Elif; Duan, Ruizhi; et al. (Am J Med Genet A, 2021)
Keywords: Alleles; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Humans; Male; Mutation, Missense; Neurodevelopmental Disorders; Osteogenesis Imperfecta; Vesicular Transport Proteins

Variants in FLRT3 and SLC35E2B identified using exome sequencing in seven high myopia families from Central Europe. - Swierkowska, Joanna; Karolak, Justyna A; Gambin, Tomasz; Rydzanicz, Malgorzata; Frajdenberg, Agata; Mrugacz, Malgorzata; Podfigurna-Musielak, Monika; Stankiewicz, Pawel; James R Lupski; Gajecka, Marzena (Adv Med Sci, 2021)
PURPOSE: High myopia (HM) is an eye disorder with both environmental and genetic factors involved. Many genetic factors responsible for HM were recognized worldwide, but little is known about genetic variants underlying HM in Central Europe. Thus, the aim of this study was to identify rare sequence variants involved in HM in families from Central Europe to better understand the genetic basis of HM. MATERIALS AND METHODS: We assessed 17 individuals from 7 unrelated Central European families with hereditary HM using exome sequencing (ES). Segregation of selected variants in other available family members was performed using Sanger sequencing. RESULTS: Detected 73 rare variants were selected for verification. We observed 2 missense variants, c.938C>T in SLC35E2B - encoding solute carrier family 35 member E2B, and c.1642G>C in FLRT3 - encoding fibronectin leucine rich transmembrane protein, segregating with HM in one family. CONCLUSIONS: FLRT3 ​and/or ​SLC35E2B ​could represent disease candidate genes and identified sequence variants might be responsible for HM in the studied family.
Keywords: Adolescent; Europe; Exome; Female; Follow-Up Studies; Genetic Predisposition to Disease; Humans; Male; Membrane Glycoproteins; Mutation; Myopia; Pedigree; Prognosis; Solute Carrier Proteins

Whole genome sequence analyses of eGFR in 23,732 people representing multiple ancestries in the NHLBI trans-omics for precision medicine (TOPMed) consortium. - Lin, Bridget M; Grinde, Kelsey E; Brody, Jennifer A; Breeze, Charles E; Raffield, Laura M; Mychaleckyj, Josyf C; Thornton, Timothy A; Perry, James A; Baier, Leslie J; de Las Fuentes, Lisa; Guo, Xiuqing; Heavner, Benjamin D; et al. (EBioMedicine, 2021)
BACKGROUND: Genetic factors that influence kidney traits have been understudied for low frequency and ancestry-specific variants. METHODS: We combined whole genome sequencing (WGS) data from 23,732 participants from 10 NHLBI Trans-Omics for Precision Medicine (TOPMed) Program multi-ethnic studies to identify novel loci for estimated glomerular filtration rate (eGFR). Participants included European, African, East Asian, and Hispanic ancestries. We applied linear mixed models using a genetic relationship matrix estimated from the WGS data and adjusted for age, sex, study, and ethnicity. FINDINGS: When testing single variants, we identified three novel loci driven by low frequency variants more commonly observed in non-European ancestry (PRKAA2, rs180996919, minor allele frequency [MAF] 0.04%, P = 6.1 × 10; METTL8, rs116951054, MAF 0.09%, P = 4.5 × 10; and MATK, rs539182790, MAF 0.05%, P = 3.4 × 10). We also replicated two known loci for common variants (rs2461702, MAF=0.49, P = 1.2 × 10, nearest gene GATM, and rs71147340, MAF=0.34, P = 3.3 × 10, CDK12). Testing aggregated variants within a gene identified the MAF gene. A statistical approach based on local ancestry helped to identify replication samples for ancestry-specific variants. INTERPRETATION: This study highlights challenges in studying variants influencing kidney traits that are low frequency in populations and more common in non-European ancestry.
Keywords: Alleles; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Glomerular Filtration Rate; Humans; Male; National Heart, Lung, and Blood Institute (U.S.); Polymorphism, Single Nucleotide; Precision Medicine; Public Health Surveillance; Quantitative Trait, Heritable; United States; Whole Genome Sequencing

Whole-genome association analyses of sleep-disordered breathing phenotypes in the NHLBI TOPMed program. - Cade, Brian E; Lee, Jiwon; Sofer, Tamar; Wang, Heming; Zhang, Man; Chen, Han; Gharib, Sina A; Gottlieb, Daniel J; Guo, Xiuqing; Lane, Jacqueline M; Liang, Jingjing; Lin, Xihong; et al. (Genome Med, 2021)
BACKGROUND: Sleep-disordered breathing is a common disorder associated with significant morbidity. The genetic architecture of sleep-disordered breathing remains poorly understood. Through the NHLBI Trans-Omics for Precision Medicine (TOPMed) program, we performed the first whole-genome sequence analysis of sleep-disordered breathing. METHODS: The study sample was comprised of 7988 individuals of diverse ancestry. Common-variant and pathway analyses included an additional 13,257 individuals. We examined five complementary traits describing different aspects of sleep-disordered breathing: the apnea-hypopnea index, average oxyhemoglobin desaturation per event, average and minimum oxyhemoglobin saturation across the sleep episode, and the percentage of sleep with oxyhemoglobin saturation < 90%. We adjusted for age, sex, BMI, study, and family structure using MMSKAT and EMMAX mixed linear model approaches. Additional bioinformatics analyses were performed with MetaXcan, GIGSEA, and ReMap. RESULTS: We identified a multi-ethnic set-based rare-variant association (p = 3.48 × 10) on chromosome X with ARMCX3. Additional rare-variant associations include ARMCX3-AS1, MRPS33, and C16orf90. Novel common-variant loci were identified in the NRG1 and SLC45A2 regions, and previously associated loci in the IL18RAP and ATP2B4 regions were associated with novel phenotypes. Transcription factor binding site enrichment identified associations with genes implicated with respiratory and craniofacial traits. Additional analyses identified significantly associated pathways. CONCLUSIONS: We have identified the first gene-based rare-variant associations with objectively measured sleep-disordered breathing traits. Our results increase the understanding of the genetic architecture of sleep-disordered breathing and highlight associations in genes that modulate lung development, inflammation, respiratory rhythmogenesis, and HIF1A-mediated hypoxic response.
Keywords: Alleles; Chromatin Immunoprecipitation Sequencing; Female; Gene Expression Regulation; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Precision Medicine; Research; Signal Transduction; Sleep Apnea Syndromes; United States; Whole Genome Sequencing

Ancestry-specific predisposing germline variants in cancer. - Oak, Ninad; Cherniack, Andrew D; Mashl, R Jay; Hirsch, Fred R; Ding, Li; Beroukhim, Rameen; Gümüş, Zeynep H; Plon, Sharon E; Huang, Kuan-Lin (Genome Med, 2020)
BACKGROUND: Distinct prevalence of inherited genetic predisposition may partially explain the difference of cancer risks across ancestries. Ancestry-specific analyses of germline genomes are required to inform cancer genetic risk and prognosis of diverse populations. METHODS: We conducted analyses using germline and somatic sequencing data generated by The Cancer Genome Atlas. Collapsing pathogenic and likely pathogenic variants to cancer predisposition genes (CPG), we analyzed the association between CPGs and cancer types within ancestral groups. We also identified the predisposition-associated two-hit events and gene expression effects in tumors. RESULTS: Genetic ancestry analysis classified the cohort of 9899 cancer cases into individuals of primarily European (N = 8184, 82.7%), African (N = 966, 9.8%), East Asian (N = 649, 6.6%), South Asian (N = 48, 0.5%), Native/Latin American (N = 41, 0.4%), and admixed (N = 11, 0.1%) ancestries. In the African ancestry, we discovered a potentially novel association of BRCA2 in lung squamous cell carcinoma (OR = 41.4 [95% CI, 6.1-275.6]; FDR = 0.002) previously identified in Europeans, along with a known association of BRCA2 in ovarian serous cystadenocarcinoma (OR = 8.5 [95% CI, 1.5-47.4]; FDR = 0.045). In the East Asian ancestry, we discovered one previously known association of BRIP1 in stomach adenocarcinoma (OR = 12.8 [95% CI, 1.8-90.8]; FDR = 0.038). Rare variant burden analysis further identified 7 suggestive associations in African ancestry individuals previously described in European ancestry, including SDHB in pheochromocytoma and paraganglioma, ATM in prostate adenocarcinoma, VHL in kidney renal clear cell carcinoma, FH in kidney renal papillary cell carcinoma, and PTEN in uterine corpus endometrial carcinoma. Most predisposing variants were found exclusively in one ancestry in the TCGA and gnomAD datasets. Loss of heterozygosity was identified for 7 out of the 15 African ancestry carriers of predisposing variants. Further, tumors from the SDHB or BRCA2 carriers showed simultaneous allelic-specific expression and low gene expression of their respective affected genes, and FH splice-site variant carriers showed mis-splicing of FH. CONCLUSIONS: While several CPGs are shared across patients, many pathogenic variants are found to be ancestry-specific and trigger somatic effects. Studies using larger cohorts of diverse ancestries are required to pinpoint ancestry-specific genetic predisposition and inform genetic screening strategies.
Keywords: Ataxia Telangiectasia Mutated Proteins; BRCA2 Protein; Fanconi Anemia Complementation Group Proteins; Female; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Male; Neoplasms; Risk Factors; RNA Helicases; Succinate Dehydrogenase; Von Hippel-Lindau Tumor Suppressor Protein

Biallelic GRM7 variants cause epilepsy, microcephaly, and cerebral atrophy. - Marafi, Dana; Mitani, Tadahiro; Isikay, Sedat; Hertecant, Jozef; Almannai, Mohammed; Manickam, Kandamurugu; Abou Jamra, Rami; El-Hattab, Ayman W; Rajah, Jaishen; Fatih, Jawid M; Du, Haowei; Karaca, Ender; et al. (Ann Clin Transl Neurol, 2020)
OBJECTIVE: Defects in ion channels and neurotransmitter receptors are implicated in developmental and epileptic encephalopathy (DEE). Metabotropic glutamate receptor 7 (mGluR7), encoded by GRM7, is a presynaptic G-protein-coupled glutamate receptor critical for synaptic transmission. We previously proposed GRM7 as a candidate disease gene in two families with neurodevelopmental disorders (NDDs). One additional family has been published since. Here, we describe three additional families with GRM7 biallelic variants and deeply characterize the associated clinical neurological and electrophysiological phenotype and molecular data in 11 affected individuals from six unrelated families. METHODS: Exome sequencing and family-based rare variant analyses on a cohort of 220 consanguineous families with NDDs revealed three families with GRM7 biallelic variants; three additional families were identified through literature search and collaboration with a clinical molecular laboratory. RESULTS: We compared the observed clinical features and variants of 11 affected individuals from the six unrelated families. Identified novel deleterious variants included two homozygous missense variants (c.2671G>A:p.Glu891Lys and c.1973G>A:p.Arg685Gln) and one homozygous stop-gain variant (c.1975C>T:p.Arg659Ter). Developmental delay, neonatal- or infantile-onset epilepsy, and microcephaly were universal. Three individuals had hypothalamic-pituitary-axis dysfunction without pituitary structural abnormality. Neuroimaging showed cerebral atrophy and hypomyelination in a majority of cases. Two siblings demonstrated progressive loss of myelination by 2 years in both and an acquired microcephaly pattern in one. Five individuals died in early or late childhood. CONCLUSION: Detailed clinical characterization of 11 individuals from six unrelated families demonstrates that rare biallelic GRM7 pathogenic variants can cause DEEs, microcephaly, hypomyelination, and cerebral atrophy.
Keywords: Adolescent; Alleles; Atrophy; Child; Child, Preschool; Cohort Studies; Consanguinity; Epilepsy; Exome Sequencing; Female; Humans; Infant; Male; Microcephaly; Neurodevelopmental Disorders; Pedigree; Phenotype; Receptors, Metabotropic Glutamate

BICRA, a SWI/SNF Complex Member, Is Associated with BAF-Disorder Related Phenotypes in Humans and Model Organisms. - Barish, Scott; Barakat, Tahsin Stefan; Michel, Brittany C; Mashtalir, Nazar; Phillips, Jennifer B; Valencia, Alfredo M; Ugur, Berrak; Wegner, Jeremy; Scott, Tiana M; Bostwick, Brett; David R Murdock; Dai, Hongzheng; et al. (Am J Hum Genet, 2020)
SWI/SNF-related intellectual disability disorders (SSRIDDs) are rare neurodevelopmental disorders characterized by developmental disability, coarse facial features, and fifth digit/nail hypoplasia that are caused by pathogenic variants in genes that encode for members of the SWI/SNF (or BAF) family of chromatin remodeling complexes. We have identified 12 individuals with rare variants (10 loss-of-function, 2 missense) in the BICRA (BRD4 interacting chromatin remodeling complex-associated protein) gene, also known as GLTSCR1, which encodes a subunit of the non-canonical BAF (ncBAF) complex. These individuals exhibited neurodevelopmental phenotypes that include developmental delay, intellectual disability, autism spectrum disorder, and behavioral abnormalities as well as dysmorphic features. Notably, the majority of individuals lack the fifth digit/nail hypoplasia phenotype, a hallmark of most SSRIDDs. To confirm the role of BICRA in the development of these phenotypes, we performed functional characterization of the zebrafish and Drosophila orthologs of BICRA. In zebrafish, a mutation of bicra that mimics one of the loss-of-function variants leads to craniofacial defects possibly akin to the dysmorphic facial features seen in individuals harboring putatively pathogenic BICRA variants. We further show that Bicra physically binds to other non-canonical ncBAF complex members, including the BRD9/7 ortholog, CG7154, and is the defining member of the ncBAF complex in flies. Like other SWI/SNF complex members, loss of Bicra function in flies acts as a dominant enhancer of position effect variegation but in a more context-specific manner. We conclude that haploinsufficiency of BICRA leads to a unique SSRIDD in humans whose phenotypes overlap with those previously reported.
Keywords: Adolescent; Animals; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Developmental Disabilities; Drosophila melanogaster; Drosophila Proteins; Female; Genes, Dominant; Genetic Variation; Haploinsufficiency; Humans; Infant; Male; Microscopy, Confocal; Mutation, Missense; Neuroglia; Neurons; Phenotype; Protein Binding; Tumor Suppressor Proteins; Zebrafish; Zebrafish Proteins

Cohort Profile: The Right Drug, Right Dose, Right Time: Using Genomic Data to Individualize Treatment Protocol (RIGHT Protocol). - Bielinski, Suzette J; St Sauver, Jennifer L; Olson, Janet E; Larson, Nicholas B; Black, John L; Steven E Scherer; Bernard, Matthew E; Eric Boerwinkle; Borah, Bijan J; Caraballo, Pedro J; Curry, Timothy B; Harshavardhan Doddapaneni; et al. (Int J Epidemiol, 2020)
Keywords: Clinical Protocols; Cohort Studies; Female; Genomics; Humans; Male; Pharmacogenetics; Precision Medicine

Combination of whole exome sequencing and animal modeling identifies TMPRSS9 as a candidate gene for autism spectrum disorder. - Chen, Chun-An; Pal, Rituraj; Yin, Jiani; Tao, Huifang; Amawi, Abdallah; Aniko Sabo; Bainbridge, Matthew N; Richard A Gibbs; Zoghbi, Huda Y; Schaaf, Christian P (Hum Mol Genet, 2020)
Autism spectrum disorders are associated with some degree of developmental regression in up to 30% of all cases. Rarely, however, is the regression so extreme that a developmentally advanced young child would lose almost all ability to communicate and interact with her surroundings. We applied trio whole exome sequencing to a young woman who experienced extreme developmental regression starting at 2.5 years of age and identified compound heterozygous nonsense mutations in TMPRSS9, which encodes for polyserase-1, a transmembrane serine protease of poorly understood physiological function. Using semiquantitative polymerase chain reaction, we showed that Tmprss9 is expressed in various mouse tissues, including the brain. To study the consequences of TMPRSS9 loss of function on the mammalian brain, we generated a knockout mouse model. Through a battery of behavioral assays, we found that Tmprss9-/- mice showed decreased social interest and social recognition. We observed a borderline recognition memory deficit by novel object recognition in aged Tmprss9-/- female mice, but not in aged Tmprss9-/- male mice or younger adult Tmprss9-/- mice in both sexes. This study provides evidence to suggest that loss of function variants in TMPRSS9 are related to an autism spectrum disorder. However, the identification of more individuals with similar phenotypes and TMPRSS9 loss of function variants is required to establish a robust gene-disease relationship.
Keywords: Adolescent; Adult; Animals; Anxiety Disorders; Autism Spectrum Disorder; Child; Child, Preschool; Codon, Nonsense; Exome Sequencing; Female; Humans; Male; Membrane Proteins; Memory Disorders; Mice; Mice, Knockout; Motor Activity; Phenotype; Serine Endopeptidases

Community-based recruitment and exome sequencing indicates high diagnostic yield in adults with intellectual disability. - Aniko Sabo; David R Murdock; Dugan, Shannon; Meng, Qingchang; Marie-Claude Gingras; Jianhong Hu; Donna M Muzny; Richard A Gibbs (Mol Genet Genomic Med, 2020)
BACKGROUND: Establishing a genetic diagnosis for individuals with intellectual disability (ID) benefits patients and their families as it may inform the prognosis, lead to appropriate therapy, and facilitate access to medical and supportive services. Exome sequencing has been successfully applied in a diagnostic setting, but most clinical exome referrals are pediatric patients, with many adults with ID lacking a comprehensive genetic evaluation. METHODS: Our unique recruitment strategy involved partnering with service and education providers for individuals with ID. We performed exome sequencing and analysis, and clinical variant interpretation for each recruited family. RESULTS: All five families enrolled in the study opted-in for the return of genetic results. In three out of five families exome sequencing analysis identified pathogenic or likely pathogenic variants in KANSL1, TUSC3, and MED13L genes. Families discussed the results and any potential medical follow-up in an appointment with a board certified clinical geneticist. CONCLUSION: Our study suggests high yield of exome sequencing as a diagnostic tool in adult patients with ID who have not undergone comprehensive sequencing-based genetic testing. Research studies including an option of return of results through a genetic clinic could help minimize the disparity in exome diagnostic testing between pediatric and adult patients with ID.
Keywords: Adult; Exome Sequencing; Female; Genetic Testing; Humans; Independent Living; Intellectual Disability; Male; Mediator Complex; Membrane Proteins; Nuclear Proteins; Patient Selection; Sensitivity and Specificity; Tumor Suppressor Proteins

Comparison of Methods To Collect Fecal Samples for Microbiome Studies Using Whole-Genome Shotgun Metagenomic Sequencing. - Byrd, Doratha A; Sinha, Rashmi; Hoffman, Kristi L; Chen, Jun; Hua, Xing; Shi, Jianxin; Chia, Nicholas; Petrosino, Joseph; Vogtmann, Emily (mSphere, 2020)
Few previous studies have assessed stability and "gold-standard" concordance of fecal sample collection methods for whole-genome shotgun metagenomic sequencing (WGSS), an increasingly popular method for studying the gut microbiome. We used WGSS data to investigate ambient temperature stability and putative gold-standard concordance of microbial profiles in fecal samples collected and stored using fecal occult blood test (FOBT) cards, fecal immunochemical test (FIT) tubes, 95% ethanol, or RNAlater. Among 15 Mayo Clinic employees, for each collection method, we calculated intraclass correlation coefficients (ICCs) to estimate stability of fecal microbial profiles after storage for 4 days at ambient temperature and concordance with immediately frozen, no-solution samples (i.e., the putative gold standard). ICCs were estimated for multiple metrics, including relative abundances of select phyla, species, KEGG k-genes (representing any coding sequence that had >70% identity and >70% query coverage with respect to a known KEGG ortholog), KEGG modules, and KEGG pathways; species and k-gene alpha diversity; and Bray-Curtis and Jaccard species beta diversity. ICCs for microbial profile stability were excellent (≥90%) for fecal samples collected via most of the collection methods, except those preserved in 95% ethanol. Concordance with the immediately frozen, no-solution samples varied for all collection methods, but the number of observed species and the beta diversity metrics tended to have higher concordance than other metrics. Our findings, taken together with previous studies and feasibility considerations, indicated that FOBT cards, FIT tubes, and RNAlater are acceptable choices for fecal sample collection methods in future WGSS studies. A major direction for future microbiome research is implementation of fecal sample collections in large-scale, prospective epidemiologic studies. Studying microbiome-disease associations likely requires microbial data to be pooled from multiple studies. Our findings suggest collection methods that are most optimal to be used standardly across future WGSS microbiome studies.
Keywords: Adult; DNA, Bacterial; Ethanol; Feces; Female; Freezing; Gastrointestinal Microbiome; Healthy Volunteers; Humans; Male; Metagenome; Metagenomics; Middle Aged; Preservation, Biological; RNA, Ribosomal, 16S; Specimen Handling; Temperature; Whole Genome Sequencing

Congenital diaphragmatic hernia as a prominent feature of a SPECC1L-related syndrome. - Wild, K Taylor; Gordon, Tia; Bhoj, Elizabeth J; Du, Haowei; Jhangiani, Shalini N; Posey, Jennifer E; James R Lupski; Scott, Daryl A; Zackai, Elaine H (Am J Med Genet A, 2020)
Congenital diaphragmatic hernias (CDH) confer substantial morbidity and mortality. Genetic defects, including chromosomal anomalies, copy number variants, and sequence variants are identified in ~30% of patients with CDH. A genetic etiology is not yet found in 70% of patients, however there is a growing number of genetic syndromes and single gene disorders associated with CDH. While there have been two reported individuals with X-linked Opitz G/BBB syndrome with MID1 mutations who have CDH as an associated feature, CDH appears to be a much more prominent feature of a SPECC1L-related autosomal dominant Opitz G/BBB syndrome. Features unique to autosomal dominant Opitz G/BBB syndrome include branchial fistulae, omphalocele, and a bicornuate uterus. Here we present one new individual and five previously reported individuals with CDH found to have SPECC1L mutations. These cases provide strong evidence that SPECC1L is a bona fide CDH gene. We conclude that a SPECC1L-related Opitz G/BBB syndrome should be considered in any patient with CDH who has additional features of hypertelorism, a prominent forehead, a broad nasal bridge, anteverted nares, cleft lip/palate, branchial fistulae, omphalocele, and/or bicornuate uterus.
Keywords: Abnormalities, Multiple; Child, Preschool; Female; Gestational Age; Hernias, Diaphragmatic, Congenital; Humans; Infant; Infant, Newborn; Male; Mutation, Missense; Phosphoproteins; Syndrome

Copy number variants and fixed duplications among 198 rhesus macaques (Macaca mulatta). - Brasó-Vives, Marina; Povolotskaya, Inna S; Hartasánchez, Diego A; Farré, Xavier; Fernandez-Callejo, Marcos; Raveendran, Muthuswamy; R. Alan Harris; Rosene, Douglas L; Lorente-Galdos, Belen; Navarro, Arcadi; Marques-Bonet, Tomas; Jeffrey Rogers; et al. (PLoS Genet, 2020)
The rhesus macaque is an abundant species of Old World monkeys and a valuable model organism for biomedical research due to its close phylogenetic relationship to humans. Copy number variation is one of the main sources of genomic diversity within and between species and a widely recognized cause of inter-individual differences in disease risk. However, copy number differences among rhesus macaques and between the human and macaque genomes, as well as the relevance of this diversity to research involving this nonhuman primate, remain understudied. Here we present a high-resolution map of sequence copy number for the rhesus macaque genome constructed from a dataset of 198 individuals. Our results show that about one-eighth of the rhesus macaque reference genome is composed of recently duplicated regions, either copy number variable regions or fixed duplications. Comparison with human genomic copy number maps based on previously published data shows that, despite overall similarities in the genome-wide distribution of these regions, there are specific differences at the chromosome level. Some of these create differences in the copy number profile between human disease genes and their rhesus macaque orthologs. Our results highlight the importance of addressing the number of copies of target genes in the design of experiments and cautions against human-centered assumptions in research conducted with model organisms. Overall, we present a genome-wide copy number map from a large sample of rhesus macaque individuals representing an important novel contribution concerning the evolution of copy number in primate genomes.
Keywords: Animals; Chromosome Mapping; DNA Copy Number Variations; Female; Gene Duplication; Genetics, Population; Genome; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Male; Open Reading Frames; Phylogeny; Sequence Analysis, DNA; Species Specificity

Critical Role of Cytosolic DNA and Its Sensing Adaptor STING in Aortic Degeneration, Dissection, and Rupture. - Luo, Wei; Wang, Yidan; Zhang, Lin; Ren, Pingping; Zhang, Chen; Li, Yanming; Azares, Alon R; Zhang, Michelle; Guo, Jiao; Ghaghada, Ketan B; Starosolski, Zbigniew A; Rajapakshe, Kimal; et al. (Circulation, 2020)
BACKGROUND: Sporadic aortic aneurysm and dissection (AAD), caused by progressive aortic smooth muscle cell (SMC) loss and extracellular matrix degradation, is a highly lethal condition. Identifying mechanisms that drive aortic degeneration is a crucial step in developing an effective pharmacologic treatment to prevent disease progression. Recent evidence has indicated that cytosolic DNA and abnormal activation of the cytosolic DNA sensing adaptor STING (stimulator of interferon genes) play a critical role in vascular inflammation and destruction. Here, we examined the involvement of this mechanism in aortic degeneration and sporadic AAD formation. METHODS: The presence of cytosolic DNA in aortic cells and activation of the STING pathway were examined in aortic tissues from patients with sporadic ascending thoracic AAD. The role of STING in AAD development was evaluated in -deficient () mice in a sporadic AAD model induced by challenging mice with a combination of a high-fat diet and angiotensin II. We also examined the direct effects of STING on SMC death and macrophage activation in vitro. RESULTS: In human sporadic AAD tissues, we observed the presence of cytosolic DNA in SMCs and macrophages and significant activation of the STING pathway. In the sporadic AAD model, mice showed significant reductions in challenge-induced aortic enlargement, dissection, and rupture in both the thoracic and abdominal aortic regions. Single-cell transcriptome analysis revealed that aortic challenge in wild-type mice induced the DNA damage response, the inflammatory response, dedifferentiation and cell death in SMCs, and matrix metalloproteinase expression in macrophages. These changes were attenuated in challenged mice. Mechanistically, nuclear and mitochondrial DNA damage in SMCs and the subsequent leak of DNA to the cytosol activated STING signaling, which induced cell death through apoptosis and necroptosis. In addition, DNA from damaged SMCs was engulfed by macrophages in which it activated STING and its target interferon regulatory factor 3, which directly induced matrix metalloproteinase-9 expression. We also found that pharmacologically inhibiting STING activation partially prevented AAD development. CONCLUSIONS: Our findings indicate that the presence of cytosolic DNA and subsequent activation of cytosolic DNA sensing adaptor STING signaling represent a key mechanism in aortic degeneration and that targeting STING may prevent sporadic AAD development.
Keywords: Animals; Aortic Dissection; Aortic Rupture; Cytosol; DNA; Female; Male; Membrane Proteins; Mice; Mice, Knockout; Signal Transduction

Cytogenetically visible inversions are formed by multiple molecular mechanisms. - Pettersson, Maria; Grochowski, Christopher M; Wincent, Josephine; Eisfeldt, Jesper; Breman, Amy M; Cheung, Sau W; Krepischi, Ana C V; Rosenberg, Carla; James R Lupski; Ottosson, Jesper; Lovmar, Lovisa; Gacic, Jelena; et al. (Hum Mutat, 2020)
Cytogenetically detected inversions are generally assumed to be copy number and phenotypically neutral events. While nonallelic homologous recombination is thought to play a major role, recent data suggest the involvement of other molecular mechanisms in inversion formation. Using a combination of short-read whole-genome sequencing (WGS), 10X Genomics Chromium WGS, droplet digital polymerase chain reaction and array comparative genomic hybridization we investigated the genomic structure of 18 large unique cytogenetically detected chromosomal inversions and achieved nucleotide resolution of at least one chromosomal inversion junction for 13/18 (72%). Surprisingly, we observed that seemingly copy number neutral inversions can be accompanied by a copy-number gain of up to 350 kb and local genomic complexities (3/18, 17%). In the resolved inversions, the mutational signatures are consistent with nonhomologous end-joining (8/13, 62%) or microhomology-mediated break-induced replication (5/13, 38%). Our study indicates that short-read 30x coverage WGS can detect a substantial fraction of chromosomal inversions. Moreover, replication-based mechanisms are responsible for approximately 38% of those events leading to a significant proportion of inversions that are actually accompanied by additional copy-number variation potentially contributing to the overall phenotypic presentation of those patients.
Keywords: Chromosome Inversion; Comparative Genomic Hybridization; DNA End-Joining Repair; DNA Repair; Female; Gene Frequency; Haplotypes; Heterozygote; Homologous Recombination; Humans; Karyotyping; Male; Pedigree; Whole Genome Sequencing

Deficiencies in vesicular transport mediated by TRAPPC4 are associated with severe syndromic intellectual disability. - Van Bergen, Nicole J; Guo, Yiran; Al-Deri, Noraldin; Lipatova, Zhanna; Stanga, Daniela; Zhao, Sarah; Murtazina, Rakhilya; Gyurkovska, Valeriya; Pehlivan, Davut; Mitani, Tadahiro; Gezdirici, Alper; Antony, Jayne; et al. (Brain, 2020)
The conserved transport protein particle (TRAPP) complexes regulate key trafficking events and are required for autophagy. TRAPPC4, like its yeast Trs23 orthologue, is a core component of the TRAPP complexes and one of the essential subunits for guanine nucleotide exchange factor activity for Rab1 GTPase. Pathogenic variants in specific TRAPP subunits are associated with neurological disorders. We undertook exome sequencing in three unrelated families of Caucasian, Turkish and French-Canadian ethnicities with seven affected children that showed features of early-onset seizures, developmental delay, microcephaly, sensorineural deafness, spastic quadriparesis and progressive cortical and cerebellar atrophy in an effort to determine the genetic aetiology underlying neurodevelopmental disorders. All seven affected subjects shared the same identical rare, homozygous, potentially pathogenic variant in a non-canonical, well-conserved splice site within TRAPPC4 (hg19:chr11:g.118890966A>G; TRAPPC4: NM_016146.5; c.454+3A>G). Single nucleotide polymorphism array analysis revealed there was no haplotype shared between the tested Turkish and Caucasian families suggestive of a variant hotspot region rather than a founder effect. In silico analysis predicted the variant to cause aberrant splicing. Consistent with this, experimental evidence showed both a reduction in full-length transcript levels and an increase in levels of a shorter transcript missing exon 3, suggestive of an incompletely penetrant splice defect. TRAPPC4 protein levels were significantly reduced whilst levels of other TRAPP complex subunits remained unaffected. Native polyacrylamide gel electrophoresis and size exclusion chromatography demonstrated a defect in TRAPP complex assembly and/or stability. Intracellular trafficking through the Golgi using the marker protein VSVG-GFP-ts045 demonstrated significantly delayed entry into and exit from the Golgi in fibroblasts derived from one of the affected subjects. Lentiviral expression of wild-type TRAPPC4 in these fibroblasts restored trafficking, suggesting that the trafficking defect was due to reduced TRAPPC4 levels. Consistent with the recent association of the TRAPP complex with autophagy, we found that the fibroblasts had a basal autophagy defect and a delay in autophagic flux, possibly due to unsealed autophagosomes. These results were validated using a yeast trs23 temperature sensitive variant that exhibits constitutive and stress-induced autophagic defects at permissive temperature and a secretory defect at restrictive temperature. In summary we provide strong evidence for pathogenicity of this variant in a member of the core TRAPP subunit, TRAPPC4 that associates with vesicular trafficking and autophagy defects. This is the first report of a TRAPPC4 variant, and our findings add to the growing number of TRAPP-associated neurological disorders.
Keywords: Atrophy; Autophagy; Cerebellum; Cerebral Cortex; Child; Child, Preschool; Craniofacial Abnormalities; Deafness; Developmental Disabilities; Epilepsy; Female; Fibroblasts; Hearing Loss, Sensorineural; Humans; Infant; Infant, Newborn; Intellectual Disability; Male; Microcephaly; Microscopy, Fluorescence; Muscle Spasticity; Nerve Tissue Proteins; Neurodevelopmental Disorders; Pedigree; Quadriplegia; RNA Splice Sites; Syndrome; Vesicular Transport Proteins

Efficient gene-environment interaction tests for large biobank-scale sequencing studies. - Wang, Xinyu; Lim, Elise; Liu, Ching-Ti; Sung, Yun Ju; Rao, Dabeeru C; Morrison, Alanna C; Eric Boerwinkle; Manning, Alisa K; Chen, Han (Genet Epidemiol, 2020)
Complex human diseases are affected by genetic and environmental risk factors and their interactions. Gene-environment interaction (GEI) tests for aggregate genetic variant sets have been developed in recent years. However, existing statistical methods become rate limiting for large biobank-scale sequencing studies with correlated samples. We propose efficient Mixed-model Association tests for GEne-Environment interactions (MAGEE), for testing GEI between an aggregate variant set and environmental exposures on quantitative and binary traits in large-scale sequencing studies with related individuals. Joint tests for the aggregate genetic main effects and GEI effects are also developed. A null generalized linear mixed model adjusting for covariates but without any genetic effects is fit only once in a whole genome GEI analysis, thereby vastly reducing the overall computational burden. Score tests for variant sets are performed as a combination of genetic burden and variance component tests by accounting for the genetic main effects using matrix projections. The computational complexity is dramatically reduced in a whole genome GEI analysis, which makes MAGEE scalable to hundreds of thousands of individuals. We applied MAGEE to the exome sequencing data of 41,144 related individuals from the UK Biobank, and the analysis of 18,970 protein coding genes finished within 10.4 CPU hours.
Keywords: Biological Specimen Banks; Body Mass Index; Computer Simulation; Exome; Exome Sequencing; Female; Gene-Environment Interaction; Humans; Linear Models; Male; Models, Genetic; Obesity; Phenotype; Quantitative Trait, Heritable; Time Factors

Epigenetic Age Acceleration and Cognitive Function in African American Adults in Midlife: The Atherosclerosis Risk in Communities Study. - Bressler, Jan; Marioni, Riccardo E; Walker, Rosie M; Xia, Rui; Gottesman, Rebecca F; Windham, B Gwen; Grove, Megan L; Guan, Weihua; Pankow, James S; Evans, Kathryn L; McIntosh, Andrew M; Deary, Ian J; et al. (J Gerontol A Biol Sci Med Sci, 2020)
Methylation levels measured at defined sites across the genome have recently been shown to be correlated with an individual's chronological age. Age acceleration, or the difference between age estimated from DNA methylation status and chronological age, has been proposed as a novel biomarker of aging. In this study, the cross-sectional association between two different measures of age acceleration and cognitive function was investigated using whole blood samples from 2,157 African American participants 47-70 years of age in the population-based Atherosclerosis Risk in Communities (ARIC) Study. Cognition was evaluated using three domain-specific tests. A significant inverse association between a 1-year increase in age acceleration calculated using a blood-based age predictor and scores on the Word Fluency Test was found using a general linear model adjusted for chronological age, gender, and years of education (β = -0.140 words; p = .001) and after adding other potential confounding variables (β = -0.104 words, p = .023). The results were replicated in 1,670 European participants in the Generation Scotland: Scottish Family Health Study (fully adjusted model: β = -0.199 words; p = .034). A significant association was also identified in a trans-ethnic meta-analysis across cohorts that included an additional 708 European American ARIC study participants (fully adjusted model: β = -0.110 words, p = .003). There were no associations found using an estimate of age acceleration derived from multiple tissues. These findings provide evidence that age acceleration is a correlate of performance on a test of verbal fluency in middle-aged adults.
Keywords: Aged; Aging; Atherosclerosis; Black or African American; Cognition; Cross-Sectional Studies; Epigenesis, Genetic; Female; Humans; Male; Middle Aged; Risk Assessment; Time Factors

Evaluation of mitochondrial DNA copy number estimation techniques. - Longchamps, Ryan J; Castellani, Christina A; Yang, Stephanie Y; Newcomb, Charles E; Sumpter, Jason A; Lane, John; Grove, Megan L; Guallar, Eliseo; Pankratz, Nathan; Taylor, Kent D; Rotter, Jerome I; Eric Boerwinkle; et al. (PLoS One, 2020)
Mitochondrial DNA copy number (mtDNA-CN), a measure of the number of mitochondrial genomes per cell, is a minimally invasive proxy measure for mitochondrial function and has been associated with several aging-related diseases. Although quantitative real-time PCR (qPCR) is the current gold standard method for measuring mtDNA-CN, mtDNA-CN can also be measured from genotyping microarray probe intensities and DNA sequencing read counts. To conduct a comprehensive examination on the performance of these methods, we use known mtDNA-CN correlates (age, sex, white blood cell count, Duffy locus genotype, incident cardiovascular disease) to evaluate mtDNA-CN calculated from qPCR, two microarray platforms, as well as whole genome (WGS) and whole exome sequence (WES) data across 1,085 participants from the Atherosclerosis Risk in Communities (ARIC) study and 3,489 participants from the Multi-Ethnic Study of Atherosclerosis (MESA). We observe mtDNA-CN derived from WGS data is significantly more associated with known correlates compared to all other methods (p < 0.001). Additionally, mtDNA-CN measured from WGS is on average more significantly associated with traits by 5.6 orders of magnitude and has effect size estimates 5.8 times more extreme than the current gold standard of qPCR. We further investigated the role of DNA extraction method on mtDNA-CN estimate reproducibility and found mtDNA-CN estimated from cell lysate is significantly less variable than traditional phenol-chloroform-isoamyl alcohol (p = 5.44x10-4) and silica-based column selection (p = 2.82x10-7). In conclusion, we recommend the field moves towards more accurate methods for mtDNA-CN, as well as re-analyze trait associations as more WGS data becomes available from larger initiatives such as TOPMed.
Keywords: Aged; DNA, Mitochondrial; Female; Gene Dosage; Genomics; Humans; Male; Middle Aged

Exome sequencing reveals a novel variant in causing intracranial aneurysm in a Chinese family. - Ding, Xinghuan; Zhao, Sen; Zhang, Qianqian; Yan, Zihui; Wang, Yang; Wu, Yong; Li, Xiaoxin; Liu, Jian; Niu, Yuchen; Zhang, Yisen; Zhang, Mingqi; Wang, Huizi; et al. (J Neurointerv Surg, 2020)
BACKGROUND: Genetic risk factors play an important role in the pathogenesis of familial intracranial aneurysms (FIAs); however, the molecular mechanisms remain largely unknown. OBJECTIVE: To investigate potential FIA-causing genetic variants by rare variant interrogation and a family-based genomics approach in a large family with an extensive multigenerational pedigree with FIAs. METHOD: Exome sequencing (ES) was performed in a dominant likely family with intracranial aneurysms (IAs). Variants were analyzed by an in-house developed pipeline and prioritized using various filtering strategies, including population frequency, variant type, and predicted variant pathogenicity. Sanger sequencing was also performed to evaluate the segregation of the variants with the phenotype. RESULTS: Based on the ES data obtained from five individuals from a family with 7/21 living members affected with IAs, a total of 14 variants were prioritized as candidate variants. Familial segregation analysis revealed that c.2519T>C (p.Leu840Pro) segregated in accordance with Mendelian expectations with the phenotype within the family-that is, present in all IA-affected cases and absent from all unaffected members of the second generation. This missense variant is absent from public databases (1000genome, ExAC, gnomAD, ESP5400), and has damaging predictions by bioinformatics tools (Gerp ++ score = 5.88, CADD score = 16.43, MutationTaster score = 1, LRT score = 0). In addition, 840Leu in NFX1 is robustly conserved in mammals and maps in a region before the RING-type zinc finger domain. CONCLUSION: c.2519T>C (p.Leu840Pro) may contribute to the pathogenetics of a subset of FIAs.
Keywords: Adult; Asian People; Computational Biology; Exome; Female; Genetic Variation; Humans; Intracranial Aneurysm; Male; Middle Aged; Pedigree; Phenotype; Repressor Proteins

Functional biology of the Steel syndrome founder allele and evidence for clan genomics derivation of COL27A1 pathogenic alleles worldwide. - Gonzaga-Jauregui, Claudia; Yesil, Gozde; Nistala, Harikiran; Gezdirici, Alper; Bayram, Yavuz; Nannuru, Kalyan C; Pehlivan, Davut; Bo Yuan; Jimenez, Johanna; Sahin, Yavuz; Paine, Ingrid S; Akdemir, Zeynep Coban; et al. (Eur J Hum Genet, 2020)
Previously we reported the identification of a homozygous COL27A1 (c.2089G>C; p.Gly697Arg) missense variant and proposed it as a founder allele in Puerto Rico segregating with Steel syndrome (STLS, MIM #615155); a rare osteochondrodysplasia characterized by short stature, congenital bilateral hip dysplasia, carpal coalitions, and scoliosis. We now report segregation of this variant in five probands from the initial clinical report defining the syndrome and an additional family of Puerto Rican descent with multiple affected adult individuals. We modeled the orthologous variant in murine Col27a1 and found it recapitulates some of the major Steel syndrome associated skeletal features including reduced body length, scoliosis, and a more rounded skull shape. Characterization of the in vivo murine model shows abnormal collagen deposition in the extracellular matrix and disorganization of the proliferative zone of the growth plate. We report additional COL27A1 pathogenic variant alleles identified in unrelated consanguineous Turkish kindreds suggesting Clan Genomics and identity-by-descent homozygosity contributing to disease in this population. The hypothesis that carrier states for this autosomal recessive osteochondrodysplasia may contribute to common complex traits is further explored in a large clinical population cohort. Our findings augment our understanding of COL27A1 biology and its role in skeletal development; and expand the functional allelic architecture in this gene underlying both rare and common disease phenotypes.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Bone Development; Child; Child, Preschool; Consanguinity; Extracellular Matrix; Female; Fibrillar Collagens; Founder Effect; Gene Frequency; Hip Dislocation; Homozygote; Humans; Male; Mice; Mice, Inbred C57BL; Mutation; Pedigree; Scoliosis; Syndrome

Genetics of schizophrenia in the South African Xhosa. - Gulsuner, S; Stein, D J; Susser, E S; Sibeko, G; Pretorius, A; Walsh, T; Majara, L; Mndini, M M; Mqulwana, S G; Ntola, O A; Casadei, S; Ngqengelele, L L; et al. (Science, 2020)
Africa, the ancestral home of all modern humans, is the most informative continent for understanding the human genome and its contribution to complex disease. To better understand the genetics of schizophrenia, we studied the illness in the Xhosa population of South Africa, recruiting 909 cases and 917 age-, gender-, and residence-matched controls. Individuals with schizophrenia were significantly more likely than controls to harbor private, severely damaging mutations in genes that are critical to synaptic function, including neural circuitry mediated by the neurotransmitters glutamine, γ-aminobutyric acid, and dopamine. Schizophrenia is genetically highly heterogeneous, involving severe ultrarare mutations in genes that are critical to synaptic plasticity. The depth of genetic variation in Africa revealed this relationship with a moderate sample size and informed our understanding of the genetics of schizophrenia worldwide.
Keywords: Age Factors; Autistic Disorder; Bipolar Disorder; Dopamine; Female; gamma-Aminobutyric Acid; Genetic Variation; Glutamine; Humans; Male; Mutation; Neural Pathways; Schizophrenia; Sex Factors; South Africa; Synapses; Synaptic Transmission

Genome sequencing analysis of a family with a child displaying severe abdominal distention and recurrent hypoglycemia. - Liu, Jidong; Ding, Guolian; Zou, Kexin; Jiang, Ziru; Zhang, Junyu; Lu, Yunhua; Pignata, Antonella; Eric Venner; Liu, Pengfei; Liu, Zhandong; Wangler, Michael F; Sun, Zheng (Mol Genet Genomic Med, 2020)
BACKGROUND: Germline mutations in PTEN are associated with the PTEN hamartoma tumor syndrome (PHTS), an umbrella term used to describe a spectrum of autosomal-dominant disorders characterized by variable phenotypic manifestations associated with cell or tissue overgrowth. We report a boy who developed severe progressive abdominal distention due to a dramatic adipose mass from the age of 7 months and developed recurrent hypoinsulinemic hypoglycemia that led to seizures at the age of 4 years. METHODS: Trio-based whole-genome sequencing was performed by using blood DNA from the child and his parents. The possible pathogenic variants were verified by Sanger sequencing. Functional characterization of the identified variant was completed by western blot. RESULTS: The child inherited a single-nucleotide deletion NM_000314.6:c.849delA (p.Glu284Argfs) in the tumor suppressor gene PTEN from his father. The paternal family members have a history of cancer. It is conceivable that PTEN loss-of-function induced the adipose tumor growth and hypoglycemia, although the proband did not meet the usual diagnosis criteria of Cowden syndrome or Bannayan-Riley-Ruvalcaba syndrome that are characterized by germline mutations of PTEN. CONCLUSION: This case underlines the variability of phenotypes associated with PTEN germline mutations and provides useful information for diagnosis and genetic counseling of PTEN-related diseases for pediatric patients.
Keywords: Abdominal Neoplasms; Child, Preschool; Humans; Hypoglycemia; Loss of Function Mutation; Male; Neoplasms, Adipose Tissue; Pedigree; Phenotype; PTEN Phosphohydrolase; Seizures; Syndrome

High-depth African genomes inform human migration and health. - Choudhury, Ananyo; Aron, Shaun; Botigué, Laura R; Sengupta, Dhriti; Botha, Gerrit; Bensellak, Taoufik; Wells, Gordon; Kumuthini, Judit; Shriner, Daniel; Fakim, Yasmina J; Ghoorah, Anisah W; Dareng, Eileen; et al. (Nature, 2020)
The African continent is regarded as the cradle of modern humans and African genomes contain more genetic variation than those from any other continent, yet only a fraction of the genetic diversity among African individuals has been surveyed. Here we performed whole-genome sequencing analyses of 426 individuals-comprising 50 ethnolinguistic groups, including previously unsampled populations-to explore the breadth of genomic diversity across Africa. We uncovered more than 3 million previously undescribed variants, most of which were found among individuals from newly sampled ethnolinguistic groups, as well as 62 previously unreported loci that are under strong selection, which were predominantly found in genes that are involved in viral immunity, DNA repair and metabolism. We observed complex patterns of ancestral admixture and putative-damaging and novel variation, both within and between populations, alongside evidence that Zambia was a likely intermediate site along the routes of expansion of Bantu-speaking populations. Pathogenic variants in genes that are currently characterized as medically relevant were uncommon-but in other genes, variants denoted as 'likely pathogenic' in the ClinVar database were commonly observed. Collectively, these findings refine our current understanding of continental migration, identify gene flow and the response to human disease as strong drivers of genome-level population variation, and underscore the scientific imperative for a broader characterization of the genomic diversity of African individuals to understand human ancestry and improve health.
Keywords: Africa; Datasets as Topic; DNA Repair; Female; Gene Flow; Genetic Variation; Genetics, Medical; Genetics, Population; Genome, Human; Genomics; Health; History, Ancient; Human Migration; Humans; Immunity; Language; Male; Metabolism; Selection, Genetic; Whole Genome Sequencing

Human NK cell deficiency as a result of biallelic mutations in MCM10. - Mace, Emily M; Paust, Silke; Conte, Matilde I; Baxley, Ryan M; Schmit, Megan M; Patil, Sagar L; Guilz, Nicole C; Mukherjee, Malini; Pezzi, Ashley E; Chmielowiec, Jolanta; Tatineni, Swetha; Chinn, Ivan K; et al. (J Clin Invest, 2020)
Human natural killer cell deficiency (NKD) arises from inborn errors of immunity that lead to impaired NK cell development, function, or both. Through the understanding of the biological perturbations in individuals with NKD, requirements for the generation of terminally mature functional innate effector cells can be elucidated. Here, we report a cause of NKD resulting from compound heterozygous mutations in minichromosomal maintenance complex member 10 (MCM10) that impaired NK cell maturation in a child with fatal susceptibility to CMV. MCM10 has not been previously associated with monogenic disease and plays a critical role in the activation and function of the eukaryotic DNA replisome. Through evaluation of patient primary fibroblasts, modeling patient mutations in fibroblast cell lines, and MCM10 knockdown in human NK cell lines, we have shown that loss of MCM10 function leads to impaired cell cycle progression and induction of DNA damage-response pathways. By modeling MCM10 deficiency in primary NK cell precursors, including patient-derived induced pluripotent stem cells, we further demonstrated that MCM10 is required for NK cell terminal maturation and acquisition of immunological system function. Together, these data define MCM10 as an NKD gene and provide biological insight into the requirement for the DNA replisome in human NK cell maturation and function.
Keywords: Alleles; Cell Cycle Checkpoints; Cell Differentiation; Cell Line; Codon, Nonsense; DNA Damage; Fatal Outcome; Female; Gene Knockdown Techniques; Heterozygote; Humans; Induced Pluripotent Stem Cells; Infant; Killer Cells, Natural; Male; Minichromosome Maintenance Proteins; Models, Immunological; Mutation; Mutation, Missense; Pedigree; Primary Immunodeficiency Diseases

Identification of novel fusion transcripts in meningioma. - Khan, A Basit; Gadot, Ron; Shetty, Arya; Bayley, James C; Hadley, Caroline C; Cardenas, Maria F; Jalali, Ali; Harmanci, Akdes S; Harmanci, Arif O; David A Wheeler; Klisch, Tiemo J; Patel, Akash J (J Neurooncol, 2020)
INTRODUCTION: Meningiomas are the most common primary intracranial tumor. Recent next generation sequencing analyses have elaborated the molecular drivers of this disease. We aimed to identify and characterize novel fusion genes in meningiomas. METHODS: We performed a secondary analysis of our RNA sequencing data of 145 primary meningioma from 140 patients to detect fusion genes. Semi-quantitative rt-PCR was performed to confirm transcription of the fusion genes in the original tumors. Whole exome sequencing was performed to identify copy number variations within each tumor sample. Comparative RNA seq analysis was performed to assess the clonality of the fusion constructs within the tumor. RESULTS: We detected six fusion events (NOTCH3-SETBP1, NF2-SPATA13, SLC6A3-AGBL3, PHF19-FOXP2 in two patients, and ITPK1-FBP2) in five out of 145 tumor samples. All but one event (NF2-SPATA13) led to extremely short reading frames, making these events de facto null alleles. Three of the five patients had a history of childhood radiation. Four out of six fusion events were detected in expression type C tumors, which represent the most aggressive meningioma. We validated the presence of the RNA transcripts in the tumor tissue by semi-quantitative RT PCR. All but the two PHF19-FOXP2 fusions demonstrated high degrees of clonality. CONCLUSIONS: Fusion genes occur infrequently in meningiomas and are more likely to be found in tumors with greater degree of genomic instability (expression type C) or in patients with history of cranial irradiation.
Keywords: Adult; Aged; Biomarkers, Tumor; Cohort Studies; Female; Follow-Up Studies; High-Throughput Nucleotide Sequencing; Humans; Male; Meningeal Neoplasms; Meningioma; Middle Aged; Mutation; Oncogene Proteins, Fusion; Prognosis

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.
Keywords: Adult; Africa; Aged; Aged, 80 and over; alpha Karyopherins; Black People; Cell Self Renewal; Clonal Hematopoiesis; Dioxygenases; DNA-Binding Proteins; Female; Genetic Predisposition to Disease; Genome, Human; Germ-Line Mutation; Hematopoietic Stem Cells; Humans; Intracellular Signaling Peptides and Proteins; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Precision Medicine; Proto-Oncogene Proteins; Tripartite Motif Proteins; United States; Whole Genome Sequencing

Knockout of mouse receptor accessory protein 6 leads to sperm function and morphology defects†. - Devlin, Darius J; Agrawal Zaneveld, Smriti; Nozawa, Kaori; Han, Xiao; Moye, Abigail R; Liang, Qingnan; Harnish, Jacob Michael; Matzuk, Martin M; Rui Chen (Biol Reprod, 2020)
Receptor accessory protein 6 (REEP6) is a member of the REEP/Ypt-interacting protein family that we recently identified as essential for normal endoplasmic reticulum homeostasis and protein trafficking in the retina of mice and humans. Interestingly, in addition to the loss of REEP6 in our knockout (KO) mouse model recapitulating the retinal degeneration of humans with REEP6 mutations causing retinitis pigmentosa (RP), we also found that male mice are sterile. Herein, we characterize the infertility caused by loss of Reep6. Expression of both Reep6 mRNA transcripts is present in the testis; however, isoform 1 becomes overexpressed during spermiogenesis. In vitro fertilization assays reveal that Reep6 KO spermatozoa are able to bind the zona pellucida but are only able to fertilize oocytes lacking the zona pellucida. Although spermatogenesis appears normal in KO mice, cauda epididymal spermatozoa have severe motility defects and variable morphological abnormalities, including bent or absent tails. Immunofluorescent staining reveals that REEP6 expression first appears in stage IV tubules within step 15 spermatids, and REEP6 localizes to the connecting piece, midpiece, and annulus of mature spermatozoa. These data reveal an important role for REEP6 in sperm motility and morphology and is the first reported function for a REEP protein in reproductive processes. Additionally, this work identifies a new gene potentially responsible for human infertility and has implications for patients with RP harboring mutations in REEP6.
Keywords: Animals; Eye Proteins; Gene Expression Regulation; Infertility, Male; Male; Membrane Proteins; Mice; Mice, Knockout; Mutation; RNA, Messenger; Spermatozoa

Mapping and characterization of structural variation in 17,795 human genomes. - Abel, Haley J; Larson, David E; Regier, Allison A; Chiang, Colby; Das, Indraniel; Kanchi, Krishna L; Layer, Ryan M; Neale, Benjamin M; Salerno, William J; Reeves, Catherine; Buyske, Steven; Matise, Tara C; et al. (Nature, 2020)
A key goal of whole-genome sequencing for studies of human genetics is to interrogate all forms of variation, including single-nucleotide variants, small insertion or deletion (indel) variants and structural variants. However, tools and resources for the study of structural variants have lagged behind those for smaller variants. Here we used a scalable pipeline to map and characterize structural variants in 17,795 deeply sequenced human genomes. We publicly release site-frequency data to create the largest, to our knowledge, whole-genome-sequencing-based structural variant resource so far. On average, individuals carry 2.9 rare structural variants that alter coding regions; these variants affect the dosage or structure of 4.2 genes and account for 4.0-11.2% of rare high-impact coding alleles. Using a computational model, we estimate that structural variants account for 17.2% of rare alleles genome-wide, with predicted deleterious effects that are equivalent to loss-of-function coding alleles; approximately 90% of such structural variants are noncoding deletions (mean 19.1 per genome). We report 158,991 ultra-rare structural variants and show that 2% of individuals carry ultra-rare megabase-scale structural variants, nearly half of which are balanced or complex rearrangements. Finally, we infer the dosage sensitivity of genes and noncoding elements, and reveal trends that relate to element class and conservation. This work will help to guide the analysis and interpretation of structural variants in the era of whole-genome sequencing.
Keywords: Alleles; Case-Control Studies; Epigenesis, Genetic; Female; Gene Dosage; Genetic Variation; Genetics, Population; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Molecular Sequence Annotation; Quantitative Trait Loci; Racial Groups; Software; Whole Genome Sequencing

Mapping the -regulatory architecture of the human retina reveals noncoding genetic variation in disease. - Cherry, Timothy J; Yang, Marty G; Harmin, David A; Tao, Peter; Timms, Andrew E; Bauwens, Miriam; Allikmets, Rando; Jones, Evan M; Rui Chen; De Baere, Elfride; Greenberg, Michael E (Proc Natl Acad Sci U S A, 2020)
The interplay of transcription factors and -regulatory elements (CREs) orchestrates the dynamic and diverse genetic programs that assemble the human central nervous system (CNS) during development and maintain its function throughout life. Genetic variation within CREs plays a central role in phenotypic variation in complex traits including the risk of developing disease. We took advantage of the retina, a well-characterized region of the CNS known to be affected by pathogenic variants in CREs, to establish a roadmap for characterizing regulatory variation in the human CNS. This comprehensive analysis of tissue-specific regulatory elements, transcription factor binding, and gene expression programs in three regions of the human visual system (retina, macula, and retinal pigment epithelium/choroid) reveals features of regulatory element evolution that shape tissue-specific gene expression programs and defines regulatory elements with the potential to contribute to Mendelian and complex disorders of human vision.
Keywords: Adult; Animals; DNA Mutational Analysis; Epigenomics; Evolution, Molecular; Female; Gene Expression Regulation, Developmental; Genetic Variation; Humans; Male; Mice; Middle Aged; Mutation; Regulatory Sequences, Nucleic Acid; Retina; Retinal Diseases; RNA-Seq; Species Specificity

A Mendelian randomization of γ' and total fibrinogen levels in relation to venous thromboembolism and ischemic stroke. - Maners, Jillian; Gill, Dipender; Pankratz, Nathan; Laffan, Michael A; Wolberg, Alisa S; de Maat, Moniek P M; Ligthart, Symen; Tang, Weihong; Ward-Caviness, Cavin K; Fornage, Myriam; Debette, Stephanie; Dichgans, Martin; et al. (Blood, 2020)
Fibrinogen is a key component of the coagulation cascade, and variation in its circulating levels may contribute to thrombotic diseases, such as venous thromboembolism (VTE) and ischemic stroke. Gamma prime (γ') fibrinogen is an isoform of fibrinogen that has anticoagulant properties. We applied 2-sample Mendelian randomization (MR) to estimate the causal effect of total circulating fibrinogen and its isoform, γ' fibrinogen, on risk of VTE and ischemic stroke subtypes using summary statistics from genome-wide association studies. Genetic instruments for γ' fibrinogen and total fibrinogen were selected, and the inverse-variance weighted MR approach was used to estimate causal effects in the main analysis, complemented by sensitivity analyses that are more robust to the inclusion of pleiotropic variants, including MR-Egger, weighted median MR, and weighted mode MR. The main inverse-variance weighted MR estimates based on a combination of 16 genetic instruments for γ' fibrinogen and 75 genetic instruments for total fibrinogen indicated a protective effect of higher γ' fibrinogen and higher total fibrinogen on VTE risk. There was also a protective effect of higher γ' fibrinogen levels on cardioembolic and large artery stroke risk. Effect estimates were consistent across sensitivity analyses. Our results provide evidence to support effects of genetically determined γ' fibrinogen on VTE and ischemic stroke risk. Further research is needed to explore mechanisms underlying these effects and their clinical applications.
Keywords: Female; Fibrinogen; Genetic Variation; Genome-Wide Association Study; Humans; Ischemic Stroke; Male; Mendelian Randomization Analysis; Risk Factors; Venous Thromboembolism

Mutations in ASH1L confer susceptibility to Tourette syndrome. - Liu, Shiguo; Tian, Miaomiao; He, Fan; Li, Jiani; Xie, Hong; Liu, Wenmiao; Zhang, Yeting; Zhang, Ru; Yi, Mingji; Che, Fengyuan; Ma, Xu; Zheng, Yi; et al. (Mol Psychiatry, 2020)
Tourette syndrome (TS) is a childhood-onset neuropsychiatric disorder characterized by repetitive motor movements and vocal tics. The clinical manifestations of TS are complex and often overlap with other neuropsychiatric disorders. TS is highly heritable; however, the underlying genetic basis and molecular and neuronal mechanisms of TS remain largely unknown. We performed whole-exome sequencing of a hundred trios (probands and their parents) with detailed records of their clinical presentations and identified a risk gene, ASH1L, that was both de novo mutated and associated with TS based on a transmission disequilibrium test. As a replication, we performed follow-up targeted sequencing of ASH1L in additional 524 unrelated TS samples and replicated the association (P value = 0.001). The point mutations in ASH1L cause defects in its enzymatic activity. Therefore, we established a transgenic mouse line and performed an array of anatomical, behavioral, and functional assays to investigate ASH1L function. The Ash1l mice manifested tic-like behaviors and compulsive behaviors that could be rescued by the tic-relieving drug haloperidol. We also found that Ash1l disruption leads to hyper-activation and elevated dopamine-releasing events in the dorsal striatum, all of which could explain the neural mechanisms for the behavioral abnormalities in mice. Taken together, our results provide compelling evidence that ASH1L is a TS risk gene.
Keywords: Adolescent; Adult; Animals; Child; Child, Preschool; China; DNA-Binding Proteins; Exome Sequencing; Family; Female; Genetic Predisposition to Disease; Histone-Lysine N-Methyltransferase; Humans; Male; Mice; Mice, Transgenic; Middle Aged; Mutation; Parents; Tic Disorders; Tourette Syndrome; Transcription Factors

NEMF mutations that impair ribosome-associated quality control are associated with neuromuscular disease. - Martin, Paige B; Kigoshi-Tansho, Yu; Sher, Roger B; Ravenscroft, Gianina; Stauffer, Jennifer E; Kumar, Rajesh; Yonashiro, Ryo; Müller, Tina; Griffith, Christopher; Allen, William; Pehlivan, Davut; Harel, Tamar; et al. (Nat Commun, 2020)
A hallmark of neurodegeneration is defective protein quality control. The E3 ligase Listerin (LTN1/Ltn1) acts in a specialized protein quality control pathway-Ribosome-associated Quality Control (RQC)-by mediating proteolytic targeting of incomplete polypeptides produced by ribosome stalling, and Ltn1 mutation leads to neurodegeneration in mice. Whether neurodegeneration results from defective RQC and whether defective RQC contributes to human disease have remained unknown. Here we show that three independently-generated mouse models with mutations in a different component of the RQC complex, NEMF/Rqc2, develop progressive motor neuron degeneration. Equivalent mutations in yeast Rqc2 selectively interfere with its ability to modify aberrant translation products with C-terminal tails which assist with RQC-mediated protein degradation, suggesting a pathomechanism. Finally, we identify NEMF mutations expected to interfere with function in patients from seven families presenting juvenile neuromuscular disease. These uncover NEMF's role in translational homeostasis in the nervous system and implicate RQC dysfunction in causing neurodegeneration.
Keywords: Amino Acid Sequence; Animals; Female; Humans; Male; Mice; Mice, Knockout; Mutation; Neuromuscular Diseases; Proteolysis; Ribosomes; RNA-Binding Proteins; Saccharomyces cerevisiae; Saccharomyces cerevisiae Proteins; Sequence Alignment

Next Generation Sequencing of 134 Children with Autism Spectrum Disorder and Regression. - Yin, Jiani; Chun, Chun-An; Zavadenko, Nikolay N; Pechatnikova, Natalia L; Naumova, Oxana Yu; Harshavardhan Doddapaneni; Jianhong Hu; Donna M Muzny; Schaaf, Christian P; Grigorenko, Elena L (Genes (Basel), 2020)
Approximately 30% of individuals with autism spectrum disorder (ASD) experience developmental regression, the etiology of which remains largely unknown. We performed a complete literature search and identified 47 genes that had been implicated in such cases. We sequenced these genes in a preselected cohort of 134 individuals with regressive autism. In total, 16 variants in 12 genes with evidence supportive of pathogenicity were identified. They were classified as variants of uncertain significance based on ACMG standards and guidelines. Among these were recurring variants in and , variants in genes that were linked to syndromic forms of ASD (, , , , , and ), and variants in the form of oligogenic heterozygosity (, , and ).
Keywords: Autism Spectrum Disorder; Child; Child, Preschool; Cohort Studies; Disease Progression; Female; Gene Expression Regulation; Genetic Markers; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Infant; Male; Mutation

Parental somatic mosaicism for CNV deletions - A need for more sensitive and precise detection methods in clinical diagnostics settings. - Liu, Qian; Karolak, Justyna A; Grochowski, Christopher M; Wilson, Theresa A; Rosenfeld, Jill A; Bacino, Carlos A; Lalani, Seema R; Patel, Ankita; Breman, Amy; Smith, Janice L; Cheung, Sau Wai; James R Lupski; et al. (Genomics, 2020)
To further assess the scale and level of parental somatic mosaicism, we queried the CMA database at Baylor Genetics. We selected 50 unrelated families where clinically relevant apparent de novo CNV-deletions were found in the affected probands. Parental blood samples screening using deletion junction-specific PCR revealed four parents with somatic mosaicism. Droplet digital PCR (ddPCR), qPCR, and amplicon-based next-generation sequencing (NGS) were applied to validate these findings. Using ddPCR levels of mosaicism ranged from undetectable to 18.5%. Amplicon-based NGS and qPCR for the father with undetectable mosaicism was able to detect mosaicism at 0.39%. In one mother, ddPCR analysis revealed 15.6%, 10.6%, 8.2%, and undetectable levels of mosaicism in her blood, buccal cells, saliva, and urine samples, respectively. Our data suggest that more sensitive and precise methods, e.g. CNV junction-specific LR-PCR, ddPCR, or qPCR may allow for a more refined assessment of the potential disease recurrence risk for an identified variant.
Keywords: Clinical Laboratory Techniques; DNA Copy Number Variations; Female; High-Throughput Nucleotide Sequencing; Humans; Inheritance Patterns; Male; Mosaicism; Polymerase Chain Reaction; Sequence Analysis, DNA

Paternal age in rhesus macaques is positively associated with germline mutation accumulation but not with measures of offspring sociability. - Wang, Richard J; Thomas, Gregg W C; Raveendran, Muthuswamy; R. Alan Harris; Harshavardhan Doddapaneni; Donna M Muzny; Capitanio, John P; Radivojac, Predrag; Jeffrey Rogers; Hahn, Matthew W (Genome Res, 2020)
Mutation is the ultimate source of all genetic novelty and the cause of heritable genetic disorders. Mutational burden has been linked to complex disease, including neurodevelopmental disorders such as schizophrenia and autism. The rate of mutation is a fundamental genomic parameter and direct estimates of this parameter have been enabled by accurate comparisons of whole-genome sequences between parents and offspring. Studies in humans have revealed that the paternal age at conception explains most of the variation in mutation rate: Each additional year of paternal age in humans leads to approximately 1.5 additional inherited mutations. Here, we present an estimate of the de novo mutation rate in the rhesus macaque () using whole-genome sequence data from 32 individuals in four large pedigrees. We estimated an average mutation rate of 0.58 × 10 per base pair per generation (at an average parental age of 7.5 yr), much lower than found in direct estimates from great apes. As in humans, older macaque fathers transmit more mutations to their offspring, increasing the per generation mutation rate by 4.27 × 10 per base pair per year. We found that the rate of mutation accumulation after puberty is similar between macaques and humans, but that a smaller number of mutations accumulate before puberty in macaques. We additionally investigated the role of paternal age on offspring sociability, a proxy for normal neurodevelopment, by studying 203 male macaques in large social groups.
Keywords: Age Factors; Animals; Behavior, Animal; Female; Germ-Line Mutation; Humans; Macaca mulatta; Male; Mutation Accumulation; Mutation Rate; Paternal Age; Pregnancy; Prenatal Exposure Delayed Effects; Social Skills; Species Specificity

Phenotypic expansion in KIF1A-related dominant disorders: A description of novel variants and review of published cases. - Montenegro-Garreaud, Ximena; Hansen, Adam W; Khayat, Michael M; Chander, Varuna; Grochowski, Christopher M; Jiang, Yunyun; Li, He; Mitani, Tadahiro; Kessler, Elena; Jayaseelan, Joy; Shen, Hua; Gezdirici, Alper; et al. (Hum Mutat, 2020)
KIF1A is a molecular motor for membrane-bound cargo important to the development and survival of sensory neurons. KIF1A dysfunction has been associated with several Mendelian disorders with a spectrum of overlapping phenotypes, ranging from spastic paraplegia to intellectual disability. We present a novel pathogenic in-frame deletion in the KIF1A molecular motor domain inherited by two affected siblings from an unaffected mother with apparent germline mosaicism. We identified eight additional cases with heterozygous, pathogenic KIF1A variants ascertained from a local data lake. Our data provide evidence for the expansion of KIF1A-associated phenotypes to include hip subluxation and dystonia as well as phenotypes observed in only a single case: gelastic cataplexy, coxa valga, and double collecting system. We review the literature and suggest that KIF1A dysfunction is better understood as a single neuromuscular disorder with variable involvement of other organ systems than a set of discrete disorders converging at a single locus.
Keywords: Child; Child, Preschool; Family; Female; Genes, Dominant; Genetic Predisposition to Disease; Humans; Kinesins; Male; Mutation; Pedigree; Peru; Phenotype

Phenotypic expansion of POGZ-related intellectual disability syndrome (White-Sutton syndrome). - Assia Batzir, Nurit; Posey, Jennifer E; Song, Xiaofei; Akdemir, Zeynep Coban; Rosenfeld, Jill A; Brown, Chester W; Chen, Emily; Holtrop, Shannon G; Mizerik, Elizabeth; Nieto Moreno, Margarita; Payne, Katelyn; Raas-Rothschild, Annick; et al. (Am J Med Genet A, 2020)
White-Sutton syndrome (WHSUS) is a recently-identified genetic disorder resulting from de novo heterozygous pathogenic variants in POGZ. Thus far, over 50 individuals have been reported worldwide, however phenotypic characterization and data regarding the natural history are still incomplete. Here we report the clinical features of 22 individuals with 21 unique loss of function POGZ variants. We observed a broad spectrum of intellectual disability and/or developmental delay with or without autism, and speech delay in all individuals. Other common problems included ocular abnormalities, hearing loss and gait abnormalities. A validated sleep disordered breathing questionnaire identified symptoms of obstructive sleep apnea in 4/12 (33%) individuals. A higher-than-expected proportion of cases also had gastrointestinal phenotypes, both functional and anatomical, as well as genitourinary anomalies. In line with previous publications, we observed an increased body mass index (BMI) z-score compared to the general population (mean 0.59, median 0.9; p 0.0253). Common facial features included microcephaly, broad forehead, midface hypoplasia, triangular mouth, broad nasal root and flat nasal bridge. Analysis of the Baylor Genetics clinical laboratory database revealed that POGZ variants were implicated in approximately 0.14% of cases who underwent clinical exome sequencing for neurological indications with or without involvement of other body systems. This study describes a greater allelic series and expands the phenotypic spectrum of this new syndromic form of intellectual disability and autism.
Keywords: Adolescent; Adult; Autistic Disorder; Child; Child, Preschool; Exome; Exome Sequencing; Female; Heterozygote; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Microcephaly; Middle Aged; Mutation; Phenotype; Transposases; Young Adult

Recurrent arginine substitutions in the ACTG2 gene are the primary driver of disease burden and severity in visceral myopathy. - Assia Batzir, Nurit; Kishor Bhagwat, Pranjali; Larson, Austin; Coban Akdemir, Zeynep; Bagłaj, Maciej; Bofferding, Leon; Bosanko, Katherine B; Bouassida, Skander; Callewaert, Bert; Cannon, Ashley; Enchautegui Colon, Yazmin; Garnica, Adolfo D; et al. (Hum Mutat, 2020)
Visceral myopathy with abnormal intestinal and bladder peristalsis includes a clinical spectrum with megacystis-microcolon intestinal hypoperistalsis syndrome and chronic intestinal pseudo-obstruction. The vast majority of cases are caused by dominant variants in ACTG2; however, the overall genetic architecture of visceral myopathy has not been well-characterized. We ascertained 53 families, with visceral myopathy based on megacystis, functional bladder/gastrointestinal obstruction, or microcolon. A combination of targeted ACTG2 sequencing and exome sequencing was used. We report a molecular diagnostic rate of 64% (34/53), of which 97% (33/34) is attributed to ACTG2. Strikingly, missense mutations in five conserved arginine residues involving CpG dinucleotides accounted for 49% (26/53) of disease in the cohort. As a group, the ACTG2-negative cases had a more favorable clinical outcome and more restricted disease. Within the ACTG2-positive group, poor outcomes (characterized by total parenteral nutrition dependence, death, or transplantation) were invariably due to one of the arginine missense alleles. Analysis of specific residues suggests a severity spectrum of p.Arg178>p.Arg257>p.Arg40 along with other less-frequently reported sites p.Arg63 and p.Arg211. These results provide genotype-phenotype correlation for ACTG2-related disease and demonstrate the importance of arginine missense changes in visceral myopathy.
Keywords: Abnormalities, Multiple; Actins; Adult; Amino Acid Substitution; Arginine; Colon; DNA Mutational Analysis; Exome Sequencing; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Intestinal Pseudo-Obstruction; Male; Molecular Diagnostic Techniques; Mutation; Phenotype; Urinary Bladder; Young Adult

Recurrent De Novo NAHR Reciprocal Duplications in the ATAD3 Gene Cluster Cause a Neurogenetic Trait with Perturbed Cholesterol and Mitochondrial Metabolism. - Gunning, Adam C; Strucinska, Klaudia; Muñoz Oreja, Mikel; Parrish, Andrew; Caswell, Richard; Stals, Karen L; Durigon, Romina; Durlacher-Betzer, Karina; Cunningham, Mitchell H; Grochowski, Christopher M; Baptista, Julia; Tysoe, Carolyn; et al. (Am J Hum Genet, 2020)
Recent studies have identified both recessive and dominant forms of mitochondrial disease that result from ATAD3A variants. The recessive form includes subjects with biallelic deletions mediated by non-allelic homologous recombination. We report five unrelated neonates with a lethal metabolic disorder characterized by cardiomyopathy, corneal opacities, encephalopathy, hypotonia, and seizures in whom a monoallelic reciprocal duplication at the ATAD3 locus was identified. Analysis of the breakpoint junction fragment indicated that these 67 kb heterozygous duplications were likely mediated by non-allelic homologous recombination at regions of high sequence identity in ATAD3A exon 11 and ATAD3C exon 7. At the recombinant junction, the duplication allele produces a fusion gene derived from ATAD3A and ATAD3C, the protein product of which lacks key functional residues. Analysis of fibroblasts derived from two affected individuals shows that the fusion gene product is expressed and stable. These cells display perturbed cholesterol and mitochondrial DNA organization similar to that observed for individuals with severe ATAD3A deficiency. We hypothesize that the fusion protein acts through a dominant-negative mechanism to cause this fatal mitochondrial disorder. Our data delineate a molecular diagnosis for this disorder, extend the clinical spectrum associated with structural variation at the ATAD3 locus, and identify a third mutational mechanism for ATAD3 gene cluster variants. These results further affirm structural variant mutagenesis mechanisms in sporadic disease traits, emphasize the importance of copy number analysis in molecular genomic diagnosis, and highlight some of the challenges of detecting and interpreting clinically relevant rare gene rearrangements from next-generation sequencing data.
Keywords: Amino Acid Sequence; ATPases Associated with Diverse Cellular Activities; Brain Diseases; Cardiomyopathies; Cholesterol; Corneal Opacity; DNA Copy Number Variations; Female; Gene Duplication; Gene Rearrangement; Homologous Recombination; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Diseases; Mitochondrial Proteins; Muscle Hypotonia; Mutation; Protein Conformation; Seizures; Sequence Homology

Role of Rare and Low-Frequency Variants in Gene-Alcohol Interactions on Plasma Lipid Levels. - Wang, Zhe; Chen, Han; Bartz, Traci M; Bielak, Lawrence F; Chasman, Daniel I; Feitosa, Mary F; Franceschini, Nora; Guo, Xiuqing; Lim, Elise; Noordam, Raymond; Richard, Melissa A; Wang, Heming; et al. (Circ Genom Precis Med, 2020)
BACKGROUND: Alcohol intake influences plasma lipid levels, and such effects may be moderated by genetic variants. We aimed to characterize the role of aggregated rare and low-frequency protein-coding variants in gene by alcohol consumption interactions associated with fasting plasma lipid levels. METHODS: In the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, fasting plasma triglycerides and high- and low-density lipoprotein cholesterol were measured in 34 153 individuals with European ancestry from 5 discovery studies and 32 277 individuals from 6 replication studies. Rare and low-frequency functional protein-coding variants (minor allele frequency, ≤5%) measured by an exome array were aggregated by genes and evaluated by a gene-environment interaction test and a joint test of genetic main and gene-environment interaction effects. Two dichotomous self-reported alcohol consumption variables, current drinker, defined as any recurrent drinking behavior, and regular drinker, defined as the subset of current drinkers who consume at least 2 drinks per week, were considered. RESULTS: We discovered and replicated 21 gene-lipid associations at 13 known lipid loci through the joint test. Eight loci (, , , , , , , and ) remained significant after conditioning on the common index single-nucleotide polymorphism identified by previous genome-wide association studies, suggesting an independent role for rare and low-frequency variants at these loci. One significant gene-alcohol interaction on triglycerides in a novel locus was significantly discovered (=6.65×10 for the interaction test) and replicated at nominal significance level (=0.013) in . CONCLUSIONS: In conclusion, this study applied new gene-based statistical approaches and suggested that rare and low-frequency genetic variants interacted with alcohol consumption on lipid levels.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Apolipoproteins E; Cholesterol, HDL; Female; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Humans; Lipids; Male; Middle Aged; Polymorphism, Single Nucleotide; Proprotein Convertase 9; Triglycerides; White People; Young Adult

Sawfly Genomes Reveal Evolutionary Acquisitions That Fostered the Mega-Radiation of Parasitoid and Eusocial Hymenoptera. - Oeyen, Jan Philip; Baa-Puyoulet, Patrice; Benoit, Joshua B; Beukeboom, Leo W; Bornberg-Bauer, Erich; Buttstedt, Anja; Calevro, Federica; Cash, Elizabeth I; Chao, Hsu; Charles, Hubert; Chen, Mei-Ju May; Childers, Christopher; et al. (Genome Biol Evol, 2020)
The tremendous diversity of Hymenoptera is commonly attributed to the evolution of parasitoidism in the last common ancestor of parasitoid sawflies (Orussidae) and wasp-waisted Hymenoptera (Apocrita). However, Apocrita and Orussidae differ dramatically in their species richness, indicating that the diversification of Apocrita was promoted by additional traits. These traits have remained elusive due to a paucity of sawfly genome sequences, in particular those of parasitoid sawflies. Here, we present comparative analyses of draft genomes of the primarily phytophagous sawfly Athalia rosae and the parasitoid sawfly Orussus abietinus. Our analyses revealed that the ancestral hymenopteran genome exhibited traits that were previously considered unique to eusocial Apocrita (e.g., low transposable element content and activity) and a wider gene repertoire than previously thought (e.g., genes for CO2 detection). Moreover, we discovered that Apocrita evolved a significantly larger array of odorant receptors than sawflies, which could be relevant to the remarkable diversification of Apocrita by enabling efficient detection and reliable identification of hosts.
Keywords: Amino Acid Sequence; Animals; Conserved Sequence; DNA Transposable Elements; Female; Gene Dosage; Genetic Speciation; Genome, Insect; Glycoproteins; Herbivory; Host-Parasite Interactions; Hymenoptera; Immunity; Insect Proteins; Male; Multigene Family; Receptors, Odorant; Social Behavior; Vision, Ocular

Sequence analysis in reveals pervasiveness of X-Y arms races in mammalian lineages. - Hughes, Jennifer F; Skaletsky, Helen; Pyntikova, Tatyana; Koutseva, Natalia; Raudsepp, Terje; Brown, Laura G; Bellott, Daniel W; Cho, Ting-Jan; Dugan-Rocha, Shannon; Ziad Khan; Kremitzki, Colin; Fronick, Catrina; et al. (Genome Res, 2020)
Studies of Y Chromosome evolution have focused primarily on gene decay, a consequence of suppression of crossing-over with the X Chromosome. Here, we provide evidence that suppression of X-Y crossing-over unleashed a second dynamic: selfish X-Y arms races that reshaped the sex chromosomes in mammals as different as cattle, mice, and men. Using super-resolution sequencing, we explore the Y Chromosome of (bull) and find it to be dominated by massive, lineage-specific amplification of testis-expressed gene families, making it the most gene-dense Y Chromosome sequenced to date. As in mice, an X-linked homolog of a bull Y-amplified gene has become testis-specific and amplified. This evolutionary convergence implies that lineage-specific X-Y coevolution through gene amplification, and the selfish forces underlying this phenomenon, were dominatingly powerful among diverse mammalian lineages. Together with Y gene decay, X-Y arms races molded mammalian sex chromosomes and influenced the course of mammalian evolution.
Keywords: Animals; Cattle; Cell Lineage; Crossing Over, Genetic; Evolution, Molecular; Female; Gene Amplification; Humans; Male; Mice; Organ Specificity; Sequence Analysis, DNA; Testis; X Chromosome; Y Chromosome

Serum sphingolipids and incident diabetes in a US population with high diabetes burden: the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). - Chen, Guo-Chong; Chai, Jin Choul; Yu, Bing; Michelotti, Gregory A; Grove, Megan L; Fretts, Amanda M; Daviglus, Martha L; Garcia-Bedoya, Olga L; Thyagarajan, Bharat; Schneiderman, Neil; Cai, Jianwen; Kaplan, Robert C; et al. (Am J Clin Nutr, 2020)
BACKGROUND: Genetic or pharmacological inhibition of de novo sphingolipid synthases prevented diabetes in animal studies. OBJECTIVES: We sought to evaluate prospective associations of serum sphingolipids with incident diabetes in a population-based cohort. METHODS: We included 2010 participants of the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) aged 18-74 y who were free of diabetes and other major chronic diseases at baseline (2008-2011). Metabolomic profiling of fasting serum was performed using a global, untargeted approach. A total of 43 sphingolipids were quantified and, considering subclasses and chemical structures of individual species, 6 sphingolipid scores were constructed. Diabetes status was assessed using standard procedures including blood tests. Multivariable survey Poisson regressions were applied to estimate RR and 95% CI of incident diabetes associated with individual sphingolipids or sphingolipid scores. RESULTS: There were 224 incident cases of diabetes identified during, on average, 6 y of follow-up. After adjustment for socioeconomic and lifestyle factors, a ceramide score (RR Q4 versus Q1 = 2.40; 95% CI: 1.24, 4.65; P-trend = 0.003) and a score of sphingomyelins with fully saturated sphingoid-fatty acid pairs (RR Q4 versus Q1 = 3.15; 95% CI: 1.75, 5.67; P-trend <0.001) both were positively associated with risk of diabetes, whereas scores of glycosylceramides, lactosylceramides, or other unsaturated sphingomyelins (even if having an SFA base) were not associated with risk of diabetes. After additional adjustment for numerous traditional risk factors (especially triglycerides), both associations were attenuated and only the saturated-sphingomyelin score remained associated with risk of diabetes (RR Q4 versus Q1 = 1.98; 95% CI: 1.09, 3.59; P-trend = 0.031). CONCLUSIONS: Our findings suggest that a cluster of saturated sphingomyelins may be associated with elevated risk of diabetes beyond traditional risk factors, which needs to be verified in other population studies. This study was registered at clinicaltrials.gov as NCT02060344.
Keywords: Adolescent; Adult; Aged; Diabetes Mellitus; Female; Hispanic or Latino; Humans; Male; Middle Aged; Prospective Studies; Risk Factors; Sphingolipids; United States; Young Adult

Single-Cell Transcriptome Analysis Reveals Dynamic Cell Populations and Differential Gene Expression Patterns in Control and Aneurysmal Human Aortic Tissue. - Li, Yanming; Ren, Pingping; Dawson, Ashley; Vasquez, Hernan G; Ageedi, Waleed; Zhang, Chen; Luo, Wei; Rui Chen; Yumei Li; Kim, Sangbae; Lu, Hong S; Cassis, Lisa A; et al. (Circulation, 2020)
BACKGROUND: Ascending thoracic aortic aneurysm (ATAA) is caused by the progressive weakening and dilatation of the aortic wall and can lead to aortic dissection, rupture, and other life-threatening complications. To improve our understanding of ATAA pathogenesis, we aimed to comprehensively characterize the cellular composition of the ascending aortic wall and to identify molecular alterations in each cell population of human ATAA tissues. METHODS: We performed single-cell RNA sequencing analysis of ascending aortic tissues from 11 study participants, including 8 patients with ATAA (4 women and 4 men) and 3 control subjects (2 women and 1 man). Cells extracted from aortic tissue were analyzed and categorized with single-cell RNA sequencing data to perform cluster identification. ATAA-related changes were then examined by comparing the proportions of each cell type and the gene expression profiles between ATAA and control tissues. We also examined which genes may be critical for ATAA by performing the integrative analysis of our single-cell RNA sequencing data with publicly available data from genome-wide association studies. RESULTS: We identified 11 major cell types in human ascending aortic tissue; the high-resolution reclustering of these cells further divided them into 40 subtypes. Multiple subtypes were observed for smooth muscle cells, macrophages, and T lymphocytes, suggesting that these cells have multiple functional populations in the aortic wall. In general, ATAA tissues had fewer nonimmune cells and more immune cells, especially T lymphocytes, than control tissues did. Differential gene expression data suggested the presence of extensive mitochondrial dysfunction in ATAA tissues. In addition, integrative analysis of our single-cell RNA sequencing data with public genome-wide association study data and promoter capture Hi-C data suggested that the erythroblast transformation-specific related gene() exerts an important role in maintaining normal aortic wall function. CONCLUSIONS: Our study provides a comprehensive evaluation of the cellular composition of the ascending aortic wall and reveals how the gene expression landscape is altered in human ATAA tissue. The information from this study makes important contributions to our understanding of ATAA formation and progression.
Keywords: Aged; Aorta; Aortic Aneurysm, Thoracic; Female; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Humans; Male; Middle Aged; Single-Cell Analysis

TBX6 missense variants expand the mutational spectrum in a non-Mendelian inheritance disease. - Chen, Weisheng; Lin, Jiachen; Wang, Lianlei; Li, Xiaoxin; Zhao, Sen; Liu, Jiaqi; Akdemir, Zeynep C; Zhao, Yanxue; Du, Renqian; Ye, Yongyu; Song, Xiaofei; Zhang, Yuanqiang; et al. (Hum Mutat, 2020)
Congenital scoliosis (CS) is a birth defect with variable clinical and anatomical manifestations due to spinal malformation. The genetic etiology underlying about 10% of CS cases in the Chinese population is compound inheritance by which the gene dosage is reduced below that of haploinsufficiency. In this genetic model, the trait manifests as a result of the combined effect of a rare variant and common pathogenic variant allele at a locus. From exome sequencing (ES) data of 523 patients in Asia and two patients in Texas, we identified six TBX6 gene-disruptive variants from 11 unrelated CS patients via ES and in vitro functional testing. The in trans mild hypomorphic allele was identified in 10 of the 11 subjects; as anticipated these 10 shared a similar spinal deformity of hemivertebrae. The remaining case has a homozygous variant in TBX6 (c.418C>T) and presents a more severe spinal deformity phenotype. We found decreased transcriptional activity and abnormal cellular localization as the molecular mechanisms for TBX6 missense loss-of-function alleles. Expanding the mutational spectrum of TBX6 pathogenic alleles enabled an increased molecular diagnostic detection rate, provided further evidence for the gene dosage-dependent genetic model underlying CS, and refined clinical classification.
Keywords: Alleles; Cell Line; Exome Sequencing; Female; Gene Expression; Genes, Reporter; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Inheritance Patterns; Male; Models, Molecular; Molecular Diagnostic Techniques; Mutation, Missense; Phenotype; Protein Conformation; Radiography; Sequence Analysis, DNA; Spine; Structure-Activity Relationship; T-Box Domain Proteins

Telomere Maintenance Mechanisms Define Clinical Outcome in High-Risk Neuroblastoma. - Koneru, Balakrishna; Lopez, Gonzalo; Farooqi, Ahsan; Conkrite, Karina L; Nguyen, Thinh H; Macha, Shawn J; Modi, Apexa; Rokita, Jo Lynne; Urias, Eduardo; Hindle, Ashly; Davidson, Heather; McCoy, Kristyn; et al. (Cancer Res, 2020)
Neuroblastoma is a childhood cancer with heterogeneous clinical outcomes. To comprehensively assess the impact of telomere maintenance mechanism (TMM) on clinical outcomes in high-risk neuroblastoma, we integrated the C-circle assay [a marker for alternative lengthening of telomeres (ALT)], TERT mRNA expression by RNA-sequencing, whole-genome/exome sequencing, and clinical covariates in 134 neuroblastoma patient samples at diagnosis. In addition, we assessed TMM in neuroblastoma cell lines ( = 104) and patient-derived xenografts ( = 28). ALT was identified in 23.4% of high-risk neuroblastoma tumors and genomic alterations in were detected in 60% of ALT tumors; 40% of ALT tumors lacked genomic alterations in known ALT-associated genes. Patients with high-risk neuroblastoma were classified into three subgroups (TERT-high, ALT, and TERT-low/non-ALT) based on presence of C-circles and TERT mRNA expression (above or below median TERT expression). Event-free survival was similar among TERT-high, ALT, or TERT-low/non-ALT patients. However, overall survival (OS) for TERT-low/non-ALT patients was significantly higher relative to TERT-high or ALT patients (log-rank test; < 0.01) independent of current clinical and molecular prognostic markers. Consistent with the observed higher OS in patients with TERT-low/non-ALT tumors, continuous shortening of telomeres and decreasing viability occurred in low TERT-expressing, non-ALT patient-derived high-risk neuroblastoma cell lines. These findings demonstrate that assaying TMM with TERT mRNA expression and C-circles provides precise stratification of high-risk neuroblastoma into three subgroups with substantially different OS: a previously undescribed TERT-low/non-ALT cohort with superior OS (even after relapse) and two cohorts of patients with poor survival that have distinct molecular therapeutic targets. SIGNIFICANCE: These findings assess telomere maintenance mechanisms with TERT mRNA and the ALT DNA biomarker C-circles to stratify neuroblastoma into three groups, with distinct overall survival independent of currently used clinical risk classifiers.
Keywords: Cell Line, Tumor; Child; Child, Preschool; Disease-Free Survival; Female; Follow-Up Studies; Gene Expression Regulation, Neoplastic; Humans; Infant; Male; Neoplasm Recurrence, Local; Neuroblastoma; RNA, Messenger; RNA-Seq; Telomerase; Telomere; Telomere Homeostasis; Whole Genome Sequencing; X-linked Nuclear Protein; Xenograft Model Antitumor Assays

Variants, N-Acetylated Amino Acids, and Progression of CKD. - Luo, Shengyuan; Surapaneni, Aditya; Zheng, Zihe; Rhee, Eugene P; Coresh, Josef; Hung, Adriana M; Nadkarni, Girish N; Yu, Bing; Eric Boerwinkle; Tin, Adrienne; Arking, Dan E; Steinbrenner, Inga; et al. (Clin J Am Soc Nephrol, 2020)
BACKGROUND AND OBJECTIVES: Genetic variants in , a liver- and kidney-specific acetyltransferase encoding gene, have been associated with eGFR and CKD in European populations. Higher circulating levels of two -associated metabolites, N--acetylornithine and N-acetyl-1-methylhistidine, have been linked to lower eGFR and higher risk of incident CKD in the Black population. We aimed to expand upon prior studies to investigate associations between rs13538, a missense variant in , N-acetylated amino acids, and kidney failure in multiple, well-characterized cohorts. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: We conducted analyses among participants with genetic and/or serum metabolomic data in the African American Study of Kidney Disease and Hypertension (AASK; =962), the Atherosclerosis Risk in Communities (ARIC) study (=1050), and Bio, an electronic health record-linked biorepository (=680). Separately, we evaluated associations between rs13538, urinary N-acetylated amino acids, and kidney failure in participants in the German CKD (GCKD) study (=1624). RESULTS: Of 31 N-acetylated amino acids evaluated, the circulating and urinary levels of 14 were associated with rs13538 (<0.05/31). Higher circulating levels of five of these N-acetylated amino acids, namely, N--acetylornithine, N-acetyl-1-methylhistidine, N-acetyl-3-methylhistidine, N-acetylhistidine, and N2,N5-diacetylornithine, were associated with kidney failure, after adjustment for confounders and combining results in meta-analysis (combined hazard ratios per two-fold higher amino acid levels: 1.48, 1.44, 1.21, 1.65, and 1.41, respectively; 95% confidence intervals: 1.21 to 1.81, 1.22 to 1.70, 1.08 to 1.37, 1.29 to 2.10, and 1.17 to 1.71, respectively; all values <0.05/14). None of the urinary levels of these N-acetylated amino acids were associated with kidney failure in the GCKD study. CONCLUSIONS: We demonstrate significant associations between an gene variant and 14 N-acetylated amino acids, five of which had circulation levels that were associated with kidney failure.
Keywords: Acetylation; Acetyltransferases; Adult; Aged; Aged, 80 and over; Amino Acids; Black People; Disease Progression; Female; Follow-Up Studies; Glomerular Filtration Rate; Histidine; Humans; Kidney Failure, Chronic; Male; Metabolomics; Methylhistidines; Middle Aged; Ornithine; Polymorphism, Single Nucleotide; Prospective Studies; Randomized Controlled Trials as Topic; White People

Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2020)
The Alzheimer's Disease Sequencing Project (ADSP) undertook whole exome sequencing in 5,740 late-onset Alzheimer disease (AD) cases and 5,096 cognitively normal controls primarily of European ancestry (EA), among whom 218 cases and 177 controls were Caribbean Hispanic (CH). An age-, sex- and APOE based risk score and family history were used to select cases most likely to harbor novel AD risk variants and controls least likely to develop AD by age 85 years. We tested ~1.5 million single nucleotide variants (SNVs) and 50,000 insertion-deletion polymorphisms (indels) for association to AD, using multiple models considering individual variants as well as gene-based tests aggregating rare, predicted functional, and loss of function variants. Sixteen single variants and 19 genes that met criteria for significant or suggestive associations after multiple-testing correction were evaluated for replication in four independent samples; three with whole exome sequencing (2,778 cases, 7,262 controls) and one with genome-wide genotyping imputed to the Haplotype Reference Consortium panel (9,343 cases, 11,527 controls). The top findings in the discovery sample were also followed-up in the ADSP whole-genome sequenced family-based dataset (197 members of 42 EA families and 501 members of 157 CH families). We identified novel and predicted functional genetic variants in genes previously associated with AD. We also detected associations in three novel genes: IGHG3 (p = 9.8 × 10), an immunoglobulin gene whose antibodies interact with β-amyloid, a long non-coding RNA AC099552.4 (p = 1.2 × 10), and a zinc-finger protein ZNF655 (gene-based p = 5.0 × 10). The latter two suggest an important role for transcriptional regulation in AD pathogenesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Exome Sequencing; Female; Gene Expression Regulation; Haplotypes; Humans; Immunity; Immunoglobulin G; Kruppel-Like Transcription Factors; Male; Polymorphism, Genetic; RNA, Long Noncoding; Transcription, Genetic

Whole genome sequence analysis of pulmonary function and COPD in 19,996 multi-ethnic participants. - Zhao, Xutong; Qiao, Dandi; Yang, Chaojie; Kasela, Silva; Kim, Wonji; Ma, Yanlin; Shrine, Nick; Batini, Chiara; Sofer, Tamar; Taliun, Sarah A Gagliano; Sakornsakolpat, Phuwanat; Balte, Pallavi P; et al. (Nat Commun, 2020)
Chronic obstructive pulmonary disease (COPD), diagnosed by reduced lung function, is a leading cause of morbidity and mortality. We performed whole genome sequence (WGS) analysis of lung function and COPD in a multi-ethnic sample of 11,497 participants from population- and family-based studies, and 8499 individuals from COPD-enriched studies in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. We identify at genome-wide significance 10 known GWAS loci and 22 distinct, previously unreported loci, including two common variant signals from stratified analysis of African Americans. Four novel common variants within the regions of PIAS1, RGN (two variants) and FTO show evidence of replication in the UK Biobank (European ancestry n ~ 320,000), while colocalization analyses leveraging multi-omic data from GTEx and TOPMed identify potential molecular mechanisms underlying four of the 22 novel loci. Our study demonstrates the value of performing WGS analyses and multi-omic follow-up in cohorts of diverse ancestry.
Keywords: Adult; Aged; Aged, 80 and over; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Black or African American; Calcium-Binding Proteins; Feasibility Studies; Female; Follow-Up Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein Inhibitors of Activated STAT; Pulmonary Disease, Chronic Obstructive; Respiratory Physiological Phenomena; Small Ubiquitin-Related Modifier Proteins; Whole Genome Sequencing

Whole-genome sequencing reveals complex chromosome rearrangement disrupting NIPBL in infant with Cornelia de Lange syndrome. - Plesser Duvdevani, Morasha; Pettersson, Maria; Eisfeldt, Jesper; Avraham, Ortal; Dagan, Judith; Frumkin, Ayala; James R Lupski; Lindstrand, Anna; Harel, Tamar (Am J Med Genet A, 2020)
Clinical laboratory diagnostic evaluation of the genomes of children with suspected genetic disorders, including chromosomal microarray and exome sequencing, cannot detect copy number neutral genomic rearrangements such as inversions, balanced translocations, and complex chromosomal rearrangements (CCRs). We describe an infant with a clinical diagnosis of Cornelia de Lange syndrome (CdLS) in whom chromosome analysis revealed a de novo complex balanced translocation, 46,XY,t(5;7;6)(q11.2;q32;q13)dn. Subsequent molecular characterization by whole-genome sequencing (WGS) identified 23 breakpoints, delineating segments derived from four chromosomes (5;6;7;21) in ancestral or inverted orientation. One of the breakpoints disrupted a known CdLS gene, NIPBL. Further investigation revealed paternal origin of the CCR allele, clustering of the breakpoint junctions, and molecular repair signatures suggestive of a single catastrophic event. Notably, very short DNA segments (25 and 41 bp) were included in the reassembled chromosomes, lending additional support that the DNA repair machinery can detect and repair such segments. Interestingly, there was an independent paternally derived miniscule complex rearrangement, possibly predisposing to subsequent genomic instability. In conclusion, we report a CCR causing a monogenic Mendelian disorder, urging WGS analysis of similar unsolved cases with suspected Mendelian disorders. Breakpoint analysis allowed for identification of the underlying molecular diagnosis and implicated chromoanagenesis in CCR formation.
Keywords: Cell Cycle Proteins; Chromosome Aberrations; Chromosomes; De Lange Syndrome; Genetic Predisposition to Disease; Humans; Infant; Male; Translocation, Genetic; Whole Genome Sequencing

Wolff-Parkinson-White syndrome: De novo variants and evidence for mutational burden in genes associated with atrial fibrillation. - Coban-Akdemir, Zeynep H; Charng, Wu-Lin; Azamian, Mahshid; Paine, Ingrid S; Punetha, Jaya; Grochowski, Christopher M; Gambin, Tomasz; Valdes, Santiago O; Cannon, Bryan; Zapata, Gladys; Hernandez, Patricia P; Jhangiani, Shalini; et al. (Am J Med Genet A, 2020)
BACKGROUND: Wolff-Parkinson-White (WPW) syndrome is a relatively common arrhythmia affecting ~1-3/1,000 individuals. Mutations in PRKAG2 have been described in rare patients in association with cardiomyopathy. However, the genetic basis of WPW in individuals with a structurally normal heart remains poorly understood. Sudden death due to atrial fibrillation (AF) can also occur in these individuals. Several studies have indicated that despite ablation of an accessory pathway, the risk of AF remains high in patients compared to general population. METHODS: We applied exome sequencing in 305 subjects, including 65 trios, 80 singletons, and 6 multiple affected families. We used de novo analysis, candidate gene approach, and burden testing to explore the genetic contributions to WPW. RESULTS: A heterozygous deleterious variant in PRKAG2 was identified in one subject, accounting for 0.6% (1/151) of the genetic basis of WPW in this study. Another individual with WPW and left ventricular hypertrophy carried a known pathogenic variant in MYH7. We found rare de novo variants in genes associated with arrhythmia and cardiomyopathy (ANK2, NEBL, PITX2, and PRDM16) in this cohort. There was an increased burden of rare deleterious variants (MAF ≤ 0.005) with CADD score ≥ 25 in genes linked to AF in cases compared to controls (P = .0023). CONCLUSIONS: Our findings show an increased burden of rare deleterious variants in genes linked to AF in WPW syndrome, suggesting that genetic factors that determine the development of accessory pathways may be linked to an increased susceptibility of atrial muscle to AF in a subset of patients.
Keywords: Adolescent; Adult; AMP-Activated Protein Kinases; Ankyrins; Atrial Fibrillation; Carrier Proteins; Child; Cohort Studies; Cytoskeletal Proteins; DNA-Binding Proteins; Exome Sequencing; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Atria; Homeodomain Proteins; Humans; LIM Domain Proteins; Male; Mutation; Transcription Factors; Wolff-Parkinson-White Syndrome; Young Adult

Xq22 deletions and correlation with distinct neurological disease traits in females: Further evidence for a contiguous gene syndrome. - Hijazi, Hadia; Coelho, Fernanda S; Gonzaga-Jauregui, Claudia; Bernardini, Laura; Mar, Soe S; Manning, Melanie A; Hanson-Kahn, Andrea; Naidu, Sakkubai; Srivastava, Siddharth; Lee, Jennifer A; Jones, Julie R; Friez, Michael J; et al. (Hum Mutat, 2020)
Xq22 deletions that encompass PLP1 (Xq22-PLP1-DEL) are notable for variable expressivity of neurological disease traits in females ranging from a mild late-onset form of spastic paraplegia type 2 (MIM# 312920), sometimes associated with skewed X-inactivation, to an early-onset neurological disease trait (EONDT) of severe developmental delay, intellectual disability, and behavioral abnormalities. Size and gene content of Xq22-PLP1-DEL vary and were proposed as potential molecular etiologies underlying variable expressivity in carrier females where two smallest regions of overlap (SROs) were suggested to influence disease. We ascertained a cohort of eight unrelated patients harboring Xq22-PLP1-DEL and performed high-density array comparative genomic hybridization and breakpoint-junction sequencing. Molecular characterization of Xq22-PLP1-DEL from 17 cases (eight herein and nine published) revealed an overrepresentation of breakpoints that reside within repeats (11/17, ~65%) and the clustering of ~47% of proximal breakpoints in a genomic instability hotspot with characteristic non-B DNA density. These findings implicate a potential role for genomic architecture in stimulating the formation of Xq22-PLP1-DEL. The correlation of Xq22-PLP1-DEL gene content with neurological disease trait in female cases enabled refinement of the associated SROs to a single genomic interval containing six genes. Our data support the hypothesis that genes contiguous to PLP1 contribute to EONDT.
Keywords: Child; Child, Preschool; Chromosome Breakpoints; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, X; Comparative Genomic Hybridization; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Nervous System Diseases; Pedigree; Phenotype; Quantitative Trait, Heritable; Repetitive Sequences, Nucleic Acid; Sex Factors; Syndrome; X Chromosome Inactivation

Biallelic and De Novo Variants in DONSON Reveal a Clinical Spectrum of Cell Cycle-opathies with Microcephaly, Dwarfism and Skeletal Abnormalities. - Karaca, Ender; Posey, Jennifer E; Bostwick, Bret; Liu, Pengfei; Gezdirici, Alper; Yesil, Gozde; Coban Akdemir, Zeynep; Bayram, Yavuz; Harms, Frederike L; Meinecke, Peter; Alawi, Malik; Bacino, Carlos A; et al. (Am J Med Genet A, 2019)
Co-occurrence of primordial dwarfism and microcephaly together with particular skeletal findings are seen in a wide range of Mendelian syndromes including microcephaly micromelia syndrome (MMS, OMIM 251230), microcephaly, short stature, and limb abnormalities (MISSLA, OMIM 617604), and microcephalic primordial dwarfisms (MPDs). Genes associated with these syndromes encode proteins that have crucial roles in DNA replication or in other critical steps of the cell cycle that link DNA replication to cell division. We identified four unrelated families with five affected individuals having biallelic or de novo variants in DONSON presenting with a core phenotype of severe short stature (z score < -3 SD), additional skeletal abnormalities, and microcephaly. Two apparently unrelated families with identical homozygous c.631C > T p.(Arg211Cys) variant had clinical features typical of Meier-Gorlin syndrome (MGS), while two siblings with compound heterozygous c.346delG p.(Asp116Ile*62) and c.1349A > G p.(Lys450Arg) variants presented with Seckel-like phenotype. We also identified a de novo c.683G > T p.(Trp228Leu) variant in DONSON in a patient with prominent micrognathia, short stature and hypoplastic femur and tibia, clinically diagnosed with Femoral-Facial syndrome (FFS, OMIM 134780). Biallelic variants in DONSON have been recently described in individuals with microcephalic dwarfism. These studies also demonstrated that DONSON has an essential conserved role in the cell cycle. Here we describe novel biallelic and de novo variants that are associated with MGS, Seckel-like phenotype and FFS, the last of which has not been associated with any disease gene to date.
Keywords: Alleles; Bone and Bones; Cell Cycle; Cell Cycle Proteins; Child; Child, Preschool; Dwarfism; Family; Female; Humans; Infant; Infant, Newborn; Male; Microcephaly; Nuclear Proteins; Pedigree; Phenotype

Biallelic CACNA2D2 variants in epileptic encephalopathy and cerebellar atrophy. - Punetha, Jaya; Karaca, Ender; Gezdirici, Alper; Lamont, Ryan E; Pehlivan, Davut; Marafi, Dana; Appendino, Juan P; Hunter, Jill V; Akdemir, Zeynep C; Fatih, Jawid M; Jhangiani, Shalini N; Richard A Gibbs; et al. (Ann Clin Transl Neurol, 2019)
OBJECTIVE: To characterize the molecular and clinical phenotypic basis of developmental and epileptic encephalopathies caused by rare biallelic variants in CACNA2D2. METHODS: Two affected individuals from a family with clinical features of early onset epileptic encephalopathy were recruited for exome sequencing at the Centers for Mendelian Genomics to identify their molecular diagnosis. GeneMatcher facilitated identification of a second family with a shared candidate disease gene identified through clinical gene panel-based testing. RESULTS: Rare biallelic CACNA2D2 variants have been previously reported in three families with developmental and epileptic encephalopathy, and one family with congenital ataxia. We identified three individuals in two unrelated families with novel homozygous rare variants in CACNA2D2 with clinical features of developmental and epileptic encephalopathy and cerebellar atrophy. Family 1 includes two affected siblings with a likely damaging homozygous rare missense variant c.1778G>C; p.(Arg593Pro) in CACNA2D2. Family 2 includes a proband with a homozygous rare nonsense variant c.485_486del; p.(Tyr162Ter) in CACNA2D2. We compared clinical and molecular findings from all nine individuals reported to date and note that cerebellar atrophy is shared among all. INTERPRETATION: Our study supports the candidacy of CACNA2D2 as a disease gene associated with a phenotypic spectrum of neurological disease that include features of developmental and epileptic encephalopathy, ataxia, and cerebellar atrophy. Age at presentation may affect apparent penetrance of neurogenetic trait manifestations and of a particular clinical neurological endophenotype, for example, seizures or ataxia.
Keywords: Adult; Atrophy; Calcium Channels; Cerebellar Ataxia; Cerebellar Diseases; Epilepsy; Female; Humans; Male; Mutation, Missense; Pedigree; Seizures; Siblings; Spasms, Infantile

Bi-allelic Pathogenic Variants in TUBGCP2 Cause Microcephaly and Lissencephaly Spectrum Disorders. - Mitani, Tadahiro; Punetha, Jaya; Akalin, Ibrahim; Pehlivan, Davut; Dawidziuk, Mateusz; Coban Akdemir, Zeynep; Yilmaz, Sarenur; Aslan, Ezgi; Hunter, Jill V; Hijazi, Hadia; Grochowski, Christopher M; Jhangiani, Shalini N; et al. (Am J Hum Genet, 2019)
Lissencephaly comprises a spectrum of malformations of cortical development. This spectrum includes agyria, pachygyria, and subcortical band heterotopia; each represents anatomical malformations of brain cortical development caused by neuronal migration defects. The molecular etiologies of neuronal migration anomalies are highly enriched for genes encoding microtubules and microtubule-associated proteins, and this enrichment highlights the critical role for these genes in cortical growth and gyrification. Using exome sequencing and family based rare variant analyses, we identified a homozygous variant (c.997C>T [p.Arg333Cys]) in TUBGCP2, encoding gamma-tubulin complex protein 2 (GCP2), in two individuals from a consanguineous family; both individuals presented with microcephaly and developmental delay. GCP2 forms the multiprotein γ-tubulin ring complex (γ-TuRC) together with γ-tubulin and other GCPs to regulate the assembly of microtubules. By querying clinical exome sequencing cases and through GeneMatcher-facilitated collaborations, we found three additional families with bi-allelic variation and similarly affected phenotypes including a homozygous variant (c.1843G>C [p.Ala615Pro]) in two families and compound heterozygous variants consisting of one missense variant (c.889C>T [p.Arg297Cys]) and one splice variant (c.2025-2A>G) in another family. Brain imaging from all five affected individuals revealed varying degrees of cortical malformations including pachygyria and subcortical band heterotopia, presumably caused by disruption of neuronal migration. Our data demonstrate that pathogenic variants in TUBGCP2 cause an autosomal recessive neurodevelopmental trait consisting of a neuronal migration disorder, and our data implicate GCP2 as a core component of γ-TuRC in neuronal migrating cells.
Keywords: Alleles; Brain; Cell Movement; Child; Exome; Female; Genetic Variation; Homozygote; Humans; Lissencephaly; Male; Microcephaly; Microtubule-Associated Proteins; Microtubules; Nervous System Malformations; Neurons; Phenotype; Tubulin

Biallelic VARS variants cause developmental encephalopathy with microcephaly that is recapitulated in vars knockout zebrafish. - Siekierska, Aleksandra; Stamberger, Hannah; Deconinck, Tine; Oprescu, Stephanie N; Partoens, Michèle; Zhang, Yifan; Sourbron, Jo; Adriaenssens, Elias; Mullen, Patrick; Wiencek, Patrick; Hardies, Katia; Lee, Jeong-Soo; et al. (Nat Commun, 2019)
Aminoacyl tRNA synthetases (ARSs) link specific amino acids with their cognate transfer RNAs in a critical early step of protein translation. Mutations in ARSs have emerged as a cause of recessive, often complex neurological disease traits. Here we report an allelic series consisting of seven novel and two previously reported biallelic variants in valyl-tRNA synthetase (VARS) in ten patients with a developmental encephalopathy with microcephaly, often associated with early-onset epilepsy. In silico, in vitro, and yeast complementation assays demonstrate that the underlying pathomechanism of these mutations is most likely a loss of protein function. Zebrafish modeling accurately recapitulated some of the key neurological disease traits. These results provide both genetic and biological insights into neurodevelopmental disease and pave the way for further in-depth research on ARS related recessive disorders and precision therapies.
Keywords: Alleles; Animals; Brain Diseases; Cell Line; Disease Models, Animal; Epilepsy; Female; Fibroblasts; Gene Knockout Techniques; Genetic Predisposition to Disease; Humans; Loss of Function Mutation; Male; Microcephaly; Models, Molecular; Neurodevelopmental Disorders; Pedigree; Prosencephalon; Valine-tRNA Ligase; Zebrafish

Blood Leukocyte DNA Methylation Predicts Risk of Future Myocardial Infarction and Coronary Heart Disease. - Agha, Golareh; Mendelson, Michael M; Ward-Caviness, Cavin K; Joehanes, Roby; Huan, Tianxiao; Gondalia, Rahul; Salfati, Elias; Brody, Jennifer A; Fiorito, Giovanni; Bressler, Jan; Chen, Brian H; Ligthart, Symen; et al. (Circulation, 2019)
BACKGROUND: DNA methylation is implicated in coronary heart disease (CHD), but current evidence is based on small, cross-sectional studies. We examined blood DNA methylation in relation to incident CHD across multiple prospective cohorts. METHODS: Nine population-based cohorts from the United States and Europe profiled epigenome-wide blood leukocyte DNA methylation using the Illumina Infinium 450k microarray, and prospectively ascertained CHD events including coronary insufficiency/unstable angina, recognized myocardial infarction, coronary revascularization, and coronary death. Cohorts conducted race-specific analyses adjusted for age, sex, smoking, education, body mass index, blood cell type proportions, and technical variables. We conducted fixed-effect meta-analyses across cohorts. RESULTS: Among 11 461 individuals (mean age 64 years, 67% women, 35% African American) free of CHD at baseline, 1895 developed CHD during a mean follow-up of 11.2 years. Methylation levels at 52 CpG (cytosine-phosphate-guanine) sites were associated with incident CHD or myocardial infarction (false discovery rate<0.05). These CpGs map to genes with key roles in calcium regulation (ATP2B2, CASR, GUCA1B, HPCAL1), and genes identified in genome- and epigenome-wide studies of serum calcium (CASR), serum calcium-related risk of CHD (CASR), coronary artery calcified plaque (PTPRN2), and kidney function (CDH23, HPCAL1), among others. Mendelian randomization analyses supported a causal effect of DNA methylation on incident CHD; these CpGs map to active regulatory regions proximal to long non-coding RNA transcripts. CONCLUSION: Methylation of blood-derived DNA is associated with risk of future CHD across diverse populations and may serve as an informative tool for gaining further insight on the development of CHD.
Keywords: Adult; Aged; Cohort Studies; Coronary Disease; CpG Islands; DNA Methylation; Europe; Female; Genome-Wide Association Study; Humans; Incidence; Leukocytes; Male; Middle Aged; Myocardial Infarction; Population Groups; Prognosis; Prospective Studies; Risk; United States

A case report of two siblings with Alstrom syndrome without hearing loss associated with two new ALMS1 variants. - Shurygina, Maria F; Parker, Maria A; Schlechter, Catie L; Rui Chen; Yumei Li; Weleber, Richard G; Yang, Paul; Pennesi, Mark E (BMC Ophthalmol, 2019)
BACKGROUND: Alström syndrome (AS) is a rare monogenic disorder characterized by progressive multi-organ pathology including retinal degeneration, hearing impairment and type 2 diabetes. Here we present clinical features in two siblings diagnosed with Alström syndrome associated with two novel changes in ALMS1. CASE PRESENTATION: Two siblings originally diagnosed as having achromatopsia presented with mild light sensitivity, nonspecific otitis media, and mild developmental delay during the first decade of life with a relatively stable ocular appearance during second decade, late onset of nystagmus and dyschromatopsia (after 20 years) and preserved vision during the third decade of life. One sibling had late onset hearing loss and both siblings had symmetric high myopia, normal stature, and ptosis. Clinical findings revealed structural and functional tests consistent with a cone-rod dystrophy. Novel variants c.9894dupC (p.S3298 fs) and c.10769delC (p.T3590 fs) in ALMS1 gene were found. CONCLUSIONS: Two North American siblings who presented with a mild clinical phenotype of Alström syndrome were found to have novel mutations in ALMS1. These two frame-shift mutations segregated with the disease phenotype lending evidence to their pathogenicity.
Keywords: Adult; Alstrom Syndrome; Cell Cycle Proteins; Humans; Male; Mutation; Retinal Degeneration; Siblings; Young Adult

Clinical exome sequencing reveals locus heterogeneity and phenotypic variability of cohesinopathies. - Bo Yuan; Neira, Juanita; Pehlivan, Davut; Santiago-Sim, Teresa; Song, Xiaofei; Rosenfeld, Jill; Posey, Jennifer E; Patel, Vipulkumar; Jin, Weihong; Adam, Margaret P; Baple, Emma L; Dean, John; et al. (Genet Med, 2019)
PURPOSE: Defects in the cohesin pathway are associated with cohesinopathies, notably Cornelia de Lange syndrome (CdLS). We aimed to delineate pathogenic variants in known and candidate cohesinopathy genes from a clinical exome perspective. METHODS: We retrospectively studied patients referred for clinical exome sequencing (CES, N = 10,698). Patients with causative variants in novel or recently described cohesinopathy genes were enrolled for phenotypic characterization. RESULTS: Pathogenic or likely pathogenic single-nucleotide and insertion/deletion variants (SNVs/indels) were identified in established disease genes including NIPBL (N = 5), SMC1A (N = 14), SMC3 (N = 4), RAD21 (N = 2), and HDAC8 (N = 8). The phenotypes in this genetically defined cohort skew towards the mild end of CdLS spectrum as compared with phenotype-driven cohorts. Candidate or recently reported cohesinopathy genes were supported by de novo SNVs/indels in STAG1 (N = 3), STAG2 (N = 5), PDS5A (N = 1), and WAPL (N = 1), and one inherited SNV in PDS5A. We also identified copy-number deletions affecting STAG1 (two de novo, one of unknown inheritance) and STAG2 (one of unknown inheritance). Patients with STAG1 and STAG2 variants presented with overlapping features yet without characteristic facial features of CdLS. CONCLUSION: CES effectively identified disease-causing alleles at the mild end of the cohensinopathy spectrum and enabled characterization of candidate disease genes.
Keywords: Adolescent; Alleles; Antigens, Nuclear; Biological Variation, Population; Carrier Proteins; Cell Cycle Proteins; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Cohort Studies; De Lange Syndrome; Exome; Female; Gene Frequency; Genetic Heterogeneity; Humans; INDEL Mutation; Male; Mutation; Nuclear Proteins; Phenotype; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins; Retrospective Studies; Whole Exome Sequencing

The comparative genomics and complex population history of baboons. - Jeffrey Rogers; Raveendran, Muthuswamy; R. Alan Harris; Mailund, Thomas; Leppälä, Kalle; Athanasiadis, Georgios; Schierup, Mikkel Heide; Cheng, Jade; Munch, Kasper; Walker, Jerilyn A; Konkel, Miriam K; Jordan, Vallmer; et al. (Sci Adv, 2019)
Recent studies suggest that closely related species can accumulate substantial genetic and phenotypic differences despite ongoing gene flow, thus challenging traditional ideas regarding the genetics of speciation. Baboons (genus ) are Old World monkeys consisting of six readily distinguishable species. Baboon species hybridize in the wild, and prior data imply a complex history of differentiation and introgression. We produced a reference genome assembly for the olive baboon () and whole-genome sequence data for all six extant species. We document multiple episodes of admixture and introgression during the radiation of baboons, thus demonstrating their value as a model of complex evolutionary divergence, hybridization, and reticulation. These results help inform our understanding of similar cases, including modern humans, Neanderthals, Denisovans, and other ancient hominins.
Keywords: Animals; Base Sequence; Biological Evolution; Female; Gene Flow; Genomics; Haplotypes; Humans; Hybridization, Genetic; Male; Papio; Phylogeny; Polymorphism, Genetic; Whole Genome Sequencing

Complex Compound Inheritance of Lethal Lung Developmental Disorders Due to Disruption of the TBX-FGF Pathway. - Karolak, Justyna A; Vincent, Marie; Deutsch, Gail; Gambin, Tomasz; Cogné, Benjamin; Pichon, Olivier; Vetrini, Francesco; Mefford, Heather C; Dines, Jennifer N; Golden-Grant, Katie; Dipple, Katrina; Freed, Amanda S; et al. (Am J Hum Genet, 2019)
Primary defects in lung branching morphogenesis, resulting in neonatal lethal pulmonary hypoplasias, are incompletely understood. To elucidate the pathogenetics of human lung development, we studied a unique collection of samples obtained from deceased individuals with clinically and histopathologically diagnosed interstitial neonatal lung disorders: acinar dysplasia (n = 14), congenital alveolar dysplasia (n = 2), and other lethal lung hypoplasias (n = 10). We identified rare heterozygous copy-number variant deletions or single-nucleotide variants (SNVs) involving TBX4 (n = 8 and n = 2, respectively) or FGF10 (n = 2 and n = 2, respectively) in 16/26 (61%) individuals. In addition to TBX4, the overlapping ∼2 Mb recurrent and nonrecurrent deletions at 17q23.1q23.2 identified in seven individuals with lung hypoplasia also remove a lung-specific enhancer region. Individuals with coding variants involving either TBX4 or FGF10 also harbored at least one non-coding SNV in the predicted lung-specific enhancer region, which was absent in 13 control individuals with the overlapping deletions but without any structural lung anomalies. The occurrence of rare coding variants involving TBX4 or FGF10 with the putative hypomorphic non-coding SNVs implies a complex compound inheritance of these pulmonary hypoplasias. Moreover, they support the importance of TBX4-FGF10-FGFR2 epithelial-mesenchymal signaling in human lung organogenesis and help to explain the histopathological continuum observed in these rare lethal developmental disorders of the lung.
Keywords: DNA Copy Number Variations; Female; Fibroblast Growth Factor 10; Gene Expression Regulation; Gestational Age; Humans; Infant, Newborn; Infant, Newborn, Diseases; Lung; Lung Diseases; Male; Maternal Inheritance; Organogenesis; Paternal Inheritance; Pedigree; Polymorphism, Single Nucleotide; Receptor, Fibroblast Growth Factor, Type 2; Signal Transduction; T-Box Domain Proteins

The Consortium of Metabolomics Studies (COMETS): Metabolomics in 47 Prospective Cohort Studies. - Yu, Bing; Zanetti, Krista A; Temprosa, Marinella; Albanes, Demetrius; Appel, Nathan; Barrera, Clara Barrios; Ben-Shlomo, Yoav; Eric Boerwinkle; Casas, Juan P; Clish, Clary; Dale, Caroline; Dehghan, Abbas; et al. (Am J Epidemiol, 2019)
The Consortium of Metabolomics Studies (COMETS) was established in 2014 to facilitate large-scale collaborative research on the human metabolome and its relationship with disease etiology, diagnosis, and prognosis. COMETS comprises 47 cohorts from Asia, Europe, North America, and South America that together include more than 136,000 participants with blood metabolomics data on samples collected from 1985 to 2017. Metabolomics data were provided by 17 different platforms, with the most frequently used labs being Metabolon, Inc. (14 cohorts), the Broad Institute (15 cohorts), and Nightingale Health (11 cohorts). Participants have been followed for a median of 23 years for health outcomes including death, cancer, cardiovascular disease, diabetes, and others; many of the studies are ongoing. Available exposure-related data include common clinical measurements and behavioral factors, as well as genome-wide genotype data. Two feasibility studies were conducted to evaluate the comparability of metabolomics platforms used by COMETS cohorts. The first study showed that the overlap between any 2 different laboratories ranged from 6 to 121 metabolites at 5 leading laboratories. The second study showed that the median Spearman correlation comparing 111 overlapping metabolites captured by Metabolon and the Broad Institute was 0.79 (interquartile range, 0.56-0.89).
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Biomarkers; Body Mass Index; Child; Epidemiologic Methods; Epidemiology; Female; Global Health; Health Behavior; Hematologic Tests; Humans; Longitudinal Studies; Male; Metabolomics; Middle Aged; Prospective Studies; Socioeconomic Factors; Young Adult

Copy number variant and runs of homozygosity detection by microarrays enabled more precise molecular diagnoses in 11,020 clinical exome cases. - Dharmadhikari, Avinash V; Ghosh, Rajarshi; Bo Yuan; Liu, Pengfei; Dai, Hongzheng; Al Masri, Sami; Scull, Jennifer; Posey, Jennifer E; Jiang, Allen H; He, Weimin; Vetrini, Francesco; Braxton, Alicia A; et al. (Genome Med, 2019)
BACKGROUND: Exome sequencing (ES) has been successfully applied in clinical detection of single nucleotide variants (SNVs) and small indels. However, identification of copy number variants (CNVs) using ES data remains challenging. The purpose of this study is to understand the contribution of CNVs and copy neutral runs of homozygosity (ROH) in molecular diagnosis of patients referred for ES. METHODS: In a cohort of 11,020 consecutive ES patients, an Illumina SNP array analysis interrogating mostly coding SNPs was performed as a quality control (QC) measurement and for CNV/ROH detection. Among these patients, clinical chromosomal microarray analysis (CMA) was performed at Baylor Genetics (BG) on 3229 patients, either before, concurrently, or after ES. We retrospectively analyzed the findings from CMA and the QC array. RESULTS: The QC array can detect ~ 70% of pathogenic/likely pathogenic CNVs (PCNVs) detectable by CMA. Out of the 11,020 ES cases, the QC array identified PCNVs in 327 patients and uniparental disomy (UPD) disorder-related ROH in 10 patients. The overall PCNV/UPD detection rate was 5.9% in the 3229 ES patients who also had CMA at BG; PCNV/UPD detection rate was higher in concurrent ES and CMA than in ES with prior CMA (7.2% vs 4.6%). The PCNVs/UPD contributed to the molecular diagnoses in 17.4% (189/1089) of molecularly diagnosed ES cases with CMA and were estimated to contribute in 10.6% of all molecularly diagnosed ES cases. Dual diagnoses with both PCNVs and SNVs were detected in 38 patients. PCNVs affecting single recessive disorder genes in a compound heterozygous state with SNVs were detected in 4 patients, and homozygous deletions (mostly exonic deletions) were detected in 17 patients. A higher PCNV detection rate was observed for patients with syndromic phenotypes and/or cardiovascular abnormalities. CONCLUSIONS: Our clinical genomics study demonstrates that detection of PCNV/UPD through the QC array or CMA increases ES diagnostic rate, provides more precise molecular diagnosis for dominant as well as recessive traits, and enables more complete genetic diagnoses in patients with dual or multiple molecular diagnoses. Concurrent ES and CMA using an array with exonic coverage for disease genes enables most effective detection of both CNVs and SNVs and therefore is recommended especially in time-sensitive clinical situations.
Keywords: Chromosome Aberrations; DNA Copy Number Variations; Exome Sequencing; Female; Genetic Testing; Homozygote; Humans; Limit of Detection; Male; Microarray Analysis

De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith-Magenis syndrome. - Vetrini, Francesco; McKee, Shane; Rosenfeld, Jill A; Suri, Mohnish; Lewis, Andrea M; Nugent, Kimberly Margaret; Roeder, Elizabeth; Littlejohn, Rebecca O; Holder, Sue; Zhu, Wenmiao; Alaimo, Joseph T; Graham, Brett; et al. (Genome Med, 2019)
BACKGROUND: Neurodevelopmental disorders are genetically and phenotypically heterogeneous encompassing developmental delay (DD), intellectual disability (ID), autism spectrum disorders (ASDs), structural brain abnormalities, and neurological manifestations with variants in a large number of genes (hundreds) associated. To date, a few de novo mutations potentially disrupting TCF20 function in patients with ID, ASD, and hypotonia have been reported. TCF20 encodes a transcriptional co-regulator structurally related to RAI1, the dosage-sensitive gene responsible for Smith-Magenis syndrome (deletion/haploinsufficiency) and Potocki-Lupski syndrome (duplication/triplosensitivity). METHODS: Genome-wide analyses by exome sequencing (ES) and chromosomal microarray analysis (CMA) identified individuals with heterozygous, likely damaging, loss-of-function alleles in TCF20. We implemented further molecular and clinical analyses to determine the inheritance of the pathogenic variant alleles and studied the spectrum of phenotypes. RESULTS: We report 25 unique inactivating single nucleotide variants/indels (1 missense, 1 canonical splice-site variant, 18 frameshift, and 5 nonsense) and 4 deletions of TCF20. The pathogenic variants were detected in 32 patients and 4 affected parents from 31 unrelated families. Among cases with available parental samples, the variants were de novo in 20 instances and inherited from 4 symptomatic parents in 5, including in one set of monozygotic twins. Two pathogenic loss-of-function variants were recurrent in unrelated families. Patients presented with a phenotype characterized by developmental delay, intellectual disability, hypotonia, variable dysmorphic features, movement disorders, and sleep disturbances. CONCLUSIONS: TCF20 pathogenic variants are associated with a novel syndrome manifesting clinical characteristics similar to those observed in Smith-Magenis syndrome. Together with previously described cases, the clinical entity of TCF20-associated neurodevelopmental disorders (TAND) emerges from a genotype-driven perspective.
Keywords: Adolescent; Child; Child, Preschool; Craniofacial Abnormalities; Developmental Disabilities; Female; Humans; INDEL Mutation; Infant; Intellectual Disability; Male; Muscle Hypotonia; Smith-Magenis Syndrome; Transcription Factors; Young Adult

Delineating the expanding phenotype associated with SCAPER gene mutation. - Fasham, James; Arno, Gavin; Lin, Siying; Xu, Mingchu; Carss, Keren J; Hull, Sarah; Lane, Amelia; Robson, Anthony G; Wenger, Olivia; Self, Jay E; Harlalka, Gaurav V; Salter, Claire G; et al. (Am J Med Genet A, 2019)
Keywords: Adolescent; Adult; Carrier Proteins; Child; Consanguinity; DNA Mutational Analysis; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Pedigree; Phenotype; Young Adult

Efficient Variant Set Mixed Model Association Tests for Continuous and Binary Traits in Large-Scale Whole-Genome Sequencing Studies. - Chen, Han; Huffman, Jennifer E; Brody, Jennifer A; Wang, Chaolong; Lee, Seunggeun; Li, Zilin; Gogarten, Stephanie M; Sofer, Tamar; Bielak, Lawrence F; Bis, Joshua C; Blangero, John; Bowler, Russell P; et al. (Am J Hum Genet, 2019)
With advances in whole-genome sequencing (WGS) technology, more advanced statistical methods for testing genetic association with rare variants are being developed. Methods in which variants are grouped for analysis are also known as variant-set, gene-based, and aggregate unit tests. The burden test and sequence kernel association test (SKAT) are two widely used variant-set tests, which were originally developed for samples of unrelated individuals and later have been extended to family data with known pedigree structures. However, computationally efficient and powerful variant-set tests are needed to make analyses tractable in large-scale WGS studies with complex study samples. In this paper, we propose the variant-set mixed model association tests (SMMAT) for continuous and binary traits using the generalized linear mixed model framework. These tests can be applied to large-scale WGS studies involving samples with population structure and relatedness, such as in the National Heart, Lung, and Blood Institute's Trans-Omics for Precision Medicine (TOPMed) program. SMMATs share the same null model for different variant sets, and a virtue of this null model, which includes covariates only, is that it needs to be fit only once for all tests in each genome-wide analysis. Simulation studies show that all the proposed SMMATs correctly control type I error rates for both continuous and binary traits in the presence of population structure and relatedness. We also illustrate our tests in a real data example of analysis of plasma fibrinogen levels in the TOPMed program (n = 23,763), using the Analysis Commons, a cloud-based computing platform.
Keywords: Chromosomes, Human, Pair 4; Cloud Computing; Female; Fibrinogen; Genetic Association Studies; Genetics, Population; Humans; Male; Models, Genetic; National Heart, Lung, and Blood Institute (U.S.); Precision Medicine; Research Design; Time Factors; United States; Whole Genome Sequencing

Exome sequencing of 20,791 cases of type 2 diabetes and 24,440 controls. - Flannick, Jason; Mercader, Josep M; Fuchsberger, Christian; Udler, Miriam S; Mahajan, Anubha; Wessel, Jennifer; Teslovich, Tanya M; Caulkins, Lizz; Koesterer, Ryan; Barajas-Olmos, Francisco; Blackwell, Thomas W; Eric Boerwinkle; et al. (Nature, 2019)
Protein-coding genetic variants that strongly affect disease risk can yield relevant clues to disease pathogenesis. Here we report exome-sequencing analyses of 20,791 individuals with type 2 diabetes (T2D) and 24,440 non-diabetic control participants from 5 ancestries. We identify gene-level associations of rare variants (with minor allele frequencies of less than 0.5%) in 4 genes at exome-wide significance, including a series of more than 30 SLC30A8 alleles that conveys protection against T2D, and in 12 gene sets, including those corresponding to T2D drug targets (P = 6.1 × 10) and candidate genes from knockout mice (P = 5.2 × 10). Within our study, the strongest T2D gene-level signals for rare variants explain at most 25% of the heritability of the strongest common single-variant signals, and the gene-level effect sizes of the rare variants that we observed in established T2D drug targets will require 75,000-185,000 sequenced cases to achieve exome-wide significance. We propose a method to interpret these modest rare-variant associations and to incorporate these associations into future target or gene prioritization efforts.
Keywords: Animals; Case-Control Studies; Decision Support Techniques; Diabetes Mellitus, Type 2; Exome; Exome Sequencing; Female; Gene Frequency; Genome-Wide Association Study; Humans; Male; Mice; Mice, Knockout

Functionally oriented analysis of cardiometabolic traits in a trans-ethnic sample. - Petty, Lauren E; Highland, Heather M; Gamazon, Eric R; Hu, Hao; Karhade, Mandar; Chen, Hung-Hsin; de Vries, Paul S; Grove, Megan L; Aguilar, David; Bell, Graeme I; Huff, Chad D; Hanis, Craig L; et al. (Hum Mol Genet, 2019)
Interpretation of genetic association results is difficult because signals often lack biological context. To generate hypotheses of the functional genetic etiology of complex cardiometabolic traits, we estimated the genetically determined component of gene expression from common variants using PrediXcan (1) and determined genes with differential predicted expression by trait. PrediXcan imputes tissue-specific expression levels from genetic variation using variant-level effect on gene expression in transcriptome data. To explore the value of imputed genetically regulated gene expression (GReX) models across different ancestral populations, we evaluated imputed expression levels for predictive accuracy genome-wide in RNA sequence data in samples drawn from European-ancestry and African-ancestry populations and identified substantial predictive power using European-derived models in a non-European target population. We then tested the association of GReX on 15 cardiometabolic traits including blood lipid levels, body mass index, height, blood pressure, fasting glucose and insulin, RR interval, fibrinogen level, factor VII level and white blood cell and platelet counts in 15 755 individuals across three ancestry groups, resulting in 20 novel gene-phenotype associations reaching experiment-wide significance across ancestries. In addition, we identified 18 significant novel gene-phenotype associations in our ancestry-specific analyses. Top associations were assessed for additional support via query of S-PrediXcan (2) results derived from publicly available genome-wide association studies summary data. Collectively, these findings illustrate the utility of transcriptome-based imputation models for discovery of cardiometabolic effect genes in a diverse dataset.
Keywords: Adult; Aged; Blood Pressure; Body Mass Index; Chromosome Mapping; Ethnicity; Female; Forecasting; Genetic Association Studies; Genome-Wide Association Study; Humans; Male; Metabolome; Middle Aged; Multifactorial Inheritance; Phenotype; Polymorphism, Single Nucleotide; Transcriptome; White People

Genetic architecture of laterality defects revealed by whole exome sequencing. - Li, Alexander H; Hanchard, Neil A; Azamian, Mahshid; D'Alessandro, Lisa C A; Coban-Akdemir, Zeynep; Lopez, Keila N; Hall, Nancy J; Dickerson, Heather; Nicosia, Annarita; Fernbach, Susan; Boone, Philip M; Gambin, Tomaz; et al. (Eur J Hum Genet, 2019)
Aberrant left-right patterning in the developing human embryo can lead to a broad spectrum of congenital malformations. The causes of most laterality defects are not known, with variants in established genes accounting for <20% of cases. We sought to characterize the genetic spectrum of these conditions by performing whole-exome sequencing of 323 unrelated laterality cases. We investigated the role of rare, predicted-damaging variation in 1726 putative laterality candidate genes derived from model organisms, pathway analyses, and human phenotypes. We also evaluated the contribution of homo/hemizygous exon deletions and gene-based burden of rare variation. A total of 28 candidate variants (26 rare predicted-damaging variants and 2 hemizygous deletions) were identified, including variants in genes known to cause heterotaxy and primary ciliary dyskinesia (ACVR2B, NODAL, ZIC3, DNAI1, DNAH5, HYDIN, MMP21), and genes without a human phenotype association, but with prior evidence for a role in embryonic laterality or cardiac development. Sanger validation of the latter variants in probands and their parents revealed no de novo variants, but apparent transmitted heterozygous (ROCK2, ISL1, SMAD2), and hemizygous (RAI2, RIPPLY1) variant patterns. Collectively, these variants account for 7.1% of our study subjects. We also observe evidence for an excess burden of rare, predicted loss-of-function variation in PXDNL and BMS1- two genes relevant to the broader laterality phenotype. These findings highlight potential new genes in the development of laterality defects, and suggest extensive locus heterogeneity and complex genetic models in this class of birth defects.
Keywords: Animals; Body Patterning; Embryonic Development; Exome Sequencing; Female; Genetic Association Studies; Genome, Human; Genomics; GTP Phosphohydrolases; Heart Defects, Congenital; Heterotaxy Syndrome; Humans; Male; Peroxidases; Zebrafish; Zebrafish Proteins

Genetic meta-analysis of diagnosed Alzheimer's disease identifies new risk loci and implicates Aβ, tau, immunity and lipid processing. - Kunkle, Brian W; Grenier-Boley, Benjamin; Sims, Rebecca; Bis, Joshua C; Damotte, Vincent; Naj, Adam C; Boland, Anne; Vronskaya, Maria; van der Lee, Sven J; Amlie-Wolf, Alexandre; Bellenguez, Céline; Frizatti, Aura; et al. (Nat Genet, 2019)
Risk for late-onset Alzheimer's disease (LOAD), the most prevalent dementia, is partially driven by genetics. To identify LOAD risk loci, we performed a large genome-wide association meta-analysis of clinically diagnosed LOAD (94,437 individuals). We confirm 20 previous LOAD risk loci and identify five new genome-wide loci (IQCK, ACE, ADAM10, ADAMTS1, and WWOX), two of which (ADAM10, ACE) were identified in a recent genome-wide association (GWAS)-by-familial-proxy of Alzheimer's or dementia. Fine-mapping of the human leukocyte antigen (HLA) region confirms the neurological and immune-mediated disease haplotype HLA-DR15 as a risk factor for LOAD. Pathway analysis implicates immunity, lipid metabolism, tau binding proteins, and amyloid precursor protein (APP) metabolism, showing that genetic variants affecting APP and Aβ processing are associated not only with early-onset autosomal dominant Alzheimer's disease but also with LOAD. Analyses of risk genes and pathways show enrichment for rare variants (P = 1.32 × 10), indicating that additional rare variants remain to be identified. We also identify important genetic correlations between LOAD and traits such as family history of dementia and education.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Case-Control Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Haplotypes; Humans; Immunity; Lipid Metabolism; Lipids; Male; tau Proteins

A genome-wide association study identifies new loci for factor VII and implicates factor VII in ischemic stroke etiology. - de Vries, Paul S; Sabater-Lleal, Maria; Huffman, Jennifer E; Marten, Jonathan; Song, Ci; Pankratz, Nathan; Bartz, Traci M; de Haan, Hugoline G; Delgado, Graciela E; Eicher, John D; Martinez-Perez, Angel; Ward-Caviness, Cavin K; et al. (Blood, 2019)
Factor VII (FVII) is an important component of the coagulation cascade. Few genetic loci regulating FVII activity and/or levels have been discovered to date. We conducted a meta-analysis of 9 genome-wide association studies of plasma FVII levels (7 FVII activity and 2 FVII antigen) among 27 495 participants of European and African ancestry. Each study performed ancestry-specific association analyses. Inverse variance weighted meta-analysis was performed within each ancestry group and then combined for a -ancestry meta-analysis. Our primary analysis included the 7 studies that measured FVII activity, and a secondary analysis included all 9 studies. We provided functional genomic validation for newly identified significant loci by silencing candidate genes in a human liver cell line (HuH7) using small-interfering RNA and then measuring messenger RNA and FVII protein expression. Lastly, we used meta-analysis results to perform Mendelian randomization analysis to estimate the causal effect of FVII activity on coronary artery disease, ischemic stroke (IS), and venous thromboembolism. We identified 2 novel ( and ) and 6 known loci associated with FVII activity, explaining 19.0% of the phenotypic variance. Adding FVII antigen data to the meta-analysis did not result in the discovery of further loci. Silencing in HuH7 cells upregulated FVII, whereas silencing downregulated FVII. Mendelian randomization analyses suggest that FVII activity has a positive causal effect on the risk of IS. Variants at and contribute to FVII activity by regulating expression levels. FVII activity appears to contribute to the etiology of IS in the general population.
Keywords: Brain Ischemia; Co-Repressor Proteins; Cohort Studies; Coronary Artery Disease; DNA-Binding Proteins; Factor VII; Female; Follow-Up Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Membrane Transport Proteins; Mendelian Randomization Analysis; Middle Aged; Neoplasm Proteins; Phenotype; Polymorphism, Single Nucleotide; Prognosis; Stroke; Venous Thromboembolism

A genomic atlas of systemic interindividual epigenetic variation in humans. - Gunasekara, Chathura J; Scott, C Anthony; Laritsky, Eleonora; Baker, Maria S; MacKay, Harry; Duryea, Jack D; Kessler, Noah J; Hellenthal, Garrett; Wood, Alexis C; Hodges, Kelly R; Gandhi, Manisha; Hair, Amy B; et al. (Genome Biol, 2019)
BACKGROUND: DNA methylation is thought to be an important determinant of human phenotypic variation, but its inherent cell type specificity has impeded progress on this question. At exceptional genomic regions, interindividual variation in DNA methylation occurs systemically. Like genetic variants, systemic interindividual epigenetic variants are stable, can influence phenotype, and can be assessed in any easily biopsiable DNA sample. We describe an unbiased screen for human genomic regions at which interindividual variation in DNA methylation is not tissue-specific. RESULTS: For each of 10 donors from the NIH Genotype-Tissue Expression (GTEx) program, CpG methylation is measured by deep whole-genome bisulfite sequencing of genomic DNA from tissues representing the three germ layer lineages: thyroid (endoderm), heart (mesoderm), and brain (ectoderm). We develop a computational algorithm to identify genomic regions at which interindividual variation in DNA methylation is consistent across all three lineages. This approach identifies 9926 correlated regions of systemic interindividual variation (CoRSIVs). These regions, comprising just 0.1% of the human genome, are inter-correlated over long genomic distances, associated with transposable elements and subtelomeric regions, conserved across diverse human ethnic groups, sensitive to periconceptional environment, and associated with genes implicated in a broad range of human disorders and phenotypes. CoRSIV methylation in one tissue can predict expression of associated genes in other tissues. CONCLUSIONS: In addition to charting a previously unexplored molecular level of human individuality, this atlas of human CoRSIVs provides a resource for future population-based investigations into how interindividual epigenetic variation modulates risk of disease.
Keywords: Aged; Brain; Case-Control Studies; Child; Disease; DNA Methylation; Epigenesis, Genetic; Female; Gambia; Genetic Variation; Genome, Human; Humans; Male; Middle Aged; Myocardium; Pregnancy; Prenatal Nutritional Physiological Phenomena; Seasons; Thyroid Gland

The Genomics of Arthrogryposis, a Complex Trait: Candidate Genes and Further Evidence for Oligogenic Inheritance. - Pehlivan, Davut; Bayram, Yavuz; Gunes, Nilay; Coban Akdemir, Zeynep; Shukla, Anju; Bierhals, Tatjana; Tabakci, Burcu; Sahin, Yavuz; Gezdirici, Alper; Fatih, Jawid M; Gulec, Elif Yilmaz; Yesil, Gozde; et al. (Am J Hum Genet, 2019)
Arthrogryposis is a clinical finding that is present either as a feature of a neuromuscular condition or as part of a systemic disease in over 400 Mendelian conditions. The underlying molecular etiology remains largely unknown because of genetic and phenotypic heterogeneity. We applied exome sequencing (ES) in a cohort of 89 families with the clinical sign of arthrogryposis. Additional molecular techniques including array comparative genomic hybridization (aCGH) and Droplet Digital PCR (ddPCR) were performed on individuals who were found to have pathogenic copy number variants (CNVs) and mosaicism, respectively. A molecular diagnosis was established in 65.2% (58/89) of families. Eleven out of 58 families (19.0%) showed evidence for potential involvement of pathogenic variation at more than one locus, probably driven by absence of heterozygosity (AOH) burden due to identity-by-descent (IBD). RYR3, MYOM2, ERGIC1, SPTBN4, and ABCA7 represent genes, identified in two or more families, for which mutations are probably causative for arthrogryposis. We also provide evidence for the involvement of CNVs in the etiology of arthrogryposis and for the idea that both mono-allelic and bi-allelic variants in the same gene cause either similar or distinct syndromes. We were able to identify the molecular etiology in nine out of 20 families who underwent reanalysis. In summary, our data from family-based ES further delineate the molecular etiology of arthrogryposis, yielded several candidate disease-associated genes, and provide evidence for mutational burden in a biological pathway or network. Our study also highlights the importance of reanalysis of individuals with unsolved diagnoses in conjunction with sequencing extended family members.
Keywords: Adolescent; Adult; Arthrogryposis; Child; Child, Preschool; Cohort Studies; Connectin; DNA Copy Number Variations; Exome Sequencing; Female; Genetic Markers; Genomics; Gestational Age; Humans; Infant; Infant, Newborn; Male; Mosaicism; Multifactorial Inheritance; Mutation; Pedigree; Ryanodine Receptor Calcium Release Channel; Vesicular Transport Proteins; Young Adult

HFE H63D Polymorphism and the Risk for Systemic Hypertension, Myocardial Remodeling, and Adverse Cardiovascular Events in the ARIC Study. - Selvaraj, Senthil; Seidelmann, Sara; Silvestre, Odilson M; Claggett, Brian; Ndumele, Chiadi E; Cheng, Susan; Yu, Bing; Fernandes-Silva, Miguel M; Grove, Megan L; Eric Boerwinkle; Shah, Amil M; Solomon, Scott D (Hypertension, 2019)
H63D has been identified as a novel locus associated with the development of hypertension. The quantitative risks for hypertension, cardiac remodeling, and adverse events are not well studied. We analyzed white participants from the ARIC study (Atherosclerosis Risk in Communities) with H63D genotyping (N=10 902). We related genotype status to prevalence of hypertension at each of 5 study visits and risk for adverse cardiovascular events. Among visit 5 participants (N=4507), we related genotype status to echocardiographic features. Frequencies of wild type (WT)/WT, H63D/WT, and H63D/H63D were 73%, 24.6%, and 2.4%. The average age at baseline was 54.9±5.7 years and 47% were men. Participants carrying the H63D variant had higher systolic blood pressure ( P=0.004), diastolic blood pressure (0.012), and more frequently had hypertension ( P<0.001). Compared with WT/WT, H63D/WT and H63D/H63D participants had a 2% to 4% and 4% to 7% absolute increase in hypertension risk at each visit, respectively. The population attributable risk of H63D for hypertension among individuals aged 45 to 64 was 3.2% (95% CI, 1.3-5.1%) and 1.3% (95% CI, 0.0-2.4%) among individuals >65 years. After 25 years of follow-up, there was no relationship between genotype status and any outcome ( P>0.05). H63D/WT and H63D/H63D genotypes were associated with small differences in cardiac remodeling. In conclusion, the HFE H63D variant confers an increased risk for hypertension per allele and, given its frequency, accounts for a significant number of cases of hypertension. However, there was no increased risk for adverse cardiovascular events or substantial left ventricular remodeling.
Keywords: Cardiovascular Diseases; Echocardiography; Female; Genetic Predisposition to Disease; Hemochromatosis Protein; Humans; Hypertension; Male; Middle Aged; Mutation; Polymorphism, Genetic; Risk Assessment; United States; Ventricular Remodeling

Homozygous Missense Variants in NTNG2, Encoding a Presynaptic Netrin-G2 Adhesion Protein, Lead to a Distinct Neurodevelopmental Disorder. - Dias, Caroline M; Punetha, Jaya; Zheng, Céline; Mazaheri, Neda; Rad, Abolfazl; Efthymiou, Stephanie; Petersen, Andrea; Dehghani, Mohammadreza; Pehlivan, Davut; Partlow, Jennifer N; Posey, Jennifer E; Salpietro, Vincenzo; et al. (Am J Hum Genet, 2019)
NTNG2 encodes netrin-G2, a membrane-anchored protein implicated in the molecular organization of neuronal circuitry and synaptic organization and diversification in vertebrates. In this study, through a combination of exome sequencing and autozygosity mapping, we have identified 16 individuals (from seven unrelated families) with ultra-rare homozygous missense variants in NTNG2; these individuals present with shared features of a neurodevelopmental disorder consisting of global developmental delay, severe to profound intellectual disability, muscle weakness and abnormal tone, autistic features, behavioral abnormalities, and variable dysmorphisms. The variants disrupt highly conserved residues across the protein. Functional experiments, including in silico analysis of the protein structure, in vitro assessment of cell surface expression, and in vitro knockdown, revealed potential mechanisms of pathogenicity of the variants, including loss of protein function and decreased neurite outgrowth. Our data indicate that appropriate expression of NTNG2 plays an important role in neurotypical development.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Exome Sequencing; Female; GPI-Linked Proteins; Homozygote; Humans; Intellectual Disability; Male; Mutation, Missense; Netrins; Neurodevelopmental Disorders; Pedigree; Young Adult

Hypertensive APOL1 risk allele carriers demonstrate greater blood pressure reduction with angiotensin receptor blockade compared to low risk carriers. - Cunningham, Patrick N; Wang, Zhiying; Grove, Megan L; Cooper-Dehoff, Rhonda M; Beitelshees, Amber L; Gong, Yan; Gums, John G; Johnson, Julie A; Turner, Stephen T; Eric Boerwinkle; Chapman, Arlene B (PLoS One, 2019)
BACKGROUND: Hypertension (HTN) disproportionately affects African Americans (AAs), who respond better to thiazide diuretics than other antihypertensives. Variants of the APOL1 gene found in AAs are associated with a higher rate of kidney disease and play a complex role in cardiovascular disease. METHODS: AA subjects from four HTN trials (n = 961) (GERA1, GERA2, PEAR1, and PEAR2) were evaluated for blood pressure (BP) response based on APOL1 genotype after 4-9 weeks of monotherapy with thiazides, beta blockers, or candesartan. APOL1 G1 and G2 variants were determined by direct sequencing or imputation. RESULTS: Baseline systolic BP (SBP) and diastolic BP (DBP) levels did not differ based on APOL1 genotype. Subjects with 1-2 APOL1 risk alleles had a greater SBP response to candesartan (-12.2 +/- 1.2 vs -7.5 +/- 1.8 mmHg, p = 0.03; GERA2), and a greater decline in albuminuria with candesartan (-8.3 +/- 3.1 vs +3.7 +/- 4.3 mg/day, p = 0.02). APOL1 genotype did not associate with BP response to thiazides or beta blockers. GWAS was performed to determine associations with BP response to candesartan depending on APOL1 genotype. While no SNPs reached genome wide significance, SNP rs10113352, intronic in CSMD1, predicted greater office SBP response to candesartan (p = 3.7 x 10-7) in those with 1-2 risk alleles, while SNP rs286856, intronic in DPP6, predicted greater office SBP response (p = 3.2 x 10-7) in those with 0 risk alleles. CONCLUSIONS: Hypertensive AAs without overt kidney disease who carry 1 or more APOL1 risk variants have a greater BP and albuminuria reduction in response to candesartan therapy. BP response to thiazides or beta blockers did not differ by APOL1 genotype. Future studies confirming this initial finding in an independent cohort are required.
Keywords: Adult; Angiotensin II Type 1 Receptor Blockers; Apolipoprotein L1; Benzimidazoles; Biphenyl Compounds; Black or African American; Female; Genome-Wide Association Study; Genotype; Humans; Hypertension; Male; Middle Aged; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Tetrazoles; Treatment Outcome

Identification of Polycystic Kidney Disease 1 Like 1 Gene Variants in Children With Biliary Atresia Splenic Malformation Syndrome. - Berauer, John-Paul; Mezina, Anya I; Okou, David T; Aniko Sabo; Donna M Muzny; Richard A Gibbs; Hegde, Madhuri R; Chopra, Pankaj; Cutler, David J; Perlmutter, David H; Bull, Laura N; Thompson, Richard J; et al. (Hepatology, 2019)
Biliary atresia (BA) is the most common cause of end-stage liver disease in children and the primary indication for pediatric liver transplantation, yet underlying etiologies remain unknown. Approximately 10% of infants affected by BA exhibit various laterality defects (heterotaxy) including splenic abnormalities and complex cardiac malformations-a distinctive subgroup commonly referred to as the biliary atresia splenic malformation (BASM) syndrome. We hypothesized that genetic factors linking laterality features with the etiopathogenesis of BA in BASM patients could be identified through whole-exome sequencing (WES) of an affected cohort. DNA specimens from 67 BASM subjects, including 58 patient-parent trios, from the National Institute of Diabetes and Digestive and Kidney Diseases-supported Childhood Liver Disease Research Network (ChiLDReN) underwent WES. Candidate gene variants derived from a prespecified set of 2,016 genes associated with ciliary dysgenesis and/or dysfunction or cholestasis were prioritized according to pathogenicity, population frequency, and mode of inheritance. Five BASM subjects harbored rare and potentially deleterious biallelic variants in polycystic kidney disease 1 like 1 (PKD1L1), a gene associated with ciliary calcium signaling and embryonic laterality determination in fish, mice, and humans. Heterozygous PKD1L1 variants were found in 3 additional subjects. Immunohistochemical analysis of liver from the one BASM subject available revealed decreased PKD1L1 expression in bile duct epithelium when compared to normal livers and livers affected by other noncholestatic diseases. Conclusion: WES identified biallelic and heterozygous PKD1L1 variants of interest in 8 BASM subjects from the ChiLDReN data set; the dual roles for PKD1L1 in laterality determination and ciliary function suggest that PKD1L1 is a biologically plausible, cholangiocyte-expressed candidate gene for the BASM syndrome.
Keywords: Abnormalities, Multiple; Biliary Atresia; Child; Databases, Factual; Exome Sequencing; Female; Gene Expression Regulation, Developmental; Genetic Variation; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Polycystic Kidney Diseases; Retrospective Studies; Spleen; Syndrome

Impact of Rare and Common Genetic Variants on Diabetes Diagnosis by Hemoglobin A1c in Multi-Ancestry Cohorts: The Trans-Omics for Precision Medicine Program. - Sarnowski, Chloe; Leong, Aaron; Raffield, Laura M; Wu, Peitao; de Vries, Paul S; DiCorpo, Daniel; Guo, Xiuqing; Xu, Huichun; Liu, Yongmei; Zheng, Xiuwen; Hu, Yao; Brody, Jennifer A; et al. (Am J Hum Genet, 2019)
Hemoglobin A1c (HbA1c) is widely used to diagnose diabetes and assess glycemic control in individuals with diabetes. However, nonglycemic determinants, including genetic variation, may influence how accurately HbA1c reflects underlying glycemia. Analyzing the NHLBI Trans-Omics for Precision Medicine (TOPMed) sequence data in 10,338 individuals from five studies and four ancestries (6,158 Europeans, 3,123 African-Americans, 650 Hispanics, and 407 East Asians), we confirmed five regions associated with HbA1c (GCK in Europeans and African-Americans, HK1 in Europeans and Hispanics, FN3K and/or FN3KRP in Europeans, and G6PD in African-Americans and Hispanics) and we identified an African-ancestry-specific low-frequency variant (rs1039215 in HBG2 and HBE1, minor allele frequency (MAF) = 0.03). The most associated G6PD variant (rs1050828-T, p.Val98Met, MAF = 12% in African-Americans, MAF = 2% in Hispanics) lowered HbA1c (-0.88% in hemizygous males, -0.34% in heterozygous females) and explained 23% of HbA1c variance in African-Americans and 4% in Hispanics. Additionally, we identified a rare distinct G6PD coding variant (rs76723693, p.Leu353Pro, MAF = 0.5%; -0.98% in hemizygous males, -0.46% in heterozygous females) and detected significant association with HbA1c when aggregating rare missense variants in G6PD. We observed similar magnitude and direction of effects for rs1039215 (HBG2) and rs76723693 (G6PD) in the two largest TOPMed African American cohorts, and we replicated the rs76723693 association in the UK Biobank African-ancestry participants. These variants in G6PD and HBG2 were monomorphic in the European and Asian samples. African or Hispanic ancestry individuals carrying G6PD variants may be underdiagnosed for diabetes when screened with HbA1c. Thus, assessment of these variants should be considered for incorporation into precision medicine approaches for diabetes diagnosis.
Keywords: Cohort Studies; Diabetes Mellitus; Female; Genetic Variation; Glycated Hemoglobin; Humans; Male; Polymorphism, Single Nucleotide; Population Groups; Precision Medicine

Insights into the evolution of social systems and species from baboon studies. - Fischer, Julia; Higham, James P; Alberts, Susan C; Barrett, Louise; Beehner, Jacinta C; Bergman, Thore J; Carter, Alecia J; Collins, Anthony; Elton, Sarah; Fagot, Joël; Ferreira da Silva, Maria Joana; Hammerschmidt, Kurt; et al. (Elife, 2019)
Baboons, members of the genus comprise six closely related species distributed throughout sub-Saharan Africa and southwest Arabia. The species exhibit more ecological flexibility and a wider range of social systems than many other primates. This article summarizes our current knowledge of the natural history of baboons and highlights directions for future research. We suggest that baboons can serve as a valuable model for complex evolutionary processes, such as speciation and hybridization. The evolution of baboons has been heavily shaped by climatic changes and population expansion and fragmentation in the African savanna environment, similar to the processes that acted during human evolution. With accumulating long-term data, and new data from previously understudied species, baboons are ideally suited for investigating the links between sociality, health, longevity and reproductive success. To achieve these aims, we propose a closer integration of studies at the proximate level, including functional genomics, with behavioral and ecological studies.
Keywords: Aging; Animals; Behavior, Animal; Biological Evolution; Ecology; Female; Genomics; Male; Models, Animal; Papio; Phylogeography; Social Behavior

Interchromosomal template-switching as a novel molecular mechanism for imprinting perturbations associated with Temple syndrome. - Carvalho, Claudia M B; Coban-Akdemir, Zeynep; Hijazi, Hadia; Bo Yuan; Pendleton, Matthew; Harrington, Eoghan; Beaulaurier, John; Juul, Sissel; Turner, Daniel J; Kanchi, Rupa S; Jhangiani, Shalini N; Donna M Muzny; et al. (Genome Med, 2019)
BACKGROUND: Intrachromosomal triplications (TRP) can contribute to disease etiology via gene dosage effects, gene disruption, position effects, or fusion gene formation. Recently, post-zygotic de novo triplications adjacent to copy-number neutral genomic intervals with runs of homozygosity (ROH) have been shown to result in uniparental isodisomy (UPD). The genomic structure of these complex genomic rearrangements (CGRs) shows a consistent pattern of an inverted triplication flanked by duplications (DUP-TRP/INV-DUP) formed by an iterative DNA replisome template-switching mechanism during replicative repair of a single-ended, double-stranded DNA (seDNA), the ROH results from an interhomolog or nonsister chromatid template switch. It has been postulated that these CGRs may lead to genetic abnormalities in carriers due to dosage-sensitive genes mapping within the copy-number variant regions, homozygosity for alleles at a locus causing an autosomal recessive (AR) disease trait within the ROH region, or imprinting-associated diseases. METHODS: Here, we report a family wherein the affected subject carries a de novo 2.2-Mb TRP followed by 42.2 Mb of ROH and manifests clinical features overlapping with those observed in association with chromosome 14 maternal UPD (UPD(14)mat). UPD(14)mat can cause clinical phenotypic features enabling a diagnosis of Temple syndrome. This CGR was then molecularly characterized by high-density custom aCGH, genome-wide single-nucleotide polymorphism (SNP) and methylation arrays, exome sequencing (ES), and the Oxford Nanopore long-read sequencing technology. RESULTS: We confirmed the postulated DUP-TRP/INV-DUP structure by multiple orthogonal genomic technologies in the proband. The methylation status of known differentially methylated regions (DMRs) on chromosome 14 revealed that the subject shows the typical methylation pattern of UPD(14)mat. Consistent with these molecular findings, the clinical features overlap with those observed in Temple syndrome, including speech delay. CONCLUSIONS: These data provide experimental evidence that, in humans, triplication can lead to segmental UPD and imprinting disease. Importantly, genotype/phenotype analyses further reveal how a post-zygotically generated complex structural variant, resulting from a replication-based mutational mechanism, contributes to expanding the clinical phenotype of known genetic syndromes. Mechanistically, such events can distort transmission genetics resulting in homozygosity at a locus for which only one parent is a carrier as well as cause imprinting diseases.
Keywords: Chromosome Aberrations; Chromosome Disorders; Chromosomes, Human, Pair 14; DNA Methylation; DNA Replication; Genomic Imprinting; Humans; Male; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Young Adult

Leveraging Human Microbiome Features to Diagnose and Stratify Children with Irritable Bowel Syndrome. - Hollister, Emily B; Oezguen, Numan; Chumpitazi, Bruno P; Luna, Ruth Ann; Weidler, Erica M; Rubio-Gonzales, Michelle; Dahdouli, Mahmoud; Cope, Julia L; Mistretta, Toni-Ann; Raza, Sabeen; Ginger A Metcalf; Donna M Muzny; et al. (J Mol Diagn, 2019)
Accurate diagnosis and stratification of children with irritable bowel syndrome (IBS) remain challenging. Given the central role of recurrent abdominal pain in IBS, we evaluated the relationships of pediatric IBS and abdominal pain with intestinal microbes and fecal metabolites using a comprehensive clinical characterization and multiomics strategy. Using rigorous clinical phenotyping, we identified preadolescent children (aged 7 to 12 years) with Rome III IBS (n = 23) and healthy controls (n = 22) and characterized their fecal microbial communities using whole-genome shotgun metagenomics and global unbiased fecal metabolomic profiling. Correlation-based approaches and machine learning algorithms identified associations between microbes, metabolites, and abdominal pain. IBS cases differed from controls with respect to key bacterial taxa (eg, Flavonifractor plautii and Lachnospiraceae bacterium 7_1_58FAA), metagenomic functions (eg, carbohydrate metabolism and amino acid metabolism), and higher-order metabolites (eg, secondary bile acids, sterols, and steroid-like compounds). Significant associations between abdominal pain frequency and severity and intestinal microbial features were identified. A random forest classifier built on metagenomic and metabolic markers successfully distinguished IBS cases from controls (area under the curve, 0.93). Leveraging multiple lines of evidence, intestinal microbes, genes/pathways, and metabolites were associated with IBS, and these features were capable of distinguishing children with IBS from healthy children. These multi-omics features, and their links to childhood IBS coupled with nutritional interventions, may lead to new microbiome-guided diagnostic and therapeutic strategies.
Keywords: Abdominal Pain; Bacteria; Case-Control Studies; Child; Feces; Female; Gastrointestinal Tract; Genomics; Humans; Irritable Bowel Syndrome; Male; Metabolome; Microbiota; Multivariate Analysis; Principal Component Analysis; Statistics, Nonparametric

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data. - He, Karen Y; Li, Xiaoyin; Kelly, Tanika N; Liang, Jingjing; Cade, Brian E; Assimes, Themistocles L; Becker, Lewis C; Beitelshees, Amber L; Bress, Adam P; Chang, Yen-Pei Christy; Chen, Yii-Der Ida; de Vries, Paul S; et al. (Hum Genet, 2019)
In this study, we investigated low-frequency and rare variants associated with blood pressure (BP) by focusing on a linkage region on chromosome 16p13. We used whole genome sequencing (WGS) data obtained through the NHLBI Trans-Omics for Precision Medicine (TOPMed) program on 395 Cleveland Family Study (CFS) European Americans (CFS-EA). By analyzing functional coding variants and non-coding rare variants with CADD score > 10 residing within the chromosomal region in families with linkage evidence, we observed 25 genes with nominal statistical evidence (burden or SKAT p < 0.05). One of the genes is RBFOX1, an evolutionarily conserved RNA-binding protein that regulates tissue-specific alternative splicing that we previously reported to be associated with BP using exome array data in CFS. After follow-up analysis of the 25 genes in ten independent TOPMed studies with individuals of European, African, and East Asian ancestry, and Hispanics (N = 29,988), we identified variants in SLX4 (p = 2.19 × 10) to be significantly associated with BP traits when accounting for multiple testing. We also replicated the associations previously reported for RBFOX1 (p = 0.007). Follow-up analysis with GTEx eQTL data shows SLX4 variants are associated with gene expression in coronary artery, multiple brain tissues, and right atrial appendage of the heart. Our study demonstrates that linkage analysis of family data can provide an efficient approach for detecting rare variants associated with complex traits in WGS data.
Keywords: Alternative Splicing; Blood Pressure; Chromosomes, Human, Pair 16; Exome; Female; Follow-Up Studies; Genetic Linkage; Genetic Variation; Genome, Human; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Male; Recombinases; RNA Splicing Factors

Metabolomic Pattern Predicts Incident Coronary Heart Disease. - Wang, Zhe; Zhu, Cong; Nambi, Vijay; Morrison, Alanna C; Folsom, Aaron R; Ballantyne, Christie M; Eric Boerwinkle; Yu, Bing (Arterioscler Thromb Vasc Biol, 2019)
Objective- Alterations in the serum metabolome may be detectable in at-risk individuals before the onset of coronary heart disease (CHD). Identifying metabolomic signatures associated with CHD may provide insight into disease pathophysiology and prevention. Approach and Results- Metabolomic profiling (chromatography-mass spectrometry) was performed in 2232 African Americans and 1366 European Americans from the ARIC study (Atherosclerosis Risk in Communities). We applied Cox regression with least absolute shrinkage and selection operator to select metabolites associated with incident CHD. A metabolite risk score was constructed to evaluate whether the metabolite risk score predicted CHD risk beyond traditional risk factors. After 30 years of follow-up, we observed 633 incident CHD cases. Thirty-two metabolites were selected by least absolute shrinkage and selection operator to be associated with CHD, and 19 of the 32 showed significant individual associations with CHD, including a sugar substitute, erythritol. Theophylline (hazard ratio [95% CI] =1.16 [1.09-1.25]) and gamma-linolenic acid (hazard ratio [95% CI] =0.89 [0.81-0.97]) showed the greatest positive and negative associations with CHD, respectively. A 1 SD greater standardized metabolite risk score was associated with a 1.37-fold higher risk of CHD (hazard ratio [95% CI] =1.37 [1.27-1.47]). Adding the metabolite risk score to the traditional risk factors significantly improved model predictive performance (30-year risk prediction: Δ C statistics [95% CI] =0.016 [0.008-0.024], continuous net reclassification index [95% CI] =0.522 [0.480-0.556], integrated discrimination index [95% CI] =0.038 [0.019-0.065]). Conclusions- We identified 19 metabolites from known and novel metabolic pathways that collectively improved CHD risk prediction. Visual Overview- An online visual overview is available for this article.
Keywords: Atherosclerosis; Coronary Disease; Female; Humans; Male; Metabolomics; Middle Aged; Proportional Hazards Models; Prospective Studies; Risk Factors

Missense Variants in the Histone Acetyltransferase Complex Component Gene TRRAP Cause Autism and Syndromic Intellectual Disability. - Cogné, Benjamin; Ehresmann, Sophie; Beauregard-Lacroix, Eliane; Rousseau, Justine; Besnard, Thomas; Garcia, Thomas; Petrovski, Slavé; Avni, Shiri; McWalter, Kirsty; Blackburn, Patrick R; Sanders, Stephan J; Uguen, Kévin; et al. (Am J Hum Genet, 2019)
Acetylation of the lysine residues in histones and other DNA-binding proteins plays a major role in regulation of eukaryotic gene expression. This process is controlled by histone acetyltransferases (HATs/KATs) found in multiprotein complexes that are recruited to chromatin by the scaffolding subunit transformation/transcription domain-associated protein (TRRAP). TRRAP is evolutionarily conserved and is among the top five genes intolerant to missense variation. Through an international collaboration, 17 distinct de novo or apparently de novo variants were identified in TRRAP in 24 individuals. A strong genotype-phenotype correlation was observed with two distinct clinical spectra. The first is a complex, multi-systemic syndrome associated with various malformations of the brain, heart, kidneys, and genitourinary system and characterized by a wide range of intellectual functioning; a number of affected individuals have intellectual disability (ID) and markedly impaired basic life functions. Individuals with this phenotype had missense variants clustering around the c.3127G>A p.(Ala1043Thr) variant identified in five individuals. The second spectrum manifested with autism spectrum disorder (ASD) and/or ID and epilepsy. Facial dysmorphism was seen in both groups and included upslanted palpebral fissures, epicanthus, telecanthus, a wide nasal bridge and ridge, a broad and smooth philtrum, and a thin upper lip. RNA sequencing analysis of skin fibroblasts derived from affected individuals skin fibroblasts showed significant changes in the expression of several genes implicated in neuronal function and ion transport. Thus, we describe here the clinical spectrum associated with TRRAP pathogenic missense variants, and we suggest a genotype-phenotype correlation useful for clinical evaluation of the pathogenicity of the variants.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Amino Acid Sequence; Autistic Disorder; Child; Child, Preschool; Female; Genetic Association Studies; Humans; Infant; Intellectual Disability; Male; Mutation, Missense; Nuclear Proteins; Prognosis; Sequence Homology; Syndrome; Young Adult

Molecular Correlates of Metastasis by Systematic Pan-Cancer Analysis Across The Cancer Genome Atlas. - Chen, Fengju; Zhang, Yiqun; Varambally, Sooryanarayana; Creighton, Chad J (Mol Cancer Res, 2019)
Tumor metastasis is a major contributor to mortality of cancer patients, but the process remains poorly understood. Molecular comparisons between primary tumors and metastases can provide insights into the pathways and processes involved. Here, we systematically analyzed and cataloged molecular correlates of metastasis using The Cancer Genome Atlas (TCGA) datasets across 11 different cancer types, these data involving 4,473 primary tumor samples and 395 tumor metastasis samples (including 369 from melanoma). For each cancer type, widespread differences in gene transcription between primary and metastasis samples were observed. For several cancer types, metastasis-associated genes from TCGA comparisons were found to overlap extensively with external results from independent profiling datasets of metastatic tumors. Although some differential expression patterns associated with metastasis were found to be shared across multiple cancer types, by and large each cancer type showed a metastasis signature that was distinctive from those of the other cancer types. Functional categories of genes enriched in multiple cancer type-specific metastatic overexpression signatures included cellular response to stress, DNA repair, oxidation-reduction process, protein deubiquitination, and receptor activity. The TCGA-derived prostate cancer metastasis signature in particular could define a subset of aggressive primary prostate cancer. Transglutaminase 2 protein and mRNA were both elevated in metastases from breast and melanoma cancers. Alterations in miRNAs and in DNA methylation were also identified. IMPLICATIONS: Our findings suggest that there are different molecular pathways to metastasis involved in different cancers. Our catalog of alterations provides a resource for future studies investigating the role of specific genes in metastasis.
Keywords: Female; Gene Expression Profiling; Genes, Neoplasm; Humans; Male; Neoplasm Metastasis; Neoplasms

Molecular profiling predicts meningioma recurrence and reveals loss of DREAM complex repression in aggressive tumors. - Patel, Akash J; Wan, Ying-Wooi; Al-Ouran, Rami; Revelli, Jean-Pierre; Cardenas, Maria F; Oneissi, Mazen; Xi, Liu; Jalali, Ali; Magnotti, John F; Donna M Muzny; Harshavardhan Doddapaneni; Sebastian, Sherly; et al. (Proc Natl Acad Sci U S A, 2019)
Meningiomas account for one-third of all primary brain tumors. Although typically benign, about 20% of meningiomas are aggressive, and despite the rigor of the current histopathological classification system there remains considerable uncertainty in predicting tumor behavior. Here, we analyzed 160 tumors from all 3 World Health Organization (WHO) grades (I through III) using clinical, gene expression, and sequencing data. Unsupervised clustering analysis identified 3 molecular types (A, B, and C) that reliably predicted recurrence. These groups did not directly correlate with the WHO grading system, which classifies more than half of the tumors in the most aggressive molecular type as benign. Transcriptional and biochemical analyses revealed that aggressive meningiomas involve loss of the repressor function of the DREAM complex, which results in cell-cycle activation; only tumors in this category tend to recur after full resection. These findings should improve our ability to predict recurrence and develop targeted treatments for these clinically challenging tumors.
Keywords: Adult; Aged; Aged, 80 and over; Cell Cycle; Cell Line; Disease Progression; DNA Copy Number Variations; Female; Gene Expression Profiling; Humans; Kv Channel-Interacting Proteins; Male; Meningeal Neoplasms; Meningioma; Middle Aged; Neoplasm Recurrence, Local; Prognosis; Repressor Proteins; Young Adult

Multiancestry Genome-Wide Association Study of Lipid Levels Incorporating Gene-Alcohol Interactions. - de Vries, Paul S; Brown, Michael R; Bentley, Amy R; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Schwander, Karen; Kraja, Aldi T; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; et al. (Am J Epidemiol, 2019)
A person's lipid profile is influenced by genetic variants and alcohol consumption, but the contribution of interactions between these exposures has not been studied. We therefore incorporated gene-alcohol interactions into a multiancestry genome-wide association study of levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides. We included 45 studies in stage 1 (genome-wide discovery) and 66 studies in stage 2 (focused follow-up), for a total of 394,584 individuals from 5 ancestry groups. Analyses covered the period July 2014-November 2017. Genetic main effects and interaction effects were jointly assessed by means of a 2-degrees-of-freedom (df) test, and a 1-df test was used to assess the interaction effects alone. Variants at 495 loci were at least suggestively associated (P < 1 × 10-6) with lipid levels in stage 1 and were evaluated in stage 2, followed by combined analyses of stage 1 and stage 2. In the combined analysis of stages 1 and 2, a total of 147 independent loci were associated with lipid levels at P < 5 × 10-8 using 2-df tests, of which 18 were novel. No genome-wide-significant associations were found testing the interaction effect alone. The novel loci included several genes (proprotein convertase subtilisin/kexin type 5 (PCSK5), vascular endothelial growth factor B (VEGFB), and apolipoprotein B mRNA editing enzyme, catalytic polypeptide 1 (APOBEC1) complementation factor (A1CF)) that have a putative role in lipid metabolism on the basis of existing evidence from cellular and experimental models.
Keywords: Adolescent; Adult; Aged; Alcohol Drinking; Cholesterol, HDL; Cholesterol, LDL; Female; Genome-Wide Association Study; Genotype; Humans; Life Style; Lipids; Male; Middle Aged; Phenotype; Racial Groups; Triglycerides; Vascular Endothelial Growth Factor B; Young Adult

Multi-ancestry genome-wide gene-smoking interaction study of 387,272 individuals identifies new loci associated with serum lipids. - Bentley, Amy R; Sung, Yun J; Brown, Michael R; Winkler, Thomas W; Kraja, Aldi T; Ntalla, Ioanna; Schwander, Karen; Chasman, Daniel I; Lim, Elise; Deng, Xuan; Guo, Xiuqing; Liu, Jingmin; et al. (Nat Genet, 2019)
The concentrations of high- and low-density-lipoprotein cholesterol and triglycerides are influenced by smoking, but it is unknown whether genetic associations with lipids may be modified by smoking. We conducted a multi-ancestry genome-wide gene-smoking interaction study in 133,805 individuals with follow-up in an additional 253,467 individuals. Combined meta-analyses identified 13 new loci associated with lipids, some of which were detected only because association differed by smoking status. Additionally, we demonstrate the importance of including diverse populations, particularly in studies of interactions with lifestyle factors, where genomic and lifestyle differences by ancestry may contribute to novel findings.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Female; Genome-Wide Association Study; Genotype; Humans; Life Style; Linkage Disequilibrium; Lipids; Male; Middle Aged; Smoking; Young Adult

A multi-ancestry genome-wide study incorporating gene-smoking interactions identifies multiple new loci for pulse pressure and mean arterial pressure. - Sung, Yun Ju; de Las Fuentes, Lisa; Winkler, Thomas W; Chasman, Daniel I; Bentley, Amy R; Kraja, Aldi T; Ntalla, Ioanna; Warren, Helen R; Guo, Xiuqing; Schwander, Karen; Manning, Alisa K; Brown, Michael R; et al. (Hum Mol Genet, 2019)
Elevated blood pressure (BP), a leading cause of global morbidity and mortality, is influenced by both genetic and lifestyle factors. Cigarette smoking is one such lifestyle factor. Across five ancestries, we performed a genome-wide gene-smoking interaction study of mean arterial pressure (MAP) and pulse pressure (PP) in 129 913 individuals in stage 1 and follow-up analysis in 480 178 additional individuals in stage 2. We report here 136 loci significantly associated with MAP and/or PP. Of these, 61 were previously published through main-effect analysis of BP traits, 37 were recently reported by us for systolic BP and/or diastolic BP through gene-smoking interaction analysis and 38 were newly identified (P < 5 × 10-8, false discovery rate < 0.05). We also identified nine new signals near known loci. Of the 136 loci, 8 showed significant interaction with smoking status. They include CSMD1 previously reported for insulin resistance and BP in the spontaneously hypertensive rats. Many of the 38 new loci show biologic plausibility for a role in BP regulation. SLC26A7 encodes a chloride/bicarbonate exchanger expressed in the renal outer medullary collecting duct. AVPR1A is widely expressed, including in vascular smooth muscle cells, kidney, myocardium and brain. FHAD1 is a long non-coding RNA overexpressed in heart failure. TMEM51 was associated with contractile function in cardiomyocytes. CASP9 plays a central role in cardiomyocyte apoptosis. Identified only in African ancestry were 30 novel loci. Our findings highlight the value of multi-ancestry investigations, particularly in studies of interaction with lifestyle factors, where genomic and lifestyle differences may contribute to novel findings.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Antiporters; Arterial Pressure; Blood Pressure; Caspase 9; Ethnicity; Female; Gene-Environment Interaction; Genome-Wide Association Study; Humans; Hypertension; Male; Membrane Proteins; Middle Aged; Polymorphism, Genetic; Racial Groups; Receptors, Vasopressin; Smoking; Sulfate Transporters; Tumor Suppressor Proteins; Young Adult

Multi-ancestry sleep-by-SNP interaction analysis in 126,926 individuals reveals lipid loci stratified by sleep duration. - Noordam, Raymond; Bos, Maxime M; Wang, Heming; Winkler, Thomas W; Bentley, Amy R; Kilpeläinen, Tuomas O; de Vries, Paul S; Sung, Yun Ju; Schwander, Karen; Cade, Brian E; Manning, Alisa; Aschard, Hugues; et al. (Nat Commun, 2019)
Both short and long sleep are associated with an adverse lipid profile, likely through different biological pathways. To elucidate the biology of sleep-associated adverse lipid profile, we conduct multi-ancestry genome-wide sleep-SNP interaction analyses on three lipid traits (HDL-c, LDL-c and triglycerides). In the total study sample (discovery + replication) of 126,926 individuals from 5 different ancestry groups, when considering either long or short total sleep time interactions in joint analyses, we identify 49 previously unreported lipid loci, and 10 additional previously unreported lipid loci in a restricted sample of European-ancestry cohorts. In addition, we identify new gene-sleep interactions for known lipid loci such as LPL and PCSK9. The previously unreported lipid loci have a modest explained variance in lipid levels: most notable, gene-short-sleep interactions explain 4.25% of the variance in triglyceride level. Collectively, these findings contribute to our understanding of the biological mechanisms involved in sleep-associated adverse lipid profiles.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Chromosome Mapping; Female; Genetic Loci; Humans; Lipids; Male; Middle Aged; Phylogeny; Polymorphism, Single Nucleotide; Sleep; Young Adult

Multi-ancestry study of blood lipid levels identifies four loci interacting with physical activity. - Kilpeläinen, Tuomas O; Bentley, Amy R; Noordam, Raymond; Sung, Yun Ju; Schwander, Karen; Winkler, Thomas W; Jakupović, Hermina; Chasman, Daniel I; Manning, Alisa; Ntalla, Ioanna; Aschard, Hugues; Brown, Michael R; et al. (Nat Commun, 2019)
Many genetic loci affect circulating lipid levels, but it remains unknown whether lifestyle factors, such as physical activity, modify these genetic effects. To identify lipid loci interacting with physical activity, we performed genome-wide analyses of circulating HDL cholesterol, LDL cholesterol, and triglyceride levels in up to 120,979 individuals of European, African, Asian, Hispanic, and Brazilian ancestry, with follow-up of suggestive associations in an additional 131,012 individuals. We find four loci, in/near CLASP1, LHX1, SNTA1, and CNTNAP2, that are associated with circulating lipid levels through interaction with physical activity; higher levels of physical activity enhance the HDL cholesterol-increasing effects of the CLASP1, LHX1, and SNTA1 loci and attenuate the LDL cholesterol-increasing effect of the CNTNAP2 locus. The CLASP1, LHX1, and SNTA1 regions harbor genes linked to muscle function and lipid metabolism. Our results elucidate the role of physical activity interactions in the genetic contribution to blood lipid levels.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asian People; Black People; Brazil; Calcium-Binding Proteins; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; Exercise; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Hispanic or Latino; Humans; LIM-Homeodomain Proteins; Lipid Metabolism; Lipids; Male; Membrane Proteins; Microtubule-Associated Proteins; Middle Aged; Muscle Proteins; Nerve Tissue Proteins; Transcription Factors; Triglycerides; White People; Young Adult

Neurodevelopmental disorder with dysmorphic facies and distal limb anomalies syndrome due to disruption of BPTF in a 35-year-old man initially diagnosed with Silver-Russell syndrome. - Midro, Alina T; Tommerup, Niels; Borys, Jan; Panasiuk, Barbara; Kosztyła-Hojna, Bożena; Zalewska, Renata; Konstantynowicz, Jerzy; Łebkowska, Urszula; Cooper, Lance; Steven E Scherer; Mehrjouy, Manna M; Liu, Qian; et al. (Clin Genet, 2019)
Keywords: Abnormalities, Multiple; Adult; Diagnosis, Differential; Facies; Humans; Male; Musculoskeletal Abnormalities; Neurodevelopmental Disorders; Phenotype; Radiography; Silver-Russell Syndrome; Syndrome

A nonhuman primate model of inherited retinal disease. - Moshiri, Ala; Rui Chen; Kim, Soohyun; R. Alan Harris; Yumei Li; Raveendran, Muthuswamy; Davis, Sarah; Liang, Qingnan; Pomerantz, Ori; Wang, Jun; Garzel, Laura; Cameron, Ashley; et al. (J Clin Invest, 2019)
Inherited retinal degenerations are a common cause of untreatable blindness worldwide, with retinitis pigmentosa and cone dystrophy affecting approximately 1 in 3500 and 1 in 10,000 individuals, respectively. A major limitation to the development of effective therapies is the lack of availability of animal models that fully replicate the human condition. Particularly for cone disorders, rodent, canine, and feline models with no true macula have substantive limitations. By contrast, the cone-rich macula of a nonhuman primate (NHP) closely mirrors that of the human retina. Consequently, well-defined NHP models of heritable retinal diseases, particularly cone disorders that are predictive of human conditions, are necessary to more efficiently advance new therapies for patients. We have identified 4 related NHPs at the California National Primate Research Center with visual impairment and findings from clinical ophthalmic examination, advanced retinal imaging, and electrophysiology consistent with achromatopsia. Genetic sequencing confirmed a homozygous R565Q missense mutation in the catalytic domain of PDE6C, a cone-specific phototransduction enzyme associated with achromatopsia in humans. Biochemical studies demonstrate that the mutant mRNA is translated into a stable protein that displays normal cellular localization but is unable to hydrolyze cyclic GMP (cGMP). This NHP model of a cone disorder will not only serve as a therapeutic testing ground for achromatopsia gene replacement, but also for optimization of gene editing in the macula and of cone cell replacement in general.
Keywords: Amino Acid Substitution; Animals; Color Vision Defects; Cone Dystrophy; Cyclic Nucleotide Phosphodiesterases, Type 6; Disease Models, Animal; Eye Proteins; Female; HEK293 Cells; Humans; Macaca mulatta; Male; Mutation, Missense; Retinitis Pigmentosa

A novel disorder involving dyshematopoiesis, inflammation, and HLH due to aberrant CDC42 function. - Lam, Michael T; Coppola, Simona; Krumbach, Oliver H F; Prencipe, Giusi; Insalaco, Antonella; Cifaldi, Cristina; Brigida, Immacolata; Zara, Erika; Scala, Serena; Di Cesare, Silvia; Martinelli, Simone; Di Rocco, Martina; et al. (J Exp Med, 2019)
Hemophagocytic lymphohistiocytosis (HLH) is characterized by immune dysregulation due to inadequate restraint of overactivated immune cells and is associated with a variable clinical spectrum having overlap with more common pathophysiologies. HLH is difficult to diagnose and can be part of inflammatory syndromes. Here, we identify a novel hematological/autoinflammatory condition (NOCARH syndrome) in four unrelated patients with superimposable features, including neonatal-onset cytopenia with dyshematopoiesis, autoinflammation, rash, and HLH. Patients shared the same de novo mutation (Chr1:22417990C>T, p.R186C) and altered hematopoietic compartment, immune dysregulation, and inflammation. mutations had been associated with syndromic neurodevelopmental disorders. In vitro and in vivo assays documented unique effects of p.R186C on CDC42 localization and function, correlating with the distinctiveness of the trait. Emapalumab was critical to the survival of one patient, who underwent successful bone marrow transplantation. Early recognition of the disorder and establishment of treatment followed by bone marrow transplant are important to survival.
Keywords: Alleles; Amino Acid Substitution; Animals; Binding Sites; cdc42 GTP-Binding Protein; Cell Line, Tumor; Child; Disease Susceptibility; Female; Genetic Association Studies; Genotype; Humans; Infant; Lymphohistiocytosis, Hemophagocytic; Male; Mice; Models, Molecular; Molecular Conformation; Mutation; Phenotype; Protein Binding

Objective measures of sleep disturbances in children with Potocki-Lupski syndrome. - Kaplan, Kevin; McCool, Caroline; James R Lupski; Glaze, Daniel; Potocki, Lorraine (Am J Med Genet A, 2019)
Potocki-Lupski syndrome (PTLS; MIM 610883) is a neurodevelopmental disorder caused by a microduplication, a 3.7 Mb copy number variant, mapping within chromosome 17p11.2, encompassing the dosage-sensitive RAI1 gene. Whereas RAI1 triplosensitivity causes PTLS, haploinsufficiency of RAI1 due to 17p11.2 microdeletion causes the clinically distinct Smith-Magenis syndrome (SMS; MIM 182290). Most individuals with SMS have an inversion of the melatonin cycle. Subjects with PTLS have mild sleep disturbances such as sleep apnea with no melatonin abnormalities described. Sleep patterns and potential disturbances in subjects with PTLS have not been objectively characterized. We delineated sleep characteristics in 23 subjects with PTLS who underwent a polysomnogram at Texas Children's Hospital. Eleven of these subjects (58%) completed the Child's Sleep Habits Questionnaire (CSHQ). Urinary melatonin was measured in one patient and published previously. While the circadian rhythm of melatonin in PTLS appears not to be disrupted, we identified significant differences in sleep efficiency, percentage of rapid eye movement sleep, oxygen nadir, obstructive apnea hypopnea index, and periodic limb movements between prepubertal subjects with PTLS and previously published normative data. Data from the CSHQ indicate that 64% (7/11) of parents do not identify a sleep disturbance in their children. Our data indicate that younger individuals, <10 years, with PTLS have statistically significant abnormalities in five components of sleep despite lack of recognition of substantial sleep disturbances by parents. Our data support the contention that patients with PTLS should undergo clinical evaluations for sleep disordered breathing and periodic limb movement disorder, both of which are treatable conditions.
Keywords: Abnormalities, Multiple; Adolescent; Child; Chromosome Disorders; Chromosome Duplication; Female; Humans; Male; Sleep Wake Disorders; Surveys and Questionnaires

Paralog Studies Augment Gene Discovery: DDX and DHX Genes. - Paine, Ingrid; Posey, Jennifer E; Grochowski, Christopher M; Jhangiani, Shalini N; Rosenheck, Sarah; Kleyner, Robert; Marmorale, Taylor; Yoon, Margaret; Wang, Kai; Robison, Reid; Cappuccio, Gerarda; Pinelli, Michele; et al. (Am J Hum Genet, 2019)
Members of a paralogous gene family in which variation in one gene is known to cause disease are eight times more likely to also be associated with human disease. Recent studies have elucidated DHX30 and DDX3X as genes for which pathogenic variant alleles are involved in neurodevelopmental disorders. We hypothesized that variants in paralogous genes encoding members of the DExD/H-box RNA helicase superfamily might also underlie developmental delay and/or intellectual disability (DD and/or ID) disease phenotypes. Here we describe 15 unrelated individuals who have DD and/or ID, central nervous system (CNS) dysfunction, vertebral anomalies, and dysmorphic features and were found to have probably damaging variants in DExD/H-box RNA helicase genes. In addition, these individuals exhibit a variety of other tissue and organ system involvement including ocular, outer ear, hearing, cardiac, and kidney tissues. Five individuals with homozygous (one), compound-heterozygous (two), or de novo (two) missense variants in DHX37 were identified by exome sequencing. We identified ten total individuals with missense variants in three other DDX/DHX paralogs: DHX16 (four individuals), DDX54 (three individuals), and DHX34 (three individuals). Most identified variants are rare, predicted to be damaging, and occur at conserved amino acid residues. Taken together, these 15 individuals implicate the DExD/H-box helicases in both dominantly and recessively inherited neurodevelopmental phenotypes and highlight the potential for more than one disease mechanism underlying these disorders.
Keywords: DEAD-box RNA Helicases; Exome Sequencing; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Male; Mutation, Missense; Neoplasm Proteins; Neurodevelopmental Disorders; Pedigree; RNA Helicases

A Patient with Berardinelli-Seip Syndrome, Novel Splicesite Mutation and Concomitant Development of Non-diabetic Polyneuropathy. - Oswiecimska, Joanna; Dawidziuk, Mateusz; Gambin, Tomasz; Ziora, Katarzyna; Marek, Marta; Rzonca, Sylwia; Guilbride, D. Lys; Jhangiani, Shalini N.; Obuchowicz, Anna; Sikora, Alicja; Lupski, James R.; Wiszniewski, Wojciech; et al. (J Clin Res Pediatr Endocrinol, 2019)
Primary polyneuropathy in the context of Seip-Berardinelli type 1 seipinopathy, or congenital generalized lipodystrophy type 1 (CGL1) has not been previously reported. We report the case history of a 27 year old female CGL1 patient presenting with an unusual additional development of non-diabetic peripheral neuropathy and learning disabilities in early adolescence. Whole exome sequencing (WES) of the patient genome identified a novel variant, homozygous for a 52 bp intronic deletion in the locus, coding for 1-acylglycerol-3-phosphate O-acyltransferase 2, which is uniquely associated with CGL1 seipinopathies, with no molecular evidence for dual diagnosis. Functional studies using RNA isolated from patient peripheral blood leucocytes showed abnormal RNA splicing resulting in the loss of 25 amino acids from the patient AGPAT2 protein coding sequence. Stability and transcription levels for the misspliced mRNA in our patient nonetheless remained normal. Any AGPAT2 protein produced in our patient is therefore likely to be dysfunctional. However, formal linkage of this deletion to the neuropathy observed remains to be shown. The classical clinical presentation of a patient with -associated lipodystrophy shows normal cognition and no development of polyneuropathy. Cognitive disabilities and polyneuropathy are features associated exclusively with clinical CGL type 2 arising from seipin gene mutations. This case study suggests that in some genetic contexts, mutations can also produce phenotypes with primary polyneuropathy.
Keywords: Acyltransferases; Adult; Female; Humans; Infant; Lipodystrophy, Congenital Generalized; Male; Mutation; Pedigree; Polyneuropathies; Prognosis; RNA Splice Sites

PHENOTYPIC VARIABILITY OF RECESSIVE RDH12-ASSOCIATED RETINAL DYSTROPHY. - Zou, Xuan; Fu, Qing; Fang, Sha; Li, Hui; Ge, Zhongqi; Yang, Lizhu; Xu, Mingchu; Sun, Zixi; Li, Huajin; Yumei Li; Dong, Fangtian; Rui Chen; et al. (Retina, 2019)
PURPOSE: To characterize the phenotypic variability and report the genetic defects in a cohort of Chinese patients with biallelic variants of the retinol dehydrogenase 12 (RDH12) gene. METHODS: The study included 38 patients from 38 unrelated families with biallelic pathogenic RDH12 variants. Systematic next-generation sequencing data analysis, Sanger sequencing validation, and segregation analysis were used to identify the pathogenic mutations. Detailed ophthalmic examinations, including electroretinogram, fundus photography, fundus autofluorescence and optical coherence tomography, and statistical analysis were performed to evaluate phenotype variability. RESULTS: Twenty-five different mutations of RDH12 were identified in the 38 families. Six of these variants were novel. Val146Asp was observed at the highest frequency (23.7%), and it was followed by Arg62Ter (14.5%) and Thr49Met (9.2%). Twenty-three probands were diagnosed with early-onset severe retinal dystrophy, 6 with Leber congenital amaurosis, 7 with autosomal recessive retinitis pigmentosa, and 2 with cone-rod dystrophy. Self-reported nyctalopia occurred in about a half of patients (55.3%) and was significantly more common among older patients (P < 0.01). Nyctalopia was not significantly associated with best-corrected visual acuity (P = 0.72), but older patients had significantly greater best-corrected visual acuity loss (P < 0.01). Only 15.8% of the patients had nystagmus, which was significantly more likely to occur among 36.8% of the patients with hyperopia >3D (P < 0.01) and/or in cases of reduced best-corrected visual acuity (P = 0.01), but was not associated with age (P = 0.87). CONCLUSION: Several high-frequency RDH12 variants were identified in patients with inherited retinal dystrophies, most of which were missense mutations. Variable but characteristic phenotypes of a progressive nature was observed. Overall, the findings indicated that biallelic RDH12 mutations are a common cause of early-onset retinal dystrophy and a rare cause of cone-rod dystrophy.
Keywords: Adolescent; Adult; Alcohol Oxidoreductases; Biological Variation, Population; Child; Child, Preschool; DNA Mutational Analysis; Electroretinography; Eye Diseases, Hereditary; Female; Genotype; Humans; Male; Middle Aged; Mutation; Pedigree; Phenotype; Retinal Dystrophies; Visual Acuity; Young Adult

Prospective virome analyses in young children at increased genetic risk for type 1 diabetes. - Vehik, Kendra; Lynch, Kristian F; Wong, Matthew C; Tian, Xiangjun; Ross, Matthew C; Richard A Gibbs; Ajami, Nadim J; Petrosino, Joseph F; Rewers, Marian; Toppari, Jorma; Ziegler, Anette G; She, Jin-Xiong; et al. (Nat Med, 2019)
Viruses are implicated in autoimmune destruction of pancreatic islet β cells, which results in insulin deficiency and type 1 diabetes (T1D). Certain enteroviruses can infect β cells in vitro, have been detected in the pancreatic islets of patients with T1D and have shown an association with T1D in meta-analyses. However, establishing consistency in findings across studies has proven difficult. Obstacles to convincingly linking RNA viruses to islet autoimmunity may be attributed to rapid viral mutation rates, the cyclical periodicity of viruses and the selection of variants with altered pathogenicity and ability to spread in populations. β cells strongly express cell-surface coxsackie and adenovirus receptor (CXADR) genes, which can facilitate enterovirus infection. Studies of human pancreata and cultured islets have shown significant variation in enteroviral virulence to β cells between serotypes and within the same serotype. In this large-scale study of known eukaryotic DNA and RNA viruses in stools from children, we evaluated fecally shed viruses in relation to islet autoimmunity and T1D. This study showed that prolonged enterovirus B rather than independent, short-duration enterovirus B infections may be involved in the development of islet autoimmunity, but not T1D, in some young children. Furthermore, we found that fewer early-life human mastadenovirus C infections, as well as CXADR rs6517774, independently correlated with islet autoimmunity.
Keywords: Adolescent; Autoimmunity; Child; Child, Preschool; Diabetes Mellitus, Type 1; Enterovirus; Feces; Female; Humans; Infant; Insulin; Insulin-Secreting Cells; Islets of Langerhans; Male; Pancreas; RNA, Viral

Protein-coding variants implicate novel genes related to lipid homeostasis contributing to body-fat distribution. - Justice, Anne E; Karaderi, Tugce; Highland, Heather M; Young, Kristin L; Graff, Mariaelisa; Lu, Yingchang; Turcot, Valérie; Auer, Paul L; Fine, Rebecca S; Guo, Xiuqing; Schurmann, Claudia; Lempradl, Adelheid; et al. (Nat Genet, 2019)
Body-fat distribution is a risk factor for adverse cardiovascular health consequences. We analyzed the association of body-fat distribution, assessed by waist-to-hip ratio adjusted for body mass index, with 228,985 predicted coding and splice site variants available on exome arrays in up to 344,369 individuals from five major ancestries (discovery) and 132,177 European-ancestry individuals (validation). We identified 15 common (minor allele frequency, MAF ≥5%) and nine low-frequency or rare (MAF <5%) coding novel variants. Pathway/gene set enrichment analyses identified lipid particle, adiponectin, abnormal white adipose tissue physiology and bone development and morphology as important contributors to fat distribution, while cross-trait associations highlight cardiometabolic traits. In functional follow-up analyses, specifically in Drosophila RNAi-knockdowns, we observed a significant increase in the total body triglyceride levels for two genes (DNAH10 and PLXND1). We implicate novel genes in fat distribution, stressing the importance of interrogating low-frequency and protein-coding variants.
Keywords: Animals; Body Fat Distribution; Body Mass Index; Case-Control Studies; Drosophila; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeostasis; Humans; Lipids; Male; Proteins; Risk Factors; Waist-Hip Ratio

Quality control and integration of genotypes from two calling pipelines for whole genome sequence data in the Alzheimer's disease sequencing project. - Naj, Adam C; Lin, Honghuang; Vardarajan, Badri N; White, Simon; Lancour, Daniel; Ma, Yiyi; Schmidt, Michael; Sun, Fangui; Butkiewicz, Mariusz; Bush, William S; Kunkle, Brian W; Malamon, John; et al. (Genomics, 2019)
The Alzheimer's Disease Sequencing Project (ADSP) performed whole genome sequencing (WGS) of 584 subjects from 111 multiplex families at three sequencing centers. Genotype calling of single nucleotide variants (SNVs) and insertion-deletion variants (indels) was performed centrally using GATK-HaplotypeCaller and Atlas V2. The ADSP Quality Control (QC) Working Group applied QC protocols to project-level variant call format files (VCFs) from each pipeline, and developed and implemented a novel protocol, termed "consensus calling," to combine genotype calls from both pipelines into a single high-quality set. QC was applied to autosomal bi-allelic SNVs and indels, and included pipeline-recommended QC filters, variant-level QC, and sample-level QC. Low-quality variants or genotypes were excluded, and sample outliers were noted. Quality was assessed by examining Mendelian inconsistencies (MIs) among 67 parent-offspring pairs, and MIs were used to establish additional genotype-specific filters for GATK calls. After QC, 578 subjects remained. Pipeline-specific QC excluded ~12.0% of GATK and 14.5% of Atlas SNVs. Between pipelines, ~91% of SNV genotypes across all QCed variants were concordant; 4.23% and 4.56% of genotypes were exclusive to Atlas or GATK, respectively; the remaining ~0.01% of discordant genotypes were excluded. For indels, variant-level QC excluded ~36.8% of GATK and 35.3% of Atlas indels. Between pipelines, ~55.6% of indel genotypes were concordant; while 10.3% and 28.3% were exclusive to Atlas or GATK, respectively; and ~0.29% of discordant genotypes were. The final WGS consensus dataset contains 27,896,774 SNVs and 3,133,926 indels and is publicly available.
Keywords: Algorithms; Alzheimer Disease; Female; Genome-Wide Association Study; Genotype; Genotyping Techniques; Humans; Male; Polymorphism, Genetic; Quality Control; Whole Genome Sequencing

Rare variants in SLC5A10 are associated with serum 1,5-anhydroglucitol (1,5-AG) in the Atherosclerosis Risk in Communities (ARIC) Study. - Loomis, Stephanie J; Köttgen, Anna; Li, Man; Tin, Adrienne; Coresh, Josef; Eric Boerwinkle; Richard A Gibbs; Donna M Muzny; Pankow, James; Selvin, Elizabeth; Duggal, Priya (Sci Rep, 2019)
Serum 1,5-anhydroglucitol (1,5-AG) is an emerging biomarker used to monitor glycemic control in persons with diabetes. We performed whole-exome sequencing, examining the association between rare, coding genetic variants and 1,5-AG among European ancestry (N = 6,589) and African ancestry (N = 2,309) participants without diagnosed diabetes in the Atherosclerosis Risk in Communities (ARIC) Study. Five variants representing 3 independent signals on chromosome 17 in SLC5A10, a glucose transporter not previously known to transport 1,5-AG, were associated with 1,5-AG levels up to 10.38 µg/mL lower per allele (1,5-AG range 3.4-32.8 µg/mL) in the European ancestry sample and validated in the African ancestry sample. Together these variants explained 6% of the variance in 1,5-AG. Two of these variants (rs61741107, p = 8.85E-56; rs148178887, p = 1.13E-36) were rare, nonsynonymous, and predicted to be damaging or deleterious by multiple algorithms. Gene-based SKAT-O analysis supported these results (SLC5A10 p = 5.13E-64 in European ancestry, validated in African ancestry, p = 0.006). Interestingly, these novel variants are not associated with other biomarkers of hyperglycemia or diabetes (p > 0.2). The large effect sizes and protein-altering, multiple independent signals suggest SLC5A10 may code for an important transporter of 1,5-AG in the kidney, with a potential nonglucose-related effect on 1,5-AG, impacting its clinical utility as a diabetes biomarker in this subpopulation.
Keywords: Atherosclerosis; Deoxyglucose; Exome Sequencing; Female; Humans; Longitudinal Studies; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Sodium-Glucose Transport Proteins

Reproducibility and Variability of Protein Analytes Measured Using a Multiplexed Modified Aptamer Assay. - Tin, Adrienne; Yu, Bing; Ma, Jianzhong; Masushita, Kunihiro; Daya, Natalie; Hoogeveen, Ron C; Ballantyne, Christie M; Couper, David; Rebholz, Casey M; Grams, Morgan E; Alonso, Alvaro; Mosley, Thomas; et al. (J Appl Lab Med, 2019)
BACKGROUND: There is growing interest in the use of multiplexed aptamer-based assays for large-scale proteomic studies. However, the analytic, short- and long-term variation of the measured proteins is largely uncharacterized. METHODS: We quantified 4001 plasma protein analytes from 42 participants in the Atherosclerosis Risk in Communities (ARIC) Study in split samples and at multiple visits using a multiplexed modified aptamer assay. We calculated the CV, Spearman correlation, and intraclass correlation (ICC) between split samples and evaluated the short-term (4-9 weeks) and long-term (approximately 20 years) variability using paired -tests with log-transformed protein concentrations and Bonferroni-corrected significance thresholds. We performed principal component (PC) analysis of protein analyte concentrations and evaluated their associations with age, sex, race, and estimated glomerular filtration rate (eGFR). RESULTS: The mean baseline age was 57 years at the first visit, 43% of participants were male and 57% were white. Among 3693 protein analytes that passed quality control, half (n = 1846) had CVs < 5.0%, Spearman correlations > 0.89, and ICCs > 0.96 among the split samples. Over the short term, only 1 analyte had a statistically significant difference between the 2 time points, whereas, over approximately 20 years, 866 analytes (23.4%) had statistically significant differences ( < 1.4 × 10, 681 increased, 185 decreased). PC1 had high correlations with age (-0.73) and eGFR (0.60). PC2 had moderate correlation with male sex (0.18) and white race (0.31). CONCLUSIONS: Multiplexed modified aptamer technology can assay thousands of proteins with excellent precision. Our results support the potential for large-scale studies of the plasma proteome over the lifespan.
Keywords: Aged; Atherosclerosis; Blood Proteins; Equipment Design; Female; Glomerular Filtration Rate; Humans; Male; Middle Aged; Prospective Studies; Proteomics; Reproducibility of Results

Review of the phenotypic spectrum associated with haploinsufficiency of MYRF. - Rossetti, Linda Z; Glinton, Kevin; Bo Yuan; Liu, Pengfei; Pillai, Nishitha; Mizerik, Elizabeth; Magoulas, Pilar; Rosenfeld, Jill A; Karaviti, Lefkothea; Sutton, Vernon R; Lalani, Seema R; Scott, Daryl A (Am J Med Genet A, 2019)
The myelin regulatory factor gene (MYRF) encodes a transcription factor that is widely expressed. There is increasing evidence that heterozygous loss-of-function variants in MYRF can lead to abnormal development of the heart, genitourinary tract, diaphragm, and lungs. Here, we searched a clinical database containing the results of 12,000 exome sequencing studies. We identified three previously unreported males with putatively deleterious variants in MYRF: one with a point mutation predicted to affect splicing and two with frameshift variants. In all cases where parental DNA was available, these variants were found to have arisen de novo. The phenotypes identified in these subjects included a variety of congenital heart defects (CHD) (hypoplastic left heart syndrome, scimitar syndrome, septal defects, and valvular anomalies), genitourinary anomalies (ambiguous genitalia, hypospadias, and cryptorchidism), congenital diaphragmatic hernia, and pulmonary hypoplasia. The phenotypes seen in our subjects overlap those described in individuals diagnosed with PAGOD syndrome [MIM# 202660], a clinically defined syndrome characterized by pulmonary artery and lung hypoplasia, agonadism, omphalocele, and diaphragmatic defects that can also be associated with hypoplastic left heart and scimitar syndrome. These cases provide additional evidence that haploinsufficiency of MYRF causes a genetic syndrome whose cardinal features include CHD, urogenital anomalies, congenital diaphragmatic hernia, and pulmonary hypoplasia. We also conclude that consideration should be given to screening individuals with PAGOD for pathogenic variants in MYRF, and that individuals with MYRF deficiency who survive the neonatal period should be monitored closely for developmental delay and intellectual disability.
Keywords: Amino Acid Sequence; Female; Haploinsufficiency; Humans; Infant, Newborn; Male; Membrane Proteins; Phenotype; Sequence Homology, Amino Acid; Transcription Factors

Single-nuclei RNA-seq on human retinal tissue provides improved transcriptome profiling. - Liang, Qingnan; Dharmat, Rachayata; Owen, Leah; Shakoor, Akbar; Yumei Li; Kim, Sangbae; Vitale, Albert; Kim, Ivana; Morgan, Denise; Liang, Shaoheng; Wu, Nathaniel; Chen, Ken; et al. (Nat Commun, 2019)
Single-cell RNA-seq is a powerful tool in decoding the heterogeneity in complex tissues by generating transcriptomic profiles of the individual cell. Here, we report a single-nuclei RNA-seq (snRNA-seq) transcriptomic study on human retinal tissue, which is composed of multiple cell types with distinct functions. Six samples from three healthy donors are profiled and high-quality RNA-seq data is obtained for 5873 single nuclei. All major retinal cell types are observed and marker genes for each cell type are identified. The gene expression of the macular and peripheral retina is compared to each other at cell-type level. Furthermore, our dataset shows an improved power for prioritizing genes associated with human retinal diseases compared to both mouse single-cell RNA-seq and human bulk RNA-seq results. In conclusion, we demonstrate that obtaining single cell transcriptomes from human frozen tissues can provide insight missed by either human bulk RNA-seq or animal models.
Keywords: Aged; Aged, 80 and over; Cell Nucleus; Female; Frozen Sections; Gene Expression Profiling; Healthy Volunteers; Humans; Male; Photoreceptor Cells; RNA-Seq; Single-Cell Analysis

Subtle changes in chromatin loop contact propensity are associated with differential gene regulation and expression. - Greenwald, William W; Li, He; Benaglio, Paola; Jakubosky, David; Matsui, Hiroko; Schmitt, Anthony; Selvaraj, Siddarth; D'Antonio, Matteo; D'Antonio-Chronowska, Agnieszka; Smith, Erin N; Frazer, Kelly A (Nat Commun, 2019)
While genetic variation at chromatin loops is relevant for human disease, the relationships between contact propensity (the probability that loci at loops physically interact), genetics, and gene regulation are unclear. We quantitatively interrogate these relationships by comparing Hi-C and molecular phenotype data across cell types and haplotypes. While chromatin loops consistently form across different cell types, they have subtle quantitative differences in contact frequency that are associated with larger changes in gene expression and H3K27ac. For the vast majority of loci with quantitative differences in contact frequency across haplotypes, the changes in magnitude are smaller than those across cell types; however, the proportional relationships between contact propensity, gene expression, and H3K27ac are consistent. These findings suggest that subtle changes in contact propensity have a biologically meaningful role in gene regulation and could be a mechanism by which regulatory genetic variants in loop anchors mediate effects on expression.
Keywords: Adolescent; Adult; Aged; Cell Line; Chromatin; DNA; Female; Gene Expression Regulation; Histones; Humans; Induced Pluripotent Stem Cells; Male; Middle Aged; Myocytes, Cardiac; Nucleic Acid Conformation; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Whole Genome Sequencing; Young Adult

Transcriptomic profiles of retinal ganglion cells are defined by the magnitude of intraocular pressure elevation in adult mice. - Park, Yong H; Snook, Joshua D; Ostrin, Edwin J; Kim, Sangbae; Rui Chen; Frankfort, Benjamin J (Sci Rep, 2019)
Elevated intraocular pressure (IOP) is the major risk factor for glaucoma, a sight threatening disease of retinal ganglion cells (RGCs) and their axons. Despite the central importance of IOP, details of the impact of IOP elevation on RGC gene expression remain elusive. We developed a 4-step immunopanning protocol to extract adult mouse RGCs with high fidelity and used it to isolate RGCs from wild type mice exposed to 2 weeks of IOP elevation generated by the microbead model. IOP was elevated to 2 distinct levels which were defined as Mild (IOP increase >1 mmHg and <4 mmHg) and Moderate (IOP increase ≥4 mmHg). RNA sequencing was used to compare the transcriptional environment at each IOP level. Differentially expressed genes were markedly different between the 2 groups, and pathway analysis revealed frequently opposed responses between the IOP levels. These results suggest that the magnitude of IOP elevation has a critical impact on RGC transcriptional changes. Furthermore, it is possible that IOP-based set points exist within RGCs to impact the direction of transcriptional change. It is possible that this improved understanding of changes in RGC gene expression can ultimately lead to novel diagnostics and therapeutics for glaucoma.
Keywords: Animals; Biomarkers; Disease Models, Animal; Female; Glaucoma; Intraocular Pressure; Male; Mice; Mice, Inbred C57BL; Retinal Ganglion Cells; Sequence Analysis, RNA; Transcriptome

Use of >100,000 NHLBI Trans-Omics for Precision Medicine (TOPMed) Consortium whole genome sequences improves imputation quality and detection of rare variant associations in admixed African and Hispanic/Latino populations. - Kowalski, Madeline H; Qian, Huijun; Hou, Ziyi; Rosen, Jonathan D; Tapia, Amanda L; Shan, Yue; Jain, Deepti; Argos, Maria; Arnett, Donna K; Avery, Christy; Barnes, Kathleen C; Becker, Lewis C; et al. (PLoS Genet, 2019)
Most genome-wide association and fine-mapping studies to date have been conducted in individuals of European descent, and genetic studies of populations of Hispanic/Latino and African ancestry are limited. In addition, these populations have more complex linkage disequilibrium structure. In order to better define the genetic architecture of these understudied populations, we leveraged >100,000 phased sequences available from deep-coverage whole genome sequencing through the multi-ethnic NHLBI Trans-Omics for Precision Medicine (TOPMed) program to impute genotypes into admixed African and Hispanic/Latino samples with genome-wide genotyping array data. We demonstrated that using TOPMed sequencing data as the imputation reference panel improves genotype imputation quality in these populations, which subsequently enhanced gene-mapping power for complex traits. For rare variants with minor allele frequency (MAF) < 0.5%, we observed a 2.3- to 6.1-fold increase in the number of well-imputed variants, with 11-34% improvement in average imputation quality, compared to the state-of-the-art 1000 Genomes Project Phase 3 and Haplotype Reference Consortium reference panels. Impressively, even for extremely rare variants with minor allele count <10 (including singletons) in the imputation target samples, average information content rescued was >86%. Subsequent association analyses of TOPMed reference panel-imputed genotype data with hematological traits (hemoglobin (HGB), hematocrit (HCT), and white blood cell count (WBC)) in ~21,600 African-ancestry and ~21,700 Hispanic/Latino individuals identified associations with two rare variants in the HBB gene (rs33930165 with higher WBC [p = 8.8x10-15] in African populations, rs11549407 with lower HGB [p = 1.5x10-12] and HCT [p = 8.8x10-10] in Hispanics/Latinos). By comparison, neither variant would have been genome-wide significant if either 1000 Genomes Project Phase 3 or Haplotype Reference Consortium reference panels had been used for imputation. Our findings highlight the utility of the TOPMed imputation reference panel for identification of novel rare variant associations not previously detected in similarly sized genome-wide studies of under-represented African and Hispanic/Latino populations.
Keywords: Adult; Aged; Aged, 80 and over; beta-Globins; Black or African American; Computational Biology; Databases, Genetic; Female; Gene Frequency; Genetic Predisposition to Disease; Genetics, Population; Genome-Wide Association Study; Genotyping Techniques; Hispanic or Latino; Humans; Linkage Disequilibrium; Male; Middle Aged; Precision Medicine; United States; Whole Genome Sequencing

Whole-Organ Genomic Characterization of Mucosal Field Effects Initiating Bladder Carcinogenesis. - Majewski, Tadeusz; Yao, Hui; Bondaruk, Jolanta; Chung, Woonbok; Lee, Sangkyou; Lee, June Goo; Zhang, Shizhen; Cogdell, David; Yang, Guoliang; Choi, Woonyoung; Dinney, Colin; Grossman, H Barton; et al. (Cell Rep, 2019)
We used whole-organ mapping to study the locoregional molecular changes in a human bladder containing multifocal cancer. Widespread DNA methylation changes were identified in the entire mucosa, representing the initial field effect. The field effect was associated with subclonal low-allele frequency mutations and a small number of DNA copy alterations. A founder mutation in the RNA splicing gene, ACIN1, was identified in normal mucosa and expanded clonally with an additional 21 mutations in progression to carcinoma. The patterns of mutations and copy number changes in carcinoma in situ and foci of carcinoma were almost identical, confirming their clonal origins. The pathways affected by the DNA copy alterations and mutations, including the Kras pathway, were preceded by the field changes in DNA methylation, suggesting that they reinforced mechanisms that had already been initiated by methylation. The results demonstrate that DNA methylation can serve as the initiator of bladder carcinogenesis.
Keywords: Carcinogenesis; Carcinoma; Clonal Evolution; DNA Methylation; Genome, Human; Humans; Male; Middle Aged; Mucous Membrane; Mutation; Nuclear Proteins; Urinary Bladder Neoplasms; Urothelium

Xia-Gibbs syndrome in adulthood: a case report with insight into the natural history of the condition. - David R Murdock; Jiang, Yunyun; Wangler, Michael; Khayat, Michael M; Aniko Sabo; Juusola, Jane; McWalter, Kirsty; Schatz, Krista Sondergaard; Gunay-Aygun, Meral; Richard A Gibbs (Cold Spring Harb Mol Case Stud, 2019)
A 55-yr-old male with severe intellectual disability, behavioral problems, kyphoscoliosis, and dysmorphic features was referred for a genetic evaluation. Chromosomal microarray, RASopathy gene panel, mitochondrial sequencing, and fragile X testing were all negative. Subsequent whole-exome sequencing revealed a heterozygous, truncating variant in the gene, consistent with a diagnosis of Xia-Gibbs syndrome (XGS). Review of his clinical history showed many classic dysmorphic and clinical features of XGS, but no major health issues in adulthood other than intellectual disability. This individual is the oldest published XGS case to date, demonstrates the wide phenotypic spectrum of the disorder, and provides information on the condition's natural history. As more adults undergo genomic studies, we will continue to learn about the adult phenotypes of genetic conditions typically diagnosed in the pediatric setting.
Keywords: Abnormalities, Multiple; Exome Sequencing; Heterozygote; Humans; Intellectual Disability; Male; Middle Aged

Additive genetic variation in the craniofacial skeleton of baboons (genus Papio) and its relationship to body and cranial size. - Joganic, Jessica L; Willmore, Katherine E; Richtsmeier, Joan T; Weiss, Kenneth M; Mahaney, Michael C; Jeffrey Rogers; Cheverud, James M (Am J Phys Anthropol, 2018)
OBJECTIVES: Determining the genetic architecture of quantitative traits and genetic correlations among them is important for understanding morphological evolution patterns. We address two questions regarding papionin evolution: (1) what effect do body and cranial size, age, and sex have on phenotypic (V ) and additive genetic (V ) variation in baboon crania, and (2) how might additive genetic correlations between craniofacial traits and body mass affect morphological evolution? MATERIALS AND METHODS: We use a large captive pedigreed baboon sample to estimate quantitative genetic parameters for craniofacial dimensions (EIDs). Our models include nested combinations of the covariates listed above. We also simulate the correlated response of a given EID due to selection on body mass alone. RESULTS: Covariates account for 1.2-91% of craniofacial V . EID V decreases across models as more covariates are included. The median genetic correlation estimate between each EID and body mass is 0.33. Analysis of the multivariate response to selection reveals that observed patterns of craniofacial variation in extant baboons cannot be attributed solely to correlated response to selection on body mass, particularly in males. DISCUSSION: Because a relatively large proportion of EID V is shared with body mass variation, different methods of correcting for allometry by statistically controlling for size can alter residual V patterns. This may conflate direct selection effects on craniofacial variation with those resulting from a correlated response to body mass selection. This shared genetic variation may partially explain how selection for increased body mass in two different papionin lineages produced remarkably similar craniofacial phenotypes.
Keywords: Animals; Anthropology, Physical; Biological Evolution; Body Size; Cephalometry; Face; Female; Genetic Variation; Genetics, Population; Male; Papio; Skull

Analysis of Genomes and Transcriptomes of Hepatocellular Carcinomas Identifies Mutations and Gene Expression Changes in the Transforming Growth Factor-β Pathway. - Chen, Jian; Zaidi, Sobia; Rao, Shuyun; Chen, Jiun-Sheng; Phan, Liem; Farci, Patrizia; Su, Xiaoping; Shetty, Kirti; White, Jon; Zamboni, Fausto; Wu, Xifeng; Rashid, Asif; et al. (Gastroenterology, 2018)
BACKGROUND & AIMS: Development of hepatocellular carcinoma (HCC) is associated with alterations in the transforming growth factor-beta (TGF-β) signaling pathway, which regulates liver inflammation and can have tumor suppressor or promoter activities. Little is known about the roles of specific members of this pathway at specific of HCC development. We took an integrated approach to identify and validate the effects of changes in this pathway in HCC and identify therapeutic targets. METHODS: We performed transcriptome analyses for a total of 488 HCCs that include data from The Cancer Genome Atlas. We also screened 301 HCCs reported in the Catalogue of Somatic Mutations in Cancer and 202 from Cancer Genome Atlas for mutations in genome sequences. We expressed mutant forms of spectrin beta, non-erythrocytic 1 (SPTBN1) in HepG2, SNU398, and SNU475 cells and measured phosphorylation, nuclear translocation, and transcriptional activity of SMAD family member 3 (SMAD3). RESULTS: We found somatic mutations in at least 1 gene whose product is a member of TGF-β signaling pathway in 38% of HCC samples. SPTBN1 was mutated in the largest proportion of samples (12 of 202, 6%). Unsupervised clustering of transcriptome data identified a group of HCCs with activation of the TGF-β signaling pathway (increased transcription of genes in the pathway) and a group of HCCs with inactivation of TGF-β signaling (reduced expression of genes in this pathway). Patients with tumors with inactivation of TGF-β signaling had shorter survival times than patients with tumors with activation of TGF-β signaling (P = .0129). Patterns of TGF-β signaling correlated with activation of the DNA damage response and sirtuin signaling pathways. HepG2, SNU398, and SNU475 cells that expressed the D1089Y mutant or with knockdown of SPTBN1 had increased sensitivity to DNA crosslinking agents and reduced survival compared with cells that expressed normal SPTBN1 (controls). CONCLUSIONS: In genome and transcriptome analyses of HCC samples, we found mutations in genes in the TGF-β signaling pathway in almost 40% of samples. These correlated with changes in expression of genes in the pathways; up-regulation of genes in this pathway would contribute to inflammation and fibrosis, whereas down-regulation would indicate loss of TGF-β tumor suppressor activity. Our findings indicate that therapeutic agents for HCCs can be effective, based on genetic features of the TGF-β pathway; agents that block TGF-β should be used only in patients with specific types of HCCs.
Keywords: Aged; Carcinoma, Hepatocellular; Case-Control Studies; Cluster Analysis; Female; Humans; Liver Neoplasms; Male; Middle Aged; Mutation; Signal Transduction; Transforming Growth Factor beta

The behavioral genetics of nonhuman primates: Status and prospects. - Jeffrey Rogers (Am J Phys Anthropol, 2018)
The complexity and diversity of primate behavior have long attracted the attention of ethologists, psychologists, behavioral ecologists, and neuroscientists. Recent studies have advanced our understanding of the nature of genetic influences on differences in behavior among individuals within species. A number of analyses have focused on the genetic analysis of behavioral reactions to specific experimental tests, providing estimates of the degree of genetic control over reactivity, and beginning to identify the genes involved. Substantial progress is also being made in identifying genetic factors that influence the structure and function of the primate brain. Most of the published studies on these topics have examined either cercopithecines or chimpanzees, though a few studies have addressed these questions in other primate species. One potentially important line of research is beginning to identify the epigenetic processes that influence primate behavior, thus revealing specific cellular and molecular mechanisms by which environmental experiences can influence gene expression or gene function relevant to behavior. This review summarizes many of these studies of non-human primate behavioral genetics. The primary focus is on analyses that address the nature of the genes and genetic processes that affect differences in behavior among individuals within non-human primate species. Analyses of between species differences and potential avenues for future research are also discussed.
Keywords: Animals; Behavior, Animal; Brain; Epigenesis, Genetic; Female; Genetics, Behavioral; Interpersonal Relations; Male; Primates

A biallelic ANTXR1 variant expands the anthrax toxin receptor associated phenotype to tooth agenesis. - Dinckan, Nuriye; Du, Renqian; Akdemir, Zeynep C; Bayram, Yavuz; Jhangiani, Shalini N; Harshavardhan Doddapaneni; Jianhong Hu; Donna M Muzny; Guven, Yeliz; Aktoren, Oya; Kayserili, Hulya; Eric Boerwinkle; et al. (Am J Med Genet A, 2018)
Tooth development is regulated by multiple genetic pathways, which ultimately drive the complex interactions between the oral epithelium and mesenchyme. Disruptions at any time point during this process may lead to failure of tooth development, also known as tooth agenesis (TA). TA is a common craniofacial abnormality in humans and represents the failure to develop one or more permanent teeth. Many genes and potentially subtle variants in these genes contribute to the TA phenotype. We report the clinical and genetic impact of a rare homozygous ANTXR1 variant (c.1312C>T), identified by whole exome sequencing (WES), in a consanguineous Turkish family with TA. Mutations in ANTXR1 have been associated with GAPO (growth retardation, alopecia, pseudoanodontia, and optic atrophy) syndrome and infantile hemangioma, however no clinical characteristics associated with these conditions were observed in our study family. We detected the expression of Antxr1 in oral and dental tissues of developing mouse embryos, further supporting a role for this gene in tooth development. Our findings implicate ANTXR1 as a candidate gene for isolated TA, suggest the involvement of specific hypomorphic alleles, and expand the previously known ANTXR1-associated phenotypes.
Keywords: Alleles; Amino Acid Substitution; Animals; Anodontia; Child; Consanguinity; Exome Sequencing; Facies; Genetic Association Studies; Genotype; Humans; Male; Mice; Microfilament Proteins; Mutation; Neoplasm Proteins; Pedigree; Phenotype; Radiography; Receptors, Cell Surface

Blood pressure signature genes and blood pressure response to thiazide diuretics: results from the PEAR and PEAR-2 studies. - Sá, Ana Caroline C; Webb, Amy; Gong, Yan; McDonough, Caitrin W; Shahin, Mohamed H; Datta, Somnath; Langaee, Taimour Y; Turner, Stephen T; Beitelshees, Amber L; Chapman, Arlene B; Eric Boerwinkle; Gums, John G; et al. (BMC Med Genomics, 2018)
BACKGROUND: Recently, 34 genes had been associated with differential expression relative to blood pressure (BP)/ hypertension (HTN). We hypothesize that some of the genes associated with BP/HTN are also associated with BP response to antihypertensive treatment with thiazide diuretics. METHODS: We assessed these 34 genes for association with differential expression to BP response to thiazide diuretics with RNA sequencing in whole blood samples from 150 hypertensive participants from the Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) and PEAR-2 studies. PEAR white and PEAR-2 white and black participants (n = 50 for each group) were selected based on the upper and lower quartile of BP response to hydrochlorothiazide (HCTZ) and to chlorthalidone. RESULTS: FOS, DUSP1 and PPP1R15A were differentially expressed across all cohorts (meta-analysis p-value < 2.0 × 10), and responders to HCTZ or chlorthalidone presented up-regulated transcripts. Rs11065987 in chromosome 12, a trans-eQTL for expression of FOS, PPP1R15A and other genes, is also associated with BP response to HCTZ in PEAR whites (SBP: β = - 2.1; p = 1.7 × 10; DBP: β = - 1.4; p = 2.9 × 10). CONCLUSIONS: These findings suggest FOS, DUSP1 and PPP1R15A as potential molecular determinants of antihypertensive response to thiazide diuretics. TRIAL REGISTRATION: NCT00246519 , NCT01203852 www.clinicaltrials.gov.
Keywords: Antihypertensive Agents; Blood Pressure; Female; Gene Expression Profiling; Humans; Hypertension; Male; Middle Aged; Pharmacogenomic Testing; Sodium Chloride Symporter Inhibitors

CD163+ macrophages promote angiogenesis and vascular permeability accompanied by inflammation in atherosclerosis. - Guo, Liang; Akahori, Hirokuni; Harari, Emanuel; Smith, Samantha L; Polavarapu, Rohini; Karmali, Vinit; Otsuka, Fumiyuki; Gannon, Rachel L; Braumann, Ryan E; Dickinson, Megan H; Gupta, Anuj; Jenkins, Audrey L; et al. (J Clin Invest, 2018)
Intake of hemoglobin by the hemoglobin-haptoglobin receptor CD163 leads to a distinct alternative non-foam cell antiinflammatory macrophage phenotype that was previously considered atheroprotective. Here, we reveal an unexpected but important pathogenic role for these macrophages in atherosclerosis. Using human atherosclerotic samples, cultured cells, and a mouse model of advanced atherosclerosis, we investigated the role of intraplaque hemorrhage on macrophage function with respect to angiogenesis, vascular permeability, inflammation, and plaque progression. In human atherosclerotic lesions, CD163+ macrophages were associated with plaque progression, microvascularity, and a high level of HIF1α and VEGF-A expression. We observed irregular vascular endothelial cadherin in intraplaque microvessels surrounded by CD163+ macrophages. Within these cells, activation of HIF1α via inhibition of prolyl hydroxylases promoted VEGF-mediated increases in intraplaque angiogenesis, vascular permeability, and inflammatory cell recruitment. CD163+ macrophages increased intraplaque endothelial VCAM expression and plaque inflammation. Subjects with homozygous minor alleles of the SNP rs7136716 had elevated microvessel density, increased expression of CD163 in ruptured coronary plaques, and a higher risk of myocardial infarction and coronary heart disease in population cohorts. Thus, our findings highlight a nonlipid-driven mechanism by which alternative macrophages promote plaque angiogenesis, leakiness, inflammation, and progression via the CD163/HIF1α/VEGF-A pathway.
Keywords: Adult; Animals; Antigens, CD; Antigens, Differentiation, Myelomonocytic; Atherosclerosis; Coronary Disease; Coronary Vessels; Disease Progression; Female; Hemoglobins; Humans; Inflammation; Macrophages; Male; Mice; Mice, Inbred C57BL; Middle Aged; Myocardial Infarction; Neovascularization, Pathologic; Oxidative Stress; Permeability; Phenotype; Polymorphism, Single Nucleotide; Receptors, Cell Surface; Signal Transduction

Challenges of Francisella classification exemplified by an atypical clinical isolate. - Matz, L M; Kamdar, K Y; Holder, M E; Ginger A Metcalf; Weissenberger, G M; Meng, Q; Vee, V; Han, Y; Donna M Muzny; Richard A Gibbs; Johnson, C L; Revell, P A; et al. (Diagn Microbiol Infect Dis, 2018)
The accumulation of sequenced Francisella strains has made it increasingly apparent that the 16S rRNA gene alone is not enough to stratify the Francisella genus into precise and clinically useful classifications. Continued whole-genome sequencing of isolates will provide a larger base of knowledge for targeted approaches with broad applicability. Additionally, examination of genomic information on a case-by-case basis will help resolve outstanding questions regarding strain stratification. We report the complete genome sequence of a clinical isolate, designated here as F. novicida-like strain TCH2015, acquired from the lymph node of a 6-year-old male. Two features were atypical for F. novicida: exhibition of functional oxidase activity and additional gene content, including proposed virulence determinants. These differences, which could potentially impact virulence and clinical diagnosis, emphasize the need for more comprehensive methods to profile Francisella isolates. This study highlights the value of whole-genome sequencing, which will lead to a more robust database of environmental and clinical genomes and inform strategies to improve detection and classification of Francisella strains.
Keywords: Child; DNA, Bacterial; Francisella; Genes, Bacterial; Genetic Variation; Genome, Bacterial; Genotype; Humans; Lymph Nodes; Male; Oxidoreductases; Sequence Analysis, DNA; Tularemia; Virulence Factors; Whole Genome Sequencing

Change in Neutrophil-to-lymphocyte ratio (NLR) in response to immune checkpoint blockade for metastatic renal cell carcinoma. - Lalani, Aly-Khan A; Xie, Wanling; Martini, Dylan J; Steinharter, John A; Norton, Craig K; Krajewski, Katherine M; Duquette, Audrey; Bossé, Dominick; Bellmunt, Joaquim; Van Allen, Eliezer M; McGregor, Bradley A; Creighton, Chad J; et al. (J Immunother Cancer, 2018)
BACKGROUND: An elevated Neutrophil-to-lymphocyte ratio (NLR) is associated with worse outcomes in several malignancies. However, its role with contemporary immune checkpoint blockade (ICB) is unknown. We investigated the utility of NLR in metastatic renal cell carcinoma (mRCC) patients treated with PD-1/PD-L1 ICB. METHODS: We examined NLR at baseline and 6 (±2) weeks later in 142 patients treated between 2009 and 2017 at Dana-Farber Cancer Institute (Boston, USA). Landmark analysis at 6 weeks was conducted to explore the prognostic value of relative NLR change on overall survival (OS), progression-free survival (PFS), and objective response rate (ORR). Cox and logistic regression models allowed for adjustment of line of therapy, number of IMDC risk factors, histology and baseline NLR. RESULTS: Median follow up was 16.6 months (range: 0.7-67.8). Median duration on therapy was 5.1 months (<1-61.4). IMDC risk groups were: 18% favorable, 60% intermediate, 23% poor-risk. Forty-four percent were on first-line ICB and 56% on 2nd line or more. Median NLR was 3.9 (1.3-42.4) at baseline and 4.1 (1.1-96.4) at week 6. Patients with a higher baseline NLR showed a trend toward lower ORR, shorter PFS, and shorter OS. Higher NLR at 6 weeks was a significantly stronger predictor of all three outcomes than baseline NLR. Relative NLR change by ≥25% from baseline to 6 weeks after ICB therapy was associated with reduced ORR and an independent prognostic factor for PFS (p < 0.001) and OS (p = 0.004), whereas a decrease in NLR by ≥25% was associated with improved outcomes. CONCLUSIONS: Early decline and NLR at 6 weeks are associated with significantly improved outcomes in mRCC patients treated with ICB. The prognostic value of the readily-available NLR warrants larger, prospective validation.
Keywords: Adult; Aged; Aged, 80 and over; Antineoplastic Agents, Immunological; B7-H1 Antigen; Carcinoma, Renal Cell; Female; Humans; Kidney Neoplasms; Lymphocytes; Male; Middle Aged; Neutrophils; Programmed Cell Death 1 Receptor; Survival Analysis; Treatment Outcome; Young Adult

Comparison of vitamin D metabolites in wild and captive baboons. - Ziegler, Toni E; Kapoor, Amita; Binkley, Neil C; Rice, Karen S; Jeffrey Rogers; Jolly, Clifford J; Phillips-Conroy, Jane E (Am J Primatol, 2018)
Vitamin D adequacy is essential for multiple physiologic processes. With limited exposure to sunlight for vitamin D synthesis, captive primates are supplemented with vitamin D (cholecalciferol). Vitamin D metabolite data from wild primates living indigenously could suggest optimum levels. The purpose of this study was to: 1) to explore whether baboons, a speciose genus whose members have significant exposed skin, coat color variation and wide geographical distribution, mirrors the skin pigmentation-vitamin D relationship found in humans; 2) compare vitamin D metabolite levels in wild and captive members of the same or similar baboon species; and 3) apply a recently developed method currently used in humans for measuring multiple vitamin D metabolites as a panel to explore if/how these metabolites can inform us on vitamin D sufficiency. Serum samples from males of three baboon species in the wild: Papio anubis (olive baboon, dark exposed skin), P. cynocephalus (yellow baboon, brown exposed skin), and P. hamadryas (hamadryas baboon, pink exposed skin), were compared with vitamin D supplemented captive olive baboons with sun exposure. Liquid chromatography/tandem mass spectrometry (LC/MS/MS) measured vitamin D and its main metabolites. Cholecalciferol, 25 hydroxyvitamin D (25(OH)D ), and 24,25 dihydroxyvitamin D (24,25(OH) D ), showed significant differences by species. The levels of cholecalciferol due to supplements in the captive olive baboons did not convert to higher 25(OH)D while the wild olive baboons exhibited the lowest levels for both cholecalciferol and 25(OH)D . Further metabolic conversion of 25(OH)D to 24,25(OH) D indicated that all baboons had more similar conversion ratios and these were within the same range found for humans that are depicted as having adequate vitamin D levels. This study provided evidence that exposed skin color does influence vitamin D3 levels, with lower levels in darker skinned species, but these differences are eliminated in the downstream metabolite conversion indicating strong regulatory control.
Keywords: Africa South of the Sahara; Aging; Animal Distribution; Animals; Animals, Wild; Animals, Zoo; Dietary Supplements; Male; Papio; Skin Pigmentation; Species Specificity; Vitamin D; Vitamin D Deficiency

A comprehensive clinical and genetic study in 127 patients with ID in Kinshasa, DR Congo. - Lumaka, Aimé; Race, Valerie; Peeters, Hilde; Corveleyn, Anniek; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Song, Xiaofei; Mubungu, Gerrye; Posey, Jennifer; Lupski, James R; Vermeesch, Joris R; Lukusa, Prosper; et al. (Am J Med Genet A, 2018)
Pathogenic variants account for 4 to 41% of patients with intellectual disability (ID) or developmental delay (DD). In Sub-Saharan Africa, the prevalence of ID is thought to be higher, but data in Central Africa are limited to some case reports. In addition, clinical descriptions of some syndromes are not available for this population. This study aimed at providing an estimate for the fraction of ID/DD for which an underlying etiological genetic cause may be elucidated and provide insights into their clinical presentation in special institutions in a Central African country. A total of 127 patients (33 females and 94 males, mean age 10.03 ± 4.68 years), were recruited from six institutions across Kinshasa. A clinical diagnosis was achieved in 44 but molecular confirmation was achieved in 21 of the 22 patients with expected genetic defect (95% clinical sensitivity). Identified diseases included Down syndrome (15%), submicroscopic copy number variants (9%), aminoacylase deficiency (0.8%), Partington syndrome in one patient (0.8%) and his similarly affected brother, X-linked syndromic Mental Retardation type 33 (0.8%), and two conditions without clear underlying molecular genetic etiologies (Oculo-Auriculo-Vertebral and Amniotic Bands Sequence). We have shown that genetic etiologies, similar to those reported in Caucasian subjects, are a common etiologic cause of ID in African patients from Africa. We have confirmed the diagnostic utility of clinical characterization prior to genetic testing. Finally, our clinical descriptions provide insights into the presentation of these genetic diseases in African patients.
Keywords: Adolescent; Adult; Algorithms; Child; Child, Preschool; Comparative Genomic Hybridization; Democratic Republic of the Congo; Developmental Disabilities; Disease Management; Exome Sequencing; Facies; Female; Genetic Association Studies; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Homeodomain Proteins; Humans; Infant; Intellectual Disability; Male; Phenotype; Syndrome; Transcription Factors; Trinucleotide Repeat Expansion; Trinucleotide Repeats; Workflow; X Chromosome Inactivation; Young Adult

Comprehensive genomic analysis of patients with disorders of cerebral cortical development. - Wiszniewski, Wojciech; Gawlinski, Pawel; Gambin, Tomasz; Bekiesinska-Figatowska, Monika; Obersztyn, Ewa; Antczak-Marach, Dorota; Akdemir, Zeynep Hande Coban; Harel, Tamar; Karaca, Ender; Jurek, Marta; Sobecka, Katarzyna; Nowakowska, Beata; et al. (Eur J Hum Genet, 2018)
Malformations of cortical development (MCDs) manifest with structural brain anomalies that lead to neurologic sequelae, including epilepsy, cerebral palsy, developmental delay, and intellectual disability. To investigate the underlying genetic architecture of patients with disorders of cerebral cortical development, a cohort of 54 patients demonstrating neuroradiologic signs of MCDs was investigated. Individual genomes were interrogated for single-nucleotide variants (SNV) and copy number variants (CNV) with whole-exome sequencing and chromosomal microarray studies. Variation affecting known MCDs-associated genes was found in 16/54 cases, including 11 patients with SNV, 2 patients with CNV, and 3 patients with both CNV and SNV, at distinct loci. Diagnostic pathogenic SNV and potentially damaging variants of unknown significance (VUS) were identified in two groups of seven individuals each. We demonstrated that de novo variants are important among patients with MCDs as they were identified in 10/16 individuals with a molecular diagnosis. Three patients showed changes in known MCDs genes  and a clinical phenotype beyond the usual characteristics observed, i.e., phenotypic expansion, for a particular known disease gene clinical entity. We also discovered 2 likely candidate genes, CDH4, and ASTN1, with human and animal studies supporting their roles in brain development, and 5 potential candidate genes. Our findings emphasize genetic heterogeneity of MCDs disorders and postulate potential novel candidate genes involved in cerebral cortical development.
Keywords: Cadherins; DNA Copy Number Variations; Exome; Female; Genetic Heterogeneity; Humans; Male; Malformations of Cortical Development; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Cell Surface

Contributions of rare coding variants in hypotension syndrome genes to population blood pressure variation. - Nandakumar, Priyanka; Morrison, Alanna C; Grove, Megan L; Eric Boerwinkle; Chakravarti, Aravinda (Medicine (Baltimore), 2018)
Rare variants, in particular renal salt handling genes, contribute to monogenic forms of hypertension and hypotension syndromes with electrolyte abnormalities. A study by Ji et al (2008) demonstrated this effect for rare loss-of-function coding variants in SLC12A3 (NCCT), SLC12A1 (NKCC2), and KCNJ1 (ROMK) that led to reduction of ∼6 mm Hg for SBP and ∼3 mm Hg for DBP among carriers in 2492 European ancestry Framingham Heart Study (FHS) subjects. These findings support a potentially large role for these variants in interindividual variation in systolic and diastolic blood pressure (SBP, DBP) in the population. The present study focuses on replicating the analyses completed by Ji et al to identify effects of rare variants in the population-based Atherosclerosis Risk in Communities (ARIC) study.We attempted to replicate the findings by Ji et al by applying their criteria to identify putative loss-of-function variants with allele frequency <0.001 and complete conservation across a set of orthologs, to exome sequencing data from 7444 European ancestry participants of the ARIC study.Although we failed to replicate the previous findings when applying their methods to the ARIC study data, we observed a similar effect when we restricted analyses to the subset of variants they observed.These results simultaneously support the utility of exome sequencing data for studying extremely rare coding variants in hypertension and underscore the need for improved filtering methods for identifying functional variants in human sequences.
Keywords: Black People; Blood Pressure; Exome Sequencing; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Hypertension; Hypotension; Male; Middle Aged; Phenotype; Potassium Channels, Inwardly Rectifying; Prospective Studies; Reproducibility of Results; Risk Factors; Solute Carrier Family 12, Member 1; Solute Carrier Family 12, Member 3; White People

Effects of Gender-Specific Differences, Inflammatory Response, and Genetic Variation on the Associations Among Depressive Symptoms and the Risk of Major Adverse Coronary Events in Patients With Acute Coronary Syndrome. - Sanner, Jennifer; Grove, Megan L; Yu, Erica; Moeller, F Gerard; Cron, Stanley G; Eric Boerwinkle; Morrison, Alanna C; Frazier, Lorraine (Biol Res Nurs, 2018)
Depressive symptoms independently contribute to major adverse coronary events (MACEs), with the biological immune response to depression being a likely mediator of this relationship. To determine whether genetic- and/or gender-specific phenotypic differences contribute to associations among depressive symptoms, inflammatory response, and risk of MACE in patients with acute coronary syndrome (ACS), we conducted a prospective study of 1,117 ACS patients to test a gender-specific model in which depressive symptoms (Beck Depression Inventory-II [BDI-II]) are associated with risk of MACE. Cox proportional hazards models were used to model time to incident MACE and determine whether single-nucleotide polymorphisms (SNPs) in specific inflammatory protein-coding genes and depressive symptoms interact to influence levels of inflammatory proteins or risk of MACE. Females had significantly higher high-sensitivity C-reactive protein and monocyte chemoattractant protein-1 levels. Depression status differed by gender (29.9% of females and 21.1% of males had BDI-II scores indicative of depression [ p = .0014]). Depressive symptoms were associated with MACE; however, the interaction between these symptoms and gender was not significant. SNPs and depressive symptoms did not interact to influence inflammation or MACE. More females than males had BDI-II scores indicative of depression, yet the association between positive depressive symptom status and MACE did not vary by gender. Nor did the SNPs interact with depressive symptoms to influence inflammation or MACE. It remains of interest to identify a high-risk subgroup of ACS patients with genetic polymorphisms that result in immunoinflammatory dysregulation in the presence of depressive symptoms.
Keywords: Acute Coronary Syndrome; Aged; Depression; Female; Genetic Variation; Humans; Inflammation; Male; Middle Aged; Prospective Studies; Risk Assessment; Sex Factors

An Epigenome-Wide Association Study of Obesity-Related Traits. - Dhana, Klodian; Braun, Kim V E; Nano, Jana; Voortman, Trudy; Demerath, Ellen W; Guan, Weihua; Fornage, Myriam; van Meurs, Joyce B J; Uitterlinden, André G; Hofman, Albert; Franco, Oscar H; Dehghan, Abbas (Am J Epidemiol, 2018)
We conducted an epigenome-wide association study on obesity-related traits. We used data from 2 prospective, population-based cohort studies: the Rotterdam Study (RS) (2006-2013) and the Atherosclerosis Risk in Communities (ARIC) Study (1990-1992). We used the RS (n = 1,450) as the discovery panel and the ARIC Study (n = 2,097) as the replication panel. Linear mixed-effect models were used to assess the cross-sectional associations between genome-wide DNA methylation in leukocytes and body mass index (BMI) and waist circumference (WC), adjusting for sex, age, smoking, leukocyte proportions, array number, and position on array. The latter 2 variables were modeled as random effects. Fourteen 5'-C-phosphate-G-3' (CpG) sites were associated with BMI and 26 CpG sites with WC in the RS after Bonferroni correction (P < 1.07 × 10-7), of which 12 and 13 CpGs were replicated in the ARIC Study, respectively. The most significant novel CpGs were located on the Musashi RNA binding protein 2 gene (MSI2; cg21139312) and the leucyl-tRNA synthetase 2, mitochondrial gene (LARS2; cg18030453) and were associated with both BMI and WC. CpGs at BRDT, PSMD1, IFI44L, MAP1A, and MAP3K5 were associated with BMI. CpGs at LGALS3BP, MAP2K3, DHCR24, CPSF4L, and TMEM49 were associated with WC. We report novel associations between methylation at MSI2 and LARS2 and obesity-related traits. These results provide further insight into mechanisms underlying obesity-related traits, which can enable identification of new biomarkers in obesity-related chronic diseases.
Keywords: Amino Acyl-tRNA Synthetases; Biomarkers; CpG Islands; DNA Methylation; Epigenomics; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Netherlands; Obesity; Phenotype; Prospective Studies; RNA-Binding Proteins; United States

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.
Keywords: Adult; Aged; Aged, 80 and over; Blood Pressure; Cardiovascular Diseases; Cells, Cultured; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Testing; Genetics, Population; Genome-Wide Association Study; Human Umbilical Vein Endothelial Cells; Humans; Hypertension; Life Style; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

Genetic and mechanistic diversity in pediatric hemophagocytic lymphohistiocytosis. - Chinn, Ivan K; Eckstein, Olive S; Peckham-Gregory, Erin C; Goldberg, Baruch R; Forbes, Lisa R; Nicholas, Sarah K; Mace, Emily M; Vogel, Tiphanie P; Abhyankar, Harshal A; Diaz, Maria I; Heslop, Helen E; Krance, Robert A; et al. (Blood, 2018)
The HLH-2004 criteria are used to diagnose hemophagocytic lymphohistiocytosis (HLH), yet concern exists for their misapplication, resulting in suboptimal treatment of some patients. We sought to define the genomic spectrum and associated outcomes of a diverse cohort of children who met the HLH-2004 criteria. Genetic testing was performed clinically or through research-based whole-exome sequencing. Clinical metrics were analyzed with respect to genomic results. Of 122 subjects enrolled over the course of 17 years, 101 subjects received genetic testing. Biallelic familial HLH (fHLH) gene defects were identified in only 19 (19%) and correlated with presentation at younger than 1 year of age ( < .0001). Digenic fHLH variants were observed but lacked statistical support for disease association. In 28 (58%) of 48 subjects, research whole-exome sequencing analyses successfully identified likely molecular explanations, including underlying primary immunodeficiency diseases, dysregulated immune activation and proliferation disorders, and potentially novel genetic conditions. Two-thirds of patients identified by the HLH-2004 criteria had underlying etiologies for HLH, including genetic defects, autoimmunity, and malignancy. Overall survival was 45%, and increased mortality correlated with HLH triggered by infection or malignancy ( < .05). Differences in survival did not correlate with genetic profile or extent of therapy. HLH should be conceptualized as a phenotype of critical illness characterized by toxic activation of immune cells from different underlying mechanisms. In most patients with HLH, targeted sequencing of fHLH genes remains insufficient for identifying pathogenic mechanisms. Whole-exome sequencing, however, may identify specific therapeutic opportunities and affect hematopoietic stem cell transplantation options for these patients.
Keywords: Adolescent; Child; Child, Preschool; Cohort Studies; Female; Genetic Testing; Genome, Human; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Infant; Infant, Newborn; Lymphohistiocytosis, Hemophagocytic; Male; Multifactorial Inheritance

Genetic variants in microRNA genes and targets associated with cardiovascular disease risk factors in the African-American population. - Li, Chang; Grove, Megan L; Yu, Bing; Jones, Barbara C; Morrison, Alanna; Eric Boerwinkle; Liu, Xiaoming (Hum Genet, 2018)
The purpose of this study is to identify microRNA (miRNA) related polymorphism, including single nucleotide variants (SNVs) in mature miRNA-encoding sequences or in miRNA-target sites, and their association with cardiovascular disease (CVD) risk factors in African-American population. To achieve our objective, we examined 1900 African-Americans from the Atherosclerosis Risk in Communities study using SNVs identified from whole-genome sequencing data. A total of 971 SNVs found in 726 different mature miRNA-encoding sequences and 16,057 SNVs found in the three prime untranslated region (3'UTR) of 3647 protein-coding genes were identified and interrogated their associations with 17 CVD risk factors. Using single-variant-based approach, we found 5 SNVs in miRNA-encoding sequences to be associated with serum Lipoprotein(a) [Lp(a)], high-density lipoprotein (HDL) or triglycerides, and 2 SNVs in miRNA-target sites to be associated with Lp(a) and HDL, all with false discovery rates of 5%. Using a gene-based approach, we identified 3 pairs of associations between gene NSD1 and platelet count, gene HSPA4L and cardiac troponin T, and gene AHSA2 and magnesium. We successfully validated the association between a variant specific to African-American population, NR_039880.1:n.18A>C, in mature hsa-miR-4727-5p encoding sequence and serum HDL level in an independent sample of 2135 African-Americans. Our study provided candidate miRNAs and their targets for further investigation of their potential contribution to ethnic disparities in CVD risk factors.
Keywords: 3' Untranslated Regions; Adult; Black or African American; Cardiovascular Diseases; Female; Genetic Predisposition to Disease; Genotyping Techniques; Humans; Male; MicroRNAs; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Whole Genome Sequencing

Genetic Variants in SGLT1, Glucose Tolerance, and Cardiometabolic Risk. - Seidelmann, Sara B; Feofanova, Elena; Yu, Bing; Franceschini, Nora; Claggett, Brian; Kuokkanen, Mikko; Puolijoki, Hannu; Ebeling, Tapani; Perola, Markus; Salomaa, Veikko; Shah, Amil; Coresh, Josef; et al. (J Am Coll Cardiol, 2018)
BACKGROUND: Loss-of-function mutations in the SGLT1 (sodium/glucose co-transporter-1) gene result in a rare glucose/galactose malabsorption disorder and neonatal death if untreated. In the general population, variants related to intestinal glucose absorption remain uncharacterized. OBJECTIVES: The goal of this study was to identify functional SGLT1 gene variants and characterize their clinical consequences. METHODS: Whole exome sequencing was performed in the ARIC (Atherosclerosis Risk in Communities) study participants enrolled from 4 U.S. communities. The association of functional, nonsynonymous substitutions in SGLT1 with 2-h oral glucose tolerance test results was determined. Variants related to impaired glucose tolerance were studied, and Mendelian randomization analysis of cardiometabolic outcomes was performed. RESULTS: Among 5,687 European-American subjects (mean age 54 ± 6 years; 47% male), those who carried a haplotype of 3 missense mutations (frequency of 6.7%)-Asn51Ser, Ala411Thr, and His615Gln-had lower 2-h glucose and odds of impaired glucose tolerance than noncarriers (β-coefficient: -8.0; 95% confidence interval [CI]: -12.7 to -3.3; OR: 0.71; 95% CI: 0.59 to 0.86, respectively). The association of the haplotype with oral glucose tolerance test results was consistent in a replication sample of 2,791 African-American subjects (β = -16.3; 95% CI: -36.6 to 4.1; OR: 0.39; 95% CI: 0.17 to 0.91) and an external European-Finnish population sample of 6,784 subjects (β = -3.2; 95% CI: -6.4 to -0.02; OR: 0.81; 95% CI: 0.68 to 0.98). Using a Mendelian randomization approach in the index cohort, the estimated 25-year effect of a reduction of 20 mg/dl in 2-h glucose via SGLT1 inhibition would be reduced prevalent obesity (OR: 0.43; 95% CI: 0.23 to 0.63), incident diabetes (hazard ratio [HR]: 0.58; 95% CI: 0.35 to 0.81), heart failure (HR: 0.53; 95% CI: 0.24 to 0.83), and death (HR: 0.66; 95% CI: 0.42 to 0.90). CONCLUSIONS: Functionally damaging missense variants in SGLT1 protect from diet-induced hyperglycemia in multiple populations. Reduced intestinal glucose uptake may protect from long-term cardiometabolic outcomes, providing support for therapies that target SGLT1 function to prevent and treat metabolic conditions.
Keywords: Cardiovascular Diseases; Exome Sequencing; Female; Genetic Variation; Glucose; Glucose Tolerance Test; Humans; Hyperglycemia; Intestinal Absorption; Loss of Function Mutation; Male; Mendelian Randomization Analysis; Middle Aged; Outcome Assessment, Health Care; Protective Factors; Risk Assessment; Sodium-Glucose Transporter 1; United States; White People

Genetic Variants Influencing Plasma Renin Activity in Hypertensive Patients From the PEAR Study (Pharmacogenomic Evaluation of Antihypertensive Responses). - McDonough, Caitrin W; Magvanjav, Oyunbileg; Sá, Ana C C; El Rouby, Nihal M; Dave, Chintan; Deitchman, Amelia N; Kawaguchi-Suzuki, Marina; Mei, Wenbin; Shen, Yong; Singh, Ravi Shankar Prasad; Solayman, Mohamed; Bailey, Kent R; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Plasma renin is an important regulator of blood pressure (BP). Plasma renin activity (PRA) has been shown to correlate with variability in BP response to antihypertensive agents. We conducted a genome-wide association study to identify single-nucleotide polymorphisms (SNPs) associated with baseline PRA using data from the PEAR study (Pharmacogenomic Evaluation of Antihypertensive Responses). METHODS: Multiple linear regression analysis was performed in 461 whites and 297 blacks using an additive model, adjusting for age, sex, and ancestry-specific principal components. Top SNPs were prioritized by testing the expected direction of association for BP response to atenolol and hydrochlorothiazide. Top regions from the BP response prioritization were tested for functional evidence through differences in gene expression by genotype using RNA sequencing data. Regions with functional evidence were assessed for replication with baseline PRA in an independent study (PEAR-2). RESULTS: Our top SNP rs3784921 was in the gene region. The G allele of rs3784921 was associated with higher baseline PRA (β=0.47; =2.09×10) and smaller systolic BP reduction in response to hydrochlorothiazide (β=2.97; 1-sided =0.006). In addition, expression differed by rs3784921 genotype (=0.007), and rs1802409, a proxy SNP for rs3784921 (=0.98-1.00), replicated in PEAR-2 (β=0.15; 1-sided =0.038). Additional SNPs associated with baseline PRA that passed BP response prioritization were in/near the genes and CONCLUSIONS: We identified multiple regions associated with baseline PRA that were prioritized through BP response signals to 2 mechanistically different antihypertensive drugs. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifier: NCT00246519.
Keywords: Adolescent; Adult; Aged; Antihypertensive Agents; Atenolol; Blood Pressure; Genome-Wide Association Study; Humans; Hydrochlorothiazide; Hypertension; Male; Middle Aged; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Prospective Studies; Renin; Treatment Outcome; United States; Young Adult

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Biomarkers; Bipolar Disorder; Body Mass Index; C-Reactive Protein; Child; Female; Genetic Loci; Genome-Wide Association Study; Humans; Inflammation; Liver; Male; Mendelian Randomization Analysis; Metabolic Networks and Pathways; Middle Aged; Schizophrenia; Young Adult

Genomes of the Hymenoptera. - Branstetter, Michael G; Childers, Anna K; Cox-Foster, Diana; Hopper, Keith R; Kapheim, Karen M; Toth, Amy L; Worley, Kim C (Curr Opin Insect Sci, 2018)
Hymenoptera is the second-most sequenced arthropod order, with 52 publically archived genomes (71 with ants, reviewed elsewhere), however these genomes do not capture the breadth of this very diverse order (Figure 1, Table 1). These sequenced genomes represent only 15 of the 97 extant families. Although at least 55 other genomes are in progress in an additional 11 families (see Table 2), stinging wasps represent 35 (67%) of the available and 42 (76%) of the in progress genomes. A more comprehensive catalog of hymenopteran genomes is needed for research into the evolutionary processes underlying the expansive diversity in terms of ecology, behavior, and physiological traits within this group. Additional sequencing is needed to generate an assembly for even 0.05% of the estimated 1 million hymenopteran species, and we recommend premier level assemblies for at least 0.1% of the >150,000 named species dispersed across the order. Given the haplodiploid sex determination in Hymenoptera, haploid male sequencing will help minimize genome assembly issues to enable higher quality genome assemblies.
Keywords: Animals; Female; Genome, Insect; Haploidy; Hymenoptera; Male; Phylogeny

A heterozygous mutation in RPGR associated with X-linked retinitis pigmentosa in a patient with Turner syndrome mosaicism (45,X/46,XX). - Zhou, Qi; Yao, Fengxia; Wang, Feng; Li, Hui; Rui Chen; Sui, Ruifang (Am J Med Genet A, 2018)
Turner syndrome with retinitis pigmentosa (RP) is rare, with only three cases reported based on clinical examination alone. We summarized the 4-year follow-up and molecular findings in a 28-year-old patient with Turner syndrome and the typical features of short stature and neck webbing, who also had X-linked RP. Her main complaints were night blindness and progressive loss of vision since the age of 9 years. Ophthalmologic examination, optical coherent tomographic imaging, and visual electrophysiology tests showed classic manifestations of RP. The karyotype of peripheral blood showed mosaicism (45,X [72%]/46,XX[28%]). A novel heterozygous frameshift mutation (c.2403_2406delAGAG, p.T801fsX812) in the RP GTPase regulator (RPGR) gene was detected using next generation sequencing and validated by Sanger sequencing. We believe that this is the first report of X-linked RP in a patient with Turner syndrome associated with mosaicism, and an RPGR heterozygous mutation. We hypothesize that X-linked RP in this woman is not related to Turner syndrome, but may be a manifestation of the lack of a normal paternal X chromosome with intact but mutated RPGR.
Keywords: Adult; Eye Proteins; Female; Frameshift Mutation; Genes, X-Linked; Genomics; Heterozygote; Humans; In Situ Hybridization, Fluorescence; Male; Mutation; Pedigree; Phenotype; Retinitis Pigmentosa; Sequence Analysis, DNA; Turner Syndrome

Heterozygous Truncating Variants in POMP Escape Nonsense-Mediated Decay and Cause a Unique Immune Dysregulatory Syndrome. - Poli, M Cecilia; Ebstein, Frédéric; Nicholas, Sarah K; de Guzman, Marietta M; Forbes, Lisa R; Chinn, Ivan K; Mace, Emily M; Vogel, Tiphanie P; Carisey, Alexandre F; Benavides, Felipe; Coban-Akdemir, Zeynep H; Richard A Gibbs; et al. (Am J Hum Genet, 2018)
The proteasome processes proteins to facilitate immune recognition and host defense. When inherently defective, it can lead to aberrant immunity resulting in a dysregulated response that can cause autoimmunity and/or autoinflammation. Biallelic or digenic loss-of-function variants in some of the proteasome subunits have been described as causing a primary immunodeficiency disease that manifests as a severe dysregulatory syndrome: chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature (CANDLE). Proteasome maturation protein (POMP) is a chaperone for proteasome assembly and is critical for the incorporation of catalytic subunits into the proteasome. Here, we characterize and describe POMP-related autoinflammation and immune dysregulation disease (PRAID) discovered in two unrelated individuals with a unique constellation of early-onset combined immunodeficiency, inflammatory neutrophilic dermatosis, and autoimmunity. We also begin to delineate a complex genetic mechanism whereby de novo heterozygous frameshift variants in the penultimate exon of POMP escape nonsense-mediated mRNA decay (NMD) and result in a truncated protein that perturbs proteasome assembly by a dominant-negative mechanism. To our knowledge, this mechanism has not been reported in any primary immunodeficiencies, autoinflammatory syndromes, or autoimmune diseases. Here, we define a unique hypo- and hyper-immune phenotype and report an immune dysregulation syndrome caused by frameshift mutations that escape NMD.
Keywords: Base Sequence; Cell Line; Endoplasmic Reticulum Stress; Exons; Family; Frameshift Mutation; Genetic Predisposition to Disease; Heterozygote; Humans; Immunologic Deficiency Syndromes; Immunophenotyping; Infant, Newborn; Inflammation; Interferon Type I; Male; Molecular Chaperones; Mutant Proteins; Mutation; Nonsense Mediated mRNA Decay; Phenotype; Proteasome Endopeptidase Complex; RNA, Messenger; Syndrome; Unfolded Protein Response

Identification of likely pathogenic and known variants in TSPEAR, LAMB3, BCOR, and WNT10A in four Turkish families with tooth agenesis. - Du, Renqian; Dinckan, Nuriye; Song, Xiaofei; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Guven, Yeliz; Aktoren, Oya; Kayserili, Hulya; Petty, Lauren E; Donna M Muzny; Below, Jennifer E; Eric Boerwinkle; et al. (Hum Genet, 2018)
Tooth agenesis (TA), the failure of development of one or more permanent teeth, is a common craniofacial abnormality observed in different world populations. The genetic etiology of TA is heterogeneous; more than a dozen genes have been associated with isolated or nonsyndromic TA, and more than 80 genes with syndromic forms. In this study, we applied whole exome sequencing (WES) to identify candidate genes contributing to TA in four Turkish families. Likely pathogenic variants with a low allele frequency in the general population were identified in four disease-associated genes, including two distinct variants in TSPEAR, associated with syndromic and isolated TA in one family each; a variant in LAMB3 associated with syndromic TA in one family; and a variant in BCOR plus a disease-associated WNT10A variant in one family with syndromic TA. With the notable exception of WNT10A (Tooth agenesis, selective, 4, MIM #150400), the genotype-phenotype relationships described in the present cohort represent an expansion of the clinical spectrum associated with these genes: TSPEAR (Deafness, autosomal recessive 98, MIM #614861), LAMB3 (Amelogenesis imperfecta, type IA, MIM #104530; Epidermolysis bullosa, junctional, MIMs #226700 and #226650), and BCOR (Microphthalmia, syndromic 2, MIM #300166). We provide evidence supporting the candidacy of these genes with TA, and propose TSPEAR as a novel nonsyndromic TA gene. Our data also suggest potential multilocus genomic variation, or mutational burden, in a single family, involving the BCOR and WNT10A loci, underscoring the complexity of the genotype-phenotype relationship in the common complex trait of TA.
Keywords: Anodontia; Cell Adhesion Molecules; Child; Child, Preschool; Female; Genetic Markers; Humans; Kalinin; Male; Mutation; Pedigree; Phenotype; Proteins; Proto-Oncogene Proteins; Repressor Proteins; Turkey; Wnt Proteins

Integrated Molecular Characterization of Testicular Germ Cell Tumors. - Shen, Hui; Shih, Juliann; Hollern, Daniel P; Wang, Linghua; Bowlby, Reanne; Tickoo, Satish K; Thorsson, Vesteinn; Mungall, Andrew J; Newton, Yulia; Hegde, Apurva M; Armenia, Joshua; Sánchez-Vega, Francisco; et al. (Cell Rep, 2018)
We studied 137 primary testicular germ cell tumors (TGCTs) using high-dimensional assays of genomic, epigenomic, transcriptomic, and proteomic features. These tumors exhibited high aneuploidy and a paucity of somatic mutations. Somatic mutation of only three genes achieved significance-KIT, KRAS, and NRAS-exclusively in samples with seminoma components. Integrated analyses identified distinct molecular patterns that characterized the major recognized histologic subtypes of TGCT: seminoma, embryonal carcinoma, yolk sac tumor, and teratoma. Striking differences in global DNA methylation and microRNA expression between histology subtypes highlight a likely role of epigenomic processes in determining histologic fates in TGCTs. We also identified a subset of pure seminomas defined by KIT mutations, increased immune infiltration, globally demethylated DNA, and decreased KRAS copy number. We report potential biomarkers for risk stratification, such as miRNA specifically expressed in teratoma, and others with molecular diagnostic potential, such as CpH (CpA/CpC/CpT) methylation identifying embryonal carcinomas.
Keywords: DNA Copy Number Variations; DNA Methylation; Gene Expression Regulation, Neoplastic; Humans; Male; MicroRNAs; Neoplasms, Germ Cell and Embryonal; Proto-Oncogene Proteins c-kit; ras Proteins; Seminoma; Testicular Neoplasms

Marker chromosome genomic structure and temporal origin implicate a chromoanasynthesis event in a family with pleiotropic psychiatric phenotypes. - Grochowski, Christopher M; Gu, Shen; Bo Yuan; Tcw, Julia; Brennand, Kristen J; Sebat, Jonathan; Malhotra, Dheeraj; McCarthy, Shane; Rudolph, Uwe; Lindstrand, Anna; Chong, Zechen; Levy, Deborah L; et al. (Hum Mutat, 2018)
Small supernumerary marker chromosomes (sSMC) are chromosomal fragments difficult to characterize genomically. Here, we detail a proband with schizoaffective disorder and a mother with bipolar disorder with psychotic features who present with a marker chromosome that segregates with disease. We explored the architecture of this marker and investigated its temporal origin. Array comparative genomic hybridization (aCGH) analysis revealed three duplications and three triplications that spanned the short arm of chromosome 9, suggestive of a chromoanasynthesis-like event. Segregation of marker genotypes, phased using sSMC mosaicism in the mother, provided evidence that it was generated during a germline-level event in the proband's maternal grandmother. Whole-genome sequencing (WGS) was performed to resolve the structure and junctions of the chromosomal fragments, revealing further complexities. While structural variations have been previously associated with neuropsychiatric disorders and marker chromosomes, here we detail the precise architecture, human life-cycle genesis, and propose a DNA replicative/repair mechanism underlying formation.
Keywords: Bipolar Disorder; Chromosome Aberrations; Chromosome Disorders; Chromosome Duplication; Chromosomes, Human, Pair 9; Comparative Genomic Hybridization; Female; Genetic Markers; Humans; In Situ Hybridization, Fluorescence; Karyotyping; Male; Pedigree; Phenotype; Psychotic Disorders; Whole Genome Sequencing

Maternal Exposures Associated with Autism Spectrum Disorder in Jamaican Children. - Christian, MacKinsey A; Samms-Vaughan, Maureen; Lee, MinJae; Bressler, Jan; Hessabi, Manouchehr; Grove, Megan L; Shakespeare-Pellington, Sydonnie; Coore Desai, Charlene; Reece, Jody-Ann; Loveland, Katherine A; Eric Boerwinkle; Rahbar, Mohammad H (J Autism Dev Disord, 2018)
Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder with poorly understood etiology. Many maternal exposures during pregnancy and breastfeeding potentially interfere with neurodevelopment. Using data from two age- and sex-matched case-control studies in Jamaica (n = 298 pairs), results of conditional logistic regression analyses suggest that maternal exposures to fever or infection (matched odds ratio (MOR) = 3.12, 95% CI 1.74-5.60), physical trauma (MOR 2.02, 95% CI 1.01-4.05), and oil-based paints (MOR 1.99, 95% CI 1.14-3.46) may be associated with ASD. Additionally, maternal exposure to oil-based paints may modify the relationship between maternal exposure to pesticides and ASD, which deepens our understanding of the association between pesticides and ASD.
Keywords: Adult; Autism Spectrum Disorder; Child; Communicable Diseases; Female; Humans; Jamaica; Male; Maternal Exposure; Pesticides; Pregnancy; Volatile Organic Compounds

MLH1-rheMac hereditary nonpolyposis colorectal cancer syndrome in rhesus macaques. - Brammer, David W; Gillespie, Patrick J; Tian, Mei; Young, Daniel; Raveendran, Muthuswamy; Williams, Lawrence E; Gagea, Mihai; Benavides, Fernando J; Perez, Carlos J; Broaddus, Russell R; Bernacky, Bruce J; Barnhart, Kirstin F; et al. (Proc Natl Acad Sci U S A, 2018)
Over the past two decades, 33 cases of colonic adenocarcinomas have been diagnosed in rhesus macaques () at the nonhuman primate colony of the Keeling Center for Comparative Medicine and Research at The University of Texas MD Anderson Cancer Center. The distinctive feature in these cases, based on PET/computed tomography (CT) imaging, was the presence of two or three tumor lesions in different locations, including proximal to the ileocecal juncture, proximal to the hepatic flexure, and/or in the sigmoid colon. These colon carcinoma lesions selectively accumulated [F]fluorodeoxyglucose ([F]FDG) and [F]fluoroacetate ([F]FACE) at high levels, reflecting elevated carbohydrate and fatty acid metabolism in these tumors. In contrast, the accumulation of [F]fluorothymidine ([F]FLT) was less significant, reflecting slow proliferative activity in these tumors. The diagnoses of colon carcinomas were confirmed by endoscopy. The expression of MLH1, MSH2, and MSH6 proteins and the degree of microsatellite instability (MSI) was assessed in colon carcinomas. The loss of MLH1 protein expression was observed in all tumors and was associated with a deletion mutation in the promoter region and/or multiple single-nucleotide polymorphism (SNP) mutations in the gene. All tumors exhibited various degrees of MSI. The pedigree analysis of this rhesus macaque population revealed several clusters of affected animals related to each other over several generations, suggesting an autosomal dominant transmission of susceptibility for colon cancer. The newly discovered hereditary nonpolyposis colorectal cancer syndrome in rhesus macaques, termed -rheMac, may serve as a model for development of novel approaches to diagnosis and therapy of Lynch syndrome in humans.
Keywords: Animals; Colorectal Neoplasms, Hereditary Nonpolyposis; Female; Macaca mulatta; Male; Microsatellite Instability; MutL Protein Homolog 1; Polymorphism, Single Nucleotide; Positron Emission Tomography Computed Tomography; Primate Diseases

NMNAT1 E257K variant, associated with Leber Congenital Amaurosis (LCA9), causes a mild retinal degeneration phenotype. - Eblimit, Aiden; Zaneveld, Smriti Agrawal; Liu, Wei; Thomas, Kandace; Wang, Keqing; Yumei Li; Mardon, Graeme; Rui Chen (Exp Eye Res, 2018)
NMNAT1 (nicotinamide mononucleotide adenylyltransferase 1) encodes a rate-limiting enzyme that catalyzes the biosynthesis of NAD and plays a role in neuroprotection. Mutations in NMNAT1 have been identified to cause a recessive, non-syndromic early form of blindness genetically defined as Leber Congenital Amaurosis 9 (LCA9). One of the most common alleles reported so far in NMNAT1 is the c.769G > A (E257K) missense mutation, which occurs in 70% of all LCA9 cases. However, given its relatively high population frequency and the observation of individuals with homozygous E257K variant without phenotype, the pathogenicity of this allele has been questioned. To address this issue, we have studied the pathogenic effects of this allele by generating a knock-in mouse model. Interestingly, no obvious morphological or functional defects are observed in Nmnat1 E257K homozygous mice up to one year old, even after light-damage. Together with the previous clinical reports, we propose that the E257K allele is a weak hypomorphic allele that has significantly reduced penetrance in the homozygous state. In contrast, compound heterozygous Nmnat1 mice exhibit photoreceptor defects which are exacerbated upon exposure to light. Furthermore, retina tissue- specific Nmnat1 conditional knockout mice exhibit photoreceptor degeneration before the retina has terminally differentiated. These findings suggest that NMNAT1 plays an important role in photoreceptors and is likely involved in both retinal development and maintenance of photoreceptor integrity.
Keywords: Alleles; Animals; Electroretinography; Exons; Female; Gene Knock-In Techniques; Genetic Variation; Leber Congenital Amaurosis; Light; Male; Mice; Mice, Knockout; Mice, Mutant Strains; Nicotinamide-Nucleotide Adenylyltransferase; Phenotype; Point Mutation; Radiation Injuries, Experimental; Retina; Retinal Degeneration

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Racial Groups; Young Adult

A novel NAA10 variant with impaired acetyltransferase activity causes developmental delay, intellectual disability, and hypertrophic cardiomyopathy. - Støve, Svein Isungset; Blenski, Marina; Stray-Pedersen, Asbjørg; Wierenga, Klaas J; Jhangiani, Shalini N; Akdemir, Zeynep Coban; Crawford, David; McTiernan, Nina; Myklebust, Line M; Purcarin, Gabriela; McNall-Knapp, Rene; Wadley, Alexandrea; et al. (Eur J Hum Genet, 2018)
The NAA10-NAA15 complex (NatA) is an N-terminal acetyltransferase that catalyzes N-terminal acetylation of ~40% of all human proteins. N-terminal acetylation has several different roles in the cell, including altering protein stability and degradation, protein localization and protein-protein interactions. In recent years several X-linked NAA10 variants have been associated with genetic disorders. We have identified a previously undescribed NAA10 c.215T>C p.(Ile72Thr) variant in three boys from two unrelated families with a milder phenotypic spectrum in comparison to most of the previously described patients with NAA10 variants. These boys have development delay, intellectual disability, and cardiac abnormalities as overlapping phenotypes. Functional studies reveal that NAA10 Ile72Thr is destabilized, while binding to NAA15 most likely is intact. Surprisingly, the NatA activity of NAA10 Ile72Thr appears normal while its monomeric activity is decreased. This study further broadens the phenotypic spectrum associated with NAA10 deficiency, and adds to the evidence that genotype-phenotype correlations for NAA10 variants are much more complex than initially anticipated.
Keywords: Cardiomyopathy, Hypertrophic; Child, Preschool; Developmental Disabilities; Enzyme Stability; HeLa Cells; Humans; Infant; Intellectual Disability; Male; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Phenotype; Protein Binding; Syndrome

Phenotype expansion and development in Kosaki overgrowth syndrome. - Gawliński, P; Pelc, M; Ciara, E; Jhangiani, S; Jurkiewicz, E; Gambin, T; Różdżyńska-Świątkowska, A; Dawidziuk, M; Coban-Akdemir, Z H; Guilbride, D L; Donna M Muzny; Lupski, J R; et al. (Clin Genet, 2018)
We expand the Kosaki overgrowth syndrome (KOGS) phenotype by over 70% to include 24 unreported KOGS symptoms, in a first male patient, the third overall associated with the PDGFRB c.1751C>G p.(Pro584Arg) mutation. Eighteen of these symptoms are unique to our patient, the remaining six are shared with other patients. Of the 24 unreported features overall, 6 show marked phenotype evolution and varying time of onset. The triangular face detected at 14 months and long palpebral fissures with lateral ectropion at 4 years are present in other members of the cohort. The remaining 4 are unique to Patient 5: pronounced macrocephaly from birth, increasingly triangular anterior skull from 14 months, camptodactyly, emerging at 4 years and worsening joint contractures from 6 years. Compilation of all new symptoms reported here with published clinical data further identifies at least 18 clinical parameters common to all cases to date, encompassing both known KOGS-associated PDGFRB mutations. We therefore propose a set of 18 core KOGS symptoms, with 16 present in early childhood. These results should also impact diagnostic/prognostic scope, intervention and outcome potential for KOGS patients, particularly for developmentally progressive conditions such as scoliosis and myofibroma.
Keywords: Adolescent; Child; Child, Preschool; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Megalencephaly; Musculoskeletal Abnormalities; Mutation; Phenotype; Receptor, Platelet-Derived Growth Factor beta

Phenotypic expansion illuminates multilocus pathogenic variation. - Karaca, Ender; Posey, Jennifer E; Coban Akdemir, Zeynep; Pehlivan, Davut; Harel, Tamar; Jhangiani, Shalini N; Bayram, Yavuz; Song, Xiaofei; Bahrambeigi, Vahid; Yuregir, Ozge Ozalp; Bozdogan, Sevcan; Yesil, Gozde; et al. (Genet Med, 2018)
PURPOSE: Multilocus variation-pathogenic variants in two or more disease genes-can potentially explain the underlying genetic basis for apparent phenotypic expansion in cases for which the observed clinical features extend beyond those reported in association with a "known" disease gene. METHODS: Analyses focused on 106 patients, 19 for whom apparent phenotypic expansion was previously attributed to variation at known disease genes. We performed a retrospective computational reanalysis of whole-exome sequencing data using stringent Variant Call File filtering criteria to determine whether molecular diagnoses involving additional disease loci might explain the observed expanded phenotypes. RESULTS: Multilocus variation was identified in 31.6% (6/19) of families with phenotypic expansion and 2.3% (2/87) without phenotypic expansion. Intrafamilial clinical variability within two families was explained by multilocus variation identified in the more severely affected sibling. CONCLUSION: Our findings underscore the role of multiple rare variants at different loci in the etiology of genetically and clinically heterogeneous cohorts. Intrafamilial phenotypic and genotypic variability allowed a dissection of genotype-phenotype relationships in two families. Our data emphasize the critical role of the clinician in diagnostic genomic analyses and demonstrate that apparent phenotypic expansion may represent blended phenotypes resulting from pathogenic variation at more than one locus.
Keywords: Child, Preschool; Exome; Exome Sequencing; Female; Genetic Association Studies; Genetic Diseases, Inborn; Genetic Variation; Genotype; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Infant; Infant, Newborn; Male; Mutation; Pathology, Molecular; Pedigree; Phenotype

The phenotypic spectrum of Xia-Gibbs syndrome. - Jiang, Yunyun; Wangler, Michael F; McGuire, Amy L; Lupski, James R; Posey, Jennifer E; Khayat, Michael M; Murdock, David R; Sanchez-Pulido, Luis; Ponting, Chris P; Xia, Fan; Hunter, Jill V; Meng, Qingchang; et al. (Am J Med Genet A, 2018)
Xia-Gibbs syndrome (XGS: OMIM # 615829) results from de novo truncating mutations within the AT-Hook DNA Binding Motif Containing 1 gene (AHDC1). To further define the phenotypic and molecular spectrum of this disorder, we established an XGS Registry and recruited patients from a worldwide pool of approximately 60 probands. Additional de novo truncating mutations were observed among 25 individuals, extending both the known number of mutation sites and the range of positions within the coding region that were sensitive to alteration. Detailed phenotypic examination of 20 of these patients via clinical records review and data collection from additional surveys showed a wider age range than previously described. Data from developmental milestones showed evidence for delayed speech and that males were more severely affected. Neuroimaging from six available patients showed an associated thinning of the corpus callosum and posterior fossa cysts. An increased risk of both scoliosis and seizures relative to the population burden was also observed. Data from a modified autism screening tool revealed that XGS shares significant overlap with autism spectrum disorders. These details of the phenotypic heterogeneity of XGS implicate specific genotype/phenotype correlations and suggest potential clinical management guidelines.
Keywords: Autism Spectrum Disorder; Child; Cognition; Corpus Callosum; Developmental Disabilities; DNA-Binding Proteins; Face; Female; Humans; Male; Mutation; Pedigree; Phenotype; Registries; Seizures; Syndrome; Young Adult

POU6f1 Mediates Neuropeptide-Dependent Plasticity in the Adult Brain. - McClard, Cynthia K; Kochukov, Mikhail Y; Herman, Isabella; Liu, Zhandong; Eblimit, Aiden; Moayedi, Yalda; Ortiz-Guzman, Joshua; Colchado, Daniel; Pekarek, Brandon; Panneerselvam, Sugi; Mardon, Graeme; Arenkiel, Benjamin R (J Neurosci, 2018)
The mouse olfactory bulb (OB) features continued, activity-dependent integration of adult-born neurons, providing a robust model with which to examine mechanisms of plasticity in the adult brain. We previously reported that local OB interneurons secrete the neuropeptide corticotropin-releasing hormone (CRH) in an activity-dependent manner onto adult-born granule neurons and that local CRH signaling promotes expression of synaptic machinery in the bulb. This effect is mediated via activation of the CRH receptor 1 (), which is developmentally regulated during adult-born neuron maturation. CRHR1 is a G-protein-coupled receptor that activates CREB-dependent transcription in the presence of CRH. Therefore, we hypothesized that locally secreted CRH activates CRHR1 to initiate circuit plasticity programs. To identify such programs, we profiled gene expression changes associated with CRHR1 activity in adult-born neurons of the OB. Here, we show that CRHR1 activity influences expression of the brain-specific Homeobox-containing transcription factor POU Class 6 Homeobox 1 (). To elucidate the contributions of toward activity-dependent circuit remodeling, we targeted CRHR1 neurons in male and female mice for cell-type-specific manipulation of expression. Whereas loss of in CRHR1 neurons resulted in reduced dendritic complexity and decreased synaptic connectivity, overexpression of in CRHR1 neurons promoted dendritic outgrowth and branching and influenced synaptic function. Together, these findings suggest that the transcriptional program directed by downstream of local CRH signaling in adult-born neurons influences circuit dynamics in response to activity-dependent peptide signaling in the adult brain. Elucidating mechanisms of plasticity in the adult brain is helpful for devising strategies to understand and treat neurodegeneration. Circuit plasticity in the adult mouse olfactory bulb is exemplified by both continued cell integration and synaptogenesis. We previously reported that these processes are influenced by local neuropeptide signaling in an activity-dependent manner. Here, we show that local corticotropin-releasing hormone (CRH) signaling induces dynamic gene expression changes in CRH receptor expressing adult-born neurons, including altered expression of the transcription factor We further show that is necessary for proper dendrite specification and patterning, as well as synapse development and function in adult-born neurons. Together, these findings reveal a novel mechanism by which peptide signaling modulates adult brain circuit plasticity.
Keywords: Animals; Behavior, Animal; Brain; Corticotropin-Releasing Hormone; Female; Gene Knock-In Techniques; Male; Mice; Mice, Knockout; Neuronal Plasticity; Neurons; Neuropeptides; Octamer Transcription Factor-3; Olfactory Bulb; Receptors, Corticotropin-Releasing Hormone; Smell

Prospective Study of Epigenetic Age Acceleration and Incidence of Cardiovascular Disease Outcomes in the ARIC Study (Atherosclerosis Risk in Communities). - Roetker, Nicholas S; Pankow, James S; Bressler, Jan; Morrison, Alanna C; Eric Boerwinkle (Circ Genom Precis Med, 2018)
BACKGROUND: DNA methylation-based patterns of biological aging, known as epigenetic age acceleration, are predictive of all-cause mortality, but little is known about their association with cardiovascular disease (CVD). METHODS: We estimated 2 versions of epigenetic age acceleration (Horvath and Hannum) using whole-blood samples from 2543 blacks. Linear and Cox proportional hazards regression, respectively, were used to assess the association of age acceleration with carotid intima-media thickness (cross-sectionally) and incident cardiovascular events, including CVD mortality, myocardial infarction, fatal coronary heart disease, peripheral arterial disease, and heart failure, during a median 21-year follow-up. All models were adjusted for chronological age and traditional CVD risk factors. RESULTS: In comparison to chronological age, the 2 measures of epigenetic age acceleration were weaker, but independent, potential risk markers for subclinical atherosclerosis and most incident cardiovascular outcomes, including fatal coronary heart disease, peripheral arterial disease, and heart failure. For example, each 5-year increment of epigenetic age acceleration was associated with an average of 0.01 mm greater carotid intima-media thickness (each ≤0.01), and the hazard ratios (95% confidence intervals) of fatal coronary heart disease per 5-year increment in Horvath and Hannum age acceleration were 1.17 (1.02-1.33) and 1.22 (1.04-1.44), respectively. CONCLUSIONS: In this sample of blacks, increased epigenetic age acceleration in whole blood was a potential risk marker for incident fatal coronary heart disease, peripheral arterial disease, and heart failure independently of chronological age and traditional CVD risk factors. DNA methylation-based measures of biological aging may help to identify new pathophysiological mechanisms contributing to the development of CVD.
Keywords: Age Factors; Black or African American; Cardiovascular Diseases; Carotid Intima-Media Thickness; DNA Methylation; Female; Humans; Male; Middle Aged; Prevalence; Proportional Hazards Models; Prospective Studies; Risk Factors

Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity. - Turcot, Valérie; Lu, Yingchang; Highland, Heather M; Schurmann, Claudia; Justice, Anne E; Fine, Rebecca S; Bradfield, Jonathan P; Esko, Tõnu; Giri, Ayush; Graff, Mariaelisa; Guo, Xiuqing; Hendricks, Audrey E; et al. (Nat Genet, 2018)
Genome-wide association studies (GWAS) have identified >250 loci for body mass index (BMI), implicating pathways related to neuronal biology. Most GWAS loci represent clusters of common, noncoding variants from which pinpointing causal genes remains challenging. Here we combined data from 718,734 individuals to discover rare and low-frequency (minor allele frequency (MAF) < 5%) coding variants associated with BMI. We identified 14 coding variants in 13 genes, of which 8 variants were in genes (ZBTB7B, ACHE, RAPGEF3, RAB21, ZFHX3, ENTPD6, ZFR2 and ZNF169) newly implicated in human obesity, 2 variants were in genes (MC4R and KSR2) previously observed to be mutated in extreme obesity and 2 variants were in GIPR. The effect sizes of rare variants are ~10 times larger than those of common variants, with the largest effect observed in carriers of an MC4R mutation introducing a stop codon (p.Tyr35Ter, MAF = 0.01%), who weighed ~7 kg more than non-carriers. Pathway analyses based on the variants associated with BMI confirm enrichment of neuronal genes and provide new evidence for adipocyte and energy expenditure biology, widening the potential of genetically supported therapeutic targets in obesity.
Keywords: Adult; Animals; Body Mass Index; Drosophila; Energy Intake; Energy Metabolism; Female; Gene Frequency; Genetic Variation; Humans; Male; Obesity; Proteins; Syndrome

Refining the accuracy of validated target identification through coding variant fine-mapping in type 2 diabetes. - Mahajan, Anubha; Wessel, Jennifer; Willems, Sara M; Zhao, Wei; Robertson, Neil R; Chu, Audrey Y; Gan, Wei; Kitajima, Hidetoshi; Taliun, Daniel; Rayner, N William; Guo, Xiuqing; Lu, Yingchang; et al. (Nat Genet, 2018)
We aggregated coding variant data for 81,412 type 2 diabetes cases and 370,832 controls of diverse ancestry, identifying 40 coding variant association signals (P < 2.2 × 10); of these, 16 map outside known risk-associated loci. We make two important observations. First, only five of these signals are driven by low-frequency variants: even for these, effect sizes are modest (odds ratio ≤1.29). Second, when we used large-scale genome-wide association data to fine-map the associated variants in their regional context, accounting for the global enrichment of complex trait associations in coding sequence, compelling evidence for coding variant causality was obtained for only 16 signals. At 13 others, the associated coding variants clearly represent 'false leads' with potential to generate erroneous mechanistic inference. Coding variant associations offer a direct route to biological insight for complex diseases and identification of validated therapeutic targets; however, appropriate mechanistic inference requires careful specification of their causal contribution to disease predisposition.
Keywords: Alleles; Chromosome Mapping; Diabetes Mellitus, Type 2; Exome Sequencing; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; White People

The Return of Actionable Variants Empirical (RAVE) Study, a Mayo Clinic Genomic Medicine Implementation Study: Design and Initial Results. - Kullo, Iftikhar J; Olson, Janet; Fan, Xiao; Jose, Merin; Safarova, Maya; Radecki Breitkopf, Carmen; Winkler, Erin; Kochan, David C; Snipes, Sara; Pacyna, Joel E; Carney, Meaghan; Chute, Christopher G; et al. (Mayo Clin Proc, 2018)
OBJECTIVES: To identify clinically actionable genetic variants from targeted sequencing of 68 disease-related genes, estimate their penetrance, and assess the impact of disclosing results to participants and providers. PATIENTS AND METHODS: The Return of Actionable Variants Empirical (RAVE) Study investigates outcomes following the return of pathogenic/likely pathogenic (P/LP) variants in 68 disease-related genes. The study was initiated in December 2016 and is ongoing. Targeted sequencing was performed in 2533 individuals with hyperlipidemia or colon polyps. The electronic health records (EHRs) of participants carrying P/LP variants in 36 cardiovascular disease (CVD) genes were manually reviewed to ascertain the presence of relevant traits. Clinical outcomes, health care utilization, family communication, and ethical and psychosocial implications of disclosure of genomic results are being assessed by surveys, telephone interviews, and EHR review. RESULTS: Of 29,208 variants in the 68 genes, 1915 were rare (frequency <1%) and putatively functional, and 102 of these (60 in 36 CVD genes) were labeled P/LP based on the American College of Medical Genetics and Genomics framework. Manual review of the EHRs of participants (n=73 with P/LP variants in CVD genes) revealed that 33 had the expected trait(s); however, only 6 of 45 participants with non-familial hypercholesterolemia (FH) P/LP variants had the expected traits. CONCLUSION: Expected traits were present in 13% of participants with P/LP variants in non-FH CVD genes, suggesting low penetrance; this estimate may change with additional testing performed as part of the clinical evaluation. Ongoing analyses of the RAVE Study will inform best practices for genomic medicine.
Keywords: Cardiovascular Diseases; Cohort Studies; Colon; Female; Genetic Predisposition to Disease; Genetic Testing; Genomics; Humans; Hyperlipidemias; Male; Middle Aged; Outcome Assessment, Health Care; Phenotype; Polymorphism, Single Nucleotide; Polyps; Surveys and Questionnaires

Rho Guanine Nucleotide Exchange Factor Is a Risk Gene for Intracranial Aneurysms. - Yang, Xinyu; Li, Jiani; Fang, Yabo; Zhang, Zhen; Jin, Daqing; Chen, Xingdong; Zhao, Yan; Li, Mengqi; Huan, Linchun; Kent, Thomas A; Dong, Jing-fei; Jiang, Rongcai; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Intracranial aneurysm (IA) is usually a late-onset disease, affecting 1% to 3% of the general population and leading to life-threatening subarachnoid hemorrhage. Genetic susceptibility has been implicated in IAs, but the causative genes remain elusive. METHODS: We performed next-generation sequencing in a discovery cohort of 20 Chinese IA patients. Bioinformatics filters were exploited to search for candidate deleterious variants with rare and low allele frequency. We further examined the candidate variants in a multiethnic sample collection of 86 whole exome sequenced unsolved familial IA cases from 3 previously published studies. RESULTS: We identified that the low-frequency variant c.4394C>A_p.Ala1465Asp (rs2298808) of was significantly associated with IA in our Chinese discovery cohort (=7.3×10; odds ratio=7.34). It was subsequently replicated in Japanese familial IA patients (=0.039; odds ratio=4.00; 95% confidence interval=0.832-14.8) and was associated with IA in the large Chinese sample collection comprising 832 sporadic IA-affected and 599 control individuals (=0.041; odds ratio=1.51; 95% confidence interval=1.02-Inf). When combining the sequencing data of all familial IA patients from 4 different ethnicities (ie, Chinese, Japanese, European American, and French-Canadian), we identified a significantly increased mutation burden for (21/106 versus 11/306; =8.1×10; odds ratio=6.6; 95% confidence interval=2.9-15.8) in cases as compared with controls. In zebrafish, was highly expressed in the brain blood vessel. knockdown caused blood extravasation in the brain region. Endothelial lesions were identified exclusively on cerebral blood vessels in the -deficient zebrafish. CONCLUSIONS: Our results provide compelling evidence that is a risk gene for IA.
Keywords: Adult; Alleles; Canada; Cohort Studies; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; Intracranial Aneurysm; Male; Middle Aged; Rho Guanine Nucleotide Exchange Factors; Risk Factors; Subarachnoid Hemorrhage

The role of FREM2 and FRAS1 in the development of congenital diaphragmatic hernia. - Jordan, Valerie K; Beck, Tyler F; Hernandez-Garcia, Andres; Kundert, Peter N; Kim, Bum-Jun; Jhangiani, Shalini N; Gambin, Tomasz; Starkovich, Molly; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Li, Alexander H; et al. (Hum Mol Genet, 2018)
Congenital diaphragmatic hernia (CDH) has been reported twice in individuals with a clinical diagnosis of Fraser syndrome, a genetic disorder that can be caused by recessive mutations affecting FREM2 and FRAS1. In the extracellular matrix, FREM2 and FRAS1 form a self-stabilizing complex with FREM1, a protein whose deficiency causes sac CDH in humans and mice. By sequencing FREM2 and FRAS1 in a CDH cohort, and searching online databases, we identified five individuals who carried recessive or double heterozygous, putatively deleterious variants in these genes which may represent susceptibility alleles. Three of these alleles were significantly enriched in our CDH cohort compared with ethnically matched controls. We subsequently demonstrated that 8% of Frem2ne/ne and 1% of Fras1Q1263*/Q1263* mice develop the same type of anterior sac CDH seen in FREM1-deficient mice. We went on to show that development of sac hernias in FREM1-deficient mice is preceded by failure of anterior mesothelial fold progression resulting in the persistence of an amuscular, poorly vascularized anterior diaphragm that is abnormally adherent to the underlying liver. Herniation occurs in the perinatal period when the expanding liver protrudes through this amuscular region of the anterior diaphragm that is juxtaposed to areas of muscular diaphragm. Based on these data, we conclude that deficiency of FREM2, and possibly FRAS1, are associated with an increased risk of developing CDH and that loss of the FREM1/FREM2/FRAS1 complex, or its function, leads to anterior sac CDH development through its effects on mesothelial fold progression.
Keywords: Animals; Child; Child, Preschool; Epithelium; Extracellular Matrix Proteins; Female; Hernias, Diaphragmatic, Congenital; Humans; Infant; Infant, Newborn; Male; Mice; Mice, Knockout; Mutation; Pregnancy; Receptors, Interleukin

Sequence-Based Analysis of Lipid-Related Metabolites in a Multiethnic Study. - Feofanova, Elena V; Yu, Bing; Ginger A Metcalf; Liu, Xiaoming; Donna M Muzny; Below, Jennifer E; Wagenknecht, Lynne E; Richard A Gibbs; Morrison, Alanna C; Eric Boerwinkle (Genetics, 2018)
Small molecule lipid-related metabolites are important components of fatty acid and steroid metabolism-two important contributors to human health. This study investigated the extent to which rare and common genetic variants spanning the human genome influence the lipid-related metabolome. Sequence data from 1552 European-Americans (EA) and 1872 African-Americans (AA) were analyzed to examine the impact of common and rare variants on the levels of 102 circulating lipid-related metabolites measured by a combination of chromatography and mass spectroscopy. We conducted single variant tests [minor allele frequency (MAF) > 5%, statistical significance -value ≤ 2.45 × 10] and tests aggregating rare variants (MAF ≤ 5%) across multiple genomic motifs, such as coding regions and regulatory domains, and sliding windows. Multiethnic meta-analyses detected 53 lipid-related metabolites-locus pairs, which were inspected for evidence of consistent signal between the two ethnic groups. Thirty-eight lipid-related metabolite-genomic region associations were consistent across ethnicities, among which seven were novel. The regions contain genes that are related to metabolite transport () and metabolism (, , , and ). Six of the seven novel findings lie in expression quantitative trait loci affecting the expression levels of 14 surrounding genes in multiple tissues. Imputed expression levels of 10 of the affected genes were associated with four corresponding lipid-related traits in at least one tissue. Our findings offer valuable insight into circulating lipid-related metabolite regulation in a multiethnic population.
Keywords: Black or African American; Female; Humans; Lipid Metabolism; Male; Metabolome; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; White People

Sheep genome functional annotation reveals proximal regulatory elements contributed to the evolution of modern breeds. - Naval-Sanchez, Marina; Nguyen, Quan; McWilliam, Sean; Porto-Neto, Laercio R; Tellam, Ross; Vuocolo, Tony; Reverter, Antonio; Perez-Enciso, Miguel; Brauning, Rudiger; Clarke, Shannon; McCulloch, Alan; Zamani, Wahid; et al. (Nat Commun, 2018)
Domestication fundamentally reshaped animal morphology, physiology and behaviour, offering the opportunity to investigate the molecular processes driving evolutionary change. Here we assess sheep domestication and artificial selection by comparing genome sequence from 43 modern breeds (Ovis aries) and their Asian mouflon ancestor (O. orientalis) to identify selection sweeps. Next, we provide a comparative functional annotation of the sheep genome, validated using experimental ChIP-Seq of sheep tissue. Using these annotations, we evaluate the impact of selection and domestication on regulatory sequences and find that sweeps are significantly enriched for protein coding genes, proximal regulatory elements of genes and genome features associated with active transcription. Finally, we find individual sites displaying strong allele frequency divergence are enriched for the same regulatory features. Our data demonstrate that remodelling of gene expression is likely to have been one of the evolutionary forces that drove phenotypic diversification of this common livestock species.
Keywords: Animals; Breeding; Evolution, Molecular; Female; Gene Frequency; Genome; Male; Molecular Sequence Annotation; Phylogeny; Regulatory Elements, Transcriptional; Sheep

Syndromic congenital myelofibrosis associated with a loss-of-function variant in . - Magoulas, Pilar L; Shchelochkov, Oleg A; Bainbridge, Matthew N; Ben-Shachar, Shay; Yatsenko, Svetlana; Potocki, Lorraine; Lewis, Richard A; Searby, Charles; Marcogliese, Andrea N; Elghetany, M Tarek; Zapata, Gladys; Hernández, Paula P; et al. (Blood, 2018)
There is a Commentary on this article in this issue.
Keywords: Abnormalities, Multiple; Bone Marrow Transplantation; Child; Consanguinity; Fatal Outcome; Female; Gonadal Dysgenesis, 46,XY; Hematopoietic Stem Cell Transplantation; Humans; Infant; Intellectual Disability; Male; Pedigree; Phenotype; Primary Myelofibrosis; Syndrome; Vesicular Transport Proteins

SYT1-associated neurodevelopmental disorder: a case series. - Baker, Kate; Gordon, Sarah L; Melland, Holly; Bumbak, Fabian; Scott, Daniel J; Jiang, Tess J; Owen, David; Turner, Bradley J; Boyd, Stewart G; Rossi, Mari; Al-Raqad, Mohammed; Elpeleg, Orly; et al. (Brain, 2018)
Synaptotagmin 1 (SYT1) is a critical mediator of fast, synchronous, calcium-dependent neurotransmitter release and also modulates synaptic vesicle endocytosis. This paper describes 11 patients with de novo heterozygous missense mutations in SYT1. All mutations alter highly conserved residues, and cluster in two regions of the SYT1 C2B domain at positions Met303 (M303K), Asp304 (D304G), Asp366 (D366E), Ile368 (I368T) and Asn371 (N371K). Phenotypic features include infantile hypotonia, congenital ophthalmic abnormalities, childhood-onset hyperkinetic movement disorders, motor stereotypies, and developmental delay varying in severity from moderate to profound. Behavioural characteristics include sleep disturbance and episodic agitation. Absence of epileptic seizures and normal orbitofrontal head circumference are important negative features. Structural MRI is unremarkable but EEG disturbance is universal, characterized by intermittent low frequency high amplitude oscillations. The functional impact of these five de novo SYT1 mutations has been assessed by expressing rat SYT1 protein containing the equivalent human variants in wild-type mouse primary hippocampal cultures. All mutant forms of SYT1 were expressed at levels approximately equal to endogenous wild-type protein, and correctly localized to nerve terminals at rest, except for SYT1M303K, which was expressed at a lower level and failed to localize at nerve terminals. Following stimulation, SYT1I368T and SYT1N371K relocalized to nerve terminals at least as efficiently as wild-type SYT1. However, SYT1D304G and SYT1D366E failed to relocalize to nerve terminals following stimulation, indicative of impairments in endocytic retrieval and trafficking of SYT1. In addition, the presence of SYT1 variants at nerve terminals induced a slowing of exocytic rate following sustained action potential stimulation. The extent of disturbance to synaptic vesicle kinetics is mirrored by the severity of the affected individuals' phenotypes, suggesting that the efficiency of SYT1-mediated neurotransmitter release is critical to cognitive development. In summary, de novo dominant SYT1 missense mutations are associated with a recognizable neurodevelopmental syndrome, and further cases can now be diagnosed based on clinical features, electrophysiological signature and mutation characteristics. Variation in phenotype severity may reflect mutation-specific impact on the diverse physiological functions of SYT1.
Keywords: Action Potentials; Adolescent; Animals; Calcium; Child; Child, Preschool; Electrophysiological Phenomena; Endocytosis; Female; Humans; Intellectual Disability; Male; Mice; Mice, Inbred C57BL; Movement Disorders; Mutation, Missense; Neurodevelopmental Disorders; Neurons; Rats; Synaptic Transmission; Synaptic Vesicles; Synaptotagmin I; Young Adult

Targeted sequencing identifies a missense variant in the BEST3 gene associated with antihypertensive response to hydrochlorothiazide. - Singh, Sonal; Wang, Zhiying; Shahin, Mohamed H; Langaee, Taimour Y; Gong, Yan; Turner, Stephen T; Chapman, Arlene B; Gums, John G; McDonough, Caitrin W; Bailey, Kent R; Beitelshees, Amber L; Cooper-Dehoff, Rhonda M; et al. (Pharmacogenet Genomics, 2018)
Chromosome 12q15 was identified in Genetic Epidemiology of Response Assessment (GERA) and replicated in Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) for its association with blood pressure (BP) response to hydrochlorothiazide (HCTZ). However, the functional variant is unknown and we aimed to identify the likely functional variants through targeted sequencing. The chromosome 12q15 region was sequenced in 397 best and worst responders to HCTZ in PEAR (N=199) and GERA (N=198) hypertensive study participants. Logistic regression was used for the association analysis adjusting for age, sex, race, and principal components 1 and 2. For validation, the significant single nucleotide polymorphism was tested for association with the change in systolic (ΔSBP) and diastolic BP (ΔDBP) post-treatment in the entire PEAR (N=370) and GERA (N=570) cohorts. A novel missense polymorphism (G>A, Pro383Leu) in BEST3, rs61747221, was significantly associated with better HCTZ response (P=0.0021, odds ratio=2.05). It was validated in the entire cohort of PEAR (ΔSBP: P=0.021, β=-1.60, ΔDBP: P=0.023, β=-1.08) and GERA (ΔSBP: P=0.028, β=-1.95, ΔDBP: P=0.032, β=-1.28). BEST3 encodes the calcium sensitive chloride channel in the vascular smooth muscle implicated in the regulation of BP, especially in response to vasoconstrictors like angiotensin II. These results suggest that BEST3 is involved in the chronic BP lowering mechanism of thiazides and highlight its importance as a genetic predictor of the BP response to thiazide diuretics.
Keywords: Adult; Angiotensin II; Antihypertensive Agents; Atenolol; Bestrophins; Blood Pressure; Female; Genetic Association Studies; Humans; Hypertension; Male; Middle Aged; Muscle Proteins; Polymorphism, Single Nucleotide; Sodium Chloride Symporter Inhibitors

Temporal development of the gut microbiome in early childhood from the TEDDY study. - Stewart, Christopher J; Ajami, Nadim J; O'Brien, Jacqueline L; Hutchinson, Diane S; Smith, Daniel P; Wong, Matthew C; Ross, Matthew C; Lloyd, Richard E; Harshavardhan Doddapaneni; Ginger A Metcalf; Donna M Muzny; Richard A Gibbs; et al. (Nature, 2018)
The development of the microbiome from infancy to childhood is dependent on a range of factors, with microbial-immune crosstalk during this time thought to be involved in the pathobiology of later life diseases such as persistent islet autoimmunity and type 1 diabetes. However, to our knowledge, no studies have performed extensive characterization of the microbiome in early life in a large, multi-centre population. Here we analyse longitudinal stool samples from 903 children between 3 and 46 months of age by 16S rRNA gene sequencing (n = 12,005) and metagenomic sequencing (n = 10,867), as part of the The Environmental Determinants of Diabetes in the Young (TEDDY) study. We show that the developing gut microbiome undergoes three distinct phases of microbiome progression: a developmental phase (months 3-14), a transitional phase (months 15-30), and a stable phase (months 31-46). Receipt of breast milk, either exclusive or partial, was the most significant factor associated with the microbiome structure. Breastfeeding was associated with higher levels of Bifidobacterium species (B. breve and B. bifidum), and the cessation of breast milk resulted in faster maturation of the gut microbiome, as marked by the phylum Firmicutes. Birth mode was also significantly associated with the microbiome during the developmental phase, driven by higher levels of Bacteroides species (particularly B. fragilis) in infants delivered vaginally. Bacteroides was also associated with increased gut diversity and faster maturation, regardless of the birth mode. Environmental factors including geographical location and household exposures (such as siblings and furry pets) also represented important covariates. A nested case-control analysis revealed subtle associations between microbial taxonomy and the development of islet autoimmunity or type 1 diabetes. These data determine the structural and functional assembly of the microbiome in early life and provide a foundation for targeted mechanistic investigation into the consequences of microbial-immune crosstalk for long-term health.
Keywords: Adolescent; Animals; Bifidobacterium; Breast Feeding; Case-Control Studies; Child; Child, Preschool; Cluster Analysis; Datasets as Topic; Diabetes Mellitus, Type 1; Female; Firmicutes; Gastrointestinal Microbiome; Humans; Infant; Male; Milk, Human; Pets; RNA, Ribosomal, 16S; Siblings; Surveys and Questionnaires; Time Factors

Truncating Variants in NAA15 Are Associated with Variable Levels of Intellectual Disability, Autism Spectrum Disorder, and Congenital Anomalies. - Cheng, Hanyin; Dharmadhikari, Avinash V; Varland, Sylvia; Ma, Ning; Domingo, Deepti; Kleyner, Robert; Rope, Alan F; Yoon, Margaret; Stray-Pedersen, Asbjørg; Posey, Jennifer E; Crews, Sarah R; Eldomery, Mohammad K; et al. (Am J Hum Genet, 2018)
N-alpha-acetylation is a common co-translational protein modification that is essential for normal cell function in humans. We previously identified the genetic basis of an X-linked infantile lethal Mendelian disorder involving a c.109T>C (p.Ser37Pro) missense variant in NAA10, which encodes the catalytic subunit of the N-terminal acetyltransferase A (NatA) complex. The auxiliary subunit of the NatA complex, NAA15, is the dimeric binding partner for NAA10. Through a genotype-first approach with whole-exome or genome sequencing (WES/WGS) and targeted sequencing analysis, we identified and phenotypically characterized 38 individuals from 33 unrelated families with 25 different de novo or inherited, dominantly acting likely gene disrupting (LGD) variants in NAA15. Clinical features of affected individuals with LGD variants in NAA15 include variable levels of intellectual disability, delayed speech and motor milestones, and autism spectrum disorder. Additionally, mild craniofacial dysmorphology, congenital cardiac anomalies, and seizures are present in some subjects. RNA analysis in cell lines from two individuals showed degradation of the transcripts with LGD variants, probably as a result of nonsense-mediated decay. Functional assays in yeast confirmed a deleterious effect for two of the LGD variants in NAA15. Further supporting a mechanism of haploinsufficiency, individuals with copy-number variant (CNV) deletions involving NAA15 and surrounding genes can present with mild intellectual disability, mild dysmorphic features, motor delays, and decreased growth. We propose that defects in NatA-mediated N-terminal acetylation (NTA) lead to variable levels of neurodevelopmental disorders in humans, supporting the importance of the NatA complex in normal human development.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Autism Spectrum Disorder; Cell Line; Child; Exons; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Genetic Variation; Humans; Intellectual Disability; Male; Middle Aged; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Pedigree; Phenotype; RNA, Messenger; Saccharomyces cerevisiae

Whole-Exome Sequencing Identifies Novel Variants for Tooth Agenesis. - Dinckan, N; Du, R; Petty, L E; Coban-Akdemir, Z; Jhangiani, S N; Paine, I; Baugh, E H; Erdem, A P; Kayserili, H; Harshavardhan Doddapaneni; Jianhong Hu; Donna M Muzny; et al. (J Dent Res, 2018)
Tooth agenesis is a common craniofacial abnormality in humans and represents failure to develop 1 or more permanent teeth. Tooth agenesis is complex, and variations in about a dozen genes have been reported as contributing to the etiology. Here, we combined whole-exome sequencing, array-based genotyping, and linkage analysis to identify putative pathogenic variants in candidate disease genes for tooth agenesis in 10 multiplex Turkish families. Novel homozygous and heterozygous variants in LRP6, DKK1, LAMA3, and COL17A1 genes, as well as known variants in WNT10A, were identified as likely pathogenic in isolated tooth agenesis. Novel variants in KREMEN1 were identified as likely pathogenic in 2 families with suspected syndromic tooth agenesis. Variants in more than 1 gene were identified segregating with tooth agenesis in 2 families, suggesting oligogenic inheritance. Structural modeling of missense variants suggests deleterious effects to the encoded proteins. Functional analysis of an indel variant (c.3607+3_6del) in LRP6 suggested that the predicted resulting mRNA is subject to nonsense-mediated decay. Our results support a major role for WNT pathways genes in the etiology of tooth agenesis while revealing new candidate genes. Moreover, oligogenic cosegregation was suggestive for complex inheritance and potentially complex gene product interactions during development, contributing to improved understanding of the genetic etiology of familial tooth agenesis.
Keywords: Anodontia; Exome Sequencing; Female; Genetic Linkage; Genetic Variation; Humans; Intercellular Signaling Peptides and Proteins; Laminin; Low Density Lipoprotein Receptor-Related Protein-6; Male; Membrane Proteins; Mutation, Missense; Pedigree; Real-Time Polymerase Chain Reaction; Turkey; Wnt Proteins

Whole-exome sequencing revealed HKDC1 as a candidate gene associated with autosomal-recessive retinitis pigmentosa. - Zhang, Lin; Sun, Zixi; Zhao, Peiquan; Huang, Lulin; Xu, Mingchu; Yang, Yeming; Chen, Xue; Lu, Fang; Zhang, Xiang; Wang, Hui; Zhang, Shanshan; Liu, Wenjing; et al. (Hum Mol Genet, 2018)
Retinitis pigmentosa (RP) is an inheritable retina degenerative disease leading to blindness. Despite the identification of 70 genes associated with RP, the genetic cause of ∼40% of RP patients remains to be elucidated. Whole-exome sequencing was applied on the probands of a RP cohort of 68 unsolved cases to identify candidate genetic mutations. A homozygous missense variant (c.173C > T, p.T58 M) was found in HKDC1 in two unrelated families presenting late-onset retinal degeneration. This variant affects highly conserved amino acid residue and is very rare in several databases and absent in 4000 ethnic-matched controls. Mutant HKDC1 protein partially lost hexokinase activity. Hkdc1 is expressed in the mouse retina and localized to photoreceptor inner segments. To elucidate the in vivo roles of Hkdc1 in the retina, we generated Hkdc1 knockout (KO) mouse models using CRISPR/Cas9 technique. Two independent alleles were identified and backcrossed to C57BL/6 J for 6 generations. Absence of HKDC1 expression in the Hkdc1 KO retina was confirmed by western blot and immunostaning using HKDC1 antibody. Hkdc1 KO mice exhibited reduced scotopic electroretinogram response and thinner outer nuclear layer, similar to some of the human patient phenotypes. Loss of Hkdc1 led to mislocalization of rhodopsin to the inner segments and cell bodies of rods in some regions in the retina. Taken together, our data demonstrated that HKDC1 is associated with autosomal recessively inherited RP.
Keywords: Animals; Disease Models, Animal; Exome; Exome Sequencing; Female; Genetic Association Studies; Hexokinase; Homozygote; Humans; Male; Mice, Knockout; Mutation; Pedigree; Retina; Retinal Degeneration; Retinitis Pigmentosa

Whole-exome sequencing reveals known and novel variants in a cohort of intracranial vertebral-basilar artery dissection (IVAD). - Wang, Kun; Zhao, Sen; Zhang, Qianqian; Yuan, Jian; Liu, Jiaqi; Ding, Xinghuan; Song, Xiaofei; Lin, Jiachen; Du, Renqian; Zhou, Yangzhong; Sugimoto, Michihiko; Chen, Weisheng; et al. (J Hum Genet, 2018)
Intracranial vertebral-basilar artery dissection (IVAD) is an arterial disorder leading to life-threatening consequences. Genetic factors are known to be causative to certain syndromic forms of IVAD. However, systematic study of the molecular basis of sporadic and isolated IVAD is lacking. To identify genetic variants contributing to the etiology of IVAD, we enrolled a cohort of 44 unrelated cases with a clinical diagnosis of isolated IVAD and performed whole-exome sequencing (WES) for all the participants; a trio exome sequencing approach was used when samples from both parents were available. Four previously reported disease-causing heterozygous variants (three in COL3A1 and one in FBN1) and seven novel heterozygous variants in IVAD-related genes were identified. In addition, six variants in novel IVAD genes including two de novo heterozygous nonsynonymous variants (each in VPS52 and CDK18), two stop-gain variants (each in MYH9 and LYL1), and two heterozygous biallelic variants in TNXB were considered to be possibly contributing to the phenotype, with unknown significance according to the existing knowledge. A significantly higher mutational rate of IVAD candidate genes was observed in patients versus our in-house controls (P = 0.002) (DISCO study, http://www.discostudy.org/ , n = 2248). Our study provided a mutational landscape for patients with isolated IVAD.
Keywords: Adult; Aneurysm, Dissecting; Basic Helix-Loop-Helix Transcription Factors; Cohort Studies; Collagen Type III; Exome; Female; Fibrillin-1; High-Throughput Nucleotide Sequencing; Humans; Intracranial Aneurysm; Male; Middle Aged; Molecular Motor Proteins; Myosin Heavy Chains; Neoplasm Proteins

WNT Signaling Perturbations Underlie the Genetic Heterogeneity of Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Coban-Akdemir, Zeynep; Bayram, Yavuz; Bahrambeigi, Vahid; Hoischen, Alexander; van Bon, Bregje W M; Gezdirici, Alper; Gulec, Elif Yilmaz; Ramond, Francis; Touraine, Renaud; Thevenon, Julien; et al. (Am J Hum Genet, 2018)
Locus heterogeneity characterizes a variety of skeletal dysplasias often due to interacting or overlapping signaling pathways. Robinow syndrome is a skeletal disorder historically refractory to molecular diagnosis, potentially stemming from substantial genetic heterogeneity. All current known pathogenic variants reside in genes within the noncanonical Wnt signaling pathway including ROR2, WNT5A, and more recently, DVL1 and DVL3. However, ∼70% of autosomal-dominant Robinow syndrome cases remain molecularly unsolved. To investigate this missing heritability, we recruited 21 families with at least one family member clinically diagnosed with Robinow or Robinow-like phenotypes and performed genetic and genomic studies. In total, four families with variants in FZD2 were identified as well as three individuals from two families with biallelic variants in NXN that co-segregate with the phenotype. Importantly, both FZD2 and NXN are relevant protein partners in the WNT5A interactome, supporting their role in skeletal development. In addition to confirming that clustered -1 frameshifting variants in DVL1 and DVL3 are the main contributors to dominant Robinow syndrome, we also found likely pathogenic variants in candidate genes GPC4 and RAC3, both linked to the Wnt signaling pathway. These data support an initial hypothesis that Robinow syndrome results from perturbation of the Wnt/PCP pathway, suggest specific relevant domains of the proteins involved, and reveal key contributors in this signaling cascade during human embryonic development. Contrary to the view that non-allelic genetic heterogeneity hampers gene discovery, this study demonstrates the utility of rare disease genomic studies to parse gene function in human developmental pathways.
Keywords: Adolescent; Adult; Base Sequence; Child; Child, Preschool; Chromosome Segregation; Craniofacial Abnormalities; Diagnosis, Differential; Dwarfism; Female; Genes, Dominant; Genetic Association Studies; Genetic Heterogeneity; Humans; Limb Deformities, Congenital; Male; Middle Aged; Mutation, Missense; Phenotype; Urogenital Abnormalities; Wnt Signaling Pathway

22q11.2q13 duplication including SOX10 causes sex-reversal and peripheral demyelinating neuropathy, central dysmyelinating leukodystrophy, Waardenburg syndrome, and Hirschsprung disease. - Falah, Nadia; Posey, Jennifer E; Thorson, Willa; Benke, Paul; Tekin, Mustafa; Tarshish, Brocha; Lupski, James R; Harel, Tamar (Am J Med Genet A, 2017)
Diagnosis of genetic syndromes may be difficult when specific components of a disorder manifest at a later age. We present a follow up of a previous report [Seeherunvong et al., (2004); AJMGA 127: 149-151], of an individual with 22q duplication and sex-reversal syndrome. The subject's phenotype evolved to include peripheral and central demyelination, Waardenburg syndrome type IV, and Hirschsprung disease (PCWH; MIM 609136). DNA microarray analysis defined the duplication at 22q11.2q13, including SOX10. Sequencing of the coding region of SOX10 did not reveal any mutations. Our data suggest that SOX10 duplication can cause disorders of sex development and PCWH, supporting the hypothesis that SOX10 toxic gain of function rather than dominant negative activity underlies PCWH.
Keywords: 46, XX Testicular Disorders of Sex Development; Black or African American; Chromosome Duplication; Chromosomes, Human, Pair 22; Demyelinating Diseases; Hirschsprung Disease; Humans; Kidney Failure, Chronic; Male; Pelizaeus-Merzbacher Disease; SOXE Transcription Factors; Waardenburg Syndrome

Activating MAPK1 (ERK2) mutation in an aggressive case of disseminated juvenile xanthogranuloma. - Chakraborty, Rikhia; Hampton, Oliver A; Abhyankar, Harshal; Zinn, Daniel J; Grimes, Amanda; Skull, Brooks; Eckstein, Olive; Mahmood, Nadia; Wheeler, David A; López-Terrada, Dolores; Peters, Tricia L; Hicks, John M; et al. (Oncotarget, 2017)
Juvenile xanthogranuloma (JXG) is a rare histiocytic disorder that is usually benign and self-limiting. We present a case of atypical, aggressive JXG harboring a novel mitogen-activated protein kinase (MAPK) pathway mutation in the MAPK1 gene, which encodes mitogen-activated protein kinase 1 or extracellular signal-regulated 2 (ERK2). Our analysis revealed that the mutation results in constitutive ERK activation that is resistant to BRAF or MEK inhibitors but susceptible to an ERK inhibitor. These data highlight the importance of identifying specific MAPK pathway alterations as part of the diagnostic workup for patients with histiocytic disorders rather than initiating empiric treatment with MEK inhibitors.
Keywords: Cells, Cultured; Child; Drug Therapy; Histiocytes; Humans; Lymph Nodes; Male; Mitogen-Activated Protein Kinase 1; Remission Induction; Signal Transduction; Stem Cell Transplantation; Xanthogranuloma, Juvenile

Alu Insertion Polymorphisms as Evidence for Population Structure in Baboons. - Steely, Cody J; Walker, Jerilyn A; Jordan, Vallmer E; Beckstrom, Thomas O; McDaniel, Cullen L; St Romain, Corey P; Bennett, Emily C; Robichaux, Arianna; Clement, Brooke N; Raveendran, Muthuswamy; Worley, Kim C; Phillips-Conroy, Jane; et al. (Genome Biol Evol, 2017)
Male dispersal from the natal group at or near maturity is a feature of most baboon (Papio) species. It potentially has profound effects upon population structure and evolutionary processes, but dispersal, especially for unusually long distances, is not readily documented by direct field observation. In this pilot study, we investigate the possibility of retrieving baboon population structure in yellow (Papio cynocephalus) and kinda (Papio kindae) baboons from the distribution of variation in a genome-wide set of 494 Alu insertion polymorphisms, made available via the recently completed Baboon Genome Analysis Consortium. Alu insertion variation in a mixed population derived from yellow and olive (Papio anubis) baboons identified each individual's proportion of heritage from either parental species. In an unmixed yellow baboon population, our analysis showed greater similarity between neighboring than between more distantly situated groups, suggesting structuring of the population by male dispersal distance. Finally (and very provisionally), an unexpectedly sharp difference in Alu insertion frequencies between members of neighboring social groups of kinda baboons suggests that intergroup migration may be more rare than predicted in this little known species.
Keywords: Alu Elements; Animals; Evolution, Molecular; Female; Genome; Male; Papio; Phylogeny; Polymorphism, Genetic

Analyses of SLC13A5-epilepsy patients reveal perturbations of TCA cycle. - Bainbridge, Matthew N; Cooney, Erin; Miller, Marcus; Kennedy, Adam D; Wulff, Jacob E; Donti, Taraka; Jhangiani, Shalini N; Richard A Gibbs; Sarah H Elsea; Porter, Brenda E; Graham, Brett H (Mol Genet Metab, 2017)
OBJECTIVE: To interrogate the metabolic profile of five subjects from three families with rare, nonsense and missense mutations in SLC13A5 and Early Infantile Epileptic Encephalopathies (EIEE) characterized by severe, neonatal onset seizures, psychomotor retardation and global developmental delay. METHODS: Mass spectrometry of plasma, CSF and urine was used to identify consistently dysregulated analytes in our subjects. RESULTS: Distinctive elevations of citrate and dysregulation of citric acid cycle intermediates, supporting the hypothesis that loss of SLC13A5 function alters tricarboxylic acid cycle (TCA) metabolism and may disrupt metabolic compartmentation in the brain. SIGNIFICANCE: Our results indicate that analysis of plasma citrate and other TCA analytes in SLC13A5 deficient patients define a diagnostic metabolic signature that can aid in diagnosing children with this disease.
Keywords: Child; Citric Acid; Citric Acid Cycle; Exome Sequencing; Female; Humans; Infant, Newborn; Male; Mass Spectrometry; Metabolome; Metabolomics; Mutation; Mutation, Missense; Seizures; Spasms, Infantile; Symporters

ANGPTL3 Deficiency and Protection Against Coronary Artery Disease. - Stitziel, Nathan O; Khera, Amit V; Wang, Xiao; Bierhals, Andrew J; Vourakis, A Christina; Sperry, Alexandra E; Natarajan, Pradeep; Klarin, Derek; Emdin, Connor A; Zekavat, Seyedeh M; Nomura, Akihiro; Erdmann, Jeanette; et al. (J Am Coll Cardiol, 2017)
BACKGROUND: Familial combined hypolipidemia, a Mendelian condition characterized by substantial reductions in all 3 major lipid fractions, is caused by mutations that inactivate the gene angiopoietin-like 3 (ANGPTL3). Whether ANGPTL3 deficiency reduces risk of coronary artery disease (CAD) is unknown. OBJECTIVES: The study goal was to leverage 3 distinct lines of evidence-a family that included individuals with complete (compound heterozygote) ANGPTL3 deficiency, a population based-study of humans with partial (heterozygote) ANGPTL3 deficiency, and biomarker levels in patients with myocardial infarction (MI)-to test whether ANGPTL3 deficiency is associated with lower risk for CAD. METHODS: We assessed coronary atherosclerotic burden in 3 individuals with complete ANGPTL3 deficiency and 3 wild-type first-degree relatives using computed tomography angiography. In the population, ANGPTL3 loss-of-function (LOF) mutations were ascertained in up to 21,980 people with CAD and 158,200 control subjects. LOF mutations were defined as nonsense, frameshift, and splice-site variants, along with missense variants resulting in <25% of wild-type ANGPTL3 activity in a mouse model. In a biomarker study, circulating ANGPTL3 concentration was measured in 1,493 people who presented with MI and 3,232 control subjects. RESULTS: The 3 individuals with complete ANGPTL3 deficiency showed no evidence of coronary atherosclerotic plaque. ANGPTL3 gene sequencing demonstrated that approximately 1 in 309 people was a heterozygous carrier for an LOF mutation. Compared with those without mutation, heterozygous carriers of ANGPTL3 LOF mutations demonstrated a 17% reduction in circulating triglycerides and a 12% reduction in low-density lipoprotein cholesterol. Carrier status was associated with a 34% reduction in odds of CAD (odds ratio: 0.66; 95% confidence interval: 0.44 to 0.98; p = 0.04). Individuals in the lowest tertile of circulating ANGPTL3 concentrations, compared with the highest, had reduced odds of MI (adjusted odds ratio: 0.65; 95% confidence interval: 0.55 to 0.77; p < 0.001). CONCLUSIONS: ANGPTL3 deficiency is associated with protection from CAD.
Keywords: Adult; Angiopoietin-Like Protein 3; Angiopoietin-like Proteins; Angiopoietins; Animals; Atherosclerosis; Case-Control Studies; Coronary Artery Disease; Female; Humans; Lipids; Male; Mice, Inbred C57BL; Mice, Knockout; Middle Aged; Mutation, Missense; Myocardial Infarction; Risk Factors

Association between mitochondrial DNA copy number and sudden cardiac death: findings from the Atherosclerosis Risk in Communities study (ARIC). - Zhang, Yiyi; Guallar, Eliseo; Ashar, Foram N; Longchamps, Ryan J; Castellani, Christina A; Lane, John; Grove, Megan L; Coresh, Josef; Sotoodehnia, Nona; Ilkhanoff, Leonard; Eric Boerwinkle; Pankratz, Nathan; et al. (Eur Heart J, 2017)
AIMS: Sudden cardiac death (SCD) is a major public health burden. Mitochondrial dysfunction has been implicated in a wide range of cardiovascular diseases including cardiomyopathy, heart failure, and arrhythmias, but it is unknown if it also contributes to SCD risk. We sought to examine the prospective association between mtDNA copy number (mtDNA-CN), a surrogate marker of mitochondrial function, and SCD risk. METHODS AND RESULTS: We measured baseline mtDNA-CN in 11 093 participants from the Atherosclerosis Risk in Communities (ARIC) study. mtDNA copy number was calculated from probe intensities of mitochondrial single nucleotide polymorphisms (SNP) on the Affymetrix Genome-Wide Human SNP Array 6.0. Sudden cardiac death was defined as a sudden pulseless condition presumed due to a ventricular tachyarrhythmia in a previously stable individual without evidence of a non-cardiac cause of cardiac arrest. Sudden cardiac death cases were reviewed and adjudicated by an expert committee. During a median follow-up of 20.4 years, we observed 361 SCD cases. After adjusting for age, race, sex, and centre, the hazard ratio for SCD comparing the 1st to the 5th quintiles of mtDNA-CN was 2.24 (95% confidence interval 1.58-3.19; P-trend <0.001). When further adjusting for traditional cardiovascular disease risk factors, prevalent coronary heart disease, heart rate, QT interval, and QRS duration, the association remained statistically significant. Spline regression models showed that the association was approximately linear over the range of mtDNA-CN values. No apparent interaction by race or by sex was detected. CONCLUSION: In this community-based prospective study, mtDNA-CN in peripheral blood was inversely associated with the risk of SCD.
Keywords: Coronary Artery Disease; Death, Sudden, Cardiac; DNA Copy Number Variations; DNA, Mitochondrial; Female; Humans; Male; Middle Aged; Prospective Studies; Risk Factors

Association of Body Mass Index with DNA Methylation and Gene Expression in Blood Cells and Relations to Cardiometabolic Disease: A Mendelian Randomization Approach. - Mendelson, Michael M; Marioni, Riccardo E; Joehanes, Roby; Liu, Chunyu; Hedman, Åsa K; Aslibekyan, Stella; Demerath, Ellen W; Guan, Weihua; Zhi, Degui; Yao, Chen; Huan, Tianxiao; Willinger, Christine; et al. (PLoS Med, 2017)
BACKGROUND: The link between DNA methylation, obesity, and adiposity-related diseases in the general population remains uncertain. METHODS AND FINDINGS: We conducted an association study of body mass index (BMI) and differential methylation for over 400,000 CpGs assayed by microarray in whole-blood-derived DNA from 3,743 participants in the Framingham Heart Study and the Lothian Birth Cohorts, with independent replication in three external cohorts of 4,055 participants. We examined variations in whole blood gene expression and conducted Mendelian randomization analyses to investigate the functional and clinical relevance of the findings. We identified novel and previously reported BMI-related differential methylation at 83 CpGs that replicated across cohorts; BMI-related differential methylation was associated with concurrent changes in the expression of genes in lipid metabolism pathways. Genetic instrumental variable analysis of alterations in methylation at one of the 83 replicated CpGs, cg11024682 (intronic to sterol regulatory element binding transcription factor 1 [SREBF1]), demonstrated links to BMI, adiposity-related traits, and coronary artery disease. Independent genetic instruments for expression of SREBF1 supported the findings linking methylation to adiposity and cardiometabolic disease. Methylation at a substantial proportion (16 of 83) of the identified loci was found to be secondary to differences in BMI. However, the cross-sectional nature of the data limits definitive causal determination. CONCLUSIONS: We present robust associations of BMI with differential DNA methylation at numerous loci in blood cells. BMI-related DNA methylation and gene expression provide mechanistic insights into the relationship between DNA methylation, obesity, and adiposity-related diseases.
Keywords: Aged; Body Mass Index; Coronary Artery Disease; DNA Methylation; Epigenesis, Genetic; Female; Gene Expression Regulation; Genome-Wide Association Study; Humans; Leukocytes; Lipid Metabolism; Male; Mendelian Randomization Analysis; Obesity; Oligonucleotide Array Sequence Analysis

The association of lipoprotein(a) with incident heart failure hospitalization: Atherosclerosis Risk in Communities study. - Agarwala, Anandita; Pokharel, Yashashwi; Saeed, Anum; Sun, Wensheng; Virani, Salim S; Nambi, Vijay; Ndumele, Chiadi; Shahar, Eyal; Heiss, Gerardo; Eric Boerwinkle; Konety, Suma; Hoogeveen, Ron C; et al. (Atherosclerosis, 2017)
BACKGROUND AND AIMS: Lipoprotein(a) [Lp(a)] is a proatherogenic lipoprotein associated with coronary heart disease, ischemic stroke, and more recently aortic stenosis and heart failure (HF). We examined the association of Lp(a) levels with incident HF hospitalization in the Atherosclerosis Risk in Communities (ARIC) study. We also assessed the relationship between Lp(a) levels and arterial stiffness as a potential mechanism for development of HF. METHODS: Lp(a) was measured in 14,154 ARIC participants without prevalent HF at ARIC visit 1 (1987-1989). The association of Lp(a) quintiles with incident HF hospitalization was assessed using Cox proportional-hazards models. Arterial stiffness parameters were stratified based on Lp(a) quintiles, and p-trend was calculated across ordered groups. RESULTS: At a median follow-up of 23.4 years, there were 2605 incident HF hospitalizations. Lp(a) levels were directly associated with incident HF hospitalization in models adjusted for age, race, gender, systolic blood pressure, history of hypertension, diabetes, smoking status, body mass index, heart rate, and high-density lipoprotein cholesterol (quintile 5 vs. quintile 1: hazard ratio [HR] 1.24, 95% confidence interval [CI] 1.09-1.41; p-trend across increasing quintiles <0.01), but not after excluding prevalent and incident myocardial infarction cases (HR 1.07, 95% CI 0.91-1.27; p-trend = 0.70). When adjusted for age, gender, and race, Lp(a) quintiles were not significantly associated with arterial stiffness parameters. CONCLUSIONS: Increased Lp(a) levels were associated with increased risk of incident HF hospitalization. After excluding prevalent and incident myocardial infarction, the association was no longer significant. Lp(a) levels were not associated with arterial stiffness parameters.
Keywords: Biomarkers; Chi-Square Distribution; Comorbidity; Female; Heart Failure; Hospitalization; Humans; Incidence; Linear Models; Lipoprotein(a); Male; Middle Aged; Multivariate Analysis; Myocardial Infarction; Prevalence; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Factors; Time Factors; United States; Up-Regulation; Vascular Stiffness

CHRNA7 Deletions are Enriched in Risperidone-Treated Children and Adolescents. - Gillentine, Madelyn A; White, Janson J; Grochowski, Christopher M; Lupski, James R; Schaaf, Christian P; Calarge, Chadi A (J Child Adolesc Psychopharmacol, 2017)
OBJECTIVE: Aggression is among the most common indications for referral to child and adolescent mental health services and is often challenging to treat. Understanding the biological underpinnings of aggression could help optimize treatment efficacy. Neuronal nicotinic acetylcholine receptors (nAChRs), specifically the α7 nAChR, encoded by the gene CHRNA7, have been implicated in aggressive behaviors in animal models as well as humans. Copy number variants (CNVs) of CHRNA7 are found in individuals with neuropsychiatric disorders, often with comorbid aggression. In this study, we aimed to determine the prevalence of CHRNA7 CNVs among individuals treated with risperidone, predominantly for irritability and aggression. METHODS: Risperidone-treated children and adolescents were assessed for CHRNA7 copy number state using droplet digital PCR and genomic quantitative PCR. Demographic, anthropometric, and clinical data, including the Child Behavior Checklist (CBCL), were collected and compared across individuals with and without the CHRNA7 deletion. RESULTS: Of 218 individuals (90% males, mean age: 12.3 ± 2.3 years), 7 (3.2%) were found to carry a CHRNA7 deletion and one proband carried a CHRNA7 duplication (0.46%). T-scores for rule breaking, aggression, and externalizing behavior factors of the CBCL were higher in the deletion group, despite taking 58% higher dose of risperidone. CONCLUSIONS: CHRNA7 loss may contribute to a phenotype of severe aggression. Given the high prevalence of the deletion among risperidone-treated youth, future studies should examine the therapeutic potential of α7 nAChR-targeting drugs to target aggression associated with CHRNA7 deletions.
Keywords: Adolescent; alpha7 Nicotinic Acetylcholine Receptor; Antipsychotic Agents; Child; Cohort Studies; Female; Gene Deletion; Humans; Male; Neurodevelopmental Disorders; Prospective Studies; Risperidone; Treatment Outcome

Comprehensive Genomic Characterization of Upper Tract Urothelial Carcinoma. - Moss, Tyler J; Qi, Yuan; Xi, Liu; Peng, Bo; Kim, Tae-Beom; Ezzedine, Nader E; Mosqueda, Maribel E; Guo, Charles C; Czerniak, Bogdan A; Ittmann, Michael; Wheeler, David A; Lerner, Seth P; et al. (Eur Urol, 2017)
BACKGROUND: Upper urinary tract urothelial cancer (UTUC) may have unique etiologic and genomic factors compared to bladder cancer. OBJECTIVE: To characterize the genomic landscape of UTUC and provide insights into its biology using comprehensive integrated genomic analyses. DESIGN, SETTING, AND PARTICIPANTS: We collected 31 untreated snap-frozen UTUC samples from two institutions and carried out whole-exome sequencing (WES) of DNA, RNA sequencing (RNAseq), and protein analysis. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Adjusting for batch effects, consensus mutation calls from independent pipelines identified DNA mutations, gene expression clusters using unsupervised consensus hierarchical clustering (UCHC), and protein expression levels that were correlated with relevant clinical variables, The Cancer Genome Atlas, and other published data. RESULTS AND LIMITATIONS: WES identified mutations in FGFR3 (74.1%; 92% low-grade, 60% high-grade), KMT2D (44.4%), PIK3CA (25.9%), and TP53 (22.2%). APOBEC and CpG were the most common mutational signatures. UCHC of RNAseq data segregated samples into four molecular subtypes with the following characteristics. Cluster 1: no PIK3CA mutations, nonsmokers, high-grade <pT2 tumors, high recurrences. Cluster 2: 100% FGFR3 mutations, low-grade tumors, tobacco use, noninvasive disease, no bladder recurrences. Cluster 3: 100% FGFR3 mutations, 71% PIK3CA, no TP53 mutations, five bladder recurrences, tobacco use, tumors all <pT2. Cluster 4: KMT2D (62.5%), FGFR3 (50%), TP53 (50%) mutations, no PIK3CA mutations, high-grade pT2+ disease, tobacco use, carcinoma in situ, shorter survival. We identified a novel SH3KBP1-CNTNAP5 fusion. CONCLUSIONS: Mutations in UTUC occur at differing frequencies from bladder cancer, with four unique molecular and clinical subtypes. A novel SH3KBP1 fusion regulates RTK signaling. Further studies are needed to validate the described subtypes, explore their responses to therapy, and better define the novel fusion mutation. PATIENT SUMMARY: We conducted a comprehensive study of the genetics of upper urinary tract urothelial cancer by evaluating DNA, RNA and protein expression in 31 tumors. We identified four molecular subtypes with distinct behaviors. Future studies will determine if these subtypes appear to have different responses to treatments.
Keywords: Aged; Aged, 80 and over; Biomarkers, Tumor; Cluster Analysis; Computational Biology; Databases, Genetic; DNA Mutational Analysis; Exome Sequencing; Female; Gene Expression Profiling; Genetic Predisposition to Disease; Genomics; Humans; Kidney Neoplasms; Kidney Pelvis; Male; Multigene Family; Mutation; Mutation Rate; Phenotype; Sequence Analysis, Protein; Sequence Analysis, RNA; Texas; Treatment Outcome; Ureter; Ureteral Neoplasms; Urinary Bladder Neoplasms; Urothelium

Congenital heart defects and left ventricular non-compaction in males with loss-of-function variants in NONO. - Scott, Daryl A; Hernandez-Garcia, Andres; Azamian, Mahshid S; Jordan, Valerie K; Kim, Bum Jun; Starkovich, Molly; Zhang, Jinglan; Wong, Lee-Jun; Darilek, Sandra A; Breman, Amy M; Yang, Yaping; Lupski, James R; et al. (J Med Genet, 2017)
BACKGROUND: The non-POU domain containing octamer-binding gene (NONO) is located on chromosome Xq13.1 and encodes a member of a small family of RNA-binding and DNA-binding proteins that perform a variety of tasks involved in RNA synthesis, transcriptional regulation and DNA repair. Loss-of-function variants in NONO have been described as a cause of intellectual disability in males but have not been described in association with congenital heart defects or cardiomyopathy. In this article, we seek to further define the phenotypic consequences of NONO depletion in human subjects. METHODS: We searched a clinical database of over 6000 individuals referred for exome sequencing and over 60 000 individuals referred for CNV analysis. RESULTS: We identified two males with atrial and ventricular septal defects, left ventricular non-compaction (LVNC), developmental delay and intellectual disability, who harboured de novo, loss-of-function variants in NONO. We also identified a male infant with developmental delay, congenital brain anomalies and severe LVNC requiring cardiac transplantation, who inherited a single-gene deletion of NONO from his asymptomatic mother. CONCLUSIONS: We conclude that in addition to global developmental delay and intellectual disability, males with loss-of-function variants in NONO may also be predisposed to developing congenital heart defects and LVNC with the penetrance of these cardiac-related problems being influenced by genetic, epigenetic, environmental or stochastic factors. Brain imaging of males with NONO deficiency may reveal structural defects with abnormalities of the corpus callosum being the most common. Although dysmorphic features vary between affected individuals, relative macrocephaly is a common feature.
Keywords: Child; Child, Preschool; Developmental Disabilities; DNA-Binding Proteins; Exome; Heart Defects, Congenital; Heart Ventricles; Humans; Infant; Male; Nuclear Matrix-Associated Proteins; Octamer Transcription Factors; RNA-Binding Proteins

Corner fracture type spondylometaphyseal dysplasia: Overlap with type II collagenopathies. - Machol, Keren; Jain, Mahim; Almannai, Mohammed; Orand, Thibault; Lu, James T; Tran, Alyssa; Chen, Yuqing; Schlesinger, Alan; Richard A Gibbs; Bonafe, Luisa; Campos-Xavier, Ana Belinda; Unger, Sheila; et al. (Am J Med Genet A, 2017)
Spondylometaphyseal dysplasia (SMD) corner fracture type (also known as SMD "Sutcliffe" type, MIM 184255) is a rare skeletal dysplasia that presents with mild to moderate short stature, developmental coxa vara, mild platyspondyly, corner fracture-like lesions, and metaphyseal abnormalities with sparing of the epiphyses. The molecular basis for this disorder has yet to be clarified. We describe two patients with SMD corner fracture type and heterozygous pathogenic variants in COL2A1. These two cases together with a third case of SMD corner fracture type with a heterozygous COL2A1 pathogenic variant previously described suggest that this disorder overlaps with type II collagenopathies. The finding of one of the pathogenic variants in a previously reported case of spondyloepimetaphyseal dysplasia (SEMD) Strudwick type and the significant clinical similarity suggest an overlap between SMD corner fracture and SEMD Strudwick types. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; Amino Acid Substitution; Bone Diseases, Developmental; Child, Preschool; Collagen Type II; Diagnosis, Differential; Exome; Genetic Association Studies; Genotype; Growth Disorders; High-Throughput Nucleotide Sequencing; Hip Joint; Humans; Infant; Male; Mutation; Osteochondrodysplasias; Phenotype; Radiography; Tibial Fractures

De Novo Disruption of the Proteasome Regulatory Subunit PSMD12 Causes a Syndromic Neurodevelopmental Disorder. - Küry, Sébastien; Besnard, Thomas; Ebstein, Frédéric; Khan, Tahir N; Gambin, Tomasz; Douglas, Jessica; Bacino, Carlos A; Craigen, William J; Sanders, Stephan J; Lehmann, Andrea; Latypova, Xénia; Khan, Kamal; et al. (Am J Hum Genet, 2017)
Degradation of proteins by the ubiquitin-proteasome system (UPS) is an essential biological process in the development of eukaryotic organisms. Dysregulation of this mechanism leads to numerous human neurodegenerative or neurodevelopmental disorders. Through a multi-center collaboration, we identified six de novo genomic deletions and four de novo point mutations involving PSMD12, encoding the non-ATPase subunit PSMD12 (aka RPN5) of the 19S regulator of 26S proteasome complex, in unrelated individuals with intellectual disability, congenital malformations, ophthalmologic anomalies, feeding difficulties, deafness, and subtle dysmorphic facial features. We observed reduced PSMD12 levels and an accumulation of ubiquitinated proteins without any impairment of proteasome catalytic activity. Our PSMD12 loss-of-function zebrafish CRISPR/Cas9 model exhibited microcephaly, decreased convolution of the renal tubules, and abnormal craniofacial morphology. Our data support the biological importance of PSMD12 as a scaffolding subunit in proteasome function during development and neurogenesis in particular; they enable the definition of a neurodevelopmental disorder due to PSMD12 variants, expanding the phenotypic spectrum of UPS-dependent disorders.
Keywords: Adolescent; Animals; Child; Child, Preschool; Disease Models, Animal; DNA Copy Number Variations; Down-Regulation; Female; Gene Deletion; Humans; Infant; Intellectual Disability; Male; Microcephaly; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Proteasome Endopeptidase Complex; Zebrafish

De Novo Missense Mutations in DHX30 Impair Global Translation and Cause a Neurodevelopmental Disorder. - Lessel, Davor; Schob, Claudia; Küry, Sébastien; Reijnders, Margot R F; Harel, Tamar; Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Denecke, Jonas; Edvardson, Shimon; Colin, Estelle; Stegmann, Alexander P A; Gerkes, Erica H; et al. (Am J Hum Genet, 2017)
DHX30 is a member of the family of DExH-box helicases, which use ATP hydrolysis to unwind RNA secondary structures. Here we identified six different de novo missense mutations in DHX30 in twelve unrelated individuals affected by global developmental delay (GDD), intellectual disability (ID), severe speech impairment and gait abnormalities. While four mutations are recurrent, two are unique with one affecting the codon of one recurrent mutation. All amino acid changes are located within highly conserved helicase motifs and were found to either impair ATPase activity or RNA recognition in different in vitro assays. Moreover, protein variants exhibit an increased propensity to trigger stress granule (SG) formation resulting in global translation inhibition. Thus, our findings highlight the prominent role of translation control in development and function of the central nervous system and also provide molecular insight into how DHX30 dysfunction might cause a neurodevelopmental disorder.
Keywords: Adenosine Triphosphatases; Adolescent; Amino Acids; Cell Line; Cell Line, Tumor; Central Nervous System; Child; Child, Preschool; Developmental Disabilities; Female; HEK293 Cells; Humans; Intellectual Disability; Male; Mutation, Missense; RNA; RNA Helicases

Disruption of the ATXN1-CIC complex causes a spectrum of neurobehavioral phenotypes in mice and humans. - Lu, Hsiang-Chih; Tan, Qiumin; Rousseaux, Maxime W C; Wang, Wei; Kim, Ji-Yoen; Richman, Ronald; Wan, Ying-Wooi; Yeh, Szu-Ying; Patel, Jay M; Liu, Xiuyun; Lin, Tao; Lee, Yoontae; et al. (Nat Genet, 2017)
Gain-of-function mutations in some genes underlie neurodegenerative conditions, whereas loss-of-function mutations in the same genes have distinct phenotypes. This appears to be the case with the protein ataxin 1 (ATXN1), which forms a transcriptional repressor complex with capicua (CIC). Gain of function of the complex leads to neurodegeneration, but ATXN1-CIC is also essential for survival. We set out to understand the functions of the ATXN1-CIC complex in the developing forebrain and found that losing this complex results in hyperactivity, impaired learning and memory, and abnormal maturation and maintenance of upper-layer cortical neurons. We also found that CIC activity in the hypothalamus and medial amygdala modulates social interactions. Informed by these neurobehavioral features in mouse mutants, we identified five individuals with de novo heterozygous truncating mutations in CIC who share similar clinical features, including intellectual disability, attention deficit/hyperactivity disorder (ADHD), and autism spectrum disorder. Our study demonstrates that loss of ATXN1-CIC complexes causes a spectrum of neurobehavioral phenotypes.
Keywords: Animals; Ataxin-1; Autism Spectrum Disorder; Cerebellum; Female; Humans; Intellectual Disability; Interpersonal Relations; Male; Mice; Nerve Tissue Proteins; Neurodegenerative Diseases; Nuclear Proteins; Phenotype; Repressor Proteins

Dominant Transmission Observed in Adolescents and Families With Orthostatic Intolerance. - Posey, Jennifer E; Martinez, Rebecca; Lankford, Jeremy E; Lupski, James R; Numan, Mohammed T; Butler, Ian J (Pediatr Neurol, 2017)
BACKGROUND: Orthostatic intolerance is typically thought to be sporadic and attributed to cerebral autonomic dysfunction. We sought to identify families with inherited autonomic dysfunction manifest as symptomatic orthostatic intolerance to characterize mode of inheritance and clinical features. METHODS: Sixteen families with two or more first- or second-degree relatives with autonomic dysfunction and orthostatic intolerance were enrolled. A clinical diagnosis of autonomic dysfunction defined by symptomatic orthostatic intolerance diagnosed by head-up tilt table testing was confirmed for each proband. Clinical features and evaluation were obtained from each proband using a standardized intake questionnaire, and family history information was obtained from probands and available relatives. RESULTS: Comprehensive pedigree analysis of 16 families (39 individuals with orthostatic intolerance and 40 individuals suspected of having orthostatic intolerance) demonstrated dominant transmission of autonomic dysfunction with incomplete penetrance. Affected individuals were predominantly female (71.8%, 28/39; F:M, 2.5:1). Male-to-male transmission, although less common, was observed and demonstrated to transmit through unaffected males with an affected parent. Similar to sporadic orthostatic intolerance, probands report a range of symptoms across multiple organ systems, with headaches and neuromuscular features being most common. CONCLUSIONS: Familial occurrence and vertical transmission of autonomic dysfunction in 16 families suggest a novel genetic syndrome with dominant transmission, incomplete penetrance, and skewing of the sex ratio. Elucidation of potential genetic contributions to orthostatic intolerance may inform therapeutic management and identification of individuals at risk. Adolescent evaluation should include identification and treatment of potential at-risk relatives.
Keywords: Adolescent; Cohort Studies; Family; Female; Genetic Testing; Humans; Male; Orthostatic Intolerance; Pedigree; Posture; Surveys and Questionnaires; Tilt-Table Test

Enrichment of mutations in chromatin regulators in people with Rett syndrome lacking mutations in MECP2. - Sajan, Samin A; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; Lupski, James R; Glaze, Daniel G; Kaufmann, Walter E; Skinner, Steven A; Annese, Fran; Friez, Michael J; Lane, Jane; Percy, Alan K; et al. (Genet Med, 2017)
PURPOSE: Rett syndrome (RTT) is a neurodevelopmental disorder caused primarily by de novo mutations in MECP2 and sometimes in CDKL5 and FOXG1. However, some RTT patients lack mutations in these genes. METHODS: Twenty-two RTT patients without apparent MECP2, CDKL5, and FOXG1 mutations were subjected to both whole-exome sequencing and single-nucleotide polymorphism array-based copy-number variant (CNV) analyses. RESULTS: Three patients had MECP2 mutations initially missed by clinical testing. Of the remaining 19, 17 (89.5%) had 29 other likely pathogenic intragenic mutations and/or CNVs (10 patients had 2 or more). Interestingly, 13 patients had mutations in a gene/region previously reported in other neurodevelopmental disorders (NDDs), thereby providing a potential diagnostic yield of 68.4%. These mutations were significantly enriched in chromatin regulators (corrected P = 0.0068) and moderately enriched in postsynaptic cell membrane molecules (corrected P = 0.076), implicating glutamate receptor signaling. CONCLUSION: The genetic etiology of RTT without MECP2, CDKL5, and FOXG1 mutations is heterogeneous, overlaps with other NDDs, and complicated by a high mutation burden. Dysregulation of chromatin structure and abnormal excitatory synaptic signaling may form two common pathological bases of RTT.Genet Med 19 1, 13-19.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromatin; DNA Copy Number Variations; Exome Sequencing; Female; Forkhead Transcription Factors; Humans; Infant; Male; Methyl-CpG-Binding Protein 2; Mutation; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases; Rett Syndrome

An exome sequencing study of Moebius syndrome including atypical cases reveals an individual with CFEOM3A and a mutation. - Patel, Ronak M; Liu, David; Gonzaga-Jauregui, Claudia; Jhangiani, Shalini; Lu, James T; Sutton, V Reid; Fernbach, Susan D; Azamian, Mahshid; White, Lisa; Edmond, Jane C; Paysse, Evelyn A; Belmont, John W; et al. (Cold Spring Harb Mol Case Stud, 2017)
Moebius syndrome is characterized by congenital unilateral or bilateral facial and abducens nerve palsies (sixth and seventh cranial nerves) causing facial weakness, feeding difficulties, and restricted ocular movements. Abnormalities of the chest wall such as Poland anomaly and variable limb defects are frequently associated with this syndrome. Most cases are isolated; however, rare families with autosomal dominant transmission with incomplete penetrance and variable expressivity have been described. The genetic basis of this condition remains unknown. In a cohort study of nine individuals suspected to have Moebius syndrome (six typical, three atypical), we performed whole-exome sequencing to try to identify a commonly mutated gene. Although no such gene was identified and we did not find mutations in and , we found a de novo heterozygous mutation, p.E410K, in the gene encoding tubulin beta 3 class III (), in an individual with atypical Moebius syndrome. This individual was diagnosed with near-complete ophthalmoplegia, agenesis of the corpus callosum, and absence of the septum pellucidum. No substantial limb abnormalities were noted. Mutations in have been associated with complex cortical dysplasia and other brain malformations and congenital fibrosis of extraocular muscles type 3A (CFEOM3A). Our report highlights the overlap of genetic etiology and clinical differences between CFEOM and Moebius syndrome and describes our approach to identifying candidate genes for typical and atypical Moebius syndrome.
Keywords: Child; Child, Preschool; Cohort Studies; Exome; Exome Sequencing; Eye Diseases, Hereditary; Facial Paralysis; Female; Humans; Infant; Male; Malformations of Cortical Development; Mobius Syndrome; Muscular Diseases; Mutation; Ocular Motility Disorders; Ophthalmoplegia; Orbital Diseases; Pedigree; Tubulin

Fifteen new risk loci for coronary artery disease highlight arterial-wall-specific mechanisms. - Howson, Joanna M M; Zhao, Wei; Barnes, Daniel R; Ho, Weang-Kee; Young, Robin; Paul, Dirk S; Waite, Lindsay L; Freitag, Daniel F; Fauman, Eric B; Salfati, Elias L; Sun, Benjamin B; Eicher, John D; et al. (Nat Genet, 2017)
Coronary artery disease (CAD) is a leading cause of morbidity and mortality worldwide. Although 58 genomic regions have been associated with CAD thus far, most of the heritability is unexplained, indicating that additional susceptibility loci await identification. An efficient discovery strategy may be larger-scale evaluation of promising associations suggested by genome-wide association studies (GWAS). Hence, we genotyped 56,309 participants using a targeted gene array derived from earlier GWAS results and performed meta-analysis of results with 194,427 participants previously genotyped, totaling 88,192 CAD cases and 162,544 controls. We identified 25 new SNP-CAD associations (P < 5 × 10, in fixed-effects meta-analysis) from 15 genomic regions, including SNPs in or near genes involved in cellular adhesion, leukocyte migration and atherosclerosis (PECAM1, rs1867624), coagulation and inflammation (PROCR, rs867186 (p.Ser219Gly)) and vascular smooth muscle cell differentiation (LMOD1, rs2820315). Correlation of these regions with cell-type-specific gene expression and plasma protein levels sheds light on potential disease mechanisms.
Keywords: Arteries; Atherosclerosis; Cell Adhesion; Chemotaxis, Leukocyte; Coronary Artery Disease; Energy Metabolism; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Histone Code; Humans; Male; Muscle, Smooth, Vascular; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

Further delineation of a rare recessive encephalomyopathy linked to mutations in GFER thanks to data sharing of whole exome sequencing data. - Nambot, S; Gavrilov, D; Thevenon, J; Bruel, A L; Bainbridge, M; Rio, M; Goizet, C; Rötig, A; Jaeken, J; Niu, N; Xia, F; Vital, A; et al. (Clin Genet, 2017)
BACKGROUND: Alterations in GFER gene have been associated with progressive mitochondrial myopathy, congenital cataracts, hearing loss, developmental delay, lactic acidosis and respiratory chain deficiency in 3 siblings born to consanguineous Moroccan parents by homozygosity mapping and candidate gene approach (OMIM#613076). Next generation sequencing recently confirmed this association by the finding of compound heterozygous variants in 19-year-old girl with a strikingly similar phenotype, but this ultra-rare entity remains however unknown from most of the scientific community. MATERIALS AND METHODS: Whole exome sequencing was performed as part of a "diagnostic odyssey" for suspected mitochondrial condition in 2 patients, presenting congenital cataracts, progressive encephalomyopathy and hypotrophy and detected unreported compound heterozygous variants in GFER. RESULTS: Thanks to an international data sharing, we found 2 additional patients carrying compound heterozygous variants in GFER. Reverse phenotyping confirmed the phenotypical similarities between the 4 patients. Together with the first literature reports, the review of these 8 cases from 4 unrelated families enables us to better describe this apparently homogeneous disorder, with the clinical and biological stigmata of mitochondrial disease. CONCLUSION: This report highlights the clinical utility of whole exome sequencing and reverse phenotyping for the diagnosis of ultra-rare diseases and underlines the importance of a broad data sharing for accurate clinical delineation of previously unrecognized entities.
Keywords: Adolescent; Adult; Child; Cytochrome Reductases; Exome Sequencing; Female; Genetic Predisposition to Disease; Heterozygote; Humans; Male; Mitochondrial Encephalomyopathies; Mutation; Oxidoreductases Acting on Sulfur Group Donors; Pedigree; Young Adult

The Genetic Causes of Nonsyndromic Congenital Retinal Detachment: A Genetic and Phenotypic Study of Pakistani Families. - Keser, Vafa; Khan, Ayesha; Siddiqui, Sorath; Lopez, Irma; Ren, Huanan; Qamar, Raheel; Nadaf, Javad; Majewski, Jacek; Rui Chen; Koenekoop, Robert K (Invest Ophthalmol Vis Sci, 2017)
PURPOSE: To evaluate consanguineous pedigrees from Pakistan with a clinical diagnosis of nonsyndromic congenital retinal nonattachment (NCRNA) and identify genes responsible for the disease as currently only one NCRNA gene is known (atonal basic helix-loop-helix transcription factor 7: ATOH7). METHODS: We implemented a three-step genotyping platform: single nucleotide polymorphism genotyping to identify loss of heterozygosity regions in patients, Retinal Information Network panel screening for mutations in currently known retinal genes. Negative patients were then subjected to whole exome sequencing. RESULTS: We evaluated 21 consanguineous NCRNA pedigrees and identified the causal mutations in known retinal genes in 13 out of our 21 families. We found mutations in ATOH7 in three families. Surprisingly, we then found mutations in familial exudative vitreoretinopathy (FEVR) genes; low-density lipoprotein receptor-related protein 5 mutations (six families), tetraspanin 12 mutations (two families), and NDP mutations (two families). Thus, 62% of the patients were successfully genotyped in our study with seven novel and six previously reported mutations in known retinal genes. CONCLUSIONS: Although the clinical diagnosis of all children was NCRNA with severe congenital fibrotic retinal detachments, the molecular diagnosis determined that the disease process was in fact a very severe form of FEVR in 10 families. Because severe congenital retinal detachment has not been previously associated with all the FEVR genes, we have thus expanded the phenotypic spectrum of FEVR, a highly variable retinal detachment phenotype that has clinical overlap with NCRNA. We identified seven novel mutations. We also established for the first time genetic overlap between the Iranian and Pakistani populations. We identified eight NCRNA families that do not harbor mutations in any known retinal genes, suggesting novel causal genes in these families.
Keywords: Basic Helix-Loop-Helix Transcription Factors; Child; Child, Preschool; DNA Mutational Analysis; Female; Genotype; Helix-Loop-Helix Motifs; Humans; Incidence; Infant; Male; Mutation; Pakistan; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Retina; Retinal Diseases

Genetic variants associated with risk of Alzheimer's disease contribute to cognitive change in midlife: The Atherosclerosis Risk in Communities Study. - Bressler, Jan; Mosley, Thomas H; Penman, Alan; Gottesman, Rebecca F; Windham, Beverly Gwen; Knopman, David S; Wruck, Lisa M; Eric Boerwinkle (Am J Med Genet B Neuropsychiatr Genet, 2017)
Alzheimer's disease (AD) is the most common form of dementia and is characterized by impairment in memory, behavioral changes, and gradual loss of autonomy. Since there is a long latent period prior to diagnosis, the aim of this study was to determine whether twenty single nucleotide polymorphisms identified in genome-wide association analyses of AD are associated with cognitive change in 8,320 white and 2,039 African-American middle-aged adults enrolled in the prospective Atherosclerosis Risk in Communities (ARIC) study. Cognition was evaluated using the Delayed Word Recall Test (DWRT; verbal memory), Digit Symbol Substitution Test (DSST; processing speed), and Word Fluency Test (WFT; executive function). General linear models were used to assess mean differences in 6-year change in test scores among individuals categorized by genotype after adjusting for age, gender, and years of education. Addition of the minor allele for rs670139 (MS4A4E), rs9331896 (CLU), and rs12155159 (NME8) was nominally associated with change on the DWRT, DSST, and WFT, respectively, in whites. The ZCWPW1 (rs1476679) and CDS33 (rs3865444) variants were nominally associated with change on the DWRT and WFT in African-Americans. For rs670139 and rs9331896 the association was only significant in individuals bearing at least one APOE ϵ4 allele in stratified analyses. An unweighted genetic risk score aggregating the risk alleles for 15 polymorphisms was not associated with change in cognitive function. Although the AD-associated genetic variants appear to have small effects on early cognitive change, replication will be required to establish whether there is a discernible influence on cognitive status in midlife. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; Alzheimer Disease; Atherosclerosis; Black or African American; Black People; Clusterin; Cognition; Cognition Disorders; Dementia; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Membrane Proteins; Memory; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Thioredoxins; White People

Genome-wide association study of 1,5-anhydroglucitol identifies novel genetic loci linked to glucose metabolism. - Li, Man; Maruthur, Nisa M; Loomis, Stephanie J; Pietzner, Maik; North, Kari E; Mei, Hao; Morrison, Alanna C; Friedrich, Nele; Pankow, James S; Nauck, Matthias; Eric Boerwinkle; Teumer, Alexander; et al. (Sci Rep, 2017)
1,5-anhydroglucitol (1,5-AG) is a biomarker of hyperglycemic excursions associated with diabetic complications. Because of its structural similarity to glucose, genetic studies of 1,5-AG can deliver complementary insights into glucose metabolism. We conducted genome-wide association studies of serum 1,5-AG concentrations in 7,550 European ancestry (EA) and 2,030 African American participants (AA) free of diagnosed diabetes from the ARIC Study. Seven loci in/near EFNA1/SLC50A1, MCM6/LCT, SI, MGAM, MGAM2, SLC5A10, and SLC5A1 showed genome-wide significant associations (P < 5 × 10) among EA participants, five of which were novel. Six of the seven loci were successfully replicated in 8,790 independent EA individuals, and MCM6/LCT and SLC5A10 were also associated among AA. Most of 1,5-AG-associated index SNPs were not associated with the clinical glycemic markers fasting glucose or the  HbA1c, and vice versa. Only the index variant in SLC5A1 showed a significant association with fasting glucose in the expected opposing direction. Products of genes in all 1,5-AG-associated loci have known roles in carbohydrate digestion and enteral or renal glucose transport, suggesting that genetic variants associated with 1,5-AG influence its concentration via effects on glucose metabolism and handling.
Keywords: Aged; Black or African American; Deoxyglucose; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose; Glycated Hemoglobin; Humans; Hyperglycemia; Insulin; Male; Middle Aged; Minichromosome Maintenance Complex Component 6; Sodium-Glucose Transporter 1; White People

Genomic Alterations of Adamantinomatous and Papillary Craniopharyngioma. - Goschzik, Tobias; Gessi, Marco; Dreschmann, Verena; Gebhardt, Ursel; Wang, Linghua; Yamaguchi, Shigeru; Wheeler, David A; Lauriola, Libero; Lau, Ching C; Müller, Hermann L; Pietsch, Torsten (J Neuropathol Exp Neurol, 2017)
Craniopharyngiomas are rare histologically benign but clinically challenging neoplasms. To obtain further information on the molecular genetics and biology of craniopharyngiomas, we analyzed a cohort of 121 adamantinomatous and 16 papillary craniopharyngiomas (ACP, PCP). We extracted DNA from formalin-fixed paraffin-embedded tissue and determined mutational status of CTNNB1, BRAF, and DDX3X by Sanger sequencing, next generation panel sequencing, and pyrosequencing. Sixteen craniopharyngiomas were further analyzed by molecular inversion profiling (MIP); 76.1% of the ACP were mutated in exon 3 of CTNNB1 encoding for β-catenin and there was a trend towards a worse event-free survival in cases mutated at Thr41. Next generation panel sequencing of 26 ACP did not detect any recurrent mutations other than CTNNB1 mutations. BRAF V600E mutations were found in 94% of the PCP, but not in ACP. GISTIC analysis of MIP data showed no significant larger chromosomal aberrations but a fraction of ACP showed recurrent focal gains of chromosomal material, other cases showed loss in the chromosomal region Xq28, and a third group and the PCP had stable genomes. In conclusion, the crucial pathogenetic event appears to be WNT activation in ACP, whereas it appears to be activation of the Ras/Raf/MEK/ERK pathway by BRAF V600E mutations in PCP.
Keywords: Adolescent; Adult; Amino Acid Sequence; Child; Craniopharyngioma; Female; Genomics; Humans; Male; Middle Aged; Mutation; Pituitary Neoplasms; Young Adult

Germline mutations in ABL1 cause an autosomal dominant syndrome characterized by congenital heart defects and skeletal malformations. - Wang, Xia; Charng, Wu-Lin; Chen, Chun-An; Rosenfeld, Jill A; Al Shamsi, Aisha; Al-Gazali, Lihadh; McGuire, Marianne; Mew, Nicholas Ah; Arnold, Georgianne L; Qu, Chunjing; Ding, Yan; Donna M Muzny; et al. (Nat Genet, 2017)
ABL1 is a proto-oncogene well known as part of the fusion gene BCR-ABL1 in the Philadelphia chromosome of leukemia cancer cells. Inherited germline ABL1 changes have not been associated with genetic disorders. Here we report ABL1 germline variants cosegregating with an autosomal dominant disorder characterized by congenital heart disease, skeletal abnormalities, and failure to thrive. The variant c.734A>G (p.Tyr245Cys) was found to occur de novo or cosegregate with disease in five individuals (families 1-3). Additionally, a de novo c.1066G>A (p.Ala356Thr) variant was identified in a sixth individual (family 4). We overexpressed the mutant constructs in HEK 293T cells and observed increased tyrosine phosphorylation, suggesting increased ABL1 kinase activities associated with both the p.Tyr245Cys and p.Ala356Thr substitutions. Our clinical and experimental findings, together with previously reported teratogenic effects of selective BCR-ABL inhibitors in humans and developmental defects in Abl1 knockout mice, suggest that ABL1 has an important role during organismal development.
Keywords: Abnormalities, Multiple; Animals; Bone Diseases, Developmental; Cell Line; Chromosome Disorders; Craniofacial Abnormalities; Feeding and Eating Disorders; Female; Fusion Proteins, bcr-abl; Germ-Line Mutation; Heart Defects, Congenital; HEK293 Cells; Humans; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Limb Deformities, Congenital; Male; Mice; Mice, Knockout; Philadelphia Chromosome; Phosphorylation; Proto-Oncogene Mas; Signal Transduction

Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features. - Zhang, Jing; Gambin, Tomasz; Bo Yuan; Szafranski, Przemyslaw; Rosenfeld, Jill A; Balwi, Mohammed Al; Alswaid, Abdulrahman; Al-Gazali, Lihadh; Shamsi, Aisha M Al; Komara, Makanko; Ali, Bassam R; Roeder, Elizabeth; et al. (Hum Genet, 2017)
Impairment of ubiquitin-proteasome system activity involving ubiquitin ligase genes UBE3A, UBE3B, and HUWE1 and deubiquitinating enzyme genes USP7 and USP9X has been reported in patients with neurodevelopmental delays. To date, only a handful of single-nucleotide variants (SNVs) and copy-number variants (CNVs) involving TRIP12, encoding a member of the HECT domain E3 ubiquitin ligases family on chromosome 2q36.3 have been reported. Using chromosomal microarray analysis and whole-exome sequencing (WES), we have identified, respectively, five deletion CNVs and four inactivating SNVs (two frameshifts, one missense, and one splicing) in TRIP12. Seven of these variants were found to be de novo; parental studies could not be completed in two families. Quantitative PCR analyses of the splicing mutation showed a dramatically decreased level of TRIP12 mRNA in the proband compared to the family controls, indicating a loss-of-function mechanism. The shared clinical features include intellectual disability with or without autistic spectrum disorders, speech delay, and facial dysmorphism. Our findings demonstrate that E3 ubiquitin ligase TRIP12 plays an important role in nervous system development and function. The nine presented pathogenic variants further document that TRIP12 haploinsufficiency causes a childhood-onset neurodevelopmental disorder. Finally, our data enable expansion of the phenotypic spectrum of ubiquitin-proteasome dependent disorders.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Cohort Studies; DNA Copy Number Variations; Facies; Female; Haploinsufficiency; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Ubiquitin-Protein Ligases

Heterozygous variants in ACTL6A, encoding a component of the BAF complex, are associated with intellectual disability. - Marom, Ronit; Jain, Mahim; Burrage, Lindsay C; Song, I-Wen; Graham, Brett H; Brown, Chester W; Stevens, Servi J C; Stegmann, Alexander P A; Gunter, Andrew T; Kaplan, Julie D; Gavrilova, Ralitza H; Shinawi, Marwan; et al. (Hum Mutat, 2017)
Pathogenic variants in genes encoding components of the BRG1-associated factor (BAF) chromatin remodeling complex have been associated with intellectual disability syndromes. We identified heterozygous, novel variants in ACTL6A, a gene encoding a component of the BAF complex, in three subjects with varying degrees of intellectual disability. Two subjects have missense variants affecting highly conserved amino acid residues within the actin-like domain. Missense mutations in the homologous region in yeast actin were previously reported to be dominant lethal and were associated with impaired binding of the human ACTL6A to β-actin and BRG1. A third subject has a splicing variant that creates an in-frame deletion. Our findings suggest that the variants identified in our subjects may have a deleterious effect on the function of the protein by disturbing the integrity of the BAF complex. Thus, ACTL6A gene mutation analysis should be considered in patients with intellectual disability, learning disabilities, or developmental language disorder.
Keywords: Actins; Adolescent; Child; Chromatin Assembly and Disassembly; Chromosomal Proteins, Non-Histone; DNA Helicases; DNA-Binding Proteins; Exome; Face; Female; Hand Deformities, Congenital; Heterozygote; Humans; Intellectual Disability; Male; Micrognathism; Multiprotein Complexes; Mutation, Missense; Nuclear Proteins; Protein Binding; Transcription Factors

The house spider genome reveals an ancient whole-genome duplication during arachnid evolution. - Schwager, Evelyn E; Sharma, Prashant P; Clarke, Thomas; Leite, Daniel J; Wierschin, Torsten; Pechmann, Matthias; Akiyama-Oda, Yasuko; Esposito, Lauren; Bechsgaard, Jesper; Bilde, Trine; Buffry, Alexandra D; Chao, Hsu; et al. (BMC Biol, 2017)
BACKGROUND: The duplication of genes can occur through various mechanisms and is thought to make a major contribution to the evolutionary diversification of organisms. There is increasing evidence for a large-scale duplication of genes in some chelicerate lineages including two rounds of whole genome duplication (WGD) in horseshoe crabs. To investigate this further, we sequenced and analyzed the genome of the common house spider Parasteatoda tepidariorum. RESULTS: We found pervasive duplication of both coding and non-coding genes in this spider, including two clusters of Hox genes. Analysis of synteny conservation across the P. tepidariorum genome suggests that there has been an ancient WGD in spiders. Comparison with the genomes of other chelicerates, including that of the newly sequenced bark scorpion Centruroides sculpturatus, suggests that this event occurred in the common ancestor of spiders and scorpions, and is probably independent of the WGDs in horseshoe crabs. Furthermore, characterization of the sequence and expression of the Hox paralogs in P. tepidariorum suggests that many have been subject to neo-functionalization and/or sub-functionalization since their duplication. CONCLUSIONS: Our results reveal that spiders and scorpions are likely the descendants of a polyploid ancestor that lived more than 450 MYA. Given the extensive morphological diversity and ecological adaptations found among these animals, rivaling those of vertebrates, our study of the ancient WGD event in Arachnopulmonata provides a new comparative platform to explore common and divergent evolutionary outcomes of polyploidization events across eukaryotes.
Keywords: Animals; Evolution, Molecular; Female; Gene Duplication; Genome; Male; Spiders; Synteny

House spider genome uncovers evolutionary shifts in the diversity and expression of black widow venom proteins associated with extreme toxicity. - Gendreau, Kerry L; Haney, Robert A; Schwager, Evelyn E; Wierschin, Torsten; Stanke, Mario; Richards, Stephen; Garb, Jessica E (BMC Genomics, 2017)
BACKGROUND: Black widow spiders are infamous for their neurotoxic venom, which can cause extreme and long-lasting pain. This unusual venom is dominated by latrotoxins and latrodectins, two protein families virtually unknown outside of the black widow genus Latrodectus, that are difficult to study given the paucity of spider genomes. Using tissue-, sex- and stage-specific expression data, we analyzed the recently sequenced genome of the house spider (Parasteatoda tepidariorum), a close relative of black widows, to investigate latrotoxin and latrodectin diversity, expression and evolution. RESULTS: We discovered at least 47 latrotoxin genes in the house spider genome, many of which are tandem-arrayed. Latrotoxins vary extensively in predicted structural domains and expression, implying their significant functional diversification. Phylogenetic analyses show latrotoxins have substantially duplicated after the Latrodectus/Parasteatoda split and that they are also related to proteins found in endosymbiotic bacteria. Latrodectin genes are less numerous than latrotoxins, but analyses show their recruitment for venom function from neuropeptide hormone genes following duplication, inversion and domain truncation. While latrodectins and other peptides are highly expressed in house spider and black widow venom glands, latrotoxins account for a far smaller percentage of house spider venom gland expression. CONCLUSIONS: The house spider genome sequence provides novel insights into the evolution of venom toxins once considered unique to black widows. Our results greatly expand the size of the latrotoxin gene family, reinforce its narrow phylogenetic distribution, and provide additional evidence for the lateral transfer of latrotoxins between spiders and bacterial endosymbionts. Moreover, we strengthen the evidence for the evolution of latrodectin venom genes from the ecdysozoan Ion Transport Peptide (ITP)/Crustacean Hyperglycemic Hormone (CHH) neuropeptide superfamily. The lower expression of latrotoxins in house spiders relative to black widows, along with the absence of a vertebrate-targeting α-latrotoxin gene in the house spider genome, may account for the extreme potency of black widow venom.
Keywords: Animals; Black Widow Spider; Coxiellaceae; Evolution, Molecular; Female; Gene Expression Profiling; Genetic Variation; Genomics; Insect Proteins; Male; Protein Domains; Sex Characteristics; Spider Venoms; Symbiosis

IFT81 as a Candidate Gene for Nonsyndromic Retinal Degeneration. - Dharmat, Rachayata; Liu, Wei; Ge, Zhongqi; Sun, Zixi; Yang, Lizhu; Yumei Li; Wang, Keqing; Thomas, Kandace; Sui, Ruifang; Rui Chen (Invest Ophthalmol Vis Sci, 2017)
PURPOSE: IFT81, a core component of the IFT-B complex, involved in the bidirectional transport of ciliary proteins, has been recently implicated in syndromic ciliopathies. However, none of the IFT-B core complex proteins have been associated with nonsyndromic retinal dystrophies. Given the importance of ciliary transport in photoreceptor function and structural maintenance, we sought to investigate the impact of IFT (intraflagellar transport) mutations in nonsyndromic retinopathies. METHODS: Whole exome sequencing was performed on 50 cone-rod dystrophy (CRD) patients that were previously screened for mutations in known retinal disease genes. The impact of candidate mutation was studied using in vitro cell system and in vivo zebrafish assay to determine the pathogenicity of the variant. RESULTS: Compound heterozygous mutations in IFT81, including one nonsense (c.1213C>T, p.R405*) and one missense variant (c.1841T>C, p.L614P), were identified in a nonsyndromic CRD proband. Extensive functional analyses of the missense variant in cell culture and zebrafish strongly suggests its pathogenic nature. Loss of IFT81 impairs ciliogenesis and, interestingly, the missense variant displayed significantly reduced rescue of ciliogenesis in the IFT81 knockdown in vitro system. Consistently, dramatic reduction of rescue efficiency of the ift81 mutant zebrafish embryo by mRNA with the missense variant was observed, further supporting its pathogenicity. CONCLUSIONS: Consistent with the function of the IFT-B complex in the maintenance of photoreceptor cilium, we report a case of mutations in a core IFT-B protein, IFT81. This represents the first report of mutations in IFT81 as a candidate gene for nonsyndromic retinal dystrophy, hence expanding the phenotype spectrum of IFT-B components.
Keywords: Animals; Cells, Cultured; Codon, Nonsense; Disease Models, Animal; DNA; DNA Mutational Analysis; Female; Humans; Male; Muscle Proteins; Mutation; Phenotype; Retina; Retinal Degeneration; Zebrafish

Incident Heart Failure and Cognitive Decline: The Atherosclerosis Risk in Communities Study. - Bressler, Jan; Knopman, David S; Sharrett, A Richey; Gottesman, Rebecca F; Penman, Alan; Chang, Patricia P; Rosamond, Wayne D; Eric Boerwinkle; Mosley, Thomas H (J Card Fail, 2017)
BACKGROUND: Cognitive impairment is found in a significant proportion of patients with heart failure (HF). Although cognitive impairment may be a consequence of HF, early signs of cognitive impairment may also indicate subclinical vascular disease, and thus a risk factor for future cardiovascular events. METHODS AND RESULTS: The Atherosclerosis Risk in Communities Study is a prospective cohort study of the development of atherosclerosis. Cox proportional hazards regression was used to examine the association between mean 6-year change in cognitive function and incident HF in 7962 white and 1933 African-American men and women aged 46 to 70 years and free of clinical stroke. Scores were obtained for the Delayed Word Recall Test, the Digit Symbol Substitution Test (DSST), and the Word Fluency Test. There was a significantly increased risk of developing HF during the mean 12.6-year follow-up period after adjustment for age, gender, race, and education for those in the quartile with the greatest decline in DSST scores (hazard ratio [HR] = 1.17, P = .009), and in the quartile with the lowest baseline DSST scores (HR = 1.43, P < .001). CONCLUSIONS: The results suggest that relatively low performance on a test of information processing speed may serve as an indicator of HF risk in middle age.
Keywords: Adult; Aged; Atherosclerosis; Cognition; Cognitive Dysfunction; Female; Follow-Up Studies; Heart Failure; Humans; Incidence; Male; Middle Aged; Neuropsychological Tests; Prospective Studies; Residence Characteristics; Risk Assessment; Risk Factors; Time Factors; United States

Integrative Genomic Analysis of Cholangiocarcinoma Identifies Distinct IDH-Mutant Molecular Profiles. - Farshidfar, Farshad; Zheng, Siyuan; Marie-Claude Gingras; Newton, Yulia; Shih, Juliann; Robertson, A Gordon; Hinoue, Toshinori; Hoadley, Katherine A; Gibb, Ewan A; Roszik, Jason; Covington, Kyle R; Wu, Chia-Chin; et al. (Cell Rep, 2017)
Cholangiocarcinoma (CCA) is an aggressive malignancy of the bile ducts, with poor prognosis and limited treatment options. Here, we describe the integrated analysis of somatic mutations, RNA expression, copy number, and DNA methylation by The Cancer Genome Atlas of a set of predominantly intrahepatic CCA cases and propose a molecular classification scheme. We identified an IDH mutant-enriched subtype with distinct molecular features including low expression of chromatin modifiers, elevated expression of mitochondrial genes, and increased mitochondrial DNA copy number. Leveraging the multi-platform data, we observed that ARID1A exhibited DNA hypermethylation and decreased expression in the IDH mutant subtype. More broadly, we found that IDH mutations are associated with an expanded histological spectrum of liver tumors with molecular features that stratify with CCA. Our studies reveal insights into the molecular pathogenesis and heterogeneity of cholangiocarcinoma and provide classification information of potential therapeutic significance.
Keywords: Adult; Aged; Aged, 80 and over; Bile Duct Neoplasms; Cholangiocarcinoma; Chromatin; DNA Methylation; DNA-Binding Proteins; Female; Gene Expression Regulation, Neoplastic; Genomics; Humans; Isocitrate Dehydrogenase; Liver; Liver Neoplasms; Male; Middle Aged; Mitochondria; Mutation; Nuclear Proteins; Pancreatic Neoplasms; Promoter Regions, Genetic; RNA, Long Noncoding; RNA, Messenger; Transcription Factors

Kaufman oculo-cerebro-facial syndrome in a child with small and absent terminal phalanges and absent nails. - Kariminejad, Ariana; Ajeawung, Norbert Fonya; Bozorgmehr, Bita; Dionne-Laporte, Alexandre; Molidperee, Sirinart; Najafi, Kimia; Richard A Gibbs; Lee, Brendan H; Hennekam, Raoul C; Campeau, Philippe M (J Hum Genet, 2017)
Kaufman oculo-cerebro-facial syndrome (KOS) is caused by recessive UBE3B mutations and presents with microcephaly, ocular abnormalities, distinctive facial morphology, low cholesterol levels and intellectual disability. We describe a child with microcephaly, brachycephaly, hearing loss, ptosis, blepharophimosis, hypertelorism, cleft palate, multiple renal cysts, absent nails, small or absent terminal phalanges, absent speech and intellectual disability. Syndromes that were initially considered include DOORS syndrome, Coffin-Siris syndrome and Dubowitz syndrome. Clinical investigations coupled with karyotype analysis, array-comparative genomic hybridization, exome and Sanger sequencing were performed to characterize the condition in this child. Sanger sequencing was negative for the DOORS syndrome gene TBC1D24 but exome sequencing identified a homozygous deletion in UBE3B (NM_183415:c.3139_3141del, p.1047_1047del) located within the terminal portion of the HECT domain. This finding coupled with the presence of characteristic features such as brachycephaly, ptosis, blepharophimosis, hypertelorism, short palpebral fissures, cleft palate and developmental delay allowed us to make a diagnosis of KOS. In conclusion, our findings highlight the importance of considering KOS as a differential diagnosis for patients under evaluation for DOORS syndrome and expand the phenotype of KOS to include small or absent terminal phalanges, nails, and the presence of hallux varus and multicystic dysplastic kidneys.
Keywords: Abnormalities, Multiple; Adult; Carrier Proteins; Child; Child, Preschool; Diagnosis, Differential; Eczema; Eye Abnormalities; Face; Facies; Female; Growth Disorders; GTPase-Activating Proteins; Hand Deformities, Congenital; Humans; Intellectual Disability; Karyotype; Limb Deformities, Congenital; Male; Membrane Proteins; Microcephaly; Micrognathism; Mutation; Neck; Nerve Tissue Proteins; Pathology, Molecular; Sequence Analysis, DNA; Ubiquitin-Protein Ligases

Lessons learned from additional research analyses of unsolved clinical exome cases. - Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Harel, Tamar; Rosenfeld, Jill A; Gambin, Tomasz; Stray-Pedersen, Asbjørg; Küry, Sébastien; Mercier, Sandra; Lessel, Davor; Denecke, Jonas; Wiszniewski, Wojciech; Penney, Samantha; et al. (Genome Med, 2017)
BACKGROUND: Given the rarity of most single-gene Mendelian disorders, concerted efforts of data exchange between clinical and scientific communities are critical to optimize molecular diagnosis and novel disease gene discovery. METHODS: We designed and implemented protocols for the study of cases for which a plausible molecular diagnosis was not achieved in a clinical genomics diagnostic laboratory (i.e. unsolved clinical exomes). Such cases were recruited to a research laboratory for further analyses, in order to potentially: (1) accelerate novel disease gene discovery; (2) increase the molecular diagnostic yield of whole exome sequencing (WES); and (3) gain insight into the genetic mechanisms of disease. Pilot project data included 74 families, consisting mostly of parent-offspring trios. Analyses performed on a research basis employed both WES from additional family members and complementary bioinformatics approaches and protocols. RESULTS: Analysis of all possible modes of Mendelian inheritance, focusing on both single nucleotide variants (SNV) and copy number variant (CNV) alleles, yielded a likely contributory variant in 36% (27/74) of cases. If one includes candidate genes with variants identified within a single family, a potential contributory variant was identified in a total of ~51% (38/74) of cases enrolled in this pilot study. The molecular diagnosis was achieved in 30/63 trios (47.6%). Besides this, the analysis workflow yielded evidence for pathogenic variants in disease-associated genes in 4/6 singleton cases (66.6%), 1/1 multiplex family involving three affected siblings, and 3/4 (75%) quartet families. Both the analytical pipeline and the collaborative efforts between the diagnostic and research laboratories provided insights that allowed recent disease gene discoveries (PURA, TANGO2, EMC1, GNB5, ATAD3A, and MIPEP) and increased the number of novel genes, defined in this study as genes identified in more than one family (DHX30 and EBF3). CONCLUSION: An efficient genomics pipeline in which clinical sequencing in a diagnostic laboratory is followed by the detailed reanalysis of unsolved cases in a research environment, supplemented with WES data from additional family members, and subject to adjuvant bioinformatics analyses including relaxed variant filtering parameters in informatics pipelines, can enhance the molecular diagnostic yield and provide mechanistic insights into Mendelian disorders. Implementing these approaches requires collaborative clinical molecular diagnostic and research efforts.
Keywords: Adenosine Triphosphatases; ATPases Associated with Diverse Cellular Activities; Computational Biology; DNA Copy Number Variations; DNA-Binding Proteins; Exome; Female; Genetic Diseases, Inborn; Genomics; GTP-Binding Protein beta Subunits; Humans; Male; Membrane Proteins; Metalloendopeptidases; Mitochondrial Proteins; Pilot Projects; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Transcription Factors

Loss-of-Function Variants in MYLK Cause Recessive Megacystis Microcolon Intestinal Hypoperistalsis Syndrome. - Halim, Danny; Brosens, Erwin; Muller, Françoise; Wangler, Michael F; Beaudet, Arthur L; Lupski, James R; Akdemir, Zeynep H Coban; Doukas, Michael; Stoop, Hans J; de Graaf, Bianca M; Brouwer, Rutger W W; van IJcken, Wilfred F J; et al. (Am J Hum Genet, 2017)
Megacystis microcolon intestinal hypoperistalsis syndrome (MMIHS) is a congenital disorder characterized by loss of smooth muscle contraction in the bladder and intestine. To date, three genes are known to be involved in MMIHS pathogenesis: ACTG2, MYH11, and LMOD1. However, for approximately 10% of affected individuals, the genetic cause of the disease is unknown, suggesting that other loci are most likely involved. Here, we report on three MMIHS-affected subjects from two consanguineous families with no variants in the known MMIHS-associated genes. By performing homozygosity mapping and whole-exome sequencing, we found homozygous variants in myosin light chain kinase (MYLK) in both families. We identified a 7 bp duplication (c.3838_3844dupGAAAGCG [p.Glu1282_Glyfs51]) in one family and a putative splice-site variant (c.3985+5C>A) in the other. Expression studies and splicing assays indicated that both variants affect normal MYLK expression. Because MYLK encodes an important kinase required for myosin activation and subsequent interaction with actin filaments, it is likely that in its absence, contraction of smooth muscle cells is impaired. The existence of a conditional-Mylk-knockout mouse model with severe gut dysmotility and abnormal function of the bladder supports the involvement of this gene in MMIHS pathogenesis. In aggregate, our findings implicate MYLK as a gene involved in the recessive form of MMIHS, confirming that this disease of the visceral organs is heterogeneous with a myopathic origin.
Keywords: Abnormalities, Multiple; Base Sequence; Colon; Female; Genes, Recessive; Homozygote; Humans; Intestinal Pseudo-Obstruction; Male; Mutation; Myosin-Light-Chain Kinase; Pedigree; Urinary Bladder

Metabolomics and cognition in African American adults in midlife: the atherosclerosis risk in communities study. - Bressler, J; Yu, B; Mosley, T H; Knopman, D S; Gottesman, R F; Alonso, A; Sharrett, A R; Wruck, L M; Eric Boerwinkle (Transl Psychiatry, 2017)
Clinical studies have shown alterations in metabolic profiles when patients with mild cognitive impairment and Alzheimer's disease dementia were compared to cognitively normal subjects. Associations between 204 serum metabolites measured at baseline (1987-1989) and cognitive change were investigated in 1035 middle-aged community-dwelling African American participants in the biracial Atherosclerosis Risk in Communities (ARIC) Study. Cognition was evaluated using the Delayed Word Recall Test (DWRT; verbal memory), the Digit Symbol Substitution Test (DSST; processing speed) and the Word Fluency Test (WFT; verbal fluency) at visits 2 (1990-1992) and 4 (1996-1998). In addition, Cox regression was used to analyze the metabolites as predictors of incident hospitalized dementia between baseline and 2011. There were 141 cases among 1534 participants over a median 17.1-year follow-up period. After adjustment for established risk factors, one standard deviation increase in N-acetyl-1-methylhistidine was significantly associated with greater 6-year change in DWRT scores (β=-0.66 words; P=3.65 × 10). Two metabolites (one unnamed and a long-chain omega-6 polyunsaturated fatty acid found in vegetable oils (docosapentaenoate (DPA, 22:5 n-6)) were significantly associated with less decline on the DSST (DPA: β=1.25 digit-symbol pairs, P=9.47 × 10). Two unnamed compounds and three sex steroid hormones were associated with an increased risk of dementia (all P<3.9 × 10). The association of 4-androstene-3beta, 17beta-diol disulfate 1 with dementia was replicated in European Americans. These results demonstrate that screening the metabolome in midlife can detect biologically plausible biomarkers that may improve risk stratification for cognitive impairment at older ages.
Keywords: Atherosclerosis; Black or African American; Black People; Cognition; Female; Humans; Longitudinal Studies; Male; Metabolomics; Middle Aged; Neuropsychological Tests; Prospective Studies; Risk Factors; White People

MicroRNAs in the miR-17 and miR-15 families are downregulated in chronic kidney disease with hypertension. - Nandakumar, Priyanka; Tin, Adrienne; Grove, Megan L; Ma, Jianzhong; Eric Boerwinkle; Coresh, Josef; Chakravarti, Aravinda (PLoS One, 2017)
BACKGROUND: In older adults (aged 70-74 years), African-Americans have 4-fold higher risk of developing hypertension-attributed end-stage renal disease (ESRD) than European-Americans. A hypothesized mechanism linking hypertension and progressive chronic kidney disease (CKD) is the innate immune response and inflammation. Persons with CKD are also more susceptible to infection. Gene expression in peripheral blood can provide a view of the innate immune activation profile. We aimed to identify differentially expressed genes, microRNAs, and pathways in peripheral blood between cases with CKD and high blood pressure under hypertension treatment versus controls without CKD and with controlled blood pressure in African Americans. METHODS: Case and control pairs (N = 15x2) were selected from those without diabetes and were matched for age, sex, body mass index, APOL1 risk allele count, and hypertension medication use. High blood pressure under hypertension treatment was defined as hypertension medication use and systolic blood pressure (SBP) ≥ 145 mmHg. CKD was defined as estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73m2. Cases were selected from those with CKD and high blood pressure under hypertension treatment, and controls were selected from those without CKD (eGFR: 75-120 mL/min/1.73m2 and urine albumin-to-creatinine ratio < 30mg/g) and with blood pressure controlled by hypertension medication use (SBP < 135 mmHg and D(diastolic)BP < 90 mm Hg). We perform RNA sequencing of mRNA and microRNA and conducted differential expression and co-expression network analysis. RESULTS: Of 347 miRNAs included in the analysis, 14 were significantly associated with case status (Benjamini-Hochberg adjusted p-value [BH p] < 0.05). Of these, ten were downregulated in cases: three of each belong to the miR-17 and miR-15 families. In co-expression network analysis of miRNA, one module, which included 13 of the 14 significant miRNAs, had significant association with case status. Of the 14,488 genes and 41,739 transcripts included in the analysis, none had significant association with case status. Gene co-expression network analyses did not yield any significant associations for mRNA. CONCLUSION: We have identified 14 differentially expressed miRNAs in the peripheral blood of CKD cases with high blood pressure under hypertension treatment as compared to appropriate controls. Most of the significant miRNAs were downregulated and have critical roles in immune cell functions. Future studies are needed to replicate our findings and determine whether the downregulation of these miRNAs in immune cells may influence CKD progression or complications.
Keywords: Down-Regulation; Female; Gene Expression Profiling; Gene Ontology; Gene Regulatory Networks; Humans; Hypertension; Male; MicroRNAs; Middle Aged; Renal Insufficiency, Chronic; RNA, Messenger; Sequence Analysis, RNA

is mutated in a distinct type of Usher syndrome. - Fu, Qing; Xu, Mingchu; Chen, Xue; Sheng, Xunlun; Yuan, Zhisheng; Liu, Yani; Li, Huajin; Sun, Zixi; Li, Huiping; Yang, Lizhu; Wang, Keqing; Zhang, Fangxia; et al. (J Med Genet, 2017)
BACKGROUND: Usher syndrome is a genetically heterogeneous disorder featured by combined visual impairment and hearing loss. Despite a dozen of genes involved in Usher syndrome having been identified, the genetic basis remains unknown in 20-30% of patients. In this study, we aimed to identify the novel disease-causing gene of a distinct subtype of Usher syndrome. METHODS: Ophthalmic examinations and hearing tests were performed on patients with Usher syndrome in two consanguineous families. Target capture sequencing was initially performed to screen causative mutations in known retinal disease-causing loci. Whole exome sequencing (WES) and whole genome sequencing (WGS) were applied for identifying novel disease-causing genes. RT-PCR and Sanger sequencing were performed to evaluate the splicing-altering effect of identified variants. RESULTS: Patients from the two independent families show a mild Usher syndrome phenotype featured by juvenile or adult-onset cone-rod dystrophy and sensorineural hearing loss. WES and WGS identified two homozygous rare variants that affect mRNA splicing of a ciliary gene . RT-PCR confirmed that the two variants indeed lead to abnormal splicing, resulting in premature stop of protein translation due to frameshift. CONCLUSIONS: Our results provide evidence that is a novel disease-causing gene for Usher syndrome, demonstrating an additional link between ciliopathy and Usher protein network in photoreceptor cells and inner ear hair cells.
Keywords: Adult; Cell Cycle Proteins; Child; Consanguinity; Exome; Female; Frameshift Mutation; Genome, Human; Hair Cells, Auditory, Inner; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Male; Pedigree; Retinitis Pigmentosa; Usher Syndromes

Mutations in EBF3 Disturb Transcriptional Profiles and Cause Intellectual Disability, Ataxia, and Facial Dysmorphism. - Harms, Frederike Leonie; Girisha, Katta M; Hardigan, Andrew A; Kortüm, Fanny; Shukla, Anju; Alawi, Malik; Dalal, Ashwin; Brady, Lauren; Tarnopolsky, Mark; Bird, Lynne M; Ceulemans, Sophia; Bebin, Martina; et al. (Am J Hum Genet, 2017)
From a GeneMatcher-enabled international collaboration, we identified ten individuals affected by intellectual disability, speech delay, ataxia, and facial dysmorphism and carrying a deleterious EBF3 variant detected by whole-exome sequencing. One 9-bp duplication and one splice-site, five missense, and two nonsense variants in EBF3 were found; the mutations occurred de novo in eight individuals, and the missense variant c.625C>T (p.Arg209Trp) was inherited by two affected siblings from their healthy mother, who is mosaic. EBF3 belongs to the early B cell factor family (also known as Olf, COE, or O/E) and is a transcription factor involved in neuronal differentiation and maturation. Structural assessment predicted that the five amino acid substitutions have damaging effects on DNA binding of EBF3. Transient expression of EBF3 mutant proteins in HEK293T cells revealed mislocalization of all but one mutant in the cytoplasm, as well as nuclear localization. By transactivation assays, all EBF3 mutants showed significantly reduced or no ability to activate transcription of the reporter gene CDKN1A, and in situ subcellular fractionation experiments demonstrated that EBF3 mutant proteins were less tightly associated with chromatin. Finally, in RNA-seq and ChIP-seq experiments, EBF3 acted as a transcriptional regulator, and mutant EBF3 had reduced genome-wide DNA binding and gene-regulatory activity. Our findings demonstrate that variants disrupting EBF3-mediated transcriptional regulation cause intellectual disability and developmental delay and are present in ∼0.1% of individuals with unexplained neurodevelopmental disorders.
Keywords: Adolescent; Adult; Amino Acid Substitution; Ataxia; Child; Child, Preschool; Chromatin; Cyclin-Dependent Kinase Inhibitor p21; Developmental Disabilities; Exome; Face; Female; Gene Expression Regulation; Genes, Reporter; HEK293 Cells; Humans; Intellectual Disability; Language Development Disorders; Male; Models, Molecular; Mosaicism; Mutation; Neurodevelopmental Disorders; Protein Transport; Syndrome; Transcription Factors; Transcription, Genetic

Mutations in the Spliceosome Component CWC27 Cause Retinal Degeneration with or without Additional Developmental Anomalies. - Xu, Mingchu; Xie, Yajing Angela; Abouzeid, Hana; Gordon, Christopher T; Fiorentino, Alessia; Sun, Zixi; Lehman, Anna; Osman, Ihab S; Dharmat, Rachayata; Riveiro-Álvarez, Rosa; Bapst-Wicht, Linda; Babino, Darwin; et al. (Am J Hum Genet, 2017)
Pre-mRNA splicing factors play a fundamental role in regulating transcript diversity both temporally and spatially. Genetic defects in several spliceosome components have been linked to a set of non-overlapping spliceosomopathy phenotypes in humans, among which skeletal developmental defects and non-syndromic retinitis pigmentosa (RP) are frequent findings. Here we report that defects in spliceosome-associated protein CWC27 are associated with a spectrum of disease phenotypes ranging from isolated RP to severe syndromic forms. By whole-exome sequencing, recessive protein-truncating mutations in CWC27 were found in seven unrelated families that show a range of clinical phenotypes, including retinal degeneration, brachydactyly, craniofacial abnormalities, short stature, and neurological defects. Remarkably, variable expressivity of the human phenotype can be recapitulated in Cwc27 mutant mouse models, with significant embryonic lethality and severe phenotypes in the complete knockout mice while mice with a partial loss-of-function allele mimic the isolated retinal degeneration phenotype. Our study describes a retinal dystrophy-related phenotype spectrum as well as its genetic etiology and highlights the complexity of the spliceosomal gene network.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Child; Child, Preschool; Cyclophilins; Female; Humans; Male; Mice; Mutation; Pedigree; Peptidylprolyl Isomerase; Retinal Degeneration; Young Adult

Neonatal fractures as a presenting feature of LMOD3-associated congenital myopathy. - Abbott, Megan; Jain, Mahim; Pferdehirt, Rachel; Chen, Yuqing; Tran, Alyssa; Duz, Mehmet B; Seven, Mehmet; Richard A Gibbs; Donna M Muzny; Lee, Brendan; Marom, Ronit; Burrage, Lindsay C (Am J Med Genet A, 2017)
Nemaline myopathy is a rare inherited disorder characterized by weakness, hypotonia, and depressed deep tendon reflexes. It is clinically and genetically heterogeneous, with the most severe phenotype presenting as perinatal akinesia, severe muscle weakness, feeding difficulties and respiratory failure, leading to early mortality. Pathogenic variants in 12 genes, encoding components of the sarcomere or factors related to myogenesis, have been reported in patients affected with the disorder. Here, we describe an early, lethal presentation of decreased fetal movements, hypotonia, muscle weakness, and neonatal respiratory failure requiring ventilator support in three siblings from a consanguineous family. All exhibited perinatal fractures, and thus, a skeletal dysplasia was considered as possibly contributing to the phenotype. However, whole exome sequencing revealed a homozygous, loss-of-function pathogenic variant in LMOD3, which has recently been associated with nemaline myopathy and, in a subset of patients, perinatal fractures. This case demonstrates the importance of considering congenital neuromuscular disorders in the differential diagnosis of perinatal fractures.
Keywords: Female; Fractures, Bone; Homozygote; Humans; Infant, Newborn; Male; Microfilament Proteins; Muscle Proteins; Mutation; Myopathies, Structural, Congenital; Pedigree

Non-malignant respiratory epithelial cells preferentially proliferate from resected non-small cell lung cancer specimens cultured under conditionally reprogrammed conditions. - Gao, Boning; Huang, Chunxian; Kernstine, Kemp; Pelekanou, Vasiliki; Kluger, Yuval; Jiang, Tingting; Peters-Hall, Jennifer R; Coquelin, Melissa; Girard, Luc; Zhang, Wei; Huffman, Kenneth; Oliver, Dwight; et al. (Oncotarget, 2017)
The "conditionally reprogrammed cells" (CRC) method, using a Rho kinase inhibitor and irradiated mouse fibroblast cells has been described for the efficient growth of cells from malignant and non-malignant samples from primary tumor and non-malignant sites. Using the CRC method, four institutions independently cultured tumor tissues from 48 non-small cell lung cancers (NSCLC, mostly from primary resected tumors) and 22 non-malignant lungs. We found that epithelial cells could be cultured from tumor and non-malignant lung. However, epithelial cells cultured from tumors had features of non-malignant respiratory epithelial cells which include: 1) among 22 mutations found in the original tumors only two mutations were found in the CRC cultures with reduced frequency (31% to 13% and 92% to 15% from original tumor and CRC culture respectively); 2) copy number variation was analyzed in 9 tumor and their CRC cultures and only diploid patterns were found in CRC cultures; 3) mRNA expression profiles were similar to those of normal respiratory epithelial cells; and 4) co-culture of tumor and non-malignant lung epithelial cells resulted in mostly non-malignant cells. We conclude that CRC method is a highly selective and useful method for the growth of non-malignant respiratory epithelial cells from tumor specimens and only occasionally do such CRC cultures contain a small subpopulation of cancer cells marked by oncogenic mutations. While our findings are restricted to resected primary NSCLC, they indicated the necessity to fully characterize all CRC cultures and the need to develop culture technology that facilitates the growth of primary lung cancers.
Keywords: A549 Cells; Adult; Aged; Aged, 80 and over; Base Sequence; Carcinoma, Non-Small-Cell Lung; Cell Line, Tumor; Cell Proliferation; Cells, Cultured; Coculture Techniques; DNA Copy Number Variations; DNA Mutational Analysis; Epithelial Cells; Female; Gene Expression Profiling; Genetic Predisposition to Disease; Humans; Lung Neoplasms; Male; Middle Aged; Mutation; Respiratory Mucosa; Tumor Cells, Cultured

An Organismal CNV Mutator Phenotype Restricted to Early Human Development. - Liu, Pengfei; Bo Yuan; Carvalho, Claudia M B; Wuster, Arthur; Walter, Klaudia; Zhang, Ling; Gambin, Tomasz; Chong, Zechen; Campbell, Ian M; Coban Akdemir, Zeynep; Gelowani, Violet; Writzl, Karin; et al. (Cell, 2017)
De novo copy number variants (dnCNVs) arising at multiple loci in a personal genome have usually been considered to reflect cancer somatic genomic instabilities. We describe a multiple dnCNV (MdnCNV) phenomenon in which individuals with genomic disorders carry five to ten constitutional dnCNVs. These CNVs originate from independent formation incidences, are predominantly tandem duplications or complex gains, exhibit breakpoint junction features reminiscent of replicative repair, and show increased de novo point mutations flanking the rearrangement junctions. The active CNV mutation shower appears to be restricted to a transient perizygotic period. We propose that a defect in the CNV formation process is responsible for the "CNV-mutator state," and this state is dampened after early embryogenesis. The constitutional MdnCNV phenomenon resembles chromosomal instability in various cancers. Investigations of this phenomenon may provide unique access to understanding genomic disorders, structural variant mutagenesis, human evolution, and cancer biology.
Keywords: Chromosome Aberrations; Chromosome Breakpoints; Chromosome Duplication; DNA Copy Number Variations; DNA Replication; Embryonic Development; Female; Gametogenesis; Genetic Diseases, Inborn; Genomic Instability; Humans; Male; Mutation

Phenotypic and molecular characterisation of CDK13-related congenital heart defects, dysmorphic facial features and intellectual developmental disorders. - Bostwick, Bret L; McLean, Scott; Posey, Jennifer E; Streff, Haley E; Gripp, Karen W; Blesson, Alyssa; Powell-Hamilton, Nina; Tusi, Jessica; Stevenson, David A; Farrelly, Ellyn; Hudgins, Louanne; Yang, Yaping; et al. (Genome Med, 2017)
BACKGROUND: De novo missense variants in CDK13 have been described as the cause of syndromic congenital heart defects in seven individuals ascertained from a large congenital cardiovascular malformations cohort. We aimed to further define the phenotypic and molecular spectrum of this newly described disorder. METHODS: To minimise ascertainment bias, we recruited nine additional individuals with CDK13 pathogenic variants from clinical and research exome laboratory sequencing cohorts. Each individual underwent dysmorphology exam and comprehensive medical history review. RESULTS: We demonstrate greater than expected phenotypic heterogeneity, including 33% (3/9) of individuals without structural heart disease on echocardiogram. There was a high penetrance for a unique constellation of facial dysmorphism and global developmental delay, as well as less frequently seen renal and sacral anomalies. Two individuals had novel CDK13 variants (p.Asn842Asp, p.Lys734Glu), while the remaining seven unrelated individuals had a recurrent, previously published p.Asn842Ser variant. Summary of all variants published to date demonstrates apparent restriction of pathogenic variants to the protein kinase domain with clustering in the ATP and magnesium binding sites. CONCLUSIONS: Here we provide detailed phenotypic and molecular characterisation of individuals with pathogenic variants in CDK13 and propose management guidelines based upon the estimated prevalence of anomalies identified.
Keywords: Adolescent; Adult; CDC2 Protein Kinase; Child; Child, Preschool; Face; Female; Heart Defects, Congenital; Humans; Infant; Intellectual Disability; Male; Mutation; Phenotype; Syndrome

Primary immunodeficiency diseases: Genomic approaches delineate heterogeneous Mendelian disorders. - Stray-Pedersen, Asbjørg; Sorte, Hanne Sørmo; Samarakoon, Pubudu; Gambin, Tomasz; Chinn, Ivan K; Coban Akdemir, Zeynep H; Erichsen, Hans Christian; Forbes, Lisa R; Gu, Shen; Bo Yuan; Jhangiani, Shalini N; Donna M Muzny; et al. (J Allergy Clin Immunol, 2017)
BACKGROUND: Primary immunodeficiency diseases (PIDDs) are clinically and genetically heterogeneous disorders thus far associated with mutations in more than 300 genes. The clinical phenotypes derived from distinct genotypes can overlap. Genetic etiology can be a prognostic indicator of disease severity and can influence treatment decisions. OBJECTIVE: We sought to investigate the ability of whole-exome screening methods to detect disease-causing variants in patients with PIDDs. METHODS: Patients with PIDDs from 278 families from 22 countries were investigated by using whole-exome sequencing. Computational copy number variant (CNV) prediction pipelines and an exome-tiling chromosomal microarray were also applied to identify intragenic CNVs. Analytic approaches initially focused on 475 known or candidate PIDD genes but were nonexclusive and further tailored based on clinical data, family history, and immunophenotyping. RESULTS: A likely molecular diagnosis was achieved in 110 (40%) unrelated probands. Clinical diagnosis was revised in about half (60/110) and management was directly altered in nearly a quarter (26/110) of families based on molecular findings. Twelve PIDD-causing CNVs were detected, including 7 smaller than 30 Kb that would not have been detected with conventional diagnostic CNV arrays. CONCLUSION: This high-throughput genomic approach enabled detection of disease-related variants in unexpected genes; permitted detection of low-grade constitutional, somatic, and revertant mosaicism; and provided evidence of a mutational burden in mixed PIDD immunophenotypes.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; DNA Copy Number Variations; Female; Genomics; High-Throughput Nucleotide Sequencing; Humans; Immunologic Deficiency Syndromes; Infant; Male; Middle Aged; Young Adult

An Promoter Polymorphism Associated With Elevated N-Terminal pro-B-Type Natriuretic Peptide and Lower Blood Pressure, Hypertension, and Mortality. - Seidelmann, Sara B; Vardeny, Orly; Claggett, Brian; Yu, Bing; Shah, Amil M; Ballantyne, Christie M; Selvin, Elizabeth; MacRae, Calum A; Eric Boerwinkle; Solomon, Scott D (J Am Heart Assoc, 2017)
BACKGROUND: Elevated B-type natriuretic peptide (BNP) levels are associated with heart failure and increased mortality in the general population. We investigated rs198389, a functional variant in the promoter region of the BNP gene (), in patients from the Atherosclerosis Risk in Communities Study to investigate associations with N-terminal pro-BNP (NT-proBNP) levels and outcomes. METHODS AND RESULTS: A total of 11 361 black and white patients with rs198389 genotyping attended visit 1 (aged 45-64 years; 1987-1989), with follow-up visits occurring every 3 years (visit 2-visit 4, 1990-1999), followed by visit 5 (2011-2013). NT-proBNP levels were measured at visits 2, 4, and 5. At visit 2, the GG genotype (frequency 18%) was associated with a 41% higher mean plasma level of NT-proBNP compared with the AA genotype (frequency 34%), with intermediate values observed in AGs (=4.2×10). The GG genotype was associated with reduced systolic blood pressure (-1.6 mm Hg, =0.006), diastolic blood pressure (-1 mm Hg, =0.003), antihypertension medication use (odds ratio, 0.85; 95% CI, 0.74-0.97 [=0.02]), and hypertension (odds ratio, 0.81; 95% CI, 0.72-0.92 [=0.002]) compared with the AA genotype with intermediate values in AGs. These relationships persisted throughout subsequent visits. After a median follow-up of 23 years, there were 4031 deaths. With and without covariate adjustment, the GG genotype was associated with modestly lower mortality (hazard ratio, 0.86; 95% CI, 0.78-0.95), primarily reflective of cardiovascular death (hazard ratio, 0.75; 95% CI, 0.61-0.92), and increased residual lifespan of 8 months from 50 years of age (=0.02) versus AAs. CONCLUSIONS: The rs198389 G allele in the promoter is associated with elevated levels of NT-proBNP throughout adult life, reduced blood pressure, hypertension and cardiovascular mortality, and increased lifespan.
Keywords: Black or African American; Blood Pressure; Chi-Square Distribution; Female; Genetic Predisposition to Disease; Humans; Hypertension; Kaplan-Meier Estimate; Linear Models; Longevity; Male; Middle Aged; Natriuretic Peptide, Brain; Odds Ratio; Peptide Fragments; Phenotype; Polymorphism, Single Nucleotide; Predictive Value of Tests; Promoter Regions, Genetic; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States; Up-Regulation; White People

PRUNE is crucial for normal brain development and mutated in microcephaly with neurodevelopmental impairment. - Zollo, Massimo; Ahmed, Mustafa; Ferrucci, Veronica; Salpietro, Vincenzo; Asadzadeh, Fatemeh; Carotenuto, Marianeve; Maroofian, Reza; Al-Amri, Ahmed; Singh, Royana; Scognamiglio, Iolanda; Mojarrad, Majid; Musella, Luca; et al. (Brain, 2017)
PRUNE is a member of the DHH (Asp-His-His) phosphoesterase protein superfamily of molecules important for cell motility, and implicated in cancer progression. Here we investigated multiple families from Oman, India, Iran and Italy with individuals affected by a new autosomal recessive neurodevelopmental and degenerative disorder in which the cardinal features include primary microcephaly and profound global developmental delay. Our genetic studies identified biallelic mutations of PRUNE1 as responsible. Our functional assays of disease-associated variant alleles revealed impaired microtubule polymerization, as well as cell migration and proliferation properties, of mutant PRUNE. Additionally, our studies also highlight a potential new role for PRUNE during microtubule polymerization, which is essential for the cytoskeletal rearrangements that occur during cellular division and proliferation. Together these studies define PRUNE as a molecule fundamental for normal human cortical development and define cellular and clinical consequences associated with PRUNE mutation.
Keywords: Adolescent; Brain; Carrier Proteins; Cell Differentiation; Cell Movement; Cerebral Cortex; Child; Child, Preschool; Cytoskeleton; Developmental Disabilities; Female; Genes, Recessive; Heredodegenerative Disorders, Nervous System; Humans; Infant; Male; Microcephaly; Microtubules; Mutation; Pedigree; Phosphoric Monoester Hydrolases; Young Adult

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

A Recurrent De Novo Variant in NACC1 Causes a Syndrome Characterized by Infantile Epilepsy, Cataracts, and Profound Developmental Delay. - Schoch, Kelly; Meng, Linyan; Szelinger, Szabolcs; Bearden, David R; Stray-Pedersen, Asbjorg; Busk, Oyvind L; Stong, Nicholas; Liston, Eriskay; Cohn, Ronald D; Scaglia, Fernando; Rosenfeld, Jill A; Tarpinian, Jennifer; et al. (Am J Hum Genet, 2017)
Whole-exome sequencing (WES) has increasingly enabled new pathogenic gene variant identification for undiagnosed neurodevelopmental disorders and provided insights into both gene function and disease biology. Here, we describe seven children with a neurodevelopmental disorder characterized by microcephaly, profound developmental delays and/or intellectual disability, cataracts, severe epilepsy including infantile spasms, irritability, failure to thrive, and stereotypic hand movements. Brain imaging in these individuals reveals delay in myelination and cerebral atrophy. We observe an identical recurrent de novo heterozygous c.892C>T (p.Arg298Trp) variant in the nucleus accumbens associated 1 (NACC1) gene in seven affected individuals. One of the seven individuals is mosaic for this variant. NACC1 encodes a transcriptional repressor implicated in gene expression and has not previously been associated with germline disorders. The probability of finding the same missense NACC1 variant by chance in 7 out of 17,228 individuals who underwent WES for diagnoses of neurodevelopmental phenotypes is extremely small and achieves genome-wide significance (p = 1.25 × 10). Selective constraint against missense variants in NACC1 makes this excess of an identical missense variant in all seven individuals more remarkable. Our findings are consistent with a germline recurrent mutational hotspot associated with an allele-specific neurodevelopmental phenotype in NACC1.
Keywords: Alleles; Amino Acid Sequence; Brain; Cataract; Child; Child, Preschool; Female; Genetic Variation; Genome-Wide Association Study; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Microcephaly; Mutation, Missense; Neoplasm Proteins; Pedigree; Phenotype; Repressor Proteins; Spasms, Infantile

REST Final-Exon-Truncating Mutations Cause Hereditary Gingival Fibromatosis. - Bayram, Yavuz; White, Janson J; Elcioglu, Nursel; Cho, Megan T; Zadeh, Neda; Gedikbasi, Asuman; Palanduz, Sukru; Ozturk, Sukru; Cefle, Kivanc; Kasapcopur, Ozgur; Coban Akdemir, Zeynep; Pehlivan, Davut; et al. (Am J Hum Genet, 2017)
Hereditary gingival fibromatosis (HGF) is the most common genetic form of gingival fibromatosis that develops as a slowly progressive, benign, localized or generalized enlargement of keratinized gingiva. HGF is a genetically heterogeneous disorder and can be transmitted either as an autosomal-dominant or autosomal-recessive trait or appear sporadically. To date, four loci (2p22.1, 2p23.3-p22.3, 5q13-q22, and 11p15) have been mapped to autosomes and one gene (SOS1) has been associated with the HGF trait observed to segregate in a dominant inheritance pattern. Here we report 11 individuals with HGF from three unrelated families. Whole-exome sequencing (WES) revealed three different truncating mutations including two frameshifts and one nonsense variant in RE1-silencing transcription factor (REST) in the probands from all families and further genetic and genomic analyses confirmed the WES-identified findings. REST is a transcriptional repressor that is expressed throughout the body; it has different roles in different cellular contexts, such as oncogenic and tumor-suppressor functions and hematopoietic and cardiac differentiation. Here we show the consequences of germline final-exon-truncating mutations in REST for organismal development and the association with the HGF phenotype.
Keywords: Adolescent; Base Sequence; Chromosome Segregation; Exons; Family; Female; Fibromatosis, Gingival; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Pedigree; Repressor Proteins

Unraveling genetic predisposition to familial or early onset gastric cancer using germline whole-exome sequencing. - Vogelaar, Ingrid P; van der Post, Rachel S; van Krieken, J Han Jm; Spruijt, Liesbeth; van Zelst-Stams, Wendy Ag; Kets, C Marleen; Lubinski, Jan; Jakubowska, Anna; Teodorczyk, Urszula; Aalfs, Cora M; van Hest, Liselotte P; Pinheiro, Hugo; et al. (Eur J Hum Genet, 2017)
Recognition of individuals with a genetic predisposition to gastric cancer (GC) enables preventive measures. However, the underlying cause of genetic susceptibility to gastric cancer remains largely unexplained. We performed germline whole-exome sequencing on leukocyte DNA of 54 patients from 53 families with genetically unexplained diffuse-type and intestinal-type GC to identify novel GC-predisposing candidate genes. As young age at diagnosis and familial clustering are hallmarks of genetic tumor susceptibility, we selected patients that were diagnosed below the age of 35, patients from families with two cases of GC at or below age 60 and patients from families with three GC cases at or below age 70. All included individuals were tested negative for germline CDH1 mutations before or during the study. Variants that were possibly deleterious according to in silico predictions were filtered using several independent approaches that were based on gene function and gene mutation burden in controls. Despite a rigorous search, no obvious candidate GC predisposition genes were identified. This negative result stresses the importance of future research studies in large, homogeneous cohorts.
Keywords: Adult; Aged; Antigens, CD; Cadherins; Early Detection of Cancer; Exome; Female; Genetic Predisposition to Disease; Genetic Testing; Germ-Line Mutation; Humans; Male; Middle Aged; Sequence Analysis, DNA; Stomach Neoplasms

Variants in SKP1, PROB1, and IL17B genes at keratoconus 5q31.1-q35.3 susceptibility locus identified by whole-exome sequencing. - Karolak, Justyna A; Gambin, Tomasz; Pitarque, Jose A; Molinari, Andrea; Jhangiani, Shalini; Stankiewicz, Pawel; Lupski, James R; Gajecka, Marzena (Eur J Hum Genet, 2017)
Keratoconus (KTCN) is a protrusion and thinning of the cornea, resulting in impairment of visual function. The extreme genetic heterogeneity makes it difficult to discover factors unambiguously influencing the KTCN phenotype. In this study, we used whole-exome sequencing (WES) and Sanger sequencing to reduce the number of candidate genes at the 5q31.1-q35.3 locus and to prioritize other potentially relevant variants in an Ecuadorian family with KTCN. We applied WES in two affected KTCN individuals from the Ecuadorian family that showed a suggestive linkage between the KTCN phenotype and the 5q31.1-q35.3 locus. Putative variants identified by WES were further evaluated in this family using Sanger sequencing. Exome capture discovered a total of 173 rare (minor allele frequency <0.001 in control population) nonsynonymous variants in both affected individuals. Among them, 16 SNVs were selected for further evaluation. Segregation analysis revealed that variants c.475T>G in SKP1, c.671G>A in PROB1, and c.527G>A in IL17B in the 5q31.1-q35.3 linkage region, and c.850G>A in HKDC1 in the 10q22 locus completely segregated with the phenotype in the studied KTCN family. We demonstrate that a combination of various techniques significantly narrowed the studied genomic region and reduced the list of the putative exonic variants. Moreover, since this locus overlapped two other chromosomal regions previously recognized in distinct KTCN studies, our findings suggest that this 5q31.1-q35.3 locus might be linked with KTCN.
Keywords: Chromosomes, Human, Pair 5; Exome; Female; Gene Frequency; Genetic Linkage; Genetic Predisposition to Disease; Genome, Human; Hexokinase; High-Throughput Nucleotide Sequencing; Humans; Interleukin-17; Keratoconus; Male; Pedigree; Phenotype; Proteins; S-Phase Kinase-Associated Proteins

Whole exome sequence-based association analyses of plasma amyloid-β in African and European Americans; the Atherosclerosis Risk in Communities-Neurocognitive Study. - Simino, Jeannette; Wang, Zhiying; Bressler, Jan; Chouraki, Vincent; Yang, Qiong; Younkin, Steven G; Seshadri, Sudha; Fornage, Myriam; Eric Boerwinkle; Mosley, Thomas H (PLoS One, 2017)
OBJECTIVE: We performed single-variant and gene-based association analyses of plasma amyloid-β (aβ) concentrations using whole exome sequence from 1,414 African and European Americans. Our goal was to identify genes that influence plasma aβ42 concentrations and aβ42:aβ40 ratios in late middle age (mean = 59 years), old age (mean = 77 years), or change over time (mean = 18 years). METHODS: Plasma aβ measures were linearly regressed onto age, gender, APOE ε4 carrier status, and time elapsed between visits (fold-changes only) separately by race. Following inverse normal transformation of the residuals, seqMeta was used to conduct race-specific single-variant and gene-based association tests while adjusting for population structure. Linear regression models were fit on autosomal variants with minor allele frequencies (MAF)≥1%. T5 burden and Sequence Kernel Association (SKAT) gene-based tests assessed functional variants with MAF≤5%. Cross-race fixed effects meta-analyses were Bonferroni-corrected for the number of variants or genes tested. RESULTS: Seven genes were associated with aβ in late middle age or change over time; no associations were identified in old age. Single variants in KLKB1 (rs3733402; p = 4.33x10-10) and F12 (rs1801020; p = 3.89x10-8) were significantly associated with midlife aβ42 levels through cross-race meta-analysis; the KLKB1 variant replicated internally using 1,014 additional participants with exome chip. ITPRIP, PLIN2, and TSPAN18 were associated with the midlife aβ42:aβ40 ratio via the T5 test; TSPAN18 was significant via the cross-race meta-analysis, whereas ITPRIP and PLIN2 were European American-specific. NCOA1 and NT5C3B were associated with the midlife aβ42:aβ40 ratio and the fold-change in aβ42, respectively, via SKAT in African Americans. No associations replicated externally (N = 725). CONCLUSION: We discovered age-dependent genetic effects, established associations between vascular-related genes (KLKB1, F12, PLIN2) and midlife plasma aβ levels, and identified a plausible Alzheimer's Disease candidate gene (ITPRIP) influencing cell death. Plasma aβ concentrations may have dynamic biological determinants across the lifespan; plasma aβ study designs or analyses must consider age.
Keywords: Aged; Amyloid beta-Peptides; Black or African American; Exome; Female; Gene Regulatory Networks; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; United States; White People

Whole exome sequencing in 342 congenital cardiac left sided lesion cases reveals extensive genetic heterogeneity and complex inheritance patterns. - Li, Alexander H; Hanchard, Neil A; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid; Nicosia, Annarita; Rosenfeld, Jill; Donna M Muzny; D'Alessandro, Lisa C A; Morris, Shaine; Jhangiani, Shalini; Parekh, Dhaval R; et al. (Genome Med, 2017)
BACKGROUND: Left-sided lesions (LSLs) account for an important fraction of severe congenital cardiovascular malformations (CVMs). The genetic contributions to LSLs are complex, and the mutations that cause these malformations span several diverse biological signaling pathways: TGFB, NOTCH, SHH, and more. Here, we use whole exome sequence data generated in 342 LSL cases to identify likely damaging variants in putative candidate CVM genes. METHODS: Using a series of bioinformatics filters, we focused on genes harboring population-rare, putative loss-of-function (LOF), and predicted damaging variants in 1760 CVM candidate genes constructed a priori from the literature and model organism databases. Gene variants that were not observed in a comparably sequenced control dataset of 5492 samples without severe CVM were then subjected to targeted validation in cases and parents. Whole exome sequencing data from 4593 individuals referred for clinical sequencing were used to bolster evidence for the role of candidate genes in CVMs and LSLs. RESULTS: Our analyses revealed 28 candidate variants in 27 genes, including 17 genes not previously associated with a human CVM disorder, and revealed diverse patterns of inheritance among LOF carriers, including 9 confirmed de novo variants in both novel and newly described human CVM candidate genes (ACVR1, JARID2, NR2F2, PLRG1, SMURF1) as well as established syndromic CVM genes (KMT2D, NF1, TBX20, ZEB2). We also identified two genes (DNAH5, OFD1) with evidence of recessive and hemizygous inheritance patterns, respectively. Within our clinical cohort, we also observed heterozygous LOF variants in JARID2 and SMAD1 in individuals with cardiac phenotypes, and collectively, carriers of LOF variants in our candidate genes had a four times higher odds of having CVM (odds ratio = 4.0, 95% confidence interval 2.5-6.5). CONCLUSIONS: Our analytical strategy highlights the utility of bioinformatic resources, including human disease records and model organism phenotyping, in novel gene discovery for rare human disease. The results underscore the extensive genetic heterogeneity underlying non-syndromic LSLs, and posit potential novel candidate genes and complex modes of inheritance in this important group of birth defects.
Keywords: Exome Sequencing; Female; Genetic Heterogeneity; Heart Defects, Congenital; Humans; Inheritance Patterns; Male

Whole Transcriptome Sequencing Analyses Reveal Molecular Markers of Blood Pressure Response to Thiazide Diuretics. - Sá, Ana Caroline C; Webb, Amy; Gong, Yan; McDonough, Caitrin W; Datta, Somnath; Langaee, Taimour Y; Turner, Stephen T; Beitelshees, Amber L; Chapman, Arlene B; Eric Boerwinkle; Gums, John G; Scherer, Steven E; et al. (Sci Rep, 2017)
Thiazide diuretics (TD) are commonly prescribed anti-hypertensives worldwide. However, <40% of patients treated with thiazide monotherapy achieve BP control. This study uses whole transcriptome sequencing to identify novel molecular markers associated with BP response to TD. We assessed global RNA expression levels in whole blood samples from 150 participants, representing patients in the upper and lower quartile of BP response to TD from the Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) (50 whites) and from PEAR-2 (50 whites and 50 blacks). In each study cohort, we performed poly-A RNA-sequencing in baseline samples from 25 responders and 25 non-responders to hydrochlorothiazide (HCTZ) or chlorthalidone. At FDR adjusted p-value < 0.05, 29 genes were differentially expressed in relation to HCTZ or chlorthalidone BP response in whites. For each differentially expressed gene, replication was attempted in the alternate white group and PEAR-2 blacks. CEBPD (meta-analysis p = 1.8 × 10) and TSC22D3 (p = 1.9 × 10) were differentially expressed in all 3 cohorts, and explain, in aggregate, 21.9% of response variability to TD. This is the first report of the use of transcriptome-wide sequencing data to identify molecular markers of antihypertensive drug response. These findings support CEBPD and TSC22D3 as potential biomarkers of BP response to TD.
Keywords: Alleles; Biomarkers; Blood Pressure; CCAAT-Enhancer-Binding Protein-delta; Chlorthalidone; Diuretics; Female; Gene Expression Profiling; Gene Expression Regulation; Humans; Hydrochlorothiazide; Logistic Models; Male; Middle Aged; Potassium; Reproducibility of Results; RNA, Messenger; ROC Curve; Transcription Factors; Uric Acid

Whole-exome sequencing in the molecular diagnosis of individuals with congenital anomalies of the kidney and urinary tract and identification of a new causative gene. - Bekheirnia, Mir Reza; Bekheirnia, Nasim; Bainbridge, Matthew N; Gu, Shen; Coban Akdemir, Zeynep Hande; Gambin, Tomek; Janzen, Nicolette K; Jhangiani, Shalini N; Donna M Muzny; Michael, Mini; Brewer, Eileen D; Elenberg, Ewa; et al. (Genet Med, 2017)
PURPOSE: To investigate the utility of whole-exome sequencing (WES) to define a molecular diagnosis for patients clinically diagnosed with congenital anomalies of kidney and urinary tract (CAKUT). METHODS: WES was performed in 62 families with CAKUT. WES data were analyzed for single-nucleotide variants (SNVs) in 35 known CAKUT genes, putatively deleterious sequence changes in new candidate genes, and potentially disease-associated copy-number variants (CNVs). RESULTS: In approximately 5% of families, pathogenic SNVs were identified in PAX2, HNF1B, and EYA1. Observed phenotypes in these families expand the current understanding about the role of these genes in CAKUT. Four pathogenic CNVs were also identified using two CNV detection tools. In addition, we found one deleterious de novo SNV in FOXP1 among the 62 families with CAKUT. The clinical database of the Baylor Miraca Genetics laboratory was queried and seven additional unrelated individuals with novel de novo SNVs in FOXP1 were identified. Six of these eight individuals with FOXP1 SNVs have syndromic urinary tract defects, implicating this gene in urinary tract development. CONCLUSION: We conclude that WES can be used to identify molecular etiology (SNVs, CNVs) in a subset of individuals with CAKUT. WES can also help identify novel CAKUT genes.Genet Med 19 4, 412-420.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Exome Sequencing; Female; Forkhead Transcription Factors; Genetic Predisposition to Disease; Hepatocyte Nuclear Factor 1-beta; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Nuclear Proteins; PAX2 Transcription Factor; Pedigree; Polymorphism, Single Nucleotide; Protein Tyrosine Phosphatases; Repressor Proteins; Urogenital Abnormalities; Vesico-Ureteral Reflux; Young Adult

Whole-genome landscape of pancreatic neuroendocrine tumours. - Scarpa, Aldo; Chang, David K; Nones, Katia; Corbo, Vincenzo; Patch, Ann-Marie; Bailey, Peter; Lawlor, Rita T; Johns, Amber L; Miller, David K; Mafficini, Andrea; Rusev, Borislav; Scardoni, Maria; et al. (Nature, 2017)
The diagnosis of pancreatic neuroendocrine tumours (PanNETs) is increasing owing to more sensitive detection methods, and this increase is creating challenges for clinical management. We performed whole-genome sequencing of 102 primary PanNETs and defined the genomic events that characterize their pathogenesis. Here we describe the mutational signatures they harbour, including a deficiency in G:C > T:A base excision repair due to inactivation of MUTYH, which encodes a DNA glycosylase. Clinically sporadic PanNETs contain a larger-than-expected proportion of germline mutations, including previously unreported mutations in the DNA repair genes MUTYH, CHEK2 and BRCA2. Together with mutations in MEN1 and VHL, these mutations occur in 17% of patients. Somatic mutations, including point mutations and gene fusions, were commonly found in genes involved in four main pathways: chromatin remodelling, DNA damage repair, activation of mTOR signalling (including previously undescribed EWSR1 gene fusions), and telomere maintenance. In addition, our gene expression analyses identified a subgroup of tumours associated with hypoxia and HIF signalling.
Keywords: Base Sequence; Calmodulin-Binding Proteins; Carcinoma, Neuroendocrine; Chromatin Assembly and Disassembly; Chromosome Aberrations; DNA Copy Number Variations; DNA Glycosylases; DNA Mutational Analysis; DNA Repair; Female; Genome, Human; Genomics; Germ-Line Mutation; Humans; Male; Pancreatic Neoplasms; RNA-Binding Protein EWS; RNA-Binding Proteins; Telomere; TOR Serine-Threonine Kinases

Whole-genome sequencing study of serum peptide levels: the Atherosclerosis Risk in Communities study. - de Vries, Paul S; Yu, Bing; Feofanova, Elena V; Ginger A Metcalf; Brown, Michael R; Zeighami, Atefeh L; Liu, Xiaoming; Donna M Muzny; Richard A Gibbs; Eric Boerwinkle; Morrison, Alanna C (Hum Mol Genet, 2017)
Oligopeptides are important markers of protein metabolism, as they are cleaved from larger polypeptides and proteins. Genetic association studies may help elucidate their origin and function. In 1,552 European Americans and 1,872 African Americans of the Atherosclerosis Risk in Communities study, we performed whole-genome and whole-exome sequencing and measured serum levels of 25 peptides. Common variants (minor allele frequency > 5%) were analysed individually. We grouped low-frequency variants (minor allele frequency ≤ 5%) by a genome-wide sliding window using region-based aggregate tests. Furthermore, low-frequency regulatory variants were grouped by gene, as were functional coding variants. All analyses were performed separately in each ancestry group and then meta-analysed. We identified 22 common variant associations with peptide levels (P-value < 4.2 × 10-10), including 16 novel gene-peptide pairs. Notably, variants in kinin-kallikrein genes KNG1, F12, KLKB1, and ACE were associated with several different peptides. Variants in KLKB1 and ACE were associated with a fragment of complement component 3f. Both common variants and low-frequency coding variants in CPN1 were associated with a fibrinogen cleavage peptide. Four sliding windows were significantly associated with peptide levels (P-value < 4.2 × 10-10). Our results highlight the importance of the kinin-kallikrein system in the regulation of serum peptide levels, strengthen the evidence for a broad link between the kinin-kallikrein and complement systems, and suggest a role of CPN1 in the conversion of fibrinogen to fibrin.
Keywords: Alleles; Atherosclerosis; Black or African American; Exome; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Kallikreins; Male; Middle Aged; Peptides; Polymorphism, Single Nucleotide; Proteins; Risk Factors; White People; Whole Genome Sequencing

ADIPOR1 Is Mutated in Syndromic Retinitis Pigmentosa. - Xu, Mingchu; Eblimit, Aiden; Wang, Jing; Li, Jianli; Wang, Feng; Zhao, Li; Wang, Xia; Xiao, Ningna; Yumei Li; Wong, Lee-Jun C; Lewis, Richard A; Rui Chen (Hum Mutat, 2016)
Retinitis pigmentosa (RP) is a genetically heterogeneous retinal disorder. Despite the numerous genes associated with RP already identified, the genetic basis remains unknown in a substantial number of patients and families. In this study, we performed whole-exome sequencing to investigate the molecular basis of a syndromic RP case that cannot be solved by mutations in known disease-causing genes. After applying a series of variant filtering strategies, we identified an apparently homozygous frameshift mutation, c.31delC (p.Q11Rfs*24) in the ADIPOR1 gene. The reported phenotypes of Adipor1-null mice contain retinal dystrophy, obesity, and behavioral abnormalities, which highly mimic those in the syndromic RP patient. We further confirmed ADIPOR1 retina expression by immunohistochemistry. Our results established ADIPOR1 as a novel disease-causing gene for syndromic RP and highlight the importance of fatty acid transport in the retina.
Keywords: Adult; Animals; Exome; Female; Frameshift Mutation; Humans; Male; Mice; Mutation; Receptors, Adiponectin; Retinitis Pigmentosa; Young Adult

Aggressive tumor growth and clinical evolution in a patient with X-linked acro-gigantism syndrome. - Naves, Luciana A; Daly, Adrian F; Dias, Luiz Augusto; Bo Yuan; Zakir, Juliano Coelho Oliveira; Barra, Gustavo Barcellos; Palmeira, Leonor; Villa, Chiara; Trivellin, Giampaolo; Júnior, Armindo Jreige; Neto, Florêncio Figueiredo Cavalcante; Liu, Pengfei; et al. (Endocrine, 2016)
X-linked acro-gigantism (X-LAG) syndrome is a newly described disease caused by microduplications on chromosome Xq26.3 leading to copy number gain of GPR101. We describe the clinical progress of a sporadic male X-LAG syndrome patient with an Xq26.3 microduplication, highlighting the aggressive natural history of pituitary tumor growth in the absence of treatment. The patient first presented elsewhere aged 5 years 8 months with a history of excessive growth for >2 years. His height was 163 cm, his weight was 36 kg, and he had markedly elevated GH and IGF-1. MRI showed a non-invasive sellar mass measuring 32.5 × 23.9 × 29.1 mm. Treatment was declined and the family was lost to follow-up. At the age of 10 years and 7 months, he presented again with headaches, seizures, and visual disturbance. His height had increased to 197 cm. MRI showed an invasive mass measuring 56.2 × 58.1 × 45.0 mm, with compression of optic chiasma, bilateral cavernous sinus invasion, and hydrocephalus. His thyrotrope, corticotrope, and gonadotrope axes were deficient. Surgery, somatostatin analogs, and cabergoline did not control vertical growth and pegvisomant was added, although vertical growth continues (currently 207 cm at 11 years 7 months of age). X-LAG syndrome is a new genomic disorder in which early-onset pituitary tumorigenesis can lead to marked overgrowth and gigantism. This case illustrates the aggressive nature of tumor evolution and the challenging clinical management in X-LAG syndrome.
Keywords: Adenoma; Child; Genetic Diseases, X-Linked; Gigantism; Humans; Male; Pituitary Neoplasms; Treatment Outcome

Altered neuronal network and rescue in a human MECP2 duplication model. - Nageshappa, S; Carromeu, C; Trujillo, C A; Mesci, P; Espuny-Camacho, I; Pasciuto, E; Vanderhaeghen, P; Verfaillie, C M; Raitano, S; Kumar, A; Carvalho, C M B; Bagni, C; et al. (Mol Psychiatry, 2016)
Increased dosage of methyl-CpG-binding protein-2 (MeCP2) results in a dramatic neurodevelopmental phenotype with onset at birth. We generated induced pluripotent stem cells (iPSCs) from patients with the MECP2 duplication syndrome (MECP2dup), carrying different duplication sizes, to study the impact of increased MeCP2 dosage in human neurons. We show that cortical neurons derived from these different MECP2dup iPSC lines have increased synaptogenesis and dendritic complexity. In addition, using multi-electrodes arrays, we show that neuronal network synchronization was altered in MECP2dup-derived neurons. Given MeCP2 functions at the epigenetic level, we tested whether these alterations were reversible using a library of compounds with defined activity on epigenetic pathways. One histone deacetylase inhibitor, NCH-51, was validated as a potential clinical candidate. Interestingly, this compound has never been considered before as a therapeutic alternative for neurological disorders. Our model recapitulates early stages of the human MECP2 duplication syndrome and represents a promising cellular tool to facilitate therapeutic drug screening for severe neurodevelopmental disorders.
Keywords: Cell Differentiation; Dendrites; Gene Dosage; Gene Duplication; Genetic Association Studies; Humans; Induced Pluripotent Stem Cells; Male; Methyl-CpG-Binding Protein 2; Nerve Net; Neurogenesis; Neurons

Alternative genetic mechanisms of BRAF activation in Langerhans cell histiocytosis. - Chakraborty, Rikhia; Burke, Thomas M; Hampton, Oliver A; Zinn, Daniel J; Lim, Karen Phaik Har; Abhyankar, Harshal; Scull, Brooks; Kumar, Vijetha; Kakkar, Nipun; Wheeler, David A; Roy, Angshumoy; Poulikakos, Poulikos I; et al. (Blood, 2016)
Langerhans cell histiocytosis (LCH) is characterized by inflammatory lesions containing pathologic CD207 dendritic cells with constitutively activated ERK. Mutually exclusive somatic mutations in MAPK pathway genes have been identified in ∼75% of LCH cases, including recurrent BRAF-V600E and MAP2K1 mutations. To elucidate mechanisms of ERK activation in the remaining 25% of patients, we performed whole-exome sequencing (WES, n = 6), targeted BRAF sequencing (n = 19), and/or whole-transcriptome sequencing (RNA-seq, n = 6) on 24 LCH patient samples lacking BRAF-V600E or MAP2K1 mutations. WES and BRAF sequencing identified in-frame BRAF deletions in the β3-αC loop in 6 lesions. RNA-seq revealed one case with an in-frame FAM73A-BRAF fusion lacking the BRAF autoinhibitory regulatory domain but retaining an intact kinase domain. High levels of phospho-ERK were detected in vitro in cells overexpressing either BRAF fusion or deletion constructs and ex vivo in CD207 cells from lesions. ERK activation was resistant to BRAF-V600E inhibition, but responsive to both a second-generation BRAF inhibitor and a MEK inhibitor. These results support an emerging model of universal ERK-activating genetic alterations driving pathogenesis in LCH. A personalized approach in which patient-specific alterations are identified may be necessary to maximize benefit from targeted therapies for patients with LCH.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; Enzyme Activation; Female; Histiocytosis, Langerhans-Cell; Humans; Infant; Male; Mutation; Oncogene Proteins, Fusion; Protein Domains; Proto-Oncogene Proteins B-raf

Association of MTOR Mutations With Developmental Brain Disorders, Including Megalencephaly, Focal Cortical Dysplasia, and Pigmentary Mosaicism. - Mirzaa, Ghayda M; Campbell, Catarina D; Solovieff, Nadia; Goold, Carleton; Jansen, Laura A; Menon, Suchithra; Timms, Andrew E; Conti, Valerio; Biag, Jonathan D; Adams, Carissa; Boyle, Evan August; Collins, Sarah; et al. (JAMA Neurol, 2016)
IMPORTANCE: Focal cortical dysplasia (FCD), hemimegalencephaly, and megalencephaly constitute a spectrum of malformations of cortical development with shared neuropathologic features. These disorders are associated with significant childhood morbidity and mortality. OBJECTIVE: To identify the underlying molecular cause of FCD, hemimegalencephaly, and diffuse megalencephaly. DESIGN, SETTING, AND PARTICIPANTS: Patients with FCD, hemimegalencephaly, or megalencephaly (mean age, 11.7 years; range, 2-32 years) were recruited from Pediatric Hospital A. Meyer, the University of Hong Kong, and Seattle Children's Research Institute from June 2012 to June 2014. Whole-exome sequencing (WES) was performed on 8 children with FCD or hemimegalencephaly using standard-depth (50-60X) sequencing in peripheral samples (blood, saliva, or skin) from the affected child and their parents and deep (150-180X) sequencing in affected brain tissue. Targeted sequencing and WES were used to screen 93 children with molecularly unexplained diffuse or focal brain overgrowth. Histopathologic and functional assays of phosphatidylinositol 3-kinase-AKT (serine/threonine kinase)-mammalian target of rapamycin (mTOR) pathway activity in resected brain tissue and cultured neurons were performed to validate mutations. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing and targeted sequencing identified variants associated with this spectrum of developmental brain disorders. RESULTS: Low-level mosaic mutations of MTOR were identified in brain tissue in 4 children with FCD type 2a with alternative allele fractions ranging from 0.012 to 0.086. Intermediate-level mosaic mutation of MTOR (p.Thr1977Ile) was also identified in 3 unrelated children with diffuse megalencephaly and pigmentary mosaicism in skin. Finally, a constitutional de novo mutation of MTOR (p.Glu1799Lys) was identified in 3 unrelated children with diffuse megalencephaly and intellectual disability. Molecular and functional analysis in 2 children with FCD2a from whom multiple affected brain tissue samples were available revealed a mutation gradient with an epicenter in the most epileptogenic area. When expressed in cultured neurons, all MTOR mutations identified here drive constitutive activation of mTOR complex 1 and enlarged neuronal size. CONCLUSIONS AND RELEVANCE: In this study, mutations of MTOR were associated with a spectrum of brain overgrowth phenotypes extending from FCD type 2a to diffuse megalencephaly, distinguished by different mutations and levels of mosaicism. These mutations may be sufficient to cause cellular hypertrophy in cultured neurons and may provide a demonstration of the pattern of mosaicism in brain and substantiate the link between mosaic mutations of MTOR and pigmentary mosaicism in skin.
Keywords: Adolescent; Adult; Amino Acids; Animals; Cells, Cultured; Cerebral Cortex; Child; Child, Preschool; Developmental Disabilities; Embryo, Mammalian; Female; Gene Expression Regulation; Genetic Association Studies; Humans; Intercellular Signaling Peptides and Proteins; Male; Malformations of Cortical Development; Mechanistic Target of Rapamycin Complex 1; Megalencephaly; Mosaicism; Multiprotein Complexes; Mutation; Nerve Tissue Proteins; Neurons; Rats; Retrospective Studies; TOR Serine-Threonine Kinases; Young Adult

Association of the IGF1 gene with fasting insulin levels. - Willems, Sara M; Cornes, Belinda K; Brody, Jennifer A; Morrison, Alanna C; Lipovich, Leonard; Dauriz, Marco; Chen, Yuning; Liu, Ching-Ti; Rybin, Denis V; Richard A Gibbs; Donna M Muzny; Pankow, James S; et al. (Eur J Hum Genet, 2016)
Insulin-like growth factor 1 (IGF-I) has been associated with insulin resistance. Genome-wide association studies (GWASs) of fasting insulin (FI) identified single-nucleotide variants (SNVs) near the IGF1 gene, raising two hypotheses: (1) these associations are mediated by IGF-I levels and (2) these noncoding variants either tag other functional variants in the region or are directly functional. In our study, analyses including 5141 individuals from population-based cohorts suggest that FI associations near IGF1 are not mediated by IGF-I. Analyses of targeted sequencing data in 3539 individuals reveal a large number of novel rare variants at the IGF1 locus and show a FI association with a subset of rare nonsynonymous variants (PSKAT=5.7 × 10(-4)). Conditional analyses suggest that this association is partly explained by the GWAS signal and the presence of a residual independent rare variant effect (Pconditional=0.019). Annotation using ENCODE data suggests that the GWAS variants may have a direct functional role in insulin biology. In conclusion, our study provides insight into variation present at the IGF1 locus and into the genetic architecture underlying FI levels, suggesting that FI associations of SNVs near IGF1 are not mediated by IGF-I and suggesting a role for both rare nonsynonymous and common functional variants in insulin biology.
Keywords: Adult; Aged; Fasting; Female; Humans; Insulin; Insulin-Like Growth Factor I; Male; Middle Aged; Polymorphism, Single Nucleotide

Avirulence gene mapping in the Hessian fly (Mayetiola destructor) reveals a protein phosphatase 2C effector gene family. - Zhao, Chaoyang; Shukle, Richard; Navarro-Escalante, Lucio; Chen, Mingshun; Richards, Stephen; Stuart, Jeffrey J (J Insect Physiol, 2016)
The genetic tractability of the Hessian fly (HF, Mayetiola destructor) provides an opportunity to investigate the mechanisms insects use to induce plant gall formation. Here we demonstrate that capacity using the newly sequenced HF genome by identifying the gene (vH24) that elicits effector-triggered immunity in wheat (Triticum spp.) seedlings carrying HF resistance gene H24. vH24 was mapped within a 230-kb genomic fragment near the telomere of HF chromosome X1. That fragment contains only 21 putative genes. The best candidate vH24 gene in this region encodes a protein containing a secretion signal and a type-2 serine/threonine protein phosphatase (PP2C) domain. This gene has an H24-virulence associated insertion in its promoter that appears to silence transcription of the gene in H24-virulent larvae. Candidate vH24 is a member of a small family of genes that encode secretion signals and PP2C domains. It belongs to the fraction of genes in the HF genome previously predicted to encode effector proteins. Because PP2C proteins are not normally secreted, our results suggest that these are PP2C effectors that HF larvae inject into wheat cells to redirect, or interfere, with wheat signal transduction pathways.
Keywords: Animals; Chromosome Mapping; Crosses, Genetic; Diptera; Female; Genes, Insect; Genes, Plant; Genes, Recessive; Genes, X-Linked; Host-Parasite Interactions; Male; Phosphoprotein Phosphatases; Plant Immunity; Plant Proteins; Plant Tumors; Protein Phosphatase 2C; Telomere; Triticum; Virulence

Bi-allelic Mutations in PKD1L1 Are Associated with Laterality Defects in Humans. - Vetrini, Francesco; D'Alessandro, Lisa C A; Akdemir, Zeynep C; Braxton, Alicia; Azamian, Mahshid S; Eldomery, Mohammad K; Miller, Kathryn; Kois, Chelsea; Sack, Virginia; Shur, Natasha; Rijhsinghani, Asha; Chandarana, Jignesh; et al. (Am J Hum Genet, 2016)
Disruption of the establishment of left-right (L-R) asymmetry leads to situs anomalies ranging from situs inversus totalis (SIT) to situs ambiguus (heterotaxy). The genetic causes of laterality defects in humans are highly heterogeneous. Via whole-exome sequencing (WES), we identified homozygous mutations in PKD1L1 from three affected individuals in two unrelated families. PKD1L1 encodes a polycystin-1-like protein and its loss of function is known to cause laterality defects in mouse and medaka fish models. Family 1 had one fetus and one deceased child with heterotaxy and complex congenital heart malformations. WES identified a homozygous splicing mutation, c.6473+2_6473+3delTG, which disrupts the invariant splice donor site in intron 42, in both affected individuals. In the second family, a homozygous c.5072G>C (p.Cys1691Ser) missense mutation was detected in an individual with SIT and congenital heart disease. The p.Cys1691Ser substitution affects a highly conserved cysteine residue and is predicted by molecular modeling to disrupt a disulfide bridge essential for the proper folding of the G protein-coupled receptor proteolytic site (GPS) motif. Damaging effects associated with substitutions of this conserved cysteine residue in the GPS motif have also been reported in other genes, namely GPR56, BAI3, and PKD1 in human and lat-1 in C. elegans, further supporting the likely pathogenicity of p.Cys1691Ser in PKD1L1. The identification of bi-allelic PKD1L1 mutations recapitulates previous findings regarding phenotypic consequences of loss of function of the orthologous genes in mice and medaka fish and further expands our understanding of genetic contributions to laterality defects in humans.
Keywords: Alleles; Amino Acid Motifs; Amino Acid Sequence; Animals; Caenorhabditis elegans; Cysteine; Exome; Female; Fetal Diseases; Functional Laterality; Heart Defects, Congenital; Heterotaxy Syndrome; Homozygote; Humans; Infant, Newborn; Introns; Male; Membrane Proteins; Mice; Middle Aged; Models, Molecular; Mutation; Mutation, Missense; Oryzias; Pedigree; RNA Splicing; Situs Inversus

Causal Role of Alcohol Consumption in an Improved Lipid Profile: The Atherosclerosis Risk in Communities (ARIC) Study. - Vu, Khanh N; Ballantyne, Christie M; Hoogeveen, Ron C; Nambi, Vijay; Volcik, Kelly A; Eric Boerwinkle; Morrison, Alanna C (PLoS One, 2016)
INTRODUCTION: Health benefits of low-to-moderate alcohol consumption may operate through an improved lipid profile. A Mendelian randomization (MR) approach was used to examine whether alcohol consumption causally affects lipid levels. METHODS: This analysis involved 10,893 European Americans (EA) from the Atherosclerosis Risk in Communities (ARIC) study. Common and rare variants in alcohol dehydrogenase and acetaldehyde dehydrogenase genes were evaluated for MR assumptions. Five variants, residing in the ADH1B, ADH1C, and ADH4 genes, were selected as genetic instruments and were combined into an unweighted genetic score. Triglycerides (TG), total cholesterol, high-density lipoprotein cholesterol (HDL-c) and its subfractions (HDL2-c and HDL3-c), low-density lipoprotein cholesterol (LDL-c), small dense LDL-c (sdLDL-c), apolipoprotein B (apoB), and lipoprotein (a) (Lp(a)) levels were analyzed. RESULTS: Alcohol consumption significantly increased HDL2-c and reduced TG, total cholesterol, LDL-c, sdLDL-c, and apoB levels. For each of these lipids a non-linear trend was observed. Compared to the first quartile of alcohol consumption, the third quartile had a 12.3% lower level of TG (p < 0.001), a 7.71 mg/dL lower level of total cholesterol (p = 0.007), a 10.3% higher level of HDL2-c (p = 0.007), a 6.87 mg/dL lower level of LDL-c (p = 0.012), a 7.4% lower level of sdLDL-c (p = 0.037), and a 3.5% lower level of apoB (p = 0.058, poverall = 0.022). CONCLUSIONS: This study supports the causal role of regular low-to-moderate alcohol consumption in increasing HDL2-c, reducing TG, total cholesterol, and LDL-c, and provides evidence for the novel finding that low-to-moderate consumption of alcohol reduces apoB and sdLDL-c levels among EA. However, given the nonlinearity of the effect of alcohol consumption, even within the range of low-to-moderate drinking, increased consumption does not always result in a larger benefit.
Keywords: Alcohol Dehydrogenase; Alcohol Drinking; Atherosclerosis; Female; Humans; Lipids; Male; Middle Aged

CAV3 mutation in a patient with transient hyperCKemia and myalgia. - Macias, Anna; Gambin, Tomasz; Szafranski, Przemyslaw; Jhangiani, Shalini N; Kolasa, Anna; Obersztyn, Ewa; Lupski, James R; Stankiewicz, Pawel; Kaminska, Anna (Neurol Neurochir Pol, 2016)
Mutations in caveolin-3 (CAV3) can lead to different clinical phenotypes affecting skeletal or cardiac muscles. Here, we describe a patient with Klinefelter syndrome, ulcerative colitis and Sjögren syndrome, who developed transient hyperCKemia, myalgia and mild muscular weakness. Using whole exome sequencing (WES), a missense mutation G169A was found in the CAV3 gene. In addition, we identified a homozygous frameshift deletion in MS4A12 that may contribute to inflammatory bowel disease, further demonstrating usefulness of WES in dual molecular diagnoses.
Keywords: Caveolin 3; Colitis, Ulcerative; Creatine Kinase; Frameshift Mutation; Humans; Klinefelter Syndrome; Magnetic Resonance Imaging; Male; Membrane Proteins; Middle Aged; Muscle, Skeletal; Muscular Diseases; Mutation, Missense; Myalgia; Phenotype; Sjogren's Syndrome; Thigh

Comparative Genomics of Two Closely Related Wolbachia with Different Reproductive Effects on Hosts. - Newton, Irene L G; Clark, Michael E; Kent, Bethany N; Bordenstein, Seth R; Qu, Jiaxin; Richards, Stephen; Kelkar, Yogeshwar D; Werren, John H (Genome Biol Evol, 2016)
Wolbachia pipientis are obligate intracellular bacteria commonly found in many arthropods. They can induce various reproductive alterations in hosts, including cytoplasmic incompatibility, male-killing, feminization, and parthenogenetic development, and can provide host protection against some viruses and other pathogens. Wolbachia differ from many other primary endosymbionts in arthropods because they undergo frequent horizontal transmission between hosts and are well known for an abundance of mobile elements and relatively high recombination rates. Here, we compare the genomes of two closely related Wolbachia (with 0.57% genome-wide synonymous divergence) that differ in their reproductive effects on hosts. wVitA induces a sperm-egg incompatibility (also known as cytoplasmic incompatibility) in the parasitoid insect Nasonia vitripennis, whereas wUni causes parthenogenetic development in a different parasitoid, Muscidifurax uniraptor Although these bacteria are closely related, the genomic comparison reveals rampant rearrangements, protein truncations (particularly in proteins predicted to be secreted), and elevated substitution rates. These changes occur predominantly in the wUni lineage, and may be due in part to adaptations by wUni to a new host environment, or its phenotypic shift to parthenogenesis induction. However, we conclude that the approximately 8-fold elevated synonymous substitution rate in wUni is due to a either an elevated mutation rate or a greater number of generations per year in wUni, which occurs in semitropical host species. We identify a set of genes whose loss or pseudogenization in the wUni lineage implicates them in the phenotypic shift from cytoplasmic incompatibility to parthenogenesis induction. Finally, comparison of these closely related strains allows us to determine the fine-scale mutation patterns in Wolbachia Although Wolbachia are AT rich, mutation probabilities estimated from 4-fold degenerate sites are not AT biased, and predict an equilibrium AT content much less biased than observed (57-50% AT predicted vs. 76% current content at degenerate sites genome wide). The contrast suggests selection for increased AT content within Wolbachia genomes.
Keywords: Animals; Arthropods; Cytoplasm; Drosophila; Genome, Bacterial; Genomics; Host Specificity; Male; Mutation; Phylogeny; Reproduction; Selection, Genetic; Wolbachia

Complex inheritance of ABCA4 disease: four mutations in a family with multiple macular phenotypes. - Lee, Winston; Xie, Yajing; Zernant, Jana; Bo Yuan; Bearelly, Srilaxmi; Tsang, Stephen H; James R Lupski; Allikmets, Rando (Hum Genet, 2016)
Over 800 mutations in the ABCA4 gene cause autosomal recessive Stargardt disease. Due to extensive genetic heterogeneity, observed variant-associated phenotypes can manifest tremendous variability of expression. Furthermore, the high carrier frequency of pathogenic ABCA4 alleles in the general population (~1:20) often results in pseudo-dominant inheritance patterns further complicating the diagnosis and characterization of affected individuals. This study describes a genotype/phenotype analysis of an unusual family with multiple macular disease phenotypes spanning across two generations and segregating four distinct ABCA4 mutant alleles. Complete sequencing of ABCA4 discovered two known missense mutations, p.C54Y and p.G1961E. Array comparative genomic hybridization revealed a large novel deletion combined with a small insertion, c.6148-698_c.6670del/insTGTGCACCTCCCTAG, and complete sequencing of the entire ABCA4 genomic locus uncovered a new deep intronic variant, c.302+68C>T. Patients with the p.G1961E mutation had the mildest, confined maculopathy phenotype with peripheral flecks while those with all other mutant allele combinations exhibited a more advanced stage of generalized retinal and choriocapillaris atrophy. This family epitomizes the clinical and genetic complexity of ABCA4-associated diseases. It contained variants from all classes of mutations, in the coding region, deep intronic, both single nucleotide variants and copy number variants that accounted for varying phenotypes segregating in an apparent dominant fashion. Unequivocally defining disease-associated alleles in the ABCA4 locus requires a multifaceted approach that includes advanced mutation detection methods and a thorough analysis of clinical phenotypes.
Keywords: Adult; Aged; ATP-Binding Cassette Transporters; Comparative Genomic Hybridization; DNA Copy Number Variations; Electroretinography; Female; High-Throughput Nucleotide Sequencing; Humans; Macula Lutea; Macular Degeneration; Male; Middle Aged; Mutation; Pedigree; Phenotype; Stargardt Disease

Comprehensive Pan-Genomic Characterization of Adrenocortical Carcinoma. - Zheng, Siyuan; Cherniack, Andrew D; Dewal, Ninad; Moffitt, Richard A; Danilova, Ludmila; Murray, Bradley A; Lerario, Antonio M; Else, Tobias; Knijnenburg, Theo A; Ciriello, Giovanni; Kim, Seungchan; Assie, Guillaume; et al. (Cancer Cell, 2016)
We describe a comprehensive genomic characterization of adrenocortical carcinoma (ACC). Using this dataset, we expand the catalogue of known ACC driver genes to include PRKAR1A, RPL22, TERF2, CCNE1, and NF1. Genome wide DNA copy-number analysis revealed frequent occurrence of massive DNA loss followed by whole-genome doubling (WGD), which was associated with aggressive clinical course, suggesting WGD is a hallmark of disease progression. Corroborating this hypothesis were increased TERT expression, decreased telomere length, and activation of cell-cycle programs. Integrated subtype analysis identified three ACC subtypes with distinct clinical outcome and molecular alterations which could be captured by a 68-CpG probe DNA-methylation signature, proposing a strategy for clinical stratification of patients based on molecular markers.
Keywords: Adolescent; Adrenal Cortex Neoplasms; Adrenocortical Carcinoma; Adult; Aged; Aged, 80 and over; Child; Disease-Free Survival; DNA Methylation; Female; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Genetic Predisposition to Disease; Genome, Human; Genomics; Humans; Male; Middle Aged; Mutation; Outcome Assessment, Health Care; Prognosis; Young Adult

A comprehensive transcriptional map of primate brain development. - Bakken, Trygve E; Miller, Jeremy A; Ding, Song-Lin; Sunkin, Susan M; Smith, Kimberly A; Ng, Lydia; Szafer, Aaron; Dalley, Rachel A; Royall, Joshua J; Lemon, Tracy; Shapouri, Sheila; Aiona, Kaylynn; et al. (Nature, 2016)
The transcriptional underpinnings of brain development remain poorly understood, particularly in humans and closely related non-human primates. We describe a high-resolution transcriptional atlas of rhesus monkey (Macaca mulatta) brain development that combines dense temporal sampling of prenatal and postnatal periods with fine anatomical division of cortical and subcortical regions associated with human neuropsychiatric disease. Gene expression changes more rapidly before birth, both in progenitor cells and maturing neurons. Cortical layers and areas acquire adult-like molecular profiles surprisingly late in postnatal development. Disparate cell populations exhibit distinct developmental timing of gene expression, but also unexpected synchrony of processes underlying neural circuit construction including cell projection and adhesion. Candidate risk genes for neurodevelopmental disorders including primary microcephaly, autism spectrum disorder, intellectual disability, and schizophrenia show disease-specific spatiotemporal enrichment within developing neocortex. Human developmental expression trajectories are more similar to monkey than rodent, although approximately 9% of genes show human-specific regulation with evidence for prolonged maturation or neoteny compared to monkey.
Keywords: Aging; Animals; Autism Spectrum Disorder; Brain; Cell Adhesion; Conserved Sequence; Female; Humans; Intellectual Disability; Macaca mulatta; Male; Microcephaly; Neocortex; Neurodevelopmental Disorders; Neurogenesis; Risk Factors; Schizophrenia; Spatio-Temporal Analysis; Species Specificity; Transcription, Genetic; Transcriptome

Copy-Number Variation Contributes to the Mutational Load of Bardet-Biedl Syndrome. - Lindstrand, Anna; Frangakis, Stephan; Carvalho, Claudia M B; Richardson, Ellen B; McFadden, Kelsey A; Willer, Jason R; Pehlivan, Davut; Liu, Pengfei; Pediaditakis, Igor L; Aniko Sabo; Lewis, Richard Alan; Banin, Eyal; et al. (Am J Hum Genet, 2016)
Bardet-Biedl syndrome (BBS) is a defining ciliopathy, notable for extensive allelic and genetic heterogeneity, almost all of which has been identified through sequencing. Recent data have suggested that copy-number variants (CNVs) also contribute to BBS. We used a custom oligonucleotide array comparative genomic hybridization (aCGH) covering 20 genes that encode intraflagellar transport (IFT) components and 74 ciliopathy loci to screen 92 unrelated individuals with BBS, irrespective of their known mutational burden. We identified 17 individuals with exon-disruptive CNVs (18.5%), including 13 different deletions in eight BBS genes (BBS1, BBS2, ARL6/BBS3, BBS4, BBS5, BBS7, BBS9, and NPHP1) and a deletion and a duplication in other ciliopathy-associated genes (ALMS1 and NPHP4, respectively). By contrast, we found a single heterozygous exon-disruptive event in a BBS-associated gene (BBS9) in 229 control subjects. Superimposing these data with resequencing revealed CNVs to (1) be sufficient to cause disease, (2) Mendelize heterozygous deleterious alleles, and (3) contribute oligogenic alleles by combining point mutations and exonic CNVs in multiple genes. Finally, we report a deletion and a splice site mutation in IFT74, inherited under a recessive paradigm, defining a candidate BBS locus. Our data suggest that CNVs contribute pathogenic alleles to a substantial fraction of BBS-affected individuals and highlight how either deletions or point mutations in discrete splice isoforms can induce hypomorphic mutations in genes otherwise intolerant to deleterious variation. Our data also suggest that CNV analyses and resequencing studies unbiased for previous mutational burden is necessary to delineate the complexity of disease architecture.
Keywords: Adolescent; Adult; Alleles; Animals; Bardet-Biedl Syndrome; Child; Child, Preschool; Chromosome Breakpoints; Cytoskeletal Proteins; DNA Copy Number Variations; Exons; Female; Gastrulation; Genes, Recessive; Humans; Infant; Male; Mutation; Pedigree; Young Adult; Zebrafish; Zebrafish Proteins

De novo missense variants in PPP1CB are associated with intellectual disability and congenital heart disease. - Ma, Lijiang; Bayram, Yavuz; McLaughlin, Heather M; Cho, Megan T; Krokosky, Alyson; Turner, Clesson E; Lindstrom, Kristin; Bupp, Caleb P; Mayberry, Katey; Mu, Weiyi; Bodurtha, Joann; Weinstein, Veronique; et al. (Hum Genet, 2016)
Intellectual disabilities are genetically heterogeneous and can be associated with congenital anomalies. Using whole-exome sequencing (WES), we identified five different de novo missense variants in the protein phosphatase-1 catalytic subunit beta (PPP1CB) gene in eight unrelated individuals who share an overlapping phenotype of dysmorphic features, macrocephaly, developmental delay or intellectual disability (ID), congenital heart disease, short stature, and skeletal and connective tissue abnormalities. Protein phosphatase-1 (PP1) is a serine/threonine-specific protein phosphatase involved in the dephosphorylation of a variety of proteins. The PPP1CB gene encodes a PP1 subunit that regulates the level of protein phosphorylation. All five altered amino acids we observed are highly conserved among the PP1 subunit family, and all are predicted to disrupt PP1 subunit binding and impair dephosphorylation. Our data suggest that our heterozygous de novo PPP1CB pathogenic variants are associated with syndromic intellectual disability.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Defects, Congenital; Humans; Intellectual Disability; Male; Mutation, Missense; Phosphorylation; Protein Phosphatase 1

Destabilized SMC5/6 complex leads to chromosome breakage syndrome with severe lung disease. - van der Crabben, Saskia N; Hennus, Marije P; McGregor, Grant A; Ritter, Deborah I; Nagamani, Sandesh C S; Wells, Owen S; Harakalova, Magdalena; Chinn, Ivan K; Alt, Aaron; Vondrova, Lucie; Hochstenbach, Ron; van Montfrans, Joris M; et al. (J Clin Invest, 2016)
The structural maintenance of chromosomes (SMC) family of proteins supports mitotic proliferation, meiosis, and DNA repair to control genomic stability. Impairments in chromosome maintenance are linked to rare chromosome breakage disorders. Here, we have identified a chromosome breakage syndrome associated with severe lung disease in early childhood. Four children from two unrelated kindreds died of severe pulmonary disease during infancy following viral pneumonia with evidence of combined T and B cell immunodeficiency. Whole exome sequencing revealed biallelic missense mutations in the NSMCE3 (also known as NDNL2) gene, which encodes a subunit of the SMC5/6 complex that is essential for DNA damage response and chromosome segregation. The NSMCE3 mutations disrupted interactions within the SMC5/6 complex, leading to destabilization of the complex. Patient cells showed chromosome rearrangements, micronuclei, sensitivity to replication stress and DNA damage, and defective homologous recombination. This work associates missense mutations in NSMCE3 with an autosomal recessive chromosome breakage syndrome that leads to defective T and B cell function and acute respiratory distress syndrome in early childhood.
Keywords: Abnormalities, Multiple; Alleles; B-Lymphocytes; Cell Cycle Proteins; Cell Proliferation; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Chromosome Breakage; Chromosome Segregation; Chromosomes; DNA Damage; DNA Repair; DNA Replication; Family Health; Female; Fibroblasts; Homozygote; Humans; Infant; Intracellular Signaling Peptides and Proteins; Lung Diseases; Male; Meiosis; Mitosis; Mutation, Missense; Pedigree; Recombination, Genetic; Syndrome; T-Lymphocytes

Discovery of Genetic Variation on Chromosome 5q22 Associated with Mortality in Heart Failure. - Smith, J Gustav; Felix, Janine F; Morrison, Alanna C; Kalogeropoulos, Andreas; Trompet, Stella; Wilk, Jemma B; Gidlöf, Olof; Wang, Xinchen; Morley, Michael; Mendelson, Michael; Joehanes, Roby; Ligthart, Symen; et al. (PLoS Genet, 2016)
Failure of the human heart to maintain sufficient output of blood for the demands of the body, heart failure, is a common condition with high mortality even with modern therapeutic alternatives. To identify molecular determinants of mortality in patients with new-onset heart failure, we performed a meta-analysis of genome-wide association studies and follow-up genotyping in independent populations. We identified and replicated an association for a genetic variant on chromosome 5q22 with 36% increased risk of death in subjects with heart failure (rs9885413, P = 2.7x10-9). We provide evidence from reporter gene assays, computational predictions and epigenomic marks that this polymorphism increases activity of an enhancer region active in multiple human tissues. The polymorphism was further reproducibly associated with a DNA methylation signature in whole blood (P = 4.5x10-40) that also associated with allergic sensitization and expression in blood of the cytokine TSLP (P = 1.1x10-4). Knockdown of the transcription factor predicted to bind the enhancer region (NHLH1) in a human cell line (HEK293) expressing NHLH1 resulted in lower TSLP expression. In addition, we observed evidence of recent positive selection acting on the risk allele in populations of African descent. Our findings provide novel genetic leads to factors that influence mortality in patients with heart failure.
Keywords: Alleles; Basic Helix-Loop-Helix Transcription Factors; Black or African American; Chromosomes, Human, Pair 5; DNA Methylation; Female; Gene Expression Regulation; Gene Knockdown Techniques; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genotype; Heart Failure; HEK293 Cells; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Cytokine

DNA methylation-based measures of biological age: meta-analysis predicting time to death. - Chen, Brian H; Marioni, Riccardo E; Colicino, Elena; Peters, Marjolein J; Ward-Caviness, Cavin K; Tsai, Pei-Chien; Roetker, Nicholas S; Just, Allan C; Demerath, Ellen W; Guan, Weihua; Bressler, Jan; Fornage, Myriam; et al. (Aging (Albany NY), 2016)
Estimates of biological age based on DNA methylation patterns, often referred to as "epigenetic age", "DNAm age", have been shown to be robust biomarkers of age in humans. We previously demonstrated that independent of chronological age, epigenetic age assessed in blood predicted all-cause mortality in four human cohorts. Here, we expanded our original observation to 13 different cohorts for a total sample size of 13,089 individuals, including three racial/ethnic groups. In addition, we examined whether incorporating information on blood cell composition into the epigenetic age metrics improves their predictive power for mortality. All considered measures of epigenetic age acceleration were predictive of mortality (p≤8.2x10, independent of chronological age, even after adjusting for additional risk factors (p<5.4x10, and within the racial/ethnic groups that we examined (non-Hispanic whites, Hispanics, African Americans). Epigenetic age estimates that incorporated information on blood cell composition led to the smallest p-values for time to death (p=7.5x10). Overall, this study a) strengthens the evidence that epigenetic age predicts all-cause mortality above and beyond chronological age and traditional risk factors, and b) demonstrates that epigenetic age estimates that incorporate information on blood cell counts lead to highly significant associations with all-cause mortality.
Keywords: Aging; DNA Methylation; Epigenesis, Genetic; Female; Humans; Logistic Models; Male; Mortality; Racial Groups; Risk Factors; Survival Analysis; T-Lymphocyte Subsets

DVL3 Alleles Resulting in a -1 Frameshift of the Last Exon Mediate Autosomal-Dominant Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Hoischen, Alexander; Bayram, Yavuz; Withers, Marjorie; Gezdirici, Alper; Kimonis, Virginia; Steehouwer, Marloes; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; van Bon, Bregje W M; et al. (Am J Hum Genet, 2016)
Robinow syndrome is a rare congenital disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features. Recent reports have identified, in individuals with dominant Robinow syndrome, a specific type of variant characterized by being uniformly located in the penultimate exon of DVL1 and resulting in a -1 frameshift allele with a premature termination codon that escapes nonsense-mediated decay. Here, we studied a cohort of individuals who had been clinically diagnosed with Robinow syndrome but who had not received a molecular diagnosis from variant studies of DVL1, WNT5A, and ROR2. Because of the uniform location of frameshift variants in DVL1-mediated Robinow syndrome and the functional redundancy of DVL1, DVL2, and DVL3, we elected to pursue direct Sanger sequencing of the penultimate exon of DVL1 and its paralogs DVL2 and DVL3 to search for potential disease-associated variants. Remarkably, targeted sequencing identified five unrelated individuals harboring heterozygous, de novo frameshift variants in DVL3, including two splice acceptor mutations and three 1 bp deletions. Similar to the variants observed in DVL1-mediated Robinow syndrome, all variants in DVL3 result in a -1 frameshift, indicating that these highly specific alterations might be a common cause of dominant Robinow syndrome. Here, we review the current knowledge of these peculiar variant alleles in DVL1- and DVL3-mediated Robinow syndrome and further elucidate the phenotypic features present in subjects with DVL1 and DVL3 frameshift mutations.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Base Sequence; Codon, Nonsense; Craniofacial Abnormalities; Dishevelled Proteins; Dwarfism; Exons; Female; Frameshift Mutation; Genetic Variation; Humans; Limb Deformities, Congenital; Male; Molecular Sequence Data; Phosphoproteins; Proto-Oncogene Proteins; Receptor Tyrosine Kinase-like Orphan Receptors; Sequence Analysis, DNA; Sequence Deletion; Urogenital Abnormalities; Wnt Proteins; Wnt-5a Protein

Evolutionary and developmental implications of asymmetric brain folding in a large primate pedigree. - Atkinson, Elizabeth G; Jeffrey Rogers; Cheverud, James M (Evolution, 2016)
Bilateral symmetry is a fundamental property of the vertebrate central nervous system. Local deviations from symmetry provide various types of information about the development, evolution, and function of elements within the CNS, especially the cerebral hemispheres. Here, we quantify the pattern and extent of asymmetry in cortical folding within the cerebrum of Papio baboons and assess the evolutionary and developmental implications of the findings. Analyses of directional asymmetry show a population-level trend in length measurements indicating that baboons are genetically predisposed to be asymmetrical, with the right side longer than the left in the anterior cerebrum while the left side is longer than the right posteriorly. We also find a corresponding bias to display a right frontal petalia (overgrowth of the anterior pole of the cerebral cortex on the right side). By quantifying fluctuating asymmetry, we assess canalization of brain features and the susceptibility of the baboon brain to developmental perturbations. We find that features are differentially canalized depending on their ontogenetic timing. We further deduce that development of the two hemispheres is to some degree independent. This independence has important implications for the evolution of cerebral hemispheres and their separate specialization. Asymmetry is a major feature of primate brains and is characteristic of both brain structure and function.
Keywords: Animals; Biological Evolution; Cerebrum; Female; Male; Pedigree; Primates

An exome array study of the plasma metabolome. - Rhee, Eugene P; Yang, Qiong; Yu, Bing; Liu, Xuan; Cheng, Susan; Deik, Amy; Pierce, Kerry A; Bullock, Kevin; Ho, Jennifer E; Levy, Daniel; Florez, Jose C; Kathiresan, Sek; et al. (Nat Commun, 2016)
The study of rare variants may enhance our understanding of the genetic determinants of the metabolome. Here, we analyze the association between 217 plasma metabolites and exome variants on the Illumina HumanExome Beadchip in 2,076 participants in the Framingham Heart Study, with replication in 1,528 participants of the Atherosclerosis Risk in Communities Study. We identify an association between GMPS and xanthosine using single variant analysis and associations between HAL and histidine, PAH and phenylalanine, and UPB1 and ureidopropionate using gene-based tests (P<5 × 10(-8) in meta-analysis), highlighting novel coding variants that may underlie inborn errors of metabolism. Further, we show how an examination of variants across the spectrum of allele frequency highlights independent association signals at select loci and generates a more integrated view of metabolite heritability. These studies build on prior metabolomics genome wide association studies to provide a more complete picture of the genetic architecture of the plasma metabolome.
Keywords: Exome; Female; Gene Frequency; Genome-Wide Association Study; Humans; Male; Metabolome; Middle Aged; Plasma; Polymorphism, Single Nucleotide; Ribonucleosides; Xanthines

Exome sequencing in mostly consanguineous Arab families with neurologic disease provides a high potential molecular diagnosis rate. - Charng, Wu-Lin; Karaca, Ender; Coban Akdemir, Zeynep; Gambin, Tomasz; Atik, Mehmed M; Gu, Shen; Posey, Jennifer E; Jhangiani, Shalini N; Donna M Muzny; Harshavardhan Doddapaneni; Jianhong Hu; Eric Boerwinkle; et al. (BMC Med Genomics, 2016)
BACKGROUND: Neurodevelopment is orchestrated by a wide range of genes, and the genetic causes of neurodevelopmental disorders are thus heterogeneous. We applied whole exome sequencing (WES) for molecular diagnosis and in silico analysis to identify novel disease gene candidates in a cohort from Saudi Arabia with primarily Mendelian neurologic diseases. METHODS: We performed WES in 31 mostly consanguineous Arab families and analyzed both single nucleotide and copy number variants (CNVs) from WES data. Interaction/expression network and pathway analyses, as well as paralog studies were utilized to investigate potential pathogenicity and disease association of novel candidate genes. Additional cases for candidate genes were identified through the clinical WES database at Baylor Miraca Genetics Laboratories and GeneMatcher. RESULTS: We found known pathogenic or novel variants in known disease genes with phenotypic expansion in 6 families, disease-associated CNVs in 2 families, and 12 novel disease gene candidates in 11 families, including KIF5B, GRM7, FOXP4, MLLT1, and KDM2B. Overall, a potential molecular diagnosis was provided by variants in known disease genes in 17 families (54.8 %) and by novel candidate disease genes in an additional 11 families, making the potential molecular diagnostic rate ~90 %. CONCLUSIONS: Molecular diagnostic rate from WES is improved by exome-predicted CNVs. Novel candidate disease gene discovery is facilitated by paralog studies and through the use of informatics tools and available databases to identify additional evidence for pathogenicity. TRIAL REGISTRATION: Not applicable.
Keywords: Arabs; Cohort Studies; Consanguinity; Data Mining; Databases, Genetic; DNA Copy Number Variations; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Molecular Diagnostic Techniques; Nervous System Diseases; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Genetic analysis of innate immunity in Behcet's disease identifies an association with IL-37 and IL-18RAP. - Tan, Handan; Deng, Bolin; Yu, Hongsong; Yang, Yi; Ding, Lin; Zhang, Qi; Qin, Jieying; Kijlstra, Aize; Rui Chen; Yang, Peizeng (Sci Rep, 2016)
Interleukin-1 (IL-1) and the IL-1 receptor (IL-1R) family play an important role in the pathogenesis of inflammatory diseases. This study aimed to investigate the association between single nucleotide polymorphisms (SNP) of IL-1 and IL-1R family genes with Vogt-Koyanagi-Harada (VKH) and Behcet's disease (BD) in Han Chinese. The case-control study was divided into two stages and included 419 VKH cases, 1063 BD cases and 1872 healthy controls. The MassARRAY platform (Sequenom), iPLEX Gold Assay and TaqMan SNP assays were used to score genotypes of 24 SNPs. The expression of IL-37 and IL-18Rap was measured by ELISA and real-time PCR in genotyped healthy individuals. A significantly lower frequency of the AG genotype, and a higher frequency of the GG genotype and G allele of IL-37/rs3811047 were observed in BD as compared to controls. AA genotype and A allele frequency of IL-18RAP/rs2058660 was significantly decreased in BD as compared to controls. Functional studies performed in healthy controls showed that rs3811047 AG genotype carriers had a higher IL-37 gene expression in peripheral blood mononuclear cells (PBMCs) than GG carriers. GG carriers showed a higher cytokine expression as compared to AG carriers. No association was detected between the tested SNPs and VKH.
Keywords: Adult; Asian People; Behcet Syndrome; Case-Control Studies; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Immunity, Innate; Interleukin-1; Interleukin-18 Receptor beta Subunit; Leukocytes, Mononuclear; Male; Middle Aged; Polymorphism, Single Nucleotide; Uveomeningoencephalitic Syndrome

Genetic Variants in LRP1 and ULK4 Are Associated with Acute Aortic Dissections. - Guo, Dong-chuan; Grove, Megan L; Prakash, Siddharth K; Eriksson, Per; Hostetler, Ellen M; LeMaire, Scott A; Body, Simon C; Shalhub, Sherene; Estrera, Anthony L; Safi, Hazim J; Regalado, Ellen S; Zhou, Wei; et al. (Am J Hum Genet, 2016)
Acute aortic dissections are a preventable cause of sudden death if individuals at risk are identified and surgically repaired in a non-emergency setting. Although mutations in single genes can be used to identify at-risk individuals, the majority of dissection case subjects do not have evidence of a single gene disorder, but rather have the other major risk factor for dissections, hypertension. Initial genome-wide association studies (GWASs) identified SNPs at the FBN1 locus associated with both thoracic aortic aneurysms and dissections. Here, we used the Illumina HumanExome array to genotype 753 individuals of European descent presenting specifically with non-familial, sporadic thoracic aortic dissection (STAD) and compared them to the genotypes of 2,259 control subjects from the Atherosclerosis Risk in Communities (ARIC) study matched for age, gender, and, for the majority of cases, hypertension. SNPs in FBN1, LRP1, and ULK4 were identified to be significantly associated with STAD, and these results were replicated in two independent cohorts. Combining the data from all cohorts confirmed an inverse association between LRP1 rs11172113 and STAD (p = 2.74 × 10(-8); OR = 0.82, 95% CI = 0.76-0.89) and a direct association between ULK4 rs2272007 and STAD (p = 1.15 × 10(-9); OR = 1.35, 95% CI = 1.23-1.49). Genomic copy-number variation analysis independently confirmed that ULK4 deletions were significantly associated with development of thoracic aortic disease. These results indicate that genetic variations in LRP1 and ULK4 contribute to risk for presenting with an acute aortic dissection.
Keywords: Aged; Aortic Aneurysm, Thoracic; Aortic Dissection; Atherosclerosis; Case-Control Studies; Cohort Studies; DNA Copy Number Variations; Europe; Exome; Female; Fibrillin-1; Gene Deletion; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Hypertension; Linkage Disequilibrium; Low Density Lipoprotein Receptor-Related Protein-1; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases; Risk Factors

Genome-culture coevolution promotes rapid divergence of killer whale ecotypes. - Foote, Andrew D; Vijay, Nagarjun; Ávila-Arcos, María C; Baird, Robin W; Durban, John W; Fumagalli, Matteo; Richard A Gibbs; Hanson, M Bradley; Korneliussen, Thorfinn S; Martin, Michael D; Robertson, Kelly M; Sousa, Vitor C; et al. (Nat Commun, 2016)
Analysing population genomic data from killer whale ecotypes, which we estimate have globally radiated within less than 250,000 years, we show that genetic structuring including the segregation of potentially functional alleles is associated with socially inherited ecological niche. Reconstruction of ancestral demographic history revealed bottlenecks during founder events, likely promoting ecological divergence and genetic drift resulting in a wide range of genome-wide differentiation between pairs of allopatric and sympatric ecotypes. Functional enrichment analyses provided evidence for regional genomic divergence associated with habitat, dietary preferences and post-zygotic reproductive isolation. Our findings are consistent with expansion of small founder groups into novel niches by an initial plastic behavioural response, perpetuated by social learning imposing an altered natural selection regime. The study constitutes an important step towards an understanding of the complex interaction between demographic history, culture, ecological adaptation and evolution at the genomic level.
Keywords: Adaptation, Biological; Animals; Biopsy; Ecotype; Evolution, Molecular; Female; Gene-Environment Interaction; Genetic Drift; Genetic Speciation; Genetic Variation; Genetics, Population; Genome; Genomics; Male; Phylogeny; Reproductive Isolation; Selection, Genetic; Skin; Sympatry; Whale, Killer

The genomic basis of circadian and circalunar timing adaptations in a midge. - Kaiser, Tobias S; Poehn, Birgit; Szkiba, David; Preussner, Marco; Fritz J Sedlazeck; Zrim, Alexander; Neumann, Tobias; Nguyen, Lam-Tung; Betancourt, Andrea J; Hummel, Thomas; Vogel, Heiko; Dorner, Silke; et al. (Nature, 2016)
Organisms use endogenous clocks to anticipate regular environmental cycles, such as days and tides. Natural variants resulting in differently timed behaviour or physiology, known as chronotypes in humans, have not been well characterized at the molecular level. We sequenced the genome of Clunio marinus, a marine midge whose reproduction is timed by circadian and circalunar clocks. Midges from different locations show strain-specific genetic timing adaptations. We examined genetic variation in five C. marinus strains from different locations and mapped quantitative trait loci for circalunar and circadian chronotypes. The region most strongly associated with circadian chronotypes generates strain-specific differences in the abundance of calcium/calmodulin-dependent kinase II.1 (CaMKII.1) splice variants. As equivalent variants were shown to alter CaMKII activity in Drosophila melanogaster, and C. marinus (Cma)-CaMKII.1 increases the transcriptional activity of the dimer of the circadian proteins Cma-CLOCK and Cma-CYCLE, we suggest that modulation of alternative splicing is a mechanism for natural adaptation in circadian timing.
Keywords: Acclimatization; Alternative Splicing; Animals; Calcium-Calmodulin-Dependent Protein Kinase Type 2; Chironomidae; Circadian Clocks; Circadian Rhythm; CLOCK Proteins; Drosophila melanogaster; Genetic Association Studies; Genetic Variation; Genome, Insect; Genomics; Male; Moon; Phenotype; Quantitative Trait Loci; Reproduction; Species Specificity; Tidal Waves; Time Factors; Transcription, Genetic

Genomic Profiling of Pediatric Acute Myeloid Leukemia Reveals a Changing Mutational Landscape from Disease Diagnosis to Relapse. - Farrar, Jason E; Schuback, Heather L; Ries, Rhonda E; Wai, Daniel; Hampton, Oliver A; Treviño, Lisa R; Alonzo, Todd A; Guidry Auvil, Jaime M; Davidsen, Tanja M; Gesuwan, Patee; Hermida, Leandro; Donna M Muzny; et al. (Cancer Res, 2016)
The genomic and clinical information used to develop and implement therapeutic approaches for acute myelogenous leukemia (AML) originated primarily from adult patients and has been generalized to patients with pediatric AML. However, age-specific molecular alterations are becoming more evident and may signify the need to age-stratify treatment regimens. The NCI/COG TARGET-AML initiative used whole exome capture sequencing (WXS) to interrogate the genomic landscape of matched trios representing specimens collected upon diagnosis, remission, and relapse from 20 cases of de novo childhood AML. One hundred forty-five somatic variants at diagnosis (median 6 mutations/patient) and 149 variants at relapse (median 6.5 mutations) were identified and verified by orthogonal methodologies. Recurrent somatic variants [in (greater than or equal to) 2 patients] were identified for 10 genes (FLT3, NRAS, PTPN11, WT1, TET2, DHX15, DHX30, KIT, ETV6, KRAS), with variable persistence at relapse. The variant allele fraction (VAF), used to measure the prevalence of somatic mutations, varied widely at diagnosis. Mutations that persisted from diagnosis to relapse had a significantly higher diagnostic VAF compared with those that resolved at relapse (median VAF 0.43 vs. 0.24, P < 0.001). Further analysis revealed that 90% of the diagnostic variants with VAF >0.4 persisted to relapse compared with 28% with VAF <0.2 (P < 0.001). This study demonstrates significant variability in the mutational profile and clonal evolution of pediatric AML from diagnosis to relapse. Furthermore, mutations with high VAF at diagnosis, representing variants shared across a leukemic clonal structure, may constrain the genomic landscape at relapse and help to define key pathways for therapeutic targeting. Cancer Res; 76(8); 2197-205. ©2016 AACR.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Female; Gene Expression Profiling; Humans; Infant; Leukemia, Myeloid, Acute; Male; Mutation; Recurrence

Genomics of Natural Populations: How Differentially Expressed Genes Shape the Evolution of Chromosomal Inversions in Drosophila pseudoobscura. - Fuller, Zachary L; Haynes, Gwilym D; Richards, Stephen; Schaeffer, Stephen W (Genetics, 2016)
Chromosomal rearrangements can shape the structure of genetic variation in the genome directly through alteration of genes at breakpoints or indirectly by holding combinations of genetic variants together due to reduced recombination. The third chromosome of Drosophila pseudoobscura is a model system to test hypotheses about how rearrangements are established in populations because its third chromosome is polymorphic for >30 gene arrangements that were generated by a series of overlapping inversion mutations. Circumstantial evidence has suggested that these gene arrangements are selected. Despite the expected homogenizing effects of extensive gene flow, the frequencies of arrangements form gradients or clines in nature, which have been stable since the system was first described >80 years ago. Furthermore, multiple arrangements exist at appreciable frequencies across several ecological niches providing the opportunity for heterokaryotypes to form. In this study, we tested whether genes are differentially expressed among chromosome arrangements in first instar larvae, adult females and males. In addition, we asked whether transcriptional patterns in heterokaryotypes are dominant, semidominant, overdominant, or underdominant. We find evidence for a significant abundance of differentially expressed genes across the inverted regions of the third chromosome, including an enrichment of genes involved in sensory perception for males. We find the majority of loci show additivity in heterokaryotypes. Our results suggest that multiple genes have expression differences among arrangements that were either captured by the original inversion mutation or accumulated after it reached polymorphic frequencies, providing a potential source of genetic variation for selection to act upon. These data suggest that the inversions are favored because of their indirect effect of recombination suppression that has held different combinations of differentially expressed genes together in the various gene arrangement backgrounds.
Keywords: Animals; Biological Evolution; Chromosome Inversion; Chromosomes, Insect; Drosophila; Female; Gene Expression Regulation; Gene Flow; Gene Order; Genomics; Male; Metagenomics; Transcriptome

Germline or somatic GPR101 duplication leads to X-linked acrogigantism: a clinico-pathological and genetic study. - Iacovazzo, Donato; Caswell, Richard; Bunce, Benjamin; Jose, Sian; Bo Yuan; Hernández-Ramírez, Laura C; Kapur, Sonal; Caimari, Francisca; Evanson, Jane; Ferraù, Francesco; Dang, Mary N; Gabrovska, Plamena; et al. (Acta Neuropathol Commun, 2016)
Non-syndromic pituitary gigantism can result from AIP mutations or the recently identified Xq26.3 microduplication causing X-linked acrogigantism (XLAG). Within Xq26.3, GPR101 is believed to be the causative gene, and the c.924G > C (p.E308D) variant in this orphan G protein-coupled receptor has been suggested to play a role in the pathogenesis of acromegaly.We studied 153 patients (58 females and 95 males) with pituitary gigantism. AIP mutation-negative cases were screened for GPR101 duplication through copy number variation droplet digital PCR and high-density aCGH. The genetic, clinical and histopathological features of XLAG patients were studied in detail. 395 peripheral blood and 193 pituitary tumor DNA samples from acromegaly patients were tested for GPR101 variants.We identified 12 patients (10 females and 2 males; 7.8 %) with XLAG. In one subject, the duplicated region only contained GPR101, but not the other three genes in found to be duplicated in the previously reported patients, defining a new smallest region of overlap of duplications. While females presented with germline mutations, the two male patients harbored the mutation in a mosaic state. Nine patients had pituitary adenomas, while three had hyperplasia. The comparison of the features of XLAG, AIP-positive and GPR101&AIP-negative patients revealed significant differences in sex distribution, age at onset, height, prolactin co-secretion and histological features. The pathological features of XLAG-related adenomas were remarkably similar. These tumors had a sinusoidal and lobular architecture. Sparsely and densely granulated somatotrophs were admixed with lactotrophs; follicle-like structures and calcifications were commonly observed. Patients with sporadic of familial acromegaly did not have an increased prevalence of the c.924G > C (p.E308D) GPR101 variant compared to public databases.In conclusion, XLAG can result from germline or somatic duplication of GPR101. Duplication of GPR101 alone is sufficient for the development of XLAG, implicating it as the causative gene within the Xq26.3 region. The pathological features of XLAG-associated pituitary adenomas are typical and, together with the clinical phenotype, should prompt genetic testing.
Keywords: Acromegaly; Adenoma; Adolescent; Child; Child, Preschool; Female; Gene Duplication; Germ-Line Mutation; Gigantism; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Pituitary Neoplasms; Receptors, G-Protein-Coupled; Treatment Outcome; Young Adult

Hypomorphic mutations identified in the candidate Leber congenital amaurosis gene CLUAP1. - Soens, Zachry T; Li, Yuanyuan; Zhao, Li; Eblimit, Aiden; Dharmat, Rachayata; Yumei Li; Chen, Yiyun; Naqeeb, Mohammed; Fajardo, Norma; Lopez, Irma; Sun, Zhaoxia; Koenekoop, Robert K; et al. (Genet Med, 2016)
PURPOSE: Leber congenital amaurosis (LCA) is an early-onset form of retinal degeneration. Six of the 22 known LCA genes encode photoreceptor ciliary proteins. Despite the identification of 22 LCA genes, the genetic basis of ~30% of LCA patients remains unknown. We sought to investigate the cause of disease in the remaining 30% by examining cilia-associated genes. METHODS: Whole-exome sequencing was performed on an LCA cohort of 212 unsolved probands previously screened for mutations in known retinal-disease genes. Immunohistochemistry using mouse retinas was used to confirm protein localization and zebrafish were used to perform rescue experiments. RESULTS: A homozygous nonsynonymous mutation was found in a single proband in CLUAP1, a gene required for ciliogenesis and cilia maintenance. Cluap1 knockout zebrafish exhibit photoreceptor cell death as early as 5 days after fertilization, and rescue experiments revealed that our proband's mutation is significantly hypomorphic. CONCLUSION: Consistent with the knowledge that CLUAP1 plays an important role in cilia function and that cilia are critical to photoreceptor function, our results indicate that hypomorphic mutations in CLUAP1 can result in dysfunctional photoreceptors without systemic abnormalities. This is the first report linking mutations in CLUAP1 to human disease and establishes CLUAP1 as a candidate LCA gene.Genet Med 18 10, 1044-1051.
Keywords: Animals; Antigens, Neoplasm; Child, Preschool; Cilia; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Leber Congenital Amaurosis; Male; Mutation; Photoreceptor Cells; Retinal Degeneration; Zebrafish

Identification of a RAI1-associated disease network through integration of exome sequencing, transcriptomics, and 3D genomics. - Loviglio, Maria Nicla; Beck, Christine R; White, Janson J; Leleu, Marion; Harel, Tamar; Guex, Nicolas; Niknejad, Anne; Bi, Weimin; Chen, Edward S; Crespo, Isaac; Yan, Jiong; Charng, Wu-Lin; et al. (Genome Med, 2016)
BACKGROUND: Smith-Magenis syndrome (SMS) is a developmental disability/multiple congenital anomaly disorder resulting from haploinsufficiency of RAI1. It is characterized by distinctive facial features, brachydactyly, sleep disturbances, and stereotypic behaviors. METHODS: We investigated a cohort of 15 individuals with a clinical suspicion of SMS who showed neither deletion in the SMS critical region nor damaging variants in RAI1 using whole exome sequencing. A combination of network analysis (co-expression and biomedical text mining), transcriptomics, and circularized chromatin conformation capture (4C-seq) was applied to verify whether modified genes are part of the same disease network as known SMS-causing genes. RESULTS: Potentially deleterious variants were identified in nine of these individuals using whole-exome sequencing. Eight of these changes affect KMT2D, ZEB2, MAP2K2, GLDC, CASK, MECP2, KDM5C, and POGZ, known to be associated with Kabuki syndrome 1, Mowat-Wilson syndrome, cardiofaciocutaneous syndrome, glycine encephalopathy, mental retardation and microcephaly with pontine and cerebellar hypoplasia, X-linked mental retardation 13, X-linked mental retardation Claes-Jensen type, and White-Sutton syndrome, respectively. The ninth individual carries a de novo variant in JAKMIP1, a regulator of neuronal translation that was recently found deleted in a patient with autism spectrum disorder. Analyses of co-expression and biomedical text mining suggest that these pathologies and SMS are part of the same disease network. Further support for this hypothesis was obtained from transcriptome profiling that showed that the expression levels of both Zeb2 and Map2k2 are perturbed in Rai1 mice. As an orthogonal approach to potentially contributory disease gene variants, we used chromatin conformation capture to reveal chromatin contacts between RAI1 and the loci flanking ZEB2 and GLDC, as well as between RAI1 and human orthologs of the genes that show perturbed expression in our Rai1 mouse model. CONCLUSIONS: These holistic studies of RAI1 and its interactions allow insights into SMS and other disorders associated with intellectual disability and behavioral abnormalities. Our findings support a pan-genomic approach to the molecular diagnosis of a distinctive disorder.
Keywords: Animals; Embryo, Mammalian; Exome; Female; Gene Regulatory Networks; Genomics; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors; Transcriptome

Identification of Rare Variants in Metabolites of the Carnitine Pathway by Whole Genome Sequencing Analysis. - Yazdani, Akram; Yazdani, Azam; Liu, Xiaoming; Eric Boerwinkle (Genet Epidemiol, 2016)
We use whole genome sequence data and rare variant analysis methods to investigate a subset of the human serum metabolome, including 16 carnitine-related metabolites that are important components of mammalian energy metabolism. Medium pass sequence data consisting of 12,820,347 rare variants and serum metabolomics data were available on 1,456 individuals. By applying a penalization method, we identified two genes FGF8 and MDGA2 with significant effects on lysine and cis-4-decenoylcarnitine, respectively, using Δ-AIC and likelihood ratio test statistics. Single variant analyses in these regions did not identify a single low-frequency variant (minor allele count > 3) responsible for the underlying signal. The results demonstrate the utility of whole genome sequence and innovative analyses for identifying candidate regions influencing complex phenotypes.
Keywords: Biomarkers; Carnitine; Female; Fibroblast Growth Factor 8; Genetic Variation; GPI-Linked Proteins; High-Throughput Nucleotide Sequencing; Humans; Linkage Disequilibrium; Lysine; Male; Metabolomics; Middle Aged; Neural Cell Adhesion Molecules; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

The impact of multiple single day blood pressure readings on cardiovascular risk estimation: The Atherosclerosis Risk in Communities study. - Ogunwale, Abayomi N; Morrison, Alanna C; Sun, Wensheng; Dodge, Rhiannon C; Virani, Salim S; Taylor, Addison; Gottesman, Rebecca F; Yang, Eric; Wei, Peng; McEvoy, John W; Heiss, Gerardo; Eric Boerwinkle; et al. (Eur J Prev Cardiol, 2016)
AIMS: The aim of this study was to determine the magnitude of change in estimated cardiovascular disease risk when multiple same day blood pressure measurements are used in estimating coronary heart disease, heart failure and stroke risks. METHODS AND RESULTS: Black and White participants, N = 11,129, enrolled in the Atherosclerosis Risk in Communities study (mean age 53.9 ± 5.7 (SD) years) were included. Each participant had three sitting, five supine, and six standing blood pressure measures during one day. Main outcome measures were changes in estimated coronary heart disease, heart failure and stroke risk when using the different blood pressure measures. Mean sitting, standing and supine systolic blood pressure values of the study population were 120.8 ± 18.6, 124.9 ± 20 and 124.7 ± 19.6 mmHg, respectively. The substitution of the second sitting systolic blood pressure with the third sitting systolic blood pressure (taken ∼5 min later) in two separate coronary heart disease risk models reclassified 3.3% to 5.1% of study participants. Similar substitutions for heart failure and stroke risk prediction models led to reclassification of 1.9% and 2.7% of participants respectively. When mean sitting systolic blood pressure was replaced with mean standing systolic blood pressure 5.4% to 11.6% of the participants were reclassified. Maximum upward and downward change in an individual's estimated risk was 31% and 26% respectively. CONCLUSIONS: Estimated risks of coronary heart disease, heart failure, and stroke for an individual can change significantly within a day due to changes in systolic blood pressure. Given recommendations to use estimated risk for therapeutic decisions, our study has implications for the use of a single systolic blood pressure in cardiovascular risk estimation.
Keywords: Atherosclerosis; Blood Pressure; Blood Pressure Determination; Cardiovascular Diseases; Female; Humans; Incidence; Male; Middle Aged; Risk Assessment; Risk Factors; United States

Isolated and Syndromic Retinal Dystrophy Caused by Biallelic Mutations in RCBTB1, a Gene Implicated in Ubiquitination. - Coppieters, Frauke; Ascari, Giulia; Dannhausen, Katharina; Nikopoulos, Konstantinos; Peelman, Frank; Karlstetter, Marcus; Xu, Mingchu; Brachet, Cécile; Meunier, Isabelle; Tsilimbaris, Miltiadis K; Tsika, Chrysanthi; Blazaki, Styliani V; et al. (Am J Hum Genet, 2016)
Inherited retinal dystrophies (iRDs) are a group of genetically and clinically heterogeneous conditions resulting from mutations in over 250 genes. Here, homozygosity mapping and whole-exome sequencing (WES) in a consanguineous family revealed a homozygous missense mutation, c.973C>T (p.His325Tyr), in RCBTB1. In affected individuals, it was found to segregate with retinitis pigmentosa (RP), goiter, primary ovarian insufficiency, and mild intellectual disability. Subsequent analysis of WES data in different cohorts uncovered four additional homozygous missense mutations in five unrelated families in whom iRD segregates with or without syndromic features. Ocular phenotypes ranged from typical RP starting in the second decade to chorioretinal dystrophy with a later age of onset. The five missense mutations affect highly conserved residues either in the sixth repeat of the RCC1 domain or in the BTB1 domain. A founder haplotype was identified for mutation c.919G>A (p.Val307Met), occurring in two families of Mediterranean origin. We showed ubiquitous mRNA expression of RCBTB1 and demonstrated predominant RCBTB1 localization in human inner retina. RCBTB1 was very recently shown to be involved in ubiquitination, more specifically as a CUL3 substrate adaptor. Therefore, the effect on different components of the CUL3 and NFE2L2 (NRF2) pathway was assessed in affected individuals' lymphocytes, revealing decreased mRNA expression of NFE2L2 and several NFE2L2 target genes. In conclusion, our study puts forward mutations in RCBTB1 as a cause of autosomal-recessive non-syndromic and syndromic iRD. Finally, our data support a role for impaired ubiquitination in the pathogenetic mechanism of RCBTB1 mutations.
Keywords: Adolescent; Adult; Age of Onset; Alleles; Child; Consanguinity; Cullin Proteins; Exome; Female; Founder Effect; Genes, Recessive; Guanine Nucleotide Exchange Factors; Haplotypes; Homozygote; Humans; Lymphocytes; Male; Mutation, Missense; NF-E2-Related Factor 2; Pedigree; Phenotype; Retina; Retinal Dystrophies; RNA, Messenger; Syndrome; Turkey; Ubiquitination

Loss-of-function variants influence the human serum metabolome. - Yu, Bing; Li, Alexander H; Ginger A Metcalf; Donna M Muzny; Morrison, Alanna C; White, Simon; Mosley, Thomas H; Richard A Gibbs; Eric Boerwinkle (Sci Adv, 2016)
The metabolome is a collection of small molecules resulting from multiple cellular and biological processes that can act as biomarkers of disease, and African-Americans exhibit high levels of genetic diversity. Exome sequencing of a sample of deeply phenotyped African-Americans allowed us to analyze the effects of annotated loss-of-function (LoF) mutations on 308 serum metabolites measured by untargeted liquid and gas chromatography coupled with mass spectrometry. In an independent sample, we identified and replicated four genes harboring six LoF mutations that significantly affected five metabolites. These sites were related to a 19 to 45% difference in geometric mean metabolite levels, with an average effect size of 25%. We show that some of the affected metabolites are risk predictors or diagnostic biomarkers of disease and, using the principle of Mendelian randomization, are in the causal pathway of disease. For example, LoF mutations in SLCO1B1 elevate the levels of hexadecanedioate, a fatty acid significantly associated with increased blood pressure levels and risk of incident heart failure in both African-Americans and an independent sample of European-Americans. We show that SLCO1B1 LoF mutations significantly increase the risk of incident heart failure, thus implicating the metabolite in the causal pathway of disease. These results reveal new avenues into gene function and the understanding of disease etiology by integrating -omic technologies into a deeply phenotyped population study.
Keywords: Aged; Biomarkers; Black or African American; Exome; Female; Genetic Variation; Heart Failure; High-Throughput Nucleotide Sequencing; Humans; Hypertension; Liver-Specific Organic Anion Transporter 1; Male; Metabolome; Middle Aged; Mutation; Risk Factors; White People

Mechanisms for Complex Chromosomal Insertions. - Gu, Shen; Szafranski, Przemyslaw; Akdemir, Zeynep Coban; Bo Yuan; Cooper, Mitchell L; Magriñá, Maria A; Bacino, Carlos A; Lalani, Seema R; Breman, Amy M; Smith, Janice L; Patel, Ankita; Song, Rodger H; et al. (PLoS Genet, 2016)
Chromosomal insertions are genomic rearrangements with a chromosome segment inserted into a non-homologous chromosome or a non-adjacent locus on the same chromosome or the other homologue, constituting ~2% of nonrecurrent copy-number gains. Little is known about the molecular mechanisms of their formation. We identified 16 individuals with complex insertions among 56,000 individuals tested at Baylor Genetics using clinical array comparative genomic hybridization (aCGH) and fluorescence in situ hybridization (FISH). Custom high-density aCGH was performed on 10 individuals with available DNA, and breakpoint junctions were fine-mapped at nucleotide resolution by long-range PCR and DNA sequencing in 6 individuals to glean insights into potential mechanisms of formation. We observed microhomologies and templated insertions at the breakpoint junctions, resembling the breakpoint junction signatures found in complex genomic rearrangements generated by replication-based mechanism(s) with iterative template switches. In addition, we analyzed 5 families with apparently balanced insertion in one parent detected by FISH analysis and found that 3 parents had additional small copy-number variants (CNVs) at one or both sides of the inserting fragments as well as at the inserted sites. We propose that replicative repair can result in interchromosomal complex insertions generated through chromothripsis-like chromoanasynthesis involving two or three chromosomes, and cause a significant fraction of apparently balanced insertions harboring small flanking CNVs.
Keywords: Chromosome Aberrations; Chromosome Inversion; Comparative Genomic Hybridization; DNA Copy Number Variations; DNA Replication; Female; Gene Duplication; Genome, Human; Humans; In Situ Hybridization, Fluorescence; Male; Sequence Analysis, DNA; Translocation, Genetic

Mechanisms for the Generation of Two Quadruplications Associated with Split-Hand Malformation. - Gu, Shen; Posey, Jennifer E; Bo Yuan; Carvalho, Claudia M B; Luk, H M; Erikson, Kelly; Lo, Ivan F M; Leung, Gordon K C; Pickering, Curtis R; Chung, Brian H Y; Lupski, James R (Hum Mutat, 2016)
Germline copy-number variants (CNVs) involving quadruplications are rare and the mechanisms generating them are largely unknown. Previously, we reported a 20-week gestation fetus with split-hand malformation; clinical microarray detected two maternally inherited triplications separated by a copy-number neutral region at 17p13.3, involving BHLHA9 and part of YWHAE. Here, we describe an 18-month-old male sibling of the previously described fetus with split-hand malformation. Custom high-density microarray and digital droplet PCR revealed the copy-number gains were actually quadruplications in the mother, the fetus, and her later born son. This quadruplication-normal-quadruplication pattern was shown to be expanded from the triplication-normal-triplication CNV at the same loci in the maternal grandmother. We mapped two breakpoint junctions and demonstrated that both are mediated by Alu repetitive elements and identical in these four individuals. We propose a three-step process combining Alu-mediated replicative-repair-based mechanism(s) and intergenerational, intrachromosomal nonallelic homologous recombination to generate the quadruplications in this family.
Keywords: 14-3-3 Proteins; Adult; Aged; Alu Elements; Base Sequence; Basic Helix-Loop-Helix Transcription Factors; Chromosome Duplication; Chromosomes, Human, Pair 17; DNA Copy Number Variations; Female; Genetic Loci; Genome, Human; Hand Deformities, Congenital; Humans; Infant; Male; Molecular Sequence Data; Pedigree; Sequence Alignment; Sequence Analysis, DNA

Meta-analysis of 49 549 individuals imputed with the 1000 Genomes Project reveals an exonic damaging variant in ANGPTL4 determining fasting TG levels. - van Leeuwen, Elisabeth M; Aniko Sabo; Bis, Joshua C; Huffman, Jennifer E; Manichaikul, Ani; Smith, Albert V; Feitosa, Mary F; Demissie, Serkalem; Joshi, Peter K; Duan, Qing; Marten, Jonathan; van Klinken, Jan B; et al. (J Med Genet, 2016)
BACKGROUND: So far, more than 170 loci have been associated with circulating lipid levels through genome-wide association studies (GWAS). These associations are largely driven by common variants, their function is often not known, and many are likely to be markers for the causal variants. In this study we aimed to identify more new rare and low-frequency functional variants associated with circulating lipid levels. METHODS: We used the 1000 Genomes Project as a reference panel for the imputations of GWAS data from ∼60 000 individuals in the discovery stage and ∼90 000 samples in the replication stage. RESULTS: Our study resulted in the identification of five new associations with circulating lipid levels at four loci. All four loci are within genes that can be linked biologically to lipid metabolism. One of the variants, rs116843064, is a damaging missense variant within the ANGPTL4 gene. CONCLUSIONS: This study illustrates that GWAS with high-scale imputation may still help us unravel the biological mechanism behind circulating lipid levels.
Keywords: Angiopoietin-Like Protein 4; Angiopoietins; Exons; Fasting; Female; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

MIPEP recessive variants cause a syndrome of left ventricular non-compaction, hypotonia, and infantile death. - Eldomery, Mohammad K; Akdemir, Zeynep C; Vögtle, F-Nora; Charng, Wu-Lin; Mulica, Patrycja; Rosenfeld, Jill A; Gambin, Tomasz; Gu, Shen; Burrage, Lindsay C; Al Shamsi, Aisha; Penney, Samantha; Jhangiani, Shalini N; et al. (Genome Med, 2016)
BACKGROUND: Mitochondrial presequence proteases perform fundamental functions as they process about 70 % of all mitochondrial preproteins that are encoded in the nucleus and imported posttranslationally. The mitochondrial intermediate presequence protease MIP/Oct1, which carries out precursor processing, has not yet been established to have a role in human disease. METHODS: Whole exome sequencing was performed on four unrelated probands with left ventricular non-compaction (LVNC), developmental delay (DD), seizures, and severe hypotonia. Proposed pathogenic variants were confirmed by Sanger sequencing or array comparative genomic hybridization. Functional analysis of the identified MIP variants was performed using the model organism Saccharomyces cerevisiae as the protein and its functions are highly conserved from yeast to human. RESULTS: Biallelic single nucleotide variants (SNVs) or copy number variants (CNVs) in MIPEP, which encodes MIP, were present in all four probands, three of whom had infantile/childhood death. Two patients had compound heterozygous SNVs (p.L582R/p.L71Q and p.E602*/p.L306F) and one patient from a consanguineous family had a homozygous SNV (p.K343E). The fourth patient, identified through the GeneMatcher tool, a part of the Matchmaker Exchange Project, was found to have inherited a paternal SNV (p.H512D) and a maternal CNV (1.4-Mb deletion of 13q12.12) that includes MIPEP. All amino acids affected in the patients' missense variants are highly conserved from yeast to human and therefore S. cerevisiae was employed for functional analysis (for p.L71Q, p.L306F, and p.K343E). The mutations p.L339F (human p.L306F) and p.K376E (human p.K343E) resulted in a severe decrease of Oct1 protease activity and accumulation of non-processed Oct1 substrates and consequently impaired viability under respiratory growth conditions. The p.L83Q (human p.L71Q) failed to localize to the mitochondria. CONCLUSIONS: Our findings reveal for the first time the role of the mitochondrial intermediate peptidase in human disease. Loss of MIP function results in a syndrome which consists of LVNC, DD, seizures, hypotonia, and cataracts. Our approach highlights the power of data exchange and the importance of an interrelationship between clinical and research efforts for disease gene discovery.
Keywords: Adult; Amino Acid Sequence; Female; Genes, Recessive; Heart Defects, Congenital; Humans; Infant; Infant, Newborn; Male; Metalloendopeptidases; Muscle Hypotonia; Pedigree; Phenotype; Sequence Homology, Amino Acid; Sudden Infant Death; Syndrome

Molecular and Clinical Findings in Patients With Knobloch Syndrome. - Hull, Sarah; Arno, Gavin; Ku, Cristy A; Ge, Zhongqi; Waseem, Naushin; Chandra, Aman; Webster, Andrew R; Robson, Anthony G; Michaelides, Michel; Weleber, Richard G; Davagnanam, Indran; Rui Chen; et al. (JAMA Ophthalmol, 2016)
IMPORTANCE: Knobloch syndrome is a rare, recessively inherited disorder classically characterized by high myopia, retinal detachment, and occipital encephalocele, but it is now known to have an increasingly variable phenotype. There is a lack of reported electrophysiologic data, and some key clinical features have yet to be described. OBJECTIVE: To expand on current clinical, electrophysiologic, and molecular genetic findings in Knobloch syndrome. DESIGN, SETTING, AND PARTICIPANTS: Twelve patients from 7 families underwent full ophthalmic examination and retinal imaging. Further investigations included electroretinography and neuroradiologic imaging. Bidirectional Sanger sequencing of COL18A1 was performed with segregation on available relatives. The study was conducted from July 4, 2013, to October 5, 2015. Data analysis was performed from May 20, 2014, to November 3, 2015. MAIN OUTCOMES AND MEASURES: Results of ophthalmic and neuroradiologic assessment and sequence analysis of COL18A1. RESULTS: Of the 12 patients (6 males; mean age at last review, 16 years [range, 2-38 years]), all had high myopia in at least 1 eye and severely reduced vision. A sibling pair had unilateral high myopia in their right eyes and near emmetropia in their left eyes from infancy. Anterior segment abnormalities included absent iris crypts, iris transillumination, lens subluxation, and cataract. Two patients with iris transillumination had glaucoma. Fundus characteristics included abnormal collapsed vitreous, macular atrophy, and a tesselated fundus. Five patients had previous retinal detachment. Electroretinography revealed a cone-rod pattern of dysfunction in 8 patients, was severely reduced or undetectable in 2 patients, and demonstrated cone-rod dysfunction in 1 eye with undetectable responses in the other eye in 2 patients. Radiologic imaging demonstrated occipital encephalocele or meningocele in 3 patients, occipital skull defects in 4 patients, minor occipital changes in 2 patients, and no abnormalities in 2 patients. Cutaneous scalp changes were present in 5 patients. Systemic associations were identified in 8 patients, including learning difficulties, epilepsy, and congenital renal abnormalities. Biallelic mutations including 2 likely novel mutations in COL18A1, were identified in 6 families that were consistent with autosomal recessive inheritance with a single mutation identified in a family with 2 affected children. CONCLUSIONS AND RELEVANCE: This report describes new features in patients with Knobloch syndrome, including pigment dispersion syndrome and glaucoma as well as cone-rod dysfunction on electroretinography. Two patients had normal neuroradiologic findings, emphasizing that some affected individuals have isolated ocular disease. Awareness of the ocular phenotype may aid early diagnosis, appropriate genetic counseling, and monitoring for potential complications.
Keywords: Adolescent; Adult; Child; Child, Preschool; Collagen Type VIII; Collagen Type XVIII; DNA Mutational Analysis; Electroretinography; Encephalocele; Exfoliation Syndrome; Exons; Female; Glaucoma, Open-Angle; Humans; Magnetic Resonance Imaging; Male; Molecular Biology; Mutation; Myopia, Degenerative; Pedigree; Photoreceptor Cells, Vertebrate; Polymerase Chain Reaction; Retinal Degeneration; Retinal Detachment; Vision Disorders; Young Adult

Molecular diagnostic experience of whole-exome sequencing in adult patients. - Posey, Jennifer E; Rosenfeld, Jill A; James, Regis A; Bainbridge, Matthew; Niu, Zhiyv; Wang, Xia; Dhar, Shweta; Wiszniewski, Wojciech; Akdemir, Zeynep H C; Gambin, Tomasz; Xia, Fan; Person, Richard E; et al. (Genet Med, 2016)
PURPOSE: Whole-exome sequencing (WES) is increasingly used as a diagnostic tool in medicine, but prior reports focus on predominantly pediatric cohorts with neurologic or developmental disorders. We describe the diagnostic yield and characteristics of WES in adults. METHODS: We performed a retrospective analysis of consecutive WES reports for adults from a diagnostic laboratory. Phenotype composition was determined using Human Phenotype Ontology terms. RESULTS: Molecular diagnoses were reported for 17.5% (85/486) of adults, which is lower than that for a primarily pediatric population (25.2%; P = 0.0003); the diagnostic rate was higher (23.9%) for those 18-30 years of age compared to patients older than 30 years (10.4%; P = 0.0001). Dual Mendelian diagnoses contributed to 7% of diagnoses, revealing blended phenotypes. Diagnoses were more frequent among individuals with abnormalities of the nervous system, skeletal system, head/neck, and growth. Diagnostic rate was independent of family history information, and de novo mutations contributed to 61.4% of autosomal dominant diagnoses. CONCLUSION: Early WES experience in adults demonstrates molecular diagnoses in a substantial proportion of patients, informing clinical management, recurrence risk, and recommendations for relatives. A positive family history was not predictive, consistent with molecular diagnoses often revealed by de novo events, informing the Mendelian basis of genetic disease in adults.Genet Med 18 7, 678-685.
Keywords: Adult; Exome; Female; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Testing; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Pathology, Molecular

Monoallelic and Biallelic Variants in EMC1 Identified in Individuals with Global Developmental Delay, Hypotonia, Scoliosis, and Cerebellar Atrophy. - Harel, Tamar; Yesil, Gozde; Bayram, Yavuz; Coban-Akdemir, Zeynep; Charng, Wu-Lin; Karaca, Ender; Al Asmari, Ali; Eldomery, Mohammad K; Hunter, Jill V; Jhangiani, Shalini N; Rosenfeld, Jill A; Pehlivan, Davut; et al. (Am J Hum Genet, 2016)
The paradigm of a single gene associated with one specific phenotype and mode of inheritance has been repeatedly challenged. Genotype-phenotype correlations can often be traced to different mutation types, localization of the variants in distinct protein domains, or the trigger of or escape from nonsense-mediated decay. Using whole-exome sequencing, we identified homozygous variants in EMC1 that segregated with a phenotype of developmental delay, hypotonia, scoliosis, and cerebellar atrophy in three families. In addition, a de novo heterozygous EMC1 variant was seen in an individual with a similar clinical and MRI imaging phenotype. EMC1 encodes a member of the endoplasmic reticulum (ER)-membrane protein complex (EMC), an evolutionarily conserved complex that has been proposed to have multiple roles in ER-associated degradation, ER-mitochondria tethering, and proper assembly of multi-pass transmembrane proteins. Perturbations of protein folding and organelle crosstalk have been implicated in neurodegenerative processes including cerebellar atrophy. We propose EMC1 as a gene in which either biallelic or monoallelic variants might lead to a syndrome including intellectual disability and preferential degeneration of the cerebellum.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Atrophy; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Endoplasmic Reticulum-Associated Degradation; Female; Genetic Association Studies; Genetic Variation; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Membrane Proteins; Molecular Sequence Data; Muscle Hypotonia; Mutation; Pedigree; Protein Folding; Proteins; Scoliosis

Mutations in POMGNT1 cause non-syndromic retinitis pigmentosa. - Xu, Mingchu; Yamada, Takeyuki; Sun, Zixi; Eblimit, Aiden; Lopez, Irma; Wang, Feng; Manya, Hiroshi; Xu, Shan; Zhao, Li; Yumei Li; Kimchi, Adva; Sharon, Dror; et al. (Hum Mol Genet, 2016)
A growing number of human diseases have been linked to defects in protein glycosylation that affects a wide range of organs. Among them, O-mannosylation is an unusual type of protein glycosylation that is largely restricted to the muscular and nerve system. Consistently, mutations in genes involved in the O-mannosylation pathway result in infantile-onset, severe developmental defects involving skeleton muscle, brain and eye, such as the muscle-eye-brain disease (MIM no. 253280). However, the functional importance of O-mannosylation in these tissues at later stages remains largely unknown. In our study, we have identified recessive mutations in POMGNT1, which encodes an essential component in O-mannosylation pathway, in three unrelated families with autosomal recessive retinitis pigmentosa (RP), but without extraocular involvement. Enzymatic assay of these mutant alleles demonstrate that they greatly reduce the POMGNT1 enzymatic activity and are likely to be hypomorphic. Immunohistochemistry shows that POMGNT1 is specifically expressed in photoreceptor basal body. Taken together, our work identifies a novel disease-causing gene for RP and indicates that proper protein O-mannosylation is not only essential for early organ development, but also important for maintaining survival and function of the highly specialized retinal cells at later stages.
Keywords: Adult; Aged; Animals; Cells, Cultured; Exome; Female; Genes, Recessive; Genetic Predisposition to Disease; Glycosylation; Humans; Male; Mice; Middle Aged; Mutation; N-Acetylglucosaminyltransferases; Pedigree; Photoreceptor Cells, Vertebrate; Retinitis Pigmentosa; Sequence Analysis, DNA

Mutations in REEP6 Cause Autosomal-Recessive Retinitis Pigmentosa. - Arno, Gavin; Agrawal, Smriti A; Eblimit, Aiden; Bellingham, James; Xu, Mingchu; Wang, Feng; Chakarova, Christina; Parfitt, David A; Lane, Amelia; Burgoyne, Thomas; Hull, Sarah; Carss, Keren J; et al. (Am J Hum Genet, 2016)
Retinitis pigmentosa (RP) is the most frequent form of inherited retinal dystrophy. RP is genetically heterogeneous and the genes identified to date encode proteins involved in a wide range of functional pathways, including photoreceptor development, phototransduction, the retinoid cycle, cilia, and outer segment development. Here we report the identification of biallelic mutations in Receptor Expression Enhancer Protein 6 (REEP6) in seven individuals with autosomal-recessive RP from five unrelated families. REEP6 is a member of the REEP/Yop1 family of proteins that influence the structure of the endoplasmic reticulum but is relatively unstudied. The six variants identified include three frameshift variants, two missense variants, and a genomic rearrangement that disrupts exon 1. Human 3D organoid optic cups were used to investigate REEP6 expression and confirmed the expression of a retina-specific isoform REEP6.1, which is specifically affected by one of the frameshift mutations. Expression of the two missense variants (c.383C>T [p.Pro128Leu] and c.404T>C [p.Leu135Pro]) and the REEP6.1 frameshift mutant in cultured cells suggest that these changes destabilize the protein. Furthermore, CRISPR-Cas9-mediated gene editing was used to produce Reep6 knock-in mice with the p.Leu135Pro RP-associated variant identified in one RP-affected individual. The homozygous knock-in mice mimic the clinical phenotypes of RP, including progressive photoreceptor degeneration and dysfunction of the rod photoreceptors. Therefore, our study implicates REEP6 in retinal homeostasis and highlights a pathway previously uncharacterized in retinal dystrophy.
Keywords: Adolescent; Alleles; Animals; Child; Child, Preschool; Eye Proteins; Female; Genes, Recessive; Humans; Induced Pluripotent Stem Cells; Male; Membrane Proteins; Membrane Transport Proteins; Mice; Mutation; Mutation, Missense; Phenotype; Photoreceptor Cells, Vertebrate; Retinitis Pigmentosa; Young Adult

Mutations in the nuclear bile acid receptor FXR cause progressive familial intrahepatic cholestasis. - Gomez-Ospina, Natalia; Potter, Carol J; Xiao, Rui; Manickam, Kandamurugu; Kim, Mi-Sun; Kim, Kang Ho; Shneider, Benjamin L; Picarsic, Jennifer L; Jacobson, Theodora A; Zhang, Jing; He, Weimin; Liu, Pengfei; et al. (Nat Commun, 2016)
Neonatal cholestasis is a potentially life-threatening condition requiring prompt diagnosis. Mutations in several different genes can cause progressive familial intrahepatic cholestasis, but known genes cannot account for all familial cases. Here we report four individuals from two unrelated families with neonatal cholestasis and mutations in NR1H4, which encodes the farnesoid X receptor (FXR), a bile acid-activated nuclear hormone receptor that regulates bile acid metabolism. Clinical features of severe, persistent NR1H4-related cholestasis include neonatal onset with rapid progression to end-stage liver disease, vitamin K-independent coagulopathy, low-to-normal serum gamma-glutamyl transferase activity, elevated serum alpha-fetoprotein and undetectable liver bile salt export pump (ABCB11) expression. Our findings demonstrate a pivotal function for FXR in bile acid homeostasis and liver protection.
Keywords: ATP Binding Cassette Transporter, Subfamily B, Member 11; ATP-Binding Cassette Transporters; Bile Acids and Salts; Cholestasis, Intrahepatic; Female; Humans; Male; Mutation; Receptors, Cytoplasmic and Nuclear; Young Adult

Next-generation sequencing-based molecular diagnosis of 12 inherited retinal disease probands of Uyghur ethnicity. - Tajiguli, Abulikemu; Xu, Mingchu; Fu, Qing; Yiming, Rouzimaimaiti; Wang, Keqing; Yumei Li; Eblimit, Aiden; Sui, Ruifang; Rui Chen; Aisa, Haji Akber (Sci Rep, 2016)
Inherited retinal disease (IRD) is a category of genetic disorders affecting retina. Understanding the molecular basis of IRD is vital for clinical and genetic classification of patients. Uyghur people is an isolated ethnic group mainly residing in northwestern China with genetic admixture from Europeans and East Asians. The genetic etiology of IRD in this specific population still remains unknown. Here, by next-generation sequencing (NGS), we screened mutations in over 200 known retinal disease genes in a cohort of 12 unrelated Uyghur IRD probands. Out of the 12 probands, six are solved with high confidence, two with low confidence, while the remaining four are unsolved. We identified known disease-causing alleles in this cohort that suggest ancient Uyghur migration and also discovered eight novel disease-associated variants. Our results showed NGS-based mutation screening as a reliable approach for molecular diagnosis. In addition, this approach can also be applied to reveal the genetic history of a specific ethnic group.
Keywords: Asian People; China; Female; Genetic Diseases, Inborn; High-Throughput Nucleotide Sequencing; Humans; Male; Retinal Diseases

Next-generation sequencing-based molecular diagnosis of 35 Hispanic retinitis pigmentosa probands. - Zhang, Qi; Xu, Mingchu; Verriotto, Jennifer D; Yumei Li; Wang, Hui; Gan, Lin; Lam, Byron L; Rui Chen (Sci Rep, 2016)
Retinitis pigmentosa (RP) is a heterogeneous group of inherited retinal diseases. The prevalence of RP and the mutation spectrum vary across populations. Hispanic people account for approximately 17% of the United States population, and the genetic etiologies of RP of this ethnic group still remain not well defined. Utilizing next-generation sequencing (NGS), we screened mutations in known retinal disease-causing genes in an RP cohort of 35 unrelated Hispanic probands from the Miami area. We achieved a solving rate of 66% and identified 15 novel putative pathogenic mutations, including a frequent founder mutation disrupting PRPF31 splicing. Our data show that the mutation spectrum of Hispanic RP receives a significant impact from disease-causing alleles of Spanish origin and may also contain population-specific alleles.
Keywords: Alleles; Eye Proteins; Female; High-Throughput Nucleotide Sequencing; Hispanic or Latino; Humans; Male; Mutation; Pedigree; Retinitis Pigmentosa; RNA Splicing

Nonrecurrent PMP22-RAI1 contiguous gene deletions arise from replication-based mechanisms and result in Smith-Magenis syndrome with evident peripheral neuropathy. - Bo Yuan; Neira, Juanita; Gu, Shen; Harel, Tamar; Liu, Pengfei; Briceño, Ignacio; Sarah H Elsea; Gómez, Alberto; Potocki, Lorraine; Lupski, James R (Hum Genet, 2016)
Hereditary neuropathy with liability to pressure palsies (HNPP) and Smith-Magenis syndrome (SMS) are genomic disorders associated with deletion copy number variants involving chromosome 17p12 and 17p11.2, respectively. Nonallelic homologous recombination (NAHR)-mediated recurrent deletions are responsible for the majority of HNPP and SMS cases; the rearrangement products encompass the key dosage-sensitive genes PMP22 and RAI1, respectively, and result in haploinsufficiency for these genes. Less frequently, nonrecurrent genomic rearrangements occur at this locus. Contiguous gene duplications encompassing both PMP22 and RAI1, i.e., PMP22-RAI1 duplications, have been investigated, and replication-based mechanisms rather than NAHR have been proposed for these rearrangements. In the current study, we report molecular and clinical characterizations of six subjects with the reciprocal phenomenon of deletions spanning both genes, i.e., PMP22-RAI1 deletions. Molecular studies utilizing high-resolution array comparative genomic hybridization and breakpoint junction sequencing identified mutational signatures that were suggestive of replication-based mechanisms. Systematic clinical studies revealed features consistent with SMS, including features of intellectual disability, speech and gross motor delays, behavioral problems and ocular abnormalities. Five out of six subjects presented clinical signs and/or objective electrophysiologic studies of peripheral neuropathy. Clinical profiling may improve the clinical management of this unique group of subjects, as the peripheral neuropathy can be more severe or of earlier onset as compared to SMS patients having the common recurrent deletion. Moreover, the current study, in combination with the previous report of PMP22-RAI1 duplications, contributes to the understanding of rare complex phenotypes involving multiple dosage-sensitive genes from a genetic mechanistic standpoint.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromosomes, Human, Pair 17; DNA Copy Number Variations; DNA Replication; Female; Gene Deletion; Haploinsufficiency; Homologous Recombination; Humans; Intellectual Disability; Male; Mutation; Myelin Proteins; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors

Novel genetic causes for cerebral visual impairment. - Bosch, Daniëlle G M; Boonstra, F Nienke; de Leeuw, Nicole; Pfundt, Rolph; Nillesen, Willy M; de Ligt, Joep; Gilissen, Christian; Jhangiani, Shalini; Lupski, James R; Cremers, Frans P M; de Vries, Bert B A (Eur J Hum Genet, 2016)
Cerebral visual impairment (CVI) is a major cause of low vision in children due to impairment in projection and/or interpretation of the visual input in the brain. Although acquired causes for CVI are well known, genetic causes underlying CVI are largely unidentified. DNAs of 25 patients with CVI and intellectual disability, but without acquired (eg, perinatal) damage, were investigated by whole-exome sequencing. The data were analyzed for de novo, autosomal-recessive, and X-linked variants, and subsequently classified into known, candidate, or unlikely to be associated with CVI. This classification was based on the Online Mendelian Inheritance in Man database, literature reports, variant characteristics, and functional relevance of the gene. After classification, variants in four genes known to be associated with CVI (AHDC1, NGLY1, NR2F1, PGAP1) in 5 patients (20%) were identified, establishing a conclusive genetic diagnosis for CVI. In addition, in 11 patients (44%) with CVI, variants in one or more candidate genes were identified (ACP6, AMOT, ARHGEF10L, ATP6V1A, DCAF6, DLG4, GABRB2, GRIN1, GRIN2B, KCNQ3, KCTD19, RERE, SLC1A1, SLC25A16, SLC35A2, SOX5, UFSP2, UHMK1, ZFP30). Our findings show that diverse genetic causes underlie CVI, some of which will provide insight into the biology underlying this disease process.
Keywords: Adolescent; Blindness, Cortical; Child; Child, Preschool; Female; Genetic Loci; Humans; Male; Polymorphism, Single Nucleotide; Young Adult

Novel mutations in LRP6 highlight the role of WNT signaling in tooth agenesis. - Ockeloen, Charlotte W; Khandelwal, Kriti D; Dreesen, Karoline; Ludwig, Kerstin U; Sullivan, Robert; van Rooij, Iris A L M; Thonissen, Michelle; Swinnen, Steven; Phan, Milien; Conte, Federica; Ishorst, Nina; Gilissen, Christian; et al. (Genet Med, 2016)
PURPOSE: We aimed to identify a novel genetic cause of tooth agenesis (TA) and/or orofacial clefting (OFC) by combining whole-exome sequencing (WES) and targeted resequencing in a large cohort of TA and OFC patients. METHODS: WES was performed in two unrelated patients: one with severe TA and OFC and another with severe TA only. After deleterious mutations were identified in a gene encoding low-density lipoprotein receptor-related protein 6 (LRP6), all its exons were resequenced with molecular inversion probes in 67 patients with TA, 1,072 patients with OFC, and 706 controls. RESULTS: We identified a frameshift (c.4594delG, p.Cys1532fs) and a canonical splice-site mutation (c.3398-2A>C, p.?) in LRP6, respectively, in the patient with TA and OFC and in the patient with severe TA only. The targeted resequencing showed significant enrichment of unique LRP6 variants in TA patients but not in nonsyndromic OFC patients. Of the five variants in patients with TA, two affected the canonical splice site and three were missense variants; all variants segregated with the dominant phenotype, and in one case the missense mutation occurred de novo. CONCLUSION: Mutations in LRP6 cause TA in humans.Genet Med 18 11, 1158-1162.
Keywords: Adolescent; Anodontia; Child; Exome; Female; Frameshift Mutation; Genetic Predisposition to Disease; Humans; Low Density Lipoprotein Receptor-Related Protein-6; Male; Mutation, Missense; Pedigree; Sequence Analysis, DNA; Wnt Signaling Pathway

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins. - Szafranski, Przemyslaw; Gambin, Tomasz; Dharmadhikari, Avinash V; Akdemir, Kadir Caner; Jhangiani, Shalini N; Schuette, Jennifer; Godiwala, Nihal; Yatsenko, Svetlana A; Sebastian, Jessica; Madan-Khetarpal, Suneeta; Surti, Urvashi; Abellar, Rosanna G; et al. (Hum Genet, 2016)
Alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV) is a lethal lung developmental disorder caused by heterozygous point mutations or genomic deletion copy-number variants (CNVs) of FOXF1 or its upstream enhancer involving fetal lung-expressed long noncoding RNA genes LINC01081 and LINC01082. Using custom-designed array comparative genomic hybridization, Sanger sequencing, whole exome sequencing (WES), and bioinformatic analyses, we studied 22 new unrelated families (20 postnatal and two prenatal) with clinically diagnosed ACDMPV. We describe novel deletion CNVs at the FOXF1 locus in 13 unrelated ACDMPV patients. Together with the previously reported cases, all 31 genomic deletions in 16q24.1, pathogenic for ACDMPV, for which parental origin was determined, arose de novo with 30 of them occurring on the maternally inherited chromosome 16, strongly implicating genomic imprinting of the FOXF1 locus in human lungs. Surprisingly, we have also identified four ACDMPV families with the pathogenic variants in the FOXF1 locus that arose on paternal chromosome 16. Interestingly, a combination of the severe cardiac defects, including hypoplastic left heart, and single umbilical artery were observed only in children with deletion CNVs involving FOXF1 and its upstream enhancer. Our data demonstrate that genomic imprinting at 16q24.1 plays an important role in variable ACDMPV manifestation likely through long-range regulation of FOXF1 expression, and may be also responsible for key phenotypic features of maternal uniparental disomy 16. Moreover, in one family, WES revealed a de novo missense variant in ESRP1, potentially implicating FGF signaling in the etiology of ACDMPV.
Keywords: Chromosomes, Human, Pair 16; Comparative Genomic Hybridization; Female; Forkhead Transcription Factors; Genes, Lethal; Genome, Human; Genomic Imprinting; High-Throughput Nucleotide Sequencing; Humans; Infant, Newborn; Male; Pedigree; Persistent Fetal Circulation Syndrome; Pulmonary Alveoli; Pulmonary Veins; Sequence Deletion

PEHO Syndrome May Represent Phenotypic Expansion at the Severe End of the Early-Onset Encephalopathies. - Gawlinski, Pawel; Posmyk, Renata; Gambin, Tomasz; Sielicka, Danuta; Chorazy, Monika; Nowakowska, Beata; Jhangiani, Shalini N; Donna M Muzny; Bekiesinska-Figatowska, Monika; Bal, Jerzy; Eric Boerwinkle; Richard A Gibbs; et al. (Pediatr Neurol, 2016)
BACKGROUND: Progressive encephalopathy with edema, hypsarrhythmia and optic atrophy (PEHO) syndrome is a distinct neurodevelopmental disorder. Patients without optic nerve atrophy and brain imaging abnormalities but fulfilling other PEHO criteria are often described as a PEHO-like syndrome. The molecular bases of both clinically defined conditions remain unknown in spite of the widespread application of genome analyses in both clinic and research. METHODS: We enrolled two patients with a prior diagnosis of PEHO and two individuals with PEHO-like syndrome. All four individuals subsequently underwent whole-exome sequencing and comprehensive genomic analysis. RESULTS: We identified disease-causing mutations in known genes associated with neurodevelopmental disorders including GNAO1 and CDKL5 in two of four individuals. One patient with PEHO syndrome and a de novoGNAO1 mutation was found to have an additional de novo mutation in HESX1 that is associated with optic atrophy. CONCLUSIONS: We hypothesize that PEHO and PEHO-like syndrome may represent a severe end of the spectrum of the early-onset encephalopathies and, in some instances, its complex phenotype may result from an aggregated effect of mutations at two loci.
Keywords: Brain Edema; Child; Child, Preschool; Female; GTP-Binding Protein alpha Subunits, Gi-Go; Humans; Infant; Male; Mutation; Neurodegenerative Diseases; Optic Atrophy; Phenotype; Protein Serine-Threonine Kinases; Spasms, Infantile

Platelet-Related Variants Identified by Exomechip Meta-analysis in 157,293 Individuals. - Eicher, John D; Chami, Nathalie; Kacprowski, Tim; Nomura, Akihiro; Chen, Ming-Huei; Yanek, Lisa R; Tajuddin, Salman M; Schick, Ursula M; Slater, Andrew J; Pankratz, Nathan; Polfus, Linda; Schurmann, Claudia; et al. (Am J Hum Genet, 2016)
Platelet production, maintenance, and clearance are tightly controlled processes indicative of platelets' important roles in hemostasis and thrombosis. Platelets are common targets for primary and secondary prevention of several conditions. They are monitored clinically by complete blood counts, specifically with measurements of platelet count (PLT) and mean platelet volume (MPV). Identifying genetic effects on PLT and MPV can provide mechanistic insights into platelet biology and their role in disease. Therefore, we formed the Blood Cell Consortium (BCX) to perform a large-scale meta-analysis of Exomechip association results for PLT and MPV in 157,293 and 57,617 individuals, respectively. Using the low-frequency/rare coding variant-enriched Exomechip genotyping array, we sought to identify genetic variants associated with PLT and MPV. In addition to confirming 47 known PLT and 20 known MPV associations, we identified 32 PLT and 18 MPV associations not previously observed in the literature across the allele frequency spectrum, including rare large effect (FCER1A), low-frequency (IQGAP2, MAP1A, LY75), and common (ZMIZ2, SMG6, PEAR1, ARFGAP3/PACSIN2) variants. Several variants associated with PLT/MPV (PEAR1, MRVI1, PTGES3) were also associated with platelet reactivity. In concurrent BCX analyses, there was overlap of platelet-associated variants with red (MAP1A, TMPRSS6, ZMIZ2) and white (PEAR1, ZMIZ2, LY75) blood cell traits, suggesting common regulatory pathways with shared genetic architecture among these hematopoietic lineages. Our large-scale Exomechip analyses identified previously undocumented associations with platelet traits and further indicate that several complex quantitative hematological, lipid, and cardiovascular traits share genetic factors.
Keywords: Blood Platelets; Exome; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Mean Platelet Volume; Platelet Count

POGZ truncating alleles cause syndromic intellectual disability. - White, Janson; Beck, Christine R; Harel, Tamar; Posey, Jennifer E; Jhangiani, Shalini N; Tang, Sha; Farwell, Kelly D; Powis, Zöe; Mendelsohn, Nancy J; Baker, Janice A; Pollack, Lynda; Mason, Kati J; et al. (Genome Med, 2016)
BACKGROUND: Large-scale cohort-based whole exome sequencing of individuals with neurodevelopmental disorders (NDDs) has identified numerous novel candidate disease genes; however, detailed phenotypic information is often lacking in such studies. De novo mutations in pogo transposable element with zinc finger domain (POGZ) have been identified in six independent and diverse cohorts of individuals with NDDs ranging from autism spectrum disorder to developmental delay. METHODS: Whole exome sequencing was performed on five unrelated individuals. Sanger sequencing was used to validate variants and segregate mutations with the phenotype in available family members. RESULTS: We identified heterozygous truncating mutations in POGZ in five unrelated individuals, which were confirmed to be de novo or not present in available parental samples. Careful review of the phenotypes revealed shared features that included developmental delay, intellectual disability, hypotonia, behavioral abnormalities, and similar facial characteristics. Variable features included short stature, microcephaly, strabismus and hearing loss. CONCLUSIONS: While POGZ has been associated with neurodevelopmental disorders in large cohort studies, our data suggest that loss of function variants in POGZ lead to an identifiable syndrome of NDD with specific phenotypic traits. This study exemplifies the era of human reverse clinical genomics ushered in by large disease-directed cohort studies; first defining a new syndrome molecularly and, only subsequently, phenotypically.
Keywords: Adolescent; Adult; Alleles; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Sequence Analysis, DNA; Transposases

Postmortem genetic screening for the identification, verification, and reporting of genetic variants contributing to the sudden death of the young. - Methner, D Nicole R; Steven E Scherer; Welch, Katherine; Walkiewicz, Magdalena; Eng, Christine M; Belmont, John W; Powell, Mark C; Korchina, Viktoriya; Harshavardhan Doddapaneni; Donna M Muzny; Richard A Gibbs; Wolf, Dwayne A; et al. (Genome Res, 2016)
Each year in the United States, thousands of cases of sudden and unexpected deaths of infants, children, and young adults are assigned an undetermined cause of death after postmortem investigation and autopsy. Heritable genetic variants have been suggested as the cause of up to a third of sudden death (SD) cases. Elucidation of the genetic variants involved in SD cases is important to not only help establish cause and manner of death of these individuals, but to also aid in determining whether familial genetic testing should be considered. Previously, these types of postmortem screenings have not been a feasible option for most county medical examiners' and coroners' offices. We sequenced full exons of 64 genes associated with SD in the largest known cohort (351) of infant and young SD decedents using massively parallel sequencing at <$600 per sample. Genetic variants were assessed through literature review and clinical evaluation by a multidisciplinary consortium of experts. Thirteen individuals (3.7%), eight infants (2.8% of those <1 yr of age) and five children/young adults (7.0% of those >1 yr of age), were found to have a reportable genetic variant contributing to SD. These percentages represent an estimate lower than those previously reported. Overall yields and results likely vary between studies due to differences in evaluation techniques and reporting. Additionally, we recommend ongoing assessment of data, including nonreported novel variants, as technology and literature continually advance. This study demonstrates a strategy to implement molecular autopsies in medicolegal investigations of young SD decedents.
Keywords: Adolescent; Adult; Autopsy; Cardiomyopathies; Child; Child, Preschool; Death, Sudden; Diagnosis; Female; Genetic Testing; Genetic Variation; Humans; Infant; Infant, Newborn; Male; United States; Young Adult

Predictive Value of Antiviral Effects in the Development of Hepatocellular Carcinoma in the General Korean Population with Chronic Hepatitis B. - Shim, Jae-Jun; Oh, In Hwan; Kim, Sang Bae; Kim, Jung Wook; Lee, Chang Kyun; Jang, Jae Young; Lee, Ju-Seog; Kim, Byung-Ho (Gut Liver, 2016)
BACKGROUND/AIMS: The benefit of oral antiviral therapy in preventing hepatocellular carcinoma (HCC) in the general population is not well understood. We used a novel prediction method to estimate the risk of HCC in the Korean population based on various treatment guidelines. METHODS: The 5-year risk of HCC following antiviral therapy was calculated using an HCC risk prediction model. A virtual cohort that represented Koreans (>40 years old) with chronic hepatitis B virus (HBV) infection was established using the fifth National Health and Nutrition Examination Survey. The antiviral indications tested were the Korean National Health Insurance (NHI) and European Association for the Study of the Liver (EASL) guidelines as well as a new extended indication (serum HBV DNA >2,000 IU/mL regardless of serum aminotransferase level). RESULTS: A total of 993,872 subjects were infected with HBV in the general Korean population. Over a 5-year period, 2,725 HCC cases were predicted per 100,000 persons (0.55%/yr). When the cohort was treated based on the Korean NHI, the EASL, and the newly extended indications, HCC risks decreased to 2,531 (-7.1%), 2,089 (-23.3%), and 1,122 (-58.8%) cases per 100,000 persons, respectively (p<0.0001). CONCLUSIONS: Simulated risk prediction suggests that extending of oral antiviral indication may reduce the HCC risk in the general population.
Keywords: Adult; Antiviral Agents; Carcinoma, Hepatocellular; DNA, Viral; Female; Hepatitis B virus; Hepatitis B, Chronic; Humans; Liver Neoplasms; Male; Middle Aged; Nutrition Surveys; Predictive Value of Tests; Republic of Korea; Risk Assessment; Risk Factors; Transaminases

Rare Exome Sequence Variants in CLCN6 Reduce Blood Pressure Levels and Hypertension Risk. - Yu, Bing; Pulit, Sara L; Hwang, Shih-Jen; Brody, Jennifer A; Amin, Najaf; Auer, Paul L; Bis, Joshua C; Eric Boerwinkle; Burke, Gregory L; Chakravarti, Aravinda; Correa, Adolfo; Dreisbach, Albert W; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: Rare genetic variants influence blood pressure (BP). METHODS AND RESULTS: Whole-exome sequencing was performed on DNA samples from 17 956 individuals of European ancestry and African ancestry (14 497, first-stage discovery and 3459, second-stage discovery) to examine the effect of rare variants on hypertension and 4 BP traits: systolic BP, diastolic BP, pulse pressure, and mean arterial pressure. Tests of ≈170 000 common variants (minor allele frequency, ≥1%; statistical significance, P≤2.9×10(-7)) and gene-based tests of rare variants (minor allele frequency, <1%; ≈17 000 genes; statistical significance, P≤1.5×10(-6)) were evaluated for each trait and ancestry, followed by multiethnic meta-analyses. In the first-stage discovery, rare coding variants (splicing, stop-gain, stop-loss, nonsynonymous variants, or indels) in CLCN6 were associated with lower diastolic BP (cumulative minor allele frequency, 1.3%; β=-3.20; P=4.1×10(-6)) and were independent of a nearby common variant (rs17367504) previously associated with BP. CLCN6 rare variants were also associated with lower systolic BP (β=-4.11; P=2.8×10(-4)), mean arterial pressure (β=-3.50; P=8.9×10(-6)), and reduced hypertension risk (odds ratio, 0.72; P=0.017). Meta-analysis of the 2-stage discovery samples showed that CLCN6 was associated with lower diastolic BP at exome-wide significance (cumulative minor allele frequency, 1.1%; β=-3.30; P=5.0×10(-7)). CONCLUSIONS: These findings implicate the effect of rare coding variants in CLCN6 in BP variation and offer new insights into BP regulation.
Keywords: Alleles; Black People; Blood Pressure; Chloride Channels; Exome; Female; Gene Frequency; Humans; Hypertension; Male; Risk Factors; White People

Rare Functional Variant in TM2D3 is Associated with Late-Onset Alzheimer's Disease. - Jakobsdottir, Johanna; van der Lee, Sven J; Bis, Joshua C; Chouraki, Vincent; Li-Kroeger, David; Yamamoto, Shinya; Grove, Megan L; Naj, Adam; Vronskaya, Maria; Salazar, Jose L; DeStefano, Anita L; Brody, Jennifer A; et al. (PLoS Genet, 2016)
We performed an exome-wide association analysis in 1393 late-onset Alzheimer's disease (LOAD) cases and 8141 controls from the CHARGE consortium. We found that a rare variant (P155L) in TM2D3 was enriched in Icelanders (~0.5% versus <0.05% in other European populations). In 433 LOAD cases and 3903 controls from the Icelandic AGES sub-study, P155L was associated with increased risk and earlier onset of LOAD [odds ratio (95% CI) = 7.5 (3.5-15.9), p = 6.6x10-9]. Mutation in the Drosophila TM2D3 homolog, almondex, causes a phenotype similar to loss of Notch/Presenilin signaling. Human TM2D3 is capable of rescuing these phenotypes, but this activity is abolished by P155L, establishing it as a functionally damaging allele. Our results establish a rare TM2D3 variant in association with LOAD susceptibility, and together with prior work suggests possible links to the β-amyloid cascade.
Keywords: Age of Onset; Aged; Alleles; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Apolipoproteins E; Drosophila melanogaster; Drosophila Proteins; Exome; Female; Genome-Wide Association Study; Genomics; Humans; Iceland; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Mutation; Phenotype; Receptors, Notch; Tropomyosin; White People

Recurrent De Novo and Biallelic Variation of ATAD3A, Encoding a Mitochondrial Membrane Protein, Results in Distinct Neurological Syndromes. - Harel, Tamar; Yoon, Wan Hee; Garone, Caterina; Gu, Shen; Coban-Akdemir, Zeynep; Eldomery, Mohammad K; Posey, Jennifer E; Jhangiani, Shalini N; Rosenfeld, Jill A; Cho, Megan T; Fox, Stephanie; Withers, Marjorie; et al. (Am J Hum Genet, 2016)
ATPase family AAA-domain containing protein 3A (ATAD3A) is a nuclear-encoded mitochondrial membrane protein implicated in mitochondrial dynamics, nucleoid organization, protein translation, cell growth, and cholesterol metabolism. We identified a recurrent de novo ATAD3A c.1582C>T (p.Arg528Trp) variant by whole-exome sequencing (WES) in five unrelated individuals with a core phenotype of global developmental delay, hypotonia, optic atrophy, axonal neuropathy, and hypertrophic cardiomyopathy. We also describe two families with biallelic variants in ATAD3A, including a homozygous variant in two siblings, and biallelic ATAD3A deletions mediated by nonallelic homologous recombination (NAHR) between ATAD3A and gene family members ATAD3B and ATAD3C. Tissue-specific overexpression of bor, the Drosophila mutation homologous to the human c.1582C>T (p.Arg528Trp) variant, resulted in a dramatic decrease in mitochondrial content, aberrant mitochondrial morphology, and increased autophagy. Homozygous null bor larvae showed a significant decrease of mitochondria, while overexpression of bor resulted in larger, elongated mitochondria. Finally, fibroblasts of an affected individual exhibited increased mitophagy. We conclude that the p.Arg528Trp variant functions through a dominant-negative mechanism that results in small mitochondria that trigger mitophagy, resulting in a reduction in mitochondrial content. ATAD3A variation represents an additional link between mitochondrial dynamics and recognizable neurological syndromes, as seen with MFN2, OPA1, DNM1L, and STAT2 mutations.
Keywords: Adenosine Triphosphatases; Adult; Alleles; Animals; ATPases Associated with Diverse Cellular Activities; Axons; Cardiomyopathies; Child; Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Drosophila melanogaster; Female; Fibroblasts; Homozygote; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Muscle Hypotonia; Muscles; Mutation; Nervous System Diseases; Neurons; Optic Atrophy; Phenotype; Polymorphism, Single Nucleotide; Syndrome; Young Adult

Recurrent Muscle Weakness with Rhabdomyolysis, Metabolic Crises, and Cardiac Arrhythmia Due to Bi-allelic TANGO2 Mutations. - Lalani, Seema R; Liu, Pengfei; Rosenfeld, Jill A; Watkin, Levi B; Chiang, Theodore; Leduc, Magalie S; Zhu, Wenmiao; Ding, Yan; Pan, Shujuan; Vetrini, Francesco; Miyake, Christina Y; Shinawi, Marwan; et al. (Am J Hum Genet, 2016)
The underlying genetic etiology of rhabdomyolysis remains elusive in a significant fraction of individuals presenting with recurrent metabolic crises and muscle weakness. Using exome sequencing, we identified bi-allelic mutations in TANGO2 encoding transport and Golgi organization 2 homolog (Drosophila) in 12 subjects with episodic rhabdomyolysis, hypoglycemia, hyperammonemia, and susceptibility to life-threatening cardiac tachyarrhythmias. A recurrent homozygous c.460G>A (p.Gly154Arg) mutation was found in four unrelated individuals of Hispanic/Latino origin, and a homozygous ∼34 kb deletion affecting exons 3-9 was observed in two families of European ancestry. One individual of mixed Hispanic/European descent was found to be compound heterozygous for c.460G>A (p.Gly154Arg) and the deletion of exons 3-9. Additionally, a homozygous exons 4-6 deletion was identified in a consanguineous Middle Eastern Arab family. No homozygotes have been reported for these changes in control databases. Fibroblasts derived from a subject with the recurrent c.460G>A (p.Gly154Arg) mutation showed evidence of increased endoplasmic reticulum stress and a reduction in Golgi volume density in comparison to control. Our results show that the c.460G>A (p.Gly154Arg) mutation and the exons 3-9 heterozygous deletion in TANGO2 are recurrent pathogenic alleles present in the Latino/Hispanic and European populations, respectively, causing considerable morbidity in the homozygotes in these populations.
Keywords: Alleles; Arabs; Arrhythmias, Cardiac; Base Sequence; Child; Child, Preschool; Endoplasmic Reticulum Stress; Exome; Exons; Female; Gene Deletion; Golgi Apparatus; Hispanic or Latino; Homozygote; Humans; Infant; Male; Molecular Sequence Data; Muscle Weakness; Pedigree; Rhabdomyolysis; White People

The role of combined SNV and CNV burden in patients with distal symmetric polyneuropathy. - Pehlivan, Davut; Beck, Christine R; Okamoto, Yuji; Harel, Tamar; Akdemir, Zeynep H C; Jhangiani, Shalini N; Withers, Marjorie A; Goksungur, Meryem Tuba; Carvalho, Claudia M B; Czesnik, Dirk; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; et al. (Genet Med, 2016)
PURPOSE: Charcot-Marie-Tooth (CMT) disease is a heterogeneous group of genetic disorders of the peripheral nervous system. Copy-number variants (CNVs) contribute significantly to CMT, as duplication of PMP22 underlies the majority of CMT1 cases. We hypothesized that CNVs and/or single-nucleotide variants (SNVs) might exist in patients with CMT with an unknown molecular genetic etiology. METHODS: Two hundred patients with CMT, negative for both SNV mutations in several CMT genes and for CNVs involving PMP22, were screened for CNVs by high-resolution oligonucleotide array comparative genomic hybridization. Whole-exome sequencing was conducted on individuals with rare, potentially pathogenic CNVs. RESULTS: Putatively causative CNVs were identified in five subjects (~2.5%); four of the five map to known neuropathy genes. Breakpoint sequencing revealed Alu-Alu-mediated junctions as a predominant contributor. Exome sequencing identified MFN2 SNVs in two of the individuals. CONCLUSION: Neuropathy-associated CNV outside of the PMP22 locus is rare in CMT. Nevertheless, there is potential clinical utility in testing for CNVs and exome sequencing in CMT cases negative for the CMT1A duplication. These findings suggest that complex phenotypes including neuropathy can potentially be caused by a combination of SNVs and CNVs affecting more than one disease-associated locus and contributing to a mutational burden.Genet Med 18 5, 443-451.
Keywords: Adult; Age of Onset; Charcot-Marie-Tooth Disease; Child, Preschool; Comparative Genomic Hybridization; DNA Copy Number Variations; Exome; Female; Genetic Predisposition to Disease; GTP Phosphohydrolases; High-Throughput Nucleotide Sequencing; Humans; Male; Mitochondrial Proteins; Motor Neurons; Myelin P0 Protein; Myelin Proteins; Neural Conduction; Polymorphism, Single Nucleotide; Polyneuropathies

Somatic mosaicism underlies X-linked acrogigantism syndrome in sporadic male subjects. - Daly, Adrian F; Bo Yuan; Fina, Frederic; Caberg, Jean-Hubert; Trivellin, Giampaolo; Rostomyan, Liliya; de Herder, Wouter W; Naves, Luciana A; Metzger, Daniel; Cuny, Thomas; Rabl, Wolfgang; Shah, Nalini; et al. (Endocr Relat Cancer, 2016)
Somatic mosaicism has been implicated as a causative mechanism in a number of genetic and genomic disorders. X-linked acrogigantism (XLAG) syndrome is a recently characterized genomic form of pediatric gigantism due to aggressive pituitary tumors that is caused by submicroscopic chromosome Xq26.3 duplications that include GPR101 We studied XLAG syndrome patients (n= 18) to determine if somatic mosaicism contributed to the genomic pathophysiology. Eighteen subjects with XLAG syndrome caused by Xq26.3 duplications were identified using high-definition array comparative genomic hybridization (HD-aCGH). We noted that males with XLAG had a decreased log2ratio (LR) compared with expected values, suggesting potential mosaicism, whereas females showed no such decrease. Compared with familial male XLAG cases, sporadic males had more marked evidence for mosaicism, with levels of Xq26.3 duplication between 16.1 and 53.8%. These characteristics were replicated using a novel, personalized breakpoint junction-specific quantification droplet digital polymerase chain reaction (ddPCR) technique. Using a separate ddPCR technique, we studied the feasibility of identifying XLAG syndrome cases in a distinct patient population of 64 unrelated subjects with acromegaly/gigantism, and identified one female gigantism patient who had had increased copy number variation (CNV) threshold for GPR101 that was subsequently diagnosed as having XLAG syndrome on HD-aCGH. Employing a combination of HD-aCGH and novel ddPCR approaches, we have demonstrated, for the first time, that XLAG syndrome can be caused by variable degrees of somatic mosaicism for duplications at chromosome Xq26.3. Somatic mosaicism was shown to occur in sporadic males but not in females with XLAG syndrome, although the clinical characteristics of the disease were similarly severe in both sexes.
Keywords: Adult; Female; Genetic Diseases, X-Linked; Gigantism; Humans; Male; Middle Aged; Mosaicism; Polymerase Chain Reaction; Syndrome; Young Adult

Sources of variation in hair cortisol in wild and captive non-human primates. - Fourie, Nicolaas H; Brown, Janine L; Jolly, Clifford J; Phillips-Conroy, Jane E; Jeffrey Rogers; Bernstein, Robin M (Zoology (Jena), 2016)
Hair cortisol analysis is a potentially powerful tool for evaluating adrenal function and chronic stress. However, the technique has only recently been applied widely to studies of wildlife, including primates, and there are numerous practical and technical factors that should be considered to ensure good quality data and the validity of results and conclusions. Here we report on various intrinsic and extrinsic sources of variation in hair cortisol measurements in wild and captive primates. Hair samples from both wild and captive primates revealed that age and sex can affect hair cortisol concentrations; these effects need to be controlled for when making comparisons between individual animals or populations. Hair growth rates also showed considerable inter-specific variation among a number of primate species. We describe technical limitations of hair analyses and variation in cortisol concentrations as a function of asynchronous hair growth, anatomical site of collection, and the amount and numbers of hair/s used for cortisol extraction. We discuss these sources of variation and their implications for proper study design and interpretation of results.
Keywords: Age Factors; Animals; Animals, Wild; Animals, Zoo; Chemistry Techniques, Analytical; Female; Hair; Hydrocortisone; Male; Primates; Sex Factors; Sonication

Targeted sequencing of genome wide significant loci associated with bone mineral density (BMD) reveals significant novel and rare variants: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) targeted sequencing study. - Hsu, Yi-Hsiang; Li, Guo; Liu, Ching-Ti; Brody, Jennifer A; Karasik, David; Chou, Wen-Chi; Demissie, Serkalem; Nandakumar, Kannabiran; Zhou, Yanhua; Cheng, Chia-Ho; Gill, Richard; Richard A Gibbs; et al. (Hum Mol Genet, 2016)
Bone mineral density (BMD) is a heritable phenotype that predicts fracture risk. We performed fine-mapping by targeted sequencing at WLS, MEF2C, ARHGAP1/F2 and JAG1 loci prioritized by eQTL and bioinformatic approaches among 56 BMD loci from our previous GWAS meta-analysis. Targeted sequencing was conducted in 1,291 Caucasians from the Framingham Heart Study ( n =  925) and Cardiovascular Health Study ( n =  366), including 206 women and men with extreme low femoral neck (FN) BMD. A total of 4,964 sequence variants (SNVs) were observed and 80% were rare with MAF <1%. The associations between previously identified SNPs in these loci and BMD, while nominally significant in sequenced participants, were no longer significant after multiple testing corrections. Conditional analyses did not find protein-coding variants that may be responsible for GWAS signals. On the other hand, in the sequenced subjects, we identified novel associations in WLS , ARHGAP1 , and 5' of MEF2C ( P- values < 8x10  -   5 ; false discovery rate (FDR) q-values < 0.01) that were much more strongly associated with BMD compared to the GWAS SNPs. These associated SNVs are less-common; independent from previous GWAS signals in the same loci; and located in gene regulatory elements. Our findings suggest that protein-coding variants in selected GWAS loci did not contribute to GWAS signals. By performing targeted sequencing in GWAS loci, we identified less-common and rare non-coding SNVs associated with BMD independently from GWAS common SNPs, suggesting both common and less-common variants may associate with disease risks and phenotypes in the same loci.
Keywords: Aging; Bone Density; Cardiovascular Diseases; Cohort Studies; Epidemiologic Studies; Female; Femur Neck; Genetic Predisposition to Disease; Genome-Wide Association Study; GTPase-Activating Proteins; Humans; Male; MEF2 Transcription Factors; Middle Aged; Polymorphism, Single Nucleotide

Two male sibs with severe micrognathia and a missense variant in MED12. - Prescott, Trine E; Kulseth, Mari Ann; Heimdal, Ketil R; Stadheim, Barbro; Hopp, Einar; Gambin, Tomasz; Coban Akdemir, Zeynep H; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; Lupski, James R; Stray-Pedersen, Asbjørg (Eur J Med Genet, 2016)
Missense variants in MED12 cause three partially overlapping dysmorphic X-linked intellectual disability (XLID) syndromes: Lujan-Fryns syndrome (also known as Lujan syndrome), FG syndrome (also known as Opitz-Kaveggia syndrome) and X-linked Ohdo syndrome. We report a family with two severely micrognathic male sibs, a 10½ year old boy and a fetus, in which hemizygosity for a previously unreported missense variant in exon 13 of MED12 (NM_005120.2), c.1862G > A, p.(Arg621Gln) was detected by whole exome sequencing. The affected sibs shared no other rare variant with relevance to the phenotype. X-chromosome inactivation in blood was completely skewed (100:0) in the unaffected heterozygous mother, most likely as a result of preferential inactivation of the X-chromosome harbouring the missense variant in MED12. Neither the unaffected brother nor the unaffected maternal grandfather carried the missense variant in MED12. In the 10½ year old boy, upper airway obstruction secondary to Pierre Robin sequence necessitated a tracheostomy for the first 10 months of life. He has mild to moderate intellectual disability and some dysmorphic features seen in MED12-related syndromes. In addition, he has a horizontal gaze paresis, anomalies of the inner ear, and a cervical block vertebra. This report contributes to the expanding phenotypic range associated with MED12-mutations.
Keywords: Exons; Genes, X-Linked; Genetic Association Studies; Genotype; Humans; Infant; Male; Mediator Complex; Micrognathism; Mutation, Missense; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Severity of Illness Index; Siblings; Tomography, X-Ray Computed; X Chromosome Inactivation

Whole exome sequencing identifies the first STRADA point mutation in a patient with polyhydramnios, megalencephaly, and symptomatic epilepsy syndrome (PMSE). - Bi, Weimin; Glass, Ian A; Donna M Muzny; Richard A Gibbs; Eng, Christine M; Yang, Yaping; Sun, Angela (Am J Med Genet A, 2016)
Polyhydramnios, megalencephaly, and symptomatic epilepsy syndrome (PMSE) is an ultra rare neurodevelopmental disorder characterized by severe, infantile-onset intractable epilepsy, neurocognitive delay, macrocephaly, and craniofacial dysmorphism. The molecular diagnosis of this condition has thus far only been made in 16 Old Order Mennonite patients carrying a homozygous 7 kb founder deletion of exons 9-13 of STRADA. We performed clinical whole exome sequencing (WES) on a 4-year-old Indian male with global developmental delay, history of failure to thrive, infantile spasms, repetitive behaviors, hypotonia, low muscle mass, marked joint laxity, and dysmorphic facial features including tall forehead, long face, arched eyebrows, small chin, wide mouth, and tented upper lip. A homozygous single nucleotide duplication, c.842dupA (p.D281fs), in exon 10 of STRADA was identified. Sanger sequencing confirmed the mutation in the individual and identified both parents as carriers. In light of the molecular discoveries, the patient's clinical phenotype was considered to be a good fit for PMSE. We identified for the first time a homozygous point mutation in STRADA causing PMSE. Additional bi-allelic mutations related to PMSE thus far have not been observed in Baylor ∼6,000 consecutive clinical WES cases, supporting the rarity of this disorder. Our findings may have treatment implications for the patient since previous studies have shown rapamycin as a potential therapeutic agent for the seizures and cognitive problems in PMSE patients. © 2016 Wiley Periodicals, Inc.
Keywords: Adaptor Proteins, Vesicular Transport; Child, Preschool; DNA Mutational Analysis; Epilepsy; Exome; Facies; Genetic Association Studies; Genotype; High-Throughput Nucleotide Sequencing; Humans; Male; Megalencephaly; Pedigree; Phenotype; Physical Examination; Point Mutation; Polyhydramnios; Psychomotor Disorders; Syndrome

Whole Exome Sequencing in Atrial Fibrillation. - Lubitz, Steven A; Brody, Jennifer A; Bihlmeyer, Nathan A; Roselli, Carolina; Weng, Lu-Chen; Christophersen, Ingrid E; Alonso, Alvaro; Eric Boerwinkle; Richard A Gibbs; Bis, Joshua C; Cupples, L Adrienne; Mohler, Peter J; et al. (PLoS Genet, 2016)
Atrial fibrillation (AF) is a morbid and heritable arrhythmia. Over 35 genes have been reported to underlie AF, most of which were described in small candidate gene association studies. Replication remains lacking for most, and therefore the contribution of coding variation to AF susceptibility remains poorly understood. We examined whole exome sequencing data in a large community-based sample of 1,734 individuals with and 9,423 without AF from the Framingham Heart Study, Cardiovascular Health Study, Atherosclerosis Risk in Communities Study, and NHLBI-GO Exome Sequencing Project and meta-analyzed the results. We also examined whether genetic variation was enriched in suspected AF genes (N = 37) in AF cases versus controls. The mean age ranged from 59 to 73 years; 8,656 (78%) were of European ancestry. None of the 99,404 common variants evaluated was significantly associated after adjusting for multiple testing. Among the most significantly associated variants was a common (allele frequency = 86%) missense variant in SYNPO2L (rs3812629, p.Pro707Leu, [odds ratio 1.27, 95% confidence interval 1.13-1.43, P = 6.6x10-5]) which lies at a known AF susceptibility locus and is in linkage disequilibrium with a top marker from prior analyses at the locus. We did not observe significant associations between rare variants and AF in gene-based tests. Individuals with AF did not display any statistically significant enrichment for common or rare coding variation in previously implicated AF genes. In conclusion, we did not observe associations between coding genetic variants and AF, suggesting that large-effect coding variation is not the predominant mechanism underlying AF. A coding variant in SYNPO2L requires further evaluation to determine whether it is causally related to AF. Efforts to identify biologically meaningful coding variation underlying AF may require large sample sizes or populations enriched for large genetic effects.
Keywords: Aged; Atrial Fibrillation; Exome; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Microfilament Proteins; Middle Aged; Polymorphism, Single Nucleotide

Whole genome sequence analysis of serum amino acid levels. - Yu, Bing; de Vries, Paul S; Ginger A Metcalf; Wang, Zhe; Feofanova, Elena V; Liu, Xiaoming; Donna M Muzny; Wagenknecht, Lynne E; Richard A Gibbs; Morrison, Alanna C; Eric Boerwinkle (Genome Biol, 2016)
BACKGROUND: Blood levels of amino acids are important biomarkers of disease and are influenced by synthesis, protein degradation, and gene-environment interactions. Whole genome sequence analysis of amino acid levels may establish a paradigm for analyzing quantitative risk factors. RESULTS: In a discovery cohort of 1872 African Americans and a replication cohort of 1552 European Americans we sequenced exons and whole genomes and measured serum levels of 70 amino acids. Rare and low-frequency variants (minor allele frequency ≤5%) were analyzed by three types of aggregating motifs defined by gene exons, regulatory regions, or genome-wide sliding windows. Common variants (minor allele frequency >5%) were analyzed individually. Over all four analysis strategies, 14 gene-amino acid associations were identified and replicated. The 14 loci accounted for an average of 1.8% of the variance in amino acid levels, which ranged from 0.4 to 9.7%. Among the identified locus-amino acid pairs, four are novel and six have been reported to underlie known Mendelian conditions. These results suggest that there may be substantial genetic effects on amino acid levels in the general population that may underlie inborn errors of metabolism. We also identify a predicted promoter variant in AGA (the gene that encodes aspartylglucosaminidase) that is significantly associated with asparagine levels, with an effect that is independent of any observed coding variants. CONCLUSIONS: These data provide insights into genetic influences on circulating amino acid levels by integrating -omic technologies in a multi-ethnic population. The results also help establish a paradigm for whole genome sequence analysis of quantitative traits.
Keywords: Adult; Aged; Amino Acids; Biomarkers; Exons; Female; Genome, Human; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Nucleotide Motifs; Polymorphism, Single Nucleotide; Population Surveillance; Regulatory Sequences, Nucleic Acid

Whole-Exome Sequencing in Familial Parkinson Disease. - Farlow, Janice L; Robak, Laurie A; Hetrick, Kurt; Bowling, Kevin; Eric Boerwinkle; Coban-Akdemir, Zeynep H; Gambin, Tomasz; Richard A Gibbs; Gu, Shen; Jain, Preti; Jankovic, Joseph; Jhangiani, Shalini; et al. (JAMA Neurol, 2016)
IMPORTANCE: Parkinson disease (PD) is a progressive neurodegenerative disease for which susceptibility is linked to genetic and environmental risk factors. OBJECTIVE: To identify genetic variants contributing to disease risk in familial PD. DESIGN, SETTING, AND PARTICIPANTS: A 2-stage study design that included a discovery cohort of families with PD and a replication cohort of familial probands was used. In the discovery cohort, rare exonic variants that segregated in multiple affected individuals in a family and were predicted to be conserved or damaging were retained. Genes with retained variants were prioritized if expressed in the brain and located within PD-relevant pathways. Genes in which prioritized variants were observed in at least 4 families were selected as candidate genes for replication in the replication cohort. The setting was among individuals with familial PD enrolled from academic movement disorder specialty clinics across the United States. All participants had a family history of PD. MAIN OUTCOMES AND MEASURES: Identification of genes containing rare, likely deleterious, genetic variants in individuals with familial PD using a 2-stage exome sequencing study design. RESULTS: The 93 individuals from 32 families in the discovery cohort (49.5% [46 of 93] female) had a mean (SD) age at onset of 61.8 (10.0) years. The 49 individuals with familial PD in the replication cohort (32.6% [16 of 49] female) had a mean (SD) age at onset of 50.1 (15.7) years. Discovery cohort recruitment dates were 1999 to 2009, and replication cohort recruitment dates were 2003 to 2014. Data analysis dates were 2011 to 2015. Three genes containing a total of 13 rare and potentially damaging variants were prioritized in the discovery cohort. Two of these genes (TNK2 and TNR) also had rare variants that were predicted to be damaging in the replication cohort. All 9 variants identified in the 2 replicated genes in 12 families across the discovery and replication cohorts were confirmed via Sanger sequencing. CONCLUSIONS AND RELEVANCE: TNK2 and TNR harbored rare, likely deleterious, variants in individuals having familial PD, with similar findings in an independent cohort. To our knowledge, these genes have not been previously associated with PD, although they have been linked to critical neuronal functions. Further studies are required to confirm a potential role for these genes in the pathogenesis of PD.
Keywords: Adult; Aged; Cohort Studies; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Male; Middle Aged; Parkinsonian Disorders; Protein-Tyrosine Kinases; Sequence Analysis, DNA; Tenascin

Whole-exome sequencing reveals an inherited R566X mutation of the epithelial sodium channel β-subunit in a case of early-onset phenotype of Liddle syndrome. - Polfus, Linda M; Eric Boerwinkle; Richard A Gibbs; Ginger A Metcalf; Donna M Muzny; Veeraraghavan, Narayanan; Grove, Megan; Shete, Sanjay; Wallace, Stephanie; Milewicz, Dianna; Hanchard, Neil; Lupski, James R; et al. (Cold Spring Harb Mol Case Stud, 2016)
To comprehensively evaluate a European-American child with severe hypertension, whole-exome sequencing (WES) was performed on the child and parents, which identified causal variation of the proband's early-onset disease. The proband's hypertension was resistant to treatment, requiring a multiple drug regimen including amiloride, spironolactone, and hydrochlorothiazide. We suspected a monogenic form of hypertension because of the persistent hypokalemia with low plasma levels of renin and aldosterone. To address this, we focused on rare functional variants and indels, and performed gene-based tests incorporating linkage scores and allele frequency and filtered on deleterious functional mutations. Drawing upon clinical presentation, 27 genes were selected evidenced to cause monogenic hypertension and matched to the gene-based results. This resulted in the identification of a stop-gain mutation in an epithelial sodium channel (ENaC), , an established Liddle syndrome gene, shared by the child and her father. Interestingly, the father also harbored a missense mutation (p.Trp552Arg) in the α-subunit of the ENaC trimer, , possibly pointing to pseudohypoaldosteronism type I. This case is unique in that we present the early-onset disease and treatment response caused by a canonical stop-gain mutation (p.Arg566*) as well as ENaC digenic hits in the father, emphasizing the utility of WES informing precision medicine.
Keywords: Adult; Aldosterone; Alleles; Amiloride; Child, Preschool; Epithelial Sodium Channels; Exome; Exome Sequencing; Female; Gene Frequency; Germ-Line Mutation; Humans; Hydrochlorothiazide; Hypertension; Hypokalemia; Liddle Syndrome; Male; Mutation; Mutation, Missense; Renin

X-Linked Retinoschisis: Phenotypic Variability in a Chinese Family. - Xiao, Yangyan; Liu, Xiao; Tang, Luosheng; Wang, Xia; Coursey, Terry G; Guo, Xiaojian; Li, Zhuo (Sci Rep, 2016)
X-linked juvenile retinoschisis (XLRS), a leading cause of juvenile macular degeneration, is characterized by a spoke-wheel pattern in the macular region of the retina and splitting of the neurosensory retina. Our study is to describe the clinical characteristics of a four generations of this family (a total of 18 members)with X-linked retinoschisis (XLRS) and detected a novel mutations of c.3G > A (p.M1?) in the initiation codon of the RS1 gene. by direct sequencing.Identification of this mutation in this family provides evidence about potential genetic or environmental factors on its phenotypic variance, as patients presented with different phenotypes regardless of having the same mutation. Importantly, OCT has proven vital for XLRS diagnosis in children.
Keywords: Adult; Aged, 80 and over; Asian People; China; Codon, Initiator; Eye Proteins; Family; Female; Humans; Male; Middle Aged; Mutation; Pedigree; Retinoschisis

Allelic Mutations of KITLG, Encoding KIT Ligand, Cause Asymmetric and Unilateral Hearing Loss and Waardenburg Syndrome Type 2. - Zazo Seco, Celia; Serrão de Castro, Luciana; van Nierop, Josephine W; Morín, Matías; Jhangiani, Shalini; Verver, Eva J J; Schraders, Margit; Maiwald, Nadine; Wesdorp, Mieke; Venselaar, Hanka; Spruijt, Liesbeth; Oostrik, Jaap; et al. (Am J Hum Genet, 2015)
Linkage analysis combined with whole-exome sequencing in a large family with congenital and stable non-syndromic unilateral and asymmetric hearing loss (NS-UHL/AHL) revealed a heterozygous truncating mutation, c.286_303delinsT (p.Ser96Ter), in KITLG. This mutation co-segregated with NS-UHL/AHL as a dominant trait with reduced penetrance. By screening a panel of probands with NS-UHL/AHL, we found an additional mutation, c.200_202del (p.His67_Cys68delinsArg). In vitro studies revealed that the p.His67_Cys68delinsArg transmembrane isoform of KITLG is not detectable at the cell membrane, supporting pathogenicity. KITLG encodes a ligand for the KIT receptor. Also, KITLG-KIT signaling and MITF are suggested to mutually interact in melanocyte development. Because mutations in MITF are causative of Waardenburg syndrome type 2 (WS2), we screened KITLG in suspected WS2-affected probands. A heterozygous missense mutation, c.310C>G (p.Leu104Val), that segregated with WS2 was identified in a small family. In vitro studies revealed that the p.Leu104Val transmembrane isoform of KITLG is located at the cell membrane, as is wild-type KITLG. However, in culture media of transfected cells, the p.Leu104Val soluble isoform of KITLG was reduced, and no soluble p.His67_Cys68delinsArg and p.Ser96Ter KITLG could be detected. These data suggest that mutations in KITLG associated with NS-UHL/AHL have a loss-of-function effect. We speculate that the mechanism of the mutation underlying WS2 and leading to membrane incorporation and reduced secretion of KITLG occurs via a dominant-negative or gain-of-function effect. Our study unveils different phenotypes associated with KITLG, previously associated with pigmentation abnormalities, and will thereby improve the genetic counseling given to individuals with KITLG variants.
Keywords: Alleles; Animals; Female; Fluorescent Antibody Technique; Genetic Linkage; Hearing Loss, Unilateral; Humans; Male; Mice; Mutation; NIH 3T3 Cells; Pedigree; Phenotype; Prognosis; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Stem Cell Factor; Waardenburg Syndrome

Alu-mediated diverse and complex pathogenic copy-number variants within human chromosome 17 at p13.3. - Gu, Shen; Bo Yuan; Campbell, Ian M; Beck, Christine R; Carvalho, Claudia M B; Nagamani, Sandesh C S; Erez, Ayelet; Patel, Ankita; Bacino, Carlos A; Shaw, Chad A; Stankiewicz, Paweł; Cheung, Sau Wai; et al. (Hum Mol Genet, 2015)
Alu repetitive elements are known to be major contributors to genome instability by generating Alu-mediated copy-number variants (CNVs). Most of the reported Alu-mediated CNVs are simple deletions and duplications, and the mechanism underlying Alu-Alu-mediated rearrangement has been attributed to non-allelic homologous recombination (NAHR). Chromosome 17 at the p13.3 genomic region lacks extensive low-copy repeat architecture; however, it is highly enriched for Alu repetitive elements, with a fraction of 30% of total sequence annotated in the human reference genome, compared with the 10% genome-wide and 18% on chromosome 17. We conducted mechanistic studies of the 17p13.3 CNVs by performing high-density oligonucleotide array comparative genomic hybridization, specifically interrogating the 17p13.3 region with ∼150 bp per probe density; CNV breakpoint junctions were mapped to nucleotide resolution by polymerase chain reaction and Sanger sequencing. Studied rearrangements include 5 interstitial deletions, 14 tandem duplications, 7 terminal deletions and 13 complex genomic rearrangements (CGRs). Within the 17p13.3 region, Alu-Alu-mediated rearrangements were identified in 80% of the interstitial deletions, 46% of the tandem duplications and 50% of the CGRs, indicating that this mechanism was a major contributor for formation of breakpoint junctions. Our studies suggest that Alu repetitive elements facilitate formation of non-recurrent CNVs, CGRs and other structural aberrations of chromosome 17 at p13.3. The common observation of Alu-mediated rearrangement in CGRs and breakpoint junction sequences analysis further demonstrates that this type of mechanism is unlikely attributed to NAHR, but rather may be due to a recombination-coupled DNA replicative repair process.
Keywords: Alleles; Alu Elements; Base Sequence; Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Duplication; Gene Rearrangement; Genome, Human; Genomic Instability; Genomics; Homologous Recombination; Humans; Male; Molecular Sequence Data; Segmental Duplications, Genomic; Sequence Deletion

The amyloidogenic V122I transthyretin variant in elderly black Americans. - Quarta, C Cristina; Buxbaum, Joel N; Shah, Amil M; Falk, Rodney H; Claggett, Brian; Kitzman, Dalane W; Mosley, Thomas H; Butler, Kenneth R; Eric Boerwinkle; Solomon, Scott D (N Engl J Med, 2015)
BACKGROUND: Approximately 4% of black Americans carry a valine-to-isoleucine substitution (V122I) in the transthyretin protein, which has been associated with late-onset restrictive amyloid cardiomyopathy and increased risks of death and heart failure. METHODS: We determined genotype status for the transthyretin gene (TTR) in 3856 black participants in the Atherosclerosis Risk in Communities study and assessed clinical profiles, mortality, and the risk of incident heart failure in V122I TTR variant carriers (124 participants [3%]) versus noncarriers (3732 participants). Cardiac structure and function and features suggestive of cardiac amyloidosis were assessed in participants who underwent echocardiography during visit 5 (2011 to 2013), when they were older than 65 years of age. RESULTS: After 21.5 years of follow-up, we did not detect a significant difference in mortality between carriers (41 deaths, 33%) and noncarriers (1382 deaths, 37%; age- and sex-stratified hazard ratio among carriers, 0.99; 95% confidence interval [CI], 0.73 to 1.36; P=0.97). The TTR variant was associated with an increased risk of incident heart failure (age- and sex-stratified hazard ratio, 1.47; 95% CI, 1.03 to 2.10; P=0.04). On echocardiography at visit 5, carriers (46 participants) had worse systolic and diastolic function, as well as a higher level of N-terminal pro-brain natriuretic peptide, than noncarriers (1194 participants), although carriers had a low prevalence (7%) of overt manifestations of amyloid cardiomyopathy. CONCLUSIONS: We did not detect a significant difference in mortality between V122I TTR allele carriers and noncarriers, a finding that contrasts with prior observations; however, the risk of heart failure was increased among carriers. The prevalence of overt cardiac abnormalities among V122I TTR carriers was low. (Funded by the National Heart, Lung, and Blood Institute and others.).
Keywords: Aged; Amyloidosis; Black or African American; Cardiomyopathy, Restrictive; Cohort Studies; Echocardiography; Female; Follow-Up Studies; Genotype; Heart Failure; Heterozygote; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Prealbumin

Association of exome sequences with plasma C-reactive protein levels in >9000 participants. - Schick, Ursula M; Auer, Paul L; Bis, Joshua C; Lin, Honghuang; Wei, Peng; Pankratz, Nathan; Lange, Leslie A; Brody, Jennifer; Stitziel, Nathan O; Kim, Daniel S; Carlson, Christopher S; Fornage, Myriam; et al. (Hum Mol Genet, 2015)
C-reactive protein (CRP) concentration is a heritable systemic marker of inflammation that is associated with cardiovascular disease risk. Genome-wide association studies have identified CRP-associated common variants associated in ∼25 genes. Our aims were to apply exome sequencing to (1) assess whether the candidate loci contain rare coding variants associated with CRP levels and (2) perform an exome-wide search for rare variants in novel genes associated with CRP levels. We exome-sequenced 6050 European-Americans (EAs) and 3109 African-Americans (AAs) from the NHLBI-ESP and the CHARGE consortia, and performed association tests of sequence data with measured CRP levels. In single-variant tests across candidate loci, a novel rare (minor allele frequency = 0.16%) CRP-coding variant (rs77832441-A; p.Thr59Met) was associated with 53% lower mean CRP levels (P = 2.9 × 10(-6)). We replicated the association of rs77832441 in an exome array analysis of 11 414 EAs (P = 3.0 × 10(-15)). Despite a strong effect on CRP levels, rs77832441 was not associated with inflammation-related phenotypes including coronary heart disease. We also found evidence for an AA-specific association of APOE-ε2 rs7214 with higher CRP levels. At the exome-wide significance level (P < 5.0 × 10(-8)), we confirmed associations for reported common variants of HNF1A, CRP, IL6R and TOMM40-APOE. In gene-based tests, a burden of rare/lower frequency variation in CRP in EAs (P ≤ 6.8 × 10(-4)) and in retinoic acid receptor-related orphan receptor α (RORA) in AAs (P = 1.7 × 10(-3)) were associated with CRP levels at the candidate gene level (P < 2.0 × 10(-3)). This inquiry did not elucidate novel genes, but instead demonstrated that variants distributed across the allele frequency spectrum within candidate genes contribute to CRP levels.
Keywords: Adult; Black or African American; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Plasma; Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors; White People

Association of Rare Loss-Of-Function Alleles in HAL, Serum Histidine: Levels and Incident Coronary Heart Disease. - Yu, Bing; Li, Alexander H; Donna M Muzny; Veeraraghavan, Narayanan; de Vries, Paul S; Bis, Joshua C; Musani, Solomon K; Alexander, Danny; Morrison, Alanna C; Franco, Oscar H; Uitterlinden, Andre; Hofman, Albert; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Histidine is a semiessential amino acid with antioxidant and anti-inflammatory properties. Few data are available on the associations between genetic variants, histidine levels, and incident coronary heart disease (CHD) in a population-based sample. METHODS AND RESULTS: By conducting whole exome sequencing on 1152 African Americans in the Atherosclerosis Risk in Communities (ARIC) study and focusing on loss-of-function (LoF) variants, we identified 3 novel rare LoF variants in HAL, a gene that encodes histidine ammonia-lyase in the first step of histidine catabolism. These LoF variants had large effects on blood histidine levels (β=0.26; P=1.2×10(-13)). The positive association with histidine levels was replicated by genotyping an independent sample of 718 ARIC African Americans (minor allele frequency=1%; P=1.2×10(-4)). In addition, high blood histidine levels were associated with reduced risk of developing incident CHD with an average of 21.5 years of follow-up among African Americans (hazard ratio=0.18; P=1.9×10(-4)). This finding was validated in an independent sample of European Americans from the Framingham Heart Study (FHS) Offspring Cohort. However, LoF variants in HAL were not directly significantly associated with incident CHD after meta-analyzing results from the CHARGE Consortium. CONCLUSIONS: Three LoF mutations in HAL were associated with increased histidine levels, which in turn were shown to be inversely related to the risk of CHD among both African Americans and European Americans. Future investigations on the association between HAL gene variation and CHD are warranted.
Keywords: Adult; Alleles; Black or African American; Coronary Disease; Female; Histidine; Histidine Ammonia-Lyase; Humans; Male; Mutation; White People

BCOR-CCNB3 fusions are frequent in undifferentiated sarcomas of male children. - Peters, Tricia L; Kumar, Vijetha; Polikepahad, Sumanth; Lin, Frank Y; Sarabia, Stephen F; Liang, Yu; Wang, Wei-Lien; Lazar, Alexander J; Harshavardhan Doddapaneni; Chao, Hsu; Donna M Muzny; Wheeler, David A; et al. (Mod Pathol, 2015)
The BCOR-CCNB3 fusion gene, resulting from a chromosome X paracentric inversion, was recently described in translocation-negative 'Ewing-like' sarcomas arising in bone and soft tissue. Genetic subclassification of undifferentiated unclassified sarcomas may potentially offer markers for reproducible diagnosis and substrates for therapy. Using whole transcriptome paired-end RNA sequencing (RNA-seq) we unexpectedly identified BCOR-CCNB3 fusion transcripts in an undifferentiated spindle-cell sarcoma. RNA-seq results were confirmed through direct RT-PCR of tumor RNA and cloning of the genomic breakpoints from tumor DNA. Five additional undifferentiated sarcomas with BCOR-CCNB3 fusions were identified in a series of 42 pediatric and adult unclassified sarcomas. Genomic breakpoint analysis demonstrated unique breakpoint locations in each case at the DNA level even though the resulting fusion mRNA was identical in all cases. All patients with BCOR-CCNB3 sarcoma were males diagnosed in mid childhood (7-13 years of age). Tumors were equally distributed between axial and extra-axial locations. Five of the six tumors were soft-tissue lesions with either predominant spindle-cell morphology or spindle-cell areas interspersed with ovoid to round cells. CCNB3 immunohistochemistry showed strong nuclear positivity in five tumors before oncologic therapy, but was patchy to negative in post-treatment tumor samples. An RT-PCR assay developed to detect the fusion transcript in archival formalin-fixed tissue was positive in all six cases, with high sensitivity and specificity in both pre- and post-treated samples. This study adds to recent reports on the clinicopathologic spectrum of BCOR-CCNB3 fusion-positive sarcomas, a newly emerging entity within the undifferentiated unclassified sarcoma category and describes a simple RT-PCR assay that in conjunction with CCNB3 immunohistochemistry can be useful in diagnosing these tumors.
Keywords: Adolescent; Adult; Aged; Child; Cyclin B; Female; Humans; Male; Middle Aged; Oncogene Fusion; Proto-Oncogene Proteins; Repressor Proteins; Sarcoma; Soft Tissue Neoplasms; Young Adult

Cerebral visual impairment and intellectual disability caused by PGAP1 variants. - Bosch, Daniëlle G M; Boonstra, F Nienke; Kinoshita, Taroh; Jhangiani, Shalini; de Ligt, Joep; Cremers, Frans P M; Lupski, James R; Murakami, Yoshiko; de Vries, Bert B A (Eur J Hum Genet, 2015)
Homozygous variants in PGAP1 (post-GPI attachment to proteins 1) have recently been identified in two families with developmental delay, seizures and/or spasticity. PGAP1 is a member of the glycosylphosphatidylinositol anchor biosynthesis and remodeling pathway and defects in this pathway are a subclass of congenital disorders of glycosylation. Here we performed whole-exome sequencing in an individual with cerebral visual impairment (CVI), intellectual disability (ID), and factor XII deficiency and revealed compound heterozygous variants in PGAP1, c.274_276del (p.(Pro92del)) and c.921_925del (p.(Lys308Asnfs*25)). Subsequently, PGAP1-deficient Chinese hamster ovary (CHO)-cell lines were transfected with either mutant or wild-type constructs and their sensitivity to phosphatidylinositol-specific phospholipase C (PI-PLC) treatment was measured. The mutant constructs could not rescue the PGAP1-deficient CHO cell lines resistance to PI-PLC treatment. In addition, lymphoblastoid cell lines (LCLs) of the affected individual showed no sensitivity to PI-PLC treatment, whereas the LCLs of the heterozygous carrier parents were partially resistant. In conclusion, we report novel PGAP1 variants in a boy with CVI and ID and a proven functional loss of PGAP1 and show, to our knowledge, for the first time this genetic association with CVI.
Keywords: Animals; Cell Line, Tumor; Child; CHO Cells; Cricetinae; Cricetulus; Humans; Intellectual Disability; Male; Membrane Proteins; Mutation; Phosphoinositide Phospholipase C; Phosphoric Monoester Hydrolases; Syndrome; Vision Disorders; Visual Perception

Clinical, morphological, biochemical, imaging and outcome parameters in 21 individuals with mitochondrial maintenance defect related to FBXL4 mutations. - Huemer, Martina; Karall, Daniela; Schossig, Anna; Abdenur, Jose E; Al Jasmi, Fatma; Biagosch, Caroline; Distelmaier, Felix; Freisinger, Peter; Graham, Brett H; Haack, Tobias B; Hauser, Natalie; Hertecant, Jozef; et al. (J Inherit Metab Dis, 2015)
FBXL4 deficiency is a recently described disorder of mitochondrial maintenance associated with a loss of mitochondrial DNA in cells. To date, the genetic diagnosis of FBXL4 deficiency has been established in 28 individuals. This paper retrospectively reviews proxy-reported clinical and biochemical findings and evaluates brain imaging, morphological and genetic data in 21 of those patients. Neonatal/early-onset severe lactic acidosis, muscular hypotonia, feeding problems and failure to thrive is the characteristic pattern at first presentation. Facial dysmorphic features are present in 67% of cases. Seven children died (mean age 37 months); 11 children were alive (mean age at follow-up 46 months), three children were lost to follow-up. All survivors developed severe psychomotor retardation. Brain imaging was non-specific in neonates but a later-onset, rapidly progressive brain atrophy was noted. Elevated blood lactate and metabolic acidosis were observed in all individuals; creatine kinase was elevated in 45% of measurements. Diagnostic workup in patient tissues and cells revealed a severe combined respiratory chain defect with a general decrease of enzymes associated with mitochondrial energy metabolism and a relative depletion of mitochondrial DNA content. Mutations were detected throughout the FBXL4 gene albeit with no clear delineation of a genotype-phenotype correlation. Treatment with "mitochondrial medications" did not prove effective. In conclusion, a clinical pattern of early-onset encephalopathy, persistent lactic acidosis, profound muscular hypotonia and typical facial dysmorphism should prompt initiation of molecular genetic analysis of FBXL4. Establishment of the diagnosis permits genetic counselling, prevents patients undergoing unhelpful diagnostic procedures and allows for accurate prognosis.
Keywords: Acidosis, Lactic; Child; Child, Preschool; Disease Progression; F-Box Proteins; Facial Asymmetry; Family; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Male; Mitochondrial Diseases; Muscle Hypotonia; Mutation; Neuroimaging; Prognosis; Retrospective Studies; Ubiquitin-Protein Ligases

Cognitive phenotypes and genomic copy number variations. - Lupski, James R (JAMA, 2015)
Keywords: DNA Copy Number Variations; Female; Heterozygote; Humans; Intellectual Disability; Male; Mental Disorders

Complexity and diversity of F8 genetic variations in the 1000 genomes. - Li, J N; Carrero, I G; Dong, J F; Yu, F L (J Thromb Haemost, 2015)
BACKGROUND: Hemophilia A (HA) is an X-linked bleeding disorder caused by deleterious mutations in the coagulation factor VIII gene (F8). To date, F8 mutations have been documented predominantly in European subjects and in American subjects of European descent. Information on F8 variants in individuals of more diverse ethnic backgrounds is limited. OBJECTIVES: To discover novel and rare F8 variants, and to characterize F8 variants in diverse population backgrounds. PATIENTS/METHODS: We analyzed 2535 subjects, including 26 different ethnicities, whose data were available from the 1000 Genomes Project (1000G) phase 3 dataset, for F8 variants and their potential functional impact. RESULTS: We identified 3030 single nucleotide variants, 31 short deletions and insertions (Indels) and a large, 497 kb, deletion. Among all variants, 86.4% were rare variants and 55.6% were novel. Eighteen variants previously associated with HA were found in our study. Most of these 'HA variants' were ethnic-specific with low allele frequency; however, one variant (p.M2257V) was present in 27% of African subjects. The p.E132D, p.T281A, p.A303V and p.D422H 'HA variants' were identified only in males. Twelve novel missense variants were predicted to be deleterious. The large deletion was discovered in eight female subjects without affecting F8 transcription and the transcription of genes on the X chromosome. CONCLUSION: Characterizing F8 in the 1000G project highlighted the complexity of F8 variants and the importance of interrogating genetic variants on multiple ethnic backgrounds for associations with bleeding and thrombosis. The haplotype analysis and the orientation of duplicons that flank the large deletion suggested that the deletion was recurrent and originated by homologous recombination.
Keywords: Alleles; Cohort Studies; Computational Biology; Ethnicity; Factor VIII; Female; Gene Frequency; Genetic Association Studies; Genetic Variation; Hemophilia A; Human Genome Project; Humans; INDEL Mutation; Male; Mutation, Missense; Polymorphism, Single Nucleotide; RNA, Messenger; Sequence Deletion; Transcription, Genetic

Comprehensive analysis of patients with Stargardt macular dystrophy reveals new genotype-phenotype correlations and unexpected diagnostic revisions. - Zaneveld, Jacques; Siddiqui, Sorath; Li, Huajin; Wang, Xia; Wang, Hui; Wang, Keqing; Li, Hui; Ren, Huanan; Lopez, Irma; Dorfman, Allison; Khan, Ayesha; Wang, Feng; et al. (Genet Med, 2015)
PURPOSE: Stargardt macular dystrophy (STGD) results in early central vision loss. We sought to explain the genetic cause of STGD in a cohort of 88 patients from three different cultural backgrounds. METHODS: Next-generation sequencing using a novel capture panel was used to search for disease-causing mutations. Patients with undetermined causes were clinically reexamined and tested for copy-number variations as well as intronic mutations. RESULTS: We determined the cause of disease in 67% of our patients. Our analysis identified 35 novel ABCA4 alleles. Eleven patients had mutations in genes not previously reported to cause STGD. Finally, 45% of our patients with unsolved causes had single deleterious mutations in ABCA4, a recessive disease gene. No likely pathogenic copy-number variations were identified. CONCLUSION: This study expands our knowledge of STGD by identifying dozens of novel alleles that cause the disease. The frequency of single mutations in ABCA4 among STGD patients is higher than that among controls, indicating that these mutations contribute to disease. Disease in 11 patients was explained by mutations outside ABCA4, underlining the need to genotype all retinal disease genes to maximize genetic diagnostic rates. Few ABCA4 mutations were observed in our French Canadian patients. This population may contain an unidentified founder mutation. Our results indicate that copy-number variations are unlikely to be a major cause of STGD.
Keywords: Adult; ATP-Binding Cassette Transporters; DNA Copy Number Variations; DNA Mutational Analysis; Female; Genetic Association Studies; High-Throughput Nucleotide Sequencing; Humans; Macular Degeneration; Male; Middle Aged; Sequence Deletion; Stargardt Disease

Comprehensive genomic characterization of head and neck squamous cell carcinomas. (Nature, 2015)
The Cancer Genome Atlas profiled 279 head and neck squamous cell carcinomas (HNSCCs) to provide a comprehensive landscape of somatic genomic alterations. Here we show that human-papillomavirus-associated tumours are dominated by helical domain mutations of the oncogene PIK3CA, novel alterations involving loss of TRAF3, and amplification of the cell cycle gene E2F1. Smoking-related HNSCCs demonstrate near universal loss-of-function TP53 mutations and CDKN2A inactivation with frequent copy number alterations including amplification of 3q26/28 and 11q13/22. A subgroup of oral cavity tumours with favourable clinical outcomes displayed infrequent copy number alterations in conjunction with activating mutations of HRAS or PIK3CA, coupled with inactivating mutations of CASP8, NOTCH1 and TP53. Other distinct subgroups contained loss-of-function alterations of the chromatin modifier NSD1, WNT pathway genes AJUBA and FAT1, and activation of oxidative stress factor NFE2L2, mainly in laryngeal tumours. Therapeutic candidate alterations were identified in most HNSCCs.
Keywords: Carcinoma, Squamous Cell; DNA Copy Number Variations; DNA, Neoplasm; Female; Gene Expression Regulation, Neoplastic; Genome, Human; Genomics; Head and Neck Neoplasms; Humans; Male; Molecular Targeted Therapy; Mutation; Oncogenes; RNA, Neoplasm; Signal Transduction; Squamous Cell Carcinoma of Head and Neck; Transcription Factors

Comprehensive molecular diagnosis of 67 Chinese Usher syndrome probands: high rate of ethnicity specific mutations in Chinese USH patients. - Jiang, Lichun; Liang, Xiaofang; Yumei Li; Wang, Jing; Zaneveld, Jacques Eric; Wang, Hui; Xu, Shan; Wang, Keqing; Wang, Binbin; Rui Chen; Sui, Ruifang (Orphanet J Rare Dis, 2015)
BACKGROUND: Usher syndrome (USH) is the most common disease causing combined deafness and blindness. It is predominantly an autosomal recessive genetic disorder with occasionally digenic cases. Molecular diagnosis of USH patients is important for disease management. Few studies have tried to find the genetic cause of USH in Chinese patients. This study was designed to determine the mutation spectrum of Chinese USH patients. METHODS: We applied next generation sequencing to characterize the mutation spectrum in 67 independent Chinese families with at least one member diagnosed with USH. Blood was collected at Peking Union Medical College Hospital. This cohort is one of the largest USH cohorts reported. We utilized customized panel and whole exome sequencing, variant analysis, Sanger validation and segregation tests to find disease causing mutations in these families. RESULTS: We identified biallelic disease causing mutations in known USH genes in 70 % (49) of our patients. As has been previously reported, MYO7A is the most frequently mutated gene in our USH type I patients while USH2A is the most mutated gene in our USH type II patients. In addition, we identify mutations in CLRN1, DFNB31, GPR98 and PCDH15 for the first time in Chinese USH patients. Together, mutations in CLRN1, DNFB31, GPR98 and PCDH15 account for 11.4 % of disease in our cohort. Interestingly, although the spectrum of disease genes is quite similar between our Chinese patient cohort and other patient cohorts from different (and primarily Caucasian) ethnic backgrounds, the mutations themselves are dramatically different. In particular, 76 % (52/68) of alleles found in this study have never been previously reported. Interestingly, we observed a strong enrichment for severe protein truncating mutations expected to have severe functional consequence on the protein in USH II patients compared to the reported mutation spectrum in RP patients, who often carry partial protein truncating mutations. CONCLUSIONS: Our study provides the first comprehensive genetic characterization of a large collection of Chinese USH patients. Up to 90 % of USH patients have disease caused by mutations in known USH disease genes. By combining NGS-based molecular diagnosis and patient clinical information, a more accurate diagnosis, prognosis and personalized treatment of USH patients can be achieved.
Keywords: China; Cohort Studies; Ethnicity; Female; Humans; Male; Molecular Diagnostic Techniques; Mutation; Pedigree; Phenotype; Usher Syndromes

Comprehensive Molecular Diagnosis of a Large Chinese Leber Congenital Amaurosis Cohort. - Wang, Hui; Wang, Xia; Zou, Xuan; Xu, Shan; Li, Hui; Soens, Zachry Tore; Wang, Keqing; Yumei Li; Dong, Fangtian; Rui Chen; Sui, Ruifang (Invest Ophthalmol Vis Sci, 2015)
PURPOSE: Leber congenital amaurosis (LCA) is an inherited retinal disease that causes early-onset severe visual impairment. To evaluate the mutation spectrum in the Chinese population, we performed a mutation screen in 145 Chinese LCA families. METHODS: First, we performed direct Sanger sequencing of 7 LCA disease genes in 81 LCA families. Next, we developed a capture panel that enriches the entire coding exons and splicing sites of 163 known retinal disease genes and other candidate retinal disease genes. The capture panel allowed us to quickly identify disease-causing mutations in a large number of genes at a relatively low cost. Thus, this method was applied to the 53 LCA families that were unsolved by direct Sanger sequencing of 7 LCA disease genes and an additional 64 LCA families. Systematic next-generation sequencing (NGS) data analysis, Sanger sequencing validation, and segregation analysis were used to identify pathogenic mutations. RESULTS: Homozygous or compound heterozygous mutations were identified in 107 families, heterozygous autosomal dominant mutations were identified in 3 families and an X-linked mutation was found in 1 family, for a combined solving rate of 76.6%. In total, 136 novel pathogenic mutations were found in this study. In combination with two previous studies carried out in Chinese LCA patients, we concluded that the mutation spectrum in the Chinese population is distinct compared to that in the European population. After revisiting, we also refined the clinical diagnosis of 10 families based on their molecular diagnosis. CONCLUSIONS: Our results highlight the importance of a molecular diagnosis as an integral part of the clinical diagnostic process.
Keywords: Adolescent; Adult; Asian People; Child; Child, Preschool; Female; Humans; Infant; Leber Congenital Amaurosis; Male; Molecular Diagnostic Techniques; Mutation; Pedigree; Phenotype

COPA mutations impair ER-Golgi transport and cause hereditary autoimmune-mediated lung disease and arthritis. - Watkin, Levi B; Jessen, Birthe; Wiszniewski, Wojciech; Vece, Timothy J; Jan, Max; Sha, Youbao; Thamsen, Maike; Santos-Cortez, Regie L P; Lee, Kwanghyuk; Gambin, Tomasz; Forbes, Lisa R; Law, Christopher S; et al. (Nat Genet, 2015)
Unbiased genetic studies have uncovered surprising molecular mechanisms in human cellular immunity and autoimmunity. We performed whole-exome sequencing and targeted sequencing in five families with an apparent mendelian syndrome of autoimmunity characterized by high-titer autoantibodies, inflammatory arthritis and interstitial lung disease. We identified four unique deleterious variants in the COPA gene (encoding coatomer subunit α) affecting the same functional domain. Hypothesizing that mutant COPA leads to defective intracellular transport via coat protein complex I (COPI), we show that COPA variants impair binding to proteins targeted for retrograde Golgi-to-ER transport. Additionally, expression of mutant COPA results in ER stress and the upregulation of cytokines priming for a T helper type 17 (TH17) response. Patient-derived CD4(+) T cells also demonstrate significant skewing toward a TH17 phenotype that is implicated in autoimmunity. Our findings uncover an unexpected molecular link between a vesicular transport protein and a syndrome of autoimmunity manifested by lung and joint disease.
Keywords: Amino Acid Sequence; Arthritis; Autoimmune Diseases; Child, Preschool; Coatomer Protein; Endoplasmic Reticulum; Endoplasmic Reticulum Stress; Female; Genetic Association Studies; Genetic Predisposition to Disease; Golgi Apparatus; HEK293 Cells; Humans; Infant; Lod Score; Lung Diseases, Interstitial; Male; Molecular Sequence Data; Pedigree; Protein Transport

Coronary heart disease and genetic variants with low phospholipase A2 activity. - Polfus, Linda M; Richard A Gibbs; Eric Boerwinkle (N Engl J Med, 2015)
Keywords: Aged; Black or African American; Coronary Disease; Exome; Female; Genetic Variation; Heterozygote; Humans; Male; Middle Aged; Mutation; Phospholipases A2; Risk Factors; White People

De Novo GMNN Mutations Cause Autosomal-Dominant Primordial Dwarfism Associated with Meier-Gorlin Syndrome. - Burrage, Lindsay C; Charng, Wu-Lin; Eldomery, Mohammad K; Willer, Jason R; Davis, Erica E; Lugtenberg, Dorien; Zhu, Wenmiao; Leduc, Magalie S; Akdemir, Zeynep C; Azamian, Mahshid; Zapata, Gladys; Hernandez, Patricia P; et al. (Am J Hum Genet, 2015)
Meier-Gorlin syndrome (MGS) is a genetically heterogeneous primordial dwarfism syndrome known to be caused by biallelic loss-of-function mutations in one of five genes encoding pre-replication complex proteins: ORC1, ORC4, ORC6, CDT1, and CDC6. Mutations in these genes cause disruption of the origin of DNA replication initiation. To date, only an autosomal-recessive inheritance pattern has been described in individuals with this disorder, with a molecular etiology established in about three-fourths of cases. Here, we report three subjects with MGS and de novo heterozygous mutations in the 5' end of GMNN, encoding the DNA replication inhibitor geminin. We identified two truncating mutations in exon 2 (the 1(st) coding exon), c.16A>T (p.Lys6(∗)) and c.35_38delTCAA (p.Ile12Lysfs(∗)4), and one missense mutation, c.50A>G (p.Lys17Arg), affecting the second-to-last nucleotide of exon 2 and possibly RNA splicing. Geminin is present during the S, G2, and M phases of the cell cycle and is degraded during the metaphase-anaphase transition by the anaphase-promoting complex (APC), which recognizes the destruction box sequence near the 5' end of the geminin protein. All three GMNN mutations identified alter sites 5' to residue Met28 of the protein, which is located within the destruction box. We present data supporting a gain-of-function mechanism, in which the GMNN mutations result in proteins lacking the destruction box and hence increased protein stability and prolonged inhibition of replication leading to autosomal-dominant MGS.
Keywords: Adolescent; Amino Acid Sequence; Base Sequence; Cell Cycle; Child, Preschool; Congenital Microtia; Dwarfism; Exons; Female; Geminin; Gene Expression; Genes, Dominant; Growth Disorders; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Inheritance Patterns; Male; Micrognathism; Molecular Sequence Data; Mutation; Patella; Pedigree; Protein Stability; Proteolysis; RNA Splicing; Sequence Alignment

Decreased expression of endogenous feline leukemia virus in cat lymphomas: a case control study. - Krunic, Milica; Ertl, Reinhard; Hagen, Benedikt; Fritz J Sedlazeck; Hofmann-Lehmann, Regina; von Haeseler, Arndt; Klein, Dieter (BMC Vet Res, 2015)
BACKGROUND: Cats infected with exogenous feline leukemia virus (exFeLV) have a higher chance of lymphoma development than uninfected cats. Furthermore, an increased exFeLV transcription has been detected in lymphomas compared to non-malignant tissues. The possible mechanisms of lymphoma development by exFeLV are insertional mutagenesis or persistent stimulation of host immune cells by viral antigens, bringing them at risk for malignant transformation. Vaccination of cats against exFeLV has in recent years decreased the overall infection rate in most countries. Nevertheless, an increasing number of lymphomas have been diagnosed among exFeLV-negative cats. Endogenous feline leukemia virus (enFeLV) is another retrovirus for which transcription has been observed in cat lymphomas. EnFeLV provirus elements are present in the germline of various cat species and share a high sequence similarity with exFeLV but, due to mutations, are incapable of producing infectious viral particles. However, recombination between exFeLV and enFeLV could produce infectious particles. RESULTS: We examined the FeLV expression in cats that have developed malignant lymphomas and discussed the possible mechanisms that could have induced malignant transformation. For expression analysis we used next-generation RNA-sequencing (RNA-Seq) and for validation reverse transcription quantitative PCR (RT-qPCR). First, we showed that there was no expression of exFeLV in all samples, which eliminates the possibility of recombination between exFeLV and enFeLV. Next, we analyzed the difference in expression of three enFeLV genes between control and lymphoma samples. Our analysis showed an average of 3.40-fold decreased viral expression for the three genes in lymphoma compared to control samples. The results were confirmed by RT-qPCR. CONCLUSIONS: There is a decreased expression of enFeLV genes in lymphomas versus control samples, which contradicts previous observations for the exFeLV. Our results suggest that a persistent stimulation of host immune cells is not an appropriate mechanism responsible for malignant transformation caused by feline endogenous retroviruses.
Keywords: Animals; Base Sequence; Case-Control Studies; Cat Diseases; Cats; Female; Gene Expression Regulation, Viral; Leukemia Virus, Feline; Lymphoma; Male; Retroviridae Infections; Reverse Transcriptase Polymerase Chain Reaction; RNA, Viral; Tumor Virus Infections

Durable sequence stability and bone marrow tropism in a macaque model of human pegivirus infection. - Bailey, Adam L; Lauck, Michael; Mohns, Mariel; Peterson, Eric J; Beheler, Kerry; Brunner, Kevin G; Crosno, Kristin; Mejia, Andres; Mutschler, James; Gehrke, Matthew; Greene, Justin; Ericsen, Adam J; et al. (Sci Transl Med, 2015)
Human pegivirus (HPgV)-formerly known as GB virus C and hepatitis G virus-is a poorly characterized RNA virus that infects about one-sixth of the global human population and is transmitted frequently in the blood supply. We create an animal model of HPgV infection by infecting macaque monkeys with a new simian pegivirus (SPgV) discovered in wild baboons. Using this model, we provide a high-resolution, longitudinal picture of SPgV viremia where the dose, route, and timing of infection are known. We detail the highly variable acute phase of SPgV infection, showing that the viral load trajectory early in infection is dependent on the infecting dose, whereas the chronic-phase viremic set point is not. We also show that SPgV has an extremely low propensity for accumulating sequence variation, with no consensus-level variants detected during the acute phase of infection and an average of only 1.5 variants generated per 100 infection-days. Finally, we show that SPgV RNA is highly concentrated in only two tissues: spleen and bone marrow, with bone marrow likely producing most of the virus detected in plasma. Together, these results reconcile several paradoxical observations from cross-sectional analyses of HPgV in humans and provide an animal model for studying pegivirus biology.
Keywords: Acquired Immunodeficiency Syndrome; Animals; Bone Marrow; Disease Models, Animal; Evolution, Molecular; Female; Flaviviridae Infections; GB virus C; Genetic Variation; High-Throughput Nucleotide Sequencing; HIV Infections; Humans; Likelihood Functions; Macaca; Male; Papio; Phylogeny; Reverse Transcriptase Polymerase Chain Reaction; RNA, Viral; Viral Load; Viral Tropism; Viremia

Epigenome-wide association study (EWAS) of BMI, BMI change and waist circumference in African American adults identifies multiple replicated loci. - Demerath, Ellen W; Guan, Weihua; Grove, Megan L; Aslibekyan, Stella; Mendelson, Michael; Zhou, Yi-Hui; Hedman, Åsa K; Sandling, Johanna K; Li, Li-An; Irvin, Marguerite R; Zhi, Degui; Deloukas, Panos; et al. (Hum Mol Genet, 2015)
Obesity is an important component of the pathophysiology of chronic diseases. Identifying epigenetic modifications associated with elevated adiposity, including DNA methylation variation, may point to genomic pathways that are dysregulated in numerous conditions. The Illumina 450K Bead Chip array was used to assay DNA methylation in leukocyte DNA obtained from 2097 African American adults in the Atherosclerosis Risk in Communities (ARIC) study. Mixed-effects regression models were used to test the association of methylation beta value with concurrent body mass index (BMI) and waist circumference (WC), and BMI change, adjusting for batch effects and potential confounders. Replication using whole-blood DNA from 2377 White adults in the Framingham Heart Study and CD4+ T cell DNA from 991 Whites in the Genetics of Lipid Lowering Drugs and Diet Network Study was followed by testing using adipose tissue DNA from 648 women in the Multiple Tissue Human Expression Resource cohort. Seventy-six BMI-related probes, 164 WC-related probes and 8 BMI change-related probes passed the threshold for significance in ARIC (P < 1 × 10(-7); Bonferroni), including probes in the recently reported HIF3A, CPT1A and ABCG1 regions. Replication using blood DNA was achieved for 37 BMI probes and 1 additional WC probe. Sixteen of these also replicated in adipose tissue, including 15 novel methylation findings near genes involved in lipid metabolism, immune response/cytokine signaling and other diverse pathways, including LGALS3BP, KDM2B, PBX1 and BBS2, among others. Adiposity traits are associated with DNA methylation at numerous CpG sites that replicate across studies despite variation in tissue type, ethnicity and analytic approaches.
Keywords: Aged; Atherosclerosis; Black or African American; Body Mass Index; DNA Methylation; Epigenesis, Genetic; Female; Genome-Wide Association Study; Humans; Lipid Metabolism; Male; Metabolic Networks and Pathways; Middle Aged; Obesity; Waist Circumference; White People

Exome Sequence Analysis Suggests that Genetic Burden Contributes to Phenotypic Variability and Complex Neuropathy. - Gonzaga-Jauregui, Claudia; Harel, Tamar; Gambin, Tomasz; Kousi, Maria; Griffin, Laurie B; Francescatto, Ludmila; Ozes, Burcak; Karaca, Ender; Jhangiani, Shalini N; Bainbridge, Matthew N; Lawson, Kim S; Pehlivan, Davut; et al. (Cell Rep, 2015)
Charcot-Marie-Tooth (CMT) disease is a clinically and genetically heterogeneous distal symmetric polyneuropathy. Whole-exome sequencing (WES) of 40 individuals from 37 unrelated families with CMT-like peripheral neuropathy refractory to molecular diagnosis identified apparent causal mutations in ∼ 45% (17/37) of families. Three candidate disease genes are proposed, supported by a combination of genetic and in vivo studies. Aggregate analysis of mutation data revealed a significantly increased number of rare variants across 58 neuropathy-associated genes in subjects versus controls, confirmed in a second ethnically discrete neuropathy cohort, suggesting that mutation burden potentially contributes to phenotypic variability. Neuropathy genes shown to have highly penetrant Mendelizing variants (HPMVs) and implicated by burden in families were shown to interact genetically in a zebrafish assay exacerbating the phenotype established by the suppression of single genes. Our findings suggest that the combinatorial effect of rare variants contributes to disease burden and variable expressivity.
Keywords: Animals; Charcot-Marie-Tooth Disease; Exome; Female; Genetic Load; Genetic Variation; HSP40 Heat-Shock Proteins; Humans; Male; Mutation; Myelin P2 Protein; Pedigree; Penetrance; Peripheral Nervous System Diseases; Phenotype; Serine C-Palmitoyltransferase; Suppression, Genetic; Zebrafish

Exome sequencing identifies a homozygous C5orf42 variant in a Turkish kindred with oral-facial-digital syndrome type VI. - Bayram, Yavuz; Aydin, Hatip; Gambin, Tomasz; Akdemir, Zeynep Coban; Atik, Mehmed M; Karaca, Ender; Karaman, Ali; Pehlivan, Davut; Jhangiani, Shalini N; Richard A Gibbs; Lupski, James R (Am J Med Genet A, 2015)
Oral-facial-digital syndrome type VI (OFDVI) is a rare ciliopathy in the spectrum of Joubert syndrome (JS) and distinguished from other oral-facial-digital syndromes by metacarpal abnormalities with central polydactyly and by a molar tooth sign on cranial MRI. Additional characteristic features include short stature, micrognathia, posteriorly rotated low-set ears, hypertelorism, epicanthal folds, broad nasal tip, tongue hamartoma, upper lip notch, intraoral frenula, cleft lip/palate, and renal anomalies. Recently, novel mutations in C5orf42 were identified in 9 out of 11 OFDVI families. In a subsequent study C5orf42 was found to be mutated in only 2 out of 17 OFDVI probands while 28 patients with a pure JS phenotype also had pathogenic mutations of C5orf42. We report on two affected cousins diagnosed with OFDVI who were born from first degree cousin marriages. Whole exome sequencing (WES) identified a homozygous predicted damaging missense mutation (c.4034A > G; p.Gln1345Arg) in the C5orf42 gene. Our data contribute to the evidence that C5orf42 is one of the causative genes for OFDVI.
Keywords: Abnormalities, Multiple; Cerebellar Diseases; Cerebellum; Child; Cleft Palate; Exome; Eye Abnormalities; Female; Genetic Predisposition to Disease; Hamartoma; Homozygote; Humans; Kidney Diseases, Cystic; Magnetic Resonance Imaging; Male; Membrane Proteins; Middle Aged; Mutation; Orofaciodigital Syndromes; Phenotype; Retina; Turkey

Exome sequencing identifies rare LDLR and APOA5 alleles conferring risk for myocardial infarction. - Do, Ron; Stitziel, Nathan O; Won, Hong-Hee; Jørgensen, Anders Berg; Duga, Stefano; Angelica Merlini, Pier; Kiezun, Adam; Farrall, Martin; Goel, Anuj; Zuk, Or; Guella, Illaria; Asselta, Rosanna; et al. (Nature, 2015)
Myocardial infarction (MI), a leading cause of death around the world, displays a complex pattern of inheritance. When MI occurs early in life, genetic inheritance is a major component to risk. Previously, rare mutations in low-density lipoprotein (LDL) genes have been shown to contribute to MI risk in individual families, whereas common variants at more than 45 loci have been associated with MI risk in the population. Here we evaluate how rare mutations contribute to early-onset MI risk in the population. We sequenced the protein-coding regions of 9,793 genomes from patients with MI at an early age (≤50 years in males and ≤60 years in females) along with MI-free controls. We identified two genes in which rare coding-sequence mutations were more frequent in MI cases versus controls at exome-wide significance. At low-density lipoprotein receptor (LDLR), carriers of rare non-synonymous mutations were at 4.2-fold increased risk for MI; carriers of null alleles at LDLR were at even higher risk (13-fold difference). Approximately 2% of early MI cases harbour a rare, damaging mutation in LDLR; this estimate is similar to one made more than 40 years ago using an analysis of total cholesterol. Among controls, about 1 in 217 carried an LDLR coding-sequence mutation and had plasma LDL cholesterol > 190 mg dl(-1). At apolipoprotein A-V (APOA5), carriers of rare non-synonymous mutations were at 2.2-fold increased risk for MI. When compared with non-carriers, LDLR mutation carriers had higher plasma LDL cholesterol, whereas APOA5 mutation carriers had higher plasma triglycerides. Recent evidence has connected MI risk with coding-sequence mutations at two genes functionally related to APOA5, namely lipoprotein lipase and apolipoprotein C-III (refs 18, 19). Combined, these observations suggest that, as well as LDL cholesterol, disordered metabolism of triglyceride-rich lipoproteins contributes to MI risk.
Keywords: Age Factors; Age of Onset; Alleles; Apolipoprotein A-V; Apolipoproteins A; Case-Control Studies; Cholesterol, LDL; Coronary Artery Disease; Exome; Female; Genetic Predisposition to Disease; Genetics, Population; Heterozygote; Humans; Male; Middle Aged; Mutation; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Receptors, LDL; Triglycerides; United States

Exome sequencing reveals homozygous TRIM2 mutation in a patient with early onset CMT and bilateral vocal cord paralysis. - Pehlivan, Davut; Coban Akdemir, Zeynep; Karaca, Ender; Bayram, Yavuz; Jhangiani, Shalini; Yildiz, Edibe Pembegul; Donna M Muzny; Uluc, Kayihan; Richard A Gibbs; Elcioglu, Nursel; Lupski, James R; Harel, Tamar (Hum Genet, 2015)
Charcot-Marie-Tooth disease is a heterogeneous group of inherited distal symmetric polyneuropathies associated with mutations in genes encoding components essential for normal functioning of the Schwann cell and axon. TRIM2, encoding a ligase that ubiquitinates the neurofilament light chain, was recently associated with early-onset neuropathy in a single patient. We report a TRIM2 homozygous missense mutation (c.2000A>C; p.D667A) in a patient with peripheral neuropathy and bilateral vocal cord paralysis, allowing for further delineation of the associated phenotypic spectrum.
Keywords: Adult; Charcot-Marie-Tooth Disease; Exome; Female; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Infant, Newborn; Male; Mutation, Missense; Nuclear Proteins; Vocal Cord Paralysis

Factors associated with blood lead concentrations of children in Jamaica. - Rahbar, Mohammad H; Samms-Vaughan, Maureen; Dickerson, Aisha S; Loveland, Katherine A; Ardjomand-Hessabi, Manouchehr; Bressler, Jan; Shakespeare-Pellington, Sydonnie; Grove, Megan L; Eric Boerwinkle (J Environ Sci Health A Tox Hazard Subst Environ Eng, 2015)
Lead is a heavy metal known to be detrimental to neurologic, physiologic, and behavioral health of children. Previous studies from Jamaica reported that mean lead levels in soil are four times that of lead levels in some other parts of the world. Other studies detected lead levels in fruits and root vegetables, which were grown in areas with lead contaminated soil. In this study, we investigate environmental factors associated with blood lead concentrations in Jamaican children. The participants in this study comprised 125 typically developing (TD) children (ages 2-8 years) who served as controls in an age- and sex-matched case-control study that enrolled children from 2009-2012 in Jamaica. We administered a questionnaire to assess demographic and socioeconomic information as well as potential exposures to lead through food. Using General Linear Models (GLMs), we identified factors associated with blood lead concentrations in Jamaican children. The geometric mean blood lead concentration (GMBLC) in the sample of children in this study was 2.80 μg dL(-1). In univariable GLM analyses, GMBLC was higher for children whose parents did not have education beyond high school compared to those whose parents had attained this level (3.00 μg dL(-1) vs. 2.31 μg dL(-1); P = 0.05), children living near a high traffic road compared to those who did not (3.43 μg dL(-1) vs. 2.52 μg dL(-1); P < 0.01), and children who reported eating ackee compared to those who did not eat this fruit (2.89 μg dL(-1) vs. 1.65 μg dL(-1); P < 0.05). In multivariable analysis, living near a high traffic road was identified as an independent risk factor for higher adjusted GMBLC (3.05 μg dL(-1) vs. 2.19 μg dL(-1); P = 0.01). While our findings indicate that GMBLC in Jamaican children has dropped by at least 62% during the past two decades, children living in Jamaica still have GMBLC that is twice that of children in more developed countries. In addition, we have identified significant risk factors for higher blood lead concentrations in Jamaican children. We believe increasing awareness among parents regarding these risk factors could potentially lead to a lower level of lead exposure in Jamaican children.
Keywords: Case-Control Studies; Child; Child, Preschool; Environmental Exposure; Environmental Pollutants; Female; Humans; Jamaica; Lead; Lead Poisoning; Male; Risk Factors; Socioeconomic Factors

FBN1 contributing to familial congenital diaphragmatic hernia. - Beck, Tyler F; Campeau, Philippe M; Jhangiani, Shalini N; Gambin, Tomasz; Li, Alexander H; Abo-Zahrah, Reem; Jordan, Valerie K; Hernandez-Garcia, Andres; Wiszniewski, Wojciech K; Donna M Muzny; Richard A Gibbs; Eric Boerwinkle; et al. (Am J Med Genet A, 2015)
Congenital diaphragmatic hernia (CDH) is a relatively common, life--threatening birth defect. We present a family with recurrent CDH--paraesophageal and central--for whom exome sequencing (ES) revealed a frameshift mutation (c.4969_4970insA, p.Ile1657Asnfs*30) in the fibrillin 1 gene (FBN1) that causes Marfan syndrome. A diagnosis of Marfan syndrome had not been considered previously in this family. However, a review of the literature demonstrated that FBN1 mutations have an unusual pattern of CDH in which paraesophageal hernias are particularly common. Subsequent clinical evaluations revealed evidence for ectopia lentis in affected family members supporting a clinical diagnosis of Marfan syndrome. Since only two other cases of familial CDH have been described in association with FBN1 mutations, we investigated an oligogenic hypothesis by examining ES data for deleterious sequence changes in other CDH-related genes. This search revealed putatively deleterious sequence changes in four other genes that have been shown to cause diaphragm defects in humans and/or mice--FREM1, DES, PAX3 and MET. It is unclear whether these changes, alone or in aggregate, are contributing to the development of CDH in this family. However, their individual contribution is likely to be small compared to that of the frameshift mutation in FBN1. We conclude that ES can be used to identify both major and minor genetic factors that may contribute to CDH. These results also suggest that ES should be considered in the diagnostic evaluation of individuals and families with CDH, particularly when other diagnostic modalities have failed to reveal a molecular etiology.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Exome; Female; Fibrillin-1; Fibrillins; Frameshift Mutation; Genetic Association Studies; Hernias, Diaphragmatic, Congenital; Humans; Male; Marfan Syndrome; Microfilament Proteins; Pedigree

Genes that Affect Brain Structure and Function Identified by Rare Variant Analyses of Mendelian Neurologic Disease. - Karaca, Ender; Harel, Tamar; Pehlivan, Davut; Jhangiani, Shalini N; Gambin, Tomasz; Coban Akdemir, Zeynep; Gonzaga-Jauregui, Claudia; Erdin, Serkan; Bayram, Yavuz; Campbell, Ian M; Hunter, Jill V; Atik, Mehmed M; et al. (Neuron, 2015)
Development of the human nervous system involves complex interactions among fundamental cellular processes and requires a multitude of genes, many of which remain to be associated with human disease. We applied whole exome sequencing to 128 mostly consanguineous families with neurogenetic disorders that often included brain malformations. Rare variant analyses for both single nucleotide variant (SNV) and copy number variant (CNV) alleles allowed for identification of 45 novel variants in 43 known disease genes, 41 candidate genes, and CNVs in 10 families, with an overall potential molecular cause identified in >85% of families studied. Among the candidate genes identified, we found PRUNE, VARS, and DHX37 in multiple families and homozygous loss-of-function variants in AGBL2, SLC18A2, SMARCA1, UBQLN1, and CPLX1. Neuroimaging and in silico analysis of functional and expression proximity between candidate and known disease genes allowed for further understanding of genetic networks underlying specific types of brain malformations.
Keywords: Brain; Cohort Studies; Databases, Genetic; Female; Gene Regulatory Networks; Genetic Association Studies; Genetic Variation; Humans; Male; Mendelian Randomization Analysis; Nervous System Diseases; Pedigree

A genetic association study of activated partial thromboplastin time in European Americans and African Americans: the ARIC Study. - Weng, Lu-Chen; Cushman, Mary; Pankow, James S; Basu, Saonli; Eric Boerwinkle; Folsom, Aaron R; Tang, Weihong (Hum Mol Genet, 2015)
Reduced activated partial thromboplastin time (aPTT) is a risk marker for incident and recurrent venous thromboembolism (VTE). Genetic factors influencing aPTT are not well understood, especially in populations of non-European ancestry. The present study aimed to identify aPTT-related gene variants in both European Americans (EAs) and African Americans (AAs). We conducted a genetic association study for aPTT in 9719 EAs and 2799 AAs from the Atherosclerosis Risk in Communities (ARIC) study. Using the Candidate Gene Association Resource (CARe) consortium candidate gene array, the analyses were based on ∼50 000 SNPs in ∼2000 candidate genes. In EAs, the analyses identified a new independent association for aPTT in F5 (rs2239852, P-value = 1.9 × 10(-8)), which clusters with a coding variant rs6030 (P-value = 7.8 × 10(-7)). The remaining significant signals were located on F5, HRG, KNG1, F11, F12 and ABO and have been previously reported in EA populations. In AAs, significant signals were identified in KNG1, HRG, F12, ABO and VWF, with the leading variants in KNG1, HRG and F12 being the same as in the EAs; the significant variant in VWF (rs2229446, P-value = 1.2 × 10(-6)) was specific to the AA sample (minor allele frequency = 19% in AAs and 0.2% in EAs) and has not been previously reported. This is the first study to report aPTT-related genetic variants in AAs. Our findings in AAs demonstrate transferability of previously reported associations with KNG1, HRG and F12 in EAs. We also identified new associations at F5 in EAs and VWF in AAs that have not been previously reported for aPTT.
Keywords: Aged; Atherosclerosis; Black or African American; Female; Genetic Association Studies; Genome-Wide Association Study; Humans; Kininogens; Male; Middle Aged; Neural Cell Adhesion Molecule L1; Partial Thromboplastin Time; Polymorphism, Single Nucleotide; Prospective Studies; Proteins; White People

Genetic contributions to variation in general cognitive function: a meta-analysis of genome-wide association studies in the CHARGE consortium (N=53949). - Davies, G; Armstrong, N; Bis, J C; Bressler, J; Chouraki, V; Giddaluru, S; Hofer, E; Ibrahim-Verbaas, C A; Kirin, M; Lahti, J; van der Lee, S J; Le Hellard, S; et al. (Mol Psychiatry, 2015)
General cognitive function is substantially heritable across the human life course from adolescence to old age. We investigated the genetic contribution to variation in this important, health- and well-being-related trait in middle-aged and older adults. We conducted a meta-analysis of genome-wide association studies of 31 cohorts (N=53,949) in which the participants had undertaken multiple, diverse cognitive tests. A general cognitive function phenotype was tested for, and created in each cohort by principal component analysis. We report 13 genome-wide significant single-nucleotide polymorphism (SNP) associations in three genomic regions, 6q16.1, 14q12 and 19q13.32 (best SNP and closest gene, respectively: rs10457441, P=3.93 × 10(-9), MIR2113; rs17522122, P=2.55 × 10(-8), AKAP6; rs10119, P=5.67 × 10(-9), APOE/TOMM40). We report one gene-based significant association with the HMGN1 gene located on chromosome 21 (P=1 × 10(-6)). These genes have previously been associated with neuropsychiatric phenotypes. Meta-analysis results are consistent with a polygenic model of inheritance. To estimate SNP-based heritability, the genome-wide complex trait analysis procedure was applied to two large cohorts, the Atherosclerosis Risk in Communities Study (N=6617) and the Health and Retirement Study (N=5976). The proportion of phenotypic variation accounted for by all genotyped common SNPs was 29% (s.e.=5%) and 28% (s.e.=7%), respectively. Using polygenic prediction analysis, ~1.2% of the variance in general cognitive function was predicted in the Generation Scotland cohort (N=5487; P=1.5 × 10(-17)). In hypothesis-driven tests, there was significant association between general cognitive function and four genes previously associated with Alzheimer's disease: TOMM40, APOE, ABCG1 and MEF2C.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognition Disorders; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; HMGN1 Protein; Humans; Male; Middle Aged; Neuropsychological Tests; Phenotype; Polymorphism, Single Nucleotide; Scotland

Genetic influences on response to novel objects and dimensions of personality in Papio baboons. - Johnson, Zachary; Brent, Linda; Alvarenga, Juan Carlos; Comuzzie, Anthony G; Shelledy, Wendy; Ramirez, Stephanie; Cox, Laura; Mahaney, Michael C; Huang, Yung-Yu; Mann, J John; Kaplan, Jay R; Jeffrey Rogers (Behav Genet, 2015)
Behavioral variation within and between populations and species of the genus Papio has been studied extensively, but little is known about the genetic causes of individual- or population-level differences. This study investigates the influence of genetic variation on personality (sometimes referred to as temperament) in baboons and identifies a candidate gene partially responsible for the variation in that phenotype. To accomplish these goals, we examined individual variation in response to both novel objects and an apparent novel social partner (using a mirror test) among pedigreed baboons (n = 578) from the Southwest National Primate Research Center. We investigated the frequency and duration of individual behaviors in response to novel objects and used multivariate factor analysis to identify trait-like dimensions of personality. Exploratory factor analysis identified two distinct dimensions of personality within this population. Factor 1 accounts for 46.8 % of the variance within the behavioral matrix, and consists primarily of behaviors related to the "boldness" of the subject. Factor 2 accounts for 18.8 % of the variation, and contains several "anxiety" like behaviors. Several specific behaviors, and the two personality factors, were significantly heritable, with the factors showing higher heritability than most individual behaviors. Subsequent analyses show that the behavioral reactions observed in the test protocol are associated with animals' social behavior observed later in their home social groups. Finally we used linkage analysis to map quantitative trait loci for the measured phenotypes. Single nucleotide polymorphisms in a positional candidate gene (SNAP25) are associated with variation in one of the personality factors, and CSF levels of homovanillic acid and 3-methoxy-4-hydroxyphenylglycol. This study documents heritable variation in personality among baboons and suggests that sequence variation in SNAP25 may influence differences in behavior and neurochemistry in these nonhuman primates.
Keywords: Animals; Behavior, Animal; Ethylene Glycols; Female; Genetic Linkage; Genetic Variation; Homovanillic Acid; Male; Multivariate Analysis; Papio; Pedigree; Personality; Phenols; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Social Behavior; Synaptosomal-Associated Protein 25

The genomes of two key bumblebee species with primitive eusocial organization. - Sadd, Ben M; Barribeau, Seth M; Bloch, Guy; de Graaf, Dirk C; Dearden, Peter; Elsik, Christine G; Gadau, Jürgen; Grimmelikhuijzen, Cornelis J P; Hasselmann, Martin; Lozier, Jeffrey D; Robertson, Hugh M; Smagghe, Guy; et al. (Genome Biol, 2015)
BACKGROUND: The shift from solitary to social behavior is one of the major evolutionary transitions. Primitively eusocial bumblebees are uniquely placed to illuminate the evolution of highly eusocial insect societies. Bumblebees are also invaluable natural and agricultural pollinators, and there is widespread concern over recent population declines in some species. High-quality genomic data will inform key aspects of bumblebee biology, including susceptibility to implicated population viability threats. RESULTS: We report the high quality draft genome sequences of Bombus terrestris and Bombus impatiens, two ecologically dominant bumblebees and widely utilized study species. Comparing these new genomes to those of the highly eusocial honeybee Apis mellifera and other Hymenoptera, we identify deeply conserved similarities, as well as novelties key to the biology of these organisms. Some honeybee genome features thought to underpin advanced eusociality are also present in bumblebees, indicating an earlier evolution in the bee lineage. Xenobiotic detoxification and immune genes are similarly depauperate in bumblebees and honeybees, and multiple categories of genes linked to social organization, including development and behavior, show high conservation. Key differences identified include a bias in bumblebee chemoreception towards gustation from olfaction, and striking differences in microRNAs, potentially responsible for gene regulation underlying social and other traits. CONCLUSIONS: These two bumblebee genomes provide a foundation for post-genomic research on these key pollinators and insect societies. Overall, gene repertoires suggest that the route to advanced eusociality in bees was mediated by many small changes in many genes and processes, and not by notable expansion or depauperation.
Keywords: Animals; Bee Venoms; Bees; Behavior, Animal; Chemoreceptor Cells; Chromosome Mapping; Databases, Genetic; Evolution, Molecular; Female; Gene Expression Regulation; Gene Rearrangement; Genes, Insect; Genomics; Interspersed Repetitive Sequences; Male; Open Reading Frames; Polymorphism, Single Nucleotide; Selenoproteins; Sequence Analysis, DNA; Social Behavior; Species Specificity; Synteny

Germline mutations in shelterin complex genes are associated with familial glioma. - Bainbridge, Matthew N; Armstrong, Georgina N; Gramatges, M Monica; Bertuch, Alison A; Jhangiani, Shalini N; Harshavardhan Doddapaneni; Lewis, Lora; Tombrello, Joseph; Tsavachidis, Spyros; Liu, Yanhong; Jalali, Ali; Plon, Sharon E; et al. (J Natl Cancer Inst, 2015)
Gliomas are the most common brain tumor, with several histological subtypes of various malignancy grade. The genetic contribution to familial glioma is not well understood. Using whole exome sequencing of 90 individuals from 55 families, we identified two families with mutations in POT1 (p.G95C, p.E450X), a member of the telomere shelterin complex, shared by both affected individuals in each family and predicted to impact DNA binding and TPP1 binding, respectively. Validation in a separate cohort of 264 individuals from 246 families identified an additional mutation in POT1 (p.D617Efs), also predicted to disrupt TPP1 binding. All families with POT1 mutations had affected members with oligodendroglioma, a specific subtype of glioma more sensitive to irradiation. These findings are important for understanding the origin of glioma and could have importance for the future diagnostics and treatment of glioma.
Keywords: Adult; Aged; Brain Neoplasms; Exome; Female; Genetic Predisposition to Disease; Germ-Line Mutation; Glioma; Humans; Male; Middle Aged; Oligodendroglioma; Pedigree; Shelterin Complex; Telomere-Binding Proteins

Germline PRKACA amplification causes variable phenotypes that may depend on the extent of the genomic defect: molecular mechanisms and clinical presentations. - Lodish, Maya B; Bo Yuan; Levy, Isaac; Braunstein, Glenn D; Lyssikatos, Charalampos; Salpea, Paraskevi; Szarek, Eva; Karageorgiadis, Alexander S; Belyavskaya, Elena; Raygada, Margarita; Faucz, Fabio Rueda; Izzat, Louise; et al. (Eur J Endocrinol, 2015)
OBJECTIVE: We have recently reported five patients with bilateral adrenocortical hyperplasia (BAH) and Cushing's syndrome (CS) caused by constitutive activation of the catalytic subunit of protein kinase A (PRKACA). By doing new in-depth analysis of their cytogenetic abnormality, we attempted a better genotype-phenotype correlation of their PRKACA amplification. DESIGN: This study is a case series. METHODS: Molecular cytogenetic, genomic, clinical, and histopathological analyses were performed in five patients with CS. RESULTS: Reinvestigation of the defects of previously described patients by state-of-the-art molecular cytogenetics showed complex genomic rearrangements in the chromosome 19p13.2p13.12 locus, resulting in copy number gains encompassing the entire PRKACA gene; three patients (one sporadic case and two related cases) were observed with gains consistent with duplications, while two sporadic patients were observed with gains consistent with triplications. Although all five patients presented with ACTH-independent CS, the three sporadic patients had micronodular BAH and underwent bilateral adrenalectomy in early childhood, whereas the two related patients, a mother and a son, presented with macronodular BAH as adults. In at least one patient, PRKACA triplication was associated with a more severe phenotype. CONCLUSIONS: Constitutional chromosomal PRKACA gene amplification is a recently identified genetic defect associated with CS, a trait that may be inherited in an autosomal dominant manner or occur de novo. Genomic rearrangements can be complex and can result in different copy number states of dosage-sensitive genes, e.g., duplication and triplication. PRKACA amplification can lead to variable phenotypes clinically and pathologically, both micro- and macro-nodular BAH, the latter of which we speculate may depend on the extent of amplification.
Keywords: Adrenal Glands; Adrenalectomy; Adult; Child; Child, Preschool; Cushing Syndrome; Cyclic AMP-Dependent Protein Kinase Catalytic Subunits; DNA Copy Number Variations; Female; Gene Amplification; Humans; Hyperplasia; Male; Phenotype; Young Adult

Global transcriptional disturbances underlie Cornelia de Lange syndrome and related phenotypes. - Bo Yuan; Pehlivan, Davut; Karaca, Ender; Patel, Nisha; Charng, Wu-Lin; Gambin, Tomasz; Gonzaga-Jauregui, Claudia; Sutton, V Reid; Yesil, Gozde; Bozdogan, Sevcan Tug; Tos, Tulay; Koparir, Asuman; et al. (J Clin Invest, 2015)
Cornelia de Lange syndrome (CdLS) is a genetically heterogeneous disorder that presents with extensive phenotypic variability, including facial dysmorphism, developmental delay/intellectual disability (DD/ID), abnormal extremities, and hirsutism. About 65% of patients harbor mutations in genes that encode subunits or regulators of the cohesin complex, including NIPBL, SMC1A, SMC3, RAD21, and HDAC8. Wiedemann-Steiner syndrome (WDSTS), which shares CdLS phenotypic features, is caused by mutations in lysine-specific methyltransferase 2A (KMT2A). Here, we performed whole-exome sequencing (WES) of 2 male siblings clinically diagnosed with WDSTS; this revealed a hemizygous, missense mutation in SMC1A that was predicted to be deleterious. Extensive clinical evaluation and WES of 32 Turkish patients clinically diagnosed with CdLS revealed the presence of a de novo heterozygous nonsense KMT2A mutation in 1 patient without characteristic WDSTS features. We also identified de novo heterozygous mutations in SMC3 or SMC1A that affected RNA splicing in 2 independent patients with combined CdLS and WDSTS features. Furthermore, in families from 2 separate world populations segregating an autosomal-recessive disorder with CdLS-like features, we identified homozygous mutations in TAF6, which encodes a core transcriptional regulatory pathway component. Together, our data, along with recent transcriptome studies, suggest that CdLS and related phenotypes may be "transcriptomopathies" rather than cohesinopathies.
Keywords: Adolescent; Adult; Cell Cycle Proteins; Child; Child, Preschool; Chondroitin Sulfate Proteoglycans; Chromosomal Proteins, Non-Histone; Codon, Nonsense; De Lange Syndrome; Exome; Exonucleases; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Heterozygote; Histone Deacetylases; Histone-Lysine N-Methyltransferase; Humans; Infant; Male; Myeloid-Lymphoid Leukemia Protein; Phenotype; Proteins; Repressor Proteins; Transcriptome

Identifying gene disruptions in novel balanced de novo constitutional translocations in childhood cancer patients by whole-genome sequencing. - Ritter, Deborah I; Haines, Katherine; Cheung, Hannah; Davis, Caleb F; Lau, Ching C; Berg, Jonathan S; Brown, Chester W; Thompson, Patrick A; Richard A Gibbs; Wheeler, David A; Plon, Sharon E (Genet Med, 2015)
PURPOSE: We applied whole-genome sequencing (WGS) to children diagnosed with neoplasms and found to carry apparently balanced constitutional translocations to discover novel genic disruptions. METHODS: We applied the structural variation (SV) calling programs CREST, BreakDancer, SV-STAT, and CGAP-CNV, and we developed an annotative filtering strategy to achieve nucleotide resolution at the translocations. RESULTS: We identified the breakpoints for t(6;12)(p21.1;q24.31), disrupting HNF1A in a patient diagnosed with hepatic adenomas and maturity-onset diabetes of the young (MODY). Translocation as the disruptive event of HNF1A, a gene known to be involved in MODY3, has not been previously reported. In a subject with Hodgkin lymphoma and subsequent low-grade glioma, we identified t(5;18)(q35.1;q21.2), disrupting both SLIT3 and DCC, genes previously implicated in both glioma and lymphoma. CONCLUSION: These examples suggest that implementing clinical WGS in the diagnostic workup of patients with novel but apparently balanced translocations may reveal unanticipated disruption of disease-associated genes and aid in prediction of the clinical phenotype.
Keywords: Adenoma; Adult; Age Factors; Base Sequence; Child; Child, Preschool; Chromosome Breakpoints; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 18; Chromosomes, Human, Pair 5; Chromosomes, Human, Pair 6; DCC Receptor; Diabetes Mellitus, Type 2; DNA Copy Number Variations; Female; Genetic Association Studies; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; INDEL Mutation; Liver Neoplasms; Male; Membrane Proteins; Molecular Sequence Data; Neoplasms; Polymorphism, Single Nucleotide; Receptors, Cell Surface; Translocation, Genetic; Tumor Suppressor Proteins

Lipoprotein associated phospholipase A2 activity, apolipoprotein C3 loss-of-function variants and cardiovascular disease: The Atherosclerosis Risk In Communities Study. - Pokharel, Yashashwi; Sun, Wensheng; Polfus, Linda M; Folsom, Aaron R; Heiss, Gerardo; Sharrett, A Richey; Eric Boerwinkle; Ballantyne, Christie M; Hoogeveen, Ron C (Atherosclerosis, 2015)
OBJECTIVE: Lipoprotein-associated phospholipase A2 (LpPLA2) activity was associated with higher CHD risk in a meta-analysis, which was partly dependent on circulating lipid levels. Apolipoprotein C3 loss-of-function (ApoC3 LOF) mutations were related with reduced postprandial lipemia and CHD risk. However, the association of LpPLA2 activity with ApoC3 LOF is not known. METHODS: We examined the association of LpPLA2 activity and ApoC3 LOF mutations and incident cardiovascular disease (CVD) (defined as coronary heart disease [CHD] plus ischemic stroke) and all-cause mortality in the biracial longitudinal Atherosclerosis Risk In Communities (ARIC) study. RESULTS: The mean LpPLA2 activity was 229.3 nmol/min/mL and was higher in men and whites. LpPLA2 activity correlated positively with atherogenic dyslipidemia. ApoC3 LOF carriers had lower LpPLA2 activity levels compared to non-carriers, and there was inverse association between LpPLA2 activity and ApoC3 LOF mutations in whites. In a fully adjusted model, greater LpPLA2 activity was independently associated with incident CVD (HR 1.35, 1.09-1.68 for highest vs. lowest quintile), which was mainly explained by its association with CHD, and was also associated with all-cause mortality (HR 1.65, 1.38-1.98). CONCLUSIONS: Greater LpPLA2 activity was associated with increased CHD and all-cause mortality in both whites and African-Americans in the ARIC study. The inverse relation between LpPLA2 activity and ApoC3 LOF mutations suggests that delayed lipoprotein clearance may at least in part explain the observed association of LpPLA2 activity with increased CVD risk.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Alleles; Apolipoprotein C-III; Atherosclerosis; Cardiovascular Diseases; Dyslipidemias; Female; Humans; Lipoprotein Lipase; Male; Middle Aged; Mutation; Postprandial Period; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; United States

Loss of Function Mutations in NNT Are Associated With Left Ventricular Noncompaction. - Bainbridge, Matthew N; Davis, Erica E; Choi, Wen-Yee; Dickson, Amy; Martinez, Hugo R; Wang, Min; Dinh, Huyen; Donna M Muzny; Pignatelli, Ricardo; Katsanis, Nicholas; Eric Boerwinkle; Richard A Gibbs; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Left ventricular noncompaction (LVNC) is an autosomal-dominant, genetically heterogeneous cardiomyopathy with variable severity, which may co-occur with cardiac hypertrophy. METHODS AND RESULTS: Here, we generated whole exome sequence data from multiple members from 5 families with LVNC. In 4 of 5 families, the candidate causative mutation segregates with disease in known LVNC genes MYH7 and TPM1. Subsequent sequencing of MYH7 in a larger LVNC cohort identified 7 novel likely disease causing variants. In the fifth family, we identified a frameshift mutation in NNT, a nuclear-encoded mitochondrial protein, not implicated previously in human cardiomyopathies. Resequencing of NNT in additional LVNC families identified a second likely pathogenic missense allele. Suppression of nnt in zebrafish caused early ventricular malformation and contractility defects, probably driven by altered cardiomyocyte proliferation. In vivo complementation studies showed that mutant human NNT failed to rescue nnt morpholino-induced heart dysfunction, indicating a probable haploinsufficiency mechanism. CONCLUSIONS: Together, our data expand the genetic spectrum of LVNC and demonstrate how the intersection of whole exome sequence with in vivo functional studies can accelerate the identification of genes that drive human genetic disorders.
Keywords: Animals; Animals, Genetically Modified; Embryo, Nonmammalian; Exome; Family Health; Female; Frameshift Mutation; Genetic Complementation Test; Genetic Predisposition to Disease; Humans; Isolated Noncompaction of the Ventricular Myocardium; Luminescent Proteins; Male; Microscopy, Confocal; Mitochondrial Proteins; NADP Transhydrogenase, AB-Specific; Pedigree; Sequence Analysis, DNA; Zebrafish

Lucilia cuprina genome unlocks parasitic fly biology to underpin future interventions. - Anstead, Clare A; Korhonen, Pasi K; Young, Neil D; Hall, Ross S; Jex, Aaron R; Murali, Shwetha C; Hughes, Daniel S T; Lee, Siu F; Perry, Trent; Stroehlein, Andreas J; Ansell, Brendan R E; Breugelmans, Bert; et al. (Nat Commun, 2015)
Lucilia cuprina is a parasitic fly of major economic importance worldwide. Larvae of this fly invade their animal host, feed on tissues and excretions and progressively cause severe skin disease (myiasis). Here we report the sequence and annotation of the 458-megabase draft genome of Lucilia cuprina. Analyses of this genome and the 14,544 predicted protein-encoding genes provide unique insights into the fly's molecular biology, interactions with the host animal and insecticide resistance. These insights have broad implications for designing new methods for the prevention and control of myiasis.
Keywords: Animals; Diptera; Female; Gene Expression Regulation; Genome, Insect; Insect Proteins; Insecticide Resistance; Insecticides; Larva; Male; Transcriptome

Metabolomics and Incidence of Atrial Fibrillation in African Americans: The Atherosclerosis Risk in Communities (ARIC) Study. - Alonso, Alvaro; Yu, Bing; Qureshi, Waqas T; Grams, Morgan E; Selvin, Elizabeth; Soliman, Elsayed Z; Loehr, Laura R; Chen, Lin Y; Agarwal, Sunil K; Alexander, Danny; Eric Boerwinkle (PLoS One, 2015)
BACKGROUND: Atrial fibrillation (AF) is a common arrhythmia. Application of metabolomic approaches, which may identify novel pathways and biomarkers of disease risk, to a longitudinal epidemiologic study of AF has been limited. METHODS: We determined the prospective association of 118 serum metabolites identified through untargeted metabolomics profiling with the incidence of newly-diagnosed AF in 1919 African-American men and women from the Atherosclerosis Risk in Communities study without AF at baseline (1987-1989). Incident AF cases through 2011 were ascertained from study electrocardiograms, hospital discharge codes, and death certificates. RESULTS: During a median follow-up of 22 years, we identified 183 incident AF cases. In Cox proportional hazards models adjusted for age, sex, smoking, body mass index, systolic blood pressure, use of antihypertensive medication, diabetes, prevalent heart failure, prevalent coronary heart disease, and kidney function, two conjugated bile acids (glycolithocholate sulfate and glycocholenate sulfate) were significantly associated with AF risk after correcting for multiple comparisons (p<0.0004). Multivariable-adjusted hazard ratios (95% confidence intervals) of AF were 1.22 (1.12-1.32) for glycolithocholate sulfate and 1.22 (1.10-1.35) for glycocholenate sulfate per 1-standard deviation higher levels. Associations were not appreciably different after additional adjustment for alcohol consumption or concentrations of circulating albumin and liver enzymes. CONCLUSION: We found an association of higher levels of two bile acids with an increased risk of AF, pointing to a potential novel pathway in AF pathogenesis. Replication of results in independent studies is warranted.
Keywords: Atherosclerosis; Atrial Fibrillation; Black or African American; Female; Humans; Incidence; Male; Metabolomics; Middle Aged; Residence Characteristics

Multiethnic genome-wide association study of cerebral white matter hyperintensities on MRI. - Verhaaren, Benjamin F J; Debette, Stephanie; Bis, Joshua C; Smith, Jennifer A; Ikram, M Kamran; Adams, Hieab H; Beecham, Ashley H; Rajan, Kumar B; Lopez, Lorna M; Barral, Sandra; van Buchem, Mark A; van der Grond, Jeroen; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: The burden of cerebral white matter hyperintensities (WMH) is associated with an increased risk of stroke, dementia, and death. WMH are highly heritable, but their genetic underpinnings are incompletely characterized. To identify novel genetic variants influencing WMH burden, we conducted a meta-analysis of multiethnic genome-wide association studies. METHODS AND RESULTS: We included 21 079 middle-aged to elderly individuals from 29 population-based cohorts, who were free of dementia and stroke and were of European (n=17 936), African (n=1943), Hispanic (n=795), and Asian (n=405) descent. WMH burden was quantified on MRI either by a validated automated segmentation method or a validated visual grading scale. Genotype data in each study were imputed to the 1000 Genomes reference. Within each ethnic group, we investigated the relationship between each single-nucleotide polymorphism and WMH burden using a linear regression model adjusted for age, sex, intracranial volume, and principal components of ancestry. A meta-analysis was conducted for each ethnicity separately and for the combined sample. In the European descent samples, we confirmed a previously known locus on chr17q25 (P=2.7×10(-19)) and identified novel loci on chr10q24 (P=1.6×10(-9)) and chr2p21 (P=4.4×10(-8)). In the multiethnic meta-analysis, we identified 2 additional loci, on chr1q22 (P=2.0×10(-8)) and chr2p16 (P=1.5×10(-8)). The novel loci contained genes that have been implicated in Alzheimer disease (chr2p21 and chr10q24), intracerebral hemorrhage (chr1q22), neuroinflammatory diseases (chr2p21), and glioma (chr10q24 and chr2p16). CONCLUSIONS: We identified 4 novel genetic loci that implicate inflammatory and glial proliferative pathways in the development of WMH in addition to previously proposed ischemic mechanisms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Models, Genetic; Racial Groups; Stroke; White Matter

Mutations in COL27A1 cause Steel syndrome and suggest a founder mutation effect in the Puerto Rican population. - Gonzaga-Jauregui, Claudia; Gamble, Candace N; Bo Yuan; Penney, Samantha; Jhangiani, Shalini; Donna M Muzny; Richard A Gibbs; Lupski, James R; Hecht, Jacqueline T (Eur J Hum Genet, 2015)
Osteochondrodysplasias represent a large group of developmental structural disorders that can be caused by mutations in a variety of genes responsible for chondrocyte development, differentiation, mineralization and early ossification. The application of whole-exome sequencing to disorders apparently segregating as Mendelian traits has proven to be an effective approach to disease gene identification for conditions with unknown molecular etiology. We identified a homozygous missense variant p.(Gly697Arg) in COL27A1, in a family with Steel syndrome and no consanguinity. Interestingly, the identified variant seems to have arisen as a founder mutation in the Puerto Rican population.
Keywords: Amino Acid Sequence; Child, Preschool; Comparative Genomic Hybridization; Exome; Female; Fibrillar Collagens; Follow-Up Studies; Founder Effect; Genotype; Hispanic or Latino; Humans; Infant; Male; Molecular Sequence Data; Mutation; Osteochondrodysplasias; Pedigree; Polymorphism, Single Nucleotide; Prostaglandins F; Puerto Rico; Sequence Alignment

Mutations in human IFT140 cause non-syndromic retinal degeneration. - Xu, Mingchu; Yang, Lizhu; Wang, Feng; Li, Huajin; Wang, Xia; Wang, Weichen; Ge, Zhongqi; Wang, Keqing; Zhao, Li; Li, Hui; Yumei Li; Sui, Ruifang; et al. (Hum Genet, 2015)
Leber congenital amaurosis (LCA) and retinitis pigmentosa (RP) are two genetically heterogeneous retinal degenerative disorders. Despite the identification of a number of genes involved in LCA and RP, the genetic etiology remains unknown in many patients. In this study, we aimed to identify novel disease-causing genes of LCA and RP. Retinal capture sequencing was initially performed to screen mutations in known disease-causing genes in different cohorts of LCA and RP patients. For patients with negative results, we performed whole exome sequencing and applied a series of variant filtering strategies. Sanger sequencing was done to validate candidate causative IFT140 variants. Exome sequencing data analysis led to the identification of IFT140 variants in multiple unrelated non-syndromic LCA and RP cases. All the variants are extremely rare and predicted to be damaging. All the variants passed Sanger validation and segregation tests provided that the family members' DNA was available. The results expand the phenotype spectrum of IFT140 mutations to non-syndromic retinal degeneration, thus extending our understanding of intraflagellar transport and primary cilia biology in the retina. This work also improves the molecular diagnosis of retinal degenerative disease.
Keywords: Adult; Amino Acid Sequence; Carrier Proteins; Child; Female; Genetic Association Studies; Humans; Leber Congenital Amaurosis; Male; Middle Aged; Mutation, Missense; Pedigree; Retinitis Pigmentosa

Mutations in PNPLA6 are linked to photoreceptor degeneration and various forms of childhood blindness. - Kmoch, S; Majewski, J; Ramamurthy, V; Cao, S; Fahiminiya, S; Ren, H; MacDonald, I M; Lopez, I; Sun, V; Keser, V; Khan, A; Stránecký, V; et al. (Nat Commun, 2015)
Blindness due to retinal degeneration affects millions of people worldwide, but many disease-causing mutations remain unknown. PNPLA6 encodes the patatin-like phospholipase domain containing protein 6, also known as neuropathy target esterase (NTE), which is the target of toxic organophosphates that induce human paralysis due to severe axonopathy of large neurons. Mutations in PNPLA6 also cause human spastic paraplegia characterized by motor neuron degeneration. Here we identify PNPLA6 mutations in childhood blindness in seven families with retinal degeneration, including Leber congenital amaurosis and Oliver McFarlane syndrome. PNPLA6 localizes mostly at the inner segment plasma membrane in photoreceptors and mutations in Drosophila PNPLA6 lead to photoreceptor cell death. We also report that lysophosphatidylcholine and lysophosphatidic acid levels are elevated in mutant Drosophila. These findings show a role for PNPLA6 in photoreceptor survival and identify phospholipid metabolism as a potential therapeutic target for some forms of blindness.
Keywords: Amino Acid Sequence; Animals; Blindness; Child; Child, Preschool; Drosophila; Female; Humans; Male; Mice; Mice, Inbred C57BL; Microscopy, Fluorescence; Molecular Sequence Data; Mutation; Pedigree; Phenotype; Phospholipases; Phospholipids; Retina; Retinal Degeneration; Sequence Analysis, DNA; Sequence Homology, Amino Acid; Spectrometry, Mass, Electrospray Ionization

New mutations in the RAB28 gene in 2 Spanish families with cone-rod dystrophy. - Riveiro-Álvarez, Rosa; Xie, Yajing Angela; López-Martínez, Miguel-Ángel; Gambin, Tomasz; Pérez-Carro, Raquel; Ávila-Fernández, Almudena; López-Molina, María-Isabel; Zernant, Jana; Jhangiani, Shalini; Donna M Muzny; Bo Yuan; Eric Boerwinkle; et al. (JAMA Ophthalmol, 2015)
IMPORTANCE: The families evaluated in this study represent the second report of cone-rod dystrophy (CRD) cases caused by mutations in RAB28, a recently discovered gene associated with CRD. OBJECTIVE: To determine the disease-causing gene in 2 families of Spanish descent presenting with CRD who do not have ABCA4 mutations. DESIGN, SETTING, AND PARTICIPANTS: Molecular genetics and observational case studies of 2 families, each with 1 affected proband with CRD and 3 or 5 unaffected family members. The affected individual from each family received a complete ophthalmic examination including assessment of refractive errors and best-corrected visual acuity, biomicroscopy, color fundus photography, electroretinography analysis, and visual-evoked potential analysis. After complete sequencing of the ABCA4 gene with negative results, the screening for disease-causing mutations was performed by whole-exome sequencing. Possible disease-associated variants were determined by filtering based on minor allele frequency, predicted pathogenicity, and segregation analysis in all family members. MAIN OUTCOMES AND MEASURES: The appearance of the macula was evaluated by clinical examination, fundus photography, and fundus autofluorescence imaging, and visual function was assessed by electroretinography. Disease-causing mutations were assessed by sequence analyses. RESULTS: Ophthalmologic findings included markedly reduced visual acuity, bull's eye maculopathy, foveal hyperpigmentation, peripapillary atrophy, dyschromatopsia, extinguished photopic responses, and reduced scotopic responses observed on electroretinography consistent with the CRD phenotype often associated with ABCA4 mutations. Although no ABCA4 mutations were detected in either patient, whole-exome sequencing analysis identified 2 new homozygous mutations in the recently described RAB28 gene, the c.172 + 1G>C splice site variant in IVS2 and the missense c.T651G:p.C217W substitution. Both variants were determined as deleterious by predictive programs and were segregated with the disease in both families. Sequencing of 107 additional patients of Spanish descent with CRD did not reveal other cases with RAB28 mutations. CONCLUSIONS AND RELEVANCE: Deleterious mutations in RAB28 result in a classic CRD phenotype and are an infrequent cause of CRD in the Spanish population.
Keywords: Adolescent; Adult; Child; Diagnosis, Differential; DNA Mutational Analysis; Female; Follow-Up Studies; Genetic Predisposition to Disease; Hispanic or Latino; Humans; Male; Microscopy, Acoustic; Mutation; Pedigree; Phenotype; rab GTP-Binding Proteins; Retinitis Pigmentosa; Retrospective Studies; Young Adult

Next-generation sequencing and novel variant determination in a cohort of 92 familial exudative vitreoretinopathy patients. - Salvo, Jason; Lyubasyuk, Vera; Xu, Mingchu; Wang, Hui; Wang, Feng; Nguyen, Duy; Wang, Keqing; Luo, Hongrong; Wen, Cindy; Shi, Catherine; Lin, Danni; Zhang, Kang; et al. (Invest Ophthalmol Vis Sci, 2015)
PURPOSE: Familial exudative vitreoretinopathy (FEVR) is a developmental disease that can cause visual impairment and retinal detachment at a young age. Four genes involved in the Wnt signaling pathway were previously linked to this disease: NDP, FDZ4, LRP5, and TSPAN12. Identification of novel disease-causing alleles allows for a deeper understanding of the disease, better molecular diagnosis, and improved treatment. METHODS: Sequencing libraries from 92 FEVR patients were generated using a custom capture panel to enrich for 163 known retinal disease-causing genes in humans. Samples were processed using next generation sequencing (NGS) techniques followed by data analysis to identify and classify single nucleotide variants and small insertions and deletions. Sanger validation and segregation testing were used to verify suspected variants. RESULTS: Of the cohort of 92, 45 patients were potentially solved (48.9%). Solved cases resulted from the determination of 49 unique mutations, 41 of which are novel. Of the novel variants discovered, 13 were highly likely to cause FEVR due to the nature of these variants (frameshifting indels, splicing mutations, and nonsense variants types). To our knowledge, this is the largest study of a FEVR cohort using NGS. CONCLUSIONS: We were able to determine probable disease-causing variants in a large number of FEVR patients, the majority of which were novel. Knowledge of these variants will help to further characterize and diagnose FEVR.
Keywords: Cohort Studies; DNA Mutational Analysis; DNA-Binding Proteins; Eye Diseases, Hereditary; Eye Proteins; Familial Exudative Vitreoretinopathies; Female; Frizzled Receptors; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Low Density Lipoprotein Receptor-Related Protein-5; Male; Mutation; Nerve Tissue Proteins; Retinal Diseases; Sequence Analysis, DNA; Tetraspanins; Transcription Factors

NGS-based Molecular diagnosis of 105 eyeGENE(®) probands with Retinitis Pigmentosa. - Ge, Zhongqi; Bowles, Kristen; Goetz, Kerry; Scholl, Hendrik P N; Wang, Feng; Wang, Xinjing; Xu, Shan; Wang, Keqing; Wang, Hui; Rui Chen (Sci Rep, 2015)
The National Ophthalmic Disease Genotyping and Phenotyping Network (eyeGENE(®)) was established in an effort to facilitate basic and clinical research of human inherited eye disease. In order to provide high quality genetic testing to eyeGENE(®)'s enrolled patients which potentially aids clinical diagnosis and disease treatment, we carried out a pilot study and performed Next-generation sequencing (NGS) based molecular diagnosis for 105 Retinitis Pigmentosa (RP) patients randomly selected from the network. A custom capture panel was designed, which incorporated 195 known retinal disease genes, including 61 known RP genes. As a result, disease-causing mutations were identified in 52 out of 105 probands (solving rate of 49.5%). A total of 82 mutations were identified, and 48 of them were novel. Interestingly, for three probands the molecular diagnosis was inconsistent with the initial clinical diagnosis, while for five probands the molecular information suggested a different inheritance model other than that assigned by the physician. In conclusion, our study demonstrated that NGS target sequencing is efficient and sufficiently precise for molecular diagnosis of a highly heterogeneous patient cohort from eyeGENE(®).
Keywords: Antigens, Neoplasm; Cell Cycle Proteins; Child; Child, Preschool; Cohort Studies; Cytoskeletal Proteins; Female; Genetic Association Studies; Genetic Testing; High-Throughput Nucleotide Sequencing; Humans; Inheritance Patterns; Male; Molecular Diagnostic Techniques; Mutation; Neoplasm Proteins; Pedigree; Phenotype; Receptors, G-Protein-Coupled; Receptors, Glutamate; Retinitis Pigmentosa

Nonrecurrent 17p11.2p12 Rearrangement Events that Result in Two Concomitant Genomic Disorders: The PMP22-RAI1 Contiguous Gene Duplication Syndrome. - Bo Yuan; Harel, Tamar; Gu, Shen; Liu, Pengfei; Burglen, Lydie; Chantot-Bastaraud, Sandra; Gelowani, Violet; Beck, Christine R; Carvalho, Claudia M B; Cheung, Sau Wai; Coe, Andrew; Malan, Valérie; et al. (Am J Hum Genet, 2015)
The genomic duplication associated with Potocki-Lupski syndrome (PTLS) maps in close proximity to the duplication associated with Charcot-Marie-Tooth disease type 1A (CMT1A). PTLS is characterized by hypotonia, failure to thrive, reduced body weight, intellectual disability, and autistic features. CMT1A is a common autosomal dominant distal symmetric peripheral polyneuropathy. The key dosage-sensitive genes RAI1 and PMP22 are respectively associated with PTLS and CMT1A. Recurrent duplications accounting for the majority of subjects with these conditions are mediated by nonallelic homologous recombination between distinct low-copy repeat (LCR) substrates. The LCRs flanking a contiguous genomic interval encompassing both RAI1 and PMP22 do not share extensive homology; thus, duplications encompassing both loci are rare and potentially generated by a different mutational mechanism. We characterized genomic rearrangements that simultaneously duplicate PMP22 and RAI1, including nine potential complex genomic rearrangements, in 23 subjects by high-resolution array comparative genomic hybridization and breakpoint junction sequencing. Insertions and microhomologies were found at the breakpoint junctions, suggesting potential replicative mechanisms for rearrangement formation. At the breakpoint junctions of these nonrecurrent rearrangements, enrichment of repetitive DNA sequences was observed, indicating that they might predispose to genomic instability and rearrangement. Clinical evaluation revealed blended PTLS and CMT1A phenotypes with a potential earlier onset of neuropathy. Moreover, additional clinical findings might be observed due to the extra duplicated material included in the rearrangements. Our genomic analysis suggests replicative mechanisms as a predominant mechanism underlying PMP22-RAI1 contiguous gene duplications and provides further evidence supporting the role of complex genomic architecture in genomic instability.
Keywords: Abnormalities, Multiple; Charcot-Marie-Tooth Disease; Child; Child, Preschool; Chromosome Disorders; Chromosome Duplication; Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; Female; Follow-Up Studies; Gene Duplication; Gene Rearrangement; Genome, Human; Genomics; Humans; Infant; Male; Models, Genetic; Myelin Proteins; Phenotype; Prognosis; Recombination, Genetic; Trans-Activators; Transcription Factors

PLD3 variants in population studies. - van der Lee, Sven J; Holstege, Henne; Wong, Tsz Hang; Jakobsdottir, Johanna; Bis, Joshua C; Chouraki, Vincent; van Rooij, Jeroen G J; Grove, Megan L; Smith, Albert V; Amin, Najaf; Choi, Seung-Hoan; Beiser, Alexa S; et al. (Nature, 2015)
Keywords: Alzheimer Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Male; Phospholipase D

Rare variants in the notch signaling pathway describe a novel type of autosomal recessive Klippel-Feil syndrome. - Karaca, Ender; Yuregir, Ozge O; Bozdogan, Sevcan T; Aslan, Huseyin; Pehlivan, Davut; Jhangiani, Shalini N; Akdemir, Zeynep C; Gambin, Tomasz; Bayram, Yavuz; Atik, Mehmed M; Erdin, Serkan; Donna M Muzny; et al. (Am J Med Genet A, 2015)
Klippel-Feil syndrome is a rare disorder represented by a subgroup of segmentation defects of the vertebrae and characterized by fusion of the cervical vertebrae, low posterior hairline, and short neck with limited motion. Both autosomal dominant and recessive inheritance patterns were reported in families with Klippel-Feil. Mutated genes for both dominant (GDF6 and GDF3) and recessive (MEOX1) forms of Klippel-Feil syndrome have been shown to be involved in somite development via transcription regulation and signaling pathways. Heterotaxy arises from defects in proteins that function in the development of left-right asymmetry of the developing embryo. We describe a consanguineous family with a male proband who presents with classical Klippel-Feil syndrome together with heterotaxy (situs inversus totalis). The present patient also had Sprengel's deformity, deformity of the sternum, and a solitary kidney. Using exome sequencing, we identified a homozygous frameshift mutation (c.299delT; p.L100fs) in RIPPLY2, a gene shown to play a crucial role in somitogenesis and participate in the Notch signaling pathway via negatively regulating Tbx6. Our data confirm RIPPLY2 as a novel gene for autosomal recessive Klippel-Feil syndrome, and in addition-from a mechanistic standpoint-suggest the possibility that mutations in RIPPLY2 could also lead to heterotaxy. © 2015 Wiley Periodicals, Inc.
Keywords: Adolescent; Base Sequence; Female; Humans; Klippel-Feil Syndrome; Male; Molecular Sequence Data; Mutation; Pedigree; Radiography; Receptors, Notch; Signal Transduction; Spine

Recurrent internal tandem duplications of BCOR in clear cell sarcoma of the kidney. - Roy, Angshumoy; Kumar, Vijetha; Zorman, Barry; Fang, Erica; Haines, Katherine M; Harshavardhan Doddapaneni; Hampton, Oliver A; White, Simon; Bavle, Abhishek A; Patel, Nimesh R; Eldin, Karen W; John Hicks, M; et al. (Nat Commun, 2015)
The X-linked BCL-6 co-repressor (BCOR) gene encodes a key constituent of a variant polycomb repressive complex (PRC) that is mutated or translocated in human cancers. Here we report on the identification of somatic internal tandem duplications (ITDs) clustering in the C terminus of BCOR in 23 of 27 (85%) pediatric clear cell sarcomas of the kidney (CCSK) from two independent cohorts. We profile CCSK tumours using a combination of whole-exome, transcriptome and targeted sequencing. Identical ITD mutations are found in primary and relapsed tumour pairs but not in adjacent normal kidney or blood. Mutant BCOR transcripts and proteins are markedly upregulated in ITD-positive tumours. Transcriptome analysis of ITD-positive CCSKs reveals enrichment for PRC2-regulated genes and similarity to undifferentiated sarcomas harbouring BCOR-CCNB3 fusions. The discovery of recurrent BCOR ITDs defines a major oncogenic event in this childhood sarcoma with significant implications for diagnostic and therapeutic approaches to this tumour.
Keywords: Case-Control Studies; Child, Preschool; Female; Gene Duplication; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Humans; Immunoblotting; Immunohistochemistry; Infant; Kidney Neoplasms; Male; Mutation; Neoplasm Recurrence, Local; Proto-Oncogene Proteins; Repressor Proteins; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Sarcoma, Clear Cell; Sequence Analysis, DNA; Sequence Analysis, RNA; Tandem Repeat Sequences

Response. - Bainbridge, Matthew; Bondy, Melissa L (J Natl Cancer Inst, 2015)
Keywords: Brain Neoplasms; Female; Germ-Line Mutation; Glioma; Humans; Male; Telomere-Binding Proteins

Rise and fall of subclones from diagnosis to relapse in pediatric B-acute lymphoblastic leukaemia. - Ma, Xiaotu; Edmonson, Michael; Yergeau, Donald; Donna M Muzny; Hampton, Oliver A; Rusch, Michael; Song, Guangchun; Easton, John; Harvey, Richard C; Wheeler, David A; Ma, Jing; Harshavardhan Doddapaneni; et al. (Nat Commun, 2015)
There is incomplete understanding of genetic heterogeneity and clonal evolution during cancer progression. Here we use deep whole-exome sequencing to describe the clonal architecture and evolution of 20 pediatric B-acute lymphoblastic leukaemias from diagnosis to relapse. We show that clonal diversity is comparable at diagnosis and relapse and clonal survival from diagnosis to relapse is not associated with mutation burden. Six pathways were frequently mutated, with NT5C2, CREBBP, WHSC1, TP53, USH2A, NRAS and IKZF1 mutations enriched at relapse. Half of the leukaemias had multiple subclonal mutations in a pathway or gene at diagnosis, but mostly with only one, usually minor clone, surviving therapy to acquire additional mutations and become the relapse founder clone. Relapse-specific mutations in NT5C2 were found in nine cases, with mutations in four cases being in descendants of the relapse founder clone. These results provide important insights into the genetic basis of treatment failure in ALL and have implications for the early detection of mutations driving relapse.
Keywords: 5'-Nucleotidase; Child; Clonal Evolution; Clone Cells; CREB-Binding Protein; Disease Progression; DNA Copy Number Variations; Exome; Extracellular Matrix Proteins; Female; GTP Phosphohydrolases; Histone-Lysine N-Methyltransferase; Humans; Ikaros Transcription Factor; Male; Membrane Proteins; Mutation; Neoplasm Recurrence, Local; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Repressor Proteins; Tumor Suppressor Protein p53

Sequence variation in telomerase reverse transcriptase (TERT) as a determinant of risk of cardiovascular disease: the Atherosclerosis Risk in Communities (ARIC) study. - Bressler, Jan; Franceschini, Nora; Demerath, Ellen W; Mosley, Thomas H; Folsom, Aaron R; Eric Boerwinkle (BMC Med Genet, 2015)
BACKGROUND: Telomerase reverse transcriptase (TERT) maintains telomere ends during DNA replication by catalyzing the addition of short telomere repeats. The expression of telomerase is normally repressed in somatic cells leading to a gradual shortening of telomeres and cellular senescence with aging. Interindividual variation in leukocyte telomere length has been previously associated with susceptibility to cardiovascular disease. The aim of the present study was to determine whether six variants in the TERT gene are associated with risk of incident coronary heart disease, incident ischemic stroke, and mortality in participants in the biracial population-based Atherosclerosis Risk in Communities (ARIC) study, including rs2736100 that was found to influence mean telomere length in a genome-wide analysis. METHODS: ARIC is a prospective study of the etiology and natural history of atherosclerosis in 15,792 individuals aged 45 to 64 years at baseline in 1987-1989. Haplotype tagging SNPs in TERT were genotyped using a custom array containing nearly 49,000 SNPs in 2,100 genes associated with cardiovascular and metabolic phenotypes. Cox proportional hazards models were used to assess the association between the TERT polymorphisms and incident cardiovascular disease and mortality over a 20-year follow-up period in 8,907 whites and 3,022 African-Americans with no history of disease at the baseline examination, while individuals with prevalent cardiovascular disease were not excluded from the analyses of mortality. RESULTS: After adjustment for age and gender, and assuming an additive genetic model, rs2736122 and rs2853668 were nominally associated with incident coronary heart disease (hazards rate ratio = 1.20, p = 0.02, 95 % confidence interval = 1.03- 1.40) and stroke (hazards rate ratio = 1.17, p = 0.05, 95 % confidence interval = 1.00 - 1.38), respectively, in African-Americans. None of the variants was significantly associated with cardiovascular disease in white study participants or with mortality in either racial group. CONCLUSIONS: Replication in additional population-based samples combined with genotyping of polymorphisms in other genes involved in maintenance of telomere length may help to determine whether genetic variants associated with telomere homeostasis influence the risk of cardiovascular disease in middle-aged adults.
Keywords: Atherosclerosis; Black or African American; Cellular Senescence; Coronary Disease; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prospective Studies; Risk; Stroke; Telomerase; Telomere Homeostasis; White People

Structure and function of the healthy pre-adolescent pediatric gut microbiome. - Hollister, Emily B; Riehle, Kevin; Luna, Ruth Ann; Weidler, Erica M; Rubio-Gonzales, Michelle; Mistretta, Toni-Ann; Raza, Sabeen; Harshavardhan Doddapaneni; Ginger A Metcalf; Donna M Muzny; Richard A Gibbs; Petrosino, Joseph F; et al. (Microbiome, 2015)
BACKGROUND: The gut microbiome influences myriad host functions, including nutrient acquisition, immune modulation, brain development, and behavior. Although human gut microbiota are recognized to change as we age, information regarding the structure and function of the gut microbiome during childhood is limited. Using 16S rRNA gene and shotgun metagenomic sequencing, we characterized the structure, function, and variation of the healthy pediatric gut microbiome in a cohort of school-aged, pre-adolescent children (ages 7-12 years). We compared the healthy pediatric gut microbiome with that of healthy adults previously recruited from the same region (Houston, TX, USA). RESULTS: Although healthy children and adults harbored similar numbers of taxa and functional genes, their composition and functional potential differed significantly. Children were enriched in Bifidobacterium spp., Faecalibacterium spp., and members of the Lachnospiraceae, while adults harbored greater abundances of Bacteroides spp. From a functional perspective, significant differences were detected with respect to the relative abundances of genes involved in vitamin synthesis, amino acid degradation, oxidative phosphorylation, and triggering mucosal inflammation. Children's gut communities were enriched in functions which may support ongoing development, while adult communities were enriched in functions associated with inflammation, obesity, and increased risk of adiposity. CONCLUSIONS: Previous studies suggest that the human gut microbiome is relatively stable and adult-like after the first 1 to 3 years of life. Our results suggest that the healthy pediatric gut microbiome harbors compositional and functional qualities that differ from those of healthy adults and that the gut microbiome may undergo a more prolonged development than previously suspected.
Keywords: Adult; Age Factors; Biodiversity; Child; Cluster Analysis; DNA Barcoding, Taxonomic; Female; Gastrointestinal Microbiome; Healthy Volunteers; Humans; Male; Metagenome; RNA, Ribosomal, 16S

Successful diagnosis of HIBCH deficiency from exome sequencing and positive retrospective analysis of newborn screening cards in two siblings presenting with Leigh's disease. - Stiles, Ashlee R; Ferdinandusse, Sacha; Besse, Arnaud; Appadurai, Vivek; Leydiker, Karen B; Cambray-Forker, E J; Bonnen, Penelope E; Abdenur, Jose E (Mol Genet Metab, 2015)
PURPOSE: 3-Hydroxyisobutryl-CoA hydrolase (HIBCH) deficiency is a rare disorder of valine metabolism. We present a family with the oldest reported subjects with HIBCH deficiency and provide support that HIBCH deficiency should be included in the differential for elevated hydroxy-C4-carnitine in newborn screening (NBS). METHODS: Whole exome sequencing (WES) was performed on one affected sibling. HIBCH enzymatic activity was measured in patient fibroblasts. Acylcarnitines were measured by electrospray ionization tandem mass spectrometry (ESI-MS/MS). Disease incidence was estimated using a cohort of 61,434 individuals. RESULTS: Two siblings presented with infantile-onset, progressive neurodegenerative disease. WES identified a novel homozygous variant in HIBCH c.196C>T; p.Arg66Trp. HIBCH enzymatic activity was significantly reduced in patients' fibroblasts. Acylcarnitine analysis showed elevated hydroxy-C4-carnitine in blood spots of both affected siblings, including in their NBS cards, while plasma acylcarnitines were normal. Estimates show HIBCH deficiency incidence as high as 1 in ~130,000 individuals. CONCLUSION: We describe a novel family with HIBCH deficiency at the biochemical, enzymatic and molecular level. Disease incidence estimates indicate HIBCH deficiency may be under-diagnosed. This together with the elevated hydroxy-C4-carnitine found in the retrospective analysis of our patient's NBS cards suggests that this disorder could be screened for by NBS programs and should be added to the differential diagnosis for elevated hydroxy-C4-carnitine which is already measured in most NBS programs using MS/MS.
Keywords: Abnormalities, Multiple; Adolescent; Amino Acid Metabolism, Inborn Errors; Carnitine; Child; Child, Preschool; Cohort Studies; Exome; Female; Fibroblasts; Humans; Infant; Infant, Newborn; Leigh Disease; Male; Mass Spectrometry; Neonatal Screening; Prognosis; Retrospective Studies; Sequence Analysis, DNA; Siblings; Thiolester Hydrolases

Targeted sequencing in chromosome 17q linkage region identifies familial glioma candidates in the Gliogene Consortium. - Jalali, Ali; Amirian, E Susan; Bainbridge, Matthew N; Armstrong, Georgina N; Liu, Yanhong; Tsavachidis, Spyros; Jhangiani, Shalini N; Plon, Sharon E; Lau, Ching C; Claus, Elizabeth B; Barnholtz-Sloan, Jill S; Il'yasova, Dora; et al. (Sci Rep, 2015)
Glioma is a rare, but highly fatal, cancer that accounts for the majority of malignant primary brain tumors. Inherited predisposition to glioma has been consistently observed within non-syndromic families. Our previous studies, which involved non-parametric and parametric linkage analyses, both yielded significant linkage peaks on chromosome 17q. Here, we use data from next generation and Sanger sequencing to identify familial glioma candidate genes and variants on chromosome 17q for further investigation. We applied a filtering schema to narrow the original list of 4830 annotated variants down to 21 very rare (<0.1% frequency), non-synonymous variants. Our findings implicate the MYO19 and KIF18B genes and rare variants in SPAG9 and RUNDC1 as candidates worthy of further investigation. Burden testing and functional studies are planned.
Keywords: Adult; Brain Neoplasms; Chromosomes, Human, Pair 17; Family; Female; Genetic Linkage; Genetic Variation; Glioma; Humans; Male; Middle Aged; Mutation; Pedigree; Sequence Analysis, DNA; Young Adult

TET2 and CSMD1 genes affect SBP response to hydrochlorothiazide in never-treated essential hypertensives. - Chittani, Martina; Zaninello, Roberta; Lanzani, Chiara; Frau, Francesca; Ortu, Maria F; Salvi, Erika; Fresu, Giovanni; Citterio, Lorena; Braga, Daniele; Piras, Daniela A; Carpini, Simona Delli; Velayutham, Dinesh; et al. (J Hypertens, 2015)
BACKGROUND: Thiazide diuretics have been recommended as a first-line antihypertensive treatment, although the choice of 'the right drug in the individual essential hypertensive patient' remains still empirical. Essential hypertension is a complex, polygenic disease derived from the interaction of patient's genetic background with the environment. Pharmacogenomics could be a useful tool to pinpoint gene variants involved in antihypertensive drug response, thus optimizing therapeutic advantages and minimizing side effects. METHODS AND RESULTS: We looked for variants associated with blood pressure response to hydrochlorothiazide over an 8-week follow-up by means of a genome-wide association analysis in two Italian cohorts of never-treated essential hypertensive patients: 343 samples from Sardinia and 142 from Milan. TET2 and CSMD1 as plausible candidate genes to affect SBP response to hydrochlorothiazide were identified. The specificity of our findings for hydrochlorothiazide was confirmed in an independent cohort of essential hypertensive patients treated with losartan. Our best findings were also tested for replication in four independent hypertensive samples of European Ancestry, such as GENetics of drug RESponsiveness in essential hypertension, Genetic Epidemiology of Responses to Antihypertensives, NORdic DILtiazem intervention, Pharmacogenomics Evaluation of Antihypertensive Responses, and Campania Salute Network-StayOnDiur. We validated a polymorphism in CSMD1 and UGGT2. CONCLUSION: This exploratory study reports two plausible loci associated with SBP response to hydrochlorothiazide: TET2, an aldosterone-responsive mediator of αENaC gene transcription; and CSMD1, previously described as associated with hypertension in a case-control study.
Keywords: Adult; Aged; Aldosterone; Antihypertensive Agents; Blood Pressure; Case-Control Studies; Dioxygenases; DNA-Binding Proteins; Essential Hypertension; Genome-Wide Association Study; Humans; Hydrochlorothiazide; Hypertension; Italy; Losartan; Male; Membrane Proteins; Middle Aged; Pharmacogenetics; Proto-Oncogene Proteins; Sodium Chloride Symporter Inhibitors; Systole; Tumor Suppressor Proteins; White People

Transethnic meta-analysis suggests genetic variation in the HEME pathway influences potassium response in patients treated with hydrochlorothiazide. - Del-Aguila, J L; Cooper-Dehoff, R M; Chapman, A B; Gums, J G; Beitelshees, A L; Bailey, K; Turner, S T; Johnson, J A; Eric Boerwinkle (Pharmacogenomics J, 2015)
Hypokalemia is a recognized adverse effect of thiazide diuretic treatment. This phenomenon, which may impair insulin secretion, has been suggested to be a reason for the adverse effects on glucose metabolism associated with thiazide diuretic treatment of hypertension. However, the mechanisms underlying thiazide diuretic-induced hypokalemia are not well understood. In an effort to identify genes or genomic regions associated with potassium response to hydrochlorothiazide, without a priori knowledge of biologic effects, we performed a genome-wide association study and a multiethnic meta-analysis in 718 European- and African-American hypertensive participants from two different pharmacogenetic studies. Single-nucleotide polymorphisms rs10845697 (Bayes factor=5.560) on chromosome 12, near to the HEME binding protein 1 gene, and rs11135740 (Bayes factor=5.258) on chromosome 8, near to the Mitoferrin-1 gene, reached genome-wide association study significance (Bayes factor >5). These results, if replicated, suggest a novel mechanism involving effects of genes in the HEME pathway influencing hydrochlorothiazide-induced renal potassium loss.
Keywords: Antihypertensive Agents; Bayes Theorem; Black or African American; Carrier Proteins; Cation Transport Proteins; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 8; Female; Genome-Wide Association Study; Heme; Heme-Binding Proteins; Hemeproteins; Humans; Hydrochlorothiazide; Hypertension; Hypokalemia; Male; Middle Aged; Mitochondrial Proteins; Polymorphism, Single Nucleotide; Potassium; White People

Variants for HDL-C, LDL-C, and triglycerides identified from admixture mapping and fine-mapping analysis in African American families. - Shetty, Priya B; Tang, Hua; Feng, Tao; Tayo, Bamidele; Morrison, Alanna C; Kardia, Sharon L R; Hanis, Craig L; Arnett, Donna K; Hunt, Steven C; Eric Boerwinkle; Rao, Dabeeru C; Cooper, Richard S; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Admixture mapping of lipids was followed-up by family-based association analysis to identify variants for cardiovascular disease in African Americans. METHODS AND RESULTS: The present study conducted admixture mapping analysis for total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides. The analysis was performed in 1905 unrelated African American subjects from the National Heart, Lung and Blood Institute's Family Blood Pressure Program (FBPP). Regions showing admixture evidence were followed-up with family-based association analysis in 3556 African American subjects from the FBPP. The admixture mapping and family-based association analyses were adjusted for age, age(2), sex, body mass index, and genome-wide mean ancestry to minimize the confounding caused by population stratification. Regions that were suggestive of local ancestry association evidence were found on chromosomes 7 (low-density lipoprotein cholesterol), 8 (high-density lipoprotein cholesterol), 14 (triglycerides), and 19 (total cholesterol and triglycerides). In the fine-mapping analysis, 52 939 single-nucleotide polymorphisms (SNPs) were tested and 11 SNPs (8 independent SNPs) showed nominal significant association with high-density lipoprotein cholesterol (2 SNPs), low-density lipoprotein cholesterol (4 SNPs), and triglycerides (5 SNPs). The family data were used in the fine-mapping to identify SNPs that showed novel associations with lipids and regions, including genes with known associations for cardiovascular disease. CONCLUSIONS: This study identified regions on chromosomes 7, 8, 14, and 19 and 11 SNPs from the fine-mapping analysis that were associated with high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides for further studies of cardiovascular disease in African Americans.
Keywords: Adult; Aged; Aged, 80 and over; Black or African American; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Chromosome Mapping; Chromosomes, Human; Family; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Triglycerides

Whole exome sequencing confirms the clinical diagnosis of Marfan syndrome combined with X-linked hypophosphatemia. - Sheng, Xunlun; Chen, Xue; Lei, Bo; Rui Chen; Wang, Hui; Zhang, Fangxia; Rong, Weining; Ha, Ruoshui; Liu, Yani; Zhao, Feng; Yang, Peizeng; Zhao, Chen (J Transl Med, 2015)
BACKGROUND: To determine the genetic lesions and to modify the clinical diagnosis for a Chinese family with significant intrafamilial phenotypic diversities and unusual presentations. METHODS: Three affected patients and the asymptomatic father were included and received comprehensive systemic examinations. Whole exome sequencing (WES) was performed for mutation detection. Structural modeling test was applied to analyze the potential structural changes caused by the missense substitution. RESULTS: The proband showed a wide spectrum of systemic anomalies, including bilateral ectopia lentis, atrial septal defect, ventricular septal defect, widening of tibial metaphysis with medial bowing, and dolichostenomelia in digits, while her mother and elder brother only demonstrated similar skeletal changes. A recurrent mutation, PHEX p.R291*, was found in all patients, while a de novo mutation, FBN1 p.C792F, was only detected in the proband. The FBN1 substitution was also predicted to cause significant conformational change in fibrillin-1 protein, thus changing its physical and biological properties. CONCLUSIONS: Taken together, we finalized the diagnosis for this family as X-linked hypophosphatemia (XLH), and diagnosed this girl as Marfan syndrome combined with XLH, and congenital heart disease. Our study also emphasizes the importance of WES in assisting the clinical diagnosis for complicated cases when the original diagnoses are challenged.
Keywords: Adult; Amino Acid Sequence; Base Sequence; Child; Exome; Familial Hypophosphatemic Rickets; Family; Female; Fibrillin-1; Fibrillins; Humans; Male; Marfan Syndrome; Microfilament Proteins; Molecular Sequence Data; Mutation; Pedigree; PHEX Phosphate Regulating Neutral Endopeptidase; Reproducibility of Results; Sequence Analysis, DNA

Whole-exome sequencing identifies novel homozygous mutation in NPAS2 in family with nonobstructive azoospermia. - Ramasamy, Ranjith; Bakırcıoğlu, M Emre; Cengiz, Cenk; Karaca, Ender; Scovell, Jason; Jhangiani, Shalini N; Akdemir, Zeynep C; Bainbridge, Matthew; Yu, Yao; Huff, Chad; Richard A Gibbs; Lupski, James R; et al. (Fertil Steril, 2015)
OBJECTIVE: To investigate the genetic cause of nonobstructive azoospermia (NOA) in a consanguineous Turkish family through homozygosity mapping followed by targeted exon/whole-exome sequencing to identify genetic variations. DESIGN: Whole-exome sequencing (WES). SETTING: Research laboratory. PATIENT(S): Two siblings in a consanguineous family with NOA. INTERVENTION(S): Validating all variants passing filter criteria with Sanger sequencing to confirm familial segregation and absence in the control population. MAIN OUTCOME MEASURE(S): Discovery of a mutation that could potentially cause NOA. RESULT(S): A novel nonsynonymous mutation in the neuronal PAS-2 domain (NPAS2) was identified in a consanguineous family from Turkey. This mutation in exon 14 (chr2: 101592000 C>G) of NPAS2 is likely a disease-causing mutation as it is predicted to be damaging, it is a novel variant, and it segregates with the disease. Family segregation of the variants showed the presence of the homozygous mutation in the three brothers with NOA and a heterozygous mutation in the mother as well as one brother and one sister who were both fertile. The mutation is not found in the single-nucleotide polymorphism database, the 1000 Genomes Project, the Baylor College of Medicine cohort of 500 Turkish patients (not a population-specific polymorphism), or the matching 50 fertile controls. CONCLUSION(S): With the use of WES we identified a novel homozygous mutation in NPAS2 as a likely disease-causing variant in a Turkish family diagnosed with NOA. Our data reinforce the clinical role of WES in the molecular diagnosis of highly heterogeneous genetic diseases for which conventional genetic approaches have previously failed to find a molecular diagnosis.
Keywords: Adult; Azoospermia; Base Sequence; Basic Helix-Loop-Helix Transcription Factors; Exome; Homozygote; Humans; Male; Molecular Sequence Data; Mutation; Nerve Tissue Proteins; Pedigree

Whole-exome sequencing points to considerable genetic heterogeneity of cerebral palsy. - McMichael, G; Bainbridge, M N; Haan, E; Corbett, M; Gardner, A; Thompson, S; van Bon, B W M; van Eyk, C L; Broadbent, J; Reynolds, C; O'Callaghan, M E; Nguyen, L S; et al. (Mol Psychiatry, 2015)
Cerebral palsy (CP) is a common, clinically heterogeneous group of disorders affecting movement and posture. Its prevalence has changed little in 50 years and the causes remain largely unknown. The genetic contribution to CP causation has been predicted to be ~2%. We performed whole-exome sequencing of 183 cases with CP including both parents (98 cases) or one parent (67 cases) and 18 singleton cases (no parental DNA). We identified and validated 61 de novo protein-altering variants in 43 out of 98 (44%) case-parent trios. Initial prioritization of variants for causality was by mutation type, whether they were known or predicted to be deleterious and whether they occurred in known disease genes whose clinical spectrum overlaps CP. Further, prioritization used two multidimensional frameworks-the Residual Variation Intolerance Score and the Combined Annotation-dependent Depletion score. Ten de novo mutations in three previously identified disease genes (TUBA1A (n=2), SCN8A (n=1) and KDM5C (n=1)) and in six novel candidate CP genes (AGAP1, JHDM1D, MAST1, NAA35, RFX2 and WIPI2) were predicted to be potentially pathogenic for CP. In addition, we identified four predicted pathogenic, hemizygous variants on chromosome X in two known disease genes, L1CAM and PAK3, and in two novel candidate CP genes, CD99L2 and TENM1. In total, 14% of CP cases, by strict criteria, had a potentially disease-causing gene variant. Half were in novel genes. The genetic heterogeneity highlights the complexity of the genetic contribution to CP. Function and pathway studies are required to establish the causative role of these putative pathogenic CP genes.
Keywords: Adult; Animals; Cerebral Palsy; Cohort Studies; Exome; Female; Gene Library; Genetic Heterogeneity; Genetic Predisposition to Disease; Gestational Age; Humans; Male; Mutation; Parents; Sequence Analysis, DNA

X-linked acrogigantism syndrome: clinical profile and therapeutic responses. - Beckers, Albert; Lodish, Maya Beth; Trivellin, Giampaolo; Rostomyan, Liliya; Lee, Misu; Faucz, Fabio R; Bo Yuan; Choong, Catherine S; Caberg, Jean-Hubert; Verrua, Elisa; Naves, Luciana Ansaneli; Cheetham, Tim D; et al. (Endocr Relat Cancer, 2015)
X-linked acrogigantism (X-LAG) is a new syndrome of pituitary gigantism, caused by microduplications on chromosome Xq26.3, encompassing the gene GPR101, which is highly upregulated in pituitary tumors. We conducted this study to explore the clinical, radiological, and hormonal phenotype and responses to therapy in patients with X-LAG syndrome. The study included 18 patients (13 sporadic) with X-LAG and microduplication of chromosome Xq26.3. All sporadic cases had unique duplications and the inheritance pattern in two families was dominant, with all Xq26.3 duplication carriers being affected. Patients began to grow rapidly as early as 2-3 months of age (median 12 months). At diagnosis (median delay 27 months), patients had a median height and weight standard deviation scores (SDS) of >+3.9 SDS. Apart from the increased overall body size, the children had acromegalic symptoms including acral enlargement and facial coarsening. More than a third of cases had increased appetite. Patients had marked hypersecretion of GH/IGF1 and usually prolactin, due to a pituitary macroadenoma or hyperplasia. Primary neurosurgical control was achieved with extensive anterior pituitary resection, but postoperative hypopituitarism was frequent. Control with somatostatin analogs was not readily achieved despite moderate to high levels of expression of somatostatin receptor subtype-2 in tumor tissue. Postoperative use of adjuvant pegvisomant resulted in control of IGF1 in all five cases where it was employed. X-LAG is a new infant-onset gigantism syndrome that has a severe clinical phenotype leading to challenging disease management.
Keywords: Acromegaly; Adenoma; Adolescent; Child; Child, Preschool; Chromosomes, Human, X; Female; Gigantism; Humans; Infant; Male; Pituitary Neoplasms; Young Adult

Analysis of prostate-specific antigen transcripts in chimpanzees, cynomolgus monkeys, baboons, and African green monkeys. - Mubiru, James N; Yang, Alice S; Olsen, Christian; Nayak, Sudhir; Livi, Carolina B; Dick, Edward J; Owston, Michael; Garcia-Forey, Magdalena; Shade, Robert E; Jeffrey Rogers (PLoS One, 2014)
The function of prostate-specific antigen (PSA) is to liquefy the semen coagulum so that the released sperm can fuse with the ovum. Fifteen spliced variants of the PSA gene have been reported in humans, but little is known about alternative splicing in nonhuman primates. Positive selection has been reported in sex- and reproductive-related genes from sea urchins to Drosophila to humans; however, there are few studies of adaptive evolution of the PSA gene. Here, using polymerase chain reaction (PCR) product cloning and sequencing, we study PSA transcript variant heterogeneity in the prostates of chimpanzees (Pan troglodytes), cynomolgus monkeys (Macaca fascicularis), baboons (Papio hamadryas anubis), and African green monkeys (Chlorocebus aethiops). Six PSA variants were identified in the chimpanzee prostate, but only two variants were found in cynomolgus monkeys, baboons, and African green monkeys. In the chimpanzee the full-length transcript is expressed at the same magnitude as the transcripts that retain intron 3. We have found previously unidentified splice variants of the PSA gene, some of which might be linked to disease conditions. Selection on the PSA gene was studied in 11 primate species by computational methods using the sequences reported here for African green monkey, cynomolgus monkey, baboon, and chimpanzee and other sequences available in public databases. A codon-based analysis (dN/dS) of the PSA gene identified potential adaptive evolution at five residue sites (Arg45, Lys70, Gln144, Pro189, and Thr203).
Keywords: Alternative Splicing; Amino Acid Sequence; Animals; Base Sequence; Bayes Theorem; Chlorocebus aethiops; Cloning, Molecular; Codon; Introns; Likelihood Functions; Macaca fascicularis; Male; Molecular Sequence Data; Pan troglodytes; Papio; Phylogeny; Prostate-Specific Antigen; Real-Time Polymerase Chain Reaction; RNA, Messenger

Analysis of the ABCA4 genomic locus in Stargardt disease. - Zernant, Jana; Xie, Yajing Angela; Ayuso, Carmen; Riveiro-Álvarez, Rosa; López-Martínez, Miguel-Ángel; Simonelli, Francesca; Testa, Francesco; Gorin, Michael B; Strom, Samuel P; Bertelsen, Mette; Rosenberg, Thomas; Boone, Philip M; et al. (Hum Mol Genet, 2014)
Autosomal recessive Stargardt disease (STGD1, MIM 248200) is caused by mutations in the ABCA4 gene. Complete sequencing of ABCA4 in STGD patients identifies compound heterozygous or homozygous disease-associated alleles in 65-70% of patients and only one mutation in 15-20% of patients. This study was designed to find the missing disease-causing ABCA4 variation by a combination of next-generation sequencing (NGS), array-Comparative Genome Hybridization (aCGH) screening, familial segregation and in silico analyses. The entire 140 kb ABCA4 genomic locus was sequenced in 114 STGD patients with one known ABCA4 exonic mutation revealing, on average, 200 intronic variants per sample. Filtering of these data resulted in 141 candidates for new mutations. Two variants were detected in four samples, two in three samples, and 20 variants in two samples, the remaining 117 new variants were detected only once. Multimodal analysis suggested 12 new likely pathogenic intronic ABCA4 variants, some of which were specific to (isolated) ethnic groups. No copy number variation (large deletions and insertions) was detected in any patient suggesting that it is a very rare event in the ABCA4 locus. Many variants were excluded since they were not conserved in non-human primates, were frequent in African populations and, therefore, represented ancestral, and not disease-associated, variants. The sequence variability in the ABCA4 locus is extensive and the non-coding sequences do not harbor frequent mutations in STGD patients of European-American descent. Defining disease-associated alleles in the ABCA4 locus requires exceptionally well characterized large cohorts and extensive analyses by a combination of various approaches.
Keywords: Alleles; ATP-Binding Cassette Transporters; Blacks; Case-Control Studies; Comparative Genomic Hybridization; Exons; Female; Gene Expression; Genes, Recessive; Genetic Loci; Genetic Variation; Heterozygote; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Introns; Macular Degeneration; Male; Mutation; Pedigree; Stargardt Disease; Whites

Association of levels of fasting glucose and insulin with rare variants at the chromosome 11p11.2-MADD locus: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Cornes, Belinda K; Brody, Jennifer A; Nikpoor, Naghmeh; Morrison, Alanna C; Chu, Huan; Ahn, Byung Soo; Wang, Shuai; Dauriz, Marco; Barzilay, Joshua I; Dupuis, Josée; Florez, Jose C; Coresh, Josef; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Common variation at the 11p11.2 locus, encompassing MADD, ACP2, NR1H3, MYBPC3, and SPI1, has been associated in genome-wide association studies with fasting glucose and insulin (FI). In the Cohorts for Heart and Aging Research in Genomic Epidemiology Targeted Sequencing Study, we sequenced 5 gene regions at 11p11.2 to identify rare, potentially functional variants influencing fasting glucose or FI levels. METHODS AND RESULTS: Sequencing (mean depth, 38×) across 16.1 kb in 3566 individuals without diabetes mellitus identified 653 variants, 79.9% of which were rare (minor allele frequency <1%) and novel. We analyzed rare variants in 5 gene regions with FI or fasting glucose using the sequence kernel association test. At NR1H3, 53 rare variants were jointly associated with FI (P=2.73×10(-3)); of these, 7 were predicted to have regulatory function and showed association with FI (P=1.28×10(-3)). Conditioning on 2 previously associated variants at MADD (rs7944584, rs10838687) did not attenuate this association, suggesting that there are >2 independent signals at 11p11.2. One predicted regulatory variant, chr11:47227430 (hg18; minor allele frequency=0.00068), contributed 20.6% to the overall sequence kernel association test score at NR1H3, lies in intron 2 of NR1H3, and is a predicted binding site for forkhead box A1 (FOXA1), a transcription factor associated with insulin regulation. In human HepG2 hepatoma cells, the rare chr11:47227430 A allele disrupted FOXA1 binding and reduced FOXA1-dependent transcriptional activity. CONCLUSIONS: Sequencing at 11p11.2-NR1H3 identified rare variation associated with FI. One variant, chr11:47227430, seems to be functional, with the rare A allele reducing transcription factor FOXA1 binding and FOXA1-dependent transcriptional activity.
Keywords: Aged; Aged, 80 and over; Aging; Blood Glucose; Chromosomes, Human, Pair 11; Cohort Studies; Death Domain Receptor Signaling Adaptor Proteins; Diabetes Mellitus, Type 2; Fasting; Female; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Genomics; Guanine Nucleotide Exchange Factors; Heart Diseases; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Association of low-frequency and rare coding-sequence variants with blood lipids and coronary heart disease in 56,000 whites and blacks. - Peloso, Gina M; Auer, Paul L; Bis, Joshua C; Voorman, Arend; Morrison, Alanna C; Stitziel, Nathan O; Brody, Jennifer A; Khetarpal, Sumeet A; Crosby, Jacy R; Fornage, Myriam; Isaacs, Aaron; Jakobsdottir, Johanna; et al. (Am J Hum Genet, 2014)
Low-frequency coding DNA sequence variants in the proprotein convertase subtilisin/kexin type 9 gene (PCSK9) lower plasma low-density lipoprotein cholesterol (LDL-C), protect against risk of coronary heart disease (CHD), and have prompted the development of a new class of therapeutics. It is uncertain whether the PCSK9 example represents a paradigm or an isolated exception. We used the "Exome Array" to genotype >200,000 low-frequency and rare coding sequence variants across the genome in 56,538 individuals (42,208 European ancestry [EA] and 14,330 African ancestry [AA]) and tested these variants for association with LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. Although we did not identify new genes associated with LDL-C, we did identify four low-frequency (frequencies between 0.1% and 2%) variants (ANGPTL8 rs145464906 [c.361C>T; p.Gln121*], PAFAH1B2 rs186808413 [c.482C>T; p.Ser161Leu], COL18A1 rs114139997 [c.331G>A; p.Gly111Arg], and PCSK7 rs142953140 [c.1511G>A; p.Arg504His]) with large effects on HDL-C and/or triglycerides. None of these four variants was associated with risk for CHD, suggesting that examples of low-frequency coding variants with robust effects on both lipids and CHD will be limited.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Adult; Aged; Alleles; Animals; Black People; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; Female; Gene Frequency; Genetic Association Studies; Genetic Code; Genetic Variation; Humans; Linear Models; Male; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Middle Aged; Phenotype; Sequence Analysis, DNA; Subtilisins; Triglycerides; White People

Associations of NINJ2 sequence variants with incident ischemic stroke in the Cohorts for Heart and Aging in Genomic Epidemiology (CHARGE) consortium. - Bis, Joshua C; DeStefano, Anita; Liu, Xiaoming; Brody, Jennifer A; Choi, Seung Hoan; Verhaaren, Benjamin F J; Debette, Stephanie; Ikram, M Arfan; Shahar, Eyal; Butler, Kenneth R; Gottesman, Rebecca F; Donna M Muzny; et al. (PLoS One, 2014)
BACKGROUND: Stroke, the leading neurologic cause of death and disability, has a substantial genetic component. We previously conducted a genome-wide association study (GWAS) in four prospective studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and demonstrated that sequence variants near the NINJ2 gene are associated with incident ischemic stroke. Here, we sought to fine-map functional variants in the region and evaluate the contribution of rare variants to ischemic stroke risk. METHODS AND RESULTS: We sequenced 196 kb around NINJ2 on chromosome 12p13 among 3,986 European ancestry participants, including 475 ischemic stroke cases, from the Atherosclerosis Risk in Communities Study, Cardiovascular Health Study, and Framingham Heart Study. Meta-analyses of single-variant tests for 425 common variants (minor allele frequency [MAF] ≥ 1%) confirmed the original GWAS results and identified an independent intronic variant, rs34166160 (MAF = 0.012), most significantly associated with incident ischemic stroke (HR = 1.80, p = 0.0003). Aggregating 278 putatively-functional variants with MAF≤ 1% using count statistics, we observed a nominally statistically significant association, with the burden of rare NINJ2 variants contributing to decreased ischemic stroke incidence (HR = 0.81; p = 0.026). CONCLUSION: Common and rare variants in the NINJ2 region were nominally associated with incident ischemic stroke among a subset of CHARGE participants. Allelic heterogeneity at this locus, caused by multiple rare, low frequency, and common variants with disparate effects on risk, may explain the difficulties in replicating the original GWAS results. Additional studies that take into account the complex allelic architecture at this locus are needed to confirm these findings.
Keywords: Cell Adhesion Molecules, Neuronal; Female; Genetic Association Studies; Genetic Heterogeneity; Humans; Introns; Ischemia; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA; White People

Blood lead concentrations in Jamaican children with and without autism spectrum disorder. - Rahbar, Mohammad H; Samms-Vaughan, Maureen; Dickerson, Aisha S; Loveland, Katherine A; Ardjomand-Hessabi, Manouchehr; Bressler, Jan; Shakespeare-Pellington, Sydonnie; Grove, Megan L; Pearson, Deborah A; Eric Boerwinkle (Int J Environ Res Public Health, 2014)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder manifesting by early childhood. Lead is a toxic metal shown to cause neurodevelopmental disorders in children. Several studies have investigated the possible association between exposure to lead and ASD, but their findings are conflicting. Using data from 100 ASD cases (2-8 years of age) and their age- and sex-matched typically developing controls, we investigated the association between blood lead concentrations (BLC) and ASD in Jamaican children. We administered a questionnaire to assess demographic and socioeconomic information as well as exposure to potential lead sources. We used General Linear Models (GLM) to assess the association of BLC with ASD status as well as with sources of exposure to lead. In univariable GLM, we found a significant difference between geometric mean blood lead concentrations of ASD cases and controls (2.25 μg/dL cases vs. 2.73 μg/dL controls, p < 0.05). However, after controlling for potential confounders, there were no significant differences between adjusted geometric mean blood lead concentrations of ASD cases and controls (2.55 μg/dL vs. 2.72 μg/dL, p = 0.64). Our results do not support an association between BLC and ASD in Jamaican children. We have identified significant confounders when assessing an association between ASD and BLC.
Keywords: Case-Control Studies; Child; Child Development Disorders, Pervasive; Child, Preschool; Diet; Environmental Pollutants; Female; Humans; Jamaica; Lead; Male; Socioeconomic Factors; Surveys and Questionnaires

Comparative validation of the D. melanogaster modENCODE transcriptome annotation. - Chen, Zhen-Xia; Sturgill, David; Qu, Jiaxin; Jiang, Huaiyang; Park, Soo; Boley, Nathan; Suzuki, Ana Maria; Fletcher, Anthony R; Plachetzki, David C; FitzGerald, Peter C; Artieri, Carlo G; Atallah, Joel; et al. (Genome Res, 2014)
Accurate gene model annotation of reference genomes is critical for making them useful. The modENCODE project has improved the D. melanogaster genome annotation by using deep and diverse high-throughput data. Since transcriptional activity that has been evolutionarily conserved is likely to have an advantageous function, we have performed large-scale interspecific comparisons to increase confidence in predicted annotations. To support comparative genomics, we filled in divergence gaps in the Drosophila phylogeny by generating draft genomes for eight new species. For comparative transcriptome analysis, we generated mRNA expression profiles on 81 samples from multiple tissues and developmental stages of 15 Drosophila species, and we performed cap analysis of gene expression in D. melanogaster and D. pseudoobscura. We also describe conservation of four distinct core promoter structures composed of combinations of elements at three positions. Overall, each type of genomic feature shows a characteristic divergence rate relative to neutral models, highlighting the value of multispecies alignment in annotating a target genome that should prove useful in the annotation of other high priority genomes, especially human and other mammalian genomes that are rich in noncoding sequences. We report that the vast majority of elements in the annotation are evolutionarily conserved, indicating that the annotation will be an important springboard for functional genetic testing by the Drosophila community.
Keywords: Animals; Cluster Analysis; Computational Biology; Drosophila melanogaster; Evolution, Molecular; Exons; Female; Gene Expression Profiling; Genome, Insect; Humans; Male; Molecular Sequence Annotation; Nucleotide Motifs; Phylogeny; Position-Specific Scoring Matrices; Promoter Regions, Genetic; Reproducibility of Results; RNA Editing; RNA Splice Sites; RNA Splicing; Transcription Initiation Site; Transcriptome

De novo truncating mutations in AHDC1 in individuals with syndromic expressive language delay, hypotonia, and sleep apnea. - Xia, Fan; Bainbridge, Matthew N; Tan, Tiong Yang; Wangler, Michael F; Scheuerle, Angela E; Zackai, Elaine H; Harr, Margaret H; Sutton, V Reid; Nalam, Roopa L; Zhu, Wenmiao; Nash, Margot; Ryan, Monique M; et al. (Am J Hum Genet, 2014)
Clinical whole-exome sequencing (WES) for identification of mutations leading to Mendelian disease has been offered to the medical community since 2011. Clinically undiagnosed neurological disorders are the most frequent basis for test referral, and currently, approximately 25% of such cases are diagnosed at the molecular level. To date, there are approximately 4,000 "known" disease-associated loci, and many are associated with striking dysmorphic features, making genotype-phenotype correlations relatively straightforward. A significant fraction of cases, however, lack characteristic dysmorphism or clinical pathognomonic traits and are dependent upon molecular tests for definitive diagnoses. Further, many molecular diagnoses are guided by recent gene-disease association discoveries. Hence, there is a critical interplay between clinical testing and research leading to gene-disease association discovery. Here, we describe four probands, all of whom presented with hypotonia, intellectual disability, global developmental delay, and mildly dysmorphic facial features. Three of the four also had sleep apnea. Each was a simplex case without a remarkable family history. Using WES, we identified AHDC1 de novo truncating mutations that most likely cause this genetic syndrome.
Keywords: Child; Child, Preschool; DNA-Binding Proteins; Exome; Female; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Muscle Hypotonia; Mutation; Sleep Apnea Syndromes; Syndrome

Design and anticipated outcomes of the eMERGE-PGx project: a multicenter pilot for preemptive pharmacogenomics in electronic health record systems. - Rasmussen-Torvik, L J; Stallings, S C; Gordon, A S; Almoguera, B; Basford, M A; Bielinski, S J; Brautbar, A; Brilliant, M H; Carrell, D S; Connolly, J J; Crosslin, D R; Doheny, K F; et al. (Clin Pharmacol Ther, 2014)
We describe here the design and initial implementation of the eMERGE-PGx project. eMERGE-PGx, a partnership of the Electronic Medical Records and Genomics Network and the Pharmacogenomics Research Network, has three objectives: (i) to deploy PGRNseq, a next-generation sequencing platform assessing sequence variation in 84 proposed pharmacogenes, in nearly 9,000 patients likely to be prescribed drugs of interest in a 1- to 3-year time frame across several clinical sites; (ii) to integrate well-established clinically validated pharmacogenetic genotypes into the electronic health record with associated clinical decision support and to assess process and clinical outcomes of implementation; and (iii) to develop a repository of pharmacogenetic variants of unknown significance linked to a repository of electronic health record-based clinical phenotype data for ongoing pharmacogenomics discovery. We describe site-specific project implementation and anticipated products, including genetic variant and phenotype data repositories, novel variant association studies, clinical decision support modules, clinical and process outcomes, approaches to managing incidental findings, and patient and clinician education methods.
Keywords: Adolescent; Aged; Child; Databases, Genetic; Drug Therapy; Electronic Health Records; Female; Genetic Association Studies; Genetic Variation; Genotype; Humans; Knowledge Bases; Male; Middle Aged; Pharmacogenetics; Phenotype; Pilot Projects; Sequence Analysis, DNA; Young Adult

The effect of dietary fat intake on hepatic gene expression in LG/J AND SM/J mice. - Partridge, Charlyn G; Fawcett, Gloria L; Wang, Bing; Semenkovich, Clay F; Cheverud, James M (BMC Genomics, 2014)
BACKGROUND: The liver plays a major role in regulating metabolic homeostasis and is vital for nutrient metabolism. Identifying the genetic factors regulating these processes could lead to a greater understanding of how liver function responds to a high-fat diet and how that response may influence susceptibilities to obesity and metabolic syndrome. In this study we examine differences in hepatic gene expression between the LG/J and SM/J inbred mouse strains and how gene expression in these strains is affected by high-fat diet. LG/J and SM/J are known to differ in their responses to a high-fat diet for a variety of obesity- and diabetes-related traits, with the SM/J strain exhibiting a stronger phenotypic response to diet. RESULTS: Dietary intake had a significant effect on gene expression in both inbred lines. Genes up-regulated by a high-fat diet were involved in biological processes such as lipid and carbohydrate metabolism; protein and amino acid metabolic processes were down regulated on a high-fat diet. A total of 259 unique transcripts exhibited a significant diet-by-strain interaction. These genes tended to be associated with immune function. In addition, genes involved in biochemical processes related to non-alcoholic fatty liver disease (NAFLD) manifested different responses to diet between the two strains. For most of these genes, SM/J had a stronger response to the high-fat diet than LG/J. CONCLUSIONS: These data show that dietary fat impacts gene expression levels in SM/J relative to LG/J, with SM/J exhibiting a stronger response. This supports previous data showing that SM/J has a stronger phenotypic response to high-fat diet. Based upon these findings, we suggest that SM/J and its cross with the LG/J strain provide a good model for examining non-alcoholic fatty liver disease and its role in metabolic syndrome.
Keywords: Animals; Diabetes Mellitus; Diet, High-Fat; Down-Regulation; Female; Liver; Male; Mice; Mice, Inbred Strains; Non-alcoholic Fatty Liver Disease; Obesity; Quantitative Trait Loci; Up-Regulation

Epigenomic profiling of young and aged HSCs reveals concerted changes during aging that reinforce self-renewal. - Sun, Deqiang; Luo, Min; Jeong, Mira; Rodriguez, Benjamin; Xia, Zheng; Hannah, Rebecca; Wang, Hui; Le, Thuc; Faull, Kym F; Rui Chen; Gu, Hongcang; Bock, Christoph; et al. (Cell Stem Cell, 2014)
To investigate the cell-intrinsic aging mechanisms that erode the function of somatic stem cells during aging, we have conducted a comprehensive integrated genomic analysis of young and aged cells. We profiled the transcriptome, DNA methylome, and histone modifications of young and old murine hematopoietic stem cells (HSCs). Transcriptome analysis indicated reduced TGF-β signaling and perturbation of genes involved in HSC proliferation and differentiation. Aged HSCs exhibited broader H3K4me3 peaks across HSC identity and self-renewal genes and showed increased DNA methylation at transcription factor binding sites associated with differentiation-promoting genes combined with a reduction at genes associated with HSC maintenance. Altogether, these changes reinforce HSC self-renewal and diminish differentiation, paralleling phenotypic HSC aging behavior. Ribosomal biogenesis emerged as a particular target of aging with increased transcription of ribosomal protein and RNA genes and hypomethylation of rRNA genes. This data set will serve as a reference for future epigenomic analysis of stem cell aging.
Keywords: Animals; Cell Differentiation; Cells, Cultured; Cellular Senescence; Chromatin Immunoprecipitation; Epigenomics; Hematopoietic Stem Cells; Male; Mice; Transforming Growth Factor beta

Exome sequencing identifies a novel homozygous mutation in the phosphate transporter SLC34A1 in hypophosphatemia and nephrocalcinosis. - Rajagopal, Abbhirami; Braslavsky, Débora; Lu, James T; Kleppe, Soledad; Clément, Florencia; Cassinelli, Hamilton; Liu, David S; Liern, Jose Miguel; Vallejo, Graciela; Bergadá, Ignacio; Richard A Gibbs; Campeau, Phillipe M; et al. (J Clin Endocrinol Metab, 2014)
CONTEXT: Two Argentinean siblings (a boy and a girl) from a nonconsanguineous family presented with hypercalcemia, hypercalciuria, hypophosphatemia, low parathyroid hormone (PTH), and nephrocalcinosis. OBJECTIVE: The goal of this study was to identify genetic causes of the clinical findings in the two siblings. DESIGN: Whole exome sequencing was performed to identify disease-causing mutations in the youngest sibling, and a candidate variant was screened in other family members by Sanger sequencing. In vitro experiments were conducted to determine the effects of the mutation that was identified. PATIENTS AND OTHER PARTICIPANTS: Affected siblings (2 y.o. female and 10 y.o male) and their parents were included in the study. Informed consent was obtained for genetic studies. RESULTS: A novel homozygous mutation in the gene encoding the renal sodium-dependent phosphate transporter SLC34A1 was identified in both siblings (c.1484G>A, p.Arg495His). In vitro studies showed that the p.Arg495His mutation resulted in decreased phosphate uptake when compared to wild-type SLC34A1. CONCLUSIONS: The homozygous G>A transition that results in the substitution of histidine for arginine at position 495 of the renal sodium-dependent phosphate transporter, SLC34A1, is involved in disease pathogenesis in these patients. Our report of the second family with two mutated SLC34A1 alleles expands the known phenotype of this rare condition.
Keywords: Child; Child, Preschool; DNA Mutational Analysis; Exome; Female; Humans; Hypercalcemia; Hypercalciuria; Hypophosphatemia; Male; Mutation; Nephrocalcinosis; Parathyroid Hormone; Pedigree; Phenotype; Sodium-Phosphate Cotransporter Proteins, Type IIa

Exonic duplication CNV of NDRG1 associated with autosomal-recessive HMSN-Lom/CMT4D. - Okamoto, Yuji; Goksungur, Meryem Tuba; Pehlivan, Davut; Beck, Christine R; Gonzaga-Jauregui, Claudia; Donna M Muzny; Atik, Mehmed M; Carvalho, Claudia M B; Matur, Zeliha; Bayraktar, Serife; Boone, Philip M; Akyuz, Kaya; et al. (Genet Med, 2014)
PURPOSE: Copy-number variations as a mutational mechanism contribute significantly to human disease. Approximately one-half of the patients with Charcot-Marie-Tooth (CMT) disease have a 1.4 Mb duplication copy-number variation as the cause of their neuropathy. However, non-CMT1A neuropathy patients rarely have causative copy-number variations, and to date, autosomal-recessive disease has not been associated with copy-number variation as a mutational mechanism. METHODS: We performed Agilent 8 × 60 K array comparative genomic hybridization on DNA from 12 recessive Turkish families with CMT disease. Additional molecular studies were conducted to detect breakpoint junctions and to evaluate gene expression levels in a family in which we detected an intragenic duplication copy-number variation. RESULTS: We detected an ~6.25 kb homozygous intragenic duplication in NDRG1, a gene known to be causative for recessive HMSNL/CMT4D, in three individuals from a Turkish family with CMT neuropathy. Further studies showed that this intragenic copy-number variation resulted in a homozygous duplication of exons 6-8 that caused decreased mRNA expression of NDRG1. CONCLUSION: Exon-focused high-resolution array comparative genomic hybridization enables the detection of copy-number variation carrier states in recessive genes, particularly small copy-number variations encompassing or disrupting single genes. In families for whom a molecular diagnosis has not been elucidated by conventional clinical assays, an assessment for copy-number variations in known CMT genes might be considered.
Keywords: Adult; Base Sequence; Cell Cycle Proteins; Charcot-Marie-Tooth Disease; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Duplication; Gene Expression; Genes, Recessive; Humans; Intracellular Signaling Peptides and Proteins; Male; Mutation; Refsum Disease; Sequence Analysis, DNA; Turkey; Young Adult

Fibular aplasia, tibial campomelia, and oligosyndactyly: a further patient with a 2-year follow-up. - Sezer, Ozlem; Gebesoglu, Ismet; Bo Yuan; Karaca, Ender; Gokce, Erkan; Gunes, Sezgin (Clin Dysmorphol, 2014)
Keywords: Adolescent; Adult; Campomelic Dysplasia; Child, Preschool; Female; Fibula; Fingers; Follow-Up Studies; Foot Deformities, Congenital; Hand Deformities, Congenital; Humans; Infant; Infant, Newborn; Male; Pregnancy; Radiography; Syndactyly; Tibia; Toes

The first myriapod genome sequence reveals conservative arthropod gene content and genome organisation in the centipede Strigamia maritima. - Chipman, Ariel D; Ferrier, David E K; Brena, Carlo; Qu, Jiaxin; Hughes, Daniel S T; Schröder, Reinhard; Torres-Oliva, Montserrat; Znassi, Nadia; Jiang, Huaiyang; Almeida, Francisca C; Alonso, Claudio R; Apostolou, Zivkos; et al. (PLoS Biol, 2014)
Myriapods (e.g., centipedes and millipedes) display a simple homonomous body plan relative to other arthropods. All members of the class are terrestrial, but they attained terrestriality independently of insects. Myriapoda is the only arthropod class not represented by a sequenced genome. We present an analysis of the genome of the centipede Strigamia maritima. It retains a compact genome that has undergone less gene loss and shuffling than previously sequenced arthropods, and many orthologues of genes conserved from the bilaterian ancestor that have been lost in insects. Our analysis locates many genes in conserved macro-synteny contexts, and many small-scale examples of gene clustering. We describe several examples where S. maritima shows different solutions from insects to similar problems. The insect olfactory receptor gene family is absent from S. maritima, and olfaction in air is likely effected by expansion of other receptor gene families. For some genes S. maritima has evolved paralogues to generate coding sequence diversity, where insects use alternate splicing. This is most striking for the Dscam gene, which in Drosophila generates more than 100,000 alternate splice forms, but in S. maritima is encoded by over 100 paralogues. We see an intriguing linkage between the absence of any known photosensory proteins in a blind organism and the additional absence of canonical circadian clock genes. The phylogenetic position of myriapods allows us to identify where in arthropod phylogeny several particular molecular mechanisms and traits emerged. For example, we conclude that juvenile hormone signalling evolved with the emergence of the exoskeleton in the arthropods and that RR-1 containing cuticle proteins evolved in the lineage leading to Mandibulata. We also identify when various gene expansions and losses occurred. The genome of S. maritima offers us a unique glimpse into the ancestral arthropod genome, while also displaying many adaptations to its specific life history.
Keywords: Animals; Arthropods; Circadian Rhythm Signaling Peptides and Proteins; DNA Methylation; Evolution, Molecular; Female; Genome; Genome, Mitochondrial; Hormones; Male; Multigene Family; Phylogeny; Polymorphism, Genetic; Protein Kinases; Receptors, Odorant; RNA, Untranslated; Selenoproteins; Sex Chromosomes; Synteny; Transcription Factors

Following-up genome-wide association study signals: lessons learned from Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Eric Boerwinkle; Heckbert, Susan R (Circ Cardiovasc Genet, 2014)
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

A framework for the interpretation of de novo mutation in human disease. - Samocha, Kaitlin E; Robinson, Elise B; Sanders, Stephan J; Stevens, Christine; Aniko Sabo; McGrath, Lauren M; Kosmicki, Jack A; Rehnström, Karola; Mallick, Swapan; Kirby, Andrew; Wall, Dennis P; MacArthur, Daniel G; et al. (Nat Genet, 2014)
Spontaneously arising (de novo) mutations have an important role in medical genetics. For diseases with extensive locus heterogeneity, such as autism spectrum disorders (ASDs), the signal from de novo mutations is distributed across many genes, making it difficult to distinguish disease-relevant mutations from background variation. Here we provide a statistical framework for the analysis of excesses in de novo mutation per gene and gene set by calibrating a model of de novo mutation. We applied this framework to de novo mutations collected from 1,078 ASD family trios, and, whereas we affirmed a significant role for loss-of-function mutations, we found no excess of de novo loss-of-function mutations in cases with IQ above 100, suggesting that the role of de novo mutations in ASDs might reside in fundamental neurodevelopmental processes. We also used our model to identify ∼1,000 genes that are significantly lacking in functional coding variation in non-ASD samples and are enriched for de novo loss-of-function mutations identified in ASD cases.
Keywords: Child Development Disorders, Pervasive; Exome; Female; Genetic Code; Genetic Predisposition to Disease; Genetics, Medical; Humans; Male; Mutation

Further evidence for phenotypic signatures of hybridization in descendant baboon populations. - Ackermann, Rebecca R; Schroeder, Lauren; Jeffrey Rogers; Cheverud, James M (J Hum Evol, 2014)
Hybridization may have played a substantial role in shaping the diversity of our evolving lineage. Although recent genomic evidence has shown that hybridization occurred between anatomically modern humans (AMHS) and Neanderthals, it remains difficult to pin down precisely where and when this gene flow took place. Investigations of the hybrid phenotype in primates and other mammals are providing models for identifying signatures of hybridization in the fossil record. However, our understanding of intra- and inter-taxon variation in hybrids is still limited. Moreover, there is little evidence from these studies that is pertinent to the question of how long hybrid skeletal traits persist in descendants, and therefore it is not clear whether observed hybrid phenotypes are evidence of recent (e.g., F1) or much earlier hybridization events. Here, we present an analysis updating a previous study of cranial variation in pedigreed olive and yellow baboons and their hybrids. Results suggest that traits previously associated with hybrids in baboons and other mammalian species are also present in this expanded data set; many of these traits are highly heritable, confirming a genetic basis for their variation in this mixed population. While F1 animals - and especially F1 males - still have the highest number of dental anomalies, these and other atypical traits persist into later hybrid generations (such as F2 and B1). Moreover, non-F1 recombinants also show extremely rare trait variations, including reduced canines and rotated teeth. However, these results must be considered in light of the possibility that some founding individuals may have themselves been unrecognized hybrids. Despite this, the data are compelling, and indicate once again that further controlled research remains to be done on primates and other mammals in order to better understand variation in the hybrid phenotype.
Keywords: Animals; Female; Hybridization, Genetic; Male; Papio anubis; Papio cynocephalus; Phenotype

Genetic and clinical analysis of ABCA4-associated disease in African American patients. - Zernant, Jana; Collison, Frederick T; Lee, Winston; Fishman, Gerald A; Nõupuu, Kalev; Bo Yuan; Cai, Carolyn; James R Lupski; Yannuzzi, Lawrence A; Tsang, Stephen H; Allikmets, Rando (Hum Mutat, 2014)
Autosomal recessive Stargardt disease (STGD1) is caused by hundreds of mutations in the ABCA4 gene, which are often specific to racial and ethnic groups. Here, we investigated the ABCA4 variation and their phenotypic expression in a cohort of 44 patients of African American descent, a previously under-characterized racial group. Patients were screened for mutations in ABCA4 by next-generation sequencing and array-comparative genomic hybridization (aCGH), followed by analyses for pathogenicity by in silico programs. Thorough ophthalmic examination was performed on all patients. At least two (expected) disease-causing alleles in the ABCA4 gene were identified in 27 (61.4%) patients, one allele in 11 (25%) patients, and no ABCA4 mutations were found in six (13.6%) patients. Altogether, 39 different disease-causing ABCA4 variants, including seven new, were identified on 65 (74%) chromosomes, most of which were unique for this racial group. The most frequent ABCA4 mutation in this cohort was c.6320G>A (p.(R2107H)), representing 19.3% of all disease-associated alleles. No large copy number variants were identified in any patient. Most patients reported later onset of symptoms. In summary, the ABCA4 mutation spectrum in patients of West African descent differs significantly from that in patients of European descent, resulting in a later onset and "milder" disease.
Keywords: Adult; African Americans; ATP-Binding Cassette Transporters; Comparative Genomic Hybridization; DNA Mutational Analysis; Electroretinography; Female; Genetic Predisposition to Disease; Humans; Macular Degeneration; Male; Middle Aged; Mutation; Stargardt Disease; United States; Whites

The genetic basis of DOORS syndrome: an exome-sequencing study. - Campeau, Philippe M; Kasperaviciute, Dalia; Lu, James T; Burrage, Lindsay C; Kim, Choel; Hori, Mutsuki; Powell, Berkley R; Stewart, Fiona; Félix, Têmis Maria; van den Ende, Jenneke; Wisniewska, Marzena; Kayserili, Hulya; et al. (Lancet Neurol, 2014)
BACKGROUND: Deafness, onychodystrophy, osteodystrophy, mental retardation, and seizures (DOORS) syndrome is a rare autosomal recessive disorder of unknown cause. We aimed to identify the genetic basis of this syndrome by sequencing most coding exons in affected individuals. METHODS: Through a search of available case studies and communication with collaborators, we identified families that included at least one individual with at least three of the five main features of the DOORS syndrome: deafness, onychodystrophy, osteodystrophy, intellectual disability, and seizures. Participants were recruited from 26 centres in 17 countries. Families described in this study were enrolled between Dec 1, 2010, and March 1, 2013. Collaborating physicians enrolling participants obtained clinical information and DNA samples from the affected child and both parents if possible. We did whole-exome sequencing in affected individuals as they were enrolled, until we identified a candidate gene, and Sanger sequencing to confirm mutations. We did expression studies in human fibroblasts from one individual by real-time PCR and western blot analysis, and in mouse tissues by immunohistochemistry and real-time PCR. FINDINGS: 26 families were included in the study. We did exome sequencing in the first 17 enrolled families; we screened for TBC1D24 by Sanger sequencing in subsequent families. We identified TBC1D24 mutations in 11 individuals from nine families (by exome sequencing in seven families, and Sanger sequencing in two families). 18 families had individuals with all five main features of DOORS syndrome, and TBC1D24 mutations were identified in half of these families. The seizure types in individuals with TBC1D24 mutations included generalised tonic-clonic, complex partial, focal clonic, and infantile spasms. Of the 18 individuals with DOORS syndrome from 17 families without TBC1D24 mutations, eight did not have seizures and three did not have deafness. In expression studies, some mutations abrogated TBC1D24 mRNA stability. We also detected Tbc1d24 expression in mouse phalangeal chondrocytes and calvaria, which suggests a role of TBC1D24 in skeletogenesis. INTERPRETATION: Our findings suggest that mutations in TBC1D24 seem to be an important cause of DOORS syndrome and can cause diverse phenotypes. Thus, individuals with DOORS syndrome without deafness and seizures but with the other features should still be screened for TBC1D24 mutations. More information is needed to understand the cellular roles of TBC1D24 and identify the genes responsible for DOORS phenotypes in individuals who do not have a mutation in TBC1D24. FUNDING: US National Institutes of Health, the CIHR (Canada), the NIHR (UK), the Wellcome Trust, the Henry Smith Charity, and Action Medical Research.
Keywords: Adolescent; Carrier Proteins; Child; Child, Preschool; Craniofacial Abnormalities; Exome; Female; GTPase-Activating Proteins; Hand Deformities, Congenital; Hearing Loss, Sensorineural; Humans; Infant; Intellectual Disability; Internationality; Male; Membrane Proteins; Nails, Malformed; Nerve Tissue Proteins; Phenotype; Sequence Analysis, DNA; Young Adult

Genetic markers associated with plasma protein C level in African Americans: the atherosclerosis risk in communities (ARIC) study. - Munir, M Shahzeb; Weng, Lu-Chen; Tang, Weihong; Basu, Saonli; Pankow, James S; Matijevic, Nena; Cushman, Mary; Eric Boerwinkle; Folsom, Aaron R (Genet Epidemiol, 2014)
Protein C is an endogenous anticoagulant protein with anti-inflammatory properties. Single-nucleotide polymorphisms (SNPs) affect the levels of circulating protein C in European Americans. We performed a genome-wide association (GWA) scan of plasma protein C concentration with approximately 2.5 million SNPs in 2,701 African Americans in the Atherosclerosis Risk in Communities Study. Seventy-nine SNPs from the 20q11 and 2q14 regions reached the genome-wide significance threshold of 5 × 10(-8) . A missense variant rs867186 in the PROCR gene at 20q11 is known to affect protein C levels in individuals of European descent and showed the strongest signal (P = 9.84 × 10(-65) ) in African Americans. The minor allele of this SNP was associated with higher protein C levels (β = 0.49 μg/ml; 10% variance explained). In the 2q14 region, the top SNPs were near or within the PROC gene: rs7580658 (β = 0.15 μg/ml; 2% variance explained, P = 1.7 × 10(-12) ) and rs1799808 (β = 0.15 μg/ml; 2% variance explained, P = 2.03 × 10(-12) ). These two SNPs were in strong linkage disequilibrium (LD) with another SNP rs1158867 that resides in a biochemically functional site and in weak to strong LD with the top PROC variants previously reported in individuals of European descent. In addition, two variants outside the PROC region were significantly and independently associated with protein C levels: rs4321325 in CYP27C1 and rs13419716 in MYO7B. In summary, this first GWA study for plasma protein C levels in African Americans confirms the associations of SNPs in the PROC and PROCR regions with circulating levels of protein C across ethnic populations and identifies new candidates for protein C regulation.
Keywords: Atherosclerosis; Black or African American; Female; Genetic Markers; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein C; Risk

Germline rearrangements in families with strong family history of glioma and malignant melanoma, colon, and breast cancer. - Andersson, Ulrika; Wibom, Carl; Cederquist, Kristina; Aradottir, Steina; Borg, Ake; Armstrong, Georgina N; Shete, Sanjay; Lau, Ching C; Bainbridge, Matthew N; Claus, Elizabeth B; Barnholtz-Sloan, Jill; Lai, Rose; et al. (Neuro Oncol, 2014)
BACKGROUND: Although familial susceptibility to glioma is known, the genetic basis for this susceptibility remains unidentified in the majority of glioma-specific families. An alternative approach to identifying such genes is to examine cancer pedigrees, which include glioma as one of several cancer phenotypes, to determine whether common chromosomal modifications might account for the familial aggregation of glioma and other cancers. METHODS: Germline rearrangements in 146 glioma families (from the Gliogene Consortium; http://www.gliogene.org/) were examined using multiplex ligation-dependent probe amplification. These families all had at least 2 verified glioma cases and a third reported or verified glioma case in the same family or 2 glioma cases in the family with at least one family member affected with melanoma, colon, or breast cancer.The genomic areas covering TP53, CDKN2A, MLH1, and MSH2 were selected because these genes have been previously reported to be associated with cancer pedigrees known to include glioma. RESULTS: We detected a single structural rearrangement, a deletion of exons 1-6 in MSH2, in the proband of one family with 3 cases with glioma and one relative with colon cancer. CONCLUSIONS: Large deletions and duplications are rare events in familial glioma cases, even in families with a strong family history of cancers that may be involved in known cancer syndromes.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Brain Neoplasms; Breast Neoplasms; Checkpoint Kinase 2; Child, Preschool; Colonic Neoplasms; Cyclin-Dependent Kinase Inhibitor p15; Cyclin-Dependent Kinase Inhibitor p16; Female; Genetic Predisposition to Disease; Germ-Line Mutation; Glioma; Humans; Male; Melanoma; Middle Aged; MutL Protein Homolog 1; MutS Homolog 2 Protein; Nuclear Proteins; Pedigree; Tumor Suppressor Protein p53; Young Adult

Gigantism and acromegaly due to Xq26 microduplications and GPR101 mutation. - Trivellin, Giampaolo; Daly, Adrian F; Faucz, Fabio R; Bo Yuan; Rostomyan, Liliya; Larco, Darwin O; Schernthaner-Reiter, Marie Helene; Szarek, Eva; Leal, Letícia F; Caberg, Jean-Hubert; Castermans, Emilie; Villa, Chiara; et al. (N Engl J Med, 2014)
BACKGROUND: Increased secretion of growth hormone leads to gigantism in children and acromegaly in adults; the genetic causes of gigantism and acromegaly are poorly understood. METHODS: We performed clinical and genetic studies of samples obtained from 43 patients with gigantism and then sequenced an implicated gene in samples from 248 patients with acromegaly. RESULTS: We observed microduplication on chromosome Xq26.3 in samples from 13 patients with gigantism; of these samples, 4 were obtained from members of two unrelated kindreds, and 9 were from patients with sporadic cases. All the patients had disease onset during early childhood. Of the patients with gigantism who did not carry an Xq26.3 microduplication, none presented before the age of 5 years. Genomic characterization of the Xq26.3 region suggests that the microduplications are generated during chromosome replication and that they contain four protein-coding genes. Only one of these genes, GPR101, which encodes a G-protein-coupled receptor, was overexpressed in patients' pituitary lesions. We identified a recurrent GPR101 mutation (p.E308D) in 11 of 248 patients with acromegaly, with the mutation found mostly in tumors. When the mutation was transfected into rat GH3 cells, it led to increased release of growth hormone and proliferation of growth hormone-producing cells. CONCLUSIONS: We describe a pediatric disorder (which we have termed X-linked acrogigantism [X-LAG]) that is caused by an Xq26.3 genomic duplication and is characterized by early-onset gigantism resulting from an excess of growth hormone. Duplication of GPR101 probably causes X-LAG. We also found a recurrent mutation in GPR101 in some adults with acromegaly. (Funded by the Eunice Kennedy Shriver National Institute of Child Health and Human Development and others.).
Keywords: Acromegaly; Adolescent; Adult; Age of Onset; Child; Child, Preschool; Chromosome Duplication; Chromosomes, Human, X; Female; Gigantism; Human Growth Hormone; Humans; Infant; Male; Mutation; Phenotype; Protein Conformation; Receptors, G-Protein-Coupled

Heterozygous de novo and inherited mutations in the smooth muscle actin (ACTG2) gene underlie megacystis-microcolon-intestinal hypoperistalsis syndrome. - Wangler, Michael F; Gonzaga-Jauregui, Claudia; Gambin, Tomasz; Penney, Samantha; Moss, Timothy; Chopra, Atul; Probst, Frank J; Xia, Fan; Yang, Yaping; Werlin, Steven; Eglite, Ieva; Kornejeva, Liene; et al. (PLoS Genet, 2014)
Megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) is a rare disorder of enteric smooth muscle function affecting the intestine and bladder. Patients with this severe phenotype are dependent on total parenteral nutrition and urinary catheterization. The cause of this syndrome has remained a mystery since Berdon's initial description in 1976. No genes have been clearly linked to MMIHS. We used whole-exome sequencing for gene discovery followed by targeted Sanger sequencing in a cohort of patients with MMIHS and intestinal pseudo-obstruction. We identified heterozygous ACTG2 missense variants in 15 unrelated subjects, ten being apparent de novo mutations. Ten unique variants were detected, of which six affected CpG dinucleotides and resulted in missense mutations at arginine residues, perhaps related to biased usage of CpG containing codons within actin genes. We also found some of the same heterozygous mutations that we observed as apparent de novo mutations in MMIHS segregating in families with intestinal pseudo-obstruction, suggesting that ACTG2 is responsible for a spectrum of smooth muscle disease. ACTG2 encodes γ2 enteric actin and is the first gene to be clearly associated with MMIHS, suggesting an important role for contractile proteins in enteric smooth muscle disease.
Keywords: Abnormalities, Multiple; Actins; Adolescent; Adult; Child; Child, Preschool; Colon; Exome; Female; Heterozygote; Humans; Intestinal Pseudo-Obstruction; Male; Muscle, Smooth; Mutation; Urinary Bladder

A homozygous missense mutation in NEUROD1 is associated with nonsyndromic autosomal recessive retinitis pigmentosa. - Wang, Feng; Li, Huajin; Xu, Mingchu; Li, Hui; Zhao, Li; Yang, Lizhu; Zaneveld, Jacques E; Wang, Keqing; Yumei Li; Sui, Ruifang; Rui Chen (Invest Ophthalmol Vis Sci, 2014)
PURPOSE: Mutations in the same gene can lead to different clinical phenotypes. In this study, we aim to identify novel genotype-phenotype correlations and novel disease genes by analyzing an unsolved autosomal recessive retinitis pigmentosa (ARRP) Han Chinese family. METHODS: Whole exome sequencing was performed for one proband from the consanguineous ARRP family. Stringent variants filtering and prioritizations were applied to identify the causative mutation. RESULTS: A homozygous missense variant, c.724G>A; p.V242I, in NEUROD1 was identified as the most likely cause of disease. This allele perfectly segregates in the family and affects an amino acid, which is highly conserved among mammals. A previous study showed that a homozygous null allele in NEUROD1 causes severe syndromic disease with neonatal diabetes, systematic neurological abnormalities, and early-onset retinal dystrophy. Consistent with these results, our patients who are homozygous for a less severe missense allele presented only late-onset retinal degeneration without any syndromic symptoms. CONCLUSIONS: We identified a potential novel genotype-phenotype correlation between NEUROD1 and nonsyndromic ARRP. Our study supports the idea that NEUROD1 is important for maintenance of the retina function and partial loss-of-function mutation in NEUROD1 is likely a rare cause of nonsyndromic ARRP.
Keywords: Adult; Basic Helix-Loop-Helix Transcription Factors; DNA; DNA Mutational Analysis; Female; Genes, Recessive; Homozygote; Humans; Male; Mutation, Missense; Pedigree; Phenotype; Retinitis Pigmentosa

Human CLP1 mutations alter tRNA biogenesis, affecting both peripheral and central nervous system function. - Karaca, Ender; Weitzer, Stefan; Pehlivan, Davut; Shiraishi, Hiroshi; Gogakos, Tasos; Hanada, Toshikatsu; Jhangiani, Shalini N; Wiszniewski, Wojciech; Withers, Marjorie; Campbell, Ian M; Erdin, Serkan; Isikay, Sedat; et al. (Cell, 2014)
CLP1 is a RNA kinase involved in tRNA splicing. Recently, CLP1 kinase-dead mice were shown to display a neuromuscular disorder with loss of motor neurons and muscle paralysis. Human genome analyses now identified a CLP1 homozygous missense mutation (p.R140H) in five unrelated families, leading to a loss of CLP1 interaction with the tRNA splicing endonuclease (TSEN) complex, largely reduced pre-tRNA cleavage activity, and accumulation of linear tRNA introns. The affected individuals develop severe motor-sensory defects, cortical dysgenesis, and microcephaly. Mice carrying kinase-dead CLP1 also displayed microcephaly and reduced cortical brain volume due to the enhanced cell death of neuronal progenitors that is associated with reduced numbers of cortical neurons. Our data elucidate a neurological syndrome defined by CLP1 mutations that impair tRNA splicing. Reduction of a founder mutation to homozygosity illustrates the importance of rare variations in disease and supports the clan genomics hypothesis.
Keywords: Abnormalities, Multiple; Animals; Central Nervous System Diseases; Cerebrum; Child, Preschool; Endoribonucleases; Female; Fibroblasts; Humans; Infant; Male; Mice; Mice, Inbred CBA; Microcephaly; Mutation, Missense; Nuclear Proteins; Peripheral Nervous System Diseases; Phosphotransferases; RNA, Transfer; RNA-Binding Proteins; Transcription Factors

Human metabolome associates with dietary intake habits among African Americans in the atherosclerosis risk in communities study. - Zheng, Yan; Yu, Bing; Alexander, Danny; Steffen, Lyn M; Eric Boerwinkle (Am J Epidemiol, 2014)
The human metabolome is a measurable outcome of interactions among an individual's inherited genome, microbiome, and dietary intake. We explored the relationship between dietary intake and serum untargeted metabolomic profiles in a subsample of 1,977 African Americans from the Atherosclerosis Risk in Communities (ARIC) Study in 1987-1989. For each metabolite, we conducted linear regression to estimate its relationships with each food group and food category. Potential confounding factors included age, sex, body mass index (weight (kg)/height (m)(2)), energy intake, kidney function, and food groups. We used a modified Bonferroni correction to determine statistical significance. In total, 48 pairs of diet-metabolite associations were identified, including multiple novel associations. The food group "sugar-rich foods and beverages" was inversely associated with 5 metabolites in the 2-hydroxybutyrate-related subpathway and positively associated with 5 γ-glutamyl dipeptides. The hypothesized mechanism of these associations may be through oxidative stress. "Sugar-rich foods and beverages" were also inversely associated with 7 unsaturated long-chain fatty acids. These findings suggest that the contribution of a sugar-rich dietary pattern to increased cardiovascular disease risk may be partially attributed to oxidative stress and disordered lipid profiles. Metabolomics may reveal novel metabolic biomarkers of dietary intake and provide insight into biochemical pathways underlying nutritional effects on disease development.
Keywords: Atherosclerosis; Biomarkers; Black or African American; Diet; Feeding Behavior; Female; Humans; Male; Metabolome; Middle Aged; Overweight; Risk Factors

Lactobacillus reuteri strain combination in Helicobacter pylori infection: a randomized, double-blind, placebo-controlled study. - Francavilla, Ruggiero; Polimeno, Lorenzo; Demichina, Antonella; Maurogiovanni, Giovanni; Principi, Beatrice; Scaccianoce, Giuseppe; Ierardi, Enzo; Russo, Francesco; Riezzo, Giuseppe; Di Leo, Alfredo; Cavallo, Luciano; Francavilla, Antonio; et al. (J Clin Gastroenterol, 2014)
GOALS: The goals of this study were to investigate the role of a new probiotic preparation (Lactobacillus reuteri DSM 17938 and L. reuteri ATCC PTA 6475) in Helicobacter pylori infection. BACKGROUND: Specific probiotic strains play a role in H. pylori infection for their ability to decrease bacterial load and gastritis, prevent antibiotic-associated side effects, and increase the eradication rate. STUDY: This is a prospective, double-blind, randomized, placebo-controlled study in a tertiary care setting. A total of 100 H. pylori-positive naive patients received either L. reuteri combination (2×10 Colony Forming Units) or placebo during a 3-phase study (pre-eradication, eradication, and follow-up). All underwent C urea breath test (C-UBT), blood assessments of gastrin-17 (G17), endoscopy, and the Gastrointestinal Symptom Rating Scale. Eradication was confirmed by C-UBT 8 weeks after the completion of therapy. RESULTS: Fifty patients were allocated in each group. During pre-eradication period, C-UBT δ decreased by 13% in L. reuteri combination as compared with a 4% increase in placebo (-13.2±34% vs. 4.3±27%; P<0.03). During eradication, GSRS increased significantly in placebo as compared with L. reuteri combination (6.8±2.9 vs. 4±3.1; P<0.01). Significantly less patients in L. reuteri combination as compared with placebo-reported side effects (40.9% vs. 62.8%; P<0.04). An abnormal G17 value was found in patients receiving placebo as compared with L. reuteri combination (28% vs. 12%; P<0.02). Eradication rate was 75% in L. reuteri combination and 65.9% in placebo (P=NS). L. reuteri combination increased eradication rate by 9.1% (odds ratio: 1.5). CONCLUSIONS: L. reuteri combination alone is able to exert an inhibitory effect on H. pylori growth, and when administered with eradication therapy, it determines a significant reduction in antibiotic-associated side effects. Moreover, L. reuteri combination was able to decrease serum G17 levels and to (not significantly) increase the H. pylori-eradication rate.
Keywords: Adolescent; Adult; Aged; Anti-Bacterial Agents; Breath Tests; Double-Blind Method; Drug Therapy, Combination; Female; Follow-Up Studies; Gastrins; Helicobacter Infections; Helicobacter pylori; Humans; Limosilactobacillus reuteri; Male; Middle Aged; Probiotics; Prospective Studies; Treatment Outcome; Young Adult

Large conserved domains of low DNA methylation maintained by Dnmt3a. - Jeong, Mira; Sun, Deqiang; Luo, Min; Huang, Yun; Challen, Grant A; Rodriguez, Benjamin; Zhang, Xiaotian; Chavez, Lukas; Wang, Hui; Hannah, Rebecca; Kim, Sang-Bae; Yang, Liubin; et al. (Nat Genet, 2014)
Gains and losses in DNA methylation are prominent features of mammalian cell types. To gain insight into the mechanisms that promote shifts in DNA methylation and contribute to changes in cell fate, including malignant transformation, we performed genome-wide mapping of 5-methylcytosine and 5-hydroxymethylcytosine in purified mouse hematopoietic stem cells. We discovered extended regions of low methylation (canyons) that span conserved domains frequently containing transcription factors and are distinct from CpG islands and shores. About half of the genes in these methylation canyons are coated with repressive histone marks, whereas the remainder are covered by activating histone marks and are highly expressed in hematopoietic stem cells (HSCs). Canyon borders are demarked by 5-hydroxymethylcytosine and become eroded in the absence of DNA methyltransferase 3a (Dnmt3a). Genes dysregulated in human leukemias are enriched for canyon-associated genes. The new epigenetic landscape we describe may provide a mechanism for the regulation of hematopoiesis and may contribute to leukemia development.
Keywords: 5-Methylcytosine; Animals; Base Sequence; Conserved Sequence; CpG Islands; Cytosine; Databases, Genetic; DNA (Cytosine-5-)-Methyltransferases; DNA Methylation; DNA Methyltransferase 3A; Epigenesis, Genetic; Gene Expression Regulation; Hematopoietic Stem Cells; Histones; Humans; Leukemia; Male; Mice; Mice, Inbred C57BL; Mice, Mutant Strains

Large-scale identification of chemically induced mutations in Drosophila melanogaster. - Haelterman, Nele A; Jiang, Lichun; Yumei Li; Bayat, Vafa; Sandoval, Hector; Ugur, Berrak; Tan, Kai Li; Zhang, Ke; Bei, Danqing; Xiong, Bo; Charng, Wu-Lin; Busby, Theodore; et al. (Genome Res, 2014)
Forward genetic screens using chemical mutagens have been successful in defining the function of thousands of genes in eukaryotic model organisms. The main drawback of this strategy is the time-consuming identification of the molecular lesions causative of the phenotypes of interest. With whole-genome sequencing (WGS), it is now possible to sequence hundreds of strains, but determining which mutations are causative among thousands of polymorphisms remains challenging. We have sequenced 394 mutant strains, generated in a chemical mutagenesis screen, for essential genes on the Drosophila X chromosome and describe strategies to reduce the number of candidate mutations from an average of -3500 to 35 single-nucleotide variants per chromosome. By combining WGS with a rough mapping method based on large duplications, we were able to map 274 (-70%) mutations. We show that these mutations are causative, using small 80-kb duplications that rescue lethality. Hence, our findings demonstrate that combining rough mapping with WGS dramatically expands the toolkit necessary for assigning function to genes.
Keywords: Animals; Chromosome Mapping; Drosophila melanogaster; Ethyl Methanesulfonate; Female; Genes, Essential; Genes, Insect; Male; Molecular Sequence Data; Mutagenesis; Mutagens; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; X Chromosome

Linkage analysis incorporating gene-age interactions identifies seven novel lipid loci: the Family Blood Pressure Program. - Simino, Jeannette; Kume, Rezart; Kraja, Aldi T; Turner, Stephen T; Hanis, Craig L; Sheu, Wayne; Chen, Ida; Jaquish, Cashell; Cooper, Richard S; Chakravarti, Aravinda; Quertermous, Thomas; Eric Boerwinkle; et al. (Atherosclerosis, 2014)
OBJECTIVE: To detect novel loci with age-dependent effects on fasting (≥ 8 h) levels of total cholesterol, high-density lipoprotein, low-density lipoprotein, and triglycerides using 3600 African Americans, 1283 Asians, 3218 European Americans, and 2026 Mexican Americans from the Family Blood Pressure Program (FBPP). METHODS: Within each subgroup (defined by network, race, and sex), we employed stepwise linear regression (retention p ≤ 0.05) to adjust lipid levels for age, age-squared, age-cubed, body-mass-index, current smoking status, current drinking status, field center, estrogen therapy (females only), as well as antidiabetic, antihypertensive, and antilipidemic medication use. For each trait, we pooled the standardized male and female residuals within each network and race and fit a generalized variance components model that incorporated gene-age interactions. We conducted FBPP-wide and race-specific meta-analyses by combining the p-values of each linkage marker across subgroups using a modified Fisher's method. RESULTS: We identified seven novel loci with age-dependent effects; four total cholesterol loci from the meta-analysis of Mexican Americans (on chromosomes 2q24.1, 4q21.21, 8q22.2, and 12p11.23) and three high-density lipoprotein loci from the meta-analysis of all FBPP subgroups (on chromosomes 1p12, 14q11.2, and 21q21.1). These loci lacked significant genome-wide linkage or association evidence in the literature and had logarithm of odds (LOD) score ≥ 3 in the meta-analysis with LOD ≥ 1 in at least two network and race subgroups (exclusively of non-European descent). CONCLUSION: Incorporating gene-age interactions into the analysis of lipids using multi-ethnic cohorts can enhance gene discovery. These interaction loci can guide the selection of families for sequencing studies of lipid-associated variants.
Keywords: Adult; Age Factors; Asian; Asian People; Black or African American; Black People; Blood Pressure; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; Coronary Disease; Ethnicity; Family Health; Female; Genetic Linkage; Genetic Markers; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Lipids; Male; Mexican Americans; Middle Aged; Phenotype; Quantitative Trait Loci; White People

Mammalian Y chromosomes retain widely expressed dosage-sensitive regulators. - Bellott, Daniel W; Hughes, Jennifer F; Skaletsky, Helen; Brown, Laura G; Pyntikova, Tatyana; Cho, Ting-Jan; Koutseva, Natalia; Zaghlul, Sara; Graves, Tina; Rock, Susie; Kremitzki, Colin; Fulton, Robert S; et al. (Nature, 2014)
The human X and Y chromosomes evolved from an ordinary pair of autosomes, but millions of years ago genetic decay ravaged the Y chromosome, and only three per cent of its ancestral genes survived. We reconstructed the evolution of the Y chromosome across eight mammals to identify biases in gene content and the selective pressures that preserved the surviving ancestral genes. Our findings indicate that survival was nonrandom, and in two cases, convergent across placental and marsupial mammals. We conclude that the gene content of the Y chromosome became specialized through selection to maintain the ancestral dosage of homologous X-Y gene pairs that function as broadly expressed regulators of transcription, translation and protein stability. We propose that beyond its roles in testis determination and spermatogenesis, the Y chromosome is essential for male viability, and has unappreciated roles in Turner's syndrome and in phenotypic differences between the sexes in health and disease.
Keywords: Animals; Chromosomes, Human, X; Chromosomes, Human, Y; Disease; Evolution, Molecular; Female; Gene Dosage; Gene Expression Regulation; Health; Humans; Male; Mammals; Marsupialia; Molecular Sequence Annotation; Molecular Sequence Data; Protein Biosynthesis; Protein Stability; Selection, Genetic; Sequence Homology; Sex Characteristics; Spermatogenesis; Testis; Transcription, Genetic; Turner Syndrome; X Chromosome; Y Chromosome

Mechanism, prevalence, and more severe neuropathy phenotype of the Charcot-Marie-Tooth type 1A triplication. - Liu, Pengfei; Gelowani, Violet; Zhang, Feng; Drory, Vivian E; Ben-Shachar, Shay; Roney, Erin; Medeiros, Adam C; Moore, Rebecca J; DiVincenzo, Christina; Burnette, William B; Higgins, Joseph J; Li, Jun; et al. (Am J Hum Genet, 2014)
Copy-number variations cause genomic disorders. Triplications, unlike deletions and duplications, are poorly understood because of challenges in molecular identification, the choice of a proper model system for study, and awareness of their phenotypic consequences. We investigated the genomic disorder Charcot-Marie-Tooth disease type 1A (CMT1A), a dominant peripheral neuropathy caused by a 1.4 Mb recurrent duplication occurring by nonallelic homologous recombination. We identified CMT1A triplications in families in which the duplication segregates. The triplications arose de novo from maternally transmitted duplications and caused a more severe distal symmetric polyneuropathy phenotype. The recombination that generated the triplication occurred between sister chromatids on the duplication-bearing chromosome and could accompany gene conversions with the homologous chromosome. Diagnostic testing for CMT1A (n = 20,661 individuals) identified 13% (n = 2,752 individuals) with duplication and 0.024% (n = 5 individuals) with segmental tetrasomy, suggesting that triplications emerge from duplications at a rate as high as ~1:550, which is more frequent than the rate of de novo duplication. We propose that individuals with duplications are predisposed to acquiring triplications and that the population prevalence of triplication is underascertained.
Keywords: Alleles; Charcot-Marie-Tooth Disease; DNA Copy Number Variations; Female; Gene Dosage; Gene Duplication; Humans; Male; Microsatellite Repeats; Muscular Atrophy; Nucleic Acid Hybridization; Pedigree; Phenotype; Polyneuropathies; Recombination, Genetic

Metabolomic patterns and alcohol consumption in African Americans in the Atherosclerosis Risk in Communities Study. - Zheng, Yan; Yu, Bing; Alexander, Danny; Steffen, Lyn M; Nettleton, Jennifer A; Eric Boerwinkle (Am J Clin Nutr, 2014)
BACKGROUND: Effects of alcohol consumption on health and disease are complex and involve a number of cellular and metabolic processes. OBJECTIVE: We examined the association between alcohol consumption habits and metabolomic profiles. DESIGN: We conducted a cross-sectional study to explore the association of alcohol consumption habits measured by using a questionnaire with serum metabolites measured by using untargeted mass spectrometry in 1977 African Americans from the Jackson field center in the Atherosclerosis Risk in Communities Study. The whole sample was split into a discovery set (n = 1500) and a replication set (n = 477). Alcohol consumption habits were treated as an ordinal variable, with nondrinkers as the reference group and quartiles of current drinkers as ordinal groups with higher values. For each metabolite, a linear regression was conducted to estimate its relation with alcohol consumption habits separately in both sets. A modified Bonferroni procedure was used in the discovery set to adjust the significance threshold (P < 1.9 × 10⁻⁴). RESULTS: In 356 named metabolites, 39 metabolites were significantly associated with alcohol consumption habits in both discovery and replication sets. In general, alcohol consumption was associated with higher levels of most metabolites such as those in amino acid and lipid pathways and with lower levels of γ-glutamyl dipeptides. Three pathways, 2-hydroxybutyrate-related metabolites, γ-glutamyl dipeptides, and lysophosphatidylcholines, which are considered to be involved in inflammation and oxidation, were associated with incident cardiovascular diseases. CONCLUSIONS: To our knowledge, this is the largest metabolomic study thus far conducted in nonwhites. Metabolomic biomarkers of alcohol consumption were identified and replicated. The results lend new insight into potential mediating effects between alcohol consumption and future health and disease.
Keywords: Alcohol Drinking; Atherosclerosis; Biomarkers; Black or African American; Cohort Studies; Cross-Sectional Studies; Female; Humans; Incidence; Linear Models; Longitudinal Studies; Male; Metabolome; Middle Aged; Prevalence; Prospective Studies; Reproducibility of Results; Risk Factors; United States; Up-Regulation

A missense mutation in HK1 leads to autosomal dominant retinitis pigmentosa. - Wang, Feng; Wang, Yandong; Zhang, Bin; Zhao, Li; Lyubasyuk, Vera; Wang, Keqing; Xu, Mingchu; Yumei Li; Wu, Frances; Wen, Cindy; Bernstein, Paul S; Lin, Danni; et al. (Invest Ophthalmol Vis Sci, 2014)
PURPOSE: Retinitis pigmentosa (RP) is a genetically heterogeneous disease with over 60 causative genes known to date. Nevertheless, approximately 40% of RP cases remain genetically unsolved, suggesting that many novel disease-causing genes are yet to be identified. In this study, we aimed to identify the causative mutation for a large autosomal dominant RP (adRP) family with negative results from known retinal disease gene screening. METHODS: Linkage analysis followed by whole-exome sequencing was performed. Stringent variant filtering and prioritization was carried out to identify the causative mutation. RESULTS: Linkage analysis identified a minimal disease region of 8 Mb on chromosome 10 with a peak parametric logarithm (base 10) of odds (LOD) score of 3.500. Further whole-exome sequencing identified a heterozygous missense mutation (NM_000188.2:c.2539G>A, p.E847K) in hexokinase 1 (HK1) that segregated with the disease phenotype in the family. Biochemical assays showed that the E847K mutation does not affect hexokinase enzymatic activity or the protein stability, suggesting that the mutation may impact other uncharacterized function or result in a gain of function of HK1. CONCLUSIONS: Here, we identified HK1 as a novel causative gene for adRP. This is the first report that associates the glucose metabolic pathway with human retinal degenerative disease, suggesting a potential new disease mechanism.
Keywords: Adolescent; Child; Child, Preschool; DNA; DNA Mutational Analysis; Female; Genes, Dominant; Genetic Linkage; Genetic Predisposition to Disease; Heterozygote; Hexokinase; Humans; Male; Mutation, Missense; Pedigree; Phenotype; Retinitis Pigmentosa; Young Adult

Molecular findings among patients referred for clinical whole-exome sequencing. - Yang, Yaping; Donna M Muzny; Xia, Fan; Niu, Zhiyv; Person, Richard; Ding, Yan; Ward, Patricia; Braxton, Alicia; Wang, Min; Buhay, Christian; Veeraraghavan, Narayanan; Hawes, Alicia; et al. (JAMA, 2014)
IMPORTANCE: Clinical whole-exome sequencing is increasingly used for diagnostic evaluation of patients with suspected genetic disorders. OBJECTIVE: To perform clinical whole-exome sequencing and report (1) the rate of molecular diagnosis among phenotypic groups, (2) the spectrum of genetic alterations contributing to disease, and (3) the prevalence of medically actionable incidental findings such as FBN1 mutations causing Marfan syndrome. DESIGN, SETTING, AND PATIENTS: Observational study of 2000 consecutive patients with clinical whole-exome sequencing analyzed between June 2012 and August 2014. Whole-exome sequencing tests were performed at a clinical genetics laboratory in the United States. Results were reported by clinical molecular geneticists certified by the American Board of Medical Genetics and Genomics. Tests were ordered by the patient's physician. The patients were primarily pediatric (1756 [88%]; mean age, 6 years; 888 females [44%], 1101 males [55%], and 11 fetuses [1% gender unknown]), demonstrating diverse clinical manifestations most often including nervous system dysfunction such as developmental delay. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing diagnosis rate overall and by phenotypic category, mode of inheritance, spectrum of genetic events, and reporting of incidental findings. RESULTS: A molecular diagnosis was reported for 504 patients (25.2%) with 58% of the diagnostic mutations not previously reported. Molecular diagnosis rates for each phenotypic category were 143/526 (27.2%; 95% CI, 23.5%-31.2%) for the neurological group, 282/1147 (24.6%; 95% CI, 22.1%-27.2%) for the neurological plus other organ systems group, 30/83 (36.1%; 95% CI, 26.1%-47.5%) for the specific neurological group, and 49/244 (20.1%; 95% CI, 15.6%-25.8%) for the nonneurological group. The Mendelian disease patterns of the 527 molecular diagnoses included 280 (53.1%) autosomal dominant, 181 (34.3%) autosomal recessive (including 5 with uniparental disomy), 65 (12.3%) X-linked, and 1 (0.2%) mitochondrial. Of 504 patients with a molecular diagnosis, 23 (4.6%) had blended phenotypes resulting from 2 single gene defects. About 30% of the positive cases harbored mutations in disease genes reported since 2011. There were 95 medically actionable incidental findings in genes unrelated to the phenotype but with immediate implications for management in 92 patients (4.6%), including 59 patients (3%) with mutations in genes recommended for reporting by the American College of Medical Genetics and Genomics. CONCLUSIONS AND RELEVANCE: Whole-exome sequencing provided a potential molecular diagnosis for 25% of a large cohort of patients referred for evaluation of suspected genetic conditions, including detection of rare genetic events and new mutations contributing to disease. The yield of whole-exome sequencing may offer advantages over traditional molecular diagnostic approaches in certain patients.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Fetus; Genetic Diseases, Inborn; Genetic Testing; Genomics; Humans; Incidental Findings; Infant; Infant, Newborn; Male; Molecular Diagnostic Techniques; Mutation; Phenotype; Referral and Consultation; Sequence Analysis, DNA

Monoallelic and biallelic mutations in MAB21L2 cause a spectrum of major eye malformations. - Rainger, Joe; Pehlivan, Davut; Johansson, Stefan; Bengani, Hemant; Sanchez-Pulido, Luis; Williamson, Kathleen A; Ture, Mehmet; Barker, Heather; Rosendahl, Karen; Spranger, Jürgen; Horn, Denise; Meynert, Alison; et al. (Am J Hum Genet, 2014)
We identified four different missense mutations in the single-exon gene MAB21L2 in eight individuals with bilateral eye malformations from five unrelated families via three independent exome sequencing projects. Three mutational events altered the same amino acid (Arg51), and two were identical de novo mutations (c.151C>T [p.Arg51Cys]) in unrelated children with bilateral anophthalmia, intellectual disability, and rhizomelic skeletal dysplasia. c.152G>A (p.Arg51His) segregated with autosomal-dominant bilateral colobomatous microphthalmia in a large multiplex family. The fourth heterozygous mutation (c.145G>A [p.Glu49Lys]) affected an amino acid within two residues of Arg51 in an adult male with bilateral colobomata. In a fifth family, a homozygous mutation (c.740G>A [p.Arg247Gln]) altering a different region of the protein was identified in two male siblings with bilateral retinal colobomata. In mouse embryos, Mab21l2 showed strong expression in the developing eye, pharyngeal arches, and limb bud. As predicted by structural homology, wild-type MAB21L2 bound single-stranded RNA, whereas this activity was lost in all altered forms of the protein. MAB21L2 had no detectable nucleotidyltransferase activity in vitro, and its function remains unknown. Induced expression of wild-type MAB21L2 in human embryonic kidney 293 cells increased phospho-ERK (pERK1/2) signaling. Compared to the wild-type and p.Arg247Gln proteins, the proteins with the Glu49 and Arg51 variants had increased stability. Abnormal persistence of pERK1/2 signaling in MAB21L2-expressing cells during development is a plausible pathogenic mechanism for the heterozygous mutations. The phenotype associated with the homozygous mutation might be a consequence of complete loss of MAB21L2 RNA binding, although the cellular function of this interaction remains unknown.
Keywords: Adult; Alleles; Animals; Anophthalmos; Brain Diseases, Metabolic, Inborn; Coloboma; Corneal Opacity; Exome; Eye Proteins; Female; Gene Expression; HEK293 Cells; Heterozygote; Homozygote; Humans; Intellectual Disability; Intracellular Signaling Peptides and Proteins; Male; Mice; Microcephaly; Microphthalmos; Mutation, Missense; Pedigree; Phenotype; Protein Conformation; Signal Transduction

Mutations in NGLY1 cause an inherited disorder of the endoplasmic reticulum-associated degradation pathway. - Enns, Gregory M; Shashi, Vandana; Bainbridge, Matthew; Gambello, Michael J; Zahir, Farah R; Bast, Thomas; Crimian, Rebecca; Schoch, Kelly; Platt, Julia; Cox, Rachel; Bernstein, Jonathan A; Scavina, Mena; et al. (Genet Med, 2014)
PURPOSE: The endoplasmic reticulum-associated degradation pathway is responsible for the translocation of misfolded proteins across the endoplasmic reticulum membrane into the cytosol for subsequent degradation by the proteasome. To define the phenotype associated with a novel inherited disorder of cytosolic endoplasmic reticulum-associated degradation pathway dysfunction, we studied a series of eight patients with deficiency of N-glycanase 1. METHODS: Whole-genome, whole-exome, or standard Sanger sequencing techniques were employed. Retrospective chart reviews were performed in order to obtain clinical data. RESULTS: All patients had global developmental delay, a movement disorder, and hypotonia. Other common findings included hypolacrima or alacrima (7/8), elevated liver transaminases (6/7), microcephaly (6/8), diminished reflexes (6/8), hepatocyte cytoplasmic storage material or vacuolization (5/6), and seizures (4/8). The nonsense mutation c.1201A>T (p.R401X) was the most common deleterious allele. CONCLUSION: NGLY1 deficiency is a novel autosomal recessive disorder of the endoplasmic reticulum-associated degradation pathway associated with neurological dysfunction, abnormal tear production, and liver disease. The majority of patients detected to date carry a specific nonsense mutation that appears to be associated with severe disease. The phenotypic spectrum is likely to enlarge as cases with a broader range of mutations are detected.
Keywords: Abnormalities, Multiple; Adolescent; Child, Preschool; Developmental Disabilities; Endoplasmic Reticulum-Associated Degradation; Exome; Family Health; Fatal Outcome; Female; Genome-Wide Association Study; Humans; Infant; Male; Microcephaly; Movement Disorders; Muscle Hypotonia; Mutation; Pedigree; Peptide-N4-(N-acetyl-beta-glucosaminyl) Asparagine Amidase; Retrospective Studies; Seizures; Sequence Analysis, DNA; Signal Transduction; Young Adult

Natural variation in genome architecture among 205 Drosophila melanogaster Genetic Reference Panel lines. - Huang, Wen; Massouras, Andreas; Inoue, Yutaka; Peiffer, Jason; Ràmia, Miquel; Tarone, Aaron M; Turlapati, Lavanya; Zichner, Thomas; Zhu, Dianhui; Lyman, Richard F; Magwire, Michael M; Blankenburg, Kerstin; et al. (Genome Res, 2014)
The Drosophila melanogaster Genetic Reference Panel (DGRP) is a community resource of 205 sequenced inbred lines, derived to improve our understanding of the effects of naturally occurring genetic variation on molecular and organismal phenotypes. We used an integrated genotyping strategy to identify 4,853,802 single nucleotide polymorphisms (SNPs) and 1,296,080 non-SNP variants. Our molecular population genomic analyses show higher deletion than insertion mutation rates and stronger purifying selection on deletions. Weaker selection on insertions than deletions is consistent with our observed distribution of genome size determined by flow cytometry, which is skewed toward larger genomes. Insertion/deletion and single nucleotide polymorphisms are positively correlated with each other and with local recombination, suggesting that their nonrandom distributions are due to hitchhiking and background selection. Our cytogenetic analysis identified 16 polymorphic inversions in the DGRP. Common inverted and standard karyotypes are genetically divergent and account for most of the variation in relatedness among the DGRP lines. Intriguingly, variation in genome size and many quantitative traits are significantly associated with inversions. Approximately 50% of the DGRP lines are infected with Wolbachia, and four lines have germline insertions of Wolbachia sequences, but effects of Wolbachia infection on quantitative traits are rarely significant. The DGRP complements ongoing efforts to functionally annotate the Drosophila genome. Indeed, 15% of all D. melanogaster genes segregate for potentially damaged proteins in the DGRP, and genome-wide analyses of quantitative traits identify novel candidate genes. The DGRP lines, sequence data, genotypes, quality scores, phenotypes, and analysis and visualization tools are publicly available.
Keywords: Animals; Chromatin; Drosophila melanogaster; Female; Genetic Linkage; Genetic Variation; Genome Size; Genome, Insect; Genome-Wide Association Study; Genotype; Genotyping Techniques; High-Throughput Nucleotide Sequencing; INDEL Mutation; Linkage Disequilibrium; Male; Molecular Sequence Annotation; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable; Reproducibility of Results

New syndrome with retinitis pigmentosa is caused by nonsense mutations in retinol dehydrogenase RDH11. - Xie, Yajing Angela; Lee, Winston; Cai, Carolyn; Gambin, Tomasz; Nõupuu, Kalev; Sujirakul, Tharikarn; Ayuso, Carmen; Jhangiani, Shalini; Donna M Muzny; Eric Boerwinkle; Richard A Gibbs; Greenstein, Vivienne C; et al. (Hum Mol Genet, 2014)
Retinitis pigmentosa (RP), a genetically heterogeneous group of retinopathies that occur in both non-syndromic and syndromic forms, is caused by mutations in ∼100 genes. Although recent advances in next-generation sequencing have aided in the discovery of novel RP genes, a number of the underlying contributing genes and loci remain to be identified. We investigated three siblings, born to asymptomatic parents of Italian-American descent, who each presented with atypical RP with systemic features, including facial dysmorphologies, psychomotor developmental delays recognized since early childhood, learning disabilities and short stature. RP-associated ophthalmological findings included salt-and-pepper retinopathy, attenuation of the arterioles and generalized rod-cone dysfunction as determined by almost extinguished electroretinogram in 2 of 3 siblings. Atypical for RP features included mottled macula at an early age and peripapillary sparing of the retinal pigment epithelium. Whole-exome sequencing data, queried under a recessive model of inheritance, identified compound heterozygous stop mutations, c.C199T:p.R67* and c.C322T:p.R108*, in the retinol dehydrogenase 11 (RDH11) gene, resulting in a non-functional protein, in all affected children. In summary, deleterious mutations in RDH11, an important enzyme for vision-related and systemic retinoic acid metabolism, cause a new syndrome with RP.
Keywords: Adolescent; Child; Codon, Nonsense; Female; Humans; Male; Oxidoreductases; Pedigree; Phenotype; Retinitis Pigmentosa; Syndrome; Vision Tests; Visual Acuity; Young Adult

Novel somatic and germline mutations in intracranial germ cell tumours. - Wang, Linghua; Yamaguchi, Shigeru; Burstein, Matthew D; Terashima, Keita; Chang, Kyle; Ng, Ho-Keung; Nakamura, Hideo; He, Zongxiao; Harshavardhan Doddapaneni; Lewis, Lora; Wang, Mark; Suzuki, Tomonari; et al. (Nature, 2014)
Intracranial germ cell tumours (IGCTs) are a group of rare heterogeneous brain tumours that are clinically and histologically similar to the more common gonadal GCTs. IGCTs show great variation in their geographical and gender distribution, histological composition and treatment outcomes. The incidence of IGCTs is historically five- to eightfold greater in Japan and other East Asian countries than in Western countries, with peak incidence near the time of puberty. About half of the tumours are located in the pineal region. The male-to-female incidence ratio is approximately 3-4:1 overall, but is even higher for tumours located in the pineal region. Owing to the scarcity of tumour specimens available for research, little is currently known about this rare disease. Here we report the analysis of 62 cases by next-generation sequencing, single nucleotide polymorphism array and expression array. We find the KIT/RAS signalling pathway frequently mutated in more than 50% of IGCTs, including novel recurrent somatic mutations in KIT, its downstream mediators KRAS and NRAS, and its negative regulator CBL. Novel somatic alterations in the AKT/mTOR pathway included copy number gains of the AKT1 locus at 14q32.33 in 19% of patients, with corresponding upregulation of AKT1 expression. We identified loss-of-function mutations in BCORL1, a transcriptional co-repressor and tumour suppressor. We report significant enrichment of novel and rare germline variants in JMJD1C, which codes for a histone demethylase and is a coactivator of the androgen receptor, among Japanese IGCT patients. This study establishes a molecular foundation for understanding the biology of IGCTs and suggests potentially promising therapeutic strategies focusing on the inhibition of KIT/RAS activation and the AKT1/mTOR pathway.
Keywords: Adult; Brain Neoplasms; Child; Female; Germ-Line Mutation; Humans; Japan; Male; Mutation; Neoplasms, Germ Cell and Embryonal; Oncogene Protein v-akt; Proto-Oncogene Proteins c-kit; ras Proteins; Reproducibility of Results; Signal Transduction; TOR Serine-Threonine Kinases; Young Adult

NR2F1 mutations cause optic atrophy with intellectual disability. - Bosch, Daniëlle G M; Boonstra, F Nienke; Gonzaga-Jauregui, Claudia; Xu, Mafei; de Ligt, Joep; Jhangiani, Shalini; Wiszniewski, Wojciech; Donna M Muzny; Yntema, Helger G; Pfundt, Rolph; Vissers, Lisenka E L M; Spruijt, Liesbeth; et al. (Am J Hum Genet, 2014)
Optic nerve atrophy and hypoplasia can be primary disorders or can result from trans-synaptic degeneration arising from cerebral visual impairment (CVI). Here we report six individuals with CVI and/or optic nerve abnormalities, born after an uneventful pregnancy and delivery, who have either de novo heterozygous missense mutations in NR2F1, also known as COUP-TFI, or deletions encompassing NR2F1. All affected individuals show mild to moderate intellectual impairment. NR2F1 encodes a nuclear receptor protein that regulates transcription. A reporter assay showed that missense mutations in the zinc-finger DNA-binding domain and the putative ligand-binding domain decrease NR2F1 transcriptional activity. These findings indicate that NR2F1 plays an important role in the neurodevelopment of the visual system and that its disruption can lead to optic atrophy with intellectual disability.
Keywords: Adolescent; Adult; Amino Acid Sequence; Child; Child, Preschool; COUP Transcription Factor I; DNA-Binding Proteins; Female; Genotype; Humans; Intellectual Disability; Male; Molecular Sequence Data; Mutation, Missense; Optic Atrophy; Phenotype; Young Adult; Zinc Fingers

Parent of origin, mosaicism, and recurrence risk: probabilistic modeling explains the broken symmetry of transmission genetics. - Campbell, Ian M; Stewart, Jonathan R; James, Regis A; Lupski, James R; Stankiewicz, Paweł; Olofsson, Peter; Shaw, Chad A (Am J Hum Genet, 2014)
Most new mutations are observed to arise in fathers, and increasing paternal age positively correlates with the risk of new variants. Interestingly, new mutations in X-linked recessive disease show elevated familial recurrence rates. In male offspring, these mutations must be inherited from mothers. We previously developed a simulation model to consider parental mosaicism as a source of transmitted mutations. In this paper, we extend and formalize the model to provide analytical results and flexible formulas. The results implicate parent of origin and parental mosaicism as central variables in recurrence risk. Consistent with empirical data, our model predicts that more transmitted mutations arise in fathers and that this tendency increases as fathers age. Notably, the lack of expansion later in the male germline determines relatively lower variance in the proportion of mutants, which decreases with paternal age. Subsequently, observation of a transmitted mutation has less impact on the expected risk for future offspring. Conversely, for the female germline, which arrests after clonal expansion in early development, variance in the mutant proportion is higher, and observation of a transmitted mutation dramatically increases the expected risk of recurrence in another pregnancy. Parental somatic mosaicism considerably elevates risk for both parents. These findings have important implications for genetic counseling and for understanding patterns of recurrence in transmission genetics. We provide a convenient online tool and source code implementing our analytical results. These tools permit varying the underlying parameters that influence recurrence risk and could be useful for analyzing risk in diverse family structures.
Keywords: Adult; Aged; Aged, 80 and over; Chromosome Aberrations; DNA Copy Number Variations; Fathers; Female; Gametogenesis; Genetic Diseases, Inborn; Genomics; Germ Cells; Germ-Line Mutation; Humans; Inheritance Patterns; Male; Middle Aged; Models, Theoretical; Mosaicism; Mothers; Pregnancy; Recurrence; Risk Factors; Young Adult

Parental somatic mosaicism is underrecognized and influences recurrence risk of genomic disorders. - Campbell, Ian M; Bo Yuan; Robberecht, Caroline; Pfundt, Rolph; Szafranski, Przemyslaw; McEntagart, Meriel E; Nagamani, Sandesh C S; Erez, Ayelet; Bartnik, Magdalena; Wiśniowiecka-Kowalnik, Barbara; Plunkett, Katie S; Pursley, Amber N; et al. (Am J Hum Genet, 2014)
New human mutations are thought to originate in germ cells, thus making a recurrence of the same mutation in a sibling exceedingly rare. However, increasing sensitivity of genomic technologies has anecdotally revealed mosaicism for mutations in somatic tissues of apparently healthy parents. Such somatically mosaic parents might also have germline mosaicism that can potentially cause unexpected intergenerational recurrences. Here, we show that somatic mosaicism for transmitted mutations among parents of children with simplex genetic disease is more common than currently appreciated. Using the sensitivity of individual-specific breakpoint PCR, we prospectively screened 100 families with children affected by genomic disorders due to rare deletion copy-number variants (CNVs) determined to be de novo by clinical analysis of parental DNA. Surprisingly, we identified four cases of low-level somatic mosaicism for the transmitted CNV in DNA isolated from parental blood. Integrated probabilistic modeling of gametogenesis developed in response to our observations predicts that mutations in parental blood increase recurrence risk substantially more than parental mutations confined to the germline. Moreover, despite the fact that maternally transmitted mutations are the minority of alleles, our model suggests that sexual dimorphisms in gametogenesis result in a greater proportion of somatically mosaic transmitting mothers who are thus at increased risk of recurrence. Therefore, somatic mosaicism together with sexual differences in gametogenesis might explain a considerable fraction of unexpected recurrences of X-linked recessive disease. Overall, our results underscore an important role for somatic mosaicism and mitotic replicative mutational mechanisms in transmission genetics.
Keywords: Cell Division; DNA Copy Number Variations; Female; Gametogenesis; Genetic Diseases, Inborn; Genomics; Germ Cells; Germ-Line Mutation; Humans; Male; Models, Genetic; Mosaicism; Mutation; Pedigree; Prospective Studies; Recurrence; Risk; Sex Characteristics; Smith-Magenis Syndrome

PGM3 mutations cause a congenital disorder of glycosylation with severe immunodeficiency and skeletal dysplasia. - Stray-Pedersen, Asbjørg; Backe, Paul H; Sorte, Hanne S; Mørkrid, Lars; Chokshi, Niti Y; Erichsen, Hans Christian; Gambin, Tomasz; Elgstøen, Katja B P; Bjørås, Magnar; Wlodarski, Marcin W; Krüger, Marcus; Jhangiani, Shalini N; et al. (Am J Hum Genet, 2014)
Human phosphoglucomutase 3 (PGM3) catalyzes the conversion of N-acetyl-glucosamine (GlcNAc)-6-phosphate into GlcNAc-1-phosphate during the synthesis of uridine diphosphate (UDP)-GlcNAc, a sugar nucleotide critical to multiple glycosylation pathways. We identified three unrelated children with recurrent infections, congenital leukopenia including neutropenia, B and T cell lymphopenia, and progression to bone marrow failure. Whole-exome sequencing demonstrated deleterious mutations in PGM3 in all three subjects, delineating their disease to be due to an unsuspected congenital disorder of glycosylation (CDG). Functional studies of the disease-associated PGM3 variants in E. coli cells demonstrated reduced PGM3 activity for all mutants tested. Two of the three children had skeletal anomalies resembling Desbuquois dysplasia: short stature, brachydactyly, dysmorphic facial features, and intellectual disability. However, these additional features were absent in the third child, showing the clinical variability of the disease. Two children received hematopoietic stem cell transplantation of cord blood and bone marrow from matched related donors; both had successful engraftment and correction of neutropenia and lymphopenia. We define PGM3-CDG as a treatable immunodeficiency, document the power of whole-exome sequencing in gene discoveries for rare disorders, and illustrate the utility of genomic analyses in studying combined and variable phenotypes.
Keywords: Bone Diseases, Developmental; Congenital Disorders of Glycosylation; Female; Humans; Immunologic Deficiency Syndromes; Male; Mutation; Pedigree; Phosphoglucomutase

Possible race and gender divergence in association of genetic variations with plasma von Willebrand factor: a study of ARIC and 1000 genome cohorts. - Zhou, Zhou; Fuli Yu; Buchanan, Ashley; Fu, Yuanyuan; Campos, Marco; Wu, Kenneth K; Chambless, Lloyd E; Folsom, Aaron R; Eric Boerwinkle; Dong, Jing-fei (PLoS One, 2014)
The synthesis, secretion and clearance of von Willebrand factor (VWF) are regulated by genetic variations in coding and promoter regions of the VWF gene. We have previously identified 19 single nucleotide polymorphisms (SNPs), primarily in introns that are associated with VWF antigen levels in subjects of European descent. In this study, we conducted race by gender analyses to compare the association of VWF SNPs with VWF antigen among 10,434 healthy Americans of European (EA) or African (AA) descent from the Atherosclerosis Risk in Communities (ARIC) study. Among 75 SNPs analyzed, 13 and 10 SNPs were associated with VWF antigen levels in EA male and EA female subjects, respectively. However, only one SNP (RS1063857) was significantly associated with VWF antigen in AA females and none was in AA males. Haplotype analysis of the ARIC samples and studying racial diversities in the VWF gene from the 1000 genomes database suggest a greater degree of variations in the VWF gene in AA subjects as compared to EA subjects. Together, these data suggest potential race and gender divergence in regulating VWF expression by genetic variations.
Keywords: Atherosclerosis; Black People; Cohort Studies; Demography; Female; Gene Frequency; Genetic Variation; Genome, Human; Haplotypes; Humans; Male; Polymorphism, Single Nucleotide; Sex Characteristics; von Willebrand Factor; White People

Prospective associations of coronary heart disease loci in African Americans using the MetaboChip: the PAGE study. - Franceschini, Nora; Hu, Yijuan; Reiner, Alex P; Buyske, Steven; Nalls, Mike; Yanek, Lisa R; Li, Yun; Hindorff, Lucia A; Cole, Shelley A; Howard, Barbara V; Stafford, Jeanette M; Carty, Cara L; et al. (PLoS One, 2014)
BACKGROUND: Coronary heart disease (CHD) is a leading cause of morbidity and mortality in African Americans. However, there is a paucity of studies assessing genetic determinants of CHD in African Americans. We examined the association of published variants in CHD loci with incident CHD, attempted to fine map these loci, and characterize novel variants influencing CHD risk in African Americans. METHODS AND RESULTS: Up to 8,201 African Americans (including 546 first CHD events) were genotyped using the MetaboChip array in the Atherosclerosis Risk in Communities (ARIC) study and Women's Health Initiative (WHI). We tested associations using Cox proportional hazard models in sex- and study-stratified analyses and combined results using meta-analysis. Among 44 validated CHD loci available in the array, we replicated and fine-mapped the SORT1 locus, and showed same direction of effects as reported in studies of individuals of European ancestry for SNPs in 22 additional published loci. We also identified a SNP achieving array wide significance (MYC: rs2070583, allele frequency 0.02, P = 8.1 × 10(-8)), but the association did not replicate in an additional 8,059 African Americans (577 events) from the WHI, HealthABC and GeneSTAR studies, and in a meta-analysis of 5 cohort studies of European ancestry (24,024 individuals including 1,570 cases of MI and 2,406 cases of CHD) from the CHARGE Consortium. CONCLUSIONS: Our findings suggest that some CHD loci previously identified in individuals of European ancestry may be relevant to incident CHD in African Americans.
Keywords: Adaptor Proteins, Vesicular Transport; Black or African American; Coronary Disease; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Prospective Studies; Proto-Oncogene Proteins c-myc

Serum metabolomic profiling and incident CKD among African Americans. - Yu, Bing; Zheng, Yan; Nettleton, Jennifer A; Alexander, Danny; Coresh, Josef; Eric Boerwinkle (Clin J Am Soc Nephrol, 2014)
BACKGROUND AND OBJECTIVES: Novel biomarkers that more accurately reflect kidney function and predict future CKD are needed. The human metabolome is the product of multiple physiologic or pathophysiologic processes and may provide novel insight into disease etiology and progression. This study investigated whether estimated kidney function would be associated with multiple metabolites and whether selected metabolomic factors would be independent risk factors for incident CKD. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: In total, 1921 African Americans free of CKD with a median of 19.6 years follow-up among the Atherosclerosis Risk in Communities Study were included. A total of 204 serum metabolites quantified by untargeted gas chromatography-mass spectrometry and liquid chromatography-mass spectrometry was analyzed by both linear regression for the cross-sectional associations with eGFR (specified by the Chronic Kidney Disease Epidemiology Collaboration equation) and Cox proportional hazards model for the longitudinal associations with incident CKD. RESULTS: Forty named and 34 unnamed metabolites were found to be associated with eGFR specified by the Chronic Kidney Disease Epidemiology Collaboration equation with creatine and 3-indoxyl sulfate showing the strongest positive (2.8 ml/min per 1.73 m(2) per +1 SD; 95% confidence interval, 2.1 to 3.5) and negative association (-14.2 ml/min per 1.73 m(2) per +1 SD; 95% confidence interval, -17.0 to -11.3), respectively. Two hundred four incident CKD events with a median follow-up time of 19.6 years were included in the survival analyses. Higher levels of 5-oxoproline (hazard ratio, 0.70; 95% confidence interval, 0.60 to 0.82) and 1,5-anhydroglucitol (hazard ratio, 0.68; 95% confidence interval, 0.58 to 0.80) were significantly related to lower risk of incident CKD, and the associations did not appreciably change when mutually adjusted. CONCLUSIONS: These data identify a large number of metabolites associated with kidney function as well as two metabolites that are candidate risk factors for CKD and may provide new insights into CKD biomarker identification.
Keywords: Biomarkers; Black or African American; Chromatography, Liquid; Creatine; Cross-Sectional Studies; Deoxyglucose; Female; Gas Chromatography-Mass Spectrometry; Humans; Incidence; Indican; Kidney; Linear Models; Longitudinal Studies; Male; Metabolomics; Middle Aged; Proportional Hazards Models; Pyrrolidonecarboxylic Acid; Renal Insufficiency, Chronic; Risk Factors; Time Factors; United States

Squamous cell carcinoma of the oral tongue in young non-smokers is genomically similar to tumors in older smokers. - Pickering, Curtis R; Zhang, Jiexin; Neskey, David M; Zhao, Mei; Jasser, Samar A; Wang, Jiping; Ward, Alexandra; Tsai, C Jillian; Ortega Alves, Marcus V; Zhou, Jane H; Drummond, Jennifer; El-Naggar, Adel K; et al. (Clin Cancer Res, 2014)
PURPOSE: Epidemiologic studies have identified an increasing incidence of squamous cell carcinoma of the oral tongue (SCCOT) in younger patients. EXPERIMENTAL DESIGN: DNA isolated from tongue tumors of young (<45 years, non-smokers) and old (>45 years) patients at was subjected to whole-exome sequencing and copy-number analysis. These data were compared with data from similar patients in the TCGA (The Cancer Genome Atlas) project. RESULTS: In this study, we found that gene-specific mutation and copy-number alteration frequencies were similar between young and old patients with SCCOT in two independent cohorts. Likewise, the types of base changes observed in the young cohort were similar to those in the old cohort even though they differed in smoking history. TCGA data also demonstrate that the genomic effects of smoking are tumor site-specific, and we find that smoking has only a minor impact on the types of mutations observed in SCCOT. CONCLUSIONS: Overall, tumors from young patients with SCCOT appear genomically similar to those of older patients with SCCOT, and the cause for the increasing incidence of young SCCOT remains unknown. These data indicate that the functional impact of smoking on carcinogenesis in SCCOT is still poorly understood.
Keywords: Adult; Age Factors; Carcinoma, Squamous Cell; DNA Copy Number Variations; DNA Mutational Analysis; Female; Humans; Male; Middle Aged; Mutation; Prognosis; Smoking; Tongue Neoplasms

Targeted sequencing in candidate genes for atrial fibrillation: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study. - Lin, Honghuang; Sinner, Moritz F; Brody, Jennifer A; Arking, Dan E; Lunetta, Kathryn L; Rienstra, Michiel; Lubitz, Steven A; Magnani, Jared W; Sotoodehnia, Nona; McKnight, Barbara; McManus, David D; Eric Boerwinkle; et al. (Heart Rhythm, 2014)
BACKGROUND: Genome-wide association studies (GWAS) have identified common genetic variants that predispose to atrial fibrillation (AF). It is unclear whether rare and low-frequency variants in genes implicated by such GWAS confer additional risk of AF. OBJECTIVE: To study the association of genetic variants with AF at GWAS top loci. METHODS: In the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study, we selected and sequenced 77 target gene regions from GWAS loci of complex diseases or traits, including 4 genes hypothesized to be related to AF (PRRX1, CAV1, CAV2, and ZFHX3). Sequencing was performed in participants with (n = 948) and without (n = 3330) AF from the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Massachusetts General Hospital. RESULTS: One common variant (rs11265611; P = 1.70 × 10(-6)) intronic to IL6R (interleukin-6 receptor gene) was significantly associated with AF after Bonferroni correction (odds ratio 0.70; 95% confidence interval 0.58-0.85). The variant was not genotyped or imputed by prior GWAS, but it is in linkage disequilibrium (r(2) = .69) with the single-nucleotide polymorphism, with the strongest association with AF so far at this locus (rs4845625). In the rare variant joint analysis, damaging variants within the PRRX1 region showed significant association with AF after Bonferroni correction (P = .01). CONCLUSIONS: We identified 1 common single-nucleotide polymorphism and 1 gene region that were significantly associated with AF. Future sequencing efforts with larger sample sizes and more comprehensive genome coverage are anticipated to identify additional AF-related variants.
Keywords: Aged; Atrial Fibrillation; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeodomain Proteins; Humans; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Interleukin-6

Two novel simian arteriviruses in captive and wild baboons (Papio spp.). - Bailey, Adam L; Lauck, Michael; Sibley, Samuel D; Pecotte, Jerilyn; Rice, Karen; Weny, Geoffrey; Tumukunde, Alex; Hyeroba, David; Greene, Justin; Correll, Michael; Gleicher, Michael; Friedrich, Thomas C; et al. (J Virol, 2014)
UNLABELLED: Since the 1960s, simian hemorrhagic fever virus (SHFV; Nidovirales, Arteriviridae) has caused highly fatal outbreaks of viral hemorrhagic fever in captive Asian macaque colonies. However, the source(s) of these outbreaks and the natural reservoir(s) of this virus remain obscure. Here we report the identification of two novel, highly divergent simian arteriviruses related to SHFV, Mikumi yellow baboon virus 1 (MYBV-1) and Southwest baboon virus 1 (SWBV-1), in wild and captive baboons, respectively, and demonstrate the recent transmission of SWBV-1 among captive baboons. These findings extend our knowledge of the genetic and geographic diversity of the simian arteriviruses, identify baboons as a natural host of these viruses, and provide further evidence that baboons may have played a role in previous outbreaks of simian hemorrhagic fever in macaques, as has long been suspected. This knowledge should aid in the prevention of disease outbreaks in captive macaques and supports the growing body of evidence that suggests that simian arterivirus infections are common in Old World monkeys of many different species throughout Africa. IMPORTANCE: Historically, the emergence of primate viruses both in humans and in other primate species has caused devastating outbreaks of disease. One strategy for preventing the emergence of novel primate pathogens is to identify microbes with the potential for cross-species transmission in their natural state within reservoir species from which they might emerge. Here, we detail the discovery and characterization of two related simian members of the Arteriviridae family that have a history of disease emergence and host switching. Our results expand the phylogenetic and geographic range of the simian arteriviruses and define baboons as a natural host for these viruses. Our findings also identify a potential threat to captive macaque colonies by showing that simian arteriviruses are actively circulating in captive baboons.
Keywords: Animals; Animals, Wild; Animals, Zoo; Arteriviridae; Female; Genetic Variation; Male; Molecular Sequence Data; Monkey Diseases; Papio; Phylogeography; RNA Virus Infections; RNA, Viral; Sequence Analysis, DNA; Topography, Medical

Whole exome sequencing identifies three novel mutations in ANTXR1 in families with GAPO syndrome. - Bayram, Yavuz; Pehlivan, Davut; Karaca, Ender; Gambin, Tomasz; Jhangiani, Shalini N; Erdin, Serkan; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; Donna M Muzny; Elcioglu, Nursel H; Yildirim, M Selman; Bozkurt, Banu; et al. (Am J Med Genet A, 2014)
GAPO syndrome (OMIM#230740) is the acronym for growth retardation, alopecia, pseudoanodontia, and optic atrophy. About 35 cases have been reported, making it among one of the rarest recessive conditions. Distinctive craniofacial features including alopecia, rarefaction of eyebrows and eyelashes, frontal bossing, high forehead, mid-facial hypoplasia, hypertelorism, and thickened eyelids and lips make GAPO syndrome a clinically recognizable phenotype. While this genomic study was in progress mutations in ANTXR1 were reported to cause GAPO syndrome. In our study we performed whole exome sequencing (WES) for five affected individuals from three Turkish kindreds segregating the GAPO trait. Exome sequencing analysis identified three novel homozygous mutations including; one frame-shift (c.1220_1221insT; p.Ala408Cysfs*2), one splice site (c.411A>G; p.Gln137Gln), and one non-synonymous (c.1150G>A; p.Gly384Ser) mutation in the ANTXR1 gene. Our studies expand the allelic spectrum in this rare condition and potentially provide insight into the role of ANTXR1 in the regulation of the extracellular matrix.
Keywords: Adolescent; Adult; Alopecia; Anodontia; Base Sequence; Child; Chromosome Segregation; DNA Mutational Analysis; Exome; Facies; Family; Female; Growth Disorders; Humans; Male; Microfilament Proteins; Molecular Sequence Data; Mutation; Neoplasm Proteins; Optic Atrophies, Hereditary; Pedigree; Protein Structure, Tertiary; Receptors, Cell Surface

Whole-exome sequencing links TMCO1 defect syndrome with cerebro-facio-thoracic dysplasia. - Pehlivan, Davut; Karaca, Ender; Aydin, Hatip; Beck, Christine R; Gambin, Tomasz; Donna M Muzny; Bilge Geckinli, B; Karaman, Ali; Jhangiani, Shalini N; Richard A Gibbs; Lupski, James R (Eur J Hum Genet, 2014)
Whole-exome sequencing (WES) is a type of disruptive technology that has tremendous influence on human and clinical genetics research. An efficient and cost-effective method, WES is now widely used as a diagnostic tool for identifying the molecular basis of genetic syndromes that are often challenging to diagnose. Here we report a patient with a clinical diagnosis of cerebro-facio-thoracic dysplasia (CFTD; MIM#213980) in whom we identified a homozygous splice-site mutation in the transmembrane and coiled-coil domains 1 (TMCO1) gene using WES. TMCO1 mutations cause craniofacial dysmorphism, skeletal anomalies characterized by multiple malformations of the vertebrae and ribs, and intellectual disability (MIM#614132). A retrospective review revealed that clinical manifestations of both syndromes are very similar and overlap remarkably. We propose that mutations of TMCO1 are not only responsible for craniofacial dysmorphism, skeletal anomalies and mental retardation syndrome but also for CFTD.
Keywords: Abnormalities, Multiple; Calcium Channels; Exome; Humans; Infant; Intellectual Disability; Male; Membrane Proteins; Mutation; Protein Isoforms

Adverse outcomes in clear cell renal cell carcinoma with mutations of 3p21 epigenetic regulators BAP1 and SETD2: a report by MSKCC and the KIRC TCGA research network. - Hakimi, A Ari; Ostrovnaya, Irina; Reva, Boris; Schultz, Nikolaus; Chen, Ying-Bei; Gonen, Mithat; Liu, Han; Takeda, Shugaku; Voss, Martin H; Tickoo, Satish K; Reuter, Victor E; Russo, Paul; et al. (Clin Cancer Res, 2013)
PURPOSE: To investigate the impact of newly identified chromosome 3p21 epigenetic tumor suppressors PBRM1, SETD2, and BAP1 on cancer-specific survival (CSS) of 609 patients with clear cell renal cell carcinoma (ccRCC) from 2 distinct cohorts. EXPERIMENTAL DESIGN: Select sequencing on 3p tumor suppressors of 188 patients who underwent resection of primary ccRCC at the Memorial Sloan-Kettering Cancer Center (MSKCC) was conducted to interrogate the genotype-phenotype associations. These findings were compared with analyses of the genomic and clinical dataset from our nonoverlapping The Cancer Genome Atlas (TCGA) cohort of 421 patients with primary ccRCC. RESULTS: 3p21 tumor suppressors are frequently mutated in both the MSKCC (PBRM1, 30.3%; SETD2, 7.4%; BAP1, 6.4%) and the TCGA (PBRM1, 33.5%; SETD2, 11.6%; BAP1, 9.7%) cohorts. BAP1 mutations are associated with worse CSS in both cohorts [MSKCC, P = 0.002; HR 7.71; 95% confidence interval (CI)2.08-28.6; TCGA, P = 0.002; HR 2.21; 95% CI 1.35-3.63]. SETD2 are associated with worse CSS in the TCGA cohort (P = 0.036; HR 1.68; 95% CI 1.04-2.73). On the contrary, PBRM1 mutations, the second most common gene mutations of ccRCC, have no impact on CSS. CONCLUSION: The chromosome 3p21 locus harbors 3 frequently mutated ccRCC tumor suppressor genes. BAP1 and SETD2 mutations (6%-12%) are associated with worse CSS, suggesting their roles in disease progression. PBRM1 mutations (30%-34%) do not impact CSS, implicating its principal role in the tumor initiation. Future efforts should focus on therapeutic interventions and further clinical, pathologic, and molecular interrogation of this novel class of tumor suppressors.
Keywords: Aged; Carcinoma, Renal Cell; Cell Transformation, Neoplastic; Chromosomes, Human, Pair 3; Clinical Trials as Topic; Disease-Free Survival; DNA-Binding Proteins; Epigenesis, Genetic; Female; Gene Expression Regulation, Neoplastic; Histone-Lysine N-Methyltransferase; Humans; Kidney Neoplasms; Male; Middle Aged; Mutation; Neoplasm Staging; Nuclear Proteins; Transcription Factors; Tumor Suppressor Proteins; Ubiquitin Thiolesterase

APOE modulates the correlation between triglycerides, cholesterol, and CHD through pleiotropy, and gene-by-gene interactions. - Maxwell, Taylor J; Ballantyne, Christie M; Cheverud, James M; Guild, Cameron S; Ndumele, Chiadi E; Eric Boerwinkle (Genetics, 2013)
Relationship loci (rQTL) exist when the correlation between multiple traits varies by genotype. rQTL often occur due to gene-by-gene (G × G) or gene-by-environmental interactions, making them a powerful tool for detecting G × G. Here we present an empirical analysis of apolipoprotein E (APOE) with respect to lipid traits and incident CHD leading to the discovery of loci that interact with APOE to affect these traits. We found that the relationship between total cholesterol (TC) and triglycerides (ln TG) varies by APOE isoform genotype in African-American (AA) and European-American (EA) populations. The e2 allele is associated with strong correlation between ln TG and TC while the e4 allele leads to little or no correlation. This led to a priori hypotheses that APOE genotypes affect the relationship of TC and/or ln TG with incident CHD. We found that APOE*TC was significant (P = 0.016) for AA but not EA while APOE*ln TG was significant for EA (P = 0.027) but not AA. In both cases, e2e2 and e2e3 had strong relationships between TC and ln TG with CHD while e2e4 and e4e4 results in little or no relationship between TC and ln TG with CHD. Using ARIC GWAS data, scans for loci that significantly interact with APOE produced four loci for African Americans (one CHD, one TC, and two HDL). These interactions contribute to the rQTL pattern. rQTL are a powerful tool to identify loci that modify the relationship between risk factors and disease and substantially increase statistical power for detecting G × G.
Keywords: Alleles; Apolipoproteins E; Black or African American; Cholesterol; Coronary Disease; Epistasis, Genetic; Female; Genetic Pleiotropy; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Triglycerides; White People

Association of genome-wide variation with highly sensitive cardiac troponin-T levels in European Americans and Blacks: a meta-analysis from atherosclerosis risk in communities and cardiovascular health studies. - Yu, Bing; Barbalic, Maja; Brautbar, Ariel; Nambi, Vijay; Hoogeveen, Ron C; Tang, Weihong; Mosley, Thomas H; Rotter, Jerome I; deFilippi, Christopher R; O'Donnell, Christopher J; Kathiresan, Sekar; Rice, Ken; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND: High levels of cardiac troponin T, measured by a highly sensitive assay (hs-cTnT), are strongly associated with incident coronary heart disease and heart failure. To date, no large-scale genome-wide association study of hs-cTnT has been reported. We sought to identify novel genetic variants that are associated with hs-cTnT levels. METHODS AND RESULTS: We performed a genome-wide association in 9491 European Americans and 2053 blacks free of coronary heart disease and heart failure from 2 prospective cohorts: the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. Genome-wide association studies were conducted in each study and race stratum. Fixed-effect meta-analyses combined the results of linear regression from 2 cohorts within each race stratum and then across race strata to produce overall estimates and probability values. The meta-analysis identified a significant association at chromosome 8q13 (rs10091374; P=9.06×10(-9)) near the nuclear receptor coactivator 2 (NCOA2) gene. Overexpression of NCOA2 can be detected in myoblasts. An additional analysis using logistic regression and the clinically motivated 99th percentile cut point detected a significant association at 1q32 (rs12564445; P=4.73×10(-8)) in the gene TNNT2, which encodes the cardiac troponin T protein itself. The hs-cTnT-associated single-nucleotide polymorphisms were not associated with coronary heart disease in a large case-control study, but rs12564445 was significantly associated with incident heart failure in Atherosclerosis Risk in Communities Study European Americans (hazard ratio=1.16; P=0.004). CONCLUSIONS: We identified 2 loci, near NCOA2 and in the TNNT2 gene, at which variation was significantly associated with hs-cTnT levels. Further use of the new assay should enable replication of these results.
Keywords: Atherosclerosis; Black People; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Nuclear Receptor Coactivator 2; Polymorphism, Single Nucleotide; Prospective Studies; Residence Characteristics; Risk Factors; Troponin T; White People

Associations between metabolomic compounds and incident heart failure among African Americans: the ARIC Study. - Zheng, Yan; Yu, Bing; Alexander, Danny; Manolio, Teri A; Aguilar, David; Coresh, Josef; Heiss, Gerardo; Eric Boerwinkle; Nettleton, Jennifer A (Am J Epidemiol, 2013)
Heart failure is more prevalent among African Americans than in the general population. Metabolomic studies among African Americans may efficiently identify novel biomarkers of heart failure. We used untargeted methods to measure 204 stable serum metabolites and evaluated their associations with incident heart failure hospitalization (n = 276) after a median follow-up of 20 years (1987-2008) by using Cox regression in data from 1,744 African Americans aged 45-64 years without heart failure at baseline from the Jackson, Mississippi, field center of the Atherosclerosis Risk in Communities (ARIC) Study. After adjustment for established risk factors, we found that 16 metabolites (6 named with known structural identities and 10 unnamed with unknown structural identities, the latter denoted by using the format X-12345) were associated with incident heart failure (P < 0.0004 based on a modified Bonferroni procedure). Of the 6 named metabolites, 4 are involved in amino acid metabolism, 1 (prolylhydroxyproline) is a dipeptide, and 1 (erythritol) is a sugar alcohol. After additional adjustment for kidney function, 2 metabolites remained associated with incident heart failure (for metabolite X-11308, hazard ratio = 0.75, 95% confidence interval: 0.65, 0.86; for metabolite X-11787, hazard ratio = 1.23, 95% confidence interval: 1.10, 1.37). Further structural analysis revealed X-11308 to be a dihydroxy docosatrienoic acid and X-11787 to be an isoform of either hydroxyleucine or hydroxyisoleucine. Our metabolomic analysis revealed novel biomarkers associated with incident heart failure independent of traditional risk factors.
Keywords: Age Distribution; Atherosclerosis; Biomarkers; Black or African American; Comorbidity; Diabetes Mellitus; Female; Follow-Up Studies; Heart Failure; Humans; Hypertension; Kidney Diseases; Male; Metabolomics; Middle Aged; Mississippi; Obesity; Proportional Hazards Models; Sedentary Behavior

Best practices and joint calling of the HumanExome BeadChip: the CHARGE Consortium. - Grove, Megan L; Yu, Bing; Cochran, Barbara J; Haritunians, Talin; Bis, Joshua C; Taylor, Kent D; Hansen, Mark; Borecki, Ingrid B; Cupples, L Adrienne; Fornage, Myriam; Gudnason, Vilmundur; Harris, Tamara B; et al. (PLoS One, 2013)
Genotyping arrays are a cost effective approach when typing previously-identified genetic polymorphisms in large numbers of samples. One limitation of genotyping arrays with rare variants (e.g., minor allele frequency [MAF] <0.01) is the difficulty that automated clustering algorithms have to accurately detect and assign genotype calls. Combining intensity data from large numbers of samples may increase the ability to accurately call the genotypes of rare variants. Approximately 62,000 ethnically diverse samples from eleven Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium cohorts were genotyped with the Illumina HumanExome BeadChip across seven genotyping centers. The raw data files for the samples were assembled into a single project for joint calling. To assess the quality of the joint calling, concordance of genotypes in a subset of individuals having both exome chip and exome sequence data was analyzed. After exclusion of low performing SNPs on the exome chip and non-overlap of SNPs derived from sequence data, genotypes of 185,119 variants (11,356 were monomorphic) were compared in 530 individuals that had whole exome sequence data. A total of 98,113,070 pairs of genotypes were tested and 99.77% were concordant, 0.14% had missing data, and 0.09% were discordant. We report that joint calling allows the ability to accurately genotype rare variation using array technology when large sample sizes are available and best practices are followed. The cluster file from this experiment is available at www.chargeconsortium.com/main/exomechip.
Keywords: Aging; Alleles; Cluster Analysis; Cohort Studies; Exome; Female; Gene Frequency; Genomics; Genotype; Heart; Humans; Male; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Racial Groups; Sample Size; Self Report; Sequence Analysis, DNA

Bioactivity and bioavailability of ginsenosides are dependent on the glycosidase activities of the A/J mouse intestinal microbiome defined by pyrosequencing. - Niu, Tao; Smith, Diane L; Yang, Zhen; Gao, Song; Yin, Taijun; Jiang, Zhi-Hong; You, Ming; Richard A Gibbs; Petrosino, Joseph F; Hu, Ming (Pharm Res, 2013)
PURPOSE: To investigate the ability of bacteria in the intestinal microbiome to convert naturally occurring primary ginsenosides in red ginseng extract to active secondary ginsenosides. METHODS: Anti-proliferative ginsenoside activity was tested using mouse lung cancer LM1 cells. Permeabilities were evaluated in Caco-2 cell monolayers. Systemic exposure of secondary ginsenosides was determined in A/J mice. 16S rRNA gene pyrosequencing was used to determine membership and abundance of bacteria in intestinal microbiome. RESULTS: Secondary ginsenoside C-K exhibited higher anti-proliferative activity and permeability than primary ginsenosides. Significant amounts of secondary ginsenosides (F2 and C-K) were found in blood of A/J mice following oral administration of primary ginsenoside Rb1. Because mammalian cells did not hydrolyze ginsenoside, we determined the ability of bacteria to hydrolyze ginsenosides and found that Rb1 underwent stepwise hydrolysis to Rd, F2, and then C-K. Formation of F2 from Rd was the rate-limiting step in the biotransformation of Rb1 to C-K. CONCLUSION: Conversion to F2 is the rate-limiting step in bioactivation of primary ginsenosides by A/J mouse intestinal microbiome, whose characterization reveals the presence of certain bacterial families capable of enabling the formation of F2 and C-K in vivo.
Keywords: Animals; Antineoplastic Agents, Phytogenic; Bacteria; Biological Availability; Biotransformation; Caco-2 Cells; Cell Line, Tumor; Cell Proliferation; Drugs, Chinese Herbal; Ginsenosides; Glycoside Hydrolases; Humans; Hydrolysis; Intestinal Mucosa; Intestines; Male; Metagenome; Mice; Neoplasms; Panax; RNA, Bacterial

CRHR1 genotypes, neural circuits and the diathesis for anxiety and depression. - Rogers, J; Raveendran, M; Fawcett, G L; Fox, A S; Shelton, S E; Oler, J A; Cheverud, J; Donna M Muzny; Richard A Gibbs; Davidson, R J; Kalin, N H (Mol Psychiatry, 2013)
The corticotrophin-releasing hormone (CRH) system integrates the stress response and is associated with stress-related psychopathology. Previous reports have identified interactions between childhood trauma and sequence variation in the CRH receptor 1 gene (CRHR1) that increase risk for affective disorders. However, the underlying mechanisms that connect variation in CRHR1 to psychopathology are unknown. To explore potential mechanisms, we used a validated rhesus macaque model to investigate association between genetic variation in CRHR1, anxious temperament (AT) and brain metabolic activity. In young rhesus monkeys, AT is analogous to the childhood risk phenotype that predicts the development of human anxiety and depressive disorders. Regional brain metabolism was assessed with (18)F-labeled fluoro-2-deoxyglucose (FDG) positron emission tomography in 236 young, normally reared macaques that were also characterized for AT. We show that single nucleotide polymorphisms (SNPs) affecting exon 6 of CRHR1 influence both AT and metabolic activity in the anterior hippocampus and amygdala, components of the neural circuit underlying AT. We also find evidence for association between SNPs in CRHR1 and metabolism in the intraparietal sulcus and precuneus. These translational data suggest that genetic variation in CRHR1 affects the risk for affective disorders by influencing the function of the neural circuit underlying AT and that differences in gene expression or the protein sequence involving exon 6 may be important. These results suggest that variation in CRHR1 may influence brain function before any childhood adversity and may be a diathesis for the interaction between CRHR1 genotypes and childhood trauma reported to affect human psychopathology.
Keywords: Animals; Anxiety; Brain; Depression; Disease Models, Animal; Female; Fluorodeoxyglucose F18; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Macaca mulatta; Male; Polymorphism, Single Nucleotide; Positron-Emission Tomography; Receptors, Corticotropin-Releasing Hormone

Deep resequencing and association analysis of schizophrenia candidate genes. - Crowley, J J; Hilliard, C E; Kim, Y; Morgan, M B; Lewis, L R; Donna M Muzny; Hawes, A C; Aniko Sabo; Wheeler, D A; Lieberman, J A; Sullivan, P F; Richard A Gibbs (Mol Psychiatry, 2013)
Keywords: Adolescent; Adult; Aged; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Schizophrenia; Young Adult

Exome sequencing of a patient with suspected mitochondrial disease reveals a likely multigenic etiology. - Craigen, William J; Graham, Brett H; Wong, Lee-Jun; Scaglia, Fernando; Lewis, Richard Alan; Bonnen, Penelope E (BMC Med Genet, 2013)
BACKGROUND: The clinical features of mitochondrial disease are complex and highly variable, leading to challenges in establishing a specific diagnosis. Despite being one of the most commonly occurring inherited genetic diseases with an incidence of 1/5000, ~90% of these complex patients remain without a DNA-based diagnosis. We report our efforts to identify the pathogenetic cause for a patient with typical features of mitochondrial disease including infantile cataracts, CPEO, ptosis, progressive distal muscle weakness, and ataxia who carried a diagnosis of mitochondrial disease for over a decade. METHODS: Whole exome sequencing and bioinformatic analysis of these data were conducted on the proband. RESULTS: Exome sequencing studies showed a homozygous splice site mutation in SETX, which is known to cause Spinocerebellar Ataxia, Autosomal Recessive 1 (SCAR1). Additionally a missense mutation was identified in a highly conserved position of the OCRL gene, which causes Lowe Syndrome and Dent Disease 2. CONCLUSIONS: This patient's complex phenotype reflects a complex genetic etiology in which no single gene explained the complete clinical presentation. These genetic studies reveal that this patient does not have mitochondrial disease but rather a genocopy caused by more than one mutant locus. This study demonstrates the benefit of exome sequencing in providing molecular diagnosis to individuals with complex clinical presentations.
Keywords: Adult; Computational Biology; DNA Helicases; Exome; Genetic Diseases, X-Linked; Genetic Loci; Homozygote; Humans; Male; Mitochondrial Diseases; Multifunctional Enzymes; Mutation, Missense; Nephrolithiasis; Oculocerebrorenal Syndrome; Pedigree; Phenotype; Phosphoric Monoester Hydrolases; RNA Helicases; RNA, Ribosomal, 16S; Sequence Analysis, DNA; Spinocerebellar Ataxias; Spinocerebellar Degenerations

Exploring the utility of whole-exome sequencing as a diagnostic tool in a child with atypical episodic muscle weakness. - Hanchard, Neil A; David R Murdock; Magoulas, Pilar L; Matthew N Bainbridge; Donna M Muzny; Wu, Yuanqing; Wang, Min; James R Lupski; Richard A Gibbs; Brown, Chester W (Clin Genet, 2013)
The advent of whole-exome next-generation sequencing (WES) has been pivotal for the molecular characterization of Mendelian disease; however, the clinical applicability of WES has remained relatively unexplored. We describe our exploration of WES as a diagnostic tool in a 3½-year old female patient with a 2-year history of episodic muscle weakness and paroxysmal dystonia who presented following a previous extensive but unrevealing diagnostic work-up. WES was performed on the proband and her two parents. Parental exome data was used to filter potential de novo genomic events in the proband and suspected variants were confirmed using di-deoxy sequencing. WES revealed a de novo non-synonymous mutation in exon 21 of the calcium channel gene CACNA1S that has been previously reported in a single patient as a rare cause of atypical hypokalemic periodic paralysis. This was unexpected, as the proband's original differential diagnosis had included hypokalemic periodic paralysis, but clinical and laboratory features were equivocal, and standard clinical molecular testing for hypokalemic periodic paralysis and related disorders was negative. This report highlights the potential diagnostic utility of WES in clinical practice, with implications for the approach to similar diagnostic dilemmas in the future.
Keywords: Base Sequence; Calcium Channels; Child, Preschool; Exome; Exons; Female; Genotype; High-Throughput Nucleotide Sequencing; Humans; Male; Muscle Weakness; Mutation; NAV1.4 Voltage-Gated Sodium Channel; Pedigree; Phenotype

Fat mass and obesity gene and cognitive decline: the Atherosclerosis Risk in Communities Study. - Bressler, Jan; Fornage, Myriam; Demerath, Ellen W; Knopman, David S; Monda, Keri L; North, Kari E; Penman, Alan; Mosley, Thomas H; Eric Boerwinkle (Neurology, 2013)
OBJECTIVE: To determine whether 4 genetic variants in the fat mass and obesity associated gene (FTO) identified in genome-wide association studies of diabetes and obesity are associated with cognitive change in midlife in the Atherosclerosis Risk in Communities (ARIC) Study. METHODS: ARIC is a prospective cohort study of the development of atherosclerosis in 15,792 individuals aged 45 to 64 years at baseline from 1986 to 1989. FTO is highly expressed in human fetal and adult brain, and a single nucleotide polymorphism in FTO has previously been associated with reduced brain volume in cognitively normal subjects. Since a relationship between brain atrophy and diminished cognitive function has been demonstrated in ARIC participants, general linear models were used to evaluate the association between 6-year change in scores on 3 neuropsychological tests and FTO genotype. RESULTS: In a sample of 8,364 white and 2,083 African American men and women with no clinical history of stroke, significantly greater mean change in performance on the Delayed Word Recall Test was associated with 2 of 4 FTO single nucleotide polymorphisms examined (rs9939609, rs805136, rs17817449, and rs1421085) in whites but not in African Americans (p ≤ 0.002). The association of the FTO polymorphisms with cognitive change was independent of potential confounding clinical and demographic variables including age, gender, education, diabetes, hypertension, and body mass index. CONCLUSIONS: Further studies will be needed to clarify the biological mechanisms and genetic pathways through which variants in FTO can increase susceptibility to decline in verbal memory detectable in middle-aged, community-dwelling adults.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Black or African American; Body Mass Index; Cognition Disorders; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Prospective Studies; Proteins; White People

A genome-wide association study for venous thromboembolism: the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) consortium. - Tang, Weihong; Teichert, Martina; Chasman, Daniel I; Heit, John A; Morange, Pierre-Emmanuel; Li, Guo; Pankratz, Nathan; Leebeek, Frank W; Paré, Guillaume; de Andrade, Mariza; Tzourio, Christophe; Psaty, Bruce M; et al. (Genet Epidemiol, 2013)
Venous thromboembolism (VTE) is a common, heritable disease resulting in high rates of hospitalization and mortality. Yet few associations between VTE and genetic variants, all in the coagulation pathway, have been established. To identify additional genetic determinants of VTE, we conducted a two-stage genome-wide association study (GWAS) among individuals of European ancestry in the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) VTE consortium. The discovery GWAS comprised 1,618 incident VTE cases out of 44,499 participants from six community-based studies. Genotypes for genome-wide single-nucleotide polymorphisms (SNPs) were imputed to approximately 2.5 million SNPs in HapMap and association with VTE assessed using study-design appropriate regression methods. Meta-analysis of these results identified two known loci, in F5 and ABO. Top 1,047 tag SNPs (P ≤ 0.0016) from the discovery GWAS were tested for association in an additional 3,231 cases and 3,536 controls from three case-control studies. In the combined data from these two stages, additional genome-wide significant associations were observed on 4q35 at F11 (top SNP rs4253399, intronic to F11) and on 4q28 at FGG (rs6536024, 9.7 kb from FGG; P < 5.0 × 10(-13) for both). The associations at the FGG locus were not completely explained by previously reported variants. Loci at or near SUSD1 and OTUD7A showed borderline yet novel associations (P < 5.0 × 10(-6) ) and constitute new candidate genes. In conclusion, this large GWAS replicated key genetic associations in F5 and ABO, and confirmed the importance of F11 and FGG loci for VTE. Future studies are warranted to better characterize the associations with F11 and FGG and to replicate the new candidate associations.
Keywords: Aged; Aging; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; Venous Thromboembolism

Genome-wide association study of a heart failure related metabolomic profile among African Americans in the Atherosclerosis Risk in Communities (ARIC) study. - Yu, Bing; Zheng, Yan; Alexander, Danny; Manolio, Teri A; Alonso, Alvaro; Nettleton, Jennifer A; Eric Boerwinkle (Genet Epidemiol, 2013)
Both the prevalence and incidence of heart failure (HF) are increasing, especially among African Americans, but no large-scale, genome-wide association study (GWAS) of HF-related metabolites has been reported. We sought to identify novel genetic variants that are associated with metabolites previously reported to relate to HF incidence. GWASs of three metabolites identified previously as risk factors for incident HF (pyroglutamine, dihydroxy docosatrienoic acid, and X-11787, being either hydroxy-leucine or hydroxy-isoleucine) were performed in 1,260 African Americans free of HF at the baseline examination of the Atherosclerosis Risk in Communities (ARIC) study. A significant association on chromosome 5q33 (rs10463316, MAF = 0.358, P-value = 1.92 × 10(-10) ) was identified for pyroglutamine. One region on chromosome 2p13 contained a nonsynonymous substitution in N-acetyltransferase 8 (NAT8) was associated with X-11787 (rs13538, MAF = 0.481, P-value = 1.71 × 10(-23) ). The smallest P-value for dihydroxy docosatrienoic acid was rs4006531 on chromosome 8q24 (MAF = 0.400, P-value = 6.98 × 10(-7) ). None of the above SNPs were individually associated with incident HF, but a genetic risk score (GRS) created by summing the most significant risk alleles from each metabolite detected 11% greater risk of HF per allele. In summary, we identified three loci associated with previously reported HF-related metabolites. Further use of metabolomics technology will facilitate replication of these findings in independent samples.
Keywords: Acetyltransferases; Alleles; Atherosclerosis; Black or African American; Chromosomes, Human, Pair 2; Chromosomes, Human, Pair 5; Cohort Studies; Fatty Acids, Unsaturated; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Failure; Humans; Incidence; Isoleucine; Leucine; Male; Metabolome; Metabolomics; Middle Aged; Polymorphism, Single Nucleotide; Pyrrolidonecarboxylic Acid; Risk Factors

Identification of TP53 as an acute lymphocytic leukemia susceptibility gene through exome sequencing. - Powell, Bradford C; Jiang, Lichun; Donna M Muzny; Treviño, Lisa R; Dreyer, Zoann E; Strong, Louise C; Wheeler, David A; Richard A Gibbs; Plon, Sharon E (Pediatr Blood Cancer, 2013)
Although acute lymphocytic leukemia (ALL) is the most common childhood cancer, genetic predisposition to ALL remains poorly understood. Whole-exome sequencing was performed in an extended kindred in which five individuals had been diagnosed with leukemia. Analysis revealed a nonsense variant of TP53 which has been previously reported in families with sarcomas and other typical Li Fraumeni syndrome-associated cancers but never in a familial leukemia kindred. This unexpected finding enabled identification of an appropriate sibling bone marrow donor and illustrates that exome sequencing will reveal atypical clinical presentations of even well-studied genes.
Keywords: Exome; Female; Genetic Predisposition to Disease; Humans; Male; Pedigree; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Tumor Suppressor Protein p53

Incidental copy-number variants identified by routine genome testing in a clinical population. - Boone, Philip M; Soens, Zachry T; Campbell, Ian M; Stankiewicz, Pawel; Cheung, Sau Wai; Patel, Ankita; Beaudet, Arthur L; Plon, Sharon E; Shaw, Chad A; McGuire, Amy L; Lupski, James R (Genet Med, 2013)
PURPOSE: Mutational load of susceptibility variants has not been studied on a genomic scale in a clinical population, nor has the potential to identify these mutations as incidental findings during clinical testing been systematically ascertained. METHODS: Array comparative genomic hybridization, a method for genome-wide detection of DNA copy-number variants, was performed clinically on DNA from 9,005 individuals. Copy-number variants encompassing or disrupting single genes were identified and analyzed for their potential to confer predisposition to dominant, adult-onset disease. Multigene copy-number variants affecting dominant, adult-onset cancer syndrome genes were also assessed. RESULTS: In our cohort, 83 single-gene copy-number variants affected 40 unique genes associated with dominant, adult-onset disorders and unrelated to the patients' referring diagnoses (i.e., incidental) were found. Fourteen of these copy-number variants are likely disease-predisposing, 25 are likely benign, and 44 are of unknown clinical consequence. When incidental copy-number variants spanning up to 20 genes were considered, 27 copy-number variants affected 17 unique genes associated with dominant, adult-onset cancer predisposition. CONCLUSION: Copy-number variants potentially conferring susceptibility to adult-onset disease can be identified as incidental findings during routine genome-wide testing. Some of these mutations may be medically actionable, enabling disease surveillance or prevention; however, most incidentally observed single-gene copy-number variants are currently of unclear significance to the patient.
Keywords: Age of Onset; Base Sequence; Chromosome Mapping; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Order; Genetic Predisposition to Disease; Humans; Inheritance Patterns; Male; Reproducibility of Results

Longitudinal study shows increasing obesity and hyperglycemia in micronesia. - Murdock, David; Salit, Jacqueline; Stoffel, Markus; Friedman, Jeffrey M; Pe'er, Itsik; Breslow, Jan L; Bonnen, Penelope E (Obesity (Silver Spring), 2013)
OBJECTIVE: Obesity and diabetes are particularly high in indigenous populations exposed to a Western diet and lifestyle. The prevalence of obesity, diabetes, hyperglycemia, dyslipidemia, and hypertension in one such population, the Micronesian island of Kosrae was described. DESIGN AND METHODS: Longitudinal screenings for metabolic traits were conducted on adult Kosraens ≥ 20 years of age in 1994 and again in 2001. Data was obtained on 3,106 Kosraens, comprising ∼80% of the adult population. Diabetes was diagnosed using World Health Organization guidelines. Prevalences of obesity, hyperglycemia, dyslipidemia, and hypertension were assessed. RESULTS: The overall age-adjusted prevalence of diabetes increased from 14 to 21%. The most significant change observed in the population was increases in obesity and hyperglycemia, especially among young Kosraens and women. Obesity age-adjusted prevalence increased from 45 to 62%, and hyperglycemia age-adjusted prevalence increased from 19 to 44%. Of note, Kosraens as a group had unusually low high density lipoprotein (HDL) levels with 80% classified as low HDL by NCEP-ATPIII criteria, despite lacking the usually accompanying increase in triglycerides. Comparison to reports from other populations shows that Kosrae experiences one of the highest rates of obesity, hyperglycemia, and low HDL globally while maintaining relatively healthy levels of triglycerides. CONCLUSION: Our study shows a dramatic increase in obesity and hyperglycemia in Kosrae in just 7 years and forebodes significantly increased health risks for this part of the world.
Keywords: Adult; Aged; Cholesterol, HDL; Diabetes Mellitus; Dyslipidemias; Female; Humans; Hyperglycemia; Hypertension; Longitudinal Studies; Male; Micronesia; Middle Aged; Obesity; Prevalence; Sex Factors; Triglycerides; Young Adult

Metabolomics and incident hypertension among blacks: the atherosclerosis risk in communities study. - Zheng, Yan; Yu, Bing; Alexander, Danny; Mosley, Thomas H; Heiss, Gerardo; Nettleton, Jennifer A; Eric Boerwinkle (Hypertension, 2013)
Development of hypertension is influenced by genes, environmental effects, and their interactions, and the human metabolome is a measurable manifestation of gene-environment interaction. We explored the metabolomic antecedents of developing incident hypertension in a sample of blacks, a population with a high prevalence of hypertension and its comorbidities. We examined 896 black normotensives (565 women; aged, 45-64 years) from the Atherosclerosis Risk in Communities study, whose metabolome was measured in serum collected at the baseline examination and analyzed by high-throughput methods. The analyses presented here focus on 204 stably measured metabolites during a period of 4 to 6 weeks. Weibull parametric models considering interval censored data were used to assess the hazard ratio for incident hypertension. We used a modified Bonferroni correction accounting for the correlations among metabolites to define a threshold for statistical significance (P<3.9 × 10(-4)). During 10 years of follow-up, 38% of baseline normotensives developed hypertension (n=344). With adjustment for traditional risk factors and estimated glomerular filtration rate, each +1SD difference in baseline 4-hydroxyhippurate, a product of gut microbial fermentation, was associated with 17% higher risk of hypertension (P=2.5 × 10(-4)), which remained significant after adjusting for both baseline systolic and diastolic blood pressure (P=3.8 × 10(-4)). After principal component analyses, a sex steroids pattern was significantly associated with risk of incident hypertension (highest versus lowest quintile hazard ratio, 1.72; 95% confidence interval, 1.05-2.82; P for trend, 0.03), and stratified analyses suggested that this association was consistent in both sexes. Metabolomic analyses identify novel pathways in the pathogenesis of hypertension.
Keywords: Atherosclerosis; Black People; Female; High-Throughput Screening Assays; Humans; Hypertension; Male; Metabolomics; Middle Aged; Principal Component Analysis; Risk Factors

Metagenomic analyses of alcohol induced pathogenic alterations in the intestinal microbiome and the effect of Lactobacillus rhamnosus GG treatment. - Bull-Otterson, Lara; Feng, Wenke; Kirpich, Irina; Wang, Yuhua; Qin, Xiang; Liu, Yanlong; Gobejishvili, Leila; Joshi-Barve, Swati; Ayvaz, Tulin; Petrosino, Joseph; Kong, Maiying; Barker, David; et al. (PLoS One, 2013)
Enteric dysbiosis plays an essential role in the pathogenesis of alcoholic liver disease (ALD). Detailed characterization of the alterations in the gut microbiome is needed for understanding their pathogenic role in ALD and developing effective therapeutic approaches using probiotic supplementation. Mice were fed liquid Lieber-DeCarli diet without or with alcohol (5% v/v) for 6 weeks. A subset of mice were administered the probiotic Lactobacillus rhamnosus GG (LGG) from 6 to 8 weeks. Indicators of intestinal permeability, hepatic steatosis, inflammation and injury were evaluated. Metagenomic analysis of the gut microbiome was performed by analyzing the fecal DNA by amplification of the V3-V5 regions of the 16S rRNA gene and large-scale parallel pyrosequencing on the 454 FLX Titanium platform. Chronic ethanol feeding caused a decline in the abundance of both Bacteriodetes and Firmicutes phyla, with a proportional increase in the gram negative Proteobacteria and gram positive Actinobacteria phyla; the bacterial genera that showed the biggest expansion were the gram negative alkaline tolerant Alcaligenes and gram positive Corynebacterium. Commensurate with the qualitative and quantitative alterations in the microbiome, ethanol caused an increase in plasma endotoxin, fecal pH, hepatic inflammation and injury. Notably, the ethanol-induced pathogenic changes in the microbiome and the liver were prevented by LGG supplementation. Overall, significant alterations in the gut microbiome over time occur in response to chronic alcohol exposure and correspond to increases in intestinal barrier dysfunction and development of ALD. Moreover, the altered bacterial communities of the gut may serve as significant therapeutic target for the prevention/treatment of chronic alcohol intake induced intestinal barrier dysfunction and liver disease.
Keywords: Animals; Anti-Infective Agents, Local; Bacteria; Biodiversity; Claudin-1; Ethanol; Feces; Gene Expression; Genetic Variation; Hydrogen-Ion Concentration; Intestinal Mucosa; Intestines; Lacticaseibacillus rhamnosus; Liver Diseases, Alcoholic; Male; Metagenome; Metagenomics; Mice; Mice, Inbred C57BL; Probiotics; Reverse Transcriptase Polymerase Chain Reaction; RNA, Ribosomal, 16S; Sequence Analysis, DNA; Species Specificity; Zonula Occludens-1 Protein

Mutations in FBXL4 cause mitochondrial encephalopathy and a disorder of mitochondrial DNA maintenance. - Bonnen, Penelope E; Yarham, John W; Besse, Arnaud; Wu, Ping; Faqeih, Eissa A; Al-Asmari, Ali Mohammad; Saleh, Mohammad A M; Eyaid, Wafaa; Hadeel, Alrukban; He, Langping; Smith, Frances; Yau, Shu; et al. (Am J Hum Genet, 2013)
Nuclear genetic disorders causing mitochondrial DNA (mtDNA) depletion are clinically and genetically heterogeneous, and the molecular etiology remains undiagnosed in the majority of cases. Through whole-exome sequencing, we identified recessive nonsense and splicing mutations in FBXL4 segregating in three unrelated consanguineous kindreds in which affected children present with a fatal encephalopathy, lactic acidosis, and severe mtDNA depletion in muscle. We show that FBXL4 is an F-box protein that colocalizes with mitochondria and that loss-of-function and splice mutations in this protein result in a severe respiratory chain deficiency, loss of mitochondrial membrane potential, and a disturbance of the dynamic mitochondrial network and nucleoid distribution in fibroblasts from affected individuals. Expression of the wild-type FBXL4 transcript in cell lines from two subjects fully rescued the levels of mtDNA copy number, leading to a correction of the mitochondrial biochemical deficit. Together our data demonstrate that mutations in FBXL4 are disease causing and establish FBXL4 as a mitochondrial protein with a possible role in maintaining mtDNA integrity and stability.
Keywords: Acidosis, Lactic; Base Sequence; Child; Child, Preschool; Chromosome Segregation; DNA, Mitochondrial; Electron Transport; F-Box Proteins; Female; Fibroblasts; Gene Dosage; Genes, Recessive; Genetic Predisposition to Disease; Humans; Infant; Infant, Newborn; Male; Mitochondrial Encephalomyopathies; Molecular Sequence Data; Muscle, Skeletal; Mutation; Oxidative Phosphorylation; Pedigree; Protein Transport; Ubiquitin-Protein Ligases

Mutations in KCTD1 cause scalp-ear-nipple syndrome. - Marneros, Alexander G; Beck, Anita E; Turner, Emily H; McMillin, Margaret J; Edwards, Matthew J; Field, Michael; de Macena Sobreira, Nara Lygia; Perez, Ana Beatriz A; Fortes, Jose A R; Lampe, Anne K; Giovannucci Uzielli, Maria Luisa; Gordon, Christopher T; et al. (Am J Hum Genet, 2013)
Scalp-ear-nipple (SEN) syndrome is a rare, autosomal-dominant disorder characterized by cutis aplasia of the scalp; minor anomalies of the external ears, digits, and nails; and malformations of the breast. We used linkage analysis and exome sequencing of a multiplex family affected by SEN syndrome to identify potassium-channel tetramerization-domain-containing 1 (KCTD1) mutations that cause SEN syndrome. Evaluation of a total of ten families affected by SEN syndrome revealed KCTD1 missense mutations in each family tested. All of the mutations occurred in a KCTD1 region encoding a highly conserved bric-a-brac, tram track, and broad complex (BTB) domain that is required for transcriptional repressor activity. KCTD1 inhibits the transactivation of the transcription factor AP-2α (TFAP2A) via its BTB domain, and mutations in TFAP2A cause cutis aplasia in individuals with branchiooculofacial syndrome (BOFS), suggesting a potential overlap in the pathogenesis of SEN syndrome and BOFS. The identification of KCTD1 mutations in SEN syndrome reveals a role for this BTB-domain-containing transcriptional repressor during ectodermal development.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Branchio-Oto-Renal Syndrome; Co-Repressor Proteins; Ear, External; Ectodermal Dysplasia; Exome; Female; Humans; Hypospadias; Male; Molecular Sequence Data; Muscle Hypotonia; Mutation, Missense; Nipples; Pedigree; Phenotype; Protein Structure, Tertiary; Repressor Proteins; Scalp; Sequence Homology, Amino Acid

Mutations in VRK1 associated with complex motor and sensory axonal neuropathy plus microcephaly. - Gonzaga-Jauregui, Claudia; Lotze, Timothy; Jamal, Leila; Penney, Samantha; Campbell, Ian M; Pehlivan, Davut; Hunter, Jill V; Woodbury, Suzanne L; Raymond, Gerald; Adesina, Adekunle M; Jhangiani, Shalini N; Reid, Jeffrey G; et al. (JAMA Neurol, 2013)
IMPORTANCE: Patients with rare diseases and complex clinical presentations represent a challenge for clinical diagnostics. Genomic approaches are allowing the identification of novel variants in genes for very rare disorders, enabling a molecular diagnosis. Genomics is also revealing a phenotypic expansion whereby the full spectrum of clinical expression conveyed by mutant alleles at a locus can be better appreciated. OBJECTIVE: To elucidate the molecular cause of a complex neuropathy phenotype in 3 patients by applying genomic sequencing strategies. DESIGN, SETTING, AND PARTICIPANTS: Three affected individuals from 2 unrelated families presented with a complex neuropathy phenotype characterized by axonal sensorimotor neuropathy and microcephaly. They were recruited into the Centers for Mendelian Genomics research program to identify the molecular cause of their phenotype. Whole-genome, targeted whole-exome sequencing, and high-resolution single-nucleotide polymorphism arrays were performed in genetics clinics of tertiary care pediatric hospitals and biomedical research institutions. MAIN OUTCOMES AND MEASURES: Whole-genome and whole-exome sequencing identified the variants responsible for the patients' clinical phenotype. RESULTS: We identified compound heterozygous alleles in 2 affected siblings from 1 family and a homozygous nonsense variant in the third unrelated patient in the vaccinia-related kinase 1 gene (VRK1). In the latter subject, we found a common haplotype on which the nonsense mutation occurred and that segregates in the Ashkenazi Jewish population. CONCLUSIONS AND RELEVANCE: We report the identification of disease-causing alleles in 3 children from 2 unrelated families with a previously uncharacterized complex axonal motor and sensory neuropathy accompanied by severe nonprogressive microcephaly and cerebral dysgenesis. Our data raise the question of whether VRK1 mutations disturb cell cycle progression and may result in apoptosis of cells in the nervous system. The application of unbiased genomic approaches allows the identification of potentially pathogenic mutations in unsuspected genes in highly genetically heterogeneous and uncharacterized neurological diseases.
Keywords: Child; Child, Preschool; DNA Mutational Analysis; Female; Genotype; Hereditary Sensory and Motor Neuropathy; Humans; Infant; Intracellular Signaling Peptides and Proteins; Magnetic Resonance Imaging; Male; Microcephaly; Mutation; Neural Conduction; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases

Next-generation sequencing-based molecular diagnosis of a Chinese patient cohort with autosomal recessive retinitis pigmentosa. - Fu, Qing; Wang, Feng; Wang, Hui; Xu, Fei; Zaneveld, Jacques E; Ren, Huanan; Keser, Vafa; Lopez, Irma; Tuan, Han-Fang; Salvo, Jason S; Wang, Xia; Zhao, Li; et al. (Invest Ophthalmol Vis Sci, 2013)
PURPOSE: Retinitis pigmentosa (RP) is a highly heterogeneous genetic disease; therefore, an accurate molecular diagnosis is essential for appropriate disease treatment and family planning. The prevalence of RP in China had been reported at 1 in 3800, resulting in an estimated total of 340,000 Chinese RP patients. However, genetic studies of Chinese RP patients have been very limited. To date, no comprehensive molecular diagnosis has been done for Chinese RP patients. With the emergence of next-generation sequencing (NGS), comprehensive molecular diagnosis of RP is now within reach. The purpose of this study was to perform the first NGS-based comprehensive molecular diagnosis for Chinese RP patients. METHODS: Thirty-one well-characterized autosomal recessive RP (arRP) families were recruited. For each family, the DNA sample from one affected member was sequenced using our custom capture panel, which includes 163 retinal disease genes. Variants were called, filtered, and annotated by our in-house automatic pipeline. RESULTS: Twelve arRP families were successfully molecular diagnosed, achieving a diagnostic rate of approximately 40%. Interestingly, approximately 63% of the pathogenic mutations we identified are novel, which is higher than that observed in a similar study on European descent (45%). Moreover, the clinical diagnoses of two families were refined based on the pathogenic mutations identified in the patients. CONCLUSIONS: We conclude that comprehensive molecular diagnosis can be vital for an accurate clinical diagnosis of RP. Applying this tool on patients from different ethnic groups is essential for enhancing our knowledge of the global spectrum of RP disease-causing mutations.
Keywords: Adolescent; Adult; Asian People; Child; China; Cohort Studies; Female; Genes, Recessive; Humans; Male; Middle Aged; Molecular Diagnostic Techniques; Mutation; Retinitis Pigmentosa; Sequence Analysis, DNA; Young Adult

Rare complete knockouts in humans: population distribution and significant role in autism spectrum disorders. - Lim, Elaine T; Raychaudhuri, Soumya; Sanders, Stephan J; Stevens, Christine; Aniko Sabo; MacArthur, Daniel G; Neale, Benjamin M; Kirby, Andrew; Ruderfer, Douglas M; Fromer, Menachem; Lek, Monkol; Liu, Li; et al. (Neuron, 2013)
To characterize the role of rare complete human knockouts in autism spectrum disorders (ASDs), we identify genes with homozygous or compound heterozygous loss-of-function (LoF) variants (defined as nonsense and essential splice sites) from exome sequencing of 933 cases and 869 controls. We identify a 2-fold increase in complete knockouts of autosomal genes with low rates of LoF variation (≤ 5% frequency) in cases and estimate a 3% contribution to ASD risk by these events, confirming this observation in an independent set of 563 probands and 4,605 controls. Outside the pseudoautosomal regions on the X chromosome, we similarly observe a significant 1.5-fold increase in rare hemizygous knockouts in males, contributing to another 2% of ASDs in males. Taken together, these results provide compelling evidence that rare autosomal and X chromosome complete gene knockouts are important inherited risk factors for ASD.
Keywords: Case-Control Studies; Child Development Disorders, Pervasive; Child, Preschool; Chromosomes, Human, X; Demography; Female; Gene Deletion; Genetic Variation; Homozygote; Humans; Linkage Disequilibrium; Loss of Heterozygosity; Male; Risk Factors

Seafood consumption and blood mercury concentrations in Jamaican children with and without autism spectrum disorders. - Rahbar, Mohammad H; Samms-Vaughan, Maureen; Loveland, Katherine A; Ardjomand-Hessabi, Manouchehr; Chen, Zhongxue; Bressler, Jan; Shakespeare-Pellington, Sydonnie; Grove, Megan L; Bloom, Kari; Pearson, Deborah A; Lalor, Gerald C; Eric Boerwinkle (Neurotox Res, 2013)
Mercury is a toxic metal shown to have harmful effects on human health. Several studies have reported high blood mercury concentrations as a risk factor for autism spectrum disorders (ASDs), while other studies have reported no such association. The goal of this study was to investigate the association between blood mercury concentrations in children and ASDs. Moreover, we investigated the role of seafood consumption in relation to blood mercury concentrations in Jamaican children. Based on data for 65 sex- and age-matched pairs (2-8 years), we used a General Linear Model to test whether there is an association between blood mercury concentrations and ASDs. After controlling for the child's frequency of seafood consumption, maternal age, and parental education, we did not find a significant difference (P = 0.61) between blood mercury concentrations and ASDs. However, in both cases and control groups, children who ate certain types of seafood (i.e., salt water fish, sardine, or mackerel fish) had significantly higher (all P < 0.05) geometric means blood mercury concentration which were about 3.5 times that of children living in the US or Canada. Our findings also indicate that Jamaican children with parents who both had education up to high school are at a higher risk of exposure to mercury compared to children with at least one parent who had education beyond high school. Based on our findings, we recommend additional education to Jamaican parents regarding potential hazards of elevated blood mercury concentrations, and its association with seafood consumption and type of seafood.
Keywords: Adult; Age Factors; Animals; Biomarkers; Case-Control Studies; Child; Child Development Disorders, Pervasive; Child, Preschool; Female; Humans; Jamaica; Male; Mercury; Seafood; Socioeconomic Factors; Surveys and Questionnaires

TM4SF20 ancestral deletion and susceptibility to a pediatric disorder of early language delay and cerebral white matter hyperintensities. - Wiszniewski, Wojciech; Hunter, Jill V; Hanchard, Neil A; Willer, Jason R; Shaw, Chad; Tian, Qi; Illner, Anna; Wang, Xueqing; Cheung, Sau W; Patel, Ankita; Campbell, Ian M; Gelowani, Violet; et al. (Am J Hum Genet, 2013)
White matter hyperintensities (WMHs) of the brain are important markers of aging and small-vessel disease. WMHs are rare in healthy children and, when observed, often occur with comorbid neuroinflammatory or vasculitic processes. Here, we describe a complex 4 kb deletion in 2q36.3 that segregates with early childhood communication disorders and WMH in 15 unrelated families predominantly from Southeast Asia. The premature brain aging phenotype with punctate and multifocal WMHs was observed in ~70% of young carrier parents who underwent brain MRI. The complex deletion removes the penultimate exon 3 of TM4SF20, a gene encoding a transmembrane protein of unknown function. Minigene analysis showed that the resultant net loss of an exon introduces a premature stop codon, which, in turn, leads to the generation of a stable protein that fails to target to the plasma membrane and accumulates in the cytoplasm. Finally, we report this deletion to be enriched in individuals of Vietnamese Kinh descent, with an allele frequency of about 1%, embedded in an ancestral haplotype. Our data point to a constellation of early language delay and WMH phenotypes, driven by a likely toxic mechanism of TM4SF20 truncation, and highlight the importance of understanding and managing population-specific low-frequency pathogenic alleles.
Keywords: Age of Onset; Aging, Premature; Asian People; Base Sequence; Brain; Child; Child, Preschool; Chromosomes, Human, Pair 2; Exons; Female; Genetic Predisposition to Disease; Humans; Language Development Disorders; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Pedigree; Sequence Analysis, DNA; Sequence Deletion; Tetraspanins

Union makes strength: a worldwide collaborative genetic and clinical study to provide a comprehensive survey of RD3 mutations and delineate the associated phenotype. - Perrault, Isabelle; Estrada-Cuzcano, Alejandro; Lopez, Irma; Kohl, Susanne; Li, Shiqiang; Testa, Francesco; Zekveld-Vroon, Renate; Wang, Xia; Pomares, Esther; Andorf, Jean; Aboussair, Nisrine; Banfi, Sandro; et al. (PLoS One, 2013)
Leber congenital amaurosis (LCA) is the earliest and most severe retinal degeneration (RD), and the most common cause of incurable blindness diagnosed in children. It is occasionally the presenting symptom of multisystemic ciliopathies which diagnosis will require a specific care of patients. Nineteen LCA genes are currently identified and three of them account for both non-syndromic and syndromic forms of the disease. RD3 (LCA12) was implicated as a LCA gene based on the identification of homozygous truncating mutations in two LCA families despite the screening of large cohorts of patients. Here we provide a comprehensive survey of RD3 mutations and of their clinical expression through the screening of a cohort of 852 patients originating worldwide affected with LCA or early-onset and severe RD. We identified three RD3 mutations in seven unrelated consanguineous LCA families - i.e., a 2 bp deletion and two nonsense mutations - predicted to cause complete loss of function. Five families originating from the Southern Shores of the Mediterranean segregated a similar mutation (c.112C>T, p.R38*) suggesting that this change may have resulted from an ancient founder effect. Considering the low frequency of RD3 carriers, the recurrence risk for LCA in non-consanguineous unions is negligible for both heterozygote and homozygote RD3 individuals. The LCA12 phenotype in our patients is highly similar to those of patients with mutant photoreceptor-specific guanylate cyclase (GUCY2D/LCA1). This observation is consistent with the report of the role of RD3 in trafficking of GUCYs and gives further support to a common mechanism of photoreceptor degeneration in LCA12 and LCA1, i.e., inability to increase cytoplasmic cGMP concentration in outer segments and thus to recover the dark-state. Similar to LCA1, LCA12 patients have no extraocular symptoms despite complete inactivation of both RD3 alleles, supporting the view that extraocular investigations in LCA infants with RD3 mutations should be avoided.
Keywords: Adolescent; Adult; Canada; Child; Child, Preschool; China; Cohort Studies; Europe; Eye Proteins; Female; Humans; Infant; Leber Congenital Amaurosis; Linkage Disequilibrium; Male; Mutation; Pedigree; Phenotype; Polymorphism, Genetic; Retina; Retinal Degeneration; United States; Young Adult

Androgen receptor CAG repeat polymorphism in males of six non-human primate species. - Mubiru, James N; Cavazos, Nicole; Hemmat, Peggah; Garcia-Forey, Magdalena; Shade, Robert E; Jeffrey Rogers (J Med Primatol, 2012)
BACKGROUND: Androgen receptor [CAG](n) microsatellite has been linked to human diseases. METHODS: Six non-human primates were genotyped for the [CAG](n) microsatellite. RESULTS: Marmosets and macaques are monomorphic, while mangabeys, baboons, and chimpanzees are polymorphic. CONCLUSIONS: Non-human primates that are polymorphic for the microsatellite are candidate animal models for CAG-related diseases.
Keywords: Animals; DNA; Male; Pan troglodytes; Polymerase Chain Reaction; Polymorphism, Genetic; Primates; Receptors, Androgen; Trinucleotide Repeats

A framework for human microbiome research. (Nature, 2012)
A variety of microbial communities and their genes (the microbiome) exist throughout the human body, with fundamental roles in human health and disease. The National Institutes of Health (NIH)-funded Human Microbiome Project Consortium has established a population-scale framework to develop metagenomic protocols, resulting in a broad range of quality-controlled resources and data including standardized methods for creating, processing and interpreting distinct types of high-throughput metagenomic data available to the scientific community. Here we present resources from a population of 242 healthy adults sampled at 15 or 18 body sites up to three times, which have generated 5,177 microbial taxonomic profiles from 16S ribosomal RNA genes and over 3.5 terabases of metagenomic sequence so far. In parallel, approximately 800 reference strains isolated from the human body have been sequenced. Collectively, these data represent the largest resource describing the abundance and variety of the human microbiome, while providing a framework for current and future studies.
Keywords: Adolescent; Adult; Bacteria; Female; Humans; Male; Metagenome; Metagenomics; Reference Standards; RNA, Ribosomal, 16S; Statistics as Topic; Young Adult

Gene structure in the sea urchin Strongylocentrotus purpuratus based on transcriptome analysis. - Tu, Qiang; Cameron, R Andrew; Worley, Kim C; Richard A Gibbs; Davidson, Eric H (Genome Res, 2012)
A comprehensive transcriptome analysis has been performed on protein-coding RNAs of Strongylocentrotus purpuratus, including 10 different embryonic stages, six feeding larval and metamorphosed juvenile stages, and six adult tissues. In this study, we pooled the transcriptomes from all of these sources and focused on the insights they provide for gene structure in the genome of this recently sequenced model system. The genome had initially been annotated by use of computational gene model prediction algorithms. A large fraction of these predicted genes were recovered in the transcriptome when the reads were mapped to the genome and appropriately filtered and analyzed. However, in a manually curated subset, we discovered that more than half the computational gene model predictions were imperfect, containing errors such as missing exons, prediction of nonexistent exons, erroneous intron/exon boundaries, fusion of adjacent genes, and prediction of multiple genes from single genes. The transcriptome data have been used to provide a systematic upgrade of the gene model predictions throughout the genome, very greatly improving the research usability of the genomic sequence. We have constructed new public databases that incorporate information from the transcriptome analyses. The transcript-based gene model data were used to define average structural parameters for S. purpuratus protein-coding genes. In addition, we constructed a custom sea urchin gene ontology, and assigned about 7000 different annotated transcripts to 24 functional classes. Strong correlations became evident between given functional ontology classes and structural properties, including gene size, exon number, and exon and intron size.
Keywords: Animals; Computational Biology; Databases, Nucleic Acid; Exons; Female; Gene Expression Profiling; Genome; Introns; Male; Models, Genetic; Molecular Sequence Annotation; Molecular Sequence Data; Open Reading Frames; RNA, Spliced Leader; Strongylocentrotus purpuratus; Trans-Splicing; Transcriptome

Genetic contributions to the midsagittal area of the corpus callosum. - Phillips, Kimberley A; Jeffrey Rogers; Barrett, Elizabeth A; Glahn, David C; Kochunov, Peter (Twin Res Hum Genet, 2012)
The degree to which genes and environment determine variations in brain structure and function is fundamentally important to understanding normal and disease-related patterns of neural organization and activity. We studied genetic contributions to the midsagittal area of the corpus callosum (CC) in pedigreed baboons (68 males, 112 females) to replicate findings of high genetic contribution to that area of the CC reported in humans, and to determine if the heritability of the CC midsagittal area in adults was modulated by fetal development rate. Measurements of callosal area were obtained from high-resolution MRI scans. Heritability was estimated from pedigree-based maximum likelihood estimation of genetic and non-genetic variance components as implemented in Sequential Oligogenic Linkage Analysis Routines (SOLAR). Our analyses revealed significant heritability for the total area of the CC and all of its subdivisions, with h2 = .46 for the total CC, and h2 = .54, .37, .62, .56, and .29 for genu, anterior midbody, medial midbody, posterior midbody and splenium, respectively. Genetic correlation analysis demonstrated that the individual subdivisions shared between 41% and 98% of genetic variability. Combined with previous research reporting high heritability of other brain structures in baboons, these results reveal a consistent pattern of high heritability for brain morphometric measures in baboons.
Keywords: Animals; Corpus Callosum; Female; Gene-Environment Interaction; Magnetic Resonance Imaging; Male; Organ Size; Papio; Quantitative Trait, Heritable

The KAT6B-related disorders genitopatellar syndrome and Ohdo/SBBYS syndrome have distinct clinical features reflecting distinct molecular mechanisms. - Campeau, Philippe M; Lu, James T; Dawson, Brian C; Fokkema, Ivo F A C; Robertson, Stephen P; Richard A Gibbs; Lee, Brendan H (Hum Mutat, 2012)
Genitopatellar syndrome (GPS) and Say-Barber-Biesecker-Young-Simpson syndrome (SBBYSS or Ohdo syndrome) have both recently been shown to be caused by distinct mutations in the histone acetyltransferase KAT6B (a.k.a. MYST4/MORF). All variants are de novo dominant mutations that lead to protein truncation. Mutations leading to GPS occur in the proximal portion of the last exon and lead to the expression of a protein without a C-terminal domain. Mutations leading to SBBYSS occur either throughout the gene, leading to nonsense-mediated decay, or more distally in the last exon. Features present only in GPS are contractures, anomalies of the spine, ribs and pelvis, renal cysts, hydronephrosis, and agenesis of the corpus callosum. Features present only in SBBYSS include long thumbs and long great toes and lacrimal duct abnormalities. Several features occur in both, such as intellectual disability, congenital heart defects, and genital and patellar anomalies. We propose that haploinsufficiency or loss of a function mediated by the C-terminal domain causes the common features, whereas gain-of-function activities would explain the features unique to GPS. Further molecular studies and the compilation of mutations in a database for genotype-phenotype correlations (www.LOVD.nl/KAT6B) might help tease out answers to these questions and understand the developmental programs dysregulated by the different truncations.
Keywords: Abnormalities, Multiple; Base Sequence; Blepharophimosis; Blepharoptosis; Craniofacial Abnormalities; Databases, Nucleic Acid; DNA; Female; Genetic Association Studies; Haploinsufficiency; Heart Defects, Congenital; Histone Acetyltransferases; Humans; Intellectual Disability; Kidney; Male; Molecular Sequence Data; Mutation; Patella; Psychomotor Disorders; Scrotum; Sequence Deletion; Urogenital Abnormalities

Landscape of somatic retrotransposition in human cancers. - Lee, Eunjung; Iskow, Rebecca; Yang, Lixing; Gokcumen, Omer; Haseley, Psalm; Luquette, Lovelace J; Lohr, Jens G; Harris, Christopher C; Ding, Li; Wilson, Richard K; Wheeler, David A; Richard A Gibbs; et al. (Science, 2012)
Transposable elements (TEs) are abundant in the human genome, and some are capable of generating new insertions through RNA intermediates. In cancer, the disruption of cellular mechanisms that normally suppress TE activity may facilitate mutagenic retrotranspositions. We performed single-nucleotide resolution analysis of TE insertions in 43 high-coverage whole-genome sequencing data sets from five cancer types. We identified 194 high-confidence somatic TE insertions, as well as thousands of polymorphic TE insertions in matched normal genomes. Somatic insertions were present in epithelial tumors but not in blood or brain cancers. Somatic L1 insertions tend to occur in genes that are commonly mutated in cancer, disrupt the expression of the target genes, and are biased toward regions of cancer-specific DNA hypomethylation, highlighting their potential impact in tumorigenesis.
Keywords: Base Sequence; Cell Transformation, Neoplastic; Colorectal Neoplasms; DNA Methylation; Female; Gene Expression Regulation, Neoplastic; Genes, Neoplasm; Genome, Human; Glioblastoma; Humans; Long Interspersed Nucleotide Elements; Male; Microsatellite Instability; Molecular Sequence Annotation; Molecular Sequence Data; Multiple Myeloma; Mutagenesis, Insertional; Mutation; Ovarian Neoplasms; Prostatic Neoplasms; Retroelements; Sequence Analysis, DNA

Loss-of-function mutations in TGFB2 cause a syndromic presentation of thoracic aortic aneurysm. - Lindsay, Mark E; Schepers, Dorien; Bolar, Nikhita Ajit; Doyle, Jefferson J; Gallo, Elena; Fert-Bober, Justyna; Kempers, Marlies J E; Fishman, Elliot K; Chen, Yichun; Myers, Loretha; Bjeda, Djahita; Oswald, Gretchen; et al. (Nat Genet, 2012)
Loeys-Dietz syndrome (LDS) associates with a tissue signature for high transforming growth factor (TGF)-β signaling but is often caused by heterozygous mutations in genes encoding positive effectors of TGF-β signaling, including either subunit of the TGF-β receptor or SMAD3, thereby engendering controversy regarding the mechanism of disease. Here, we report heterozygous mutations or deletions in the gene encoding the TGF-β2 ligand for a phenotype within the LDS spectrum and show upregulation of TGF-β signaling in aortic tissue from affected individuals. Furthermore, haploinsufficient Tgfb2(+/-) mice have aortic root aneurysm and biochemical evidence of increased canonical and noncanonical TGF-β signaling. Mice that harbor both a mutant Marfan syndrome (MFS) allele (Fbn1(C1039G/+)) and Tgfb2 haploinsufficiency show increased TGF-β signaling and phenotypic worsening in association with normalization of TGF-β2 expression and high expression of TGF-β1. Taken together, these data support the hypothesis that compensatory autocrine and/or paracrine events contribute to the pathogenesis of TGF-β-mediated vasculopathies.
Keywords: Animals; Aortic Aneurysm, Thoracic; Disease Models, Animal; Female; Fibrillin-1; Fibrillins; Haploinsufficiency; Humans; Loeys-Dietz Syndrome; Male; Marfan Syndrome; Mice; Mice, Knockout; Mice, Mutant Strains; Microfilament Proteins; Mutation; Pedigree; Phenotype; Signal Transduction; Syndrome; Transforming Growth Factor beta2

Maternal and paternal age are jointly associated with childhood autism in Jamaica. - Rahbar, Mohammad H; Samms-Vaughan, Maureen; Loveland, Katherine A; Pearson, Deborah A; Bressler, Jan; Chen, Zhongxue; Ardjomand-Hessabi, Manouchehr; Shakespeare-Pellington, Sydonnie; Grove, Megan L; Beecher, Compton; Bloom, Kari; Eric Boerwinkle (J Autism Dev Disord, 2012)
Several studies have reported maternal and paternal age as risk factors for having a child with Autism Spectrum Disorder (ASD), yet the results remain inconsistent. We used data for 68 age- and sex-matched case-control pairs collected from Jamaica. Using Multivariate General Linear Models (MGLM) and controlling for parity, gestational age, and parental education, we found a significant (p < 0.0001) joint effect of parental ages on having children with ASD indicating an adjusted mean paternal age difference between cases and controls of [5.9 years; 95% CI (2.6, 9.1)] and a difference for maternal age of [6.5 years; 95% CI (4.0, 8.9)]. To avoid multicollinearity in logistic regression, we recommend joint modeling of parental ages as a vector of outcome variables using MGLM.
Keywords: Autistic Disorder; Child; Child, Preschool; Female; Humans; Infant; Jamaica; Male; Maternal Age; Paternal Age; Registries; Risk Factors

Microarray-based capture of novel expressed cell type-specific transfrags (CoNECT) to annotate tissue-specific transcription in Drosophila melanogaster. - Hong, X; Harshavardhan Doddapaneni; Comeron, J M; Rodesch, M J; Halvensleben, H A; Nien, C Y; Bolei, F; Metpally, R; Richmond, T A; Albert, T J; Manak, J R (G3 (Bethesda), 2012)
Faithful annotation of tissue-specific transcript isoforms is important not only to understand how genes are organized and regulated but also to identify potential novel, unannotated exons of genes, which may be additional targets of mutation in disease states or while performing mutagenic screens. We have developed a microarray enrichment methodology followed by long-read, next-generation sequencing for identification of unannotated transcript isoforms expressed in two Drosophila tissues, the ovary and the testis. Even with limited sequencing, these studies have identified a large number of novel transcription units, including 5' exons and extensions, 3' exons and extensions, internal exons and exon extensions, gene fusions, and both germline-specific splicing events and promoters. Additionally, comparing our capture dataset with tiling array and traditional RNA-seq analysis, we demonstrate that our enrichment strategy is able to capture low-abundance transcripts that cannot readily be identified by the other strategies. Finally, we show that our methodology can help identify transcriptional signatures of minority cell types within the ovary that would otherwise be difficult to reveal without the CoNECT enrichment strategy. These studies introduce an efficient methodology for cataloging tissue-specific transcriptomes in which specific classes of genes or transcripts can be targeted for capture and sequence, thus reducing the significant sequencing depth normally required for accurate annotation. Ovary and testis isotigs over 200 bp have been deposited with the GenBank Transcriptome Shotgun Assembly Sequence Database as bioproject no.PRJNA89451 (accession nos. JV208106–JV230865).
Keywords: Animals; Databases, Genetic; Drosophila melanogaster; Drosophila Proteins; Exons; Female; Male; Oligonucleotide Array Sequence Analysis; Ovary; Promoter Regions, Genetic; Protein Isoforms; RNA Splicing; Testis; Transcriptome

Mutations in KAT6B, encoding a histone acetyltransferase, cause Genitopatellar syndrome. - Campeau, Philippe M; Kim, Jaeseung C; Lu, James T; Schwartzentruber, Jeremy A; Abdul-Rahman, Omar A; Schlaubitz, Silke; Murdock, David M; Jiang, Ming-Ming; Lammer, Edward J; Enns, Gregory M; Rhead, William J; Rowland, Jon; et al. (Am J Hum Genet, 2012)
Genitopatellar syndrome (GPS) is a skeletal dysplasia with cerebral and genital anomalies for which the molecular basis has not yet been determined. By exome sequencing, we found de novo heterozygous truncating mutations in KAT6B (lysine acetyltransferase 6B, formerly known as MYST4 and MORF) in three subjects; then by Sanger sequencing of KAT6B, we found similar mutations in three additional subjects. The mutant transcripts do not undergo nonsense-mediated decay in cells from subjects with GPS. In addition, human pathological analyses and mouse expression studies point to systemic roles of KAT6B in controlling organismal growth and development. Myst4 (the mouse orthologous gene) is expressed in mouse tissues corresponding to those affected by GPS. Phenotypic differences and similarities between GPS, the Say-Barber-Biesecker variant of Ohdo syndrome (caused by different mutations of KAT6B), and Rubinstein-Taybi syndrome (caused by mutations in other histone acetyltransferases) are discussed. Together, the data support an epigenetic dysregulation of the limb, brain, and genital developmental programs.
Keywords: Abnormalities, Multiple; Animals; Blepharophimosis; Blepharoptosis; Bone Diseases, Developmental; Cerebellum; Epigenomics; Exome; Female; Heart Defects, Congenital; Heterozygote; Histone Acetyltransferases; Humans; Intellectual Disability; Male; Mice; Mice, Inbred C57BL; Musculoskeletal Abnormalities; Mutation; Phenotype; Rubinstein-Taybi Syndrome; Sequence Analysis, DNA; Urogenital Abnormalities

PDX-1 is a therapeutic target for pancreatic cancer, insulinoma and islet neoplasia using a novel RNA interference platform. - Liu, Shi-He; Rao, Donald D; Nemunaitis, John; Senzer, Neil; Zhou, Guisheng; Dawson, David; Marie-Claude Gingras; Wang, Zhaohui; Richard A Gibbs; Norman, Michael; Templeton, Nancy S; DeMayo, Francesco J; et al. (PLoS One, 2012)
Pancreatic and duodenal homeobox-1 (PDX-1) is a transcription factor that regulates insulin expression and islet maintenance in the adult pancreas. Our recent studies demonstrate that PDX-1 is an oncogene for pancreatic cancer and is overexpressed in pancreatic cancer. The purpose of this study was to demonstrate that PDX-1 is a therapeutic target for both hormonal symptoms and tumor volume in mouse models of pancreatic cancer, insulinoma and islet neoplasia. Immunohistochemistry of human pancreatic and islet neoplasia specimens revealed marked PDX-1 overexpression, suggesting PDX-1 as a "drugable" target within these diseases. To do so, a novel RNA interference effector platform, bifunctional shRNA(PDX-1), was developed and studied in mouse and human cell lines as well as in mouse models of pancreatic cancer, insulinoma and islet neoplasia. Systemic delivery of bi-shRNA(humanPDX-1) lipoplexes resulted in marked reduction of tumor volume and improved survival in a human pancreatic cancer xenograft mouse model. bi-shRNA(mousePDX-1) lipoplexes prevented death from hyperinsulinemia and hypoglycemia in an insulinoma mouse model. shRNA(mousePDX-1) lipoplexes reversed hyperinsulinemia and hypoglycemia in an immune-competent mouse model of islet neoplasia. PDX-1 was overexpressed in pancreatic neuroendocrine tumors and nesidioblastosis. These data demonstrate that PDX-1 RNAi therapy controls hormonal symptoms and tumor volume in mouse models of pancreatic cancer, insulinoma and islet neoplasia, therefore, PDX-1 is a potential therapeutic target for these pancreatic diseases.
Keywords: Animals; Cell Line, Tumor; Cell Proliferation; Disease Models, Animal; Glucose Tolerance Test; Homeodomain Proteins; Humans; Immunohistochemistry; In Situ Nick-End Labeling; Insulin; Insulinoma; Islets of Langerhans; Male; Mice; Mice, SCID; Neoplasm Transplantation; Pancreas; Pancreatic Neoplasms; RNA Interference; Trans-Activators

PNPLA3 polymorphisms and liver aminotransferase levels in a Mexican American population. - Li, Quan; Qu, Hui-Qi; Rentfro, Anne R; Grove, Megan L; Mirza, Shaper; Lu, Yang; Hanis, Craig L; Fallon, Michael B; Eric Boerwinkle; Fisher-Hoch, Susan P; McCormick, Joseph B (Clin Invest Med, 2012)
PURPOSE: This study examined genetic associations of patatin-like phospholipase domain containing 3 gene (PNPLA3) polymorphisms and liver aminotransferases in an extensively documented, randomly recruited Mexican American population at high risk of liver disease. METHODS: Two single nucleotide polymorphisms (SNP) in the PNPLA3 gene (i.e., rs738409 and rs2281135) were genotyped in 1532 individuals. Population stratification was corrected by the genotyping of 103 ancestry informative markers (AIMs) for Mexican Americans. RESULTS: Both PNPLA3 SNPs showed highly significant association with alanine aminotransferase (ALT) levels, but was also, in males, associated with aspartate aminotransferase (AST) levels. Haplotypic association test of the two SNPs suggested stronger genetic association with rs738409 than rs2281135. Obvious sex effects were observed: rs738409-sex interaction in ALT levels P = 8.37 x 10(-4); rs738409-sex interaction in AST levels P = 5.03 x 10(-3). CONCLUSIONS: This population study highlights a sex-specific association of PNPLA3 polymorphisms and elevated liver enzymes in a population-based study, independent of common pathological factors of the metabolic syndrome. The strong genetic association found in women ≤ 50 years old, but not in women > 50 years old, suggests that sex hormones may mediate the sex effect.
Keywords: Adult; Age Factors; Alanine Transaminase; Aspartate Aminotransferases; Female; Genotype; Humans; Lipase; Liver; Liver Diseases; Male; Membrane Proteins; Metabolic Syndrome; Mexican Americans; Middle Aged; Polymorphism, Single Nucleotide; Sex Characteristics

Population-based risk factors for elevated alanine aminotransferase in a South Texas Mexican-American population. - Qu, Hui-Qi; Li, Quan; Grove, Megan L; Lu, Yang; Pan, Jen-Jung; Rentfro, Anne R; Bickel, Perry E; Fallon, Michael B; Hanis, Craig L; Eric Boerwinkle; McCormick, Joseph B; Fisher-Hoch, Susan P (Arch Med Res, 2012)
BACKGROUND AND AIMS: Elevated alanine aminotransferase (ALT >40 IU/mL) is a marker of liver injury but provides little insight into etiology. We aimed to identify and stratify risk factors associated with elevated ALT in a randomly selected population with a high prevalence of elevated ALT (39%), obesity (49%) and diabetes (30%). METHODS: Two machine learning methods, the support vector machine (SVM) and Bayesian logistic regression (BLR), were used to capture risk factors in a community cohort of 1532 adults from the Cameron County Hispanic Cohort (CCHC). A total of 28 predictor variables were used in the prediction models. The recently identified genetic marker rs738409 on the PNPLA3 gene was genotyped using the Sequenom iPLEX assay. RESULTS: The four major risk factors for elevated ALT were fasting plasma insulin level and insulin resistance, increased BMI and total body weight, plasma triglycerides and non-HDL cholesterol, and diastolic hypertension. In spite of the highly significant association of rs738409 in females, the role of rs738409 in the prediction model is minimal, compared to other epidemiological risk factors. Age and drug and alcohol consumption were not independent determinants of elevated ALT in this analysis. CONCLUSIONS: The risk factors most strongly associated with elevated ALT in this population are components of the metabolic syndrome and point to nonalcoholic fatty liver disease (NAFLD). This population-based model identifies the likely cause of liver disease without the requirement of individual pathological diagnosis of liver diseases. Use of such a model can greatly contribute to a population-based approach to prevention of liver disease.
Keywords: Alanine Transaminase; Female; Humans; Male; Mexican Americans; Risk Factors; Support Vector Machine; Texas

Quantitative trait loci affecting liver fat content in mice. - Minkina, Olga; Cheverud, James M; Fawcett, Gloria; Semenkovich, Clay F; Kenney-Hunt, Jane P (G3 (Bethesda), 2012)
Nonalcoholic fatty liver disease, a condition in which excess fat accumulates in the liver, is strongly associated with the metabolic syndrome, including obesity and other related conditions. This disease has the potential to progress from steatosis to steatohepatitis, fibrosis, and cirrhosis. The recent increase in the prevalence of the metabolic syndrome is largely driven by changes in diet and activity levels. Individual variation in the response to this obesogenic environment, however, is attributable in part to genetic variation between individuals, but very few mammalian genetic loci have been identified with effects on fat accumulation in the liver. To study the genetic basis for variation in liver fat content in response to dietary fat, liver fat proportion was determined using quantitative magnetic resonance imaging in 478 mice from 16 LG/J X SM/J recombinant inbred strains fed either a high-fat (42% kcal from fat) or low-fat (15% kcal from fat) diet. An analysis of variance confirmed that there is a genetic basis for variation in liver fat content within the population with significant effects of sex and diet. Three quantitative trail loci that contribute to liver fat content also were mapped.
Keywords: Animals; Diabetes Mellitus; Diet, Fat-Restricted; Diet, High-Fat; Fats; Fatty Liver; Female; Liver; Male; Mice; Non-alcoholic Fatty Liver Disease; Obesity; Quantitative Trait Loci

Residual plasmatic activity of ADAMTS13 is correlated with phenotype severity in congenital thrombotic thrombocytopenic purpura. - Lotta, Luca A; Wu, Haifeng M; Mackie, Ian J; Noris, Marina; Veyradier, Agnes; Scully, Marie A; Remuzzi, Giuseppe; Coppo, Paul; Liesner, Ri; Donadelli, Roberta; Loirat, Chantal; Richard A Gibbs; et al. (Blood, 2012)
The quantification of residual plasmatic ADAMTS13 activity in congenital thrombotic thrombocytopenic purpura (TTP) patients is constrained by limitations in sensitivity and reproducibility of commonly used assays at low levels of ADAMTS13 activity, blunting efforts to establish genotype-phenotype correlations. In the present study, the residual plasmatic activity of ADAMTS13 was measured centrally by surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (limit of detection = 0.5%) in 29 congenital TTP patients. The results were used to study correlations among ADAMTS13 genotype, residual plasmatic activity, and clinical phenotype severity. An ADAMTS13 activity above 0.5% was measured in 26 (90%) patients and lower levels of activity were associated with earlier age at first TTP episode requiring plasma infusion, more frequent recurrences, and prescription of fresh-frozen plasma prophylaxis. Receiver operating characteristic curve analysis showed that activity levels of less than 2.74% and 1.61% were discriminative of age at first TTP episode requiring plasma infusion < 18 years, annual rate of TTP episodes > 1, and use of prophylaxis. Mutations affecting the highly conserved N-terminal domains of the protein were associated with lower residual ADAMTS13 activity and a more severe phenotype in an allelic-dose dependent manner. The results of the present study show that residual ADAMTS13 activity is associated with the severity of clinical phenotype in congenital TTP and provide insights into genotype-phenotype correlations.
Keywords: ADAM Proteins; ADAMTS13 Protein; Adolescent; Adult; Age Factors; Aged; Blood Chemical Analysis; Blood Transfusion; Child; Child, Preschool; DNA Mutational Analysis; Female; Genetic Association Studies; Humans; Male; Middle Aged; Mutation; Plasma; Purpura, Thrombotic Thrombocytopenic; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Young Adult

Serum prostate specific antigen changes in cynomolgus monkeys (Macaca fascicularis) on a high sugar high fat diet. - Mubiru, James N; Garcia-Forey, Magdalena; Cavazos, Nicole; Hemmat, Peggah; Dick, Edward J; Owston, Michael A; Bauer, Cassondra A; Shade, Robert E; Jeffrey Rogers (Prostate, 2012)
BACKGROUND: An inverse relationship between serum prostate specific antigen (PSA) levels and body mass index (BMI) has been reported in men but not in any animal model. METHODS: Serum PSA in a colony of cynomolgus monkeys was assayed and correlated to body weight, prostate weight, and age. In addition, 15 animals were selected and fed a high sugar high fat (HSHF) diet for 49 weeks to increase their BMI and correlate it to PSA RESULTS: Serum PSA levels were positively correlated to prostate weight (r = 0.515, P = 0.025) and age (r = 0.548, P = 0.00072) but was not significantly correlated to body weight (r = -0.032, P = 0.419). For the animals on the HSHF diet, body weight, lean mass, fat mass, and BMI were significantly higher at 49 weeks than at baseline (P < 0.01). PSA was not significantly correlated to body weight and insulin at both baseline and 49 weeks. PSA was negatively correlated to BMI and insulin resistance (HOMA-IR) at 49 weeks but not at baseline. In addition, we observed hepatic steatosis and increases in serum liver enzymes. CONCLUSIONS: Increases in BMI in cynomolgus monkeys as a result of consuming a HSHF diet resulted in PSA changes similar to those in humans with increased BMI. Cynomolgus monkeys are a useful model for investigating the relationship between obesity, diabetes, and PSA changes resulting from prostate gland pathology.
Keywords: Absorptiometry, Photon; Animals; Blood Glucose; Body Mass Index; Body Weight; Dietary Carbohydrates; Dietary Fats; Disease Models, Animal; Insulin; Insulin Resistance; Macaca fascicularis; Male; Obesity; Organ Size; Prostate; Prostate-Specific Antigen

Strict evolutionary conservation followed rapid gene loss on human and rhesus Y chromosomes. - Hughes, Jennifer F; Skaletsky, Helen; Brown, Laura G; Pyntikova, Tatyana; Graves, Tina; Fulton, Robert S; Dugan, Shannon; Ding, Yan; Buhay, Christian J; Kremitzki, Colin; Wang, Qiaoyan; Shen, Hua; et al. (Nature, 2012)
The human X and Y chromosomes evolved from an ordinary pair of autosomes during the past 200-300 million years. The human MSY (male-specific region of Y chromosome) retains only three percent of the ancestral autosomes' genes owing to genetic decay. This evolutionary decay was driven by a series of five 'stratification' events. Each event suppressed X-Y crossing over within a chromosome segment or 'stratum', incorporated that segment into the MSY and subjected its genes to the erosive forces that attend the absence of crossing over. The last of these events occurred 30 million years ago, 5 million years before the human and Old World monkey lineages diverged. Although speculation abounds regarding ongoing decay and looming extinction of the human Y chromosome, remarkably little is known about how many MSY genes were lost in the human lineage in the 25 million years that have followed its separation from the Old World monkey lineage. To investigate this question, we sequenced the MSY of the rhesus macaque, an Old World monkey, and compared it to the human MSY. We discovered that during the last 25 million years MSY gene loss in the human lineage was limited to the youngest stratum (stratum 5), which comprises three percent of the human MSY. In the older strata, which collectively comprise the bulk of the human MSY, gene loss evidently ceased more than 25 million years ago. Likewise, the rhesus MSY has not lost any older genes (from strata 1-4) during the past 25 million years, despite its major structural differences to the human MSY. The rhesus MSY is simpler, with few amplified gene families or palindromes that might enable intrachromosomal recombination and repair. We present an empirical reconstruction of human MSY evolution in which each stratum transitioned from rapid, exponential loss of ancestral genes to strict conservation through purifying selection.
Keywords: Animals; Chromosomes, Human, Y; Conserved Sequence; Crossing Over, Genetic; Evolution, Molecular; Gene Amplification; Gene Deletion; Humans; In Situ Hybridization, Fluorescence; Macaca mulatta; Male; Models, Genetic; Molecular Sequence Data; Pan troglodytes; Radiation Hybrid Mapping; Selection, Genetic; Time Factors; Y Chromosome

Structure, function and diversity of the healthy human microbiome. (Nature, 2012)
Studies of the human microbiome have revealed that even healthy individuals differ remarkably in the microbes that occupy habitats such as the gut, skin and vagina. Much of this diversity remains unexplained, although diet, environment, host genetics and early microbial exposure have all been implicated. Accordingly, to characterize the ecology of human-associated microbial communities, the Human Microbiome Project has analysed the largest cohort and set of distinct, clinically relevant body habitats so far. We found the diversity and abundance of each habitat's signature microbes to vary widely even among healthy subjects, with strong niche specialization both within and among individuals. The project encountered an estimated 81-99% of the genera, enzyme families and community configurations occupied by the healthy Western microbiome. Metagenomic carriage of metabolic pathways was stable among individuals despite variation in community structure, and ethnic/racial background proved to be one of the strongest associations of both pathways and microbes with clinical metadata. These results thus delineate the range of structural and functional configurations normal in the microbial communities of a healthy population, enabling future characterization of the epidemiology, ecology and translational applications of the human microbiome.
Keywords: Adolescent; Adult; Bacteria; Biodiversity; Ecosystem; Female; Health; Humans; Male; Metabolic Networks and Pathways; Metagenome; Metagenomics; Phenotype; RNA, Ribosomal, 16S; Young Adult

Treponema pallidum infection in the wild baboons of East Africa: distribution and genetic characterization of the strains responsible. - Harper, Kristin N; Fyumagwa, Robert D; Hoare, Richard; Wambura, Philemon N; Coppenhaver, Dorian H; Sapolsky, Robert M; Alberts, Susan C; Tung, Jenny; Jeffrey Rogers; Kilewo, Morris; Batamuzi, Emmanuel K; Leendertz, Fabian H; et al. (PLoS One, 2012)
It has been known for decades that wild baboons are naturally infected with Treponema pallidum, the bacterium that causes the diseases syphilis (subsp. pallidum), yaws (subsp. pertenue), and bejel (subsp. endemicum) in humans. Recently, a form of T. pallidum infection associated with severe genital lesions has been described in wild baboons at Lake Manyara National Park in Tanzania. In this study, we investigated ten additional sites in Tanzania and Kenya using a combination of macroscopic observation and serology, in order to determine whether the infection was present in each area. In addition, we obtained genetic sequence data from six polymorphic regions using T. pallidum strains collected from baboons at two different Tanzanian sites. We report that lesions consistent with T. pallidum infection were present at four of the five Tanzanian sites examined, and serology was used to confirm treponemal infection at three of these. By contrast, no signs of treponemal infection were observed at the six Kenyan sites, and serology indicated T. pallidum was present at only one of them. A survey of sexually mature baboons at Lake Manyara National Park in 2006 carried out as part of this study indicated that roughly ten percent displayed T. pallidum-associated lesions severe enough to cause major structural damage to the genitalia. Finally, we found that T. pallidum strains from Lake Manyara National Park and Serengeti National Park were genetically distinct, and a phylogeny suggested that baboon strains may have diverged prior to the clade containing human strains. We conclude that T. pallidum infection associated with genital lesions appears to be common in the wild baboons of the regions studied in Tanzania. Further study is needed to elucidate the infection's transmission mode, its associated morbidity and mortality, and the relationship between baboon and human strains.
Keywords: Africa, Eastern; Animals; Antibodies, Bacterial; DNA, Bacterial; Evolution, Molecular; Female; Humans; Male; Monkey Diseases; Papio; Phylogeny; Sequence Analysis, DNA; Species Specificity; Syphilis; Treponema pallidum

WDR35 mutation in siblings with Sensenbrenner syndrome: a ciliopathy with variable phenotype. - Bacino, Carlos A; Dhar, Shweta U; Brunetti-Pierri, Nicola; Lee, Brendan; Bonnen, Penelope E (Am J Med Genet A, 2012)
Sensenbrenner syndrome and unclassified short rib-polydactyly conditions are ciliopathies with overlapping phenotypes and genetic heterogeneity. Mutations in WDR35 were identified recently in a sub-group of patients with Sensenbrenner syndrome and in a single family that presented with an unclassified form of short-rib polydactyly (SRP) syndrome. We report on siblings with an unusual combination of phenotypes: narrow thorax, short stature, minor anomalies, developmental delay, and severe hepatic fibrosis leading to liver failure and early death in two of the children. Both parents were unaffected suggesting autosomal recessive inheritance. The family and their affected children were followed over a decade. Exome sequencing was performed in one affected individual. It showed a homozygous missense mutation in a highly conserved position of the WDR35 gene. This family represents a WDR35-ciliopathy with a complex clinical presentation that includes significant overlap of the phenotypes described in Sensenbrenner syndrome and the unclassified SRPs. The accurate molecular diagnosis of this family exemplifies the power of exome sequencing in the diagnosis of Mendelian disorders and enabled us to broaden and refine our understanding of Sensenbrenner syndrome and SRP. Detailed genotype-phenotype information is provided as well as discussion of previously reported cases.
Keywords: Amino Acid Sequence; Base Sequence; Bone and Bones; Craniosynostoses; Cytoskeletal Proteins; Ectodermal Dysplasia; Exome; Female; Hedgehog Proteins; Homozygote; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Mutation; Mutation, Missense; Pedigree; Phenotype; Proteins; Siblings

WDR62 missense mutation in a consanguineous family with primary microcephaly. - Bacino, Carlos A; Arriola, Luis A; Wiszniewska, Joanna; Bonnen, Penelope E (Am J Med Genet A, 2012)
We report on a consanguineous couple with two affected sons who presented with primary microcephaly and moderate to severe intellectual disabilities. A SNP array uncovered two overlapping regions of copy-neutral absence of heterozygosity (AOH) in both sibs. This led to sequencing of WDR62, a gene that codes for a spindle pole protein recently identified as a cause of primary microcephaly. A homozygous missense mutation in WDR62, p.E400K, was found in both boys and segregated with the condition in this family. WDR62 is one of seven genes responsible for autosomal recessive primary microcephaly (MCPH), and appears to be one of the most frequently involved in MCPH following ASPM. Studies of ASPM and WDR62 should perhaps be pursued in all cases of primary microcephaly with or without gross brain malformations.
Keywords: Cell Cycle Proteins; Consanguinity; Female; Homozygote; Humans; Infant; Male; Microcephaly; Mutation, Missense; Nerve Tissue Proteins; Pedigree; Polymorphism, Single Nucleotide

Whole genome sequence of Treponema pallidum ssp. pallidum, strain Mexico A, suggests recombination between yaws and syphilis strains. - Pětrošová, Helena; Zobaníková, Marie; Čejková, Darina; Mikalová, Lenka; Pospíšilová, Petra; Strouhal, Michal; Chen, Lei; Qin, Xiang; Donna M Muzny; Weinstock, George M; Smajs, David (PLoS Negl Trop Dis, 2012)
BACKGROUND: Treponema pallidum ssp. pallidum (TPA), the causative agent of syphilis, and Treponema pallidum ssp. pertenue (TPE), the causative agent of yaws, are closely related spirochetes causing diseases with distinct clinical manifestations. The TPA Mexico A strain was isolated in 1953 from male, with primary syphilis, living in Mexico. Attempts to cultivate TPA Mexico A strain under in vitro conditions have revealed lower growth potential compared to other tested TPA strains. METHODOLOGY/PRINCIPAL FINDINGS: The complete genome sequence of the TPA Mexico A strain was determined using the Illumina sequencing technique. The genome sequence assembly was verified using the whole genome fingerprinting technique and the final sequence was annotated. The genome size of the Mexico A strain was determined to be 1,140,038 bp with 1,035 predicted ORFs. The Mexico A genome sequence was compared to the whole genome sequences of three TPA (Nichols, SS14 and Chicago) and three TPE (CDC-2, Samoa D and Gauthier) strains. No large rearrangements in the Mexico A genome were found and the identified nucleotide changes occurred most frequently in genes encoding putative virulence factors. Nevertheless, the genome of the Mexico A strain, revealed two genes (TPAMA_0326 (tp92) and TPAMA_0488 (mcp2-1)) which combine TPA- and TPE- specific nucleotide sequences. Both genes were found to be under positive selection within TPA strains and also between TPA and TPE strains. CONCLUSIONS/SIGNIFICANCE: The observed mosaic character of the TPAMA_0326 and TPAMA_0488 loci is likely a result of inter-strain recombination between TPA and TPE strains during simultaneous infection of a single host suggesting horizontal gene transfer between treponemal subspecies.
Keywords: DNA, Bacterial; Genome, Bacterial; Humans; Male; Mexico; Molecular Sequence Data; Open Reading Frames; Recombination, Genetic; Sequence Analysis, DNA; Synteny; Syphilis; Treponema pallidum; Yaws

Association between somatostatin receptor 5 gene polymorphisms and pancreatic cancer risk and survival. - Li, Donghui; Tanaka, Motofumi; Brunicardi, F Charles; Fisher, William E; Richard A Gibbs; Marie-Claude Gingras (Cancer, 2011)
BACKGROUND: Somatostatin (SST) inhibited cell proliferation and negatively regulated the release of growth hormones by means of specific receptors (SSTR). Genetic variation in SSTR had been associated with risk of human cancers but had never been investigated in pancreatic cancer. METHODS: In this retrospective study the SSTR5 gene in paired tumor and blood samples from 33 pancreatic adenocarcinoma patients using the Sanger method were sequenced. Three single nucleotide polymorphisms (SNPs) in samples from 863 patients with pancreatic ductal adenocarcinoma and 876 healthy controls using the TaqMan method were analyzed. The associations between gene polymorphisms and pancreatic cancer risk and survival were analyzed by multivariate logistic regression and Cox proportional hazard models, respectively. RESULTS: No somatic mutations were identified, but 3 nonsynonymous SSTR5 SNPs (P109S, L48M, and P335L) in pancreatic tumors were identified. The SSTR5 P109S variant allele was associated with a 1.62-fold increased risk of pancreatic cancer (95% confidence interval [CI]: 1.08-2.43, P = 0.019). Furthermore, the SSTR5 L48M AC variant and smoking had a joint effect on pancreatic cancer risk (p(interaction) = 0.035). The odds ratios (95% confidence intervals) were 0.58 (0.34-0.97), 1.49 (1.18-1.89), and 2.27 (1.35-3.83) for the variant genotype alone, smoking alone, and both factors, respectively, compared with no factors. Finally, SSTR5 P335L CC and P109S CC combined were associated with lower overall survival durations in patients with resectable disease. CONCLUSIONS: These data suggest that SSTR5 genetic variants play a role in pancreatic cancer development and progression.
Keywords: Adult; Aged; Aged, 80 and over; Carcinoma, Pancreatic Ductal; Female; Genetic Predisposition to Disease; Genotype; Humans; Male; Middle Aged; Pancreatic Neoplasms; Polymorphism, Single Nucleotide; Proportional Hazards Models; Receptors, Somatostatin; Retrospective Studies; Risk; Sequence Analysis, DNA; Smoking; Somatostatin

Comparative and demographic analysis of orang-utan genomes. - Locke, Devin P; Hillier, LaDeana W; Warren, Wesley C; Worley, Kim C; Nazareth, Lynne V; Donna M Muzny; Yang, Shiaw-Pyng; Wang, Zhengyuan; Chinwalla, Asif T; Minx, Pat; Mitreva, Makedonka; Cook, Lisa; et al. (Nature, 2011)
'Orang-utan' is derived from a Malay term meaning 'man of the forest' and aptly describes the southeast Asian great apes native to Sumatra and Borneo. The orang-utan species, Pongo abelii (Sumatran) and Pongo pygmaeus (Bornean), are the most phylogenetically distant great apes from humans, thereby providing an informative perspective on hominid evolution. Here we present a Sumatran orang-utan draft genome assembly and short read sequence data from five Sumatran and five Bornean orang-utan genomes. Our analyses reveal that, compared to other primates, the orang-utan genome has many unique features. Structural evolution of the orang-utan genome has proceeded much more slowly than other great apes, evidenced by fewer rearrangements, less segmental duplication, a lower rate of gene family turnover and surprisingly quiescent Alu repeats, which have played a major role in restructuring other primate genomes. We also describe a primate polymorphic neocentromere, found in both Pongo species, emphasizing the gradual evolution of orang-utan genome structure. Orang-utans have extremely low energy usage for a eutherian mammal, far lower than their hominid relatives. Adding their genome to the repertoire of sequenced primates illuminates new signals of positive selection in several pathways including glycolipid metabolism. From the population perspective, both Pongo species are deeply diverse; however, Sumatran individuals possess greater diversity than their Bornean counterparts, and more species-specific variation. Our estimate of Bornean/Sumatran speciation time, 400,000 years ago, is more recent than most previous studies and underscores the complexity of the orang-utan speciation process. Despite a smaller modern census population size, the Sumatran effective population size (N(e)) expanded exponentially relative to the ancestral N(e) after the split, while Bornean N(e) declined over the same period. Overall, the resources and analyses presented here offer new opportunities in evolutionary genomics, insights into hominid biology, and an extensive database of variation for conservation efforts.
Keywords: Animals; Centromere; Cerebrosides; Chromosomes; Evolution, Molecular; Female; Gene Rearrangement; Genetic Speciation; Genetic Variation; Genetics, Population; Genome; Humans; Male; Phylogeny; Pongo abelii; Pongo pygmaeus; Population Density; Population Dynamics; Species Specificity

Cortical sulcal areas in baboons (Papio hamadryas spp.) with generalized interictal epileptic discharges on scalp EEG. - Szabó, C A; Kochunov, P; Knape, K D; McCoy, K J M; Leland, M M; Lancaster, J L; Fox, P T; Williams, J T; Rogers, J (Epilepsy Res, 2011)
Brain MRI studies in people with idiopathic generalized epilepsies demonstrate regional morphometric differences, though variable in magnitude and location. As the baboon provides an excellent electroclinical and neuroimaging model for photosensitive generalized epilepsy in humans, this study evaluated MRI volumetric and morphometric differences between baboons with interictal epileptic discharges (IEDs) on scalp EEG and baboons with normal EEG studies. Seventy-seven baboons underwent high-resolution brain MRI and scalp EEG studies. The scans were acquired using an 8-channel primate head coil (Siemens TRIO 3T scanner, Erlangen, Germany). After spatial normalization, sulcal measurements were obtained by object-based-morphology methods. One-hour scalp EEG studies were performed in animals sedated with ketamine. Thirty-eight (22F/16M) baboons had normal EEGs (IED-), while 39 (22F/17M) had generalized IEDs (IED+). The two groups were compared for age, total brain volume, and sulcal areas (Hotelling's Trace) as well as between-subjects comparison of 11 individual sulcal areas (averaged between left and right hemispheres). There were no differences between IED- and IED+ groups with respect to age or total brain (gray or white matter) volume, and multivariate tests demonstrated a marginally significant decrease of sulcal areas in IED+ baboons (p=0.075). Tests of between-subjects effects showed statistically significant decreases in the intraparietal (p=0.002), central (p=0.03) and cingulate sulci (p=0.02), and marginal decreases involving the lunate (p=0.07) and superior temporal sulci (p=0.08). Differences in sulcal areas in IED+ baboons may reflect global developmental abnormalities, while decreases of areas of specific sulci reflect anatomical markers for potential generators or cortical nodes of the networks underlying spontaneous seizures and photosensitivity in the baboon.
Keywords: Animals; Brain; Cerebral Cortex; Data Interpretation, Statistical; Electroencephalography; Epilepsy; Female; Functional Laterality; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Papio; Parietal Lobe; Seizures

Diet-dependent genetic and genomic imprinting effects on obesity in mice. - Cheverud, James M; Lawson, Heather A; Fawcett, Gloria L; Wang, Bing; Pletscher, L Susan; R Fox, Ashley; Maxwell, Taylor J; Ehrich, Thomas H; Kenney-Hunt, Jane P; Wolf, Jason B; Semenkovich, Clay F (Obesity (Silver Spring), 2011)
Although the current obesity epidemic is of environmental origin, there is substantial genetic variation in individual response to an obesogenic environment. In this study, we perform a genome-wide scan for quantitative trait loci (QTLs) affecting obesity per se, or an obese response to a high-fat diet in mice from the LG/J by SM/J Advanced Intercross (AI) Line (Wustl:LG,SM-G16). A total of 1,002 animals from 78 F₁₆ full sibships were weaned at 3 weeks of age and half of each litter placed on high- and low-fat diets. Animals remained on the diet until 20 weeks of age when they were necropsied and the weights of the reproductive, kidney, mesenteric, and inguinal fat depots were recorded. Effects on these phenotypes, along with total fat depot weight and carcass weight at necropsy, were mapped across the genome using 1,402 autosomal single-nucleotide polymorphism (SNP) markers. Haplotypes were reconstructed and additive, dominance, and imprinting genotype scores were derived every 1 cM along the F₁₆ map. Analysis was performed using a mixed model with additive, dominance, and imprinting genotype scores, their interactions with sex, diet, and with sex-by-diet as fixed effects and with family and its interaction with sex, diet, and sex-by-diet as random effects. We discovered 95 trait-specific QTLs mapping to 40 locations. Most QTLs had additive effects with dominance and imprinting effects occurring at two-thirds of the loci. Nearly every locus interacted with sex and/or diet in important ways demonstrating that gene effects are primarily context dependent, changing depending on sex and/or diet.
Keywords: Adipose Tissue; Adiposity; Animals; Body Weight; Diet; Epigenesis, Genetic; Female; Genome-Wide Association Study; Genomic Imprinting; Male; Mice; Obesity; Organ Size; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Disruptive TP53 mutation is associated with aggressive disease characteristics in an orthotopic murine model of oral tongue cancer. - Sano, Daisuke; Xie, Tong-Xin; Ow, Thomas J; Zhao, Mei; Pickering, Curtis R; Zhou, Ge; Sandulache, Vlad C; Wheeler, David A; Richard A Gibbs; Caulin, Carlos; Myers, Jeffrey N (Clin Cancer Res, 2011)
PURPOSE: To characterize tumor growth and metastatic potential in head and neck squamous cell carcinoma (HNSCC) cell lines in an orthotopic murine model of oral tongue cancer and to correlate TP53 mutation status with these findings. EXPERIMENTAL DESIGN: Cells from each of 48 HNSCC cell lines were orthotopically injected into the oral tongues of nude mice. Tumor volume, cervical lymph node metastasis, and mouse survival were recorded. Direct sequencing of the TP53 gene and Western blot analysis for the p53 protein after induction with 5-fluorouracil was conducted. Cell lines were categorized as either mutant TP53 or wild-type TP53, and lines with TP53 mutation were further categorized on the basis of type of mutation (disruptive or nondisruptive) and level of p53 protein expression. The behavior of tumors in these different groups was compared. RESULTS: These 48 HNSCC cell lines showed a wide range of behavior from highly aggressive and metastatic to no tumor formation. Mice injected with cells harboring disruptive TP53 mutations had faster tumor growth, greater incidence of cervical lymph node metastasis, and shorter survival than mice injected with cells lacking these mutations. CONCLUSIONS: HNSCC cell lines display a wide spectrum of behavior in an orthotopic model of oral cancer. Cell lines with disruptive TP53 mutations are more aggressive in this system, corroborating clinical reports that have linked these mutations to poor patient outcome.
Keywords: Animals; Carcinoma, Squamous Cell; Cell Line, Tumor; Disease Models, Animal; Genes, p53; Head and Neck Neoplasms; Humans; Male; Mice; Mice, Nude; Mutation; Squamous Cell Carcinoma of Head and Neck; Tongue Neoplasms; Transplantation, Heterologous; Tumor Suppressor Protein p53

Dissociation between APOC3 variants, hepatic triglyceride content and insulin resistance. - Kozlitina, Julia; Eric Boerwinkle; Cohen, Jonathan C; Hobbs, Helen H (Hepatology, 2011)
UNLABELLED: Nonalcoholic fatty liver disease (NAFLD) is an escalating health problem that is frequently associated with obesity and insulin resistance. The mechanistic relationship between NAFLD, obesity, and insulin resistance is not well understood. A nonsynonymous variant in patatin-like phospholipase domain containing 3 (rs738409, I148M) has been reproducibly associated with increased hepatic triglyceride content (HTGC) but has not been associated with either the body mass index (BMI) or indices of insulin resistance. Conversely, two sequence variants in apolipoprotein C3 (APOC3) that have been linked to hypertriglyceridemia (rs2854117 C > T and rs2854116 T > C) have recently been reported to be associated with both hepatic fat content and insulin resistance. Here we genotyped two APOC3 variants in 1228 African Americans, 843 European Americans and 426 Hispanics from a multiethnic population based study, the Dallas Heart Study and test for association with HTGC and homeostatic model of insulin resistance (HOMA-IR). We also examined the relationship between these two variants and HOMA-IR in the Atherosclerosis Risk in Communities (ARIC) study. No significant difference in hepatic fat content was found between carriers and noncarriers in the Dallas Heart Study. Neither APOC3 variant was associated with HOMA-IR in the Dallas Heart Study; this lack of association was confirmed in the ARIC study, even after the analysis was restricted to lean (BMI < 25 kg/m(2) ) individuals (n = 4399). CONCLUSION: Our data do not support a causal relationship between these two variants in APOC3 and either HTGC or insulin resistance in middle-aged men and women.
Keywords: Adult; Apolipoprotein C-III; Black or African American; Body Mass Index; Female; Gene Frequency; Genetic Variation; Genotype; Heterozygote; Hispanic or Latino; Humans; Insulin Resistance; Liver; Male; Middle Aged; Triglycerides; White People

The Drosophila melanogaster transcriptome by paired-end RNA sequencing. - Daines, Bryce; Wang, Hui; Wang, Liguo; Yumei Li; Yi Han; Emmert, David; Gelbart, William; Wang, Xia; Li, Wei; Richard A Gibbs; Rui Chen (Genome Res, 2011)
RNA-seq was used to generate an extensive map of the Drosophila melanogaster transcriptome by broad sampling of 10 developmental stages. In total, 142.2 million uniquely mapped 64-100-bp paired-end reads were generated on the Illumina GA II yielding 356× sequencing coverage. More than 95% of FlyBase genes and 90% of splicing junctions were observed. Modifications to 30% of FlyBase gene models were made by extension of untranslated regions, inclusion of novel exons, and identification of novel splicing events. A total of 319 novel transcripts were identified, representing a 2% increase over the current annotation. Alternate splicing was observed in 31% of D. melanogaster genes, a 38% increase over previous estimations, but significantly less than that observed in higher organisms. Much of this splicing is subtle such as tandem alternate splice sites.
Keywords: Alternative Splicing; Animals; Drosophila melanogaster; Female; Gene Expression Profiling; Genes, Y-Linked; Male; Molecular Sequence Annotation; Molecular Sequence Data; Oligonucleotide Array Sequence Analysis; Sequence Analysis, RNA

Exome capture sequencing identifies a novel mutation in BBS4. - Wang, Hui; Chen, Xianfeng; Dudinsky, Lynn; Patenia, Claire; Chen, Yiyun; Yumei Li; Wei, Yue; Abboud, Emad B; Al-Rajhi, Ali A; Lewis, Richard Alan; Lupski, James R; Mardon, Graeme; et al. (Mol Vis, 2011)
PURPOSE: Leber congenital amaurosis (LCA) is one of the most severe eye dystrophies characterized by severe vision loss at an early stage and accounts for approximately 5% of all retinal dystrophies. The purpose of this study was to identify a novel LCA disease allele or gene and to develop an approach combining genetic mapping with whole exome sequencing. METHODS: Three patients from King Khaled Eye Specialist Hospital (KKESH205) underwent whole genome single nucleotide polymorphism genotyping, and a single candidate region was identified. Taking advantage of next-generation high-throughput DNA sequencing technologies, whole exome capture sequencing was performed on patient KKESH205#7. Sanger direct sequencing was used during the validation step. The zebrafish model was used to examine the function of the mutant allele. RESULTS: A novel missense mutation in Bardet-Biedl syndrome 4 protein (BBS4) was identified in a consanguineous family from Saudi Arabia. This missense mutation in the fifth exon (c.253G>C;p.E85Q) of BBS4 is likely a disease-causing mutation as it segregates with the disease. The mutation is not found in the single nucleotide polymorphism (SNP) database, the 1000 Genomes Project, or matching normal controls. Functional analysis of this mutation in zebrafish indicates that the G253C allele is pathogenic. Coinjection of the G253C allele cannot rescue the mislocalization of rhodopsin in the retina when BBS4 is knocked down by morpholino injection. Immunofluorescence analysis in cell culture shows that this missense mutation in BBS4 does not cause obvious defects in protein expression or pericentriolar localization. CONCLUSIONS: This mutation likely mainly reduces or abolishes BBS4 function in the retina. Further studies of this allele will provide important insights concerning the pleiotropic nature of BBS4 function.
Keywords: Alleles; Animals; Base Sequence; Chromosome Mapping; Consanguinity; Exome; Exons; Female; Genotype; High-Throughput Nucleotide Sequencing; Humans; Infant; Leber Congenital Amaurosis; Male; Microtubule-Associated Proteins; Molecular Sequence Data; Mutation, Missense; Pedigree; Polymorphism, Single Nucleotide; Proteins; Retina; Rhodopsin; Saudi Arabia; Zebrafish

Familial thoracic aortic aneurysms and dissections: identification of a novel locus for stable aneurysms with a low risk for progression to aortic dissection. - Guo, Dong-chuan; Regalado, Ellen S; Minn, Charles; Tran-Fadulu, Van; Coney, Joshua; Cao, Jiumei; Wang, Min; Yu, Robert K; Estrera, Anthony L; Safi, Hazim J; Shete, Sanjay S; Milewicz, Dianna M (Circ Cardiovasc Genet, 2011)
BACKGROUND: Thoracic aortic aneurysms leading to acute aortic dissections are the major diseases that affect the thoracic aorta. Approximately 20% of patients with thoracic aortic aneurysms and dissections (TAAD) have a family history of TAAD, and these patients present younger with more rapidly enlarging aneurysms than patients without a family history of aortic disease. METHODS AND RESULTS: A large family with multiple members with TAAD inherited in an autosomal-dominant manner was identified. The ascending aortic aneurysms were associated with slow enlargement, a low risk of dissection, and decreased penetrance in women. Genome-wide linkage analysis was performed, and a novel locus on chromosome 12 was identified for the mutant gene causing disease in this family. Of the 12 male members who carry the disease-linked microsatellite haplotype, 9 had ascending aortic aneurysms with an average diameter of 4.7 cm at an average age of 52.4 years (range, 32 to 76 years) at the time of diagnosis; only 1 individual had progressed to acute aortic dissection, and no other members with aortic dissections were identified. Women harboring the disease-linked haplotype did not have thoracic aortic disease, including 1 aged 84 years. Sequencing of 9 genes within the critical interval at the chromosome 12 locus did not identify the mutant gene. CONCLUSIONS: Mapping a locus for ascending thoracic aortic aneurysms associated with a low risk of aortic dissection supports our hypothesis that genes leading to familial disease can be associated with less-aggressive thoracic aortic disease.
Keywords: Adult; Aged; Aged, 80 and over; Aorta; Aortic Aneurysm, Thoracic; Aortic Dissection; Chromosomes, Human, Pair 12; Disease Progression; Family; Female; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Haplotypes; Humans; Lod Score; Male; Middle Aged; Pedigree; Risk Factors; Sequence Analysis, DNA

Gastrointestinal microbiome signatures of pediatric patients with irritable bowel syndrome. - Saulnier, Delphine M; Riehle, Kevin; Mistretta, Toni-Ann; Diaz, Maria-Alejandra; Mandal, Debasmita; Raza, Sabeen; Weidler, Erica M; Qin, Xiang; Coarfa, Cristian; Milosavljevic, Aleksandar; Petrosino, Joseph F; Highlander, Sarah; et al. (Gastroenterology, 2011)
BACKGROUND & AIMS: The intestinal microbiomes of healthy children and pediatric patients with irritable bowel syndrome (IBS) are not well defined. Studies in adults have indicated that the gastrointestinal microbiota could be involved in IBS. METHODS: We analyzed 71 samples from 22 children with IBS (pediatric Rome III criteria) and 22 healthy children, ages 7-12 years, by 16S ribosomal RNA gene sequencing, with an average of 54,287 reads/stool sample (average 454 read length = 503 bases). Data were analyzed using phylogenetic-based clustering (Unifrac), or an operational taxonomic unit (OTU) approach using a supervised machine learning tool (randomForest). Most samples were also hybridized to a microarray that can detect 8741 bacterial taxa (16S rRNA PhyloChip). RESULTS: Microbiomes associated with pediatric IBS were characterized by a significantly greater percentage of the class γ-proteobacteria (0.07% vs 0.89% of total bacteria, respectively; P < .05); 1 prominent component of this group was Haemophilus parainfluenzae. Differences highlighted by 454 sequencing were confirmed by high-resolution PhyloChip analysis. Using supervised learning techniques, we were able to classify different subtypes of IBS with a success rate of 98.5%, using limited sets of discriminant bacterial species. A novel Ruminococcus-like microbe was associated with IBS, indicating the potential utility of microbe discovery for gastrointestinal disorders. A greater frequency of pain correlated with an increased abundance of several bacterial taxa from the genus Alistipes. CONCLUSIONS: Using 16S metagenomics by PhyloChip DNA hybridization and deep 454 pyrosequencing, we associated specific microbiome signatures with pediatric IBS. These findings indicate the important association between gastrointestinal microbes and IBS in children; these approaches might be used in diagnosis of functional bowel disorders in pediatric patients.
Keywords: Abdominal Pain; Case-Control Studies; Child; DNA Probes; Female; Gastrointestinal Tract; Haemophilus parainfluenzae; Humans; Incidence; Irritable Bowel Syndrome; Male; Metagenome; Phenotype; Phylogeny; RNA, Ribosomal, 16S; Ruminococcus

Genetical genomics of Th1 and Th2 immune response in a baboon model of atherosclerosis risk factors. - Vinson, A; Curran, J E; Johnson, M P; Dyer, T D; Moses, E K; Blangero, J; Cox, L A; Rogers, J; Havill, L M; VandeBerg, J L; Mahaney, M C (Atherosclerosis, 2011)
OBJECTIVE: CD4(+) T-cells mediate inflammation in atherosclerosis, but additive genetic effects on associated pathways of Th1 and Th2 immune response have not been described. We sought to characterize heritability, pleiotropy, and QTL effects on the expression of genes implicated in Th1 and Th2 immune response in a baboon model of risk factors for atherosclerosis. METHODS: We employed a maximum likelihood-based variance decomposition approach to estimate additive genetic effects on transcript levels generated from a gene expression profile of lymphocytes in 499 pedigreed baboons maintained on a basal diet. Transcript levels for 57 genes implicated in Th1 and Th2 immune response were selected for analysis based on significant heritability in this profile. Multipoint whole genome scans were conducted on heritable transcript levels to localize QTLs influencing these measures. To evaluate pleiotropic effects on transcript levels, we estimated genetic and phenotypic correlations among transcript measures, and assessed their correspondence using a Mantel test. Network analysis using GeneGo's MetaCore™ software was conducted to characterize known interaction among coded proteins. RESULTS: Heritabilities for candidate gene transcript levels ranged from 0.092-0.786 (median h(2)=0.278, P=4.72×10(-4)). Linkage analyses yielded significant evidence (LOD≥2.73) for 14 eQTLs (LOD score range 2.76-14.87, genome-wide P=4.9×10(-2)-1.03×10(-14)). Estimates of genetic correlation supported shared additive genetic effects incorporating all 57 transcripts (null hypothesis of ρ(G)=0 rejected at FDR≤0.05 for 522 of 1596 estimates), and accounted for most of the observed phenotypic correlation among transcripts (Mantel test, r([ρP],)([ρG])=0.781, P<0.0001). Network analysis revealed direct interactions among 54 of the 57 coded proteins. CONCLUSIONS: We conclude that major genetic effects influence expression levels of multiple genes implicated in Th1 and Th2 immune response. Additionally, we find that expression levels of these candidate genes are characterized by extensive pleiotropy, consistent with known interaction among their coded proteins, many of which are independently associated with atherosclerosis.
Keywords: Animals; Atherosclerosis; Disease Models, Animal; Female; Gene Expression Profiling; Gene Regulatory Networks; Genetic Pleiotropy; Genetic Predisposition to Disease; Heredity; Inflammation; Male; Models, Genetic; Papio hamadryas; Phenotype; Quantitative Trait Loci; Risk Assessment; Risk Factors; Th1 Cells; Th2 Cells; Transcription, Genetic

Genome-wide association analysis of incident coronary heart disease (CHD) in African Americans: a short report. - Barbalic, Maja; Reiner, Alex P; Wu, Chunyuan; Hixson, James E; Franceschini, Nora; Eaton, Charles B; Heiss, Gerardo; Couper, David; Mosley, Thomas; Eric Boerwinkle (PLoS Genet, 2011)
African Americans have the highest rate of mortality due to coronary heart disease (CHD). Although multiple loci have been identified influencing CHD risk in European-Americans using a genome-wide association (GWAS) approach, no GWAS of incident CHD has been reported for African Americans. We performed a GWAS for incident CHD events collected during 19 years of follow-up in 2,905 African Americans from the Atherosclerosis Risk in Communities (ARIC) study. We identified a genome-wide significant SNP (rs1859023, MAF = 31%) located at 7q21 near the PFTK1 gene (HR = 0.57, 95% CI 0.46 to 0.69, p = 1.86×10(-08)), which replicated in an independent sample of over 8,000 African American women from the Women's Health Initiative (WHI) (HR = 0.81, 95% CI 0.70 to 0.93, p = 0.005). PFTK1 encodes a serine/threonine-protein kinase, PFTAIRE-1, that acts as a cyclin-dependent kinase regulating cell cycle progression and cell proliferation. This is the first finding of incident CHD locus identified by GWAS in African Americans.
Keywords: Aged; Black or African American; Coronary Disease; Female; Gene Expression Regulation; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genome-wide association studies of cerebral white matter lesion burden: the CHARGE consortium. - Fornage, Myriam; Debette, Stephanie; Bis, Joshua C; Schmidt, Helena; Ikram, M Arfan; Dufouil, Carole; Sigurdsson, Sigurdur; Lumley, Thomas; DeStefano, Anita L; Fazekas, Franz; Vrooman, Henri A; Shibata, Dean K; et al. (Ann Neurol, 2011)
OBJECTIVE: White matter hyperintensities (WMHs) detectable by magnetic resonance imaging are part of the spectrum of vascular injury associated with aging of the brain and are thought to reflect ischemic damage to the small deep cerebral vessels. WMHs are associated with an increased risk of cognitive and motor dysfunction, dementia, depression, and stroke. Despite a significant heritability, few genetic loci influencing WMH burden have been identified. METHODS: We performed a meta-analysis of genome-wide association studies (GWASs) for WMH burden in 9,361 stroke-free individuals of European descent from 7 community-based cohorts. Significant findings were tested for replication in 3,024 individuals from 2 additional cohorts. RESULTS: We identified 6 novel risk-associated single nucleotide polymorphisms (SNPs) in 1 locus on chromosome 17q25 encompassing 6 known genes including WBP2, TRIM65, TRIM47, MRPL38, FBF1, and ACOX1. The most significant association was for rs3744028 (p(discovery) = 4.0 × 10(-9) ; p(replication) = 1.3 × 10(-7) ; p(combined) = 4.0 × 10(-15) ). Other SNPs in this region also reaching genome-wide significance were rs9894383 (p = 5.3 × 10(-9) ), rs11869977 (p = 5.7 × 10(-9) ), rs936393 (p = 6.8 × 10(-9) ), rs3744017 (p = 7.3 × 10(-9) ), and rs1055129 (p = 4.1 × 10(-8) ). Variant alleles at these loci conferred a small increase in WMH burden (4-8% of the overall mean WMH burden in the sample). INTERPRETATION: This large GWAS of WMH burden in community-based cohorts of individuals of European descent identifies a novel locus on chromosome 17. Further characterization of this locus may provide novel insights into the pathogenesis of cerebral WMH.
Keywords: Aged; Aged, 80 and over; Cerebral Cortex; Chromosomes, Human, Pair 17; Cognition Disorders; Cohort Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Movement Disorders; Nerve Fibers, Myelinated; Polymorphism, Single Nucleotide; Residence Characteristics; RNA, Messenger; White People

Genome-wide high-density SNP linkage search for glioma susceptibility loci: results from the Gliogene Consortium. - Shete, Sanjay; Lau, Ching C; Houlston, Richard S; Claus, Elizabeth B; Barnholtz-Sloan, Jill; Lai, Rose; Il'yasova, Dora; Schildkraut, Joellen; Sadetzki, Siegal; Johansen, Christoffer; Bernstein, Jonine L; Olson, Sara H; et al. (Cancer Res, 2011)
Gliomas, which generally have a poor prognosis, are the most common primary malignant brain tumors in adults. Recent genome-wide association studies have shown that inherited susceptibility plays a role in the development of glioma. Although first-degree relatives of patients exhibit a two-fold increased risk of glioma, the search for susceptibility loci in familial forms of the disease has been challenging because the disease is relatively rare, fatal, and heterogeneous, making it difficult to collect sufficient biosamples from families for statistical power. To address this challenge, the Genetic Epidemiology of Glioma International Consortium (Gliogene) was formed to collect DNA samples from families with two or more cases of histologically confirmed glioma. In this study, we present results obtained from 46 U.S. families in which multipoint linkage analyses were undertaken using nonparametric (model-free) methods. After removal of high linkage disequilibrium single-nucleotide polymorphism, we obtained a maximum nonparametric linkage score (NPL) of 3.39 (P = 0.0005) at 17q12-21.32 and the Z-score of 4.20 (P = 0.000007). To replicate our findings, we genotyped 29 independent U.S. families and obtained a maximum NPL score of 1.26 (P = 0.008) and the Z-score of 1.47 (P = 0.035). Accounting for the genetic heterogeneity using the ordered subset analysis approach, the combined analyses of 75 families resulted in a maximum NPL score of 3.81 (P = 0.00001). The genomic regions we have implicated in this study may offer novel insights into glioma susceptibility, focusing future work to identify genes that cause familial glioma.
Keywords: Adolescent; Adult; Aged; Brain Neoplasms; Child; Chromosome Mapping; Family Health; Female; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Glioma; Humans; Linkage Disequilibrium; Lod Score; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; United States; Young Adult

Global DNA methylation and risk of subclinical atherosclerosis in young adults: the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) study. - Bressler, Jan; Shimmin, Lawrence C; Eric Boerwinkle; Hixson, James E (Atherosclerosis, 2011)
OBJECTIVE: The association between hepatic global DNA methylation measured using pyrosequencing technology and the risk of subclinical atherosclerosis was examined in the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) study. PDAY is a bi-racial investigation of the natural history of atherosclerosis and its risk factors involving 3013 individuals aged 15-34 years who underwent autopsy after dying of unrelated causes in 1987-1994. METHODS: Raised atherosclerotic lesions were defined as the sum of the percentages of intimal surface area detected in the right coronary artery and left half of the abdominal and thoracic aorta harboring fibrous plaques, complicated lesions, and calcified lesions during a postmortem pathological examination. To conduct the case-control study, 300 cases selected with the highest raised lesion scores were paired with 300 controls without raised lesions after matching for age, race, and gender. RESULTS: Global DNA methylation was not associated with disease risk in the study population considered as a whole using conditional logistic regression models to analyze matched pairs. Since the estimation of the risk of atherosclerosis associated with inter-individual variation in DNA methylation was similar if unconditional logistic regression was used, subgroup analyses were carried out after adjusting for matching variables. A modest association with methylation levels below the median value was found in white but not in African-American study participants (odds ratio = 1.59, 95% confidence interval = 1.02-2.49, p = 0.04). CONCLUSIONS: Hepatic global DNA methylation does not appear to be a definitive determinant of atherosclerosis burden in a postmortem sample of young adults.
Keywords: Adolescent; Adult; Age Factors; Aorta, Abdominal; Aorta, Thoracic; Aortic Diseases; Asymptomatic Diseases; Atherosclerosis; Autopsy; Black or African American; Case-Control Studies; Coronary Artery Disease; Coronary Vessels; DNA; DNA Methylation; Female; Humans; Liver; Logistic Models; Male; Matched-Pair Analysis; Odds Ratio; Plaque, Atherosclerotic; Risk Assessment; Risk Factors; Texas; White People; Young Adult

Heritability of alveolar bone loss from periodontal disease in a baboon population: a pilot study. - Miley, D Douglas; Baumgartner, Mark H; Cheverud, James M; Roseman, Charles C; Jeffrey Rogers; McLeod, Dwight E; Reyes, Elio; Hildebolt, Charles F (J Periodontol, 2011)
BACKGROUND: Reports from studies of twins, disease aggregation in families, animal models for periodontal disease, and various genetic-analysis studies have determined that genetics plays a role in the susceptibility to periodontal disease. The purpose of this pilot study is to evaluate the effect of genetics on periodontal disease by evaluating the heritability of alveolar bone loss in a captive baboon population. METHODS: A collection of baboon skulls from a pedigreed colony (for which scientists and veterinarians maintain complete genealogic and veterinary records) was obtained from the Southwest National Primate Research Center, San Antonio, Texas and used in this pilot study. Measurements of alveolar bone loss were performed on 390 dry baboon skulls. A periodontal probe was used to measure alveolar bone loss. Maximum likelihood methods (designed to handle complex genealogies) were used to determine the heritability of alveolar bone loss. This software used known pedigrees in the captive baboon sample and tested the relationship between pairwise kinship and alveolar bone loss data to determine the heritability of alveolar bone loss from periodontal disease. RESULTS: Genetic data were available for 347 of the 390 specimens. Using age and sex as covariates, genetic analysis indicated a heritability of 35% (standard error = 20%; P = 0.01). Although gender was not a significant factor in periodontal disease (P = 0.96), age was highly significantly associated with periodontal disease (P <0.0001). CONCLUSIONS: In this pilot study, analysis of alveolar bone loss measurements from captive baboons indicates that bone loss increases with age and that a portion of periodontal disease risk may be caused by genetic variance. These findings provide evidence that periodontal disease is heritable in captive baboons and indicate that a larger, more-detailed study is warranted.
Keywords: Age Factors; Alveolar Bone Loss; Animals; Disease Models, Animal; Female; Genetic Predisposition to Disease; Male; Mandible; Papio; Periodontal Diseases; Pilot Projects

High-resolution identity by descent mapping uncovers the genetic basis for blood pressure differences between spontaneously hypertensive rat lines. - Bell, Rebecca; Herring, Stacy M; Gokul, Nisha; Monita, Monique; Grove, Megan L; Eric Boerwinkle; Doris, Peter A (Circ Cardiovasc Genet, 2011)
BACKGROUND: The recent development of a large panel of genome-wide single nucleotide polymorphisms (SNPs) provides the opportunity to examine genetic relationships between distinct SHR lines that share hypertension but differ in their susceptibility to hypertensive end-organ disease. METHODS AND RESULTS: We compared genotypes at nearly 10,000 SNPs obtained for the hypertension end-organ injury-susceptible spontaneously hypertensive rat (SHR)-A3 (SHRSP, SHR-stroke prone) line and the injury-resistant SHR-B2 line. This revealed that that the 2 lines were genetically identical by descent (IBD) across 86.6% of the genome. Areas of the genome that were not IBD were distributed across 19 of the 20 autosomes and the X chromosome. A block structure of non-IBD comprising a total of 121 haplotype blocks was formed by clustering of SNPs inherited from different ancestors. To test the null hypothesis that distinct SHR lines share a common set of hypertension susceptibility alleles, we compared blood pressure in adult SHR animals from both lines and their F1 and F2 progeny using telemetry. In 16- to 18-week-old animals fed a normal diet, systolic blood pressure (SBP, mm Hg) in SHR-A3 was 205.7 ± 3.86 (mean ± SEM, n = 26), whereas in similar SHR-B2 animals, SBP was 186.7 ± 2.53 (n = 20). In F1 and F2 animals, SBP was 188.2 ± 4.23 (n = 19) and 185.6 ± 1.1 (n = 211), respectively (P<10(-6), ANOVA). To identify non-IBD haplotype blocks contributing to blood pressure differences between these SHR lines, we developed a high-throughput SNP genotyping system to genotype SNPs marking non-IBD blocks. We mapped a single non-IBD block on chromosome 17 extending over <10 Mb, at which SHR-A3 alleles significantly elevate blood pressure compared with SHR-B2. CONCLUSIONS: Thus hypertension in SHR-A3 and -B2 appears to arise from an overlapping set of susceptibility alleles, with SHR-A3 possessing an additional hypertension locus that contributes to further increase blood pressure.
Keywords: Animals; Blood Pressure; Chromosome Mapping; Female; Gene Expression; Genetic Predisposition to Disease; Genotype; Haplotypes; Lod Score; Male; Molecular Sequence Data; Polymorphism, Single Nucleotide; Rats; Rats, Inbred SHR

Immunoglobulin locus associates with serum IgG levels and albuminuria. - Herring, Stacy M; Gokul, Nisha; Monita, Monique; Bell, Rebecca; Eric Boerwinkle; Wenderfer, Scott E; Braun, Michael C; Doris, Peter A (J Am Soc Nephrol, 2011)
The interaction between IgG and Fc-γ receptors in glomeruli contributes to the development of several types of proteinuric glomerular disease, but the involvement of immunological mechanisms in hypertensive renal injury is incompletely understood. Here, we investigated serum IgG levels in SHR-A3 rats, which develop hypertensive injury, and compared them with the injury-resistant SHR-B2 line. At 18 weeks old, SHR-A3 rats had serum total IgG levels nearly twice those of SHR-B2 rats, although subclass IgG2b was undetectable in SHR-A3 rats compared with mean levels (± SEM) of 80.7 ± 12.8 mg/dl (18 weeks) and 116.6 ± 19.0 mg/dl (30 weeks) in SHR-B2 rats. In addition, these two strains had significantly different serum levels of IgG1, IgG2a, and IgG2c; differences persisted at 30 weeks for all subclasses except IgG2a. Genetic mapping revealed that a locus on chromosome 6 linked to IgG subclass levels that affected IgG1, IgG2b, and IgG2c but not IgG2a. The mapped haplotype block contains IgH, suggesting regulation of three of four serum IgG subclass levels in cis. Resequencing revealed variation in the sequence of the Fc portion of the IgG heavy chain, which predicts important functional changes. To examine whether there is any relationship between this haplotype block and susceptibility to renal injury, we examined the effect of SHR-A3 and SHR-B2 alleles at this block on albumin excretion in an F2 intercross. Albuminuria doubled with inheritance of SHR-A3 alleles. In summary, allelic variation in IgH or nearby genes may modulate the susceptibility to hypertensive renal injury in SHR-A3 rats.
Keywords: Albuminuria; Animals; Chromosome Mapping; Female; Haplotypes; Hypertension; Immunoglobulin G; Immunoglobulin Heavy Chains; Male; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Rats; Rats, Inbred SHR

The importance of context to the genetic architecture of diabetes-related traits is revealed in a genome-wide scan of a LG/J × SM/J murine model. - Lawson, Heather A; Lee, Arthur; Fawcett, Gloria L; Wang, Bing; Pletscher, L Susan; Maxwell, Taylor J; Ehrich, Thomas H; Kenney-Hunt, Jane P; Wolf, Jason B; Semenkovich, Clay F; Cheverud, James M (Mamm Genome, 2011)
Variations in diabetic phenotypes are caused by complex interactions of genetic effects, environmental factors, and the interplay between the two. We tease apart these complex interactions by examining genome-wide genetic and epigenetic effects on diabetes-related traits among different sex, diet, and sex-by-diet cohorts in a Mus musculus model. We conducted a genome-wide scan for quantitative trait loci that affect serum glucose and insulin levels and response to glucose stress in an F(16) Advanced Intercross Line of the LG/J and SM/J intercross (Wustl:LG,SM-G16). Half of each sibship was fed a high-fat diet and half was fed a relatively low-fat diet. Context-dependent genetic (additive and dominance) and epigenetic (parent-of-origin imprinting) effects were characterized by partitioning animals into sex, diet, and sex-by-diet cohorts. We found that different cohorts often have unique genetic effects at the same loci, and that genetic signals can be masked or erroneously assigned to specific cohorts if they are not considered individually. Our data demonstrate that the effects of genes on complex trait variation are highly context-dependent and that the same genomic sequence can affect traits differently depending on an individual's sex and/or dietary environment. Our results have important implications for studies of complex traits in humans.
Keywords: Animals; Animals, Outbred Strains; Blood Glucose; Diabetes Mellitus, Type 2; Disease Models, Animal; Female; Genome-Wide Association Study; Humans; Hybridization, Genetic; Insulin; Male; Mice; Quantitative Trait Loci

Interaction of folate intake and the paraoxonase Q192R polymorphism with risk of incident coronary heart disease and ischemic stroke: the atherosclerosis risk in communities study. - Luu, Hung N; Kingah, Pascal L; North, Kari; Eric Boerwinkle; Volcik, Kelly A (Ann Epidemiol, 2011)
PURPOSE: To investigate the potential interaction between folate intake and the paraoxonase 1 (PON1) Q192R polymorphism with the risk of incident coronary heart disease (CHD) and ischemic stroke in the Atherosclerosis Risk in Communities study, a population-based prospective cohort of cardiovascular disease in 15,792 white and African-American subject. METHODS: Race-stratified Cox proportional hazards models were performed to examine the interaction between folate intake and the PON1 Q192R polymorphism. RESULTS: A significant inverse association between folate intake and risk of incident CHD among white subjects was found (hazard rate ratio, 1.30; 95% confidence interval, 1.09-1.56; P = .004; folate intake ≤155 μg vs ≥279 μg, reference group). An interaction effect was observed between the dominant genetic model and folate intake with regards to incident ischemic stroke in white subjects (hazard rate ratio, 0.68; 95% confidence interval, 0.91-0.99; and 1.24 from 1st-4th quartile, respectively; P-trend = .05). CONCLUSIONS: There was an interaction between folate intake and PON1 Q192 polymorphism with regard to the risk of ischemic stroke in white subjects. Future studies should investigate the interaction between additional polymorphisms within the PON1 gene and genetic variants in other folate metabolizing genes with folate intake on the risk of incident CHD and stroke.
Keywords: Adult; Aryldialkylphosphatase; Atherosclerosis; Black or African American; Cohort Studies; Coronary Disease; Female; Folic Acid; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies; Stroke; United States; White People

Kinda baboons (Papio kindae) and grayfoot chacma baboons (P. ursinus griseipes) hybridize in the Kafue river valley, Zambia. - Jolly, C J; Burrell, A S; Phillips-Conroy, J E; Bergey, C; Rogers, J (Am J Primatol, 2011)
The ranges of small kinda (Papio kindae) and much larger grayfooted chacma (P. ursinus griseipes) baboons adjoin in the Kafue National Park, Zambia. In a visual survey of baboons at 48 sites in the Kafue River drainage we found that, contrary to previous reports, groups at the species interface near the town of Ngoma are phenotypically diverse and presumably formed by multigenerational hybridization. Mitochondrial and/or Y-chromosome genetic markers from fecal samples (N=164) collected at 29 sites support this conclusion. Groups with phenotypic signs of a history of hybridization also had taxon-specific mitochondria and Y-haplotypes from both parental species. Although the distribution of mitochondrial haplotypes largely mirrored that of external phenotypes, a significant proportion of male specimens from grayfoot as well as hybrid groups carried kinda Y-chromosomes, and kinda Y-chromosomes were involved in all observed cases of mitochondrial/Y-chromosome discordance. These observations are consistent with, though they do not prove, a population history in which the range of chacmas and the hybrid zone have advanced at the expense of the kinda range. They also suggest that, unexpectedly, kinda male×chacma female matings are much more common than the reciprocal cross in the ancestry of hybrids. We suggest that distinctive male kinda behavior and the "juvenile" appearance of kinda baboons of both sexes, perhaps combined with obstetric difficulties of a small kinda female carrying the large offspring of a chacma male, may account for this bias.
Keywords: Animals; Animals, Wild; DNA, Mitochondrial; Female; Genes, Y-Linked; Genetic Markers; Genetic Variation; Haplotypes; Hybridization, Genetic; Male; Papio; Papio ursinus; Phenotype; Sexual Behavior, Animal; Zambia

Oligogenic heterozygosity in individuals with high-functioning autism spectrum disorders. - Schaaf, Christian P; Aniko Sabo; Sakai, Yasunari; Crosby, Jacy; Donna M Muzny; Hawes, Alicia; Lewis, Lora; Akbar, Humeira; Varghese, Robin; Eric Boerwinkle; Richard A Gibbs; Zoghbi, Huda Y (Hum Mol Genet, 2011)
Autism spectrum disorders (ASDs) are a heterogeneous group of neuro-developmental disorders. While significant progress has been made in the identification of genes and copy number variants associated with syndromic autism, little is known to date about the etiology of idiopathic non-syndromic autism. Sanger sequencing of 21 known autism susceptibility genes in 339 individuals with high-functioning, idiopathic ASD revealed de novo mutations in at least one of these genes in 6 of 339 probands (1.8%). Additionally, multiple events of oligogenic heterozygosity were seen, affecting 23 of 339 probands (6.8%). Screening of a control population for novel coding variants in CACNA1C, CDKL5, HOXA1, SHANK3, TSC1, TSC2 and UBE3A by the same sequencing technology revealed that controls were carriers of oligogenic heterozygous events at significantly (P < 0.01) lower rate, suggesting oligogenic heterozygosity as a new potential mechanism in the pathogenesis of ASDs.
Keywords: Adolescent; Child; Child Development Disorders, Pervasive; Child, Preschool; Genetic Predisposition to Disease; Heterozygote; Humans; Male; Mutation

A preliminary report on the feeding of cynomolgus monkeys (Macaca fascicularis) with a high-sugar high-fat diet for 33 weeks. - Mubiru, James N; Garcia-Forey, Magdalena; Higgins, Paul B; Hemmat, Peggah; Cavazos, Nicole E; Dick, Edward J; Owston, Michael A; Bauer, Cassondra A; Shade, Robert E; Comuzzie, Anthony G; Jeffrey Rogers (J Med Primatol, 2011)
BACKGROUND: The metabolic syndrome is common in populations exposed to a typical Western diet. There is a lack of an animal model that mimics this condition. METHODS: We fed 15 cynomolgus monkeys ad libitum a high-sugar high-fat (HSHF) diet for 33 weeks. Body weight, body composition, serum lipids, and insulin were measured at baseline and at 33 weeks. RESULTS: The animals tolerated the HSHF diet very well. In the intervention group, total serum cholesterol and low-density lipoprotein cholesterol were 3- and 5-fold higher, respectively, at 33 weeks as compared with their baseline levels. Serum high-density lipoprotein cholesterol and triglycerides were not significantly affected. Dual-energy X-ray absorptiometry (DXA) analysis of the intervention group indicated that the trunk fat mass increased by 187% during this period. CONCLUSIONS: Cynomolgus monkeys should be a useful model for investigating the interactions of diet and other factors such as genetics in the development of the metabolic syndrome.
Keywords: Absorptiometry, Photon; Animals; Biomarkers; Blood Glucose; Body Composition; Body Weight; Cholesterol; Dietary Carbohydrates; Dietary Fats; Energy Metabolism; Insulin; Macaca fascicularis; Male; Metabolic Syndrome; Models, Animal; Triglycerides

Recurrent chromosome 16p13.1 duplications are a risk factor for aortic dissections. - Kuang, Shao-Qing; Guo, Dong-chuan; Prakash, Siddharth K; McDonald, Merry-Lynn N; Johnson, Ralph J; Wang, Min; Regalado, Ellen S; Russell, Ludivine; Cao, Jiu-Mei; Kwartler, Callie; Fraivillig, Kurt; Coselli, Joseph S; et al. (PLoS Genet, 2011)
Chromosomal deletions or reciprocal duplications of the 16p13.1 region have been implicated in a variety of neuropsychiatric disorders such as autism, schizophrenia, epilepsies, and attention-deficit hyperactivity disorder (ADHD). In this study, we investigated the association of recurrent genomic copy number variants (CNVs) with thoracic aortic aneurysms and dissections (TAAD). By using SNP arrays to screen and comparative genomic hybridization microarrays to validate, we identified 16p13.1 duplications in 8 out of 765 patients of European descent with adult-onset TAAD compared with 4 of 4,569 controls matched for ethnicity (P = 5.0 × 10⁻⁵, OR = 12.2). The findings were replicated in an independent cohort of 467 patients of European descent with TAAD (P = 0.005, OR = 14.7). Patients with 16p13.1 duplications were more likely to harbor a second rare CNV (P = 0.012) and to present with aortic dissections (P = 0.010) than patients without duplications. Duplications of 16p13.1 were identified in 2 of 130 patients with familial TAAD, but the duplications did not segregate with TAAD in the families. MYH11, a gene known to predispose to TAAD, lies in the duplicated region of 16p13.1, and increased MYH11 expression was found in aortic tissues from TAAD patients with 16p13.1 duplications compared with control aortas. These data suggest chromosome 16p13.1 duplications confer a risk for TAAD in addition to the established risk for neuropsychiatric disorders. It also indicates that recurrent CNVs may predispose to disorders involving more than one organ system, an observation critical to the understanding of the role of recurrent CNVs in human disease and a finding that may be common to other recurrent CNVs involving multiple genes.
Keywords: Adult; Aged; Aorta; Aortic Aneurysm, Thoracic; Aortic Dissection; Case-Control Studies; Chromosome Duplication; Chromosomes, Human, Pair 16; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Myosin Heavy Chains; Pedigree; Phenotype; Risk Factors

Whole-exome sequencing identifies compound heterozygous mutations in WDR62 in siblings with recurrent polymicrogyria. - Murdock, David R; Clark, Gary D; Bainbridge, Matthew N; Newsham, Irene; Wu, Yuan-Qing; Donna M Muzny; Cheung, Sau Wai; Richard A Gibbs; Ramocki, Melissa B (Am J Med Genet A, 2011)
Polymicrogyria is a disorder of neuronal development resulting in structurally abnormal cerebral hemispheres characterized by over-folding and abnormal lamination of the cerebral cortex. Polymicrogyria is frequently associated with severe neurologic deficits including intellectual disability, motor problems, and epilepsy. There are acquired and genetic causes of polymicrogyria, but most patients with a presumed genetic etiology lack a specific diagnosis. Here we report using whole-exome sequencing to identify compound heterozygous mutations in the WD repeat domain 62 (WDR62) gene as the cause of recurrent polymicrogyria in a sibling pair. Sanger sequencing confirmed that the siblings both inherited 1-bp (maternal allele) and 2-bp (paternal allele) frameshift deletions, which predict premature truncation of WDR62, a protein that has a role in early cortical development. The probands are from a non-consanguineous family of Northern European descent, suggesting that autosomal recessive PMG due to compound heterozygous mutation of WDR62 might be a relatively common cause of PMG in the population. Further studies to identify mutation frequency in the population are needed.
Keywords: Abnormalities, Multiple; Adult; Base Sequence; Cell Cycle Proteins; Child; Craniofacial Abnormalities; Exome; Female; Frameshift Mutation; Genetic Testing; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Magnetic Resonance Imaging; Male; Malformations of Cortical Development; Mutation; Nerve Tissue Proteins; Sequence Analysis, DNA; Sequence Deletion; Siblings

Whole-genome sequencing for optimized patient management. - Bainbridge, Matthew N; Wiszniewski, Wojciech; Murdock, David R; Friedman, Jennifer; Gonzaga-Jauregui, Claudia; Newsham, Irene; Reid, Jeffrey G; Fink, John K; Morgan, Margaret B; Marie-Claude Gingras; Donna M Muzny; Hoang, Linh D; et al. (Sci Transl Med, 2011)
Whole-genome sequencing of patient DNA can facilitate diagnosis of a disease, but its potential for guiding treatment has been under-realized. We interrogated the complete genome sequences of a 14-year-old fraternal twin pair diagnosed with dopa (3,4-dihydroxyphenylalanine)-responsive dystonia (DRD; Mendelian Inheritance in Man #128230). DRD is a genetically heterogeneous and clinically complex movement disorder that is usually treated with l-dopa, a precursor of the neurotransmitter dopamine. Whole-genome sequencing identified compound heterozygous mutations in the SPR gene encoding sepiapterin reductase. Disruption of SPR causes a decrease in tetrahydrobiopterin, a cofactor required for the hydroxylase enzymes that synthesize the neurotransmitters dopamine and serotonin. Supplementation of l-dopa therapy with 5-hydroxytryptophan, a serotonin precursor, resulted in clinical improvements in both twins.
Keywords: Adolescent; Decision Making; Dystonic Disorders; Female; Genome, Human; Humans; Levodopa; Male; Patient Care; Pedigree; Sequence Analysis, DNA; Treatment Outcome; Twins, Dizygotic

Amygdalar and hippocampal substrates of anxious temperament differ in their heritability. - Oler, Jonathan A; Fox, Andrew S; Shelton, Steven E; Jeffrey Rogers; Dyer, Thomas D; Davidson, Richard J; Shelledy, Wendy; Oakes, Terrence R; Blangero, John; Kalin, Ned H (Nature, 2010)
Anxious temperament (AT) in human and non-human primates is a trait-like phenotype evident early in life that is characterized by increased behavioural and physiological reactivity to mildly threatening stimuli. Studies in children demonstrate that AT is an important risk factor for the later development of anxiety disorders, depression and comorbid substance abuse. Despite its importance as an early predictor of psychopathology, little is known about the factors that predispose vulnerable children to develop AT and the brain systems that underlie its expression. To characterize the neural circuitry associated with AT and the extent to which the function of this circuit is heritable, we studied a large sample of rhesus monkeys phenotyped for AT. Using 238 young monkeys from a multigenerational single-family pedigree, we simultaneously assessed brain metabolic activity and AT while monkeys were exposed to the relevant ethological condition that elicits the phenotype. High-resolution (18)F-labelled deoxyglucose positron-emission tomography (FDG-PET) was selected as the imaging modality because it provides semi-quantitative indices of absolute glucose metabolic rate, allows for simultaneous measurement of behaviour and brain activity, and has a time course suited for assessing temperament-associated sustained brain responses. Here we demonstrate that the central nucleus region of the amygdala and the anterior hippocampus are key components of the neural circuit predictive of AT. We also show significant heritability of the AT phenotype by using quantitative genetic analysis. Additionally, using voxelwise analyses, we reveal significant heritability of metabolic activity in AT-associated hippocampal regions. However, activity in the amygdala region predictive of AT is not significantly heritable. Furthermore, the heritabilities of the hippocampal and amygdala regions significantly differ from each other. Even though these structures are closely linked, the results suggest differential influences of genes and environment on how these brain regions mediate AT and the ongoing risk of developing anxiety and depression.
Keywords: Amygdala; Animals; Anxiety; Depression; Female; Freezing Reaction, Cataleptic; Genetic Predisposition to Disease; Glucose; Heredity; Hippocampus; Macaca mulatta; Male; Models, Animal; Neural Pathways; Pedigree; Phenotype; Positron-Emission Tomography; Stress, Psychological; Temperament; Temporal Lobe; Vocalization, Animal

Association of glycemic index and glycemic load with risk of incident coronary heart disease among Whites and African Americans with and without type 2 diabetes: the Atherosclerosis Risk in Communities study. - Hardy, Dale S; Hoelscher, Deanna M; Aragaki, Corinne; Stevens, June; Steffen, Lyn M; Pankow, James S; Eric Boerwinkle (Ann Epidemiol, 2010)
PURPOSE: In this study we examined whether high glycemic index (GI) and glycemic load (GL) diets are associated with increased risk of developing coronary heart disease (CHD) in Whites and African Americans with and without type 2 diabetes. METHODS: Data on 13,051 patients ages 45 to 64 years from the Atherosclerosis Risk in Communities study were analyzed. The ARIC food frequency questionnaire baseline data provided GI and GL indices. A propensity score was created to estimate the effect of a patient's covariates on energy-adjusted GI or GL. During a maximum of 17 years of follow-up, 1683 cases of CHD (371 with diabetes and 1312 without diabetes) were recorded. RESULTS: For every 5-units increase in GI, there was a 1.16-fold (95% confidence interval [95% CI], 1.01-1.33) increased risk of incident CHD in African Americans. For every 30-units increase in GL, there was a 1.11-fold (95% CI, 1.01-1.21) increased risk of incident CHD in Whites. High GL was an especially important CHD risk factor for Whites without diabetes (per 30-units increase; hazard ratio, 1.14; 95% CI, 1.02-1.26). However, these relationships were not seen in individuals with diabetes. CONCLUSIONS: Nutritional advice to reduce the GI and GL in diets of African Americans and Whites subjects (without diabetes) may play a role in reducing CHD risk.
Keywords: Black or African American; Coronary Disease; Diabetes Mellitus, Type 2; Diet; Female; Follow-Up Studies; Glycemic Index; Humans; Male; Middle Aged; Risk Assessment; Surveys and Questionnaires; White People

Associations between dietary patterns and flow cytometry-measured biomarkers of inflammation and cellular activation in the Atherosclerosis Risk in Communities (ARIC) Carotid Artery MRI Study. - Nettleton, Jennifer A; Matijevic, Nena; Follis, Jack L; Folsom, Aaron R; Eric Boerwinkle (Atherosclerosis, 2010)
BACKGROUND: Specific foods and overall dietary patterns are associated with soluble biomarkers of systemic inflammation and endothelial activation. However, no large epidemiological studies have evaluated relationships between such dietary factors and cell-specific markers of activation and inflammation as measured by flow cytometry. METHODS: Cell aggregates and multiple platelet and leukocyte markers were quantified by flow cytometry in fresh whole blood from 1101 white adults participating in the Carotid Artery MRI Study, a subset of the larger Atherosclerosis Risk in Communities (ARIC) Study. Two dietary patterns ("Healthy" and "Western") were empirically derived via principal components analysis using data collected by food frequency questionnaire. Cross-sectional associations between dietary patterns and flow cytometry-measured biomarkers were evaluated, adjusting for demographics and lifestyle factors, including medications use. RESULTS: After multivariable adjustment, monocyte lipopolysaccharide receptor (CD14), monocyte toll-like receptor-2, and platelet glycoprotein IIb (CD41) showed inverse associations with the Healthy dietary pattern (p=0.01, 0.04, and 0.01, respectively). In contrast, the Western dietary pattern was positively associated with CD41 and platelet-granulocyte aggregates (p=0.01 and 0.04, respectively). Independent of other dietary factors, alcohol consumption was inversely associated with levels of pan-leukocyte marker (CD45), P-selectin (CD62P) on PLA1 and on PLA2 platelets, and platelet-monocyte, platelet-granulocyte, and platelet-lymphocyte aggregates. CONCLUSION: Dietary patterns and alcohol intake were each cross-sectionally associated with select markers of cellular activation and inflammation measured by flow cytometry. These data are consistent with the hypothesis that holistic measures of dietary intake are associated with inflammation.
Keywords: Aged; Alcohol Drinking; Biomarkers; Carotid Arteries; Carotid Artery Diseases; Cross-Sectional Studies; Diet Records; Feeding Behavior; Female; Flow Cytometry; Humans; Inflammation; Inflammation Mediators; Leukocyte Common Antigens; Life Style; Linear Models; Lipopolysaccharide Receptors; Magnetic Resonance Angiography; Male; P-Selectin; Platelet Membrane Glycoprotein IIb; Principal Component Analysis; Risk Assessment; Risk Factors; Surveys and Questionnaires; Toll-Like Receptor 2; United States

Calpain-10 is a component of the obesity-related quantitative trait locus Adip1. - Cheverud, James M; Fawcett, Gloria L; Jarvis, Joseph P; Norgard, Elizabeth A; Pavlicev, Mihaela; Pletscher, L Susan; Polonsky, Kenneth S; Ye, Honggang; Bell, Graeme I; Semenkovich, Clay F (J Lipid Res, 2010)
We previously mapped Adip1, an obesity quantitative trait locus (QTL), to the central portion of murine chromosome 1 containing the calpain-10 (Capn10) gene. Human studies have associated calpain-10 (CAPN10) variants with type 2 diabetes and various metabolic traits. We performed a quantitative hybrid complementation test (QHCT) to determine whether differences attributed to Adip1 are the result of variant Capn10 alleles in LG/J and SM/J mice. We crossed LG/J and SM/J to wild-type (C57BL/6J) and Capn10 knockout (Capn10(-/-)) mice to form four F(1) hybrid groups: LG/J by wild-type, LG/J by Capn10(-/-), SM/J by wild-type, and SM/J by Capn10(-/-). We performed a two-way ANOVA with the experimental strain, tester strain, and their interaction as the factors. Significant interaction indicates a quantitative failure to complement. We found failure to complement for fat, organ, and body weights, and leptin, female free fatty acid, and triglyceride levels. Capn10(-/-) resulted in heavier weights and higher serum levels in LG/J crosses but not in SM/J crosses. For glucose tolerance and insulin response tests, the Capn10(-/-) allele resulted in lower glucose levels in crosses with SM/J but had no effect in the LG/J crosses. Differences between the LG/J and SM/J Capn10 alleles are the likely source of some of the QTL effects mapped to Adip1 in the LG/J-by-SM/J cross. Capn10 plays an important role in regulating obesity and diabetes in mice.
Keywords: Alleles; Animals; Calpain; Female; Gene Knockout Techniques; Genetic Complementation Test; Genetic Variation; Hybridization, Genetic; Male; Mice; Obesity; Quantitative Trait Loci

Common INSIG2 polymorphisms are associated with age-related changes in body size and high-density lipoprotein cholesterol from young adulthood to middle age. - Fornage, Myriam; Papanicolaou, George; Lewis, Cora E; Eric Boerwinkle; Siscovick, David S (Metabolism, 2010)
Insulin-induced gene 2 (INSIG2) plays an important role in the regulation of cholesterol and fatty acids synthesis. A polymorphism, rs7566605, located 10 kilobases upstream of the INSIG2 gene, was identified in a genomewide association study of obesity. We conducted an association study of 12 INSIG2 tag-single nucleotide polymorphisms with longitudinal measures of body size (body mass index and waist circumference) and lipid metabolism (plasma high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides levels). We investigated their interaction with age in 4304 Coronary Artery Risk Development in Young Adults participants (49.5% blacks, 50.5% whites) followed prospectively for 20 years. rs7566605 was not associated with variation in body size or lipid metabolism at any age in either racial group. However, rs1352083 and rs10185316 were associated with age-related decline in high-density lipoprotein cholesterol in whites (P = .0005 and .04, respectively). A similar trend was observed in blacks who consistently maintained a body mass index less than 25 kg/m(2) over the study period. These data support a role of INSIG2 sequence variation in the regulation of cholesterol metabolism.
Keywords: Adolescent; Adult; Age Factors; Body Mass Index; Body Size; Cholesterol, HDL; Cross-Sectional Studies; Female; Humans; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Polymorphism, Single Nucleotide; Young Adult

Comparative genomics of Gardnerella vaginalis strains reveals substantial differences in metabolic and virulence potential. - Yeoman, Carl J; Yildirim, Suleyman; Thomas, Susan M; Durkin, A Scott; Torralba, Manolito; Sutton, Granger; Buhay, Christian J; Ding, Yan; Dugan-Rocha, Shannon P; Donna M Muzny; Qin, Xiang; Richard A Gibbs; et al. (PLoS One, 2010)
BACKGROUND: Gardnerella vaginalis is described as a common vaginal bacterial species whose presence correlates strongly with bacterial vaginosis (BV). Here we report the genome sequencing and comparative analyses of three strains of G. vaginalis. Strains 317 (ATCC 14019) and 594 (ATCC 14018) were isolated from the vaginal tracts of women with symptomatic BV, while Strain 409-05 was isolated from a healthy, asymptomatic individual with a Nugent score of 9. PRINCIPAL FINDINGS: Substantial genomic rearrangement and heterogeneity were observed that appeared to have resulted from both mobile elements and substantial lateral gene transfer. These genomic differences translated to differences in metabolic potential. All strains are equipped with significant virulence potential, including genes encoding the previously described vaginolysin, pili for cytoadhesion, EPS biosynthetic genes for biofilm formation, and antimicrobial resistance systems, We also observed systems promoting multi-drug and lantibiotic extrusion. All G. vaginalis strains possess a large number of genes that may enhance their ability to compete with and exclude other vaginal colonists. These include up to six toxin-antitoxin systems and up to nine additional antitoxins lacking cognate toxins, several of which are clustered within each genome. All strains encode bacteriocidal toxins, including two lysozyme-like toxins produced uniquely by strain 409-05. Interestingly, the BV isolates encode numerous proteins not found in strain 409-05 that likely increase their pathogenic potential. These include enzymes enabling mucin degradation, a trait previously described to strongly correlate with BV, although commonly attributed to non-G. vaginalis species. CONCLUSIONS: Collectively, our results indicate that all three strains are able to thrive in vaginal environments, and therein the BV isolates are capable of occupying a niche that is unique from 409-05. Each strain has significant virulence potential, although genomic and metabolic differences, such as the ability to degrade mucin, indicate that the detection of G. vaginalis in the vaginal tract provides only partial information on the physiological potential of the organism.
Keywords: Bacterial Proteins; Female; Gardnerella vaginalis; Genomics; Humans; Male; Molecular Sequence Data; Phylogeny; Vagina; Vaginosis, Bacterial; Virulence

Diabetes genes and prostate cancer in the Atherosclerosis Risk in Communities study. - Meyer, Tamra E; Eric Boerwinkle; Morrison, Alanna C; Volcik, Kelly A; Sanderson, Maureen; Coker, Ann L; Pankow, James S; Folsom, Aaron R (Cancer Epidemiol Biomarkers Prev, 2010)
There is a known inverse association between type 2 diabetes (T2D) and prostate cancer (PrCa) that is poorly understood. Genetic studies of the T2D-PrCa association may provide insight into the underlying mechanisms of this association. We evaluated associations in the Atherosclerosis Risk in Communities study between PrCa and nine T2D single nucleotide polymorphisms from genome-wide association studies of T2D (in CDKAL1, CDKN2A/B, FTO, HHEX, IGF2BP2, KCNJ11, PPARG, SLC30A8, and TCF7L2) and four T2D single nucleotide polymorphisms from pre-genome-wide association studies (in ADRB2, CAPN10, SLC2A2, and UCP2). From 1987 to 2000, there were 397 incident PrCa cases among 6,642 men ages 45 to 64 years at baseline. We used race-adjusted Cox proportional hazards models to estimate associations between PrCa and increasing number of T2D risk-raising alleles. PrCa was positively associated with the CAPN10 rs3792267 G allele [hazard ratio (HR) 1.20; 95% confidence interval (CI), 1.00-1.44] and inversely associated with the SLC2A2 rs5400 Thr110 allele (HR, 0.85; 95% CI, 0.72, 1.00), the UCP2 rs660339 Val55 allele (HR, 0.84; 95% CI, 0.73, 0.97) and the IGF2BP2 rs4402960 T allele (HR, 0.79; 95% CI, 0.61-1.02; blacks only). The TCF7L2 rs7903146 T allele was inversely associated with PrCa using a dominant genetic model (HR, 0.79; 95% CI, 0.65-0.97). Further knowledge of T2D gene-PrCa mechanisms may improve understanding of PrCa etiology.
Keywords: Atherosclerosis; Calpain; Cohort Studies; Diabetes Mellitus, Type 2; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Transporter Type 2; Humans; Ion Channels; Male; Middle Aged; Mitochondrial Proteins; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prostatic Neoplasms; RNA-Binding Proteins; TCF Transcription Factors; Transcription Factor 7-Like 2 Protein; Uncoupling Protein 2

European admixture on the Micronesian island of Kosrae: lessons from complete genetic information. - Bonnen, Penelope E; Lowe, Jennifer K; Altshuler, David M; Breslow, Jan L; Stoffel, Markus; Friedman, Jeffrey M; Pe'er, Itsik (Eur J Hum Genet, 2010)
The architecture of natural variation present in a contemporary population is a result of multiple population genetic forces, including population bottleneck and expansion, selection, drift, and admixture. We seek to untangle the contribution of admixture to genetic diversity on the Micronesian island of Kosrae. Toward this goal, we used a complete genetic approach by combining a dense genome-wide map of 100,000 single-nucleotide polymorphisms (SNPs) with data from uniparental markers from the mitochondrial genome and the nonrecombining portion of the Y chromosome. These markers were typed in approximately 3200 individuals from Kosrae, representing 80% of the adult population of the island. We developed novel software that uses SNP data to delineate ancestry for individual segments of the genome. Through this analysis, we determined that 39% of Kosraens have some European ancestry. However, the vast majority of admixed individuals (77%) have European alleles spanning less than 10% of their genomes. Data from uniparental markers show most of this admixture to be male, introduced in the late nineteenth century. Furthermore, pedigree analysis shows that the majority of European admixture on Kosrae is because of the contribution of one individual. This approach shows the benefit of combining information from autosomal and uniparental polymorphisms and provides new methodology for determining ancestry in a population.
Keywords: Chromosomes, Human, Y; DNA, Mitochondrial; Europe; Female; Gene Pool; Genetic Markers; Genetics, Population; Genome, Human; Geography; Haplotypes; Humans; Inheritance Patterns; Male; Micronesia; Pedigree; Phylogeny; Software; Time Factors

Functional and evolutionary insights from the genomes of three parasitoid Nasonia species. - Werren, John H; Richards, Stephen; Desjardins, Christopher A; Niehuis, Oliver; Gadau, Jürgen; Colbourne, John K; Werren, John H; Richards, Stephen; Desjardins, Christopher A; Niehuis, Oliver; Gadau, Jürgen; Colbourne, John K; et al. (Science, 2010)
We report here genome sequences and comparative analyses of three closely related parasitoid wasps: Nasonia vitripennis, N. giraulti, and N. longicornis. Parasitoids are important regulators of arthropod populations, including major agricultural pests and disease vectors, and Nasonia is an emerging genetic model, particularly for evolutionary and developmental genetics. Key findings include the identification of a functional DNA methylation tool kit; hymenopteran-specific genes including diverse venoms; lateral gene transfers among Pox viruses, Wolbachia, and Nasonia; and the rapid evolution of genes involved in nuclear-mitochondrial interactions that are implicated in speciation. Newly developed genome resources advance Nasonia for genetic research, accelerate mapping and cloning of quantitative trait loci, and will ultimately provide tools and knowledge for further increasing the utility of parasitoids as pest insect-control agents.
Keywords: Animals; Arthropods; Biological Evolution; DNA Methylation; DNA Transposable Elements; Female; Gene Transfer, Horizontal; Genes, Insect; Genetic Speciation; Genetic Variation; Genome, Insect; Host-Parasite Interactions; Insect Proteins; Insect Viruses; Insecta; Male; Molecular Sequence Data; Quantitative Trait Loci; Recombination, Genetic; Sequence Analysis, DNA; Wasp Venoms; Wasps; Wolbachia

On the genetic architecture of cortical folding and brain volume in primates. - Jeffrey Rogers; Kochunov, Peter; Zilles, Karl; Shelledy, Wendy; Lancaster, Jack; Thompson, Paul; Duggirala, Ravindranath; Blangero, John; Fox, Peter T; Glahn, David C (Neuroimage, 2010)
Understanding the evolutionary forces that produced the human brain is a central problem in neuroscience and human biology. Comparisons across primate species show that both brain volume and gyrification (the degree of folding in the cerebral cortex) have progressively increased during primate evolution and there is a strong positive correlation between these two traits across primate species. The human brain is exceptional among primates in both total volume and gyrification, and therefore understanding the genetic mechanisms influencing variation in these traits will improve our understanding of a landmark feature of our species. Here we show that individual variation in gyrification is significantly heritable in both humans and an Old World monkey (baboons, Papio hamadryas). Furthermore, contrary to expectations based on the positive phenotypic correlation across species, the genetic correlation between cerebral volume and gyrification within both humans and baboons is estimated as negative. These results suggest that the positive relationship between cerebral volume and cortical folding across species cannot be explained by one set of selective pressures or genetic changes. Our data suggest that one set of selective pressures favored the progressive increase in brain volume documented in the primate fossil record, and that a second independent selective process, possibly related to parturition and neonatal brain size, may have favored brains with progressively greater cortical folding. Without a second separate selective pressure, natural selection favoring increased brain volume would be expected to produce less folded, more lissencephalic brains. These results provide initial evidence for the heritability of gyrification, and possibly a new perspective on the evolutionary mechanisms underlying long-term changes in the nonhuman primate and human brain.
Keywords: Animals; Biological Evolution; Cerebral Cortex; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Papio; Primates; Species Specificity

Genetic variants identified in a European genome-wide association study that were found to predict incident coronary heart disease in the atherosclerosis risk in communities study. - Bressler, Jan; Folsom, Aaron R; Couper, David J; Volcik, Kelly A; Eric Boerwinkle (Am J Epidemiol, 2010)
In 2007, the Wellcome Trust Case Control Consortium (WTCCC) performed a genome-wide association study in 2,000 British coronary heart disease (CHD) cases and 3,000 controls after genotyping 469,557 single nucleotide polymorphisms (SNPs). Seven variants associated with CHD were initially identified, and 5 SNPs were later found in replication studies. In the current study, the authors aimed to determine whether the 12 SNPs reported by the WTCCC predicted incident CHD through 2004 in a biracial, prospective cohort study (Atherosclerosis Risk in Communities) comprising 15,792 persons aged 45-64 years who had been selected by probability sampling from 4 different US communities in 1987-1989. Cox proportional hazards models with adjustment for age and gender were used to estimate CHD hazard rate ratios (HRRs) over a 17-year period (1,362 cases in whites and 397 cases in African Americans) under an additive genetic model. The results showed that 3 SNPs in whites (rs599839, rs1333049, and rs501120; HRRs were 1.10 (P = 0.044), 1.14 (P < 0.001), and 1.14 (P = 0.030), respectively) and 1 SNP in African Americans (rs7250581; HRR = 1.60, P = 0.05) were significantly associated with incident CHD. This study demonstrates that genetic variants revealed in a case-control genome-wide association study enriched for early disease onset may play a role in the genetic etiology of CHD in the general population.
Keywords: Black or African American; Case-Control Studies; Coronary Artery Disease; Female; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Residence Characteristics; Risk; Risk Assessment; Risk Factors; United Kingdom; United States; White People

Genetics of primary cerebral gyrification: Heritability of length, depth and area of primary sulci in an extended pedigree of Papio baboons. - Kochunov, P; Glahn, D C; Fox, P T; Lancaster, J L; Saleem, K; Shelledy, W; Zilles, K; Thompson, P M; Coulon, O; Mangin, J F; Blangero, J; Rogers, J (Neuroimage, 2010)
Genetic control over morphological variability of primary sulci and gyri is of great interest in the evolutionary, developmental and clinical neurosciences. Primary structures emerge early in development and their morphology is thought to be related to neuronal differentiation, development of functional connections and cortical lateralization. We measured the proportional contributions of genetics and environment to regional variability, testing two theories regarding regional modulation of genetic influences by ontogenic and phenotypic factors. Our measures were surface area, and average length and depth of eleven primary cortical sulci from high-resolution MR images in 180 pedigreed baboons. Average heritability values for sulcal area, depth and length (h(2)(Area)=.38+/-.22; h(2)(Depth)=.42+/-.23; h(2)(Length)=.34+/-.22) indicated that regional cortical anatomy is under genetic control. The regional pattern of genetic contributions was complex and, contrary to previously proposed theories, did not depend upon sulcal depth, or upon the sequence in which structures appear during development. Our results imply that heritability of sulcal phenotypes may be regionally modulated by arcuate U-fiber systems. However, further research is necessary to unravel the complexity of genetic contributions to cortical morphology.
Keywords: Animals; Brain; Female; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Papio; Quantitative Trait, Heritable

Genome-wide association studies of serum magnesium, potassium, and sodium concentrations identify six Loci influencing serum magnesium levels. - Meyer, Tamra E; Verwoert, Germaine C; Hwang, Shih-Jen; Glazer, Nicole L; Smith, Albert V; van Rooij, Frank J A; Ehret, Georg B; Eric Boerwinkle; Felix, Janine F; Leak, Tennille S; Harris, Tamara B; Yang, Qiong; et al. (PLoS Genet, 2010)
Magnesium, potassium, and sodium, cations commonly measured in serum, are involved in many physiological processes including energy metabolism, nerve and muscle function, signal transduction, and fluid and blood pressure regulation. To evaluate the contribution of common genetic variation to normal physiologic variation in serum concentrations of these cations, we conducted genome-wide association studies of serum magnesium, potassium, and sodium concentrations using approximately 2.5 million genotyped and imputed common single nucleotide polymorphisms (SNPs) in 15,366 participants of European descent from the international CHARGE Consortium. Study-specific results were combined using fixed-effects inverse-variance weighted meta-analysis. SNPs demonstrating genome-wide significant (p<5 x 10(-8)) or suggestive associations (p<4 x 10(-7)) were evaluated for replication in an additional 8,463 subjects of European descent. The association of common variants at six genomic regions (in or near MUC1, ATP2B1, DCDC5, TRPM6, SHROOM3, and MDS1) with serum magnesium levels was genome-wide significant when meta-analyzed with the replication dataset. All initially significant SNPs from the CHARGE Consortium showed nominal association with clinically defined hypomagnesemia, two showed association with kidney function, two with bone mineral density, and one of these also associated with fasting glucose levels. Common variants in CNNM2, a magnesium transporter studied only in model systems to date, as well as in CNNM3 and CNNM4, were also associated with magnesium concentrations in this study. We observed no associations with serum sodium or potassium levels exceeding p<4 x 10(-7). Follow-up studies of newly implicated genomic loci may provide additional insights into the regulation and homeostasis of human serum magnesium levels.
Keywords: Adult; Aged; Female; Genome-Wide Association Study; Humans; Magnesium; Male; Middle Aged; Polymorphism, Single Nucleotide; Potassium; Sodium; White People

Genomic variation associated with mortality among adults of European and African ancestry with heart failure: the cohorts for heart and aging research in genomic epidemiology consortium. - Morrison, Alanna C; Felix, Janine F; Cupples, L Adrienne; Glazer, Nicole L; Loehr, Laura R; Dehghan, Abbas; Demissie, Serkalem; Bis, Joshua C; Rosamond, Wayne D; Aulchenko, Yurii S; Wang, Ying A; Haritunians, Talin; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Prognosis and survival are significant concerns for individuals with heart failure (HF). To better understand the pathophysiology of HF prognosis, the association between 2,366,858 single-nucleotide polymorphisms (SNPs) and all-cause mortality was evaluated among individuals with incident HF from 4 community-based prospective cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. METHODS AND RESULTS: Participants were 2526 individuals of European ancestry and 466 individuals of African ancestry who experienced an incident HF event during follow-up in the respective cohorts. Within each study, the association between genetic variants and time to mortality among individuals with HF was assessed by Cox proportional hazards models that included adjustment for sex and age at the time of the HF event. Prospective fixed-effect meta-analyses were conducted for the 4 study populations of European ancestry (N=1645 deaths) and for the 2 populations of African ancestry (N=281 deaths). Genome-wide significance was set at P=5.0x10(-7). Meta-analytic findings among individuals of European ancestry revealed 1 genome-wide significant locus on chromosome 3p22 in an intron of CKLF-like MARVEL transmembrane domain containing 7 (CMTM7, P=3.2x10(-7)). Eight additional loci in individuals of European ancestry and 4 loci in individuals of African ancestry were identified by high-signal SNPs (P<1.0x10(-5)) but did not meet genome-wide significance. CONCLUSIONS: This study identified a novel locus associated with all-cause mortality among individuals of European ancestry with HF. This finding warrants additional investigation, including replication, in other studies of HF.
Keywords: Aged; Aged, 80 and over; Black or African American; Chemokines; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Heart Failure; Humans; Introns; Male; MARVEL Domain-Containing Proteins; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; White People

Identification of a QTL for adipocyte volume and of shared genetic effects with aspartate aminotransferase. - Bose, Tanushree; Voruganti, V Saroja; Tejero, M Elizabeth; Proffit, J Michael; Cox, Laura A; VandeBerg, John L; Mahaney, Michael C; Jeffrey Rogers; Freeland-Graves, Jeanne H; Cole, Shelley A; Comuzzie, Anthony G (Biochem Genet, 2010)
Plasma levels of aspartate aminotransferase (AST), a liver enzyme, are elevated in patients with visceral obesity. This study examined whether adipocyte volume is under the influence of genetic factors and evaluated its genetic correlations with AST. Fasting plasma levels of 344 pedigreed baboons from the Southwest National Primate Research Center in San Antonio, TX, USA, were assayed for AST. Adipocyte volume was measured using biopsies of omental adipose tissue. Adipocyte volume, body weight, and plasma AST were heritable. Genetic correlations between the measured adiposity-related phenotypes and AST were significant. A quantitative trait locus (LOD score 3.2) for adipocyte volume was identified on the baboon homolog of human chromosome 6 near marker D6S1028. These results suggest that omental adipocyte volume is under genetic regulation and that shared genetic factors influence adiposity-associated traits and AST.
Keywords: Adipocytes; Animals; Aspartate Aminotransferases; Biomarkers; Cell Size; Female; Genomics; Humans; Male; Obesity; Papio; Quantitative Trait Loci

Interactions of dietary whole-grain intake with fasting glucose- and insulin-related genetic loci in individuals of European descent: a meta-analysis of 14 cohort studies. - Nettleton, Jennifer A; McKeown, Nicola M; Kanoni, Stavroula; Lemaitre, Rozenn N; Hivert, Marie-France; Ngwa, Julius; van Rooij, Frank J A; Sonestedt, Emily; Wojczynski, Mary K; Ye, Zheng; Tanaka, Tosh; Garcia, Melissa; et al. (Diabetes Care, 2010)
OBJECTIVE: Whole-grain foods are touted for multiple health benefits, including enhancing insulin sensitivity and reducing type 2 diabetes risk. Recent genome-wide association studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) associated with fasting glucose and insulin concentrations in individuals free of diabetes. We tested the hypothesis that whole-grain food intake and genetic variation interact to influence concentrations of fasting glucose and insulin. RESEARCH DESIGN AND METHODS: Via meta-analysis of data from 14 cohorts comprising ∼ 48,000 participants of European descent, we studied interactions of whole-grain intake with loci previously associated in GWAS with fasting glucose (16 loci) and/or insulin (2 loci) concentrations. For tests of interaction, we considered a P value <0.0028 (0.05 of 18 tests) as statistically significant. RESULTS: Greater whole-grain food intake was associated with lower fasting glucose and insulin concentrations independent of demographics, other dietary and lifestyle factors, and BMI (β [95% CI] per 1-serving-greater whole-grain intake: -0.009 mmol/l glucose [-0.013 to -0.005], P < 0.0001 and -0.011 pmol/l [ln] insulin [-0.015 to -0.007], P = 0.0003). No interactions met our multiple testing-adjusted statistical significance threshold. The strongest SNP interaction with whole-grain intake was rs780094 (GCKR) for fasting insulin (P = 0.006), where greater whole-grain intake was associated with a smaller reduction in fasting insulin concentrations in those with the insulin-raising allele. CONCLUSIONS: Our results support the favorable association of whole-grain intake with fasting glucose and insulin and suggest a potential interaction between variation in GCKR and whole-grain intake in influencing fasting insulin concentrations.
Keywords: Adult; Aged; Blood Glucose; Edible Grain; Fasting; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; White People

A map of human genome variation from population-scale sequencing. - Abecasis, Gonçalo R; Altshuler, David; Auton, Adam; Brooks, Lisa D; Durbin, Richard M; Richard A Gibbs; Hurles, Matt E; McVean, Gil A (Nature, 2010)
The 1000 Genomes Project aims to provide a deep characterization of human genome sequence variation as a foundation for investigating the relationship between genotype and phenotype. Here we present results of the pilot phase of the project, designed to develop and compare different strategies for genome-wide sequencing with high-throughput platforms. We undertook three projects: low-coverage whole-genome sequencing of 179 individuals from four populations; high-coverage sequencing of two mother-father-child trios; and exon-targeted sequencing of 697 individuals from seven populations. We describe the location, allele frequency and local haplotype structure of approximately 15 million single nucleotide polymorphisms, 1 million short insertions and deletions, and 20,000 structural variants, most of which were previously undescribed. We show that, because we have catalogued the vast majority of common variation, over 95% of the currently accessible variants found in any individual are present in this data set. On average, each person is found to carry approximately 250 to 300 loss-of-function variants in annotated genes and 50 to 100 variants previously implicated in inherited disorders. We demonstrate how these results can be used to inform association and functional studies. From the two trios, we directly estimate the rate of de novo germline base substitution mutations to be approximately 10(-8) per base pair per generation. We explore the data with regard to signatures of natural selection, and identify a marked reduction of genetic variation in the neighbourhood of genes, due to selection at linked sites. These methods and public data will support the next phase of human genetic research.
Keywords: Calibration; Chromosomes, Human, Y; Computational Biology; DNA Mutational Analysis; DNA, Mitochondrial; Evolution, Molecular; Female; Genetic Association Studies; Genetic Variation; Genetics, Population; Genome, Human; Genome-Wide Association Study; Genomics; Genotype; Haplotypes; Humans; Male; Mutation; Pilot Projects; Polymorphism, Single Nucleotide; Recombination, Genetic; Sample Size; Selection, Genetic; Sequence Alignment; Sequence Analysis, DNA

MMP2 genetic variation is associated with measures of fibrous cap thickness: The Atherosclerosis Risk in Communities Carotid MRI Study. - Volcik, Kelly A; Campbell, Stephen; Chambless, Lloyd E; Coresh, Josef; Folsom, Aaron R; Mosley, Thomas H; Ni, Hanyu; Wagenknecht, Lynne E; Wasserman, Bruce A; Eric Boerwinkle (Atherosclerosis, 2010)
OBJECTIVE: Genetic variation in matrix metalloproteinase (MMP) promoter regions alter the transcriptional activity of MMPs and has been consistently associated with CHD, presumably through plaque degradation and remodeling. We examined the association of MMP promoter variation with multiple plaque characteristics measured by gadolinium-enhanced MRI among 1700 participants in the Atherosclerosis Risk in Communities (ARIC) Carotid MRI Study. METHODS: For the analyses presented here, 1700 participants of the biracial ARIC Carotid MRI Study ( approximately 1000 participants with thick carotid artery walls and approximately 700 randomly sampled participants) were evaluated for associations of MMP genetic variation with multiple plaque characteristics, including carotid artery wall thickness, lipid core and fibrous cap measures. MRI studies were performed on a 1.5T scanner equipped with a bilateral 4-element phased array carotid coil. RESULTS: Fifty-one percent of the participants were female, 77% white, 23% African American, and the mean age was 70 years. MMP2 C-1306T variant genotypes (CT+TT) were significantly associated with higher cap thickness measures, but not with wall thickness or lipid core measures. Individuals with the CC genotype had approximately 0.1mm thinner cap thickness compared to those carrying a T allele (P=0.02). CONCLUSION: Genetic variation within the MMP2 promoter region was associated with cap thickness and therefore may influence the role of MMP2 in plaque vulnerability.
Keywords: Aged; Atherosclerosis; Carotid Arteries; Female; Genetic Variation; Genotype; Humans; Magnetic Resonance Imaging; Male; Matrix Metalloproteinase 2; Middle Aged; Promoter Regions, Genetic; Prospective Studies; Transcription, Genetic

Risk of type 2 diabetes and obesity is differentially associated with variation in FTO in whites and African-Americans in the ARIC study. - Bressler, Jan; Kao, W H Linda; Pankow, James S; Eric Boerwinkle (PLoS One, 2010)
Single nucleotide polymorphisms (SNPs) in the fat mass and obesity associated (FTO) gene are associated with body mass index (BMI) in populations of European descent. The FTO rs9939609 variant, first detected in a genome-wide association study of diabetes, conferred an increased disease risk that was abolished after adjustment for BMI, suggesting that the association may be due to variation in adiposity. The relationship between diabetes, four previously identified FTO polymorphisms that span a 19.6-kb genomic region, and obesity was therefore evaluated in the biracial population-based Atherosclerosis Risk in Communities Study with the goal of further refining the association by comparing results between the two ethnic groups. The prevalence of diabetes and obesity (BMI > or = 30 kg/m(2)) was established at baseline, and diabetes was determined by either self-report, a fasting glucose level > or = 126 mg/dL, or non-fasting glucose > or = 200 mg/dL. There were 1,004 diabetes cases and 10,038 non-cases in whites, and 670 cases and 2,780 non-cases in African-Americans. Differences in mean BMI were assessed by a general linear model, and multivariable logistic regression was used to predict the risk of diabetes and obesity. For white participants, the FTO rs9939609 A allele was associated with an increased risk of diabetes (odds ratio (OR) = 1.19, p<0.001) and obesity (OR = 1.22, p<0.001) under an additive genetic model that was similar for all of the SNPs analyzed. In African-Americans, only the rs1421085 C allele was a determinant of obesity risk (OR = 1.17, p = 0.05), but was found to be protective against diabetes (OR = 0.79, p = 0.03). Adjustment for BMI did not eliminate any of the observed associations with diabetes. Significant statistical interaction between race and the FTO variants suggests that the effect on diabetes susceptibility may be context dependent.
Keywords: Alleles; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Atherosclerosis; Black or African American; Body Mass Index; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins; Quantitative Trait, Heritable; White People

Whole-genome sequencing in a patient with Charcot-Marie-Tooth neuropathy. - Lupski, James R; Reid, Jeffrey G; Gonzaga-Jauregui, Claudia; Rio Deiros, David; Chen, David C Y; Nazareth, Lynne; Bainbridge, Matthew; Dinh, Huyen; Jing, Chyn; Wheeler, David A; McGuire, Amy L; Zhang, Feng; et al. (N Engl J Med, 2010)
BACKGROUND: Whole-genome sequencing may revolutionize medical diagnostics through rapid identification of alleles that cause disease. However, even in cases with simple patterns of inheritance and unambiguous diagnoses, the relationship between disease phenotypes and their corresponding genetic changes can be complicated. Comprehensive diagnostic assays must therefore identify all possible DNA changes in each haplotype and determine which are responsible for the underlying disorder. The high number of rare, heterogeneous mutations present in all humans and the paucity of known functional variants in more than 90% of annotated genes make this challenge particularly difficult. Thus, the identification of the molecular basis of a genetic disease by means of whole-genome sequencing has remained elusive. We therefore aimed to assess the usefulness of human whole-genome sequencing for genetic diagnosis in a patient with Charcot-Marie-Tooth disease. METHODS: We identified a family with a recessive form of Charcot-Marie-Tooth disease for which the genetic basis had not been identified. We sequenced the whole genome of the proband, identified all potential functional variants in genes likely to be related to the disease, and genotyped these variants in the affected family members. RESULTS: We identified and validated compound, heterozygous, causative alleles in SH3TC2 (the SH3 domain and tetratricopeptide repeats 2 gene), involving two mutations, in the proband and in family members affected by Charcot-Marie-Tooth disease. Separate subclinical phenotypes segregated independently with each of the two mutations; heterozygous mutations confer susceptibility to neuropathy, including the carpal tunnel syndrome. CONCLUSIONS: As shown in this study of a family with Charcot-Marie-Tooth disease, whole-genome sequencing can identify clinically relevant variants and provide diagnostic information to inform the care of patients.
Keywords: Adult; Aged; Aged, 80 and over; Charcot-Marie-Tooth Disease; Codon, Nonsense; Female; Genes, Recessive; Genetic Association Studies; Genome, Human; Genotype; Humans; Male; Middle Aged; Mutation, Missense; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

A-beta-subtype of ketosis-prone diabetes is not predominantly a monogenic diabetic syndrome. - Haaland, Wade C; Scaduto, Diane I; Maldonado, Mario R; Mansouri, Dena L; Nalini, Ramaswami; Iyer, Dinakar; Patel, Sanjeet; Guthikonda, Anu; Hampe, Christiane S; Balasubramanyam, Ashok; Metzker, Michael L (Diabetes Care, 2009)
OBJECTIVE: Ketosis-prone diabetes (KPD) is an emerging syndrome that encompasses several distinct phenotypic subgroups that share a predisposition to diabetic ketoacidosis. We investigated whether the A-beta- subgroup of KPD, characterized by complete insulin dependence, absent beta-cell functional reserve, lack of islet cell autoantibodies, and strong family history of type 2 diabetes, represents a monogenic form of diabetes. RESEARCH DESIGN AND METHODS: Over 8 years, 37 patients with an A-beta- phenotype were identified in our longitudinally followed cohort of KPD patients. Seven genes, including hepatocyte nuclear factor 4A (HNF4A), glucokinase (GCK), HNF1A, pancreas duodenal homeobox 1 (PDX1), HNF1B, neurogenic differentiation 1 (NEUROD1), and PAX4, were directly sequenced in all patients. Selected gene regions were also sequenced in healthy, unrelated ethnically matched control subjects, consisting of 84 African American, 96 Caucasian, and 95 Hispanic subjects. RESULTS: The majority (70%) of the A-beta- KPD patients had no significant causal polymorphisms in either the proximal promoter or coding regions of the seven genes. The combination of six potentially significant low-frequency, heterozygous sequence variants in HNF-1 alpha (A174V or G574S), PDX1 (putative 5'-untranslated region CCAAT box, P33T, or P239Q), or PAX4 (R133W) were found in 27% (10/37) of patients, with one additional patient revealing two variants, PDX1 P33T and PAX4 R133W. The A174V variant has not been previously reported. CONCLUSIONS: Despite its well-circumscribed, robust, and distinctive phenotype of severe, nonautoimmune-mediated beta-cell dysfunction, A-beta- KPD is most likely not a predominantly monogenic diabetic syndrome. Several A-beta- KPD patients have low-frequency variants in HNF1A, PDX1, or PAX4 genes, which may be of functional significance in their pathophysiology.
Keywords: Adult; Autoantibodies; Basic Helix-Loop-Helix Transcription Factors; Diabetes Mellitus, Type 1; Diabetes Mellitus, Type 2; Female; Genetic Variation; Glucokinase; Glycated Hemoglobin; Hepatocyte Nuclear Factor 1-beta; Hepatocyte Nuclear Factor 4; Homeodomain Proteins; Humans; Insulin; Insulin-Secreting Cells; Islets of Langerhans; Male; Middle Aged; Paired Box Transcription Factors; Trans-Activators

Carbohydrate intake modifies associations between ANGPTL4[E40K] genotype and HDL-cholesterol concentrations in White men from the Atherosclerosis Risk in Communities (ARIC) study. - Nettleton, Jennifer A; Volcik, Kelly A; Hoogeveen, Ron C; Eric Boerwinkle (Atherosclerosis, 2009)
BACKGROUND: Common allelic variation in the angiopoietin-like 4 gene (ANGPTL4[E40K]) has been associated with low triglyceride (TG) and high HDL-C. OBJECTIVE: We examined whether dietary macronutrient intake modified associations between ANGPTL4[E40K] variation and TG and HDL-C in White men and women from the Atherosclerosis Risk in Communities study. DESIGN: Diet was assessed by food frequency questionnaire. Intake of fat (total fat [TF], saturated fat [SF], monounsaturated fat [MUFA], polyunsaturated fat [PUFA], and n-3 PUFA) and carbohydrate were expressed as percentage of total energy intake. ANGPTL4 A allele carriers (n=148 in men, 200 in women) were compared to non-carriers (n=3667 in men, 4496 in women). Interactions were tested separately in men and women, adjusting for study center, age, smoking, physical activity, BMI, and alcohol intake. RESULTS: ANGPTL4 A allele carriers had significantly greater HDL-C and lower TG than non-carriers (p<or=0.001). In all participants, carbohydrate intake was inversely associated with HDL-C and positively associated with TG, whereas TF, SF, and MUFA showed opposite associations with TG and HDL-C (p<0.001). These relations were uniform between sex-specific genotype groups, with one exception. In men, but not women, the inverse association between carbohydrate and HDL-C was stronger in A allele carriers (beta+/-S.E. -1.80+/-0.54) than non-carriers (beta+/-S.E. -0.54+/-0.11, p(interaction)=0.04 in men and 0.69 in women; p 3-way interaction=0.14). CONCLUSIONS: These data suggest that ANGPTL4 variation and relative contributions of dietary fat and carbohydrate influence TG and HDL-C concentrations. In men, ANGPTL4 variation and dietary carbohydrate may interactively influence HDL-C.
Keywords: Alleles; Angiopoietin-Like Protein 4; Angiopoietins; Atherosclerosis; Cholesterol; Cholesterol, HDL; Community Health Services; Diet; Female; Genetic Variation; Genotype; Humans; Male; Middle Aged; Nutritional Sciences; Risk; Sex Factors; Triglycerides; White People

Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium: Design of prospective meta-analyses of genome-wide association studies from 5 cohorts. - Psaty, Bruce M; O'Donnell, Christopher J; Gudnason, Vilmundur; Lunetta, Kathryn L; Folsom, Aaron R; Rotter, Jerome I; Uitterlinden, André G; Harris, Tamara B; Witteman, Jacqueline C M; Eric Boerwinkle (Circ Cardiovasc Genet, 2009)
BACKGROUND: The primary aim of genome-wide association studies is to identify novel genetic loci associated with interindividual variation in the levels of risk factors, the degree of subclinical disease, or the risk of clinical disease. The requirement for large sample sizes and the importance of replication have served as powerful incentives for scientific collaboration. Methods- The Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium was formed to facilitate genome-wide association studies meta-analyses and replication opportunities among multiple large population-based cohort studies, which collect data in a standardized fashion and represent the preferred method for estimating disease incidence. The design of the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium includes 5 prospective cohort studies from the United States and Europe: the Age, Gene/Environment Susceptibility-Reykjavik Study, the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. With genome-wide data on a total of about 38 000 individuals, these cohort studies have a large number of health-related phenotypes measured in similar ways. For each harmonized trait, within-cohort genome-wide association study analyses are combined by meta-analysis. A prospective meta-analysis of data from all 5 cohorts, with a properly selected level of genome-wide statistical significance, is a powerful approach to finding genuine phenotypic associations with novel genetic loci. CONCLUSIONS: The Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium and collaborating non-member studies or consortia provide an excellent framework for the identification of the genetic determinants of risk factors, subclinical-disease measures, and clinical events.
Keywords: Adult; Aged; Aging; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Diseases; Humans; Male; Meta-Analysis as Topic; Middle Aged; Phenotype; Research Design; Risk Factors

Common and rare variants of DAOA in bipolar disorder. - Maheshwari, Manjula; Shi, Jiajun; Badner, Judith A; Skol, Andrew; Willour, Virginia L; Donna M Muzny; Wheeler, David A; Gerald, Fowler R; Detera-Wadleigh, Sevilla; McMahon, Francis J; Potash, James B; Gershon, Elliot S; et al. (Am J Med Genet B Neuropsychiatr Genet, 2009)
The D-amino acid oxidase activator (DAOA, previously known as G72) gene, mapped on 13q33, has been reported to be genetically associated with bipolar disorder (BP) in several populations. The consistency of associated variants is unclear and rare variants in exons of the DAOA gene have not been investigated in psychiatric diseases. We employed a conditional linkage method-STatistical Explanation for Positional Cloning (STEPC) to evaluate whether any associated single nucleotide polymorphisms (SNPs) account for the evidence of linkage in a pedigree series that previously has been linked to marker D13S779 at 13q33. We also performed an association study in a sample of 376 Caucasian BP parent-proband trios by genotyping 38 common SNPs in the gene region. Besides, we resequenced coding regions and flanking intronic sequences of DAOA in 555 Caucasian unrelated BP patients and 564 mentally healthy controls, to identify putative functional rare variants that may contribute to disease. One SNP rs1935058 could "explain" the linkage signal in the family sample set (P = 0.055) using STEPC analysis. No significant allelic association was detected in an association study by genotyping 38 common SNPs in 376 Caucasian BP trios. Resequencing identified 53 SNPs, of which 46 were novel SNPs. There was no significant excess of rare variants in cases relative to controls. Our results suggest that DAOA does not have a major effect on BP susceptibility. However, DAOA may contribute to bipolar susceptibility in some specific families as evidenced by the STEPC analysis.
Keywords: Bipolar Disorder; Carrier Proteins; Cloning, Molecular; Exons; Female; Genetic Predisposition to Disease; Humans; Intracellular Signaling Peptides and Proteins; Male; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Fine mapping of chromosome 6q23-25 region in familial lung cancer families reveals RGS17 as a likely candidate gene. - You, Ming; Wang, Daolong; Liu, Pengyuan; Vikis, Haris; James, Michael; Lu, Yan; Wang, Yian; Wang, Min; Chen, Qiong; Jia, Dongmei; Liu, Yan; Wen, Weidong; et al. (Clin Cancer Res, 2009)
PURPOSE: We have previously mapped a major susceptibility locus influencing familial lung cancer risk to chromosome 6q23-25. However, the causal gene at this locus remains undetermined. In this study, we further refined this locus to identify a single candidate gene, by fine mapping using microsatellite markers and association studies using high-density single nucleotide polymorphisms (SNP). EXPERIMENTAL DESIGN: Six multigenerational families with five or more affected members were chosen for fine-mapping the 6q linkage region using microsatellite markers. For association mapping, we genotyped 24 6q-linked cases and 72 unrelated noncancer controls from the Genetic Epidemiology of Lung Cancer Consortium resources using the Affymetrix 500K chipset. Significant associations were validated in two independent familial lung cancer populations: 226 familial lung cases and 313 controls from the Genetic Epidemiology of Lung Cancer Consortium, and 154 familial cases and 325 controls from Mayo Clinic. Each familial case was chosen from one high-risk lung cancer family that has three or more affected members. RESULTS: A region-wide scan across 6q23-25 found significant association between lung cancer susceptibility and three single nucleotide polymorphisms in the first intron of the RGS17 gene. This association was further confirmed in two independent familial lung cancer populations. By quantitative real-time PCR analysis of matched tumor and normal human tissues, we found that RGS17 transcript accumulation is highly and consistently increased in sporadic lung cancers. Human lung tumor cell proliferation and tumorigenesis in nude mice are inhibited upon knockdown of RGS17 levels. CONCLUSION: RGS17 is a major candidate for the familial lung cancer susceptibility locus on chromosome 6q23-25.
Keywords: Aged; Animals; Cell Line, Tumor; Chromosome Mapping; Chromosomes, Human, Pair 6; Female; Gene Knockdown Techniques; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Lung; Lung Neoplasms; Male; Mice; Mice, Nude; Microsatellite Repeats; Middle Aged; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; RGS Proteins; RNA, Small Interfering; Transplantation, Heterologous

Gene by smoking interaction in hypertension: identification of a major quantitative trait locus on chromosome 15q for systolic blood pressure in Mexican-Americans. - Montasser, May E; Shimmin, Lawrence C; Hanis, Craig L; Eric Boerwinkle; Hixson, James E (J Hypertens, 2009)
OBJECTIVE: Our objective was to investigate the influence of gene by smoking (GxS) interaction on hypertension and blood pressure (BP) using genome-wide linkage analysis in Mexican-Americans, followed by single nucleotide polymorphism (SNP) fine mapping of candidate genes in the linked chromosomal region. METHODS: We used nonparametric methods to test for linkage of microsatellites with hypertension and BP measures in smokers, nonsmokers, and the combined group. To begin fine mapping of a major quantitative trait locus (QTL) for systolic blood pressure (SBP) on chromosome 15q that showed strong evidence for GxS interaction, we genotyped 55 SNPs in nine candidate genes for association studies using two population-based statistical methods. RESULTS: The strongest evidence for GxS interaction (P = 0.0004) was found for SBP on chromosome 15q, where a major QTL (LOD = 3.36) was identified only in nonsmokers. Follow-up studies identified three SNPs in three genes (ANPEP, IGF1R, and SLCO3A1) that showed associations with SBP only in nonsmokers, cumulatively accounting for a 7 mmHg increase in SBP. However, conditional linkage analyses that accounted for phenotypic effects of these SNPs only slightly reduced the original LOD score. CONCLUSION: The detection of a major QTL on chromosome 15q for SBP in nonsmokers indicates the presence of loci that influence BP via GxS interactions. However, identification of the genes that underlie such QTL effects remains a challenge. Although we found three candidate genes that showed significant associations with SBP in nonsmokers, further studies are required to identify the gene(s) that underlie the chromosome 15q QTL that influences SBP via GxS interactions.
Keywords: Aged; Blood Pressure; Chromosomes, Human, Pair 15; Female; Genetic Linkage; Humans; Hypertension; Lod Score; Male; Mexican Americans; Microsatellite Repeats; Middle Aged; Physical Chromosome Mapping; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Smoking; Statistics, Nonparametric; Texas

Genetic variation in baboon craniofacial sexual dimorphism. - Willmore, Katherine E; Roseman, Charles C; Jeffrey Rogers; Richtsmeier, Joan T; Cheverud, James M (Evolution, 2009)
Sexual dimorphism is a widespread phenomenon and contributes greatly to intraspecies variation. Despite a long history of active research, the genetic basis of dimorphism for complex traits remains unknown. Understanding the sex-specific differences in genetic architecture for cranial traits in a highly dimorphic species could identify possible mechanisms through which selection acts to produce dimorphism. Using distances calculated from three-dimensional landmark data from CT scans of 402 baboon skulls from a known genealogy, we estimated genetic variance parameters in both sexes to determine the presence of gene-by-sex (G x S) interactions and X-linked heritability. We hypothesize that traits exhibiting the greatest degree of sexual dimorphism (facial traits in baboons) will demonstrate either stronger G x S interactions or X-linked effects. We found G x S interactions and X-linked effects for a few measures that span the areas connecting the face to the neurocranium but for no traits restricted to the face. This finding suggests that facial traits will have a limited response to selection for further evolution of dimorphism in this population. We discuss the implications of our results with respect to the origins of cranial sexual dimorphism in this baboon sample, and how the genetic architecture of these traits affects their potential for future evolution.
Keywords: Animals; Biological Evolution; Female; Genes, X-Linked; Genetic Variation; Male; Papio hamadryas; Sex Characteristics; Skull

The genome sequence of taurine cattle: a window to ruminant biology and evolution. - Elsik, Christine G; Tellam, Ross L; Worley, Kim C; Richard A Gibbs; Donna M Muzny; Weinstock, George M; Adelson, David L; Eichler, Evan E; Elnitski, Laura; Guigó, Roderic; Hamernik, Debora L; Kappes, Steve M; et al. (Science, 2009)
To understand the biology and evolution of ruminants, the cattle genome was sequenced to about sevenfold coverage. The cattle genome contains a minimum of 22,000 genes, with a core set of 14,345 orthologs shared among seven mammalian species of which 1217 are absent or undetected in noneutherian (marsupial or monotreme) genomes. Cattle-specific evolutionary breakpoint regions in chromosomes have a higher density of segmental duplications, enrichment of repetitive elements, and species-specific variations in genes associated with lactation and immune responsiveness. Genes involved in metabolism are generally highly conserved, although five metabolic genes are deleted or extensively diverged from their human orthologs. The cattle genome sequence thus provides a resource for understanding mammalian evolution and accelerating livestock genetic improvement for milk and meat production.
Keywords: Alternative Splicing; Animals; Animals, Domestic; Biological Evolution; Cattle; Evolution, Molecular; Female; Genetic Variation; Genome; Humans; Male; MicroRNAs; Molecular Sequence Data; Proteins; Sequence Analysis, DNA; Species Specificity; Synteny

Genome-wide identification of allelic expression in hypertensive rats. - Dmitrieva, Renata I; Hinojos, Cruz A; Grove, Megan L; Bell, Rebecca J; Eric Boerwinkle; Fornage, Myriam; Doris, Peter A (Circ Cardiovasc Genet, 2009)
BACKGROUND: Identification of genes involved in complex cardiovascular disease traits has proven challenging. Inbred animal models can facilitate genetic studies of disease traits. The spontaneously hypertensive rat (SHR) is an inbred model of hypertension that exists in several closely related but genetically distinct lines. METHODS AND RESULTS: We used renal gene-expression profiling across 3 distinct SHR lines to identify genes that show different expression in SHR than in the genetically related normotensive control strain, Wistar-Kyoto. To ensure robust discovery of genes showing SHR-specific expression differences, we considered only those genes in which differential expression is replicated in multiple animals of each of multiple hypertensive rat lines at multiple time points during the ontogeny of hypertension. Mutation analysis was performed on the identified genes to uncover allelic variation. We identified those genes in which all SHR lines share a single allele of the gene when normotensive controls (Wistar-Kyoto) have fixed the alternative allele. We then identified which of the differentially expressed genes show expression that is controlled by the alleleic variation present in and around the gene. Allelic expression was demonstrated by observing the effect on gene expression of alleles inherited in the freely segregating F(2) progeny of a cross between SHR and Wistar-Kyoto animals. CONCLUSIONS: The result of these studies is the identification of several genes (Ptprj, Ela1, Dapk-2, and Gstt2) in which each of 4 SHR lines examined have fixed the same allele and in which each of 2 Wistar-Kyoto lines have a contrasting allele for which the inherited allele influences the level of gene expression. We further show that alleles of these genes lie in extensive haplotype blocks that have been inherited identical by descent in the hypertensive lines.
Keywords: Alleles; Animals; Blood Pressure; Disease Models, Animal; Female; Gene Expression Profiling; Genome-Wide Association Study; Humans; Hypertension; Kidney; Male; Pedigree; Polymorphism, Single Nucleotide; Rats; Rats, Inbred SHR; Rats, Inbred WKY

Genome-wide survey of SNP variation uncovers the genetic structure of cattle breeds. - Richard A Gibbs; Taylor, Jeremy F; Van Tassell, Curtis P; Barendse, William; Eversole, Kellye A; Gill, Clare A; Green, Ronnie D; Hamernik, Debora L; Kappes, Steven M; Lien, Sigbjørn; Matukumalli, Lakshmi K; McEwan, John C; et al. (Science, 2009)
The imprints of domestication and breed development on the genomes of livestock likely differ from those of companion animals. A deep draft sequence assembly of shotgun reads from a single Hereford female and comparative sequences sampled from six additional breeds were used to develop probes to interrogate 37,470 single-nucleotide polymorphisms (SNPs) in 497 cattle from 19 geographically and biologically diverse breeds. These data show that cattle have undergone a rapid recent decrease in effective population size from a very large ancestral population, possibly due to bottlenecks associated with domestication, selection, and breed formation. Domestication and artificial selection appear to have left detectable signatures of selection within the cattle genome, yet the current levels of diversity within breeds are at least as great as exists within humans.
Keywords: Animals; Breeding; Cattle; Female; Gene Frequency; Genetic Variation; Genome; Male; Molecular Sequence Data; Mutation; Polymorphism, Single Nucleotide; Population Density

Kininogen gene (KNG) variation has a consistent effect on aldosterone response to antihypertensive drug therapy: the GERA study. - Barbalic, Maja; Schwartz, Gary L; Chapman, Arlene B; Turner, Stephen T; Eric Boerwinkle (Physiol Genomics, 2009)
Recent experimental and clinical studies suggested that apart from playing an essential role in blood pressure homeostasis, aldosterone is involved in the pathophysiology of cardiovascular and renal diseases by inducing structural changes in the heart, kidney, and vessel wall. The interindividual variation of aldosterone response to antihypertensive treatment is considerable, and is at least partially explained by genetic variation. In this study, we investigated aldosterone response to two antihypertensive drugs-a thiazide diuretic and an angiotensin receptor blocker (ARB). Genetic variations in 50 candidate genes were tested for association with aldosterone response in four independent samples: African American (AA) responders to a diuretic (n = 289), AA responders to an ARB (n = 252), European American (EA) responders to a diuretic (n = 295) and EA responders to an ARB (n = 300). Linear regression was used to test the association with inclusion of age, sex, and body mass index as covariates. The results indicated the existence of one or more variants in the kininogen gene (KNG) that influence interindividual variation in aldosterone response. The significant association was replicated in three of four studied groups. The single nucleotide polymorphism rs4686799 was associated in AA and EA responders to the diuretic (P = 0.04 and P = 0.07, respectively), and rs5030062 and rs698078 were significantly associated in EA responders to the diuretic (P = 0.05 and P = 0.01) and EA responders to the ARB (P = 0.04 and P = 0.02). Although the clinical implication of KNG gene variation to antihypertensive drug response is yet to be determined, this novel candidate locus provides important new insights into drug response physiology.
Keywords: Adult; Aldosterone; Antihypertensive Agents; Female; Genetic Variation; Genotype; Humans; Kininogens; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide

Microarray analysis of somatostatin receptor 5-regulated gene expression profiles in murine pancreas. - Patel, Sanjeet G; Zhou, Guisheng; Liu, Shi-He; Li, Min; Jeong, Jae-Wook; DeMayo, Francesco J; Marie-Claude Gingras; Richard A Gibbs; Fisher, William E; Brunicardi, F Charles (World J Surg, 2009)
BACKGROUND: We previously demonstrated that somatostatin receptor type 5 (SSTR5) gene ablation results in alterations in insulin secretion and glucose metabolism, accompanied by morphologic alterations in the islets of Langerhans. The underlying mechanism(s) by which SSTR5 exerts its cellular functions remain(s) unknown. We hypothesized that SSTR5 mediates the inhibitory effect of somatostatin (SST) on insulin secretion and islet proliferation by regulating a specific set of pancreatic genes. METHODS: To identify SSTR5-regulated pancreatic genes, gene expression microarray analysis was performed on the whole pancreas of 1- and 3-month-old wild-type (WT) and SSTR5 knockout (SSTR5-/-) male mice. Real-time RT-PCR and immunofluorescence were performed to validate selected differentially expressed genes. RESULTS: A set of 143 probes were identified to be differentially expressed in the pancreas of 1-month-old SSTR5-/- mice, 72 of which were downregulated and 71 upregulated. At 3 months of age, SSTR5 gene ablation resulted in downregulation of a set of 30 probes and upregulation of a set of 37 probes. Among these differentially expressed genes, there were 15 and 5 genes that were upregulated and downregulated, respectively, in mice at both 1 and 3 months of age. Three genes, PAP/INGAP, ANG, and TDE1, were selected to be validated by real-time RT-PCR and immunofluorescence. CONCLUSIONS: A specific set of genes linked to a wide range of cellular functions such as islet proliferation, apoptosis, angiogenesis, and tumorigenesis were either upregulated or downregulated in SSTR5-deficient male mice compared with their expression in wild-type mice. Therefore, these genes are potential SSTR5-regulated genes during normal pancreatic development and functional maintenance.
Keywords: Animals; Apoptosis; Cell Proliferation; Down-Regulation; Fluorescent Antibody Technique; Gene Expression Profiling; Islets of Langerhans; Male; Mice; Mice, Knockout; Neoplasm Proteins; Neovascularization, Pathologic; Oligonucleotide Array Sequence Analysis; Pancreas; Pancreatitis-Associated Proteins; Proteins; Receptors, Cell Surface; Receptors, Somatostatin; Reverse Transcriptase Polymerase Chain Reaction; Ribonuclease, Pancreatic; Up-Regulation

Mutation survey of known LCA genes and loci in the Saudi Arabian population. - Yumei Li; Wang, Hui; Peng, Jianlan; Richard A Gibbs; Lewis, Richard Alan; Lupski, James R; Mardon, Graeme; Rui Chen (Invest Ophthalmol Vis Sci, 2009)
PURPOSE: The purpose of this study was to perform a comprehensive survey of all known Leber congenital amaurosis (LCA) genes and loci in a collection of 37 consanguineous LCA families from Saudi Arabia. METHODS: Direct PCR and sequencing were used to screen 13 known LCA genes (GUCY2D, CRX, RPE65, TULP1, AIPL1, CRB1, RPGRIP1, LRAT, RDH12, IMPDH1, CEP290, RD3, LCA5). In addition, families without mutations identified were further screened with STR markers around these 13 known LCA genes and two loci. RESULTS: Disease-causing mutations were identified in nine of the 37 families: five in TULP1, two in CRB1, one in RPE65, and one in GUCY2D. Mutations in known genes only accounted for 24% of the Saudi families--much less than what has been observed in the European population (65%). Phenotype-genotype analysis was carried out to investigate the LCA disease penetrance for all families whose mutations identified. All identified mutations were found to segregate perfectly with the disease phenotype. On the other hand, severity of the disease varies for different patients carrying the same mutation and even within the same family. Furthermore, based on homozygosity mapping with both STR and SNP markers, one family is likely to map to the LCA3 locus. CONCLUSIONS: These results underscore the importance of studying LCA disease families from different ethnic backgrounds to identify additional novel LCA disease genes. Furthermore, perfect segregation between mutation and disease indicates that LCA is fully penetrant. However, phenotypic variations among patients carrying the same mutation suggest that at least some of the variations in the clinical phenotype is due to modification from the genetic background, environment, or other factors.
Keywords: Blindness; Carrier Proteins; cis-trans-Isomerases; Consanguinity; DNA Mutational Analysis; Eye Proteins; Female; Genes; Genotype; Guanylate Cyclase; Humans; Male; Membrane Proteins; Microsatellite Repeats; Mutation; Nerve Tissue Proteins; Pedigree; Phenotype; Polymerase Chain Reaction; Receptors, Cell Surface; Retinal Degeneration; Saudi Arabia

Mutations in smooth muscle alpha-actin (ACTA2) cause coronary artery disease, stroke, and Moyamoya disease, along with thoracic aortic disease. - Guo, Dong-chuan; Papke, Christina L; Tran-Fadulu, Van; Regalado, Ellen S; Avidan, Nili; Johnson, Ralph Jay; Kim, Dong H; Pannu, Hariyadarshi; Willing, Marcia C; Sparks, Elizabeth; Pyeritz, Reed E; Singh, Michael N; et al. (Am J Hum Genet, 2009)
The vascular smooth muscle cell (SMC)-specific isoform of alpha-actin (ACTA2) is a major component of the contractile apparatus in SMCs located throughout the arterial system. Heterozygous ACTA2 mutations cause familial thoracic aortic aneurysms and dissections (TAAD), but only half of mutation carriers have aortic disease. Linkage analysis and association studies of individuals in 20 families with ACTA2 mutations indicate that mutation carriers can have a diversity of vascular diseases, including premature onset of coronary artery disease (CAD) and premature ischemic strokes (including Moyamoya disease [MMD]), as well as previously defined TAAD. Sequencing of DNA from patients with nonfamilial TAAD and from premature-onset CAD patients independently identified ACTA2 mutations in these patients and premature onset strokes in family members with ACTA2 mutations. Vascular pathology and analysis of explanted SMCs and myofibroblasts from patients harboring ACTA2 suggested that increased proliferation of SMCs contributed to occlusive diseases. These results indicate that heterozygous ACTA2 mutations predispose patients to a variety of diffuse and diverse vascular diseases, including TAAD, premature CAD, ischemic strokes, and MMD. These data demonstrate that diffuse vascular diseases resulting from either occluded or enlarged arteries can be caused by mutations in a single gene and have direct implications for clinical management and research on familial vascular diseases.
Keywords: Actins; Adolescent; Adult; Aortic Aneurysm, Thoracic; Aortic Dissection; Cell Proliferation; Cells, Cultured; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Models, Molecular; Moyamoya Disease; Mutation; Myocytes, Smooth Muscle; Protein Isoforms; Stroke; Young Adult

Replication of long-bone length QTL in the F9-F10 LG,SM advanced intercross. - Norgard, Elizabeth A; Jarvis, Joseph P; Roseman, Charles C; Maxwell, Taylor J; Kenney-Hunt, Jane P; Samocha, Kaitlin E; Pletscher, L Susan; Wang, Bing; Fawcett, Gloria L; Leatherwood, Christopher J; Wolf, Jason B; Cheverud, James M (Mamm Genome, 2009)
Quantitative trait locus (QTL) mapping techniques are frequently used to identify genomic regions associated with variation in phenotypes of interest. However, the F(2) intercross and congenic strain populations usually employed have limited genetic resolution resulting in relatively large confidence intervals that greatly inhibit functional confirmation of statistical results. Here we use the increased resolution of the combined F(9) and F(10) generations (n = 1455) of the LG,SM advanced intercross to fine-map previously identified QTL associated with the lengths of the humerus, ulna, femur, and tibia. We detected 81 QTL affecting long-bone lengths. Of these, 49 were previously identified in the combined F(2)-F(3) population of this intercross, while 32 represent novel contributors to trait variance. Pleiotropy analysis suggests that most QTL affect three to four long bones or serially homologous limb segments. We also identified 72 epistatic interactions involving 38 QTL and 88 novel regions. This analysis shows that using later generations of an advanced intercross greatly facilitates fine-mapping of confidence intervals, resolving three F(2)-F(3) QTL into multiple linked loci and narrowing confidence intervals of other loci, as well as allowing identification of additional QTL. Further characterization of the biological bases of these QTL will help provide a better understanding of the genetics of small variations in long-bone length.
Keywords: Animals; Bone and Bones; Crosses, Genetic; DNA Replication; Female; Hybridization, Genetic; Male; Mice; Organ Size; Quantitative Trait Loci

Serotonin transporter binding and genotype in the nonhuman primate brain using [C-11]DASB PET. - Christian, B T; Fox, A S; Oler, J A; Vandehey, N T; Murali, D; Rogers, J; Oakes, T R; Shelton, S E; Davidson, R J; Kalin, N H (Neuroimage, 2009)
UNLABELLED: The length polymorphism of the serotonin (5-HT) transporter gene promoter region has been implicated in altered 5-HT function and, in turn, neuropsychiatric illnesses, such as anxiety and depression. The nonhuman primate has been used as a model to study anxiety-related mechanisms in humans based upon similarities in behavior and the presence of a similar 5-HT transporter gene polymorphism. Stressful and threatening contexts in the nonhuman primate model have revealed 5-HT transporter genotype dependent differences in regional glucose metabolism. Using the rhesus monkey, we examined the extent to which serotonin transporter genotype is associated with 5-HT transporter binding in brain regions implicated in emotion-related pathology. METHODS: Genotype data and high resolution PET scans were acquired in 29 rhesus (Macaca mulatta) monkeys. [C-11]DASB dynamic PET scans were acquired for 90 min in the anesthetized animals and images of distribution volume ratio (DVR) were created to serve as a metric of 5-HT transporter binding for group comparison based on a reference region method of analysis. Regional and voxelwise statistical analysis were performed with corrections for anatomical differences in gray matter probability, sex, age and radioligand mass. RESULTS: There were no significant differences when comparing l/l homozygotes with s-carriers in the regions of the brain implicated in anxiety and mood related illnesses (amygdala, striatum, thalamus, raphe nuclei, temporal and prefrontal cortex). There was a significant sex difference in 5-HT transporter binding in all regions with females having 18%-28% higher DVR than males. CONCLUSIONS: Because these findings are consistent with similar genotype findings in humans, this further strengthens the use of the rhesus model for studying anxiety-related neuropathologies.
Keywords: Aniline Compounds; Animals; Brain; Carbon Radioisotopes; Female; Genotype; Humans; Macaca mulatta; Male; Positron-Emission Tomography; Protein Binding; Radiopharmaceuticals; Serotonin Plasma Membrane Transport Proteins; Sulfides; Tissue Distribution

A simple and evolutional approach proven to recanalise the nasolacrimal duct obstruction. - Chen, D; Ge, J; Wang, L; Gao, Q; Ma, P; Li, N; Li, D-Q; Wang, Z (Br J Ophthalmol, 2009)
AIM: To evaluate a new approach of recanalisation of nasolacrimal duct obstruction (RC-NLDO) in the treatment of the nasolacrimal duct obstruction (NLDO) and chronic dacryocystitis. METHODS: 583 patients with 641 eyes suffering from NLDO and chronic dacryocystitis were enrolled in this study. The RC-NLDO was performed in 506 eyes, with 135 eyes undergoing external dacryocystorhinostomy (EX-DCR) as controls. Patient follow-up for 54 months was evaluated by symptoms, dye disappearance test, lacrimal irrigation and digital subtraction dacryocystogram. The RC-NLDO was also performed in 12 rhesus monkeys for histopathological examination. RESULTS: The clinical success rates were 93.1% in 506 cases of RC-NLDO and 91.11% in 135 cases of EX-DCR. The success rates for second surgery were achieved in 85.19% on RC-NLDO and 40.0% on EX-DCR. No major intra- or postoperative complications were observed in the RC-NLDO group. The mean operative duration was 12.5 min for RC-NLDO and 40.3 min for EX-DCR (p<0.001). A pathological study in rhesus monkeys demonstrated that the RC-NLDO wounded epithelium in nasolacrimal duct healed completely within 1 month without granulation tissue formation. CONCLUSION: The findings demonstrate that the RC-NLDO is a simple and effective approach proven to recanalise the obstructed nasolacrimal duct with a comparable success rate to EX-DCR.
Keywords: Animals; Catheterization; Dacryocystorhinostomy; Equipment Design; Female; Humans; Lacrimal Duct Obstruction; Macaca mulatta; Male; Middle Aged; Nasolacrimal Duct; Postoperative Care; Wound Healing

APOE/C1/C4/C2 hepatic control region polymorphism influences plasma apoE and LDL cholesterol levels. - Klos, Kathy; Shimmin, Lawrence; Ballantyne, Christie; Eric Boerwinkle; Clark, Andrew; Coresh, Josef; Hanis, Craig; Liu, Kiang; Sayre, Scott; Hixson, James (Hum Mol Genet, 2008)
We characterized 102 kb of chromosome 19 containing the apolipoprotein (APO) E/C1/C4/C2 cluster and two flanking genes for common DNA variants associated with plasma low-density lipoprotein cholesterol (LDL-C) level. DNA variants were identified by comparing sequences of 48 haploid hybrid cell lines. We genotyped participants (1943 Whites and 2046 African-Americans) of the Coronary Artery Risk Development in Young Adults study for 115 variants. After controlling for the effects of the APOE epsilon2/3/4 polymorphism, a single nucleotide polymorphism, rs35136575, in the downstream hepatic control region 2 (HCR-2) was associated with LDL-C in Caucasians (P = 0.0004), accounting for 1% of variation. We genotyped rs35136575 in the Atherosclerosis Risk in Communities (ARIC) cohort (3679 African-Americans and 10 427 Whites) and in the Genetic Epidemiology Network of Arteriopathy (GENOA) sibships (1381 African-Americans in 592 sibships, 1116 Caucasians in 503 sibships and 1378 Mexican-Americans in 416 sibships), finding association with LDL-C level in ARIC Caucasians (P = 0.0064). Lower plasma LDL-C was observed with the rare allele. Plasma apoE level was strongly associated with HCR-2 variant genotype in all three GENOA samples (P </= 0.002), indicating an effect on apoE concentration. Patterns of association for plasma apo A-I, apoB, LDL-C, high-density lipoprotein cholesterol, total cholesterol and triglyceride levels with rs35136575 in the population-based samples evaluated in this study suggest a pleiotropic effect that may be context-dependent.
Keywords: Adult; Aged; Animals; Apolipoproteins; Apolipoproteins E; Black or African American; Cholesterol; Cholesterol, LDL; Chromosomes, Human, Pair 19; Female; Genotype; Humans; Hybrid Cells; Male; Mexican Americans; Mice; Middle Aged; Polymorphism, Single Nucleotide; United States; White People

Association of the complement factor H Y402H polymorphism with cardiovascular disease is dependent upon hypertension status: The ARIC study. - Volcik, Kelly A; Ballantyne, Christie M; Braun, Michael C; Coresh, Josef; Mosley, Thomas H; Eric Boerwinkle (Am J Hypertens, 2008)
BACKGROUND: Complement factor H (CFH) is a plasma protein that is essential in the regulation of the alternative complement pathway and has been implicated as taking part in complement inhibition in atherogenesis. We evaluated the association of the Y402H polymorphism with incident coronary heart disease (CHD), incident ischemic stroke, and carotid artery wall thickness (intima-media thickness (IMT)) in the Atherosclerosis Risk in Communities (ARIC) cohort. METHODS: Incident ischemic stroke and CHD were identified through annual telephone calls and hospital and death certificate surveillance. Carotid IMT was measured by means of high-resolution B-mode ultrasound. Four hundred eighty-three validated ischemic stroke and 1,544 CHD events were identified. Because of allele frequency differences between whites and African Americans, analyses were performed separately according to the racial group. RESULTS: The 402HH homozygous genotype was a significant predictor of incident ischemic stroke in whites (hazard rate ratio (HRR) 1.47, 95% confidence interval (CI) 1.05-2.05). Significant interaction effects between genotype and hypertension were observed for CHD in whites and for cIMT in whites and African Americans. In further analyses of incident CHD, genotypes carrying the 402H allele were a significant predictor of incident CHD in whites who had hypertension (402YH: HRR 1.19, 95% CI 1.01-1.40; 402HH: HRR 1.28, 95% CI 1.04-1.57). The 402H allele was also associated with higher cIMT measures for whites in the overall cohort, and for whites with hypertension. CONCLUSION: The CFH 402H allele was associated with an increased risk for incident CHD and ischemic stroke in whites, with the strength and significance of the association dependent upon hypertension status.
Keywords: Black or African American; Brain Ischemia; Cardiovascular Diseases; Carotid Artery Diseases; Complement Factor H; Coronary Disease; Female; Gene Frequency; Genetic Predisposition to Disease; Homozygote; Humans; Hypertension; Male; Middle Aged; Polymorphism, Genetic; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Stroke; United States; White People

The complete genome of an individual by massively parallel DNA sequencing. - Wheeler, David A; Srinivasan, Maithreyan; Egholm, Michael; Shen, Yufeng; Chen, Lei; McGuire, Amy; He, Wen; Chen, Yi-Ju; Makhijani, Vinod; Roth, G Thomas; Gomes, Xavier; Tartaro, Karrie; et al. (Nature, 2008)
The association of genetic variation with disease and drug response, and improvements in nucleic acid technologies, have given great optimism for the impact of 'genomic medicine'. However, the formidable size of the diploid human genome, approximately 6 gigabases, has prevented the routine application of sequencing methods to deciphering complete individual human genomes. To realize the full potential of genomics for human health, this limitation must be overcome. Here we report the DNA sequence of a diploid genome of a single individual, James D. Watson, sequenced to 7.4-fold redundancy in two months using massively parallel sequencing in picolitre-size reaction vessels. This sequence was completed in two months at approximately one-hundredth of the cost of traditional capillary electrophoresis methods. Comparison of the sequence to the reference genome led to the identification of 3.3 million single nucleotide polymorphisms, of which 10,654 cause amino-acid substitution within the coding sequence. In addition, we accurately identified small-scale (2-40,000 base pair (bp)) insertion and deletion polymorphism as well as copy number variation resulting in the large-scale gain and loss of chromosomal segments ranging from 26,000 to 1.5 million base pairs. Overall, these results agree well with recent results of sequencing of a single individual by traditional methods. However, in addition to being faster and significantly less expensive, this sequencing technology avoids the arbitrary loss of genomic sequences inherent in random shotgun sequencing by bacterial cloning because it amplifies DNA in a cell-free system. As a result, we further demonstrate the acquisition of novel human sequence, including novel genes not previously identified by traditional genomic sequencing. This is the first genome sequenced by next-generation technologies. Therefore it is a pilot for the future challenges of 'personalized genome sequencing'.
Keywords: Alleles; Computational Biology; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Genomics; Genotype; Humans; Individuality; Male; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Reproducibility of Results; Sensitivity and Specificity; Sequence Alignment; Sequence Analysis, DNA; Software

Comprehensive genomic characterization defines human glioblastoma genes and core pathways. (Nature, 2008)
Human cancer cells typically harbour multiple chromosomal aberrations, nucleotide substitutions and epigenetic modifications that drive malignant transformation. The Cancer Genome Atlas (TCGA) pilot project aims to assess the value of large-scale multi-dimensional analysis of these molecular characteristics in human cancer and to provide the data rapidly to the research community. Here we report the interim integrative analysis of DNA copy number, gene expression and DNA methylation aberrations in 206 glioblastomas--the most common type of adult brain cancer--and nucleotide sequence aberrations in 91 of the 206 glioblastomas. This analysis provides new insights into the roles of ERBB2, NF1 and TP53, uncovers frequent mutations of the phosphatidylinositol-3-OH kinase regulatory subunit gene PIK3R1, and provides a network view of the pathways altered in the development of glioblastoma. Furthermore, integration of mutation, DNA methylation and clinical treatment data reveals a link between MGMT promoter methylation and a hypermutator phenotype consequent to mismatch repair deficiency in treated glioblastomas, an observation with potential clinical implications. Together, these findings establish the feasibility and power of TCGA, demonstrating that it can rapidly expand knowledge of the molecular basis of cancer.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Brain Neoplasms; DNA Methylation; DNA Modification Methylases; DNA Repair; DNA Repair Enzymes; Female; Gene Dosage; Gene Expression Regulation, Neoplastic; Genes, erbB-1; Genes, Tumor Suppressor; Genome, Human; Genomics; Glioblastoma; Humans; Male; Middle Aged; Models, Molecular; Mutation; Neurofibromin 1; Phosphatidylinositol 3-Kinases; Protein Structure, Tertiary; Retrospective Studies; Signal Transduction; Tumor Suppressor Proteins

ESR1 polymorphism is associated with plasma lipid and apolipoprotein levels in Caucasians of the Rochester Family Heart Study. - Klos, Kathy L E; Eric Boerwinkle; Ferrell, Robert E; Turner, Stephen T; Morrison, Alanna C (J Lipid Res, 2008)
We evaluated six estrogen receptor 1 (ESR1) polymorphisms for association with ten plasma lipid and apolipoprotein traits in 1,847 individuals (941 females and 906 males) in the multi-generation Rochester Family Heart Study using a generalized estimating equation approach. Apolipoprotein A-I (apoA-I), apoA-II, and HDL-cholesterol (HDL-C) were associated with exon 4 rs1801132 (Pro325Pro) genotype (P = 0.0044, P = 0.0048, and P = 0.0035, respectively). Positive correlation between levels of apoA-I, apoA-II, and HDL-C and the number of G alleles was observed in females (P = 0.0120, P = 0.0032, and P = 0.0030), but not males (P > 0.05). Because few studies have evaluated the effect of ESR1 gene polymorphisms on lipid traits in children, we also stratified our sample at the age of 15 years. There was evidence of association between intron 1 single-nucleotide polymorphisms rs9322331 and rs9340799 and apoC-II, and triglycerides (TGs) in youths 15 years and younger. In youths, evidence of association between rs9322331 and rs9340799 and apoC-II was stronger in males (P = 0.0036 and P = 0.0124) than in females (P > 0.05), whereas evidence of association with TG was stronger in females (P = 0.0030 and P = 0.0024) than in males (P > 0.05). These findings suggest that ESR1 variation plays an age- and sex-dependent role in determining plasma lipid and apolipoprotein levels.
Keywords: Adolescent; Adult; Aged; Apolipoprotein A-I; Apolipoprotein A-II; Apolipoproteins; Cholesterol, HDL; Estrogen Receptor alpha; Female; Humans; Male; Polymorphism, Genetic; Triglycerides; White People

Genetic architecture of adiposity and organ weight using combined generation QTL analysis. - Fawcett, Gloria L; Roseman, Charles C; Jarvis, Joseph P; Wang, Bing; Wolf, Jason B; Cheverud, James M (Obesity (Silver Spring), 2008)
We present here a detailed study of the genetic contributions to adult body size and adiposity in the LG,SM advanced intercross line (AIL), an obesity model. This study represents a first step in fine-mapping obesity quantitative trait loci (QTLs) in an AIL. QTLs for adiposity in this model were previously isolated to chromosomes 1, 6, 7, 8, 9, 12, 13, and 18. This study focuses on heritable contributions and the genetic architecture of fatpad and organ weights. We analyzed both the F(2) and F(3) generations of the LG,SM AIL population single-nucleotide polymorphism (SNP) genotyped with a marker density of approximately 4 cM. We replicate 88% of the previously identified obesity QTLs and identify 13 new obesity QTLs. Nearly half of the single-trait QTLs were sex-specific. Several broad QTL regions were resolved into multiple, narrower peaks. The 113 single-trait QTLs for organs and body weight clustered into 27 pleiotropic loci. A large number of epistatic interactions are described which begin to elucidate potential interacting molecular networks. We present a relatively rapid means to obtain fine-mapping details from AILs using dense marker maps and consecutive generations. Analysis of the complex genetic architecture underlying fatpad and organ weights in this model may eventually help to elucidate not only heritable contributions to obesity but also common gene sets for obesity and its comorbidities.
Keywords: Adipose Tissue; Adiposity; Animals; Disease Models, Animal; Epistasis, Genetic; Female; Kidney; Liver; Male; Mice; Mice, Inbred Strains; Myocardium; Obesity; Organ Size; Quantitative Trait Loci; Sex Characteristics; Spleen

Genetic influences on behavioral inhibition and anxiety in juvenile rhesus macaques. - Rogers, J; Shelton, S E; Shelledy, W; Garcia, R; Kalin, N H (Genes Brain Behav, 2008)
In humans and other animals, behavioral responses to threatening stimuli are an important component of temperament. Among children, extreme behavioral inhibition elicited by novel situations or strangers predicts the subsequent development of anxiety disorders and depression. Genetic differences among children are known to affect risk of developing behavioral inhibition and anxiety, but a more detailed understanding of genetic influences on susceptibility is needed. Nonhuman primates provide valuable models for studying the mechanisms underlying human behavior. Individual differences in threat-induced behavioral inhibition (freezing behavior) in young rhesus monkeys are stable over time and reflect individual levels of anxiety. This study used the well-established human intruder paradigm to elicit threat-induced freezing behavior and other behavioral responses in 285 young pedigreed rhesus monkeys. We examined the overall influence of quantitative genetic variation and tested the specific effect of the serotonin transporter promoter repeat polymorphism. Quantitative genetic analyses indicated that the residual heritability of freezing duration (behavioral inhibition) is h(2) = 0.384 (P = 0.012) and of 'orienting to the intruder' (vigilance) is h(2) = 0.908 (P = 0.00001). Duration of locomotion and hostility and frequency of cooing were not significantly heritable. The serotonin transporter polymorphism showed no significant effect on either freezing or orienting to the intruder. Our results suggest that this species could be used for detailed studies of genetic mechanisms influencing extreme behavioral inhibition, including the identification of specific genes that are involved in predisposing individuals to such behavior.
Keywords: Animals; Anxiety Disorders; Behavior, Animal; Brain; Brain Chemistry; Disease Models, Animal; Fear; Female; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Genetic Variation; Inhibition, Psychological; Macaca mulatta; Male; Neural Inhibition; Polymorphism, Single Nucleotide; Serotonin; Serotonin Plasma Membrane Transport Proteins; Social Behavior

A genomewide linkage scan for quantitative trait loci influencing the craniofacial complex in baboons (Papio hamadryas spp.). - Sherwood, Richard J; Duren, Dana L; Havill, Lorena M; Jeffrey Rogers; Cox, Laura A; Towne, Bradford; Mahaney, Michael C (Genetics, 2008)
Numerous studies have detected significant contributions of genes to variation in development, size, and shape of craniofacial traits in a number of vertebrate taxa. This study examines 43 quantitative traits derived from lateral cephalographs of 830 baboons (Papio hamadryas) from the pedigreed population housed at the Southwest National Primate Research Center. Quantitative genetic analyses were conducted using the SOLAR analytic platform, a maximum-likelihood variance components method that incorporates all familial information for parameter estimation. Heritability estimates were significant and of moderate to high magnitude for all craniofacial traits. Additionally, 14 significant quantitative trait loci (QTL) were identified for 12 traits from the three developmental components (basicranium, splanchnocranium, and neurocranium) of the craniofacial complex. These QTL were found on baboon chromosomes (and human orthologs) PHA1 (HSA1), PHA 2 (HSA3), PHA4 (HSA6), PHA11 (HSA12), PHA13 (HSA2), PHA16 (HSA17), and PHA17 (HSA13) (PHA, P. hamadryas; HSA, Homo sapiens). This study of the genetic architecture of the craniofacial complex in baboons provides the groundwork needed to establish the baboon as an animal model for the study of genetic and nongenetic influences on craniofacial variation.
Keywords: Animals; Anthropometry; Female; Genetic Linkage; Genetic Variation; Genome; Humans; Likelihood Functions; Male; Models, Biological; Models, Genetic; Papio hamadryas; Quantitative Trait Loci; Skull; Species Specificity

Genomic imprinting effects on adult body composition in mice. - Cheverud, James M; Hager, Reinmar; Roseman, Charles; Fawcett, Gloria; Wang, Bing; Wolf, Jason B (Proc Natl Acad Sci U S A, 2008)
Genomic imprinting results in the differential expression of genes, depending on which allele is inherited from the mother and which from the father. The effects of such differential gene expression are reflected in phenotypic differences between the reciprocal heterozygotes (Aa vs. aA). Although many imprinted genes have been identified and play a key role in development, little is known about the contribution of imprinting to quantitative variation in trait expression. Here, we examine this problem by mapping imprinting effects on adult body composition traits in the F(3) generation of an intercross between the Large (LG/J) and Small (SM/J) inbred mouse strains. We identified eight pleiotropic imprinted quantitative trait loci (iQTL) located throughout the genome. Most iQTL are in novel locations that have not previously been associated with imprinting effects, but those on chromosomes 7, 12, and centromeric 18 lie in regions previously identified as containing imprinted genes. Our results show that the effects of genomic imprinting are relatively small, with reciprocal heterozygotes differing by approximately 0.25 standard deviation units and the effects at each locus accounting for 1% to 4% of the phenotypic variance. We detected a variety of imprinting patterns, with paternal expression being the most common. These results indicate that genomic imprinting has small, but detectable, effects on the normal variation of complex traits in adults and is likely to be more common than usually thought.
Keywords: Aging; Animals; Body Composition; Body Weight; Female; Genomic Imprinting; Male; Mice; Quantitative Trait Loci

Genotype-by-diet effects on co-variation in Lp-PLA2 activity and LDL-cholesterol concentration in baboons fed an atherogenic diet. - Vinson, Amanda; Mahaney, Michael C; Diego, Vince P; Cox, Laura A; Jeffrey Rogers; VandeBerg, John L; Rainwater, David L (J Lipid Res, 2008)
Both lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) activity, a biomarker of inflammation, and concentration of its primary associated lipoprotein, LDL, are correlated with adverse coronary outcomes. We previously reported a quantitative trait locus (QTL) corresponding to HSA2p24.3-p23.2 with pleiotropic effects on Lp-PLA(2) activity and LDL-cholesterol (LDL-C) concentration in baboons fed a basal diet. Here, our goal was to locate pleiotropic QTLs influencing both traits in the same baboons fed a high-cholesterol, high-fat (HCHF) diet, and to assess whether shared genetic effects on these traits differ between diets. We assayed Lp-PLA(2) activity and LDL-C concentration in 683 baboons fed the HCHF diet. We used a bivariate maximum likelihood-based variance components approach in whole-genome linkage screens to locate a QTL [logarithm of odds (LOD) = 3.13, genome-wide P = 0.019] corresponding to HSA19q12-q13.2 with pleiotropic effects on Lp-PLA(2) activity and LDL-C levels in the HCHF diet. We additionally found significant evidence of genetic variance in response to diet for Lp-PLA(2) activity (P = 0.0017) and for LDL-C concentration (P = 0.00001), revealing a contribution of genotype-by-diet interaction to covariation in these two traits. We conclude that the pleiotropic QTLs detected at 2p24.3-p23.2 and 19q12-q13.2 on the basal and HCHF diets, respectively, exert diet-specific effects on covariation in Lp-PLA(2) activity and LDL-C concentration.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Animals; Cholesterol, LDL; Dietary Fats; Female; Genetic Predisposition to Disease; Genotype; Male; Papio; Quantitative Trait Loci; Risk Factors

Hepatocyte nuclear factor 1 and hypertensive nephropathy. - Dmitrieva, Renata I; Hinojos, Cruz A; Eric Boerwinkle; Braun, Michael C; Fornage, Myriam; Doris, Peter A (Hypertension, 2008)
Hypertension in spontaneously hypertensive rat (SHR) is associated with renal redox stress, and we hypothesized that nephropathy arises in SHR-A3 from altered capacity to mitigate redox stress compared with nephropathy-resistant SHR lines. We measured renal expression of redox genes in distinct lines of the spontaneously hypertensive rat (SHR-A3, SHR-B2, SHR-C) and the normotensive Wistar-Kyoto (WKY) strain. The SHR lines differ in either resisting (SHR-B2, SHR-C) or experiencing hypertensive nephropathy (SHR-A3). Immediately before the emergence of hypertensive renal injury expression of redox genes in SHR-A3 was profoundly altered compared with the injury-resistant SHR lines and WKY. This change appeared to arise in antioxidant genes where 16 of 28 were expressed at 34.3% of the level in the reference strain (WKY). No such change was observed in the injury-resistant SHR lines. We analyzed occurrence of transcription factor matrices in the promoters of the downregulated antioxidant genes. In these genes, the hepatocyte nuclear factor 1 (HNF1) transcription factor matrix was found to be nearly twice as likely to be present and the overall frequency of HNF1 sites was nearly 5 times higher, compared with HNF1 transcription factor matrices in antioxidant genes that were not downregulated. We identified 35 other (nonredox) renal genes regulated by HNF1. These were also significantly downregulated in SHR-A3, but not in SHR-B2 or SHR-C. Finally, expression of genes that comprise HNF1 (Tcf1, Tcf2, and Dcoh) was also downregulated in SHR-A3. The present experiments uncover a major change in transcriptional control by HNF1 that affects redox and other genes and precedes emergence of hypertensive renal injury.
Keywords: Animal Feed; Animals; Blood Pressure; Gene Expression Profiling; Hepatocyte Nuclear Factor 1; Hypertension, Renal; Kidney; Male; Oxidation-Reduction; Oxidative Stress; Rats; Rats, Inbred SHR; Rats, Inbred WKY; Transcription, Genetic

Identification of quantitative trait loci affecting murine long bone length in a two-generation intercross of LG/J and SM/J Mice. - Norgard, Elizabeth A; Roseman, Charles C; Fawcett, Gloria L; Pavlicev, Mihaela; Morgan, Clinton D; Pletscher, L Susan; Wang, Bing; Cheverud, James M (J Bone Miner Res, 2008)
INTRODUCTION: Study of mutations with large phenotypic effects has allowed the identification of key players in skeletal development. However, the molecular nature of variation in large, phenotypically normal populations tends to be characterized by smaller phenotypic effects that remain undefined. MATERIALS AND METHODS: We use interval mapping and quantitative trait locus (QTL) mapping techniques in the combined F2-F3 populations (n = 2111) of an LG/J x SM/J mouse intercross to detect QTLs associated with the lengths of the humerus, ulna, femur, and tibia. RESULTS: Seventy individual trait QTLs affecting long bone lengths were detected, with several chromosomes harboring multiple QTLs. The genetic architecture suggests mainly small, additive effects on long bone length, with roughly one third of the QTLs displaying dominance. Sex interactions were common, and four sex-specific QTLs were observed. Pleiotropy could not be rejected for most of the QTLs identified. Thirty-one epistatic interactions were detected, almost all affecting regions including or immediately adjacent to QTLs. CONCLUSIONS: A complex regulatory network with many gene interactions modulates bone growth, possibly with integrated skeletal modules that allow fine-tuning of developmental processes present. Candidate genes in the QTL CIs include many genes known to affect endochondral bone growth and genes that have not yet been associated with bone growth or body size but have a strong potential to influence these traits.
Keywords: Animals; Bone and Bones; Chromosomes; Epistasis, Genetic; Female; Male; Mice; Quantitative Trait Loci

Longitudinal changes in triglycerides according to ANGPTL4[E40K] genotype and longitudinal body weight change in the atherosclerosis risk in communities study. - Nettleton, Jennifer A; Volcik, Kelly A; Demerath, Ellen W; Eric Boerwinkle; Folsom, Aaron R (Ann Epidemiol, 2008)
PURPOSE: Allelic variation in the adipokine angiopoietin-like 4 gene (ANGPTL4[E40K]) has been cross-sectionally associated with triglycerides, but the effects of genotype, or the interaction between genotype and body weight, on longitudinal triglyceride change have not been studied. METHODS: Body weight, triglycerides, and ANGPTL4[E40K] genotype were determined at baseline (1987-1989) and at 3 follow-up exams (1990-1992, 1993-1995, 1996-1998) in 7,939 white ANGPTL4[E40K] G allele homozygotes and 344 A allele carriers. Changes in body weight and triglycerides were characterized as the difference between exam 4 and baseline measurements. RESULTS: ANGPTL4[E40K] A allele carriers had triglyceride concentrations that were 15 to 18 mg/dL lower than G allele homozygotes at all exams (P<0.0001). Triglycerides increased in both genotype groups over the 9-year period (+19.1+/-0.9 and +16.2+/-4.1 mg/dL in GG and GA/AA, respectively; P difference, 0.48). Weight gain was associated with increased triglycerides to a comparable degree in both genotype groups (+5.5+/-0.3 and +4.3+/-0.9 mg/dL per 2-kg increase in body weight in GG and GA/AA, respectively, p interaction=0.30). CONCLUSIONS: Differences in triglyceride concentrations between ANGPTL4[E40K] A allele carriers and G allele homozygotes are maintained over time, but the degree of increase in triglycerides was similar between groups and was not modified by body weight changes.
Keywords: Aged; Angiopoietin-Like Protein 4; Angiopoietins; Atherosclerosis; Body Mass Index; Female; Humans; Longitudinal Studies; Male; Middle Aged; Risk Factors; Triglycerides; United States; Weight Gain

Nonhuman primates as models for studies of prostate specific antigen and prostatic diseases. - Mubiru, James N; Hubbard, Gene B; Dick, Edward J; Furman, Jaime; Troyer, Dean A; Jeffrey Rogers (Prostate, 2008)
BACKGROUND: Because prostate specific antigen (PSA) is released at increased levels into the blood early in the development of prostate cancer, benign prostatic hyperplasia (BPH) and prostatitis, it is widely used as a marker for these diseases. However, PSA has clinical limitations as a screen for prostatic diseases due to its low sensitivity and specificity. There is a strong need to better understand the biology of PSA and factors affecting its serum levels. METHODS: We evaluated cynomolgus macaques, rhesus macaques, baboons, and marmosets for their suitability as models for the study of PSA biology and prostatic diseases. RESULTS: Prostates of several nonhuman primates are anatomically similar to the human counterpart. Anti-human PSA antibody detected PSA antigens in all the Old World monkeys (cynomolgus macaques, rhesus macaques, and baboons) but not in marmosets. Of the Old World monkeys, cynomolgus macaques have the highest serum PSA levels; baboons have the lowest. Serum PSA levels from macaques includes a number of outlier samples with unusually high values. We also report two cases of abnormal pathologies in macaques accompanied by high serum PSA levels. One case consisted of prostatic hyperplasia involving both glandular and basal cells in a cynomolgus macaque and another of glandular hyperplasia and atrophy in a rhesus macaque. The finding that pathological changes in the prostate of macaques may lead to increases in serum PSA is worthy of further exploration. CONCLUSION: Cynomolgus macaques and rhesus macaques are promising animal models for PSA biology studies.
Keywords: Animals; Body Weight; Callithrix; Disease Models, Animal; Haplorhini; Immunoblotting; Macaca fascicularis; Macaca mulatta; Male; Organ Size; Papio; Prostate-Specific Antigen; Prostatic Hyperplasia; Prostatic Neoplasms; Racemases and Epimerases; Reverse Transcriptase Polymerase Chain Reaction; RNA

PDX-1 acts as a potential molecular target for treatment of human pancreatic cancer. - Liu, Shihe; Ballian, Nikiforos; Belaguli, Narasimhaswamy S; Patel, Sanjeet; Li, Min; Templeton, Nancy Smyth; Marie-Claude Gingras; Richard A Gibbs; Fisher, William; Brunicardi, F Charles (Pancreas, 2008)
OBJECTIVES: The purpose of this study was to investigate whether pancreatic and duodenal homeobox factor 1 (PDX-1) could serve as a potential molecular target for the treatment of pancreatic cancer. METHODS: Cell proliferation, invasion capacity, and protein levels of cell cycle mediators were determined in human pancreatic cancer cells transfected with mouse PDX-1 (mPDX-1) alone or with mPDX-1 short hairpin RNA (shRNA) and/or human PDX-1 shRNA (huPDX-1 shRNA). Tumor cell growth and apoptosis were also evaluated in vivo in PANC-1 tumor-bearing severe combined immunodeficient mice receiving multiple treatments of intravenous liposomal huPDX-1 shRNA. RESULTS: mPDX-1 overexpression resulted in the significant increase of cell proliferation and invasion in MIA PaCa2, but not PANC-1 cells. This effect was blocked by knocking down mPDX-1 expression with mPDX-1 shRNA. Silencing of huPDX-1 expression in PANC-1 cells inhibited cell proliferation in vitro and suppressed tumor growth in vivo which was associated with increased tumor cell apoptosis. PDX-1 overexpression resulted in dysregulation of the cell cycle with up-regulation of cyclin D, cyclin E, and Cdk2 and down-regulation of p27. CONCLUSIONS: PDX-1 regulates cell proliferation and invasion in human pancreatic cancer cells. Down-regulation of PDX-1 expression inhibits pancreatic cancer cell growth in vitro and in vivo, implying its use as a potential therapeutic target for the treatment of pancreatic cancer.
Keywords: Animals; Base Sequence; Biomarkers, Tumor; Cell Line, Tumor; Cell Proliferation; Homeodomain Proteins; Humans; Islets of Langerhans; Male; Mice; Mice, SCID; Molecular Sequence Data; Neoplasm Invasiveness; Neoplasm Transplantation; Pancreatic Neoplasms; RNA Interference; RNA, Small Interfering; Trans-Activators; Transfection; Transplantation, Heterologous

Peroxisome proliferator-activated receptor [alpha] genetic variation interacts with n-6 and long-chain n-3 fatty acid intake to affect total cholesterol and LDL-cholesterol concentrations in the Atherosclerosis Risk in Communities Study. - Volcik, Kelly A; Nettleton, Jennifer A; Ballantyne, Christie M; Eric Boerwinkle (Am J Clin Nutr, 2008)
BACKGROUND: Peroxisome proliferator-activated receptor-alpha (PPARA) regulates the expression of genes involved in lipid metabolism. The binding of polyunsaturated fatty acids (PUFAs) to PPARA results in rapid changes in the expression of genes involved in lipid oxidation, with long-chain n-3 fatty acids being potent activators of PPARA. OBJECTIVE: We evaluated the potential effect modification of PPARA genetic variation on the association between PUFA intake, specifically n-6 and long-chain n-3 fatty acid intakes, and multiple lipid measures in the large biethnic Atherosclerosis Risk in Communities (ARIC) Study. DESIGN: Study participants (10 134 whites and 3480 African Americans) were selected from the ARIC Study--a prospective investigation of atherosclerosis and its clinical sequelae. Multiple linear regression models were used to assess the relation between PPARA genotypes, as well as dietary fatty acid intake, and baseline lipid measures. PPARA-specific effects of variation were assessed by including genotype-by-fatty acid interaction terms in each statistical model. RESULTS: PPARA genotype frequencies were significantly different between whites and African Americans. No significant associations between lipid measures and PPARA genotype were observed in either whites or African Americans. Significant genotype-by-n-6 fatty acid intake interactions were observed only in whites for the 3'untranslated region (UTR) G-->A single nucleotide polymorphism (SNP) and total cholesterol (P = 0.03) and LDL cholesterol (P = 0.03). Significant genotype-by-long-chain n-3 fatty acid intake interactions were observed only in African Americans for the 3'UTR C-->T SNP and total cholesterol (P = 0.03) and LDL cholesterol (P = 0.02). CONCLUSIONS: Findings from the current study suggest that PPARA 3'UTR SNPs modulate the association between lipid concentrations and dietary n-6 fatty acid intake (in whites) and long-chain n-3 fatty acid intake (in African Americans) such that persons with homozygous variant genotypes have significantly lower total cholesterol and LDL-cholesterol measures when consuming higher quantities of n-6 or long-chain n-3 fatty acids.
Keywords: 3' Untranslated Regions; Atherosclerosis; Black People; Cholesterol; Cholesterol, LDL; Dietary Fats; Fatty Acids, Omega-3; Fatty Acids, Omega-6; Female; Gene Frequency; Genetic Variation; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; PPAR alpha; Risk Factors; United States; White People

A pleiotropic QTL on 2p influences serum Lp-PLA2 activity and LDL cholesterol concentration in a baboon model for the genetics of atherosclerosis risk factors. - Vinson, A; Mahaney, M C; Cox, L A; Rogers, J; VandeBerg, J L; Rainwater, D L (Atherosclerosis, 2008)
Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)), the major portion of which is bound to low-density lipoprotein, is an independent biomarker of cardiovascular disease risk. To search for common genetic determinants of variation in both Lp-PLA(2) activity and LDL cholesterol (LDL-C) concentration, we assayed these substances in serum from 679 pedigreed baboons. Using a maximum likelihood-based variance components approach, we detected significant evidence for a QTL affecting Lp-PLA(2) activity (LOD=2.79, genome-wide P=0.039) and suggestive evidence for a QTL affecting LDL-C levels (LOD=2.16) at the same location on the baboon ortholog of human chromosome 2p. Because we also found a significant genetic correlation between the two traits (rho(G)=0.50, P<0.00001), we conducted bivariate linkage analyses of Lp-PLA(2) activity and LDL-C concentration. These bivariate analyses improved the evidence (LOD=3.19, genome-wide P=0.015) for a QTL at the same location on 2p, corresponding to the human cytogenetic region 2p24.3-p23.2. The QTL-specific correlation between the traits (rho(Q)=0.62) was significantly different from both zero and 1 (P[rho(Q)=0]=0.047; P[rho(Q)=1]=0.022), rejecting the hypothesis of co-incident linkage and consistent with incomplete pleiotropy at this locus. We conclude that polymorphisms at the QTL described in this study exert some genetic effects that are shared between Lp-PLA(2) activity and LDL-C concentration.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Animals; Atherosclerosis; Cholesterol, LDL; Disease Models, Animal; Female; Male; Multivariate Analysis; Papio hamadryas; Quantitative Trait Loci; Risk Factors

Pulmonary alveolar proteinosis caused by deletion of the GM-CSFRalpha gene in the X chromosome pseudoautosomal region 1. - Martinez-Moczygemba, Margarita; Doan, Minh L; Elidemir, Okan; Fan, Leland L; Cheung, Sau Wai; Lei, Jonathan T; Moore, James P; Tavana, Ghamartaj; Lewis, Lora R; Zhu, Yiming; Donna M Muzny; Richard A Gibbs; et al. (J Exp Med, 2008)
Pulmonary alveolar proteinosis (PAP) is a rare lung disorder in which surfactant-derived lipoproteins accumulate excessively within pulmonary alveoli, causing severe respiratory distress. The importance of granulocyte/macrophage colony-stimulating factor (GM-CSF) in the pathogenesis of PAP has been confirmed in humans and mice, wherein GM-CSF signaling is required for pulmonary alveolar macrophage catabolism of surfactant. PAP is caused by disruption of GM-CSF signaling in these cells, and is usually caused by neutralizing autoantibodies to GM-CSF or is secondary to other underlying diseases. Rarely, genetic defects in surfactant proteins or the common beta chain for the GM-CSF receptor (GM-CSFR) are causal. Using a combination of cellular, molecular, and genomic approaches, we provide the first evidence that PAP can result from a genetic deficiency of the GM-CSFR alpha chain, encoded in the X-chromosome pseudoautosomal region 1.
Keywords: Animals; CD11b Antigen; Child, Preschool; Chromosomes, Human, X; Exons; Female; Genotype; Granulocyte-Macrophage Colony-Stimulating Factor; Humans; In Situ Hybridization, Fluorescence; Karyotyping; Male; Mice; Monocytes; Pulmonary Alveolar Proteinosis; Pulmonary Surfactants; Receptors, Granulocyte-Macrophage Colony-Stimulating Factor; Signal Transduction; Turner Syndrome

Quantitative monitoring of adenocarcinoma development in rodents by magnetic resonance imaging. - Garbow, Joel R; Wang, Min; Wang, Yian; Lubet, Ronald A; You, Ming (Clin Cancer Res, 2008)
PURPOSE: Accurately following the time course of tumor progression and response to therapy in animal models of cancer is key to the development of better chemopreventive and chemotherapeutic agents. The goal of this work was to monitor quantitatively the development and progression of adenocarcinoma in a time course study of mice treated with the carcinogen urethane using in vivo small-animal magnetic resonance imaging (MRI). EXPERIMENTAL DESIGN: Mice treated with a single dose of urethane were imaged at four time points beginning 8 months after treatment. High-resolution images of mouse lung were obtained in vivo using respiratory-gated MRI methods. Individual tumors were manually segmented and their volumes calculated. At the end of the study, mice were euthanized and MRI tumor quantification was validated by histology and histopathology. RESULTS: Tumors as small as 0.4 mm in diameter can be detected and quantitatively measured in mice by in vivo MRI. Total tumor burden increased consistently in all mice studied, whereas the growth rate of individual tumors varied widely. The positions and diameters of individual tumors as measured by MRI correlated well with histology results. Histologic study of large, rapidly growing tumors showed that these were adenocarcinomas, whereas small, slowly growing lesions were predominantly adenomas. CONCLUSIONS: Longitudinal in vivo MRI is a powerful modality that can be of great aid in elucidating the factors that control the onset of lung tumors and can serve as a platform for the development and preclinical testing of novel therapies having a high likelihood of efficacy in human clinical trials.
Keywords: Adenocarcinoma; Animals; Carcinogens; Disease Models, Animal; Image Interpretation, Computer-Assisted; Image Processing, Computer-Assisted; Lung Neoplasms; Magnetic Resonance Imaging; Male; Mice; Mice, Inbred A; Urethane

Regional association-based fine-mapping for sodium-lithium countertransport on chromosome 10. - Morrison, Alanna C; Eric Boerwinkle; Turner, Stephen T; Ferrell, Robert E (Am J Hypertens, 2008)
BACKGROUND: Increased erythrocyte sodium-lithium countertransport (SLC) has been observed in patients with essential hypertension. Consistent evidence of genetic linkage was shown for SLC on chromosome 10, and a region of interest was localized between 26 and 56 Mb. METHODS: This study surveyed single nucleotide polymorphisms (SNPs) in 54 genes that reside in the region of interest, and investigated their association with SLC and blood pressure. These SNPs were genotyped in 1,133 non-Hispanic white individuals from 255 pedigrees comprising the second phase of the Rochester Family Heart Study. The variance-components-based genetics software package SOLAR was used for evaluating whether an SNP contributed to a significant fraction of the trait heritability. RESULTS: Of the 77 SNPs surveyed in this study across the region of interest, four SNPs were associated with SLC (P < 0.04), five SNPs were associated with blood pressure (P < 0.04), and two SNPs in mannose-binding lectin 2 (MBL2) were associated with both phenotypes. In general, the pairwise linkage disequilibrium among the genotyped SNPs was low. CONCLUSIONS: This fine-mapping survey of genetic variation in a linkage region of interest provides overall support for association-mapping for SLC on chromosome 10. Genes significantly associated with systolic blood pressure and/or SLC in these families will be prioritized for future studies.
Keywords: Adolescent; Adult; Aged; Antiporters; Blood Pressure; Child; Chromosome Mapping; Chromosomes, Human, Pair 10; Erythrocytes; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Hypertension; Linkage Disequilibrium; Male; Mannose-Binding Lectin; Middle Aged; Minnesota; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

The serotonin transporter genotype is associated with intermediate brain phenotypes that depend on the context of eliciting stressor. - Kalin, N H; Shelton, S E; Fox, A S; Rogers, J; Oakes, T R; Davidson, R J (Mol Psychiatry, 2008)
A variant allele in the promoter region of the serotonin transporter gene, SLC6A4, the s allele, is associated with increased vulnerability to develop anxiety-related traits and depression. Furthermore, functional magnetic resonance imaging (fMRI) studies reveal that s carriers have increased amygdala reactivity in response to aversive stimuli, which is thought to be an intermediate phenotype mediating the influences of the s allele on emotionality. We used high-resolution microPET [18F]fluoro-2-deoxy-D-glucose (FDG) scanning to assess regional brain metabolic activity in rhesus monkeys to further explore s allele-related intermediate phenotypes. Rhesus monkeys provide an excellent model to understand mechanisms underlying human anxiety, and FDG microPET allows for the assessment of brain activity associated with naturalistic environments outside the scanner. During FDG uptake, monkeys were exposed to different ethologically relevant stressful situations (relocation and threat) as well as to the less stressful familiar environment of their home cage. The s carriers displayed increased orbitofrontal cortex activity in response to both relocation and threat. However, during relocation they displayed increased amygdala reactivity and in response to threat they displayed increased reactivity of the bed nucleus of the stria terminalis. No increase in the activity of any of these regions occurred when the animals were administered FDG in their home cages. These findings demonstrate context-dependent intermediate phenotypes in s carriers that provide a framework for understanding the mechanisms underlying the vulnerabilities of s-allele carriers exposed to different types of stressors.
Keywords: Animals; Behavior, Animal; Brain; Brain Mapping; Disease Models, Animal; Female; Fluorodeoxyglucose F18; Genotype; Macaca mulatta; Male; Phenotype; Polymorphism, Genetic; Positron-Emission Tomography; Serotonin Plasma Membrane Transport Proteins; Stress, Psychological

Single nucleotide polymorphisms associated with coronary heart disease predict incident ischemic stroke in the atherosclerosis risk in communities study. - Morrison, Alanna C; Bare, Lance A; Luke, May M; Pankow, James S; Mosley, Thomas H; Devlin, James J; Willerson, James T; Eric Boerwinkle (Cerebrovasc Dis, 2008)
Ischemic stroke and coronary heart disease (CHD) may share genetic factors contributing to a common etiology. This study investigates whether 51 single nucleotide polymorphisms (SNPs) associated with CHD in multiple antecedent studies are associated with incident ischemic stroke in the Atherosclerosis Risk in Communities (ARIC) study. From the multiethnic ARIC cohort of 14,215 individuals, 495 validated ischemic strokes were identified. Cox proportional hazards models, adjusted for age and gender, identified three SNPs in Whites and two SNPs in Blacks associated with incident stroke (p <or= 0.05). The rs11628722 polymorphism in SERPINA9 was associated with incident stroke in Whites and Blacks, even after taking into account traditional risk factors. The idea that ischemic stroke and CHD may share some common genetic factors, such as variation in SERPINA9, should be investigated in other studies.
Keywords: Black People; Brain Ischemia; Coronary Disease; Female; Genetic Predisposition to Disease; Genotype; Humans; Incidence; Intracranial Arteriosclerosis; Male; Middle Aged; Myocardial Infarction; Neoplasm Proteins; Polymorphism, Single Nucleotide; Predictive Value of Tests; Proportional Hazards Models; Risk Factors; Serpins; Stroke; White People

Somatic mutations affect key pathways in lung adenocarcinoma. - Ding, Li; Getz, Gad; Wheeler, David A; Mardis, Elaine R; McLellan, Michael D; Cibulskis, Kristian; Sougnez, Carrie; Greulich, Heidi; Donna M Muzny; Morgan, Margaret B; Fulton, Lucinda; Fulton, Robert S; et al. (Nature, 2008)
Determining the genetic basis of cancer requires comprehensive analyses of large collections of histopathologically well-classified primary tumours. Here we report the results of a collaborative study to discover somatic mutations in 188 human lung adenocarcinomas. DNA sequencing of 623 genes with known or potential relationships to cancer revealed more than 1,000 somatic mutations across the samples. Our analysis identified 26 genes that are mutated at significantly high frequencies and thus are probably involved in carcinogenesis. The frequently mutated genes include tyrosine kinases, among them the EGFR homologue ERBB4; multiple ephrin receptor genes, notably EPHA3; vascular endothelial growth factor receptor KDR; and NTRK genes. These data provide evidence of somatic mutations in primary lung adenocarcinoma for several tumour suppressor genes involved in other cancers--including NF1, APC, RB1 and ATM--and for sequence changes in PTPRD as well as the frequently deleted gene LRP1B. The observed mutational profiles correlate with clinical features, smoking status and DNA repair defects. These results are reinforced by data integration including single nucleotide polymorphism array and gene expression array. Our findings shed further light on several important signalling pathways involved in lung adenocarcinoma, and suggest new molecular targets for treatment.
Keywords: Adenocarcinoma, Bronchiolo-Alveolar; Female; Gene Dosage; Gene Expression Regulation, Neoplastic; Genes, Tumor Suppressor; Humans; Lung Neoplasms; Male; Mutation; Proto-Oncogenes

Understanding the development of human bladder cancer by using a whole-organ genomic mapping strategy. - Majewski, Tadeusz; Lee, Sangkyou; Jeong, Joon; Yoon, Dong-Sup; Kram, Andrzej; Kim, Mi-Sook; Tuziak, Tomasz; Bondaruk, Jolanta; Lee, Sooyong; Park, Weon-Seo; Tang, Kuang S; Chung, Woonbok; et al. (Lab Invest, 2008)
The search for the genomic sequences involved in human cancers can be greatly facilitated by maps of genomic imbalances identifying the involved chromosomal regions, particularly those that participate in the development of occult preneoplastic conditions that progress to clinically aggressive invasive cancer. The integration of such regions with human genome sequence variation may provide valuable clues about their overall structure and gene content. By extension, such knowledge may help us understand the underlying genetic components involved in the initiation and progression of these cancers. We describe the development of a genome-wide map of human bladder cancer that tracks its progression from in situ precursor conditions to invasive disease. Testing for allelic losses using a genome-wide panel of 787 microsatellite markers was performed on multiple DNA samples, extracted from the entire mucosal surface of the bladder and corresponding to normal urothelium, in situ preneoplastic lesions, and invasive carcinoma. Using this approach, we matched the clonal allelic losses in distinct chromosomal regions to specific phases of bladder neoplasia and produced a detailed genetic map of bladder cancer development. These analyses revealed three major waves of genetic changes associated with growth advantages of successive clones and reflecting a stepwise conversion of normal urothelial cells into cancer cells. The genetic changes map to six regions at 3q22-q24, 5q22-q31, 9q21-q22, 10q26, 13q14, and 17p13, which may represent critical hits driving the development of bladder cancer. Finally, we performed high-resolution mapping using single nucleotide polymorphism markers within one region on chromosome 13q14, containing the model tumor suppressor gene RB1, and defined a minimal deleted region associated with clonal expansion of in situ neoplasia. These analyses provided new insights on the involvement of several non-coding sequences mapping to the region and identified novel target genes, termed forerunner (FR) genes, involved in early phases of cancer development.
Keywords: Aged; Carcinoma, Transitional Cell; Chromosome Mapping; Chromosomes, Human, Pair 13; Humans; Male; Microsatellite Repeats; Middle Aged; Polymorphism, Single Nucleotide; Retinoblastoma Protein; Urinary Bladder; Urinary Bladder Neoplasms; Urothelium

Absence of an interaction between the angiotensin-converting enzyme insertion-deletion polymorphism and pravastatin on cardiovascular disease in high-risk hypertensive patients: the Genetics of Hypertension-Associated Treatment (GenHAT) study. - Maitland-van der Zee, Anke-Hilse; Eric Boerwinkle; Arnett, Donna K; Davis, Barry R; Leiendecker-Foster, Catherine; Miller, Michael B; Klungel, Olaf H; Ford, Charles E; Eckfeldt, John H (Am Heart J, 2007)
BACKGROUND: The aim of this study was to determine whether the angiotensin-converting enzyme (ACE) insertion-deletion (ID) polymorphism interacts with pravastatin to modify the risk of coronary heart disease (CHD) and other cardiovascular end points in a large clinical trial. METHODS: GenHAT is an ancillary study of the ALLHAT. The ACE ID genotyped population in the lipid-lowering arm of ALLHAT included 9467 participants randomly assigned to pravastatin (n = 4741) or to usual care (n = 4726). The efficacy of pravastatin in reducing the risk of primary outcome (all-cause mortality) and secondary outcomes (fatal CHD and nonfatal myocardial infarction, cardiovascular disease [CVD] mortality, CHD, stroke, other CVD, non-CVD mortality, stroke, and heart failure) was compared between the genotype strata (dominant model ID + II vs DD, additive model II vs ID vs DD), by examining an interaction term in a Cox proportional hazards model. RESULTS: The relative risk of fatal CHD and nonfatal myocardial infarction among subjects randomized to pravastatin compared with subjects randomized to usual care was similar in subjects with the II genotype (hazard ratio [HR] 0.84, 95% CI 0.59-1.18), the ID genotype (HR 0.84, 95% CI 0.68-1.03), and the DD genotype (HR 0.99, 95% CI 0.77-1.27). CONCLUSIONS: We found no evidence that the ACE ID genotype was a major modifier of the efficacy of pravastatin in reducing the risk of cardiovascular events.
Keywords: Aged; Antihypertensive Agents; Coronary Disease; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Hypertension; Male; Middle Aged; Myocardial Infarction; Peptidyl-Dipeptidase A; Pharmacogenetics; Polymorphism, Genetic; Pravastatin; Proportional Hazards Models; Randomized Controlled Trials as Topic; Risk Assessment

Corticotropin releasing hormone (CRH) gene variation: comprehensive resequencing for variant and molecular haplotype discovery in monosomic hybrid cell lines. - Shimmin, Lawrence C; Natarajan, Sivamani; Ibarguen, Heladio; Montasser, May; Kim, Do-Kyun; Hanis, Craig L; Eric Boerwinkle; Wadhwa, Pathik D; Hixson, James E (DNA Seq, 2007)
Candidate gene association studies have met with mixed success due to many reasons including incomplete surveys of genetic variation and differences in patterns of genetic variation among study populations. We present the results of comprehensive variant discovery for the corticotropin releasing hormone gene (CRH on chromosome 8) encoding a neuropeptide that is central to many physiologic pathways. Mouse-human hybrid cell lines were constructed that are monosomic for human chromosome 8 for resequencing of separated CRH alleles to identify variants and directly determine their chromosomal phase for three major ethnic groups including African Americans (AA), Mexican Americans (MA) and European Americans (EA). We also resequenced diploid individuals to evaluate single nucleotide polymorphism (SNP) discovery in the limited numbers of monosomic hybrid cell lines. Our results show that CRH variation is very different in AA, yielding larger numbers of variants and haplotypes compared to MA and EA. Analysis of LD structure found three haplotype blocks in AA and two blocks in EA. Comparisons between AA and EA groups yielded extremely high measures of genetic differentiation (Wright's F(ST)>0.6), likely reflecting disruptive selection in CRH evolution. Network analysis showed that AA have retained an ancestral CRH haplotype, while the most common EA haplotype is derived from a single recombination event.
Keywords: Animals; Base Sequence; Cell Line; Corticotropin-Releasing Hormone; Ethnicity; Female; Haplotypes; Humans; Hybrid Cells; Linkage Disequilibrium; Male; Mice; Molecular Sequence Data; Monosomy; Phylogeny; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Evolutionary and biomedical insights from the rhesus macaque genome. - Richard A Gibbs; Jeffrey Rogers; Katze, Michael G; Bumgarner, Roger; Weinstock, George M; Mardis, Elaine R; Remington, Karin A; Strausberg, Robert L; Venter, J Craig; Wilson, Richard K; Batzer, Mark A; Bustamante, Carlos D; et al. (Science, 2007)
The rhesus macaque (Macaca mulatta) is an abundant primate species that diverged from the ancestors of Homo sapiens about 25 million years ago. Because they are genetically and physiologically similar to humans, rhesus monkeys are the most widely used nonhuman primate in basic and applied biomedical research. We determined the genome sequence of an Indian-origin Macaca mulatta female and compared the data with chimpanzees and humans to reveal the structure of ancestral primate genomes and to identify evidence for positive selection and lineage-specific expansions and contractions of gene families. A comparison of sequences from individual animals was used to investigate their underlying genetic diversity. The complete description of the macaque genome blueprint enhances the utility of this animal model for biomedical research and improves our understanding of the basic biology of the species.
Keywords: Animals; Biomedical Research; Evolution, Molecular; Female; Gene Duplication; Gene Rearrangement; Genetic Diseases, Inborn; Genetic Variation; Genome; Humans; Macaca mulatta; Male; Multigene Family; Mutation; Pan troglodytes; Sequence Analysis, DNA; Species Specificity

Family-based association study of matrix metalloproteinase-3 and -9 haplotypes with susceptibility to ischemic white matter injury. - Fornage, Myriam; Mosley, Thomas H; Jack, Clifford R; de Andrade, Mariza; Kardia, Sharon L R; Eric Boerwinkle; Turner, Stephen T (Hum Genet, 2007)
Susceptibility to ischemic damage to the subcortical white matter of the brain has a strong genetic basis. Dysregulation of matrix metalloproteinases (MMPs) contributes to loss of cerebrovascular integrity and white matter injury. We investigated whether sequence variation in the genes encoding MMP3 and MMP9 is associated with variation in leukoaraiosis volume, determined by magnetic resonance imaging, in non-Hispanic whites and African-Americans using family-based association tests. Seven hundred and fifty-six white and 671 African-American individuals from sibships ascertained through two or more siblings with hypertension were genotyped for 7 and 8 haplotype-tagging polymorphisms in the MMP3 and MMP9 genes, respectively. MMP3 sequence variation was significantly associated with variation in leukoaraiosis volume in Whites. Two common haplotypes with opposing relationships to leukoaraiosis volume were identified. MMP9 sequence variation was also significantly associated with variation in leukoaraiosis volume in both African-Americans and Whites. Different haplotypes contributed to these associations in the two racial groups. These findings add to the growing body of evidence from animal models and human clinical studies suggesting a role of MMPs in ischemic white matter injury. They provide the basis for further investigation of the role of these genes in susceptibility and/or progression to clinical disease.
Keywords: Aged; Base Sequence; Black or African American; Brain Ischemia; Family Health; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Leukoaraiosis; Linkage Disequilibrium; Male; Matrix Metalloproteinase 3; Matrix Metalloproteinase 9; Middle Aged; Polymorphism, Single Nucleotide; Siblings; White People

Fine mapping and candidate gene analyses of pulmonary adenoma resistance 1, a major genetic determinant of mouse lung adenoma resistance. - Wang, Min; Zhang, Zhongqiu; Zhang, Zhuo; Vikis, Haris; Yan, Ying; Wang, Yian; You, Ming (Cancer Res, 2007)
Pulmonary adenoma resistance 1 (Par1) is a major genetic determinant of mouse lung adenoma resistance. Although Par1 was previously mapped to mouse chromosome 11 by conventional linkage analyses, its candidate region was broad and undefined. In our present study, we generated Par1 congenic mice using two mouse strains A/J (Par1/-) and Mus spretus (Par1/+). Analyzing these congenic mice enabled us to fine map the Par1 quantitative trait loci (QTL) into a 2.0-cM (2.2 Mb) chromosomal region between genetic marker D11Mit70 and the gene Hoxb9. We then conducted systematic candidate gene screening through nucleotide polymorphism and expression analyses. Genes showing differential lung tissue expression or carrying nonsynonymous single nucleotide polymorphisms were identified and discussed. In particular, we evaluated tumor suppressor gene Tob1 for its Par1 candidacy. Our findings have narrowed the Par1 QTL region and will greatly facilitate the identification of the major genetic determinant of mouse lung adenoma resistance.
Keywords: Adenoma; Animals; Carrier Proteins; Chromosome Mapping; Female; Genes, Tumor Suppressor; Intracellular Signaling Peptides and Proteins; Lung Neoplasms; Male; Mice; Mice, Inbred A; Polymorphism, Single Nucleotide; Quantitative Trait Loci

A genome-wide linkage scan for diabetic retinopathy susceptibility genes in Mexican Americans with type 2 diabetes from Starr County, Texas. - Hallman, D Michael; Eric Boerwinkle; Gonzalez, Victor H; Klein, Barbara E K; Klein, Ronald; Hanis, Craig L (Diabetes, 2007)
We conducted a genome-wide linkage scan for genes contributing to retinopathy risk using 794 diabetes case subjects from 393 Mexican-American families from Starr County, Texas, having at least two diabetic siblings. The sample included 567 retinopathy case subjects comprising 282 affected sibling pairs. Retinopathy was classified as none, early nonproliferative, moderate-to-severe nonproliferative, or proliferative. Using 360 polymorphic markers (average spacing 9.4 cM), we conducted nonparametric linkage analysis followed by ordered-subset analysis (OSA) ranking families by average age of diabetes diagnosis. For any retinopathy, the highest LOD scores including all families were on chromosomes 3 (2.41 at 117 cM) and 12 (2.47 at 15.5). OSA logarithm of odds (LOD) scores >2 for any retinopathy occurred on chromosomes 12 (4.47 at 13.2 cM), 15 (3.65 at 100.6), and 20 (2.67 at 54.1). Scores >2 for either moderate-to-severe nonproliferative or proliferative retinopathy occurred on chromosomes 5 (2.53 at 11.2 cM), 6 (2.28 at 30.6), and 19 (2.21 at 100.6). Thus, unconditional linkage analysis revealed suggestive evidence of linkage with retinopathy on two chromosomes, whereas OSA revealed strong evidence of linkage on two chromosomes, and suggestive evidence on four. Candidate genes were identified in most implicated regions.
Keywords: Adult; Age of Onset; Body Mass Index; Diabetes Mellitus, Type 2; Diabetic Retinopathy; Family; Female; Genetic Predisposition to Disease; Genome, Human; Humans; Lod Score; Male; Mexican Americans; Middle Aged; Retinal Diseases; Siblings; Texas

Heritability of brain volume, surface area and shape: an MRI study in an extended pedigree of baboons. - Jeffrey Rogers; Kochunov, Peter; Lancaster, Jack; Shelledy, Wendy; Glahn, David; Blangero, John; Fox, Peter (Hum Brain Mapp, 2007)
To evaluate baboons (Papio hamadryas) as a primate model for the study of the genetic control of brain size and internal structure, we performed high resolution (<500 microm) magnetic resonance imaging on 109 pedigreed baboons. Quantitative genetic analysis of these MR images using a variance components approach indicates that native (untransformed) brain volume exhibits significant heritability among these baboons (h(2) = 0.52, P = 0.0049), with age and sex also accounting for substantial variation. Using global spatial normalization, we transformed all images to a standard population-specific reference, and recalculated the heritability of brain volume. The transformed images generated heritability estimates of h(2) = 0.82 (P = 0.00022) for total brain volume, h(2) = 0.86 (P = 0.0006) for cerebral volume, h(2) = 0.73 (P = 0.0069) for exposed surface area of the cerebrum and h(2) = 0.67 (P = 0.01) for gray matter volume. Regional differences in the genetic effects on brain structure were calculated using a voxel-based morphometry (VBM) approach. This analysis of regional variation shows that some areas of motor cortex and the superior temporal gyrus show relatively high heritability while other regions (e.g. superior parietal cortex) exhibit lower heritability. The general pattern of regional differences is similar to that observed in previous studies of humans. The present study demonstrates that there is substantial genetic variation underlying individual variation in brain size and structure among Papio baboons, and that broad patterns of genetic influence on variation in brain structure may be similar in baboons and humans.
Keywords: Animals; Brain; Brain Mapping; Female; Genetic Linkage; Magnetic Resonance Imaging; Male; Papio; Pedigree

Interaction effects of high-density lipoprotein metabolism gene variation and alcohol consumption on coronary heart disease risk: the atherosclerosis risk in communities study. - Volcik, Kelly; Ballantyne, Christie M; Pownall, Henry J; Sharrett, A Richey; Eric Boerwinkle (J Stud Alcohol Drugs, 2007)
OBJECTIVE: Light to moderate alcohol consumption has been widely established to be protective against coronary heart disease (CHD), whereas heavy alcohol consumption has been shown to have a potential detrimental effect. The reduction in risk of CHD associated with light and moderate alcohol intake is generally attributed to the beneficial effects of alcohol on high-density lipoprotein (HDL) cholesterol levels. Previous research in the Atherosclerosis Risk in Communities (ARIC) study showed all levels of alcohol consumption to be protective against CHD in whites but to be associated with an increased risk of CHD in black men. We investigated the ARIC cohort to determine whether risk of incident CHD is influenced by an interaction effect between alcohol intake and genetic variation involved in the regulation of HDL cholesterol. Genes of interest included cholesterol ester transfer protein (CETP), lipoprotein lipase (LPL), hepatic lipase (HL), and paraoxonase-1 (PON1). METHOD: Participants were selected from the ARIC study, a prospective investigation of atherosclerosis and its clinical sequelae, involving 15,792 individuals, ages 45-64 years at recruitment (1987-1989). Incident CHD was identified through annual telephone calls and hospital and death certificate surveillance. Because of ethnic differences in the alcohol-CHD relationship observed in the ARIC cohort and pattern of alcohol consumption differences, statistical analyses were evaluated separately for each race-gender stratum (white men/women, black men/women). RESULTS: Genotype modified the relationship between heavy drinking and CHD risk but did not modify this relationship for light or moderate drinking. Interaction analyses were significant for heavy alcohol intake and PON1 genotype (p=.02) in black men, with a suggested interaction for heavy alcohol intake and CETP genotype (p=.06) in black men. Heavy drinking was associated with an increased risk for CHD in black men with the PON1 QQ and CETP GG genotypes (PON1 hazard rate ratio [HRR]=17.3, 95% confidence interval [CI]: 1.76-170.2; CETP HRR=2.23, 95% CI: 1.01-4.91). CONCLUSIONS: Results from the current study suggest that interaction effects between alcohol consumption and HDL cholesterol metabolism gene variation influence the risk of incident CHD in black men. Additional studies are warranted to confirm these findings.
Keywords: Age Factors; Alcohol Drinking; Aryldialkylphosphatase; Black People; Cholesterol Ester Transfer Proteins; Cholesterol, HDL; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Lipase; Lipoprotein Lipase; Male; Middle Aged; Prospective Studies; Risk; Sex Factors; White People

Mutations in smooth muscle alpha-actin (ACTA2) lead to thoracic aortic aneurysms and dissections. - Guo, Dong-chuan; Pannu, Hariyadarshi; Tran-Fadulu, Van; Papke, Christina L; Yu, Robert K; Avidan, Nili; Bourgeois, Scott; Estrera, Anthony L; Safi, Hazim J; Sparks, Elizabeth; Amor, David; Ades, Lesley; et al. (Nat Genet, 2007)
The major function of vascular smooth muscle cells (SMCs) is contraction to regulate blood pressure and flow. SMC contractile force requires cyclic interactions between SMC alpha-actin (encoded by ACTA2) and the beta-myosin heavy chain (encoded by MYH11). Here we show that missense mutations in ACTA2 are responsible for 14% of inherited ascending thoracic aortic aneurysms and dissections (TAAD). Structural analyses and immunofluorescence of actin filaments in SMCs derived from individuals heterozygous for ACTA2 mutations illustrate that these mutations interfere with actin filament assembly and are predicted to decrease SMC contraction. Aortic tissues from affected individuals showed aortic medial degeneration, focal areas of medial SMC hyperplasia and disarray, and stenotic arteries in the vasa vasorum due to medial SMC proliferation. These data, along with the previously reported MYH11 mutations causing familial TAAD, indicate the importance of SMC contraction in maintaining the structural integrity of the ascending aorta.
Keywords: Actins; Aorta; Aortic Aneurysm, Thoracic; Aortic Dissection; Female; Genetic Predisposition to Disease; Humans; Male; Mutation, Missense; Myocytes, Smooth Muscle; Pedigree

MYH11 mutations result in a distinct vascular pathology driven by insulin-like growth factor 1 and angiotensin II. - Pannu, Hariyadarshi; Tran-Fadulu, Van; Papke, Christina L; Scherer, Steve; Liu, Yaozhong; Presley, Caroline; Guo, Dongchuan; Estrera, Anthony L; Safi, Hazim J; Brasier, Allan R; Vick, G Wesley; Marian, A J; et al. (Hum Mol Genet, 2007)
Non-syndromic thoracic aortic aneurysms and dissections (TAADs) are inherited in an autosomal dominant manner in approximately 20% of cases. Familial TAAD is genetically heterogeneous and four loci have been mapped for this disease to date, including a locus at 16p for TAAD associated with patent ductus arteriosus (PDA). The defective gene at the 16p locus has recently been identified as the smooth muscle cell (SMC)-specific myosin heavy chain gene (MYH11). On sequencing MYH11 in 93 families with TAAD alone and three families with TAAD/PDA, we identified novel mutations in two families with TAAD/PDA, but none in families with TAAD alone. Histopathological analysis of aortic sections from two individuals with MYH11 mutations revealed SMC disarray and focal hyperplasia of SMCs in the aortic media. SMC hyperplasia leading to significant lumen narrowing in some of the vessels of the adventitia was also observed. Insulin-like growth factor-1 (IGF-1) was upregulated in mutant aortas as well as explanted SMCs, but no increase in transforming growth factor-beta expression or downstream targets was observed. Enhanced expression of angiotensin-converting enzyme and markers of Angiotensin II (Ang II) vascular inflammation (macrophage inflammatory protein-1alpha and beta) were also found. These data suggest that MYH11 mutations are likely to be specific to the phenotype of TAAD/PDA and result in a distinct aortic and occlusive vascular pathology potentially driven by IGF-1 and Ang II.
Keywords: Adult; Amino Acid Sequence; Angiotensin II; Aortic Aneurysm, Thoracic; Child, Preschool; Ductus Arteriosus, Patent; Female; Genetic Testing; Humans; Insulin-Like Growth Factor I; Male; Middle Aged; Models, Molecular; Molecular Sequence Data; Mutation; Myosin Heavy Chains; Pedigree; Sequence Homology, Amino Acid; Vascular Diseases

Prediction of coronary heart disease risk using a genetic risk score: the Atherosclerosis Risk in Communities Study. - Morrison, Alanna C; Bare, Lance A; Chambless, Lloyd E; Ellis, Stephen G; Malloy, Mary; Kane, John P; Pankow, James S; Devlin, James J; Willerson, James T; Eric Boerwinkle (Am J Epidemiol, 2007)
Recent studies have evaluated whether incorporating nontraditional risk factors improves coronary heart disease (CHD) prediction models. This 1986-2001 US study aggregated the contribution of multiple single nucleotide polymorphisms into a genetic risk score (GRS) and assessed whether the GRS plus traditional risk factors predict CHD better than traditional risk factors alone. The Atherosclerosis Risk in Communities (ARIC) cohort was followed for a median of 13 years for CHD events (n = 1,452). Individuals were genotyped for 116 single nucleotide polymorphisms associated with CHD in multiple case-control studies. Single nucleotide polymorphisms nominally predicting incident CHD in the ARIC study were included in the GRS. The GRS was significantly associated with incident CHD in Blacks (hazard rate ratio = 1.20, 95% confidence interval: 1.11, 1.29) and Whites (hazard rate ratio = 1.10, 95% confidence interval: 1.06, 1.14) as well as in each tertile defined by the traditional cardiovascular risk score (p < or = 0.02). When receiver operating characteristic curves based on traditional risk factors were recalculated after the GRS was added, the increase in the area under the receiver operating characteristic curve was statistically significant for Blacks and suggestive of improved CHD prediction for Whites. This study demonstrates the concept of aggregating information from multiple single nucleotide polymorphisms into a risk score and indicates that it can improve prediction of incident CHD in the ARIC study.
Keywords: Atherosclerosis; Black People; Blood Pressure; Cholesterol; Coronary Disease; Female; Follow-Up Studies; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prospective Studies; Risk Factors; ROC Curve; United States; White People

A preliminary study of the baboon prostate pathophysiology. - Mubiru, James N; Hubbard, Gene B; Dick, Edward J; Butler, Stephanie D; Valente, Anthony J; Troyer, Dean A; Jeffrey Rogers (Prostate, 2007)
BACKGROUND: Prostate cancer, benign prostatic hyperplasia, and prostatitis frequently affect men worldwide. At present there are no suitable animal models for these diseases. This study explores the potential use of the baboon as a model for prostatic diseases. METHODS: Prostates of 48 baboons of different ages were studied. Prostate specific antigen (PSA) and alpha-methyl-acyl-CoA racemase (AMACR) were localized in the different lobes of the prostate by Western blotting and immunohistochemistry. PSA in baboon serum was demonstrated by radioimmunoassay and western blotting. Baboon AMACR cDNA was cloned and its expression assayed in baboon tissues. RESULTS: The baboon prostate is anatomically and histologically similar to its human counterpart, with cranial and caudal lobes corresponding to central and peripheral zones of the human prostate. We found lymphocytic infiltration (91%), and sclerosing/atrophic lesions (34%). PSA tissue immunostaining intensity and alpha-methyl-acyl-CoA racemase (AMACR) gene expression levels differed between the cranial and caudal lobes of the prostate. The cloned baboon AMACR cDNA showed 96% homology with its human counterpart. Anti-human AMACR, PSA and basal keratin antibodies stained intracellular and basement membrane structures in the baboon prostate. The sclerosing/atrophic lesions were comparable to their human counterparts. CONCLUSIONS: The similarity of baboon prostate to its human counterpart and the fact that human antibodies (AMACR, PSA, basal keratin) are reactive to baboon prostatic proteins indicates that the baboon is a promising model for human prostatic diseases.
Keywords: Animals; Cloning, Molecular; Disease Models, Animal; Immunoblotting; Immunohistochemistry; Male; Papio hamadryas; Pilot Projects; Prostate; Prostate-Specific Antigen; Prostatic Diseases; Racemases and Epimerases; Reverse Transcriptase Polymerase Chain Reaction; RNA

Quantitative trait loci for peripheral blood cell counts: a study in baboons. - Bertin, Angéline; Mahaney, Michael C; Cox, Laura A; Jeffrey Rogers; VandeBerg, John L; Brugnara, Carlo; Platt, Orah S (Mamm Genome, 2007)
Increasingly, baseline peripheral blood cell counts are implicated as risk factors for common complex diseases. While genetic influences on these hematologic parameters are firmly established, the genetic architecture of the blood counts is still poorly understood. In this article we used data from 582 healthy pedigreed baboons and variance components methods to localize quantitative trait loci (QTLs) influencing complete blood count variables. Besides performing genome-wide linkage scans for each trait individually, we conducted bivariate linkage analyses for all pairwise trait combinations to also identify pleiotropic QTLs influencing several blood counts. While significant and suggestive QTLs were localized throughout the genome (LOD range: 1.5-3.5), chromosomal regions associated with the expression of various hematologic parameters stand out. In particular, our results provide significant and consistent evidence for a QTL on the orthologous human chromosome 1p that is shared by several blood counts, mainly erythrocyte parameters. In addition, multiple suggestive evidence of linkage was detected on the orthologous human chromosomes 10 (near the q-terminus) and 19 (centromeric section). Future studies should help identify the genes responsible for these QTL and elucidate their role on baseline variation in hematologic indicators of health and disease.
Keywords: Animals; Blood Cell Count; Chromosome Mapping; Female; Humans; Male; Papio; Phenotype; Quantitative Trait Loci; Synteny

Relation of PCSK9 mutations to serum low-density lipoprotein cholesterol in childhood and adulthood (from The Bogalusa Heart Study). - Hallman, D Michael; Srinivasan, Sathanur R; Chen, Wei; Eric Boerwinkle; Berenson, Gerald S (Am J Cardiol, 2007)
Specific mutations in the gene for proprotein convertase, subtilisin-kexin type 9 (PCSK9), that are associated with lower coronary heart disease risk may produce lifelong decreases in low-density lipoprotein (LDL) cholesterol levels, but data on their effects in younger subjects are lacking. We analyzed associations of 1 missense (R46L) and 2 nonsense (Y142X and C679X) PCSK9 mutations with serum LDL cholesterol in 478 African-Americans and 1,086 whites, 4 to 38 years of age, examined 3 to 8 times in the Bogalusa Heart Study. L46 allele frequency in whites was 0.017 +/- 0.003; the combined frequency of X142 or X679 alleles in African-Americans was 0.016 +/- 0.005. In whites, LDL cholesterol was lower in L46 carriers (78.9 +/- 21.8 mg/dl) than in noncarriers (89.7 +/- 24.9 mg/dl, p = 0.027) at their first examination (mean age 9.4 +/- 3.2 years). African-Americans carrying the X142 or X679 allele had lower LDL cholesterol levels than did noncarriers (77.3 +/- 15.1 vs 91.4 +/- 23.9 mg/dl, p = 0.043) at their first examination (mean age 9.0 +/- 3.0 years). Longitudinal LDL cholesterol profiles were significantly lower in whites with the L46 allele and in African-Americans with the X142 or X679 allele. In conclusion, our results show that these PCSK9 variants are associated with significantly lower LDL cholesterol levels starting in childhood.
Keywords: Alleles; Black or African American; Cholesterol, LDL; Codon, Nonsense; Coronary Disease; Female; Humans; Louisiana; Male; Mutation, Missense; Proprotein Convertase 9; Proprotein Convertases; Risk Factors; Serine Endopeptidases; White People

A second generation human haplotype map of over 3.1 million SNPs. - Frazer, Kelly A; Ballinger, Dennis G; Cox, David R; Hinds, David A; Stuve, Laura L; Richard A Gibbs; Belmont, John W; Boudreau, Andrew; Hardenbol, Paul; Leal, Suzanne M; Pasternak, Shiran; Wheeler, David A; et al. (Nature, 2007)
We describe the Phase II HapMap, which characterizes over 3.1 million human single nucleotide polymorphisms (SNPs) genotyped in 270 individuals from four geographically diverse populations and includes 25-35% of common SNP variation in the populations surveyed. The map is estimated to capture untyped common variation with an average maximum r2 of between 0.9 and 0.96 depending on population. We demonstrate that the current generation of commercial genome-wide genotyping products captures common Phase II SNPs with an average maximum r2 of up to 0.8 in African and up to 0.95 in non-African populations, and that potential gains in power in association studies can be obtained through imputation. These data also reveal novel aspects of the structure of linkage disequilibrium. We show that 10-30% of pairs of individuals within a population share at least one region of extended genetic identity arising from recent ancestry and that up to 1% of all common variants are untaggable, primarily because they lie within recombination hotspots. We show that recombination rates vary systematically around genes and between genes of different function. Finally, we demonstrate increased differentiation at non-synonymous, compared to synonymous, SNPs, resulting from systematic differences in the strength or efficacy of natural selection between populations.
Keywords: Female; Haplotypes; Homozygote; Humans; Linkage Disequilibrium; Male; Polymorphism, Single Nucleotide; Racial Groups; Recombination, Genetic; Selection, Genetic

Sequence variation in DOCK9 and heterogeneity in bipolar disorder. - Detera-Wadleigh, Sevilla D; Liu, Chun-yu; Maheshwari, Manjula; Cardona, Imer; Corona, Winston; Akula, Nirmala; Steele, C J M; Badner, Judith A; Kundu, Mukta; Kassem, Layla; Potash, James B; Richard A Gibbs; et al. (Psychiatr Genet, 2007)
BACKGROUND: Linkage of bipolar disorder to a broad region on chromosome 13q has been supported in several studies including a meta-analysis on genome scans. Subsequent reports have shown that variations in the DAOA (G72) locus on 13q33 display association with bipolar disorder but these may not account for all of the linkage evidence in the region. OBJECTIVE: To identify additional susceptibility loci on 13q32-q33 by linkage disequilibrium mapping and explore the impact of phenotypic heterogeneity on association. METHODS: In the initial phase, 98 single nucleotide polymorphism (SNPs) located on 13q32-q33 were genotyped on 285 probands with bipolar disorder and their parents were drawn from families in the NIMH Genetics Initiative consortium for bipolar disorder (NIMH1-4) and two other series. Fine scale mapping using one family series (NIMH1-2) as the test sample was targeted on a gene that displayed the highest evidence of association. A secondary analysis of familial component phenotypes of bipolar disorder was conducted. RESULTS: Three of seven SNPs in DOCK9, a gene that encodes an activator of the Rho-GTPase Cdc42, showed significant excess allelic transmission (P=0.0477-0.00067). Fine scale mapping on DOCK9 yielded evidence of association at nine SNPs in the gene (P=0.02-0.006). Follow-up tests detected excess transmission of the same allele of rs1340 in two out of three other sets of families. The association signals were largely attributable to maternally transmitted alleles (rs1927568: P=0.000083; odds ratio=3.778). A secondary analysis of familial component phenotypes of bipolar disorder detected significant association across multiple DOCK9 markers for racing thoughts, psychosis, delusion during mania and course of illness indicators. CONCLUSION: These results suggest that DOCK9 contributes to both risk and increased illness severity in bipolar disorder. We found evidence for the effect of phenotypic heterogeneity on association. To our knowledge this is the first report to implicate DOCK9 or the Rho-GTPase pathway in the etiology of bipolar disorder.
Keywords: Bipolar Disorder; Family; Female; Genetic Predisposition to Disease; Genetic Variation; Guanine Nucleotide Exchange Factors; Humans; Linkage Disequilibrium; Male; Phenotype; Polymorphism, Single Nucleotide; Severity of Illness Index

Sequence variation in the soluble epoxide hydrolase gene and subclinical coronary atherosclerosis: interaction with cigarette smoking. - Wei, Qi; Doris, Peter A; Pollizotto, Martin V; Eric Boerwinkle; Jacobs, David R; Siscovick, David S; Fornage, Myriam (Atherosclerosis, 2007)
Soluble epoxide hydrolase (EPHX2) catalyses the degradation of the vasoactive and anti-inflammatory epoxyeicosatrienoic acids and may play a role in the pathophysiology of atherosclerosis. 1337 African-Americans and 1645 Whites from the CARDIA study were genotyped for 22 and 15 EPHX2 single nucleotide polymorphisms (SNPs), respectively, to examine the associations of common EPHX2 haplotypes and genotypes with presence of coronary artery calcified plaque (CAC). The potential influence of cigarette smoking, which increases EPHX2 gene expression, on these associations was also assessed. In African-Americans, a common haplotype uniquely tagged by the R287Q polymorphism was associated with significantly greater risk for CAC (OR=1.7; 95% CI=1.04-3.0). In Whites, a common haplotype uniquely tagged by a polymorphism in Intron 11 of the gene was associated with significantly greater risk for CAC (OR=1.3; 95% CI=1.02-1.6). These haplotype-tagging polymorphisms also showed significant associations with CAC in individual SNP analyses, and these relationships were significantly modified by smoking. This detailed investigation of the association of EPHX2 genetic variation with CAC supports EPHX2's emerging role as a risk factor for atherosclerosis, whose effects are influenced by smoking.
Keywords: Adolescent; Adult; Black or African American; Coronary Artery Disease; Epoxide Hydrolases; Female; Gene Frequency; Haplotypes; Humans; Linkage Disequilibrium; Male; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Smoking; Solubility; White People

Trisomy 17 in a baboon (Papio hamadryas) with polydactyly, patent foramen ovale and pyelectasis. - Moore, Charleen M; Hubbard, Gene B; Dick, Edward; Dunn, Betty G; Raveendran, Muthuswamy; Jeffrey Rogers; Williams, Vick; Gomez, Jeremiah J; Butler, Stephanie D; Leland, M Michelle; Schlabritz-Loutsevitch, Natalia E (Am J Primatol, 2007)
Trisomy 13 in humans is the third most common autosomal abnormality at birth, after trisomy 21 and trisomy 18. It has a reported incidence of between 1:5,000 and 1:30,000 live births. It is associated with multiple abnormalities, many of which shorten lifespan. We describe here the first reported case of a baboon (Papio hamadryas) with trisomy of chromosome 17, which is homologous to human chromosome 13. The trisomic infant was born to a consanguineous pair of baboons and had morphological characteristics similar to those observed in human trisomy 13, including bilateral polydactyly in the upper limbs, a patent foramen ovale, and pyelectasis. Molecular DNA analysis using human chromosome 13 markers was consistent with the affected infant inheriting two copies of chromosome 17 derived from the same parental chromosome. This trisomy was, therefore, due to either an error in meiosis II or the result of postzygotic nondisjunction. The parental origin, however, could not be determined.
Keywords: Animals; Arm; Chromosomes, Mammalian; Dilatation, Pathologic; Female; Heart Atria; Heart Septal Defects, Atrial; Humans; Inbreeding; Kidney Pelvis; Male; Papio hamadryas; Polydactyly; Trisomy

Widespread lateral gene transfer from intracellular bacteria to multicellular eukaryotes. - Dunning Hotopp, Julie C; Clark, Michael E; Oliveira, Deodoro C S G; Foster, Jeremy M; Fischer, Peter; Muñoz Torres, Mónica C; Giebel, Jonathan D; Kumar, Nikhil; Ishmael, Nadeeza; Wang, Shiliang; Ingram, Jessica; Nene, Rahul V; et al. (Science, 2007)
Although common among bacteria, lateral gene transfer-the movement of genes between distantly related organisms-is thought to occur only rarely between bacteria and multicellular eukaryotes. However, the presence of endosymbionts, such as Wolbachia pipientis, within some eukaryotic germlines may facilitate bacterial gene transfers to eukaryotic host genomes. We therefore examined host genomes for evidence of gene transfer events from Wolbachia bacteria to their hosts. We found and confirmed transfers into the genomes of four insect and four nematode species that range from nearly the entire Wolbachia genome (>1 megabase) to short (<500 base pairs) insertions. Potential Wolbachia-to-host transfers were also detected computationally in three additional sequenced insect genomes. We also show that some of these inserted Wolbachia genes are transcribed within eukaryotic cells lacking endosymbionts. Therefore, heritable lateral gene transfer occurs into eukaryotic hosts from their prokaryote symbionts, potentially providing a mechanism for acquisition of new genes and functions.
Keywords: Animals; Chromosome Mapping; Crosses, Genetic; DNA, Bacterial; Drosophila; Female; Gene Transfer, Horizontal; Genes, Bacterial; In Situ Hybridization, Fluorescence; Insecta; Male; Molecular Sequence Data; Nematoda; Retroelements; Reverse Transcriptase Polymerase Chain Reaction; Sequence Analysis, DNA; Symbiosis; Wolbachia

Apolipoprotein E polymorphisms predict low density lipoprotein cholesterol levels and carotid artery wall thickness but not incident coronary heart disease in 12,491 ARIC study participants. - Volcik, Kelly A; Barkley, Ruth Ann; Hutchinson, Richard G; Mosley, Thomas H; Heiss, Gerardo; Sharrett, A Richey; Ballantyne, Christie M; Eric Boerwinkle (Am J Epidemiol, 2006)
Elevated levels of low density lipoprotein (LDL) cholesterol is a well-established risk factor for cardiovascular disease, and recent advancements have provided evidence that carotid artery intima-media thickness (IMT) is associated with increased occurrence of cardiovascular events. Apolipoprotein E (ApoE) has been widely studied in regard to its role in lipid transport and metabolism, but the role that ApoE genetic variation plays in relation to carotid artery IMT and risk of incident coronary heart disease remains a subject of debate. In 1987-2001, the authors examined the effect of each ApoE allele (epsilon2, epsilon3, epsilon4) on LDL cholesterol and carotid IMT, as well as the association with coronary heart disease risk, in 12,491 participants of the US Atherosclerosis Risk in Communities Study. ApoE epsilon2, epsilon3, and epsilon4 allele frequencies were determined, respectively, in Whites (0.08, 0.77, 0.15) and African Americans (0.11, 0.67, 0.22). These alleles did not predict incident coronary heart disease in either racial group. The ApoE epsilon2 allele was associated with lower LDL cholesterol and the epsilon4 allele with higher LDL cholesterol in both Whites and African Americans. The ApoE epsilon2 and epsilon4 alleles were associated with carotid IMT measures in both racial groups, but, after adjusting for lipid parameters, only the epsilon4 allele was associated with carotid IMT measures in African Americans.
Keywords: Apolipoproteins E; Black People; Carotid Arteries; Cholesterol, LDL; Coronary Disease; Female; Genetic Predisposition to Disease; Humans; Incidence; Male; Middle Aged; Polymorphism, Genetic; Prospective Studies; Tunica Intima; White People

Consistent effects of genes involved in reverse cholesterol transport on plasma lipid and apolipoprotein levels in CARDIA participants. - Klos, Kathy L E; Sing, Charles F; Eric Boerwinkle; Hamon, Sara C; Rea, Thomas J; Clark, Andrew; Fornage, Myriam; Hixson, James E (Arterioscler Thromb Vasc Biol, 2006)
OBJECTIVE: To identify common variations in genes in the reverse cholesterol transport pathway with nongender-specific influence on plasma lipid and apolipoprotein levels. METHODS AND RESULTS: An average of 5 single nucleotide polymorphisms (SNPs) were genotyped within each of 45 genomic regions (54 genes) in blacks (1131 females and 812 males) and whites (1102 females and 954 males) from the Coronary Artery Risk Development in Young Adults (CARDIA) study. SNPs and gene-based 3-SNP haplotypes were evaluated for their ability to predict variation in plasma apolipoproteins (apo) A-I and apoB, total cholesterol (TC), high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides (TG). We identified 14 SNPs in 6 candidate gene regions that explained statistically significant variation in the same trait in both genders of at least one race and with evidence of consistent genotype mean trend across gender within race. Haplotype analyses identified 9 candidate gene regions that explained statistically significant variation in one or both races. CONCLUSIONS: Four gene regions, ABCA1, APOA1/C3/A4/A5, APOE/C1/C4/C2, and CETP, explained plasma lipoprotein variation most consistently across strata. Other gene regions that influence plasma lipid and apolipoprotein levels within race include CYP7A1, LPL, PPARA, SOAT1, and SREBF2.
Keywords: Adult; Apolipoproteins; Apolipoproteins A; Apolipoproteins C; Apolipoproteins E; ATP Binding Cassette Transporter 1; ATP-Binding Cassette Transporters; Biological Transport, Active; Black People; Carrier Proteins; Cholesterol; Cholesterol Ester Transfer Proteins; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genotype; Glycoproteins; Haplotypes; Humans; Lipids; Male; Polymorphism, Single Nucleotide; White People

The genome of the sea urchin Strongylocentrotus purpuratus. - Sodergren, Erica; Weinstock, George M; Davidson, Eric H; Cameron, R Andrew; Richard A Gibbs; Angerer, Robert C; Angerer, Lynne M; Arnone, Maria Ina; Burgess, David R; Burke, Robert D; Coffman, James A; Dean, Michael; et al. (Science, 2006)
We report the sequence and analysis of the 814-megabase genome of the sea urchin Strongylocentrotus purpuratus, a model for developmental and systems biology. The sequencing strategy combined whole-genome shotgun and bacterial artificial chromosome (BAC) sequences. This use of BAC clones, aided by a pooling strategy, overcame difficulties associated with high heterozygosity of the genome. The genome encodes about 23,300 genes, including many previously thought to be vertebrate innovations or known only outside the deuterostomes. This echinoderm genome provides an evolutionary outgroup for the chordates and yields insights into the evolution of deuterostomes.
Keywords: Animals; Calcification, Physiologic; Cell Adhesion Molecules; Complement Activation; Computational Biology; Embryonic Development; Evolution, Molecular; Gene Expression Regulation, Developmental; Genes; Genome; Immunity, Innate; Immunologic Factors; Male; Nervous System Physiological Phenomena; Proteins; Sequence Analysis, DNA; Signal Transduction; Strongylocentrotus purpuratus; Transcription Factors

Longitudinal analysis of haplotypes and polymorphisms of the APOA5 and APOC3 genes associated with variation in serum triglyceride levels: the Bogalusa Heart Study. - Hallman, D Michael; Srinivasan, Sathanur R; Chen, Wei; Eric Boerwinkle; Berenson, Gerald S (Metabolism, 2006)
Polymorphisms in the APOC3 and APOA5 genes, from the APOA1/APOC3/APOA4/APOA5 gene cluster on chromosome 11q23, have been associated with interindividual variation in plasma triglycerides. APOA5 polymorphisms implicated include 2 in the promoter region (-1131 T/C and -3 A/G) and 1 in exon 2 (+56 C/G). APOC3 polymorphisms implicated include 1 (SstI) in the 3' untranslated region and 1 (-2854 G/T) in the APOC3-APOA4 intergenic region. We analyzed the associations of haplotypes and multilocus genotypes of these polymorphisms on longitudinal serum triglyceride profiles in 360 African American and 823 white subjects from the Bogalusa Heart Study. Subjects were examined from 2 to 8 times (mean +/- SD, 5.4 +/- 1.3) between 1973 and 1996, at ages ranging from 4 to 38 years, with 1978 observations in African Americans and 4465 in whites. Serum triglycerides were significantly higher among whites across all ages. Allele frequencies differed significantly between African Americans and whites at all but the APOA5 +56 C/G locus. Linkage disequilibrium among the loci was higher in whites and haplotype diversity lower: 6 haplotypes had estimated frequencies of more than 1% in African Americans, 5 in whites. Individually, all polymorphisms except APOC3 -2854 G/T showed significant associations with triglyceride levels in the full sample. However, genotype models including all 5 loci showed significant triglyceride associations for only 3 (APOC3 SstI, APOA5 -1131 T/C, and APOA5 +56 C/G); significant interactions among them indicated their effects were not independent. Neither APOC3 -2854 G/T nor APOA5 -3 A/G had significant effects when the other 3 loci were in the models. The EM algorithm was used to estimate haplotype frequencies and assign haplotype probabilities to individuals, which is conditional on their genotypes; individuals' haplotype probability vectors were then used as predictors in multilevel mixed models of longitudinal triglyceride profiles. Of haplotypes comprising, in order, APOC3 SstI and -2854 G/T and APOA5 -1131 T/C, -3 A/G, and +56 C/G, 3 were significantly associated with higher triglycerides, even after adjusting for multiple tests: GGTAG (P = .002), GTTAG (P < .0001), and CGCGC (P = .0002). Each GGTAG haplotype carried would be expected to raise triglyceride levels (relative to those of GTTAC homozygotes) by approximately 19 mg/dL, each GTTAG haplotype by approximately 15 mg/dL, and each CGCGC haplotype by approximately 7 mg/dL. Haplotypes comprising the 3 loci implicated by genotype analyses (SstI, -1131 T/C, and +56 C/G) were also tested: haplotypes C_C_C and G_T_G significantly raised triglycerides, even after adjustment for multiple comparisons (P < .002 for both), with each copy of C_C_C expected to raise triglycerides by approximately 7 mg/dL and each copy of G_T_G by approximately 15 mg/dL. Overall, our findings support those of others in associating specific polymorphisms and haplotypes in the APOA1/C3/A4/A5 gene cluster with higher serum triglyceride levels. However, the degree to which polymorphisms in the APOC3 and APOA5 genes may be independently associated with triglyceride levels remains to be determined.
Keywords: Adolescent; Adult; Apolipoprotein A-V; Apolipoprotein C-III; Apolipoproteins A; Body Mass Index; Child; Child, Preschool; Female; Haplotypes; Humans; Longitudinal Studies; Male; Polymorphism, Genetic; Triglycerides

New technique for lacrimal system intubation. - Wang, Linghua; Chen, Dong; Wang, Zhichong (Am J Ophthalmol, 2006)
PURPOSE: To propose a new technique for silicone intubation in disorders of the lacrimal system in children and adults. DESIGN: Retrospective, noncomparative case series. METHODS: The surgery was performed in 513 eyes of 426 patients from March 2003 to July 2005 in our hospital. With the help of a so-called soft probe and intranasal endoscope, silicone tubes were inserted through both puncta into nasolacrimal duct and left in place for three to six months. RESULTS: The surgery was performed successfully in all cases. No intraoperative complications were found in the procedure. Tubes were removed between 2.1 and 5.3 months (mean 3.4 months) after surgery. Mean follow-up time after tube removal was 15.1 months (range 3.3 to 27.5 months). Tube displacement occurred in 11 cases (2.14%); no other complications associated with silicone tubes, such as granuloma formation or corneal erosion, occurred. All the tubes were removed successfully. No ophthalmic injuries occurred during tube removal. CONCLUSIONS: The technique proved to be effective in both children and adults. This technique, which is atraumatic, easy to perform, time-saving, and better tolerated, may be considered as an alternative method for lacrimal system intubation.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; Device Removal; Endoscopy; Female; Humans; Infant; Intraoperative Complications; Intubation; Lacrimal Duct Obstruction; Male; Middle Aged; Nasolacrimal Duct; Postoperative Complications; Retrospective Studies; Silicones; Time Factors

P-selectin Thr715Pro polymorphism predicts P-selectin levels but not risk of incident coronary heart disease or ischemic stroke in a cohort of 14595 participants: the Atherosclerosis Risk in Communities Study. - Volcik, Kelly A; Ballantyne, Christie M; Coresh, Josef; Folsom, Aaron R; Wu, Kenneth K; Eric Boerwinkle (Atherosclerosis, 2006)
OBJECTIVE: Inflammation, characterized by the recruitment/adhesion of circulating leukocytes by cellular adhesion molecules, plays an important role in the pathogenesis of atherosclerosis. Genetic analyses of P-selectin, a key adhesion molecule in the progression of atherosclerosis, have provided conflicting results regarding the role of variation within the P-selectin gene and risk for heart disease. No studies have examined the association of this polymorphism with stroke. Therefore, we examined the association of the P-selectin Thr715Pro polymorphism with incident coronary heart disease (CHD) and ischemic stroke among 14595 participants in the prospective cohort of the Atherosclerosis Risk in Communities (ARIC) Study. METHODS AND RESULTS: Incidences of ischemic stroke and CHD were determined through annual telephone calls and hospital and death certificate surveillance. Four hundred fifty-six validated ischemic stroke and 1533 CHD events were identified. P-selectin Pro715 allele frequency was determined in whites and African-Americans, respectively, for CHD cases (0.11, 0.02), CHD non-cases (0.11, 0.02), ischemic stroke cases (0.11, 0.02) and stroke non-cases (0.11, 0.02). The P-selectin Pro715 allele was not associated with risk of CHD or stroke in whites or African-Americans. P-selectin levels, however, were associated with the P-selectin Thr715Pro variant in whites, but not in African-Americans. CONCLUSIONS: Genotypes carrying the P-selectin Pro715 variant allele are associated with decreased P-selectin levels compared to the homozygous wild-type genotype in whites. The P-selectin Thr715Pro polymorphism is not associated with incident CHD or ischemic stroke in either whites or African-Americans.
Keywords: Alleles; Biomarkers; Coronary Artery Disease; Disease Progression; Female; Follow-Up Studies; Gene Frequency; Genotype; Humans; Incidence; Male; Middle Aged; P-Selectin; Polymorphism, Genetic; Prospective Studies; Risk Factors; Stroke; United States

Sequence variations in PCSK9, low LDL, and protection against coronary heart disease. - Cohen, Jonathan C; Eric Boerwinkle; Mosley, Thomas H; Hobbs, Helen H (N Engl J Med, 2006)
BACKGROUND: A low plasma level of low-density lipoprotein (LDL) cholesterol is associated with reduced risk of coronary heart disease (CHD), but the effect of lifelong reductions in plasma LDL cholesterol is not known. We examined the effect of DNA-sequence variations that reduce plasma levels of LDL cholesterol on the incidence of coronary events in a large population. METHODS: We compared the incidence of CHD (myocardial infarction, fatal CHD, or coronary revascularization) over a 15-year interval in the Atherosclerosis Risk in Communities study according to the presence or absence of sequence variants in the proprotein convertase subtilisin/kexin type 9 serine protease gene (PCSK9) that are associated with reduced plasma levels of LDL cholesterol. RESULTS: Of the 3363 black subjects examined, 2.6 percent had nonsense mutations in PCSK9; these mutations were associated with a 28 percent reduction in mean LDL cholesterol and an 88 percent reduction in the risk of CHD (P=0.008 for the reduction; hazard ratio, 0.11; 95 percent confidence interval, 0.02 to 0.81; P=0.03). Of the 9524 white subjects examined, 3.2 percent had a sequence variation in PCSK9 that was associated with a 15 percent reduction in LDL cholesterol and a 47 percent reduction in the risk of CHD (hazard ratio, 0.50; 95 percent confidence interval, 0.32 to 0.79; P=0.003). CONCLUSIONS: These data indicate that moderate lifelong reduction in the plasma level of LDL cholesterol is associated with a substantial reduction in the incidence of coronary events, even in populations with a high prevalence of non-lipid-related cardiovascular risk factors.
Keywords: Black People; Carotid Arteries; Cholesterol, LDL; Codon, Nonsense; Cohort Studies; Coronary Disease; Female; Gene Frequency; Genetic Variation; Genotype; Humans; Hypolipoproteinemias; Incidence; Male; Middle Aged; Proportional Hazards Models; Proprotein Convertase 9; Proprotein Convertases; Risk; Serine Endopeptidases; United States; White People

Spectrum of CHD7 mutations in 110 individuals with CHARGE syndrome and genotype-phenotype correlation. - Lalani, Seema R; Safiullah, Arsalan M; Fernbach, Susan D; Harutyunyan, Karine G; Thaller, Christina; Peterson, Leif E; McPherson, John D; Richard A Gibbs; White, Lisa D; Hefner, Margaret; Davenport, Sandra L H; Graham, John M; et al. (Am J Hum Genet, 2006)
CHARGE syndrome is a well-established multiple-malformation syndrome with distinctive consensus diagnostic criteria. Characteristic associated anomalies include ocular coloboma, choanal atresia, cranial nerve defects, distinctive external and inner ear abnormalities, hearing loss, cardiovascular malformations, urogenital anomalies, and growth retardation. Recently, mutations of the chromodomain helicase DNA-binding protein gene CHD7 were reported to be a major cause of CHARGE syndrome. We sequenced the CHD7 gene in 110 individuals who had received the clinical diagnosis of CHARGE syndrome, and we detected mutations in 64 (58%). Mutations were distributed throughout the coding exons and conserved splice sites of CHD7. Of the 64 mutations, 47 (73%) predicted premature truncation of the protein. These included nonsense and frameshift mutations, which most likely lead to haploinsufficiency. Phenotypically, the mutation-positive group was more likely to exhibit cardiovascular malformations (54 of 59 in the mutation-positive group vs. 30 of 42 in the mutation-negative group; P=.014), coloboma of the eye (55 of 62 in the mutation-positive group vs. 30 of 43 in the mutation-negative group; P=.022), and facial asymmetry, often caused by seventh cranial nerve abnormalities (36 of 56 in the mutation-positive group vs. 13 of 39 in the mutation-negative group; P=.004). Mouse embryo whole-mount and section in situ hybridization showed the expression of Chd7 in the outflow tract of the heart, optic vesicle, facio-acoustic preganglion complex, brain, olfactory pit, and mandibular component of the first branchial arch. Microarray gene-expression analysis showed a signature pattern of gene-expression differences that distinguished the individuals with CHARGE syndrome with CHD7 mutation from the controls. We conclude that cardiovascular malformations, coloboma, and facial asymmetry are common findings in CHARGE syndrome caused by CHD7 mutation.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Child; Child, Preschool; Coloboma; DNA Helicases; DNA Mutational Analysis; DNA-Binding Proteins; Embryo, Mammalian; Facial Asymmetry; Female; Genotype; Heart Defects, Congenital; Humans; In Situ Hybridization, Fluorescence; Male; Mice; Molecular Sequence Data; Mutation; Pedigree; Phenotype; RNA Splice Sites; RNA, Messenger; Syndrome

APOA5 polymorphisms influence plasma triglycerides in young, healthy African Americans and whites of the CARDIA Study. - Klos, Kathy L E; Hamon, Sara; Clark, Andrew G; Eric Boerwinkle; Liu, Kiang; Sing, Charles F (J Lipid Res, 2005)
Genetic variation in the apolipoprotein A-V gene (APOA5) has been associated with variation in plasma triglyceride (TG) levels in African American and white females and males older than 40 years and/or at increased risk of coronary artery disease. We have examined whether plasma TG levels are associated with 16 APOA5 polymorphisms in young (18-30 years) African American (1,075 females and 783 males) and white (1,041 females and 932 males) individuals of the Coronary Artery Risk Development in Young Adults (CARDIA) Study selected without regard to health. Plasma TG was significantly (P < 0.01) associated with markers 27376 and 28837 (-3A/G) in both white females and males, with 27709 (-1131T/C) and 29085 in white males, with 29009 (S19W) in African American females and white males, and with 30966 in African American females. No statistically significant associations were observed in African American males. These six single-nucleotide polymorphisms individually accounted for 0-0.78% of lnTG variation among white females, 0-2.46% among white males, and 0-0.69% among African American females. The results of our study suggest a small but replicable context-dependent influence of the APOA5 gene region on plasma TG levels in young, healthy individuals.
Keywords: Adolescent; Adult; Alleles; Apolipoprotein A-V; Apolipoproteins; Apolipoproteins A; Black or African American; Cohort Studies; Coronary Artery Disease; Cross-Sectional Studies; Female; Genetic Variation; Genotype; Humans; Male; Polymorphism, Genetic; Risk Factors; Sex Factors; Triglycerides; United States; White People

Deletion of FMR1 in Purkinje cells enhances parallel fiber LTD, enlarges spines, and attenuates cerebellar eyelid conditioning in Fragile X syndrome. - Koekkoek, S K E; Yamaguchi, K; Milojkovic, B A; Dortland, B R; Ruigrok, T J H; Maex, R; De Graaf, W; Smit, A E; VanderWerf, F; Bakker, C E; Willemsen, R; Ikeda, T; et al. (Neuron, 2005)
Absence of functional FMRP causes Fragile X syndrome. Abnormalities in synaptic processes in the cerebral cortex and hippocampus contribute to cognitive deficits in Fragile X patients. So far, the potential roles of cerebellar deficits have not been investigated. Here, we demonstrate that both global and Purkinje cell-specific knockouts of Fmr1 show deficits in classical delay eye-blink conditioning in that the percentage of conditioned responses as well as their peak amplitude and peak velocity are reduced. Purkinje cells of these mice show elongated spines and enhanced LTD induction at the parallel fiber synapses that innervate these spines. Moreover, Fragile X patients display the same cerebellar deficits in eye-blink conditioning as the mutant mice. These data indicate that a lack of FMRP leads to cerebellar deficits at both the cellular and behavioral levels and raise the possibility that cerebellar dysfunctions can contribute to motor learning deficits in Fragile X patients.
Keywords: Animals; Cerebellum; Conditioning, Eyelid; Dendrites; Fragile X Mental Retardation Protein; Fragile X Syndrome; Gene Deletion; Humans; Long-Term Synaptic Depression; Male; Mice; Mice, Knockout; Mice, Mutant Strains; Models, Neurological; Nerve Fibers; Nerve Tissue Proteins; Purkinje Cells; Reflex, Startle; RNA-Binding Proteins

Demographic, environmental, and genetic predictors of metabolic side effects of hydrochlorothiazide treatment in hypertensive subjects. - Maitland-van der Zee, Anke-Hilse; Turner, Stephen T; Schwartz, Gary L; Chapman, Arlene B; Klungel, Olaf H; Eric Boerwinkle (Am J Hypertens, 2005)
BACKGROUND: Thiazide diuretics are recommended for first-line treatment of hypertension. Although considered safe and effective, their use is associated with dyslipidemia, hyperglycemia, and an increased risk of developing type 2 diabetes. The aim of this study was to characterize interindividual variation in glucose and lipid responses to hydrochlorothiazide and to identify demographic, environmental, and genetic predictors associated with this variation. METHODS: A community-based sample of 585 adults with essential hypertension (291 African Americans [150 women and 141 men] and 294 non-Hispanic whites [126 women and 168 men]) underwent monotherapy with hydrochlorothiazide for 4 weeks. Linear regression was used to construct prediction models for the changes in plasma total cholesterol, triglyceride, and glucose concentrations. RESULTS: The mean changes (+/- standard deviation) in response to hydrochlorothiazide were 6.13 +/- 22.8 mg/dL for total cholesterol, 17.21 +/- 70 mg/dL for triglycerides, and 3.5 +/- 9.5 mg/dL for plasma glucose. Ethnicity and baseline levels of the analytes were the only predictors that were significant for more than one response. Therefore, the mechanism for these metabolic effects are not entirely shared. CONCLUSIONS: Taken together, demographic, environmental, and genetic factors accounted for only 13% of the total variation in total cholesterol response, 17% of the variation in triglyceride response, and 11% of the variation in glucose response to hydrochlorothiazide, and less than half of this predicted variation in response was explained by measured genotypes.
Keywords: Adult; Black or African American; Blood Glucose; Blood Pressure; Cholesterol; Diuretics; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Hydrochlorothiazide; Hypertension; Logistic Models; Male; Middle Aged; Multivariate Analysis; Polymorphism, Genetic; Potassium; Predictive Value of Tests; Treatment Outcome; Triglycerides; White People

The DNA sequence of the human X chromosome. - Ross, Mark T; Grafham, Darren V; Coffey, Alison J; Scherer, Steven; McLay, Kirsten; Donna M Muzny; Platzer, Matthias; Howell, Gareth R; Burrows, Christine; Bird, Christine P; Frankish, Adam; Lovell, Frances L; et al. (Nature, 2005)
The human X chromosome has a unique biology that was shaped by its evolution as the sex chromosome shared by males and females. We have determined 99.3% of the euchromatic sequence of the X chromosome. Our analysis illustrates the autosomal origin of the mammalian sex chromosomes, the stepwise process that led to the progressive loss of recombination between X and Y, and the extent of subsequent degradation of the Y chromosome. LINE1 repeat elements cover one-third of the X chromosome, with a distribution that is consistent with their proposed role as way stations in the process of X-chromosome inactivation. We found 1,098 genes in the sequence, of which 99 encode proteins expressed in testis and in various tumour types. A disproportionately high number of mendelian diseases are documented for the X chromosome. Of this number, 168 have been explained by mutations in 113 X-linked genes, which in many cases were characterized with the aid of the DNA sequence.
Keywords: Animals; Antigens, Neoplasm; Centromere; Chromosomes, Human, X; Chromosomes, Human, Y; Contig Mapping; Crossing Over, Genetic; Dosage Compensation, Genetic; Evolution, Molecular; Female; Genetic Linkage; Genetics, Medical; Genomics; Humans; Male; Polymorphism, Single Nucleotide; Repetitive Sequences, Nucleic Acid; RNA; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; Testis

G309D and W437OPA PINK1 mutations in Caucasian Parkinson's disease patients. - Deng, H; Le, W D; Zhang, X; Pan, T H; Jankovic, J (Acta Neurol Scand, 2005)
OBJECTIVE: To determine whether the G309D and W437OPA mutations in PINK1 gene are present in American Caucasian population of patients with Parkinson's disease (PD). METHODS: We searched for the G309D and W437OPA mutation by sequencing the regions of interest in the PINK1 gene in 237 unrelated Caucasian patients. RESULTS: None of the 237 samples showed the G309D or W437OPA mutations. CONCLUSIONS: The G309D and W437OPA mutations in PINK1 gene probably do not represent common causes of familial or sporadic PD in a Caucasian population.
Keywords: Adult; Amino Acid Substitution; DNA Mutational Analysis; Female; Genetic Testing; Genome, Human; Humans; Male; Middle Aged; Mutation; Parkinson Disease; Protein Kinases; United States; White People

Genetic testing, biotechnology, and GMOs: A snapshot of public opinion, 2003 through 2004. - Alford, Raye L; Morris, Kelley E; C Michelle Rives; Steven E Scherer; Weinstock, George; Richard A Gibbs; Ghonima, Karim; Belcher, Mark; Valdes, Hayden; Sumners, Carolyn; Law, Colin; Reiff, Patricia (Genet Med, 2005)
Keywords: Adolescent; Adult; Biotechnology; Female; Food, Genetically Modified; Genetic Engineering; Genetic Testing; Humans; Male; Middle Aged; Public Opinion

Identification of prognosis markers in pediatric high-risk acute lymphoblastic leukemia. - Al-Lamki, Zakia; Wali, Yasser A; Wasifuddin, Shah M; Zachariah, Mathew; Al-Mjeni, Rayhanah; Li, Changping; Muralitharan, Shanmugakonar; Al-Kharusi, Khalsa; Gunaratne, Preethi; Peterson, Leif; Richard A Gibbs; Marie-Claude Gingras; et al. (Pediatr Hematol Oncol, 2005)
Gene expression profiling may improve the understanding of the biology behind relapse in pediatric acute lymphoblastic leukemia. Using suppression subtractive hybridization (SSH), cDNA concatenated sequencing (CCS), and reverse transcriptase real-time quantitative polymerase chain reaction (RT-RQ-PCR) on high-risk patient samples with nondeterminant chromosomal translocation, the authors identified 3 genes that were significantly overexpressed in the nonrelapsed patients: the calcium/calmodulin-dependent serine protein kinase (CASK), subunit 2 of the cofactor required for SP1 transcriptional activation (CRSP2), and granzyme K (GZMK). The level of expression of these biomarkers may help identify patients with potentially good prognosis within a group otherwise at high risk of relapse.
Keywords: Adolescent; Biomarkers, Tumor; Child; Child, Preschool; Female; Gene Expression Profiling; Gene Expression Regulation, Leukemic; Humans; Male; Neoplasm Proteins; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Predictive Value of Tests; Prognosis; Recurrence; Reverse Transcriptase Polymerase Chain Reaction; Risk Factors

A multilocus approach to the antihypertensive pharmacogenetics of hydrochlorothiazide. - Maitland-van der Zee, Anke-Hilse; Turner, Stephen T; Schwartz, Gary L; Chapman, Arlene B; Klungel, Olaf H; Eric Boerwinkle (Pharmacogenet Genomics, 2005)
OBJECTIVES: To assess the influence of variations in multiple candidate genes on inter-individual variation in diastolic blood pressure (DBP) response to hydrochlorothiazide. METHODS: A community-based sample of 585 adults with essential hypertension underwent monotherapy with hydrochlorothiazide for 4 weeks. In a nested case-control design, 195 individuals in the highest tertile of DBP response (responders) and 195 individuals in the lowest tertile of DBP response (non-responders) were genotyped for 45 polymorphisms in 19 candidate genes. For those polymorphisms where the set association approach found to be significantly associated with DBP response, logistic regression was performed to estimate the odds ratio (OR) for response associated variation in the identified genotype/haplotype. RESULTS: Two polymorphisms in the sodium channel gamma-subunit promotor gene, and a polymorphism in the endothelial nitric oxide synthase gene, were significantly associated with blood pressure response to hydrochlorothiazide. In the final experiment for the set association model P=0.038. In the logistic regression analyses, compared to subjects with the CT/CT haplotype of the SCNN1G gene, those with the GA/GA haplotype had OR 5.21 of being a DBP responder [95% CI 1.65-16.47]. Compared to subjects with the GT genotype of the ENOSA_rs1799983 polymorphism, those with the GG genotype had an OR 2.19 of being a DBP responder [95% CI 1.27-3.77]. CONCLUSIONS: Two polymorphisms in the sodium channel gamma-subunit promotor gene, and a polymorphism in the endothelial nitric oxide synthase gene, were associated with significant differences in odds of DBP response to hydrochlorothiazide. Follow-up studies are needed to define the functional genetic variations and their mechanisms of pharmacogenetic effects.
Keywords: Antihypertensive Agents; Blood Pressure; Cytochrome P-450 CYP11B2; Female; Humans; Hydrochlorothiazide; Male; Middle Aged; Nitric Oxide Synthase; Polymorphism, Genetic; Sodium Channels

Orphan nuclear receptor GCNF is required for the repression of pluripotency genes during retinoic acid-induced embryonic stem cell differentiation. - Gu, Peili; LeMenuet, Damien; Chung, Arthur C-K; Mancini, Michael; Wheeler, David A; Cooney, Austin J (Mol Cell Biol, 2005)
Embryonic stem (ES) cell pluripotency and differentiation are controlled by a network of transcription factors and signaling molecules. Transcription factors such as Oct4 and Nanog are required for self-renewal and maintain the undifferentiated state of ES cells. Decreases in the expression of these factors indicate the initiation of differentiation of ES cells. Inactivation of the gene encoding the orphan nuclear receptor GCNF showed that it plays an important role in the repression of Oct4 expression in somatic cells during early embryonic development. GCNF-/- ES cells were isolated to study the function of GCNF in the down-regulation of pluripotency genes during differentiation. Loss of repression of ES cell marker genes Oct4, Nanog, Sox2, FGF4, and Stella was observed upon treatment of GCNF-/- ES cells with retinoic acid. The loss of repression of pluripotency genes is either a direct or indirect consequence of loss of GCNF. Both the Oct4 and Nanog genes are direct targets of GCNF repression during ES cell differentiation and early mouse embryonic development. In contrast Sox2 and FGF4 are indirectly regulated by GCNF through Oct4. These findings establish a central role for GCNF in the repression of pluripotency gene expression during retinoic acid-induced ES cell differentiation.
Keywords: Animals; Blotting, Northern; Blotting, Western; Cell Differentiation; Cell Line; Cell Nucleus; Chromatin Immunoprecipitation; DNA-Binding Proteins; Down-Regulation; Embryo, Mammalian; Female; Fibroblast Growth Factor 4; Genotype; Homeodomain Proteins; In Situ Hybridization; Male; Mice; Mice, Transgenic; Microscopy, Fluorescence; Models, Genetic; Nanog Homeobox Protein; Nuclear Receptor Subfamily 6, Group A, Member 1; Octamer Transcription Factor-3; Phenotype; Plasmids; Protein Binding; Receptors, Cytoplasmic and Nuclear; Response Elements; Reverse Transcriptase Polymerase Chain Reaction; Signal Transduction; SOXB1 Transcription Factors; Stem Cells; Time Factors; Trans-Activators; Transfection; Tretinoin

Single nucleotide polymorphisms in genes for 2'-5'-oligoadenylate synthetase and RNase L inpatients hospitalized with West Nile virus infection. - Yakub, Imtiaz; Lillibridge, Kristy M; Moran, Ana; Gonzalez, Omar Y; Belmont, John; Richard A Gibbs; Tweardy, David J (J Infect Dis, 2005)
BACKGROUND: Infection with the flavivirus West Nile virus (WNV) is a growing problem across the United States, where there is a case-fatality rate of 15%-29% in individuals >70 years old and no consistently effective treatment. Susceptibility to WNV disease in inbred strains of mice was mapped to a nonsense mutation in the gene encoding the 1b isoform of 2'-5'-oligoadenylate synthetase (OAS), a member of the OAS/RNase L system of innate viral resistance. Genetic susceptibility to severe WNV disease in humans has not been determined. METHODS: We sequenced each exon within all OAS and RNASEL genes in 33 individuals hospitalized with WNV infection in Houston to assess if there is a defect in this system in patients with severe WNV disease. RESULTS: Sequencing did not reveal any insertions, deletions, or nonsense mutations in any OAS or RNASEL gene. However, comparison of the exonic sequences between case patients and control subjects identified 23 single nucleotide polymorphisms (SNPs), including a synonymous SNP in OASL exon 2 (rs3213545), in which the reference allele occurred at a higher frequency in case patients (P < .004). CONCLUSION: Because the reference allele contains a splice enhancer site, our finding suggests that the RNA transcripts generated from this allele may undergo increased splicing, which results in a dominant-negative OASL isozyme similar to the nonsense/truncation mutant form of Oas1b in mice.
Keywords: 2',5'-Oligoadenylate Synthetase; Adult; Aged; Endoribonucleases; Exons; Female; Genetic Predisposition to Disease; Hospitalization; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; West Nile Fever; West Nile virus

The soluble epoxide hydrolase gene harbors sequence variation associated with susceptibility to and protection from incident ischemic stroke. - Fornage, Myriam; Lee, Craig R; Doris, Peter A; Bray, Molly S; Heiss, Gerardo; Zeldin, Darryl C; Eric Boerwinkle (Hum Mol Genet, 2005)
Stroke is the leading cause of severe disability and the third leading cause of death, accounting for one of every 15 deaths in the USA. We investigated the association of polymorphisms in the soluble epoxide hydrolase gene (EPHX2) with incident ischemic stroke in African-Americans and Whites. Twelve single nucleotide polymorphisms (SNPs) spanning EPHX2 were genotyped in a case-cohort sample of 1336 participants from the Atherosclerosis Risk in Communities (ARIC) study. In each racial group, Cox proportional hazard models were constructed to assess the relationship between incident ischemic stroke and EPHX2 polymorphisms. A score test method was used to investigate the association of common haplotypes of the gene with risk of ischemic stroke. In African-Americans, two common EPHX2 haplotypes with significant and opposing relationships to ischemic stroke risk were identified. In Whites, two common haplotypes showed suggestive indication of an association with ischemic stroke risk but, as in African-Americans, these relationships were in opposite direction. These findings suggest that multiple variants exist within or near the EPHX2 gene, with greatly contrasting relationships to ischemic stroke incidence; some associated with a higher incidence and others with a lower incidence.
Keywords: Base Sequence; Black or African American; Brain Ischemia; Epoxide Hydrolases; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Middle Aged; Polymorphism, Genetic; Stroke; White People

The beta(2)-adrenergic receptor Arg16-gly polymorphism and interactions involving beta(2)- and beta(3)-adrenergic receptor polymorphisms are associated with variations in longitudinal serum lipid profiles: the Bogalusa Heart Study. - Hallman, D Michael; Srinivasan, Sathanur R; Chen, Wei; Eric Boerwinkle; Berenson, Gerald S (Metabolism, 2004)
We examined the effects of combined genotypes of the beta(2)-adrenergic receptor (AR) Arg(16)-Gly and beta(3)-AR Trp(64)-Arg polymorphisms on longitudinal serum total (T-C) and low-density lipoprotein cholesterol (LDL-C) profiles in 1,198 subjects examined multiple times (6,488 observations) from 1973 to 1996 in the Bogalusa Heart Study, at ages from 4.5 to 38 years. Within 5-year age groups, T-C was significantly (P <.05) higher in beta(2)-AR Arg(16)/Arg(16) homozygotes than in Gly(16) carriers among those 4 to 8 (171.4 +/- 30.0 v 161.5 +/- 27.7 mg/dL), 9 to 13 (167.7 +/- 28.6 v 162.4 +/- 27.4 mg/dL), and 14 to 18 (158.8 +/- 29.6 v 154.7 +/- 27.5 mg/dL) years of age, but not in those 19 to 23, 24 to 28, 29 to 33, or 34 to 38 years of age. The beta(3)-AR polymorphism was not associated with variation in either T-C or LDL-C. In multilevel polynomial growth curve models, the combination of the beta(2)-AR Arg(16)/Arg(16) genotype with either the beta(3)-AR Arg(64)/Arg(64) or Trp(64)/Arg(64) genotypes, denoted AA/AX, was associated with variation in longitudinal T-C (P <.01) and LDL-C (P <.01) profiles. The association between combined beta(2)/beta(3)-AR genotype and lipid profiles differed among race/sex groups, being most marked in black females, in whom the AA/AX combination was associated with higher T-C and LDL-C profiles across all ages. In White males, the AA/AX combination was most strongly associated with higher lipids in adults. In black males and white females, lipid profiles differed little between genotype groups. Our findings suggest that the beta(2)-AR Arg(16)-Gly genotype influences T-C and LDL-C levels in an age-specific manner, that it may interact with beta(3)-AR Trp(64)-Arg genotypes to influence longitudinal T-C and LDL-C profiles, and that the effect of combined beta(2)/beta(3)-AR genotypes on T-C and LDL-C profiles may differ among race/sex groups.
Keywords: Age Factors; Algorithms; Amino Acid Substitution; Black People; Body Mass Index; Cardiovascular Diseases; Child; Cholesterol, LDL; DNA Primers; Female; Genotype; Humans; Lipids; Longitudinal Studies; Male; Polymorphism, Genetic; Receptors, Adrenergic, beta-2; Receptors, Adrenergic, beta-3; Reverse Transcriptase Polymerase Chain Reaction; Risk Factors; Sex Factors; Triglycerides; White People

Biochemical and genetic interaction between the fragile X mental retardation protein and the microRNA pathway. - Jin, Peng; Zarnescu, Daniela C; Ceman, Stephanie; Nakamoto, Mika; Mowrey, Julie; Jongens, Thomas A; Nelson, David L; Moses, Kevin; Warren, Stephen T (Nat Neurosci, 2004)
Fragile X syndrome is caused by a loss of expression of the fragile X mental retardation protein (FMRP). FMRP is a selective RNA-binding protein which forms a messenger ribonucleoprotein (mRNP) complex that associates with polyribosomes. Recently, mRNA ligands associated with FMRP have been identified. However, the mechanism by which FMRP regulates the translation of its mRNA ligands remains unclear. MicroRNAs are small noncoding RNAs involved in translational control. Here we show that in vivo mammalian FMRP interacts with microRNAs and the components of the microRNA pathways including Dicer and the mammalian ortholog of Argonaute 1 (AGO1). Using two different Drosophila melanogaster models, we show that AGO1 is critical for FMRP function in neural development and synaptogenesis. Our results suggest that FMRP may regulate neuronal translation via microRNAs and links microRNAs with human disease.
Keywords: Animals; Argonaute Proteins; Blotting, Western; Disease Models, Animal; Drosophila melanogaster; Drosophila Proteins; Eye; Fragile X Syndrome; HeLa Cells; Humans; Immunohistochemistry; Male; MicroRNAs; Microscopy, Electron, Scanning; Nerve Tissue Proteins; Neuromuscular Junction; Neuronal Plasticity; Precipitin Tests; Ribonuclease III; RNA-Induced Silencing Complex

A bioinformatics analysis of memory consolidation reveals involvement of the transcription factor c-rel. - Levenson, Jonathan M; Choi, Sangdun; Lee, Sun-Young; Cao, Yun Anna; Ahn, Hyung Jin; Worley, Kim C; Pizzi, Marina; Liou, Hsiou-Chi; Sweatt, J David (J Neurosci, 2004)
Consolidation of long-term memory (LTM) is a complex process requiring synthesis of new mRNAs and proteins. Many studies have characterized the requirement for de novo mRNA and protein synthesis; however, few studies have comprehensively identified genes regulated during LTM consolidation. We show that consolidation of long-term contextual memory in the hippocampus triggers altered expression of numerous genes encompassing many aspects of neuronal function. Like contextual memory formation, this altered gene expression required NMDA receptor activation and was specific for situations in which the animal formed an association between a physical context and a sensory stimulus. Using a bioinformatics approach, we found that regulatory elements for several transcription factors are over-represented in the upstream region of genes regulated during consolidation of LTM. Using a knock-out mouse, we found that c-rel, one of the transcription factors identified in our bioinformatics study, is necessary for hippocampus-dependent long-term memory formation.
Keywords: Animals; Behavior, Animal; Chromosomes; Computational Biology; Conditioning, Classical; Electroshock; Fear; Gene Expression Profiling; Gene Expression Regulation; Hippocampus; Male; Memory; Mice; Mice, Inbred C57BL; Mice, Knockout; Oligonucleotide Array Sequence Analysis; Pain Measurement; Proto-Oncogene Proteins c-rel; Receptors, N-Methyl-D-Aspartate; Spatial Behavior

Genetics. The critical region in trisomy 21. - Nelson, David L; Richard A Gibbs (Science, 2004)
Keywords: Animals; Chromosome Deletion; Chromosomes, Human, Pair 21; Chromosomes, Mammalian; Craniofacial Abnormalities; Crosses, Genetic; Disease Models, Animal; Down Syndrome; Female; Gene Duplication; Humans; Male; Mice; Recombination, Genetic; Skull; Trisomy

Genome sequence of the Brown Norway rat yields insights into mammalian evolution. - Richard A Gibbs; Weinstock, George M; Metzker, Michael L; Donna M Muzny; Sodergren, Erica J; Scherer, Steven; Scott, Graham; Steffen, David; Worley, Kim C; Burch, Paula E; Okwuonu, Geoffrey; Hines, Sandra; et al. (Nature, 2004)
The laboratory rat (Rattus norvegicus) is an indispensable tool in experimental medicine and drug development, having made inestimable contributions to human health. We report here the genome sequence of the Brown Norway (BN) rat strain. The sequence represents a high-quality 'draft' covering over 90% of the genome. The BN rat sequence is the third complete mammalian genome to be deciphered, and three-way comparisons with the human and mouse genomes resolve details of mammalian evolution. This first comprehensive analysis includes genes and proteins and their relation to human disease, repeated sequences, comparative genome-wide studies of mammalian orthologous chromosomal regions and rearrangement breakpoints, reconstruction of ancestral karyotypes and the events leading to existing species, rates of variation, and lineage-specific and lineage-independent evolutionary events such as expansion of gene families, orthology relations and protein evolution.
Keywords: Animals; Base Composition; Centromere; Chromosomes, Mammalian; CpG Islands; DNA Transposable Elements; DNA, Mitochondrial; Evolution, Molecular; Gene Duplication; Genome; Genomics; Humans; Introns; Male; Mice; Models, Molecular; Mutagenesis; Polymorphism, Single Nucleotide; Rats; Rats, Inbred BN; Regulatory Sequences, Nucleic Acid; Retroelements; RNA Splice Sites; RNA, Untranslated; Sequence Analysis, DNA; Telomere

Levodopa-responsive aromatic L-amino acid decarboxylase deficiency. - Chang, Yuh Terng; Sharma, Radhakant; Marsh, J Lawrence; McPherson, John D; Bedell, Joey A; Knust, Andreas; Bräutigam, Christa; Hoffmann, Georg F; Hyland, Keith (Ann Neurol, 2004)
We report three siblings, who were treated empirically with levodopa combined with carbidopa. There was an immediate therapeutic response. Biochemical investigation surprisingly showed the clinical phenotype to be caused by aromatic L-amino acid decarboxylase deficiency. Molecular characterization showed a homozygous point mutation (c.387 G-->A) in exon 3. Kinetic studies showed the mutation to decrease the binding affinity for the substrate. This, combined with structural modeling suggesting alteration of active site configuration, provided an explanation for the therapeutic response to levodopa.
Keywords: Adolescent; Adult; Alanine; Antiparkinson Agents; Aromatic-L-Amino-Acid Decarboxylases; Binding Sites; Carbidopa; Chromatography, High Pressure Liquid; Developmental Disabilities; DNA Mutational Analysis; Drug Combinations; Electrochemistry; Family Health; Female; Glycine; Humans; Levodopa; Male; Models, Structural; Point Mutation; Protein Binding; Protein Conformation

Parental history of stroke and myocardial infarction predicts coronary artery calcification: The Coronary Artery Risk Development in Young Adults (CARDIA) study. - Fornage, Myriam; Lopez, David S; Roseman, Jeffrey M; Siscovick, David S; Wong, Nathan D; Eric Boerwinkle (Eur J Cardiovasc Prev Rehabil, 2004)
BACKGROUND: Few studies have examined the relationship between parental history of stroke and myocardial infarction (MI) and subclinical atherosclerosis, especially among young, asymptomatic individuals. This study investigates the association between coronary artery calcification (CAC) and parental history of stroke and MI in African-Americans and Caucasians from the CARDIA study. METHODS: Parental history of stroke and MI was determined by self-administered family history questionnaire at baseline and Year 5 examinations. Presence of coronary calcification was determined by computed tomography on 3041 individuals, age 32 to 47, including 1375 African-Americans and 1666 Caucasians. Analyses were restricted to individuals free of clinically manifest coronary heart disease (CHD) and stroke. RESULTS: Parental history of stroke is associated with a two-fold greater risk of CAC in African-Americans, and this relationship is independent from established CHD risk factors (95% CI=1.14-3.43). There is no relationship between parental history of stroke and CAC status in Caucasians. Parental history of MI is associated with a two-fold greater risk of CAC in Caucasians (95% CI=1.38-2.92). The impact of parental history of MI in African-Americans is lower (OR=1.65; 95% CI=1.01-2.69) and no longer statistically significant after adjusting for known CHD risk factors. CONCLUSIONS: The identification of individuals with a parental history of stroke and MI provides important information for clinicians by which to target primary prevention efforts. Further characterization of familial factors, especially genetic factors, contributing to increased risk of CAC will shed light on the basis of the observed associations.
Keywords: Adolescent; Adult; Black or African American; Calcinosis; Coronary Artery Disease; Fathers; Female; Humans; Male; Mothers; Myocardial Infarction; Prospective Studies; Stroke; White People

Polymorphism of the soluble epoxide hydrolase is associated with coronary artery calcification in African-American subjects: The Coronary Artery Risk Development in Young Adults (CARDIA) study. - Fornage, Myriam; Eric Boerwinkle; Doris, Peter A; Jacobs, David; Liu, Kiang; Wong, Nathan D (Circulation, 2004)
BACKGROUND: Modulation of endogenous epoxide levels by soluble epoxide hydrolase (sEH) in the endothelium represents an important mechanism in the regulation of cardiovascular function. We examined the relationship between a common, functional polymorphism of the human sEH gene and coronary artery calcification (CAC) in young, largely asymptomatic African-American and non-Hispanic white subjects. METHODS AND RESULTS: Multiple logistic regression and Tobit regression models were used to assess the relationship between the sEH Arg287Gln polymorphism and presence and quantity of CAC. Models adjusting for race (except in race-specific analyses), age, sex, smoking, body mass index, systolic blood pressure, LDL cholesterol, and HDL cholesterol were estimated. Allele and genotype frequency distributions were not significantly different between the 2 ethnic groups (P=0.22; P=0.17, respectively). The Arg287Gln polymorphism of the sEH gene was a significant predictor of CAC status in African-American participants, either alone or after adjusting for other risk factors. African-American subjects with at least 1 copy of the Gln287 allele had a 2-fold greater risk of having CAC compared with those not carrying this allele (95% CI, 1.1 to 2.9; P=0.02). There was no relationship between Arg287Gln polymorphism and the probability of having CAC in white participants (OR, 0.8; 95% CI, 0.5 to 1.3; P=0.49). Inferences from multivariable Tobit regression were similar to those obtained in the logistic regression models, indicating that the Arg287Gln polymorphism was a significant independent predictor of both presence and quantity of CAC in African-American but not white subjects. CONCLUSIONS: These data suggest an intriguing and possibly novel role for sEH in the pathogenesis of atherosclerosis, which deserves additional investigation.
Keywords: Adolescent; Adult; Black or African American; Calcinosis; Coronary Artery Disease; Coronary Vessels; Epoxide Hydrolases; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Male; Polymorphism, Genetic; Risk Factors

Relationship between low-density lipoprotein subclasses and asymptomatic atherosclerosis in subjects from the Atherosclerosis Risk in Communities (ARIC) Study. - Hallman, D Michael; Brown, Spencer A; Ballantyne, Christie M; Sharrett, A Richey; Eric Boerwinkle (Biomarkers, 2004)
Low-density lipoprotein (LDL) particle size has been associated with coronary heart disease, but an association between LDL size and preclinical atherosclerosis is less well established. Using gradient gel electrophoresis, large (A), intermediate (I) and small (B) LDL size subclasses were determined in 198 cases with asymptomatic carotid artery atherosclerosis (determined by B-mode ultrasonography) and 318 controls from the Atherosclerosis Risk in Communities (ARIC) Study. In Caucasians, a smaller LDL size was more prevalent in men and associated with a higher body mass index, hypertension prevalence, and plasma total- and LDL-cholesterol and triglycerides, but lower HDL-cholesterol. In African-Americans, a smaller LDL size was associated with higher triglycerides and lower HDL-cholesterol and hypertension prevalence. In Caucasians, Subclass B prevalence was 29.1% among cases and 14.8% among controls. The odds ratio (95% confidence interval) for Subclass B rather than Subclass A in Caucasian cases was 2.94 (1.67-5.17); the association remained significant after controlling for age, body mass index, smoking, and either plasma triglycerides or HDL-cholesterol. In African-Americans, however, there was no significant association between LDL subclass and case status. A predominance of smaller LDL particles is associated with asymptomatic carotid artery atherosclerosis in Caucasians, through mechanisms that remain to be elucidated.
Keywords: Arteriosclerosis; Carotid Arteries; Case-Control Studies; Cholesterol, HDL; Female; Humans; Hypertension; Lipoproteins, LDL; Male; Middle Aged; Odds Ratio; Particle Size; Racial Groups; Triglycerides; Tunica Intima

Somatic and germline instability of the ATTCT repeat in spinocerebellar ataxia type 10. - Matsuura, Tohru; Fang, Ping; Lin, Xi; Khajavi, Mehrdad; Tsuji, Kuniko; Rasmussen, Astrid; Grewal, Raji P; Achari, Madhureeta; Alonso, Maria E; Pulst, Stefan M; Zoghbi, Huda Y; Nelson, David L; et al. (Am J Hum Genet, 2004)
Spinocerebellar ataxia type 10 (SCA10) is an autosomal dominant disorder characterized by ataxia, seizures, and anticipation. It is caused by an expanded ATTCT pentanucleotide repeat in intron 9 of a novel gene, designated "SCA10." The ATTCT expansion in SCA10 represents a novel class of microsatellite repeat and is one of the largest found to cause human diseases. The expanded ATTCT repeat is unstably transmitted from generation to generation, and an inverse correlation has been observed between size of repeat and age at onset. In this multifamily study, we investigated the intergenerational instability, somatic and germline mosaicism, and age-dependent repeat-size changes of the expanded ATTCT repeat. Our results showed that (1) the expanded ATTCT repeats are highly unstable when paternally transmitted, whereas maternal transmission resulted in significantly smaller changes in repeat size; (2) blood leukocytes, lymphoblastoid cells, buccal cells, and sperm have a variable degree of mosaicism in ATTCT expansion; (3) the length of the expanded repeat was not observed to change in individuals over a 5-year period; and (4) clinically determined anticipation is sometimes associated with intergenerational contraction rather than expansion of the ATTCT repeat.
Keywords: Age Distribution; Cell Line; Disease Transmission, Infectious; DNA; Female; Genes, Dominant; Germ Cells; Humans; Leukocytes; Male; Microsatellite Repeats; Mouth Mucosa; Pedigree; Repetitive Sequences, Nucleic Acid; Spermatozoa; Spinocerebellar Ataxias

Are extended biopsies really necessary to improve prostate cancer detection? - Damiano, R; Autorino, R; Perdonà, S; De Sio, M; Oliva, A; Esposito, C; Cantiello, F; Di Lorenzo, G; Sacco, R; D'Armiento, M (Prostate Cancer Prostatic Dis, 2003)
The aim of this study is to understand the value of specific sites in extended peripheral and transition zone biopsy schemes in order to define the optimal systematic biopsy regimen correlated with the percentage of positivity of each single bioptic site. A total of 165 consecutive patients underwent transrectal ultrasonography examination to detect prostate cancer followed by a lesion-directed and systematic 14-step biopsy scheme. The detection rate was examined for the lesion-directed and for each zone region biopsy. The frequency of positive biopsies in the various prostate regions was determined to evaluate the diagnostic yield of each biopsy site. Analysis was stratified for prostate-specific antigen (PSA), free-to-total PSA ratio, age, prostate size and digital rectal examination. The biopsy protocol detected 40% of patients (66/165) as positive and 55.1% (91/165) as negative for cancer. Standard sextant biopsy was expected to detect only 51 cancer on 66, lateral peripheral (PZ), transition (TZ) and central zone (CZ) biopsies only 56 cancer on 66, while the combination of sextant, PZ, TZ and CZ biopsies, for a total of 14 zone biopsies, detected 64 on 66 patients with cancer (97%) at recruitment. Sampling only the eight prostate regions with higher frequency of positive cancer biopsy was expected to detect 61 cancer patients against the 64 found with the 14-step scheme. This eight-biopsy regimen outperforms the conventional sextant regimen in cancer detection rate (93 vs 77%) and has an overall detection rate lower by only 3.1% (36.9 vs 40%) compared to the 14-biopsy regimen. This difference in detection rate is even smaller in patients with PSA values <10 ng/ml, age <70 y and prostate size <50 ml. This eight-biopsy scheme, including sampling in PZ and TZ toward the base, should be considered in an initial biopsy scheme to maintain a similar detection rate of an extensive biopsy scheme reducing the number of biopsies.
Keywords: Biopsy; Humans; Male; Middle Aged; Prostate; Prostate-Specific Antigen; Prostatic Neoplasms; Ultrasonography

Differentially expressed nucleolar TGF-beta1 target (DENTT) in mouse development. - Ozbun, Laurent L; Martínez, Alfredo; Angdisen, Jerry; Umphress, Sarah; Kang, Yang; Wang, Min; You, Ming; Jakowlew, Sonia B (Dev Dyn, 2003)
Differentially expressed nucleolar TGF-beta1 target (DENTT) is a recently identified gene whose mRNA is differentially affected by TGF-beta1 in TGF-beta1-responsive human lung cancer cells and who is a new member of the TSPY/TSPY-like/SET/NAP-1 (TTSN) protein superfamily. Here, we report that mouse DENTT mRNA contains a 2031-bp open reading frame that encodes a predicted polypeptide of 677-amino acids with a relative molecular mass of 77,671 Da. The mouse and human DENTT sequences show 77% and 78% homology at the nucleotide and amino acid level, respectively. Mouse DENTT is predicted to be a nuclear protein with two nuclear localization signals (NLS), two coiled-coil regions, and a domain that shows significant identity to a region that defines the TTSN superfamily. Green fluorescent protein (GFP)-tagged full-length mouse DENTT transfected into COS-7 cells showed localization predominantly in the nucleolus. Reverse transcription-polymerase chain reaction amplification, Northern hybridization, and Western blot analyses showed expression of mouse DENTT mRNA and protein throughout mouse embryogenesis. Immunohistochemical staining analysis showed that DENTT is expressed in multiple tissues in a defined spatiotemporal pattern during mouse embryogenesis. The heart and primitive brain were the first organs of the embryo that showed immunoreactivity for the DENTT antibody by day 8 of development (E8). In the developing mouse brain, the choroid plexus was intensely stained for DENTT in all stages of development. The spinal cord and dorsal root ganglia were also positive for DENTT staining beginning in the 11-day-old embryo (E11), where homogeneous immunostaining was observed throughout the developing neurons. By day 16 of development (E16), only a small subset of the neuronal population in the spinal cord and dorsal root ganglia was positively stained for DENTT. DENTT immunoreactivity increased steadily with maturation as the differentiation of cartilage and osteoblasts proceeded and reached a maximum in the growth plate during endochondral ossification. DENTT expression was also detected in multiple rodent cell types in vitro, including mouse F9 embryonal carcinoma (EC) cells. Addition of retinoic acid or sodium butyrate to F9 EC cells showed a rapid decrease in expression of DENTT protein occurring by 1 hr that continued to decrease to almost undetectable levels after 24 hr. Cotransfection of full-length mouse DENTT expression plasmid with 3TPLux or COL7A1Luc Luciferase reporter plasmids into F9 EC cells significantly increased the level of 3TPLux reporter transcription while decreasing the level of COL7A1Luc reporter transcription, suggesting that DENTT may play multiple roles in modulating transcriptional responses. These findings suggest new roles for the TTSN superfamily during embryogenesis and differentiation.
Keywords: 3T3 Cells; Animals; Base Sequence; Blotting, Northern; Blotting, Western; Bone and Bones; Cardiovascular System; Cell Cycle Proteins; Cell Differentiation; Cell Nucleolus; Chorion; Digestive System; DNA-Binding Proteins; Female; Gene Expression Regulation, Developmental; Genes, Reporter; Heart; Humans; Immunohistochemistry; Male; Mice; Mice, Inbred C57BL; Molecular Sequence Data; Nervous System; Nuclear Proteins; Placenta; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Sequence Homology, Amino Acid; Transcriptional Activation; Transforming Growth Factor beta; Transforming Growth Factor beta1

Evaluating the context-dependent effect of family history of stroke in a genome scan for hypertension. - Morrison, Alanna C; Brown, Andrew; Kardia, Sharon L R; Turner, Stephen T; Eric Boerwinkle (Stroke, 2003)
BACKGROUND AND PURPOSE: Hypertension is an important risk factor for stroke, and the 2 diseases may share susceptibility genes in common. We sought to identify genomic regions influencing susceptibility to both hypertension and stroke. SUBJECTS AND METHODS: Genome-wide linkage scans were performed in samples of 338 white and 265 black hypertensive sibships recruited by the Genetic Epidemiology Network of Arteriopathy Study of the NHLBI Family Blood Pressure Program (FBPP). The hypertensive sibships were stratified by positive (+FH) or negative (-FH) family history of stroke. Genome-wide scans were repeated in each stratum, and the results were compared within each ethnic group by a regression-based analysis of heterogeneity. RESULTS: In whites, the best evidence for linkage was found on chromosome 16 in the unstratified sample of hypertensive sibpairs (logarithm of odds [LOD]=1.85 at 71 cM). In blacks, the best evidence for linkage was found on chromosome 2 in the unstratified sample of hypertensive sibpairs (LOD=1.95 at 230 cM). Additional evidence for linkage (LOD >or=1.5) was observed among white hypertensive sibpairs with a -FH on chromosome 13 and among black hypertensive sibpairs with a +FH of stroke on chromosome 19. CONCLUSIONS: Significant evidence for linkage heterogeneity among hypertensive sibpairs stratified by family history of stroke suggests the presence of genes influencing susceptibility to both hypertension and stroke on chromosomes 13 (whites) and 19 (blacks). Although no significant evidence of heterogeneity was observed on chromosome 16 in whites and chromosome 2 in blacks, these chromosomes do provide evidence of linkage to hypertension.
Keywords: Adult; Aged; Black People; Body Mass Index; Chromosomes, Human, Pair 13; Chromosomes, Human, Pair 16; Chromosomes, Human, Pair 19; Chromosomes, Human, Pair 2; Ethnicity; Family Health; Female; Genes; Genetic Heterogeneity; Genetic Linkage; Genetic Predisposition to Disease; Genetic Testing; Genome, Human; Humans; Hypercholesterolemia; Hypertension; Male; Middle Aged; Minnesota; Mississippi; Risk Factors; Sample Size; Siblings; Stroke; Texas; White People

From vulnerable plaque to vulnerable patient: a call for new definitions and risk assessment strategies: Part II. - Naghavi, Morteza; Libby, Peter; Falk, Erling; Casscells, S Ward; Litovsky, Silvio; Rumberger, John; Badimon, Juan Jose; Stefanadis, Christodoulos; Moreno, Pedro; Pasterkamp, Gerard; Fayad, Zahi; Stone, Peter H; et al. (Circulation, 2003)
Atherosclerotic cardiovascular disease results in >19 million deaths annually, and coronary heart disease accounts for the majority of this toll. Despite major advances in treatment of coronary heart disease patients, a large number of victims of the disease who are apparently healthy die suddenly without prior symptoms. Available screening and diagnostic methods are insufficient to identify the victims before the event occurs. The recognition of the role of the vulnerable plaque has opened new avenues of opportunity in the field of cardiovascular medicine. This consensus document concludes the following. (1) Rupture-prone plaques are not the only vulnerable plaques. All types of atherosclerotic plaques with high likelihood of thrombotic complications and rapid progression should be considered as vulnerable plaques. We propose a classification for clinical as well as pathological evaluation of vulnerable plaques. (2) Vulnerable plaques are not the only culprit factors for the development of acute coronary syndromes, myocardial infarction, and sudden cardiac death. Vulnerable blood (prone to thrombosis) and vulnerable myocardium (prone to fatal arrhythmia) play an important role in the outcome. Therefore, the term "vulnerable patient" may be more appropriate and is proposed now for the identification of subjects with high likelihood of developing cardiac events in the near future. (3) A quantitative method for cumulative risk assessment of vulnerable patients needs to be developed that may include variables based on plaque, blood, and myocardial vulnerability. In Part I of this consensus document, we cover the new definition of vulnerable plaque and its relationship with vulnerable patients. Part II of this consensus document will focus on vulnerable blood and vulnerable myocardium and provide an outline of overall risk assessment of vulnerable patients. Parts I and II are meant to provide a general consensus and overviews the new field of vulnerable patient. Recently developed assays (eg, C-reactive protein), imaging techniques (eg, CT and MRI), noninvasive electrophysiological tests (for vulnerable myocardium), and emerging catheters (to localize and characterize vulnerable plaque) in combination with future genomic and proteomic techniques will guide us in the search for vulnerable patients. It will also lead to the development and deployment of new therapies and ultimately to reduce the incidence of acute coronary syndromes and sudden cardiac death. We encourage healthcare policy makers to promote translational research for screening and treatment of vulnerable patients.
Keywords: Animals; Biomarkers; Coronary Artery Disease; Death, Sudden, Cardiac; Disease Susceptibility; Female; Humans; Male; Mass Screening; Myocardial Infarction; Myocardium; Risk Assessment; Severity of Illness Index; Swine; Thrombophilia

Gene expression profiling and functional proteomic analysis reveal perturbed kinase-mediated signaling in genetic stroke susceptibility. - Fornage, Myriam; Swank, Michael W; Eric Boerwinkle; Doris, Peter A (Physiol Genomics, 2003)
The stroke-prone spontaneously hypertensive rat (SHRSP) is a model of heritable hypertension-associated cerebrovascular injury. This study sought to compare SHRSP to the stroke-resistant SHR strain to identify genes and protein pathways whose expression and/or function was significantly altered between the strains prior to the onset of stroke. Cerebral cortex gene expression profiles from male SHRSPs and matched SHRs were examined by Affymetrix microarray analysis. mRNAs encoding the brain-derived neurotrophic factor receptor (TrkB) and multiple kinases of the MAPK/AKT signaling pathways, including JNK2, AKT2, and PI3K, were differentially expressed between SHRSP and SHR. Because these data suggest altered function in pathways involving MAP and AKT kinase activity, we performed Western blot using phosphorylation state-specific antibodies to characterize activity of MAP kinase and PI3K/AKT pathways. Changes in the levels of the phosphorylated forms of these kinases paralleled the changes in transcript levels observed between the strains. Two-dimensional gel electrophoresis and peptide fragment mass fingerprinting were used to identify altered protein substrates of these kinases. Protein profiling of kinase substrates further supported the notion of perturbed kinase-mediated signaling in SHRSP and identified adenylyl cyclase associated protein 2, TOAD-64, propionyl CoA carboxylase, APG-1, and valosin-containing protein as kinase targets whose phosphorylation state is altered between these strains. Altered gene and protein expression patterns in SHRSP are consistent with increased vulnerability of this strain to cerebrovascular injury.
Keywords: Animals; Blotting, Western; Cerebral Cortex; Enzyme Activation; Gene Expression Profiling; Genetic Predisposition to Disease; Male; MAP Kinase Signaling System; Mitogen-Activated Protein Kinases; Oligonucleotide Array Sequence Analysis; Phosphorylation; Protein Kinases; Proteomics; Rats; Rats, Inbred SHR; Receptor, trkB; Stroke

Genetic disruption of cortical interneuron development causes region- and GABA cell type-specific deficits, epilepsy, and behavioral dysfunction. - Powell, Elizabeth M; Campbell, Daniel B; Stanwood, Gregg D; Davis, Caleb; Noebels, Jeffrey L; Levitt, Pat (J Neurosci, 2003)
The generation of properly functioning circuits during brain development requires precise timing of cell migration and differentiation. Disruptions in the developmental plan may lead to neurological and psychiatric disorders. Neocortical circuits rely on inhibitory GABAergic interneurons, the majority of which migrate from subcortical sources. We have shown that the pleiotropic molecule hepatocyte growth factor/scatter factor (HGF/SF) mediates interneuron migration. Mice with a targeted mutation of the gene encoding urokinase plasminogen activator receptor (uPAR), a key component in HGF/SF activation and function, have decreased levels of HGF/SF and a 50% reduction in neocortical GABAergic interneurons at embryonic and perinatal ages. Disruption of interneuron development leads to early lethality in most models. Thus, the long-term consequences of such perturbations are unknown. Mice of the uPAR-/- strain survive until adulthood, and behavior testing demonstrates that they have an increased anxiety state. The uPAR-/- strain also exhibits spontaneous seizure activity and higher susceptibility to pharmacologically induced convulsions. The neocortex of the adult uPAR-/- mouse exhibits a dramatic region- and subtype-specific decrease in GABA-immunoreactive interneurons. Anterior cingulate and parietal cortical areas contain 50% fewer GABAergic interneurons compared with wild-type littermates. However, interneuron numbers in piriform and visual cortical areas do not differ from those of normal mice. Characterization of interneuron subpopulations reveals a near complete loss of the parvalbumin subtype, with other subclasses remaining intact. These data demonstrate that a single gene mutation can selectively alter the development of cortical interneurons in a region- and cell subtype-specific manner, with deficits leading to long-lasting changes in circuit organization and behavior.
Keywords: Animals; Anxiety; Behavior, Animal; Calcium-Binding Proteins; Cell Count; Darkness; Electroencephalography; Epilepsy; Exploratory Behavior; GABA Antagonists; gamma-Aminobutyric Acid; Genetic Predisposition to Disease; Interneurons; Light; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Neocortex; Receptors, Cell Surface; Receptors, Urokinase Plasminogen Activator; Spatial Behavior

Interaction between soluble thrombomodulin and intercellular adhesion molecule-1 in predicting risk of coronary heart disease. - Wu, Kenneth K; Aleksic, Nena; Ballantyne, Christie M; Ahn, Chul; Juneja, Harinder; Eric Boerwinkle (Circulation, 2003)
BACKGROUND: Results from previous ARIC (Atherosclerosis Risk In Communities) analyses indicate that soluble intercellular adhesive molecule-1 (sICAM) and soluble thrombomodulin (sTM) levels are associated with risk of coronary heart disease (CHD) in an opposite direction. A high sICAM level increases the risk of CHD, whereas a high level of sTM has a lower risk of CHD. It was unclear whether there was an interaction between sTM and sICAM. METHODS AND RESULTS: Using a nested case-cohort design, we measured sTM and sICAM in 317 incident CHD cases and 726 non-cases from the ARIC participants. Consistent with our previous reports, sICAM values in the upper versus the lower tertile increased the risk of CHD event by approximately 2-fold (95% confidence interval [CI], 1.46 to 2.87) whereas sTM values in the lower versus the upper tertile increased CHD risk by approximately 4-fold (95% CI, 2.80 to 5.74). Interaction between these 2 parameters was determined by weighted Cox proportional hazard regression. A significant interaction (P=0.038) was noted. Combinatorial analysis shows a significant increase in CHD risk ratio (RR) (4.66, 95% CI, 1.89 to 11.46) of the lower sTM/upper sICAM group versus the upper sTM/lower sICAM group. Individuals whose sTM values were in the upper tertile had a RR below 1, even when sICAM were in the upper tertile. The RR of lower tertile sTM was increased by sICAM in a tertile-dependent manner. CONCLUSIONS: Weighted Cox proportional hazard analysis shows a significant interaction between sTM and sICAM in predicting risk of CHD event. Combinatorial analysis reveals that an upper tertile sICAM had a significant increase in the risk of a CHD event only when sTM was in the lower tertile.
Keywords: Case-Control Studies; Coronary Disease; Female; Humans; Intercellular Adhesion Molecule-1; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Thrombomodulin

Lack of genetic linkage evidence for a trans-acting factor having a large effect on plasma lipoprotein[a] levels in African Americans. - Barkley, Ruth Ann; Brown, Andrew C; Hanis, Craig L; Kardia, Sharon L; Turner, Stephen T; Eric Boerwinkle (J Lipid Res, 2003)
The distribution of plasma lipoprotein[a] (Lp[a]) concentrations, a risk factor for cardiovascular disease, varies greatly among racial groups, with African Americans having values that are shifted toward higher levels than those of whites. The underlying cause of this heterogeneity is unknown, but a role for "trans-acting" factors has been hypothesized. This study used genetic linkage analysis to localize genetic factors influencing Lp[a] levels in African Americans that were absent in other populations; linkage results were analyzed separately in non-Hispanic whites, Hispanic whites, and African Americans. As expected, all three samples showed highly significant linkage at the approximate location of the lysophosphatidic acid locus. The white populations also independently had regions of significant linkage on chromosome 19 (LOD 3.80) and suggestive linkage on chromosomes 12 (LOD 1.60), 14 (LOD 2.56), and 19 (LOD 2.52). No linkage evidence was found to support the hypothesis of another single gene with large effects specifically segregating in African Americans that may account for their elevated Lp[a] levels.
Keywords: Adult; Aged; Black or African American; Black People; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 14; Chromosomes, Human, Pair 19; Genetic Linkage; Humans; Lipoprotein(a); Lod Score; Lysophospholipids; Male; Middle Aged; Transcriptional Activation; White People

The male-specific region of the human Y chromosome is a mosaic of discrete sequence classes. - Skaletsky, Helen; Kuroda-Kawaguchi, Tomoko; Minx, Patrick J; Cordum, Holland S; Hillier, LaDeana; Brown, Laura G; Repping, Sjoerd; Pyntikova, Tatyana; Ali, Johar; Bieri, Tamberlyn; Chinwalla, Asif; Delehaunty, Andrew; et al. (Nature, 2003)
The male-specific region of the Y chromosome, the MSY, differentiates the sexes and comprises 95% of the chromosome's length. Here, we report that the MSY is a mosaic of heterochromatic sequences and three classes of euchromatic sequences: X-transposed, X-degenerate and ampliconic. These classes contain all 156 known transcription units, which include 78 protein-coding genes that collectively encode 27 distinct proteins. The X-transposed sequences exhibit 99% identity to the X chromosome. The X-degenerate sequences are remnants of ancient autosomes from which the modern X and Y chromosomes evolved. The ampliconic class includes large regions (about 30% of the MSY euchromatin) where sequence pairs show greater than 99.9% identity, which is maintained by frequent gene conversion (non-reciprocal transfer). The most prominent features here are eight massive palindromes, at least six of which contain testis genes.
Keywords: Chromosomes, Human, X; Chromosomes, Human, Y; Crossing Over, Genetic; DNA Transposable Elements; Euchromatin; Evolution, Molecular; Female; Gene Amplification; Gene Conversion; Genes; Heterochromatin; Humans; In Situ Hybridization, Fluorescence; Male; Models, Genetic; Multigene Family; Organ Specificity; Pseudogenes; Sequence Homology, Nucleic Acid; Sex Characteristics; Sex Determination Processes; Species Specificity; Testis; Transcription, Genetic; Transducin

Mapping a locus for familial thoracic aortic aneurysms and dissections (TAAD2) to 3p24-25. - Hasham, Sumera N; Willing, Marcia C; Guo, Dong-chuan; Muilenburg, Ann; He, Rumin; Tran, Van T; Steven E Scherer; Shete, Sanjay S; Milewicz, Dianna M (Circulation, 2003)
BACKGROUND: Familial thoracic aortic aneurysms and dissections (TAAD) occur as part of known syndromes such as Marfan syndrome but can also be inherited in families in an autosomal dominant manner as an isolated condition. Previous studies have mapped genes causing nonsyndromic familial TAAD to 5q13-15 (TAAD1) and 11q23.2-q24 (FAA1). Further genetic heterogeneity for the condition was evident by the presence of TAAD in some families not linked to these known loci. METHODS AND RESULTS: A 4-generation family with dominant mode of inheritance of TAAD was studied. Affected status was determined by dilation of the ascending aorta, surgical repair of an aneurysm or dissection, or death as the result of aortic dissection. None of the family members evaluated met the diagnostic criteria for Marfan syndrome. After exclusion of known loci for familial TAAD, a genome-wide scan was carried out to map the defective gene causing the disease in the family. A locus was mapped to a 25-cM region on 3p24-25 with a maximum multipoint logarithm of the odds score of 4.28. CONCLUSIONS: A third locus for nonsyndromic TAAD was mapped to 3p24-25 and termed the TAAD2 locus. This locus overlaps a previously mapped second locus for Marfan syndrome, termed the MFS2 locus. Future characterization of the TAAD2 gene will determine if TAAD2 is allelic to MFS2. In addition, identification of the TAAD2 gene will improve the presymptomatic diagnosis of individuals with this life-threatening genetic syndrome and provide information concerning the pathogenesis of the disease.
Keywords: Adolescent; Adult; Aortic Aneurysm, Thoracic; Aortic Dissection; Calcium-Binding Proteins; Child; Chromosome Mapping; Chromosomes, Human, Pair 3; Comorbidity; DNA Mutational Analysis; Echocardiography; Extracellular Matrix Proteins; Female; Genes, Dominant; Genetic Linkage; Genetic Markers; Genotype; Germany; Haplotypes; Humans; Lod Score; Male; Marfan Syndrome; Middle Aged; Pedigree; Penetrance; Switzerland

Positional cloning of the major quantitative trait locus underlying lung tumor susceptibility in mice. - Zhang, Zhongqiu; Futamura, Manabu; Vikis, Haris G; Wang, Min; Li, Jie; Wang, Yian; Guan, Kun-Liang; You, Ming (Proc Natl Acad Sci U S A, 2003)
Pulmonary adenoma susceptibility 1 (Pas1), located on chromosome 6, is the major locus affecting inherited predisposition to lung tumor development in mice. We have fine mapped the Pas1 locus to a region of approximately 0.5 megabases by using congenic strains of mice, constructed by placing the Pas1 region of chromosome 6 from A/J mice onto the genetic background of C57BL/6J mice. Systematic characterization of Pas1 candidates establishes the Las1 (lung adenoma susceptibility 1) and Kras2 (Kirsten rat sarcoma oncogene 2) genes as primary candidates for the Pas1 locus. Clearly, Kras2 affects lung tumor progression only, and Las1 is likely to affect lung tumor multiplicity.
Keywords: Adenoma; Amino Acid Sequence; Animals; Base Sequence; Blotting, Northern; Chromosome Mapping; Ciona intestinalis; Cloning, Molecular; DNA Primers; Genetic Markers; Genetic Predisposition to Disease; Humans; Lung Neoplasms; Male; Mice; Mice, Inbred A; Mice, Inbred C57BL; Mice, Nude; Microsatellite Repeats; Molecular Sequence Data; Proto-Oncogene Proteins; Proto-Oncogene Proteins p21(ras); Quantitative Trait Loci; ras Proteins; Reverse Transcriptase Polymerase Chain Reaction; Sequence Alignment; Sequence Homology, Amino Acid

ADD1 460W allele associated with cardiovascular disease in hypertensive individuals. - Morrison, Alanna C; Bray, Molly S; Folsom, Aaron R; Eric Boerwinkle (Hypertension, 2002)
High blood pressure is a predictor of cardiovascular disease. Hence, genes contributing to essential hypertension may play a role in the etiology of cardiovascular disease. For this reason, we examined the association between the alpha-adducin (ADD1) G460W and G-protein beta3 subunit (GNB3) 825C>T polymorphisms and the prevalence of peripheral arterial disease (PAD) and incidence of coronary heart disease (CHD) in non-Hispanic whites from the Atherosclerosis Risk in Communities (ARIC) Study. PAD prevalence was defined by an ankle-brachial index, ie, the ratio of ankle systolic blood pressure to brachial artery systolic blood pressure, of </=0.90 for men and </=0.85 for women. CHD incidence was determined by following the ARIC cohort for a median of 5.3 years for potential coronary events. Stratified random samples of the ARIC cohort (n=703 and n=684) were used, respectively, as the comparison groups for the PAD (n=144) and incident CHD (n=408) cases. The GNB3 825T allele and the ADD1 460W allele were not significantly associated with prevalence of PAD or incidence of CHD. However, a test of the interaction between hypertension status and the ADD1 G460W polymorphism indicated that further evaluation of the ADD1 polymorphism in only hypertensive individuals was warranted. The ADD1 460W allele was significantly associated with PAD (odds ratio [OR]: 2.61, 95% CI, 1.27-5.37, P=0.01) and CHD (hazard rate ratio [HRR]: 2.30, 95% CI, 1.20-4.42, P=0.01) in hypertensive individuals after adjustment for multiple cardiovascular disease risk factors. An interaction with hypertension in the association between the ADD1 G460W polymorphism and cardiovascular disease merits further testing in additional populations.
Keywords: Alleles; Arterial Occlusive Diseases; Calmodulin-Binding Proteins; Cardiovascular Diseases; Case-Control Studies; Coronary Disease; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Heterotrimeric GTP-Binding Proteins; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Prevalence; White People

The beta-globin C-->G mutation at 6 bp 3' to the termination codon causes beta-thalassaemia by decreasing the mRNA level. - Sgourou, Argyro; Papachatzopoulou, Adamandia; Psiouri, Lambrini; Antoniou, Michael; Zoumbos, Nicholas; Richard A Gibbs; Athanassiadou, Aglaia (Br J Haematol, 2002)
We have studied the expression of the silent beta-thalassaemia term+6 (C-->G) mutation, at nucleotide 6 after the stop codon within the human beta-globin 3' untranslated regions (3'UTR), by stable transfection in murine erythroleukaemia (MEL) cells. Steady state mRNA levels from transfected MEL cells containing the term+6 mutant allele were reduced by 52-60%, compared with those obtained from the normal beta-globin gene, in both total and cytoplasmic RNA fractions, showing that the mutation itself is responsible for the similar data obtained from patients. Upon analysis of nuclear RNA, the term+6 mutation was found to also lower the ratio of cleaved/uncleaved transcripts by 22-30%, thus revealing that it interferes with correct 3'-end formation of beta-globin mRNA. The term+6 mutation lies within a polypyrimidine track, similar to that in the beta-intervening sequence II (beta-IVSII), which is known to be an important contributor to the promotion of premRNA 3'-end formation. We propose that the two polypyrimidine tracks flanking the translated region of exon III of the human beta-globin gene may co-operate during beta-globin mRNA biogenesis.
Keywords: beta-Thalassemia; Child; Codon, Terminator; Globins; Humans; Male; Mutation; RNA, Messenger; Transfection

Factor XIIIA Val34Leu polymorphism does not predict risk of coronary heart disease: The Atherosclerosis Risk in Communities (ARIC) Study. - Aleksic, Nena; Ahn, Chul; Wang, Yao-Wei; Juneja, Harinder; Folsom, Aaron R; Eric Boerwinkle; Wu, Kenneth K (Arterioscler Thromb Vasc Biol, 2002)
Factor XIII catalyzes the cross-linking of fibrin. Cross-sectional studies have suggested that a common polymorphism site at residue 34 of the A subunit of factor XIII (FXIIIA) with a substitution of Leu for Val (FXIIIA Val34Leu) was associated with reduced coronary heart disease (CHD). This association has not been examined in prospective studies. Healthy subjects (n=15 792) were recruited from 4 US communities into the Atherosclerosis Risk in Communities (ARIC) study from 1987 to 1989. They were followed, and incident CHD events were identified and verified. For the present study, we included 423 patients with CHD as cases and 479 noncases. FXIIIA Val34Leu polymorphism was determined by the single-strand conformational polymorphism method. There were no significant differences in the genotype frequencies between cases and noncases. The genotypes showed little association with known CHD risk factors. A weighted proportional hazards regression analysis adjusting for other risk factors confirmed no association of the genotypes with risk of CHD. This prospective study did not provide evidence of a reduced CHD risk for the FXIIIA 34Leu allele.
Keywords: Case-Control Studies; Coronary Artery Disease; Factor XIIIa; Female; Gene Frequency; Genotype; Humans; Incidence; Male; Maryland; Middle Aged; Minnesota; Mississippi; North Carolina; Polymorphism, Single-Stranded Conformational; Risk Factors

LPL polymorphism predicts stroke risk in men. - Morrison, Alanna C; Ballantyne, Christie M; Bray, Molly; Chambless, Lloyd E; Sharrett, A Richey; Eric Boerwinkle (Genet Epidemiol, 2002)
Variation in lipid levels has been associated with atherosclerotic vascular disease, including stroke. Genes contributing to interindividual variation in lipid levels may play a role in the etiology of stroke, either through their effects on lipid synthesis and metabolism or through separate pathways. For this reason, we sought to examine the association between polymorphisms in the lipoprotein lipase (LPL) and apolipoprotein E (APOE) genes and subclinical and clinical stroke in the Atherosclerosis Risk in Communities (ARIC) Study. Subclinical stroke was determined by cerebral magnetic resonance imaging (MRI). Subclinical cerebral infarct cases (n = 197) were compared to a stratified random sample identified from individuals participating in the MRI examination (n = 200). Incidence of clinical ischemic stroke was determined by following the ARIC cohort for an average of 7.5 years for potential cerebrovascular events; 218 validated clinical ischemic strokes were identified. A stratified random sample of the ARIC cohort (CRS, n = 964) was used as the comparison group for clinical cases. The LPL S291-carrying genotypes and APOE epsilon2- and epsilon4-carrying genotypes were not significantly associated with subclinical or clinical stroke. The LPL X447-containing genotypes were significantly associated with subclinical (odds ratio [OR], 4.32; 95% confidence interval [CI], 1.23-15.15; P = 0.020) and clinical stroke (hazard rate ratio [HRR], 2.57; 95% CI, 1.24-5.34; P = 0.01) in men, both by themselves and after adjustment for multiple stroke risk factors. The LPL S447X polymorphism is significantly associated with subclinical cerebral infarction and incident clinical ischemic stroke in men from a middle-aged American population. This association does not appear to be mediated by triglyceride, high-density lipoprotein (HDL)- and low-density lipoprotein (LDL)-cholesterol levels, or additional stroke risk factors.
Keywords: Apolipoproteins E; Genetic Predisposition to Disease; Genotype; Humans; Lipoprotein Lipase; Logistic Models; Magnetic Resonance Imaging; Male; Middle Aged; Polymorphism, Genetic; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke

Molecular evidence of HIV-1 transmission in a criminal case. - Metzker, Michael L; Mindell, David P; Liu, Xiao-Mei; Ptak, Roger G; Richard A Gibbs; Hillis, David M (Proc Natl Acad Sci U S A, 2002)
A gastroenterologist was convicted of attempted second-degree murder by injecting his former girlfriend with blood or blood-products obtained from an HIV type 1 (HIV-1)-infected patient under his care. Phylogenetic analyses of HIV-1 sequences were admitted and used as evidence in this case, representing the first use of phylogenetic analyses in a criminal court case in the United States. Phylogenetic analyses of HIV-1 reverse transcriptase and env DNA sequences isolated from the victim, the patient, and a local population sample of HIV-1-positive individuals showed the victim's HIV-1 sequences to be most closely related to and nested within a lineage comprised of the patient's HIV-1 sequences. This finding of paraphyly for the patient's sequences was consistent with the direction of transmission from the patient to the victim. Analysis of the victim's viral reverse transcriptase sequences revealed genotypes consistent with known mutations that confer resistance to AZT, similar to those genotypes found in the patient. A priori establishment of the patient and victim as a suspected transmission pair provided a clear hypothesis for phylogenetic testing. All phylogenetic models and both genes examined strongly supported the close relationship between the HIV-1 sequences of the patient and the victim. Resampling of blood from the suspected transmission pair and independent sequencing by different laboratories provided precaution against laboratory error.
Keywords: Base Sequence; Crime; Crime Victims; DNA, Viral; Female; Forensic Medicine; HIV Envelope Protein gp120; HIV Infections; HIV Reverse Transcriptase; HIV-1; Humans; Male; Molecular Sequence Data; Phylogeny; Sequence Analysis, DNA

Polymorphism in soluble epoxide hydrolase and blood pressure in spontaneously hypertensive rats. - Fornage, Myriam; Hinojos, Cruz A; Nurowska, Barbara W; Eric Boerwinkle; Hammock, Bruce D; Morisseau, Christophe H P; Doris, Peter A (Hypertension, 2002)
We measured soluble epoxide hydrolase (sEH) renal gene expression in prehypertensive (4 to 5 weeks old) spontaneously hypertensive rats of the Heidelberg SP substrain (SHR [Heid]) and when blood pressure levels entered the hypertensive plateau (17 to 18 weeks old) and compared expression with matched Wistar-Kyoto (WKY [Heid]) rats. Less expression of the gene encoding sEH (EPHX2) was observed in SHR (Heid) than in WKY (Heid). Analysis of sEH protein abundance showed a similar difference. However, no correlation between sEH abundance and blood pressure was observed in the F(2) progeny of a parental strain cross. Measurement of protein abundance in SHR and WKY obtained from Charles River confirmed a recent report that abundance of sEH was greater in SHR (CRiv) than WKY (CRiv) strains. Polymorphisms were detected in EPHX2. Resequencing revealed that 2 alleles of EPHX2 exist in these 4 rat strains, differing by 4 single nucleotide polymorphisms, of which 3 produce nonsynonymous amino acid substitutions. The ancestral allele was shared by SHR (Heid) and WKY (CRiv), and the variant allele was shared by WKY (Heid) and SHR (CRiv). Activity of sEH was greater in animals carrying the variant allele. However, inheritance of this allele was not correlated with blood pressure in the F(2) progeny of a cross between SHR (Heid) and WKY (Heid). These data indicate that sequence variation determining functional alterations in EPHX2 is not likely to contribute to blood pressure levels in SHR.
Keywords: Animals; Blood Pressure; Epoxide Hydrolases; Hypertension; Kidney; Male; Polymorphism, Single Nucleotide; Rats; Rats, Inbred SHR; Rats, Inbred WKY; RNA, Messenger

PTPN11 mutations in Noonan syndrome type I: detection of recurrent mutations in exons 3 and 13. - Maheshwari, M; Belmont, J; Fernbach, S; Ho, T; Molinari, L; Yakub, I; Fuli Yu; Combes, A; Towbin, J; Craigen, W J; Richard A Gibbs (Hum Mutat, 2002)
We surveyed 16 subjects with the clinical diagnosis of Noonan Syndrome (NS1) from 12 families and their relevant family members for mutations in PTPN11/SHP2 using direct DNA sequencing. We found three different mutations among five families. Two unrelated subjects shared the same de novo missense substitution in exon 13 (S502T); an additional two unrelated families had a mutation in exon 3 (Y63C); and one subject had the amino acid substitution Y62D, also in exon 3. None of the three mutations were present in ethnically matched controls. In the mature protein model, the exon 3 mutants and the exon 13 mutant amino acids cluster at the interface between the N' SH2 domain and the phosphatase catalytic domain. Six of eight subjects with PTPN11/SHP2 mutations had pulmonary valve stenosis while no mutations were identified in those subjects (N = 4) with hypertrophic cardiomyopathy. An additional four subjects with possible Noonan syndrome were evaluated, but no mutations in PTPN11/SHP2 were identified. These results confirm that mutations in PTPN11/SHP2 underlie a common form of Noonan syndrome, and that the disease exhibits both allelic and locus heterogeneity. The observation of recurrent mutations supports the hypothesis that a special class of gain-of-function mutations in SHP2 give rise to Noonan syndrome.
Keywords: Catalytic Domain; DNA Mutational Analysis; Exons; Female; Humans; Intracellular Signaling Peptides and Proteins; Isoenzymes; Male; Mutation; Noonan Syndrome; Phenotype; Protein Structure, Quaternary; Protein Tyrosine Phosphatase, Non-Receptor Type 11; Protein Tyrosine Phosphatases; Recurrence; SH2 Domain-Containing Protein Tyrosine Phosphatases; src Homology Domains

Genetic mapping and DNA sequence-based analysis of deleted regions on chromosome 16 involved in progression of bladder cancer from occult preneoplastic conditions to invasive disease. - Yoon, D S; Li, L; Zhang, R D; Kram, A; Ro, J Y; Johnston, D; Grossman, H B; Scherer, S; Czerniak, B (Oncogene, 2001)
Histologic and genetic mapping with 30 hypervariable markers mapped to chromosome 16 were performed on 234 DNA samples of five cystectomy specimens from patients with invasive bladder cancer. Allelic losses of individual markers were related to microscopically identified precursor conditions in the entire bladder mucosa and invasive cancer. Their significance for the development and progression of neoplasia from in situ preneoplastic conditions to invasive disease was analysed by the nearest neighbor algorithm and binomial maximum likelihood analysis. Using this approach we identified five distinct regions of allelic losses defined by their flanking markers and predicted size as follows. p13.3(D16S418-D16S406, 1.2 cM), p13.1(D16S748-D16S287, 12.9 cM), q12 1(D16S409-D16S514, 24.0 cM), q22.1 (D16S496-D16S515, 5.4 cM), and q24 (D16S507-D16S511, 5.9 cM and D16S402-D16S413, 17.4 cM). The regions mapping to p13.1 and q24 were involved in early intraurothelial phases of bladder neoplasia such as mild to moderate dysplasia. On the other hand the deleted region mapping to p13.3 was involved in progression of severe dysplasia/carcinoma in situ to invasive bladder cancer. Testing of markers that exhibited statistically significant LOH in relation to progression of neoplasia from precursor conditions to invasive cancer on 28 tumors and voided urine samples from 25 patients with bladder cancer revealed that q12.1 showed LOH in 46.4% of tumor and 32.0% of voided urine samples. The LOH of a single marker D16S541 could be detected in approximately 28% of tumors and 20% of voided urine samples of patients with bladder cancer. These data imply that the deleted region centered around marker D16S541 spanning approximately 10 cM and flanked by D16S409 and D16S415 contains a novel putative tumor suppressor gene or genes playing an important role in the development of human bladder cancer. To facilitate more precise positional mapping and identification of pathogenetically relevant genes, we analysed of human genome contig and sequence databases spanning the deleted regions. Multiple known candidate genes and several smaller gene-rich areas mapping to the target regions of chromosome 16 were identified.
Keywords: Aged; Chromosome Mapping; Chromosomes, Human, Pair 16; Disease Progression; DNA, Neoplasm; Genes, Tumor Suppressor; Genetic Markers; Humans; Loss of Heterozygosity; Male; Middle Aged; Neoplasm Invasiveness; Precancerous Conditions; Sequence Deletion; Tissue Distribution; Urinary Bladder Neoplasms; Urine

Mapping and genome sequence analysis of chromosome 5 regions involved in bladder cancer progression. - Kram, A; Li, L; Zhang, R D; Yoon, D S; Ro, J Y; Johnston, D; Grossman, H B; Scherer, S; Czerniak, B (Lab Invest, 2001)
We studied the evolution of allelic losses on chromosome 5 by whole-organ histologic and genetic mapping in 234 mucosal DNA samples of 5 cystectomy specimens with invasive bladder cancer and preneoplastic changes in adjacent urothelium. The frequency of alterations in individual loci was verified on 32 tumors and 29 voided urine samples from patients with bladder cancer. Finally, deleted regions on chromosome 5 were integrated with the human genome contigs and sequence-based databases. Deleted regions on chromosome 5 involved in intraurothelial phases of bladder neoplasia defined by their nearest flanking markers and predicted size were identified as follows: q13.3-q22 (D5S424-D5S656; 38.8 centimorgan [cM]); q22-q31.1 (D5S656-D5S808; 19.2 cM), q31.1-q32 (D5S816-SPARC; 11.5 cM), and q34 (GABRA1-D5S415; 6.4 cM). The two most frequently deleted neighbor markers (D5S2055 and D5S818) mapping to q22-q31.1 defined a 9 cM region, which may contain genes that play an important role in early phases of urinary bladder carcinogenesis. Human genome database analysis provided an accurate map of deleted regions with positions of 138 known genes and revealed several smaller gene-rich areas representing putative targets for further mapping. The strategic approach presented here, which combines whole-organ histologic and genetic mapping with analysis of the rapidly emerging human genome sequence database, facilitates identification of genes potentially involved in early phases of bladder carcinogenesis.
Keywords: Aged; Alleles; Chromosome Mapping; Chromosomes, Human, Pair 5; Expressed Sequence Tags; Genome; Humans; Loss of Heterozygosity; Male; Middle Aged; Urinary Bladder Neoplasms

AluY insertion (IVS4-52ins316alu) in the glycerol kinase gene from an individual with benign glycerol kinase deficiency. - Zhang, Y; Dipple, K M; Vilain, E; Huang, B L; Finlayson, G; Therrell, B L; Kim C Worley; Deininger, P; McCabe, E R (Hum Mutat, 2000)
Glycerol kinase deficiency has three distinct forms: an isolated form which may be benign or symptomatic, and a complex form which is symptomatic and part of an Xp21 contiguous gene syndrome. Here we report the case of a male with benign isolated glycerol kinase deficiency who was incidentally identified after observation of pseudohypertriglyceridemia. DNA sequencing of this subject's glycerol kinase gene showed the insertion of an AluY sequence in intron 4 of the glycerol kinase gene. Although Alu insertions have been implicated in other diseases, and a closely related AluY element is found as an insert in the C1 inhibitor gene in patients with hereditary angioedema, this is the first case of glycerol kinase deficiency caused by an Alu insertion.
Keywords: Adult; Alu Elements; Base Sequence; Black People; Consensus Sequence; Exons; Gene Amplification; Glycerol Kinase; Humans; Introns; Male; Molecular Sequence Data

Construction of a high-resolution physical map of the chromosome 10q22-q23 dilated cardiomyopathy locus and analysis of candidate genes. - Bowles, K R; Abraham, S E; Brugada, R; Zintz, C; Comeaux, J; Sorajja, D; Tsubata, S; Li, H; Brandon, L; Richard A Gibbs; Steven E Scherer; Bowles, N E; et al. (Genomics, 2000)
Dilated cardiomyopathy (DCM) is a major cause of morbidity and mortality and a leading cause of cardiac transplantation worldwide. Multiple loci and three genes encoding cardiac actin, desmin, and lamin A/C have been described for autosomal dominant DCM. Using recombination analysis, we have narrowed the 10q21-q23 locus to a region of approximately 4.1 cM. In addition, we have constructed a BAC contig, composed of 199 clones, which was used to develop a high-resolution physical map that contains the DCM critical region (approximately 3.9 Mb long). Seven genes, including ANX11, PPIF, DLG5, RPC155, RPS24, SFTPA1, and KCNMA1, have been mapped to the region of interest. RPC155, RPS24, SFTPA1, and KCNMA1 were excluded from further analysis based on their known functions and tissue-specific expression patterns. Mutational analysis of ANX11, DLG5, and PPIF revealed no disease-associated mutations. Multiple ESTs have also been mapped to the critical region.
Keywords: Cardiomyopathy, Dilated; Chromosomes, Bacterial; Chromosomes, Human, Pair 10; DNA Mutational Analysis; Expressed Sequence Tags; Family Health; Female; Genetic Predisposition to Disease; Genomic Library; Humans; Male; Pedigree; Phenotype; Physical Chromosome Mapping; Sequence Analysis, DNA

Fine mapping and characterization of candidate lung tumor resistance genes for the Par2 locus on mouse chromosome 18. - Zhang, Z; Lin, L; Liu, G; Wang, M; Hill, J; Wang, Y; You, M; Devereux, T R (Exp Lung Res, 2000)
In a number of recent studies, a lung tumor resistance locus designated either Par2 or Pas7 was mapped to distal chromosome 18 in crosses between susceptible A/J and more resistant BALB/c mice. This locus is important in that it accounts for as much as 60% of the difference in lung tumor susceptibility between the A/J and BALB/c mice, both of which contain the susceptible allele of Kras2, a marker and strong candidate for the major lung tumor susceptibility gene on mouse chromosome 6. We have now fine-mapped the Par2 locus by using congenic mice that were constructed by placing part of chromosome 18 from the susceptible A/J onto the genetic background of lung tumor-resistant BALB/c mice. After 7 generations of backcrossing, N7 mice that carried 28 cM of the A/J quantitative trait locus (QTL) region were crossed to the BALB/c to generate the N8 generation. Congenic strains (N8) that contain various QTL regions were generated. N9 mice, generated from N8 males x 3 BALB/c females, were genotyped in the region of the Par2 locus and treated with an initiating dose of urethane and allowed to form lung tumors over 6 months. The mice were killed and the lung tumors counted. With this cross the Par2 locus was narrowed to a 6-cM region. Potential candidate genes in this region include Smad4, Smad2, and Dcc. Previously, we excluded Smad4 and Smad2 as candidates for Par2 based on the lack of functional polymorphism(s) and differential expression in lungs from A/J and BALB/c mice. In this study, no polymorphism of the coding sequence of Dcc was observed between A/J and BALB/c mice. Further fine mapping and positional cloning are required for the identification of the Par2 gene.
Keywords: Adenoma; Animals; Animals, Congenic; Chromosome Mapping; Disease Models, Animal; DNA, Neoplasm; Female; Genetic Markers; Genetic Predisposition to Disease; Lung Neoplasms; Male; Mice; Mice, Inbred BALB C; Polymerase Chain Reaction; Polymorphism, Single-Stranded Conformational; Pregnancy; Sequence Analysis, DNA

Large expansion of the ATTCT pentanucleotide repeat in spinocerebellar ataxia type 10. - Matsuura, T; Yamagata, T; Burgess, D L; Rasmussen, A; Grewal, R P; Watase, K; Khajavi, M; McCall, A E; Davis, C F; Zu, L; Achari, M; Pulst, S M; et al. (Nat Genet, 2000)
Spinocerebellar ataxia type 10 (SCA10; MIM 603516; refs 1,2) is an autosomal dominant disorder characterized by cerebellar ataxia and seizures. The gene SCA10 maps to a 3.8-cM interval on human chromosome 22q13-qter (refs 1,2). Because several other SCA subtypes show trinucleotide repeat expansions, we examined microsatellites in this region. We found an expansion of a pentanucleotide (ATTCT) repeat in intron 9 of SCA10 in all patients in five Mexican SCA10 families. There was an inverse correlation between the expansion size, up to 22.5 kb larger than the normal allele, and the age of onset (r2=0.34, P=0.018). Analysis of 562 chromosomes from unaffected individuals of various ethnic origins (including 242 chromosomes from Mexican persons) showed a range of 10 to 22 ATTCT repeats with no evidence of expansions. Our data indicate that the new SCA10 intronic ATTCT pentanucleotide repeat in SCA10 patients is unstable and represents the largest microsatellite expansion found so far in the human genome.
Keywords: Animals; Asian People; Brain; Chromosome Mapping; Chromosomes, Human, Pair 22; DNA; Epilepsy; Female; Humans; Male; Mexican Americans; Mice; Mice, Inbred C57BL; Molecular Sequence Data; Pedigree; Polymorphism, Genetic; Repetitive Sequences, Nucleic Acid; Spinocerebellar Ataxias; United States; White People

Association between serum insulin growth factor-I (IGF-I) and a simple sequence repeat in IGF-I gene: implications for genetic studies of bone mineral density. - Rosen, C J; Kurland, E S; Vereault, D; Adler, R A; Rackoff, P J; Craig, W Y; Witte, S; Rogers, J; Bilezikian, J P (J Clin Endocrinol Metab, 1998)
We recently demonstrated that insulin growth factor-I (IGF-I) cosegregates with bone mineral density (BMD) in progenitor crosses of two inbred strains of mice. Additionally, we reported that men with idiopathic osteoporosis (IOM) have low serum IGF-I levels, which can be related to BMD and bone turnover. In this study, we considered the possibility that serum IGF-I levels are influenced by molecular genetic variation in the IGF-I structural gene, and that a polymorphic microsatellite (CA repeat) in this locus can be used as a genetic marker for such comparisons. We studied 171 men and women, classified according to the trial in which they were participating. First, in 25 Caucasian men with IOM we noted a very high frequency (64%) of homozygosity for the most common allele (192 bp) in a dinucleotide repeat 1 kb upstream from the transcription start site of the IGF-I gene. This compared with a frequency of only 32% in healthy populations (both men and women) (P < 0.004). Next, we determined that for 116 healthy Caucasian men and women the 192/192 genotype was associated with lower serum IGF-I levels than all other genotypes (192/192: 129 +/- 7 ng/mL vs. others: 154 +/- 7 ng/mL, P = 0.03). We also noted that subjects possessing one 194-bp allele exhibited serum IGF-I levels 25% higher than those homozygous for 192 bp (192/192), (P < 0.005) even after correction for age and sex. Similarly, for men with the 192/192 genotype, serum IGF-I concentrations were lower than any other genotype (145 +/- 10 ng/mL vs. 183 +/- 9 ng/ml P < 0.02). In conclusion, low serum IGF-I levels found in men with IOM are associated with homozygosity for a specific allele of the IGF-I microsatellite (192/192), and individual variation in serum IGF-I levels is influenced by genetic factors and may be specifically influenced by variation at the IGF-I structural locus. Further family and pedigree studies are needed to characterize the relationship of bone mass acquisition to the IGF-I genotype.
Keywords: Aged; Alleles; Bone Density; Dinucleotide Repeats; Female; Gene Frequency; Genotype; Humans; Insulin-Like Growth Factor I; Male; Middle Aged; Phenotype; Polymorphism, Genetic

DNA deletion confined to the iduronate-2-sulfatase promoter abolishes IDS gene expression. - Timms, K M; Huckett, L E; Belmont, J W; Shapira, S K; Richard A Gibbs (Hum Mutat, 1998)
Deficiency of the enzyme iduronate-2-sulfatase (IDS) results in Hunter syndrome, an X-linked recessive lysosomal storage disorder. In this study, analysis of a patient with features of moderate to severe Hunter syndrome identified a 178-bp deletion upstream of IDS exon 1 spanning a predicted promoter element. Sequencing of all nine IDS exons from this patient failed to identify any additional mutations within the coding regions or in intron-exon boundaries. The 178-bp deletion is flanked by two 13-bp direct repeats and potential DNA topoisomerase II recognition sites. These findings point toward nonhomologous recombination as a possible mechanism for this mutation. Expression studies on this patient do not detect any IDS transcripts, indicating that the deletion spans sequences essential for IDS expression. Complete lack of expression of IDS is consistent with the moderate to severe phenotype observed in this patient.
Keywords: Base Sequence; Child, Preschool; DNA Mutational Analysis; Gene Expression Regulation; Humans; Iduronate Sulfatase; Male; Molecular Sequence Data; Mucopolysaccharidosis II; Pedigree; Phenotype; Promoter Regions, Genetic; Sequence Analysis, DNA; Sequence Deletion

The genomic organization of Isopeptidase T-3 (ISOT-3), a new member of the ubiquitin specific protease family (UBP). - Timms, K M; Ansari-Lari, M A; Morris, W; Brown, S N; Richard A Gibbs (Gene, 1998)
A novel Isopeptidase T gene (ISOT-3) has been identified on human mosome 3q26.2--q26.3. gene shows 67.3% nucleotide identity and 54.8% amino acid identity to n Isopeptidase (ISOT-1). Northern blot analysis has shown that ISOT-3 is highly essed in ovary and testes, low-level expression in six other tissues tested. In contrast, ISOT-1 is essed at high levels in brain, and there is no detectable expression in ovary. The exonic nization of these two genes highly conserved with only one variant intron position. Intron 15 in -3 is absent in ISOT-1, there is an alternate splice site at the same location. Although the --intron structure has been erved between the two genes, ISOT-3 has significantly larger intronic ons, and the overall of this gene is at least 90 kb compared to 15 kb for ISOT-1. These data suggest that both ISOT-1 and ISOT-3 have descended from a common ancestor. In addition, the low overall sequence identity and different expression patterns may reflect differences in substrate specificity.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Carbon-Nitrogen Lyases; Chromosome Mapping; Chromosomes, Human, Pair 3; Consensus Sequence; DNA, Complementary; Exons; Female; Gene Library; Humans; Male; Mice; Molecular Sequence Data; Organ Specificity; Ovary; Polymerase Chain Reaction; Recombinant Proteins; Saccharomyces cerevisiae; Sequence Alignment; Sequence Homology, Amino Acid; Substrate Specificity; Testis; Ubiquitins

Reassessment of biochemically determined Hunter syndrome carrier status by DNA testing. - Timms, K M; Edwards, F J; Belmont, J W; Yates, J R; Richard A Gibbs (J Med Genet, 1998)
Deficiency of iduronate-2-sulphatase (IDS) results in the X linked recessive lysosomal storage disorder Hunter syndrome. Determination of carrier status in families affected by this disorder has been performed using a variety of enzymatic tests. None of these tests has proved to be 100% effective at identifying carriers. The aim of this study was to perform carrier testing in a family affected by the disorder, where testing was complicated by the fact that no surviving affected subjects were available for study. Direct dye primer sequencing of PCR products was used to identify mixed bases in an obligate carrier. Two mixed bases were observed within exon VIII. The first base change (T-->A) at nucleotide position 1150 results in a missense mutation (H342Q), while the second base change (G-->T) at nucleotide position 1151 results in a nonsense mutation (G343X). Four additional female family members were screened for the same mutation. Using this approach it is possible to provide unambiguous information about a subject's carrier status and, unlike biochemical testing, this approach will be equally effective when applied to families with the mild form of this disorder.
Keywords: DNA; Female; Heterozygote; Humans; Iduronate Sulfatase; Male; Mucopolysaccharidosis II; Pedigree

Relationship of HIV testing and high-risk behaviors among clients in methadone maintenance treatment. - Grella, C E; Campos, M; Anglin, M D (AIDS Educ Prev, 1998)
This article reports on the association between frequency of HIV testing and high-risk behaviors among 339 individuals in the Los Angeles Enhanced Methadone Maintenance Project. Individuals who reported taking three or more HIV tests prior to entering treatment (45% of the sample) were more likely to know someone who was HIV positive, to engage in illegal activity, to perceive their risk for HIV as high, and to use condoms; they were less likely to disinfect injection equipment; and they scored higher on measures of HIV knowledge and depression as compared with less frequent testers. The strongest predictor of frequent HIV testing (three or more tests) after treatment entry, reported by 43% of the sample, was having a high number of injection-sharing partners. Although a substantial number of individuals in methadone maintenance treatment continued to take HIV tests, test taking was more strongly related to high-risk injection behavior than to sexual behavior.
Keywords: Adult; Data Interpretation, Statistical; Depression; Female; Heroin Dependence; HIV Infections; HIV Seropositivity; Humans; Logistic Models; Male; Methadone; Risk-Taking; Sexual Behavior; Substance Abuse, Intravenous

Autosomal dominant cerebellar ataxia (SCA6) associated with small polyglutamine expansions in the alpha 1A-voltage-dependent calcium channel. - Zhuchenko, O; Bailey, J; Bonnen, P; Ashizawa, T; Stockton, D W; Amos, C; Dobyns, W B; Subramony, S H; Zoghbi, H Y; Lee, C C (Nat Genet, 1997)
A polymorphic CAG repeat was identified in the human alpha 1A voltage-dependent calcium channel subunit. To test the hypothesis that expansion of this CAG repeat could be the cause of an inherited progressive ataxia, we genotyped a large number of unrelated controls and ataxia patients. Eight unrelated patients with late onset ataxia had alleles with larger repeat numbers (21-27) compared to the number of repeats (4-16) in 475 non-ataxia individuals. Analysis of the repeat length in families of the affected individuals revealed that the expansion segregated with the phenotype in every patient. We identified six isoforms of the human alpha 1A calcium channel subunit. The CAG repeat is within the open reading frame and is predicted to encode glutamine in three of the isoforms. We conclude that a small polyglutamine expansion in the human alpha 1A calcium channel is most likely the cause of a newly classified autosomal dominant spinocerebellar ataxia, SCA6.
Keywords: Alleles; Amino Acid Sequence; Animals; Calcium Channels; Cerebellar Ataxia; Female; Genes, Dominant; Genotype; Humans; Male; Molecular Sequence Data; Mutation; Nerve Tissue Proteins; Pedigree; Peptides; Rabbits; Sequence Homology, Amino Acid; Trinucleotide Repeats

Molecular and phenotypic variation in patients with severe Hunter syndrome. - Timms, K M; Bondeson, M L; Ansari-Lari, M A; Lagerstedt, K; Donna M Muzny; Dugan-Rocha, S P; Nelson, D L; Pettersson, U; Richard A Gibbs (Hum Mol Genet, 1997)
Severe Hunter syndrome is a fatal X-linked lysosomal storage disorder caused by iduronate-2-sulphatase (IDS) deficiency. Patients with complete deletion of the IDS locus often have atypical phenotypes including ptosis, obstructive sleep apnoea, and the occurrence of seizures. We have used genomic DNA sequencing to identify several new genes in the IDS region. DNA deletion patients with atypical symptoms have been analysed to determine whether these atypical symptoms could be due to involvement of these other loci. The occurrence of seizures in two individuals correlated with a deletion extending proximal of IDS, up to and including part of the FMR2 locus. Other (non-seizure) symptoms were associated with distal deletions. In addition, a group of patients with no variant symptoms, and a characteristic rearrangement involving a recombination between the IDS gene and an adjacent IDS pseudogene (IDS psi), showed normal expression of loci distal to IDS. Together, these results identify FMR2 as a candidate gene for seizures, when mutated along with IDS.
Keywords: Chromosome Mapping; Cloning, Molecular; Electrophoresis, Agar Gel; Gene Deletion; Gene Expression; Gene Rearrangement; Humans; Iduronate Sulfatase; Male; Molecular Sequence Data; Mucopolysaccharidosis II; Nuclear Proteins; Phenotype; Polymerase Chain Reaction; Proteins; Pseudogenes; Recombination, Genetic; Seizures; Trans-Activators; X Chromosome

Conservation of human chromosome 18 in baboons (Papio hamadryas): a linkage map of eight human microsatellites. - Perelygin, A A; Kammerer, C M; Stowell, N C; Rogers, J (Cytogenet Cell Genet, 1996)
A panel of 25 microsatellite loci known to map to human chromosome 18 was screened for length polymorphisms in a multigenerational pedigree of baboons (Papio hamadryas). Eight of these loci were polymorphic in the baboon pedigrees, with observed heterozygosity values ranging from 0.16 to 0.88. All eight loci show strong evidence of linkage. The most likely map order among the microsatellite loci for Papio is completely compatible with the locus order found in the human genome, and sex differences in recombination rates are also similar in the two species. We conclude that the organization of the chromosomal region defined by these loci is largely conserved between baboons and humans.
Keywords: Animals; Chromosomes, Human, Pair 18; Evolution, Molecular; Female; Hominidae; Humans; Lod Score; Male; Microsatellite Repeats; Papio; Pedigree; Phylogeny; Polymerase Chain Reaction; Recombination, Genetic; Species Specificity

Potential salmon sperm origin of the E3 region insert of the adenovirus 5 dl309 mutant. - Marie-Claude Gingras; Arevalo, P; Aguilar-Cordova, E (Cancer Gene Ther, 1996)
The plasmid pJM17 is a commonly used adenoviral backbone derived from the dl309 mutant virus. It contains unknown sequences inserted in the E3 region during construction of the dl309 mutant. Complete description of the backbone sequence is required for interpretation of potential vector effects and for regulatory approval of a vector to be used in clinical trials. The anonymous E3 insert was sequenced and analyzed. The insert fragment is 646 base pairs (bp) long and is 100 bp shorter than the vector sequences it replaces. It interrupts the expression of the E3B 10.4K, 14.6K, and 14.7K genes, but not the E3A glycoprotein (gp) 19K gene. Sequence analysis and Southern blotting suggest that the insert might originate from salmon sperm DNA used as carrier during the construction of dl309. Transcription from the insert was not detected by Northern blot analysis of vector-transduced cells but was detected by reverse transcriptase polymerase chain reaction.
Keywords: Adenovirus E3 Proteins; Adenoviruses, Human; Animals; Avian Sarcoma Viruses; Base Sequence; DNA; DNA Primers; Genetic Vectors; HeLa Cells; Humans; Male; Molecular Sequence Data; Plasmids; Polymerase Chain Reaction; Prolactin; Proton-Translocating ATPases; Repetitive Sequences, Nucleic Acid; Salmon; Sequence Homology, Nucleic Acid; Spermatozoa; Thymidine Kinase; Transfection

130 kb of DNA sequence reveals two new genes and a regional duplication distal to the human iduronate-2-sulfate sulfatase locus. - Timms, K M; Lu, F; Shen, Y; Pierson, C A; Donna M Muzny; Gu, Y; Nelson, D L; Richard A Gibbs (Genome Res, 1995)
Deficiency of IDs activity results in Hunter Syndrome (mucopolysaccharidosis type II), a fatal X-linked recessive disorder. We report characterization of 28 cosmids around the IDS locus in Xq28. Four overlapping cosmids have been sequenced in their entirety generating a 130-kb contig. These studies show the fine structure of the IDS gene and identify an IDS pseudogene-like structure located 20 kb distal to the active gene. Two novel genes have also been identified in this sequence, and one of these genes is also locally duplicated. Both homologs are expressed, and a number of alternative transcript products have been characterized. The presence of a highly conserved pseudogene-like structure within a larger duplicated region close to the IDS gene has significant implications for the study of mutations at this locus.
Keywords: Base Sequence; Chromosome Walking; Chromosomes, Artificial, Yeast; Cosmids; Gene Expression; Genes; Genetic Markers; Humans; Iduronate Sulfatase; Male; Mucopolysaccharidosis II; Multigene Family; Polymerase Chain Reaction; Pseudogenes; Repetitive Sequences, Nucleic Acid; RNA, Messenger; Sequence Alignment; Transcription, Genetic; X Chromosome

Collaborative social and medical service application. - Petermann, C A; Buffone, G J; Bobroff, R B; Moore, D M; Dargahi, R; Moreau, D R; Gilson, H S; Li, Y; Fowler, J; Beck, J R (Medinfo, 1995)
Baylor College of Medicine has five Teen Health Clinics (THC) dispersed throughout Harris county. The population served by the clinics includes inner-city adolescent boys and girls 19 years of age and under. Patients receive services such as family planning, sexually transmitted disease screening and treatment, perinatal care, counseling, and support services. Adolescents may receive services at any one of the clinics at no cost to the adolescent or their dependents. Given the geographical distribution of the clinics and the reliance on paper-based records, client services cannot be provided efficiently or expeditiously. According to the statistics developed by Clinic staff, ineffective coordination of service needs and client schedules undermine the follow-up needed for effective care. For example, a counselor will often need to balance a school schedule, clinic visits, well baby follow-up, and the Best Friends Program for a new mother. In addition, the lack of ready access to patient information impairs the ability of clinical and social service staff to provide continuity of care. In fact, some cases of client dropout are attributable to these difficulties. We have developed the Collaborative Social and Medical Service Application (CSMSA) to facilitate the provision of social and medical services to this population. The CSMSA is a domain-specific application based on a robust infrastructure known as the Ambulatory Services Architecture (ASA). This system is designed to support integrated social and ambulatory care. The ASA is a Baylor developed application framework and architecture for the computerization of the patient medical record in the ambulatory care setting. The working environment for the CSMSA user is an integrated desktop which provides an operating environment for both third-party applications and the CSMSA, as well as a fundamental set of services. The integrated desktop services include a mechanism for object organization or grouping, a facility for the management of desktop objects including disposal and storage, and an embedded search utility to assist in the location of desktop objects as well as other application objects. The access control mechanism will provide the security for the desktop environment by requiring the user to log into and out of the environment. This security mechanism will also enable/disable CSMSA tools based on the user's role at the clinic. The CSMSA is designed to provide work process, functionality and data access appropriate to the responsibilities of the user, e.g., a THC clerk may have permission to view a patient's orders but does not have the facility to create an order. Patient context is defined through a patient browser containing the master patient index or a user defined patient list. Patient encounters are managed using forms based on the process for each encounter type (e.g., initial visit). Forms are used for data entry and for queries. Data entry forms are only committed to the patient database (i.e., making the patient data available to other users who have permission to access the data) when the user approves the data. The CSMSA provides a means to suspend an entry into a chart by saving incomplete or non-committed data entry forms as part of the desktop state which is restored when the user logs into the system. CSMSA was designed to provide a robust, expandable application capable of accommodating the changes in health care and social services delivery while encompassing evolving software standards and new technology. This goal was achieved using object-oriented methodologies and technologies, combined with an object-oriented database management system as the foundation of our server to facilitate the evolution of our data model.
Keywords: Adolescent; Adolescent Health Services; Adult; Ambulatory Care Information Systems; Female; Humans; Male; Medical Records Systems, Computerized; Social Work; Systems Integration; Texas

Linkage mapping in Papio baboons: conservation of a syntenic group of six markers on human chromosome 1. - Rogers, J; Witte, S M; Kammerer, C M; Hixson, J E; MacCluer, J W (Genomics, 1995)
We have established multipoint genetic linkage among six loci in baboons (Papio hamadryas). Published PCR primers designed to amplify five human microsatellite loci were used to amplify homologous loci in 229 pedigreed baboons. Southern blotting was used to type two RFLPs in a functional gene (anti-thrombin III) in a subset of those animals. All six loci are known to map to human chromosome 1q, a region of the genome predicted by karyotype studies to be conserved in baboons. Pairwise recombination frequencies and lod scores indicate that the six loci are also linked in baboons. Recombination distances among the loci are similar to those reported for humans. Like humans, the baboons exhibit higher rates of recombination in females than in males. This study demonstrates that (1) microsatellite loci first described and characterized in the human genome can be effectively used for genetic linkage mapping in non-human primates, (2) a group of genetic loci known to be linked on human chromosome 1q are also linked in the baboon genome, and (3) sex differences in recombination frequencies among loci on human chromosome 1q are also observed in the genome of this Old World monkey. This constitutes the first reported multipoint linkage map in any nonhuman primate.
Keywords: Animals; Antithrombin III; Chromosome Mapping; Evolution, Molecular; Female; Genes; Genetic Linkage; Genetic Markers; Humans; Male; Microsatellite Repeats; Papio; Polymorphism, Restriction Fragment Length; Recombination, Genetic; Species Specificity

Rapid molecular cytogenetic analysis of X-chromosomal microdeletions: fluorescence in situ hybridization (FISH) for complex glycerol kinase deficiency. - Kim C Worley; Lindsay, E A; Bailey, W; Wise, J; McCabe, E R; Baldini, A (Am J Med Genet, 1995)
Diagnosis of X-chromosomal microdeletions has relied upon the traditional methods of Southern blotting and DNA amplification, with carrier identification requiring time-consuming and unreliable dosage calculations. In this report, we describe rapid molecular cytogenetic identification of deleted DNA in affected males with the Xp21 contiguous gene syndrome (complex glycerol kinase deficiency, CGKD) and female carriers for this disorder. CGKD deletions involve the genes for glycerol kinase, Duchenne muscular dystrophy, and/or adrenal hypoplasia congenita. We report an improved method for diagnosis of deletions in individuals with CGKD and for identification of female carriers within their families, using fluorescence in situ hybridization (FISH) with a cosmid marker (cosmid 35) within the glycerol kinase gene. When used in combination with an Xq control probe, affected males demonstrate a single signal from the control probe, while female carriers demonstrate a normal chromosome with two signals, as well as a deleted chromosome with a single signal from the control probe. FISH analysis for CGKD provides the advantages of speed and accuracy for evaluation of submicroscopic X-chromosomal deletions, particularly in identification of female carriers. In addition to improving carrier evaluation, FISH will make prenatal diagnosis of CGKD more readily available.
Keywords: Chromosome Mapping; Female; Gene Deletion; Glycerol Kinase; Heterozygote; Humans; In Situ Hybridization, Fluorescence; Infant, Newborn; Male; Pedigree; X Chromosome

Collaborative Social and Medical Service System. - Petermann, C A; Bobroff, R B; Moore, D M; Gilson, H S; Li, Y; Dargahi, R; Classen, D W; Fowler, J; Moreau, D R; Beck, J R (Proc Annu Symp Comput Appl Med Care, 1994)
This paper describes the Collaborative Social and Medical Services System, a robust information infrastructure for integrated social and medical care. The Collaborative Social and Medical Services System design and architecture address the primary goals of creating a readily extensible social and ambulatory care system. Our initial step toward reaching this goal is the delivery of an application supporting the operations of the Baylor Teen Health Clinics. This paper discusses our prototype experiences, system architecture, components, and the standards we are addressing.
Keywords: Adolescent; Adolescent Health Services; Ambulatory Care Information Systems; Computer Communication Networks; Computer Security; Computer Systems; Female; Humans; Male; Medical Records Systems, Computerized; Social Work; Software; Texas; User-Computer Interface

A dosage sensitive locus at chromosome Xp21 is involved in male to female sex reversal. - Bardoni, B; Zanaria, E; Guioli, S; Floridia, G; Kim C Worley; Tonini, G; Ferrante, E; Chiumello, G; McCabe, E R; Fraccaro, M (Nat Genet, 1994)
Male to female sex reversal has been observed in individuals with duplications of the short arm of the X chromosome. Here we demonstrate that sex reversal results from the presence of two active copies of an Xp locus rather than from its rearrangement and that alterations at this locus constitute one of the causes of sex reversal in individuals with a normal 46,XY karyotype. We have named this locus DSS (Dosage Sensitive Sex reversal) and localized it to a 160 kilobase region of chromosome Xp21, adjacent to the adrenal hypoplasia congenita locus. The identification of male individuals deleted for DSS suggests that this locus is not required for testis differentiation. We propose that DSS has a role in ovarian development and/or functions as a link between ovary and testis formation.
Keywords: Chromosome Mapping; Dosage Compensation, Genetic; Female; Gene Deletion; Genetic Markers; Humans; Male; Multigene Family; Ovary; Phenotype; Sex Differentiation; Testis; X Chromosome

A transposon-like element in the deletion-prone region of the dystrophin gene. - Pizzuti, A; Pieretti, M; Fenwick, R G; Richard A Gibbs; Caskey, C T (Genomics, 1992)
The central portion of the dystrophin gene locus is a preferential site for deletions causing progressive muscular dystrophy of the Duchenne type (DMD). The nucleotide sequence of a deletion junction fragment from a DMD patient was determined, revealing that the proximal breakpoint of the deletion in intron 43 fell within the sequence of a transposon-like element. This segment, belonging to the THE-1 family of human transposable elements, is normally present in a complete form in intron 43 of the dystrophin gene. The deletion mutation was maternally transmitted and eliminated two-thirds of the THE-1 element. Analysis of DNA from additional DMD patients revealed a second deletion with the proximal breakpoint mapping within the same THE-1 element.
Keywords: Base Sequence; Chromosome Deletion; DNA; DNA Mutational Analysis; DNA Transposable Elements; Dystrophin; Humans; Introns; Male; Molecular Sequence Data; Muscular Dystrophies; Restriction Mapping; Sequence Homology, Nucleic Acid

Carrier detection and prenatal diagnosis in Duchenne and Becker muscular dystrophy families, using dinucleotide repeat polymorphisms. - Clemens, P R; Fenwick, R G; Chamberlain, J S; Richard A Gibbs; de Andrade, M; Chakraborty, R; Caskey, C T (Am J Hum Genet, 1991)
To improve carrier detection and prenatal diagnosis for Duchenne and Becker muscular dystrophy families, we determined allele frequencies and measures of variation for four (dC-dA)n.(dG-dT)n loci identified within a deletion-prone region of the human dystrophin gene. The loci are highly polymorphic, with predicted heterozygosities of 71.6%-93.3%. Direct DNA sequence analysis of the (dC-dA)n.(dG-dT)n locus in intron 49 revealed an additional length polymorphism which varies by single-basepair increments, is adjacent to the dinucleotide repeat block, and enhances the polymorphic content of this marker. The four (dC-dA)n.(dG-dT)n loci are each easily amplified by PCR in two diplex reactions. The variability of allele lengths at these loci makes them ideal for carrier detection and prenatal diagnosis, often providing diagnostic information when RFLP analysis is uninformative. These markers have aided in identification of deletion mutations, exclusion of maternal cell contamination of chorionic villus samples, confirmation of paternity, and mapping of gene recombinations. The allele identification of these loci can be performed either with a radiolabel or with an automated, nonradioactive, fluorescent gel detection system.
Keywords: Alleles; Base Sequence; Cells, Cultured; Dystrophin; Female; Gene Frequency; Genetic Carrier Screening; Genetic Markers; Humans; Male; Molecular Sequence Data; Muscular Dystrophies; Pedigree; Polydeoxyribonucleotides; Polymerase Chain Reaction; Polymorphism, Genetic; Pregnancy; Prenatal Diagnosis; Repetitive Sequences, Nucleic Acid

Evolution of human immunodeficiency virus type 1 nucleotide sequence diversity among close contacts. - Burger, H; Weiser, B; Flaherty, K; Gulla, J; Nguyen, P N; Richard A Gibbs (Proc Natl Acad Sci U S A, 1991)
The degree of change in the nucleotide sequence of human immunodeficiency virus type 1 (HIV-1) that occurs when it is transmitted sexually from one individual to another or vertically from mother to child is unknown. Previous studies have shown that most cultured HIV-1 isolates from the same individuals differed in the entire envelope gene nucleotide sequence by up to 2%, although most isolates from unrelated individuals differed by 6-22%. To examine diversity among HIV-1 isolates from close contacts, we determined the nucleotide sequences of viruses from a family with a known epidemiologic profile, in which a woman transmitted HIV-1 heterosexually to her partner and vertically to her daughter. Direct DNA sequence analysis of primary HIV-1 isolates amplified by PCR was used to distinguish the major and minor viral sequences, termed quasispecies, to rapidly determine the predominant sequences and their phylogenetic relationships. The nucleotide sequence diversity of a major portion of the HIV-1 envelope gene was 3.7% between isolates from the woman and her heterosexual partner and 8.5% between isolates from this woman and her daughter, who had been infected for a longer period than the partner. The configuration of the phylogenetic tree demonstrated that the daughter's predominant isolate evolved from a progenitor of her mother's current strain. This study provides evidence of a continuous spectrum of sequence diversity between any two isolates ranging from those derived from the same person to those from close contacts and, ultimately, those from unrelated individuals. These data and methods can be applied to epidemiologic investigations of possible HIV-1 transmission between health care workers and their patients.
Keywords: Acquired Immunodeficiency Syndrome; Adolescent; Adult; Amino Acid Sequence; Base Sequence; Biological Evolution; DNA, Viral; Female; Genes, env; Genetic Variation; HIV-1; Humans; Male; Molecular Sequence Data; Oligodeoxyribonucleotides; Phylogeny; Polymerase Chain Reaction; Sequence Homology, Nucleic Acid

An overview of industrial accidents with particular reference to facial trauma. - Shalhoub, S Y (Aust Dent J, 1991)
As an integral part of the economy of Saudi Arabia the industrial sector has rapidly developed in the last decade and is still open for more growth. Thus, there is likely to be an increase in industrial accidents, often with added consequences for the medical services. Because of this, cumulative information on industrial accidents is needed. This paper reports on industrial accidents in order to alert medical researchers to the need for specific studies of different industrial occupations in Saudi Arabia so that adequate administrative and medical services may be available should an industrial accident occur.
Keywords: Accidents, Occupational; Adult; Facial Injuries; Humans; Male; Middle Aged; Occupational Diseases; Saudi Arabia

Long HIV-1 incubation periods and dynamics of transmission within a family. - Burger, H; Belman, A L; Grimson, R; Kaell, A; Flaherty, K; Gulla, J; Richard A Gibbs; Nguyun, P N; Weiser, B (Lancet, 1990)
The incubation period of human immunodeficiency virus type 1 (HIV-1) infection was studied in a family of five in which vertical and heterosexual transmission occurred from one index case. This investigation documented incubation periods of longer than 12 years in a mother and her daughter; although neither has symptoms, both are definitely infected and have very low CD4(+)-lymphocyte counts. The study confirmed the predictions of incubation periods longer than 10 years in a small proportion of infected individuals. It provides evidence that vertically HIV-1-infected teenagers can be expected to appear in the population.
Keywords: Acquired Immunodeficiency Syndrome; Adolescent; Adult; CD4-Positive T-Lymphocytes; Child; DNA, Viral; Family; Family Health; Female; HIV Antibodies; HIV Seropositivity; HIV-1; Humans; Leukocyte Count; Male; Sexual Behavior; Substance Abuse, Intravenous; Time Factors

Multiplex DNA deletion detection and exon sequencing of the hypoxanthine phosphoribosyltransferase gene in Lesch-Nyhan families. - Richard A Gibbs; Nguyen, P N; Edwards, A; Civitello, A B; Caskey, C T (Genomics, 1990)
The Lesch-Nyhan (LN) syndrome is a genetically lethal human neurological disease that results from mutations that inactivate the hypoxanthine phosphoribosyltransferase (HPRT) gene. The elucidation of the complete DNA sequence of the human HPRT gene locus has enabled the construction of multiple oligonucleotide primer sets for the simultaneous in vitro amplification of all nine HPRT exons. The multiplex polymerase chain reaction provides a facile assay for the detection of HPRT exon deletions and the reaction products can be analyzed by direct automated fluorescent DNA sequencing to identify subtle alterations in the gene. Alterations have been identified in the HPRT genes from 15 independent LN cases, and 10 LN family studies were performed. The sequencing method uses solid supports and is sufficiently simple and sensitive to be a favored approach for LN diagnosis. LN heterozygotes can be diagnosed without reference to the affected male. In addition, these procedures will be useful for somatic mutagenesis studies.
Keywords: Base Sequence; Chromosome Deletion; DNA; Exons; Female; Genes; Genetic Carrier Screening; Humans; Hypoxanthine Phosphoribosyltransferase; Lesch-Nyhan Syndrome; Male; Molecular Sequence Data; Pedigree; Polymerase Chain Reaction

Automated DNA sequencing methods for detection and analysis of mutations: applications to the Lesch-Nyhan syndrome. - Edwards, A; Richard A Gibbs; Nguyen, P N; Ansorge, W; Caskey, C T (Trans Assoc Am Physicians, 1989)
Keywords: Base Sequence; Chromosome Deletion; DNA; Female; Genetic Carrier Screening; Humans; Hypoxanthine Phosphoribosyltransferase; Lesch-Nyhan Syndrome; Male; Mutation; Pedigree; Polymerase Chain Reaction; Polymorphism, Genetic; Pregnancy; Prenatal Diagnosis; Repetitive Sequences, Nucleic Acid; Restriction Mapping

Deletion screening of the Duchenne muscular dystrophy locus via multiplex DNA amplification. - Chamberlain, J S; Richard A Gibbs; Ranier, J E; Nguyen, P N; Caskey, C T (Nucleic Acids Res, 1988)
The application of recombinant DNA technology to prenatal diagnosis of many recessively inherited X-linked diseases is complicated by a high frequency of heterogeneous, new mutations (1). Partial gene deletions account for more than 50% of Duchenne muscular dystrophy (DMD) lesions, and approximately one-third of all cases result from a new mutation (2-5). We report the isolation and DNA sequence of several deletion prone exons from the human DMD gene. We also describe a rapid method capable of detecting the majority of deletions in the DMD gene. This procedure utilizes simultaneous genomic DNA amplification of multiple widely separated sequences and should permit deletion scanning at any hemizygous locus. We demonstrate the application of this multiplex reaction for prenatal and postnatal diagnosis of DMD.
Keywords: Base Sequence; Chromosome Deletion; Cloning, Molecular; DNA; Female; Gene Amplification; Humans; Male; Molecular Sequence Data; Muscular Dystrophies; Prenatal Diagnosis

[Results of treatment of flexion spasms in children]. - Popielarska, A; Gregorczuk, J; Suffczyńska-Kotowska, M; Mazurowa, M (Neurol Neurochir Pol, 1971)
Keywords: Adrenocorticotropic Hormone; Age Factors; Anticonvulsants; Child, Preschool; Electroencephalography; Female; Humans; Infant; Male; Pneumoencephalography; Prednisone; Psychomotor Disorders; Spasm; Succinates; Time Factors